12 x 6 Gy stereotactic radiotherapy for lung tumors. Is there a difference in response between lung metastases and primary bronchial carcinoma? - Lubgan, Dorota; Semrau, Sabine; Lambrecht, Ulrike; Gaipl, Udo; Fietkau, Rainer (Strahlentherapie und Onkologie, 2021)
Purpose The aim of this study was to evaluate the safety and long-term tumor control after stereotactic radiotherapy (SRT) with 12 x 6 Gy of patients with primary bronchial carcinoma (BC) or with pulmonary metastases (MET) of various solid tumors. Local progression-free survival (LPFS), progression-free survival (PFS), overall survival (OS), and prognostic factors were compared. Methods Between May 2012 and January 2020, 168 patients with 206 pulmonary lesions (170 MET and 36 primary BC) were treated with 12 x 6 Gy (BED10 116 Gy). The irradiated pulmonary MET were from the following cancers: 47 (27.6%) head and neck, 37 (21.8%) rectum or colon, 30 (17.6%) bronchial, 13 (7.6%) malignant melanoma, 9 (5.3%) esophageal, 9 (5.3%) sarcoma, and 25 (14.8%) other. Results The median follow-up was 16.26 months (range: 0.46-89.34) for BC and 19.18 months (0.89-91.11) for MET. Survival rates at 3 years were: OS 43% for BC and 35% for MET; LPFS BC 96% and MET 85%; PFS BC 35% and MET 29%. The most frequently observed grade 3 adverse events (AEs) were pneumonitis (5.9% BC, 4.8% MET), pulmonary fibrosis (2.9% BC, 4% MET), and pulmonary embolism (2.9% BC, 0.8% MET). The favorable prognostic effects on overall survival of patients with MET were female gender (log-rank: p < 0.001), no systemic progression (log-rank; p = 0.048, multivariate COX regression p = 0.039), and malignant melanoma histology (log-rank; p = 0.015, multivariate COX regression p = 0.020). For patients with BC, it was tumor location within the lower lobe (vs. upper lobe, log-rank p = 0.027). LPFS of patients with metastatic disease was beneficially influenced by female gender (log-rank: p = 0.049). Conclusion The treatment concept of 12 x 6 Gy is associated with 96% local progression-free survival for BC and 85% for pulmonary metastases after 3 years. There was no difference in response after SRT of primary lung carcinoma or pulmonary metastases.
CRIS-Team WoS Importer:2021-07-30

12 x 6 Gy stereotactic radiotherapy for lung tumours. Is there a difference in response between lung metastases and primary bronchial carcinoma? - Lubgan, Dorota; Semrau, Sabine; Lambrecht, U.; Gaipl, Udo; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

12x6Gy-the Erlangen stereotactic radiotherapy treatment concept result in 95% local progression-free survival for bronchial carcinoma and 83% for pulmonary metastases after 3 years - Lubgan, Dorota; Rutzner, Sandra; Lambrecht, U.; Fietkau, Rainer (2018)
EVALuna2:36517

3D convolutional neural network-based autosegmentation improves brain metastases detection and quantification for brain stereotactic radiotherapy treatment planning - Putz, Florian; Weissmann, Thomas; Mansoorian, Sina; Schmidt, Manuel; Heiß, Rafael; Semrau, Sabine; Frey, Benjamin; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

49th Annual Conference of the German Society for Medical Physics and 21st Annual Conference of the German Section of the ISMRM - Bert, Christoph; Wucherer, Michael; Laun, Frederik B. (Zeitschrift für Medizinische Physik, 2018)
EVALuna2:36480

4D optimization of scanned ion beam tracking therapy for moving tumors - Eley, John Gordon; Newhauser, Wayne David; Lüchtenborg, Robert; Graeff, Christian; Bert, Christoph (Physics in Medicine and Biology, 2014)
Motion mitigation strategies are needed to fully realize the theoretical advantages of scanned ion beam therapy for patients with moving tumors. The purpose of this study was to determine whether a new four-dimensional (4D) optimization approach for scanned-ion-beam tracking could reduce dose to avoidance volumes near a moving target while maintaining target dose coverage, compared to an existing 3D-optimized beam tracking approach. We tested these approaches computationally using a simple 4D geometrical phantom and a complex anatomic phantom, that is, a 4D computed tomogram of the thorax of a lung cancer patient. We also validated our findings using measurements of carbon-ion beams with a motorized film phantom. Relative to 3D-optimized beam tracking, 4D-optimized beam tracking reduced the maximum predicted dose to avoidance volumes by 53% in the simple phantom and by 13% in the thorax phantom. 4D-optimized beam tracking provided similar target dose homogeneity in the simple phantom (standard deviation of target dose was 0.4% versus 0.3%) and dramatically superior homogeneity in the thorax phantom (D5-D95 was 1.9% versus 38.7%). Measurements demonstrated that delivery of 4D-optimized beam tracking was technically feasible and confirmed a 42% decrease in maximum film exposure in the avoidance region compared with 3D-optimized beam tracking. In conclusion, we found that 4D-optimized beam tracking can reduce the maximum dose to avoidance volumes near a moving target while maintaining target dose coverage, compared with 3D-optimized beam tracking.
EVALuna2:18202

5-year results of accelerated partial breast irradiation using sole interstitial multicatheter brachytherapy versus whole-breast irradiation with boost after breast-conserving surgery for low-risk invasive and in-situ carcinoma of the female breast: a ran - Strnad, Vratislav; Ott, Oliver J.; Hildebrandt, Guido; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Lyczek, Jaroslaw; Guinot, Jose Luis; Dunst, Juergen; Gutierrez Miguelez, Cristina; Slampa, Pavel; Allgaeuer, Michael; et al. (Lancet, 2016)
In a phase 3, randomised, non-inferiority trial, accelerated partial breast irradiation (APBI) for patients with stage 0, I, and IIA breast cancer who underwent breast-conserving treatment was compared with whole-breast irradiation. Here, we present 5-year follow-up results.We did a phase 3, randomised, non-inferiority trial at 16 hospitals and medical centres in seven European countries. 1184 patients with low-risk invasive and ductal carcinoma in situ treated with breast-conserving surgery were centrally randomised to either whole-breast irradiation or APBI using multicatheter brachytherapy. The primary endpoint was local recurrence. Analysis was done according to treatment received. This trial is registered with ClinicalTrials.gov, number NCT00402519.Between April 20, 2004, and July 30, 2009, 551 patients had whole-breast irradiation with tumour-bed boost and 633 patients received APBI using interstitial multicatheter brachytherapy. At 5-year follow-up, nine patients treated with APBI and five patients receiving whole-breast irradiation had a local recurrence; the cumulative incidence of local recurrence was 1.44% (95% CI 0.51-2.38) with APBI and 0.92% (0.12-1.73) with whole-breast irradiation (difference 0.52%, 95% CI -0.72 to 1.75; p=0.42). No grade 4 late side-effects were reported. The 5-year risk of grade 2-3 late side-effects to the skin was 3.2% with APBI versus 5.7% with whole-breast irradiation (p=0.08), and 5-year risk of grade 2-3 subcutaneous tissue late side-effects was 7.6% versus 6.3% (p=0.53). The risk of severe (grade 3) fibrosis at 5 years was 0.2% with whole-breast irradiation and 0% with APBI (p=0.46).The difference between treatments was below the relevance margin of 3 percentage points. Therefore, adjuvant APBI using multicatheter brachytherapy after breast-conserving surgery in patients with early breast cancer is not inferior to adjuvant whole-breast irradiation with respect to 5-year local control, disease-free survival, and overall survival.German Cancer Aid.
EVALuna2:5536

AAPM Task Group Report 290: Respiratory motion management for particle therapy - Li, Heng; Dong, Lei; Bert, Christoph; Chang, Joe; Flampouri, Stella; Jee, Kyung-Wook; Lin, Liyong; Moyers, Michael; Mori, Shinichiro; Rottmann, Joerg; Tryggestad, Erik; Vedam, Sastry (Medical Physics, 2022)
Dose uncertainty induced by respiratory motion remains a major concern for treating thoracic and abdominal lesions using particle beams. This Task Group report reviews the impact of tumor motion and dosimetric considerations in particle radiotherapy, current motion-management techniques, and limitations for different particle-beam delivery modes (i.e., passive scattering, uniform scanning, and pencil-beam scanning). Furthermore, the report provides guidance and risk analysis for quality assurance of the motion-management procedures to ensure consistency and accuracy, and discusses future development and emerging motion-management strategies. This report supplements previously published AAPM report TG76, and considers aspects of motion management that are crucial to the accurate and safe delivery of particle-beam therapy. To that end, this report produces general recommendations for commissioning and facility-specific dosimetric characterization, motion assessment, treatment planning, active and passive motion-management techniques, image guidance and related decision-making, monitoring throughout therapy, and recommendations for vendors. Key among these recommendations are that: (1) facilities should perform thorough planning studies (using retrospective data) and develop standard operating procedures that address all aspects of therapy for any treatment site involving respiratory motion; (2) a risk-based methodology should be adopted for quality management and ongoing process improvement.
CRIS-Team Scopus Importer:2022-02-11

Abstracts DEGRO 2018 Low-dose irradiation has an impact on bone metabolism as well as on local and systemic immune cell-mediated inflammation - Deloch, Lisa; Rückert, Michael; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
Created from Fastlane, Scopus look-up

Abstracts of the 20th Annual Meeting of the German Society for Radiation Oncology (DEGRO), 3-4 July, 2014, Dusseldorf, Germany 20. Jahrestagung der Deutschen Gesellschaft für Radioonkologie - Deloch, Lisa; Derer, Anja; Rühle, Paul-Friedrich; Ott, Oliver; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2014)
Created from Fastlane, Scopus look-up

Accelerated Partial Breast Irradiation: Frequent non-professional Phagocytosis in Patients with early, Hormone Receptor-positive Breast Cancer is associated with good Survival - Bauer, Marcus; Schnellhardt, S.; Rosahl, M. -C; Erber, Ramona; Ott, Oliver; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Accelerated Partial Breast Irradiation: Identification of High Risk Tumors in Early Hormone Receptor-positive Breast Cancer by Macrophage Shift Classification - Schnellhardt, S.; Erber, Ramona; Büttner-Herold, Maike; Rosahl, M. -C; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, L.; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Accelerated partial breast irradiation: Macrophage polarisation shift classification identifies high-risk tumours in early hormone receptor-positive breast cancer - Schnellhardt, Sören; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie Charlotte; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, Lillian; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cancers, 2020)
Studies have demonstrated correlations between accumulations of tumour-associated macrophages (TAMs), especially of M2-like phenotype, and increased mortality in advanced breast cancer. We investigated the prognostic potential of both main macrophage phenotypes in early hormone receptor-positive (HR+) breast cancer. The studied cohort of 136 patients participated in an institutional APBI phase II trial. Patient selection was characterized by HR+, small tumour size and no metastasis. Tissue microarrays from pre-RT resection samples were double stained for CD68/CD163 using immunohistochemistry. CD68+/CD163− cells were considered M1-like macrophages and CD68+/CD163+ was representative of M2-like macrophages. M1 and M2 macrophage densities were analysed semi-automatically in the stromal and intraepithelial tumour compartment. Low M1 and high M2 densities were strongly associated with decreased disease-free survival (DFS). Combined TAM phenotype densities were studied after defining a macrophage shift classification: M1-shifted (M1 high, M2 low) and non-shifted (M1 low, M2 low; M1 high, M2 high) tumours entailed a favourable outcome. In contrast, M2-shifted (M1 low, M2 high) TAM populations were associated with extremely reduced DFS. Thus, the full predictive potential of TAMs was revealed in a combined analysis of both phenotypes. The M2-shifted subgroup of tumours is classified as high-risk and probably not suitable for partial breast irradiation.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Accelerated partial breast irradiation; CD163; CD68; Early breast cancer; Hormone receptor-positive; Prognosis; Tumour associated macrophages

Accelerated partial breast irradiation using sole interstitial multicatheter brachytherapy compared with whole-breast irradiation with boost for early breast cancer: 10-year results of a GEC-ESTRO randomised, phase 3, non-inferiority trial - Strnad, Vratislav; Polgár, Csaba; Ott, Oliver; Hildebrandt, Guido; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Łyczek, Jarosław; Guinot, Jose Luis; Gutierrez Miguelez, Cristina; Slampa, Pavel; Allgäuer, Michael; et al. (The Lancet. Oncology, 2023)
BACKGROUND: Several randomised, phase 3 trials have investigated the value of different techniques of accelerated partial breast irradiation (APBI) for patients with early breast cancer after breast-conserving surgery compared with whole-breast irradiation. In a phase 3 randomised trial, we evaluated whether APBI using multicatheter brachytherapy is non-inferior compared with whole-breast irradiation. Here, we present the 10-year follow-up results. METHODS: We did a randomised, phase 3, non-inferiority trial at 16 hospitals and medical centres in Austria, Czech Republic, Germany, Hungary, Poland, Spain, and Switzerland. Patients aged 40 years or older with early invasive breast cancer or ductal carcinoma in situ treated with breast-conserving surgery were centrally randomly assigned (1:1) to receive either whole-breast irradiation or APBI using multicatheter brachytherapy. Whole-breast irradiation was delivered in 25 daily fractions of 50 Gy over 5 weeks, with a supplemental boost of 10 Gy to the tumour bed, and APBI was delivered as 30·1 Gy (seven fractions) and 32·0 Gy (eight fractions) of high-dose-rate brachytherapy in 5 days or as 50 Gy of pulsed-dose-rate brachytherapy over 5 treatment days. Neither patients nor investigators were masked to treatment allocation. The primary endpoint was ipsilateral local recurrence, analysed in the as-treated population; the non-inferiority margin for the recurrence rate difference (defined for 5-year results) was 3 percentage points. The trial is registered with ClinicalTrials.gov, NCT00402519; the trial is complete. FINDINGS: Between April 20, 2004, and July 30, 2009, 1328 female patients were randomly assigned to whole breast irradiation (n=673) or APBI (n=655), of whom 551 in the whole-breast irradiation group and 633 in the APBI group were eligible for analysis. At a median follow-up of 10·36 years (IQR 9·12-11·28), the 10-year local recurrence rates were 1·58% (95% CI 0·37 to 2·8) in the whole-breast irradiation group and 3·51% (1·99 to 5·03) in the APBI group. The difference in 10-year rates between the groups was 1·93% (95% CI -0·018 to 3·87; p=0·074). Adverse events were mostly grade 1 and 2, in 234 (60%) of 393 participants in the whole-breast irradiation group and 314 (67%) of 470 participants in the APBI group, at 7·5-year or 10-year follow-up, or both. Patients in the APBI group had a significantly lower incidence of treatment-related grade 3 late side-effects than those in the whole-breast irradiation group (17 [4%] of 393 for whole-breast irradiation vs seven [1%] of 470 for APBI; p=0·021; at 7·5-year or 10-year follow-up, or both). At 10 years, the most common type of grade 3 adverse event in both treatment groups was fibrosis (six [2%] of 313 patients for whole-breast irradiation and three [1%] of 375 patients for APBI, p=0·56). No grade 4 adverse events or treatment-related deaths have been observed. INTERPRETATION: Postoperative APBI using multicatheter brachytherapy after breast-conserving surgery in patients with early breast cancer is a valuable alternative to whole-breast irradiation in terms of treatment efficacy and is associated with fewer late side-effects. FUNDING: German Cancer Aid, Germany.
CRIS-Team Scopus Importer:2023-03-10

Accelerated partial breast irradiation with external beam radiotherapy : First results of the German phase 2 trial - Ott, Oliver J.; Strnad, Vratislav; Stillkrieg, Wilhelm; Uter, Wolfgang; Beckmann, Matthias; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
BACKGROUND AND PURPOSE: To evaluate the feasibility and efficacy of external beam three-dimensional (3D) conformal accelerated partial breast irradiation (APBI) for selected patients with early breast cancer. PATIENTS AND METHODS: Between 2011 and 2016, 72 patients were recruited for this prospective phase 2 trial. Patients were eligible for APBI if they had histologically confirmed breast cancer or pure ductal carcinoma in situ (DCIS), a tumor diameter ≤3 cm, clear resection margins ≥2 mm, no axillary lymph node involvement, no distant metastases, tumor bed clips, and were aged ≥50 years. Patients were excluded if mammography showed a multicentric invasive growth pattern, or if they had residual diffuse microcalcifications postoperatively, an extensive intraductal component, or vessel invasion. Patients received 3D conformal external beam APBI with a total dose of 38 Gy in 10 fractions in 1-2 weeks. The trial had been registered at the German Clinical Trials Register, DRKS-ID: DRKS00004417. RESULTS: Median follow-up was 25.5 months (range 1-61 months). Local control was maintained in 71 of 72 patients. The 3‑year local recurrence rate was 2.1% (95% confidence interval, CI: 0-6.1%). Early toxicity (grade 1 radiodermatitis) was seen in 34.7% (25/72). Late side effects ≥ grade 3 did not occur. Cosmetic results were rated as excellent/good in 96.7% (59/61). CONCLUSION: APBI with external beam radiotherapy techniques is feasible with low toxicity and, according to the results of the present and other studies, on the way to becoming a standard treatment option for a selected subgroup of patients.
EVALuna2:32915

Accelerated partial breast irradiation with external beam radiotherapy: results of the German phase 2-trial - Ott, O. J.; Strnad, Vratislav; Sillkrieg, W.; Uter, Wolfgang; Beckmann, Matthias; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Accumulation of the delivered treatment dose in volumetric modulated arc therapy with breath-hold for pancreatic cancer patients based on daily cone beam computed tomography images with limited field-of-view - Ziegler, Marc; Nakamura, Mitsuhiro; Hirashima, Hideaki; Ashida, Ryo; Yoshimura, Michio; Bert, Christoph; Mizowaki, Takashi (Medical Physics, 2019)
Background and purpose: Inter-fractional changes of the daily anatomy of the patient are a source of error in radiotherapy. This effect is especially present in the abdomen, where there are daily differences in the filling of the stomach or the intestines. This study investigated the impact of inter-fractional changes of pancreatic cancer patients who underwent breath-hold volumetric modulated arc therapy on the applied dose by using deformable image registration. Material and methods: Deformable image registration was used to determine a displacement field which maps the computed tomography (CT) used for treatment planning onto daily breath-hold cone-beam CT images with limited field-of-view (FOV) which were acquired at the beginning of every treatment fraction. Different B-spline registration methods utilizing different metrics and regularizations were used and compared. The resulting deformed planning CT images were used to calculate the dose distributions on the anatomy of the day which can therefore be seen as a good estimation of the actually delivered dose during the treatment fractions. Additionally, the accumulated dose distribution was determined by accumulating all daily dose distributions using inverted deformation fields. The calculated dose distributions were then compared to the planned dose by comparison of dose volume histograms and dosimetric volumetric indices. Results: Best registration results were obtained using a gradient magnitude metric and a regularization of λ = 0.05. The accumulated dose distributions showed that the mean dose delivered to the clinical target volume was on median reduced by 0.61 Gy after 15 fractions from the planned dose. For the organs at risk, the accumulated dose distributions were still fulfilling all clinical goals for the patient cohort used in this study. It was found that rotating and shearing motions of the tumor led to a greater reduction in the mean target dose which correlated with the proximity of the target to the spine (r = 0.54, P = 0.038). Conclusion: With the proposed method, it is possible to generate a deformed planning CT image which matches the anatomy of the day based on cone beam computed tomography images with a limited FOV and calculating the dose distribution of the day. The dosimetric impact of the inter-fractional variations was small for most patients but showed larger deviations if the tumor is located in close proximity to the spine.
CRIS-Team Scopus Importer:2019-06-28
Keywords: breath-hold; deformable image registration; inter-fractional changes; pancreatic cancer

Accuracy of MRI-CT registration in brain stereotactic radiotherapy: Impact of MRI acquisition setup and registration method - Masitho, Siti; Putz, Florian; Mengling, Veit; Reißig, Lisa; Voigt, Raphaela; Bäuerle, Tobias; Janka, Rolf Matthias; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Background: In MR-based radiotherapy (RT), MRI images are co-registered to the planning CT to leverage MR image information for RT planning. Especially in brain stereotactic RT, where typical CTV-PTV margins are 1-2 mm, high registration accuracy is critical. Several factors influence the registration accuracy, including the acquisition setup during MR simulation and the registration methods. Purpose: In this work, the impact of the MRI acquisition setup and registration method was evaluated in the context of brain RT, both geometrically and dosimetrically. Methods and Materials: MRI of 20 brain radiotherapy patients was acquired in two MRI acquisition setups (RT and diagnostic). Three different automatic registration tools provided by three treatment planning systems were used to rigidly register both MRIs and CT in addition to the clinical registration. Segmentation-based evaluation using Hausdorff Distance (HD)/Dice Similarity Coefficient and landmark-based evaluation were used as evaluation metrics. Dose-volume-histograms were evaluated for target volumes and various organs at risks. Results: MRI acquisition in the RT setup provided a similar head extension as compared to the planning CT. The registration method had a more significant influence than the acquisition setup (Wilcoxon signed-rank test, p<0.05). When registering using a less optimal registration method, the RT setup improved the registration accuracy compared to the diagnostic setup (Difference: ΔMHD = 0.16 mm, ΔHDP95 = 0.64 mm, mean Euclidean distance (ΔmEuD) = 2.65 mm). Different registration methods and acquisition setups lead to the variation of the clinical DVH. Acquiring MRI in the RT setup can improve PTV and GTV coverage compared to the diagnostic setup. Conclusions: Both MRI acquisition setup and registration method influence the MRI-CT registration accuracy in brain RT patients geometrically and dosimetrically. MR-simulation in the RT setup assures optimal registration accuracy if automatic registration is impaired, and therefore recommended for brain RT.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Brain radiotherapy; Intracranial stereotactic radiotherapy; Magnetic-resonance imaging; Patient immobilization; Registration

A clinician's plea to test glioma patients for CMV - Goerig, Nicole; Frey, Benjamin; Überla, Klaus; Gaipl, Udo; Fietkau, Rainer (Neuro-Oncology, 2017)
EVALuna2:32871

A Comparison of Single- and Multiparametric MRI Models for Differentiation of Recurrent Glioblastoma from Treatment-Related Change - Eisenhut, Felix; Engelhorn, Tobias; Arinrad, Soheil; Brandner, Sebastian; Coras, Roland; Putz, Florian; Fietkau, Rainer; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2021)
To evaluate single- and multiparametric MRI models to differentiate recurrent glioblastoma (GBM) and treatment-related changes (TRC) in clinical routine imaging. Selective and unselective apparent diffusion coefficient (ADC) and minimum, mean, and maximum cerebral blood volume (CBV) measurements in the lesion were performed. Minimum, mean, and maximum ratios(CBV) (CBVlesion to CBVhealthy white matter) were computed. All data were tested for lesion discrimination. A multiparametric model was compiled via multiple logistic regression using data demonstrating significant difference between GBM and TRC and tested for its diagnostic strength in an independent patient cohort. A total of 34 patients (17 patients with recurrent GBM and 17 patients with TRC) were included. ADC measurements showed no significant difference between both entities. All CBV and ratios(CBV) measurements were significantly higher in patients with recurrent GBM than TRC. A minimum CBV of 8.5, mean CBV of 116.5, maximum CBV of 327 and ratio(CBV) (minimum) of 0.17, ratio(CBV) (mean) of 2.26 and ratio(CBV) (maximum) of 3.82 were computed as optimal cut-off values. By integrating these parameters in a multiparametric model and testing it in an independent patient cohort, 9 of 10 patients, i.e., 90%, were classified correctly. The multiparametric model further improves radiological discrimination of GBM from TRC in comparison to single-parameter approaches and enables reliable identification of recurrent tumors.
CRIS-Team WoS Importer:2022-01-07

A comprehensive quality assurance protocol for electromagnetic tracking in brachytherapy - Dürrbeck, Christopher; Gomez-Sarmiento, Isaac Neri; Androulakis, Ioannis; Sauer, Birte; Kolkman-Deurloo, Inger Karine; Bert, Christoph; Beaulieu, Luc (Medical Physics, 2024)
Background: Electromagnetic tracking (EMT) systems have proven to be a valuable source of information regarding the location and geometry of applicators in patients undergoing brachytherapy (BT). As an important element of an enhanced and individualized pre-treatment verification, EMT can play a pivotal role in detecting treatment errors and uncertainties to increase patient safety. Purpose: The purpose of this study is two-fold: to design, develop and test a dedicated measurement protocol for the use of EMT-enabled afterloaders in BT and to collect and compare the data acquired from three different radiation oncology centers in different clinical environments. Methods: A novel quality assurance (QA) phantom composed of a scaffold with supports to fix the field generator, different BT applicators, and reference sensors (sensor verification tools) was used to assess the precision (jitter error) and accuracy (relative distance errors and target registration error) of the EMT sensor integrated into an afterloader prototype. Measurements were repeated in different environments where EMT measurements are likely to be performed, namely an electromagnetically clean laboratory, a BT suite, an operating room, and, if available, a CT suite and an MRI suite dedicated to BT. Results: The mean positional jitter was consistently under 0.1 mm across all measurement points, with a slight trend of increased jitter at greater distances from the field generator. The mean variability of sensor positioning in the tested tandem and ring gynecological applicator was also below 0.1 mm. The tracking accuracy close to the center of the measurement volume was higher than at its edges. The relative distance error at the center was 0.2-0.3 mm with maximum values reaching 1.2-1.8 mm, but up to 5.5 mm for measurement points close to the edges. In general, similar accuracy results were obtained in the clinical environments and in all investigated institutions (median distance error 0.1-0.4 mm, maximum error 1.0-2.0 mm), however, errors were found to be larger in the CT suite (median distance error up to 1.0 mm, maximum error up to 3.6 mm). Conclusion: The presented quality assessment protocol for EMT systems in BT has demonstrated that EMT offers a high-accuracy determination of the applicator/implant geometry even in clinical environments. In addition to that, it has provided valuable insights into the performance of EMT-enabled afterloaders across different radiation oncology centers.
CRIS-Team Scopus Importer:2024-05-17
Keywords: brachytherapy; electromagnetic tracking; quality assurance

Acquired temozolomide resistance in human glioblastoma cell line U251 is caused by mismatch repair deficiency and can be overcome by lomustine - Stritzelberger, Jenny; Distel, Luitpold; Buslei, R.; Fietkau, Rainer; Putz, Florian (Clinical & Translational Oncology, 2018)
PURPOSE: Glioblastoma multiforme (GBM) is the most common malignant primary brain tumor in adults. While the alkylating agent temozolomide (TMZ) has prolonged overall survival, resistance evolution represents an important clinical problem. Therefore, we studied the effectiveness of radiotherapy and CCNU in an in vitro model of acquired TMZ resistance. METHODS: We studied the MGMT-methylated GBM cell line U251 and its in vitro derived TMZ-resistant subline, U251/TMZ-R. Cytotoxicity of TMZ, CCNU, and radiation was tested. Both cell lines were analyzed for MGMT promotor status and expression of mismatch repair genes (MMR). The influence of MMR inhibition by cadmium chloride (CdCl2) on the effects of both drugs was evaluated. RESULTS: During the resistance evolution process in vitro, U251/TMZ-R developed MMR deficiency, but MGMT status did not change. U251/TMZ-R cells were more resistant to TMZ than parental U251 cells (cell viability: 92.0% in U251/TMZ-R/69.2% in U251; p = 0.032) yet more sensitive to CCNU (56.4%/80.8%; p = 0.023). The effectiveness of radiotherapy was not reduced in the TMZ-resistant cell line. Combination of CCNU and TMZ showed promising results for both cell lines and overcame resistance. CdCl2-induced MMR deficiency increased cytotoxicity of CCNU. CONCLUSION: Our results confirm MMR deficiency as a crucial process for resistance evolution to TMZ. MMR-deficient TMZ-resistant GBM cells were particularly sensitive to CCNU and to combined CCNU/TMZ. Effectiveness of radiotherapy was preserved in TMZ-resistant cells. Consequently, CCNU might be preferentially considered as a treatment option for recurrent MGMT-methylated GBM and may even be suitable for prevention of resistance evolution in primary treatment.
EVALuna2:34594

Adaptive radiotherapy and the dosimetric impact of inter- and intrafractional motion on the planning target volume for prostate cancer patients - Böckelmann, Felix; Putz, Florian; Kallis, Karoline; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2020)
Purpose: To investigate the dosimetric influence of daily interfractional (inter) setup errors and intrafractional (intra) target motion on the planning target volume (PTV) and the possibility of an offline adaptive radiotherapy (ART) method to correct larger patient positioning uncertainties in image-guided radiotherapy for prostate cancer (PCa). Materials and methods: A CTV (clinical target volume)-to-PTV margin ranging from 15 mm in LR (left-right) and SI (superior-inferior) and 5–10 mm in AP (anterior-posterior) direction was applied to all patients. The dosimetric influence of this margin was retrospectively calculated by analysing systematic and random components of inter and intra errors of 31 consecutive intermediate- and high-risk localized PCa patients using daily cone beam computed tomography and kV/kV (kilo-Voltage) imaging. For each patient inter variation was assessed by observing the first 4 treatment days, which led to an offline ART-based treatment plan in case of larger variations. Results:: Systematic inter uncertainties were larger (1.12 in LR, 2.28 in SI and 1.48 mm in AP) than intra systematic errors (0.44 in LR, 0.69 in SI and 0.80 mm in AP). Same findings for the random error in SI direction with 3.19 (inter) and 2.30 mm (intra), whereas in LR and AP results were alike with 1.89 (inter) and 1.91 mm (intra) and 2.10 (inter) and 2.27 mm (intra), respectively. The calculated margin revealed dimensions of 4–5 mm in LR, 8–9 mm in SI and 6–7 mm in AP direction. Treatment plans which had to be adapted showed smaller variations with 1.12 (LR) and 1.72 mm (SI) for Σ and 4.17 (LR) and 3.75 mm (SI) for σ compared to initial plans with 1.77 and 2.62 mm for Σ and 4.46 and 5.39 mm for σ in LR and SI, respectively. Conclusion: The currently clinically used margin of 15 mm in LR and SI and 5–10 mm in AP direction includes inter and intra uncertainties. The results show that offline ART is feasible which becomes a necessity with further reductions in PTV margins.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Cone beam computed tomography; Drinking protocol; Endorectal balloon; Margin calculation

Adherence to oral anticoagulation in secondary stroke prevention - the first year of direct oral anticoagulants - Sauer, Rolf; Sauer, Eva-Maria; Bobinger, Tobias; Blinzler, Christian; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2015)
Patients with ischemic stroke caused by atrial fibrillation (AF) have a high risk of recurrence without adequate secondary prevention with oral anticoagulation (OAC). We investigated adherence to OAC in the first year after introduction of direct oral anticoagulants.In 284 appropriate patients, the rate of anticoagulation (AC) at discharge, adherence at 90 days and 1 year, changes between substances, and predictors for adherence to AC were analyzed. Functional outcome was assessed using the modified Rankin Scale score.AC was initiated in 70.3% of survivors before discharge. In these patients, only 8.6% and 9.9% discontinued AC after 90 days and 1 year, respectively. In 22.1%, AC was recommended but not started before discharge. Only 53.2% of them received AC at 90 days, increasing to 67.5% at 1 year. A total of 7.6% of patients were deemed unsuitable for AC, none of them subsequently received AC. Overall, 85.4% of patients suitable for AC were treated at 1-year follow-up. No independent predictors for withholding AC were identified. Switching of medication occurred in only a minority of patients within the first year.AC is feasible in more than 90% patients with acute ischemic stroke and AF. When initiated during the acute hospital stay, AC is discontinued in only a minority of patients. However, if AC is recommended but not started during initial hospitalization the rate of AC treatment at 90 days and 1 year is much lower. Therefore, AC should be initiated within the acute hospital stay whenever possible.
EVALuna2:22269

A disease-specific enteral nutrition formula improves nutritional status and functional performance in patients with head and neck and esophageal cancer undergoing chemoradiotherapy: Results of a randomized, controlled, multicenter trial - Fietkau, Rainer; Lewitzki, Victor; Kuhnt, Thomas; Hoelscher, Tobias; Hess, Clemens-F.; Berger, Bernhard; Wiegel, Thomas; Roedel, Claus; Niewald, Marcus; Hermann, Robert M.; Lubgan, Dorota (Cancer, 2013)
Background: In patients with head and neck and esophageal tumors, nutritional status may deteriorate during concurrent chemoradiotherapy (CRT). The aim of this study was to investigate the influence of enteral nutrition enriched with eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on body composition and nutritional and functional status. Methods: In a controlled, randomized, prospective, double-blind, multicenter study, 111 patients with head and neck and esophageal cancer undergoing concurrent CRT received either an enteral standard nutrition (control group) or disease-specific enteral nutrition Supportan®-containing EPA+DHA (experimental group) via percutaneous endoscopic gastrostomy. The primary endpoint was the change of body cell mass (BCM) following CRT at weeks 7 and 14 compared with the baseline value. Secondary endpoints were additional parameters of body composition, anthropometric parameters, and nutritional and functional status. Results: The primary endpoint of the study, improvement in BCM, reached borderline statistical significance. Following CRT, patients with experimental nutrition lost only 0.82 ± 0.64 kg of BCM compared with 2.82 ± 0.77 kg in the control group (P =.055). The objectively measured nutritional parameters, such as body weight and fat-free mass, showed a tendency toward improvement, but the differences were not significant. The subjective parameters, in particular the Kondrup score (P =.0165) and the subjective global assessment score (P =.0065) after follow-up improved significantly in the experimental group, compared with the control group. Both enteral regimens were safe and well tolerated. CONCLUSION Enteral nutrition with EPA and DHA may be advantageous in patients with head and neck or esophageal cancer by improving parameters of nutritional and functional status during CRT. © 2013 American Cancer Society.
Created from Fastlane, Scopus look-up
Keywords: concurrent chemoradiotherapy; docosahexaenoic acid; eicosapentaenoic acid; esophageal cancer; head and neck cancer; nutritional status; nutritional therapy; supportive care

Advanced Multimodal Methods for Cranial Pseudo-CT Generation Validated by IMRT and VMAT Radiation Therapy Plans - Speier, Christoph; Pileggi, Giampaolo; Izquierdo-Garcia, David; Catana, Ciprian; Sharp, Gregory C.; Spadea, Maria Francesca; Bert, Christoph; Seco, Joao (International Journal of Radiation Oncology Biology Physics, 2018)
PURPOSE: To investigate advanced multimodal methods for pseudo-computed tomography (CT) generation from standard magnetic resonance imaging sequences and to validate the results by intensity-modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) plans. We present 2 novel methods that employ key techniques to enhance pseudo-CTs and investigate the effect on image quality and applicability for IMRT and VMAT planning. MATERIALS AND METHODS: The data set contains CT and magnetic resonance image scans from 15 patients who underwent cranial radiation therapy. For each patient, pseudo-CTs of the head were generated with a patch-based and a voxel-based algorithm. The accuracy of the pseudo-CTs in comparison to clinical CTs was evaluated by mean absolute error, bias, and the Dice coefficient (of bone). IMRT and VMAT plans were created for each patient. Dose distributions were calculated with both the pseudo-CT and the clinical CT scans and compared by gamma tests, dose-volume histograms, and isocenter doses. RESULTS: The generated pseudo-CTs exhibited average mean absolute errors of 118.7 ± 10.4 HU for the voxel-based algorithm and 73.0 ± 6.4 HU for the patch-based algorithm. The dose calculations were in good agreement and showed gamma test (2 mm, 2%) pass rates for both beam setups (IMRT and VMAT) of over 99% for 14 patients and over 98% for 1 patient. CONCLUSIONS: We showed that the key techniques of our 2 novel algorithms advance the quality of pseudo-CT significantly and generate very competitive pseudo-CTs compared with previously published methods. This quality was confirmed by low dose error in comparison to the ground-truth CT. With the achieved level of accuracy, our patch-based algorithm especially is a candidate for clinical routine use in IMRT and VMAT planning.
EVALuna2:36471

Advances in 4D treatment planning for scanned particle beam therapy - report of dedicated workshops - Bert, Christoph; Graeff, Christian; Riboldi, Marco; Nill, Simeon; Baroni, Guido; Knopf, Antje-Christin (Technology in Cancer Research & Treatment, 2014)
We report on recent progress in the field of mobile tumor treatment with scanned particle beams, as discussed in the latest editions of the 4D treatment planning workshop. The workshop series started in 2009, with about 20 people from 4 research institutes involved, all actively working on particle therapy delivery and development. The first workshop resulted in a summary of recommendations for the treatment of mobile targets, along with a list of requirements to apply these guidelines clinically. The increased interest in the treatment of mobile tumors led to a continuously growing number of attendees: the 2012 edition counted more than 60 participants from 20 institutions and commercial vendors. The focus of research discussions among workshop participants progressively moved from 4D treatment planning to complete 4D treatments, aiming at effective and safe treatment delivery. Current research perspectives on 4D treatments include all critical aspects of time resolved delivery, such as in-room imaging, motion detection, beam application, and quality assurance techniques. This was motivated by the start of first clinical treatments of hepato cellular tumors with a scanned particle beam, relying on gating or abdominal compression for motion mitigation. Up to date research activities emphasize significant efforts in investigating advanced motion mitigation techniques, with a specific interest in the development of dedicated tools for experimental validation. Potential improvements will be made possible in the near future through 4D optimized treatment plans that require upgrades of the currently established therapy control systems for time resolved delivery. But since also these novel optimization techniques rely on the validity of the 4DCT, research focusing on alternative 4D imaging technique, such as MRI based 4DCT generation will continue.
EVALuna2:18197

A generic curriculum development model for the biomedical physics component of the educational and training programmes of the non-physics healthcare professions - Caruana, C. J.; Karenauskaite, V.; Mornstein, V.; Vano, E.; Pace, E.; Lammertsma, A. A.; Maas, A. J.J.; Bert, Christoph; Byrne, B.; Colgan, N.; Essers, M.; Isidoro, J.; et al. (Physica Medica, 2021)
The objective of the study was the construction of a generic curriculum development model for the use of biomedical physics (BMP) educators teaching the non-physics healthcare professions (HCP) in Europe. A comprehensive, qualitative cross-sectional Europe-wide survey of the curricula delivered by BMP in Faculties of Medicine and Health Sciences (FMHS) was carried out. Curricular content was collected from faculty web-sites, curricular documents and textbooks. The survey data was supplemented with semi-structured interviews and direct observation during onsite visits. The number of faculties studied was 118 from 67 universities spread all over Europe, whilst the number of onsite visits/interviews was 15 (geographically distributed as follows: Eastern Europe 6, North Western Europe 5, and South Western Europe 4). EU legislation, recommendations by European national medical councils, educational benchmark statements by higher education quality assurance agencies, research journals concerning HCP education and other documents relevant to standards in clinical practice and undergraduate education were also analyzed. Best practices and BMP learning outcomes were elicited from the curricular materials, interviews and documentation and these were subsequently used to construct the curriculum development model. A structured, comprehensive BMP learning outcomes inventory was designed in the format required by the European Qualifications Framework (EQF). The structures of the inventory and curriculum development model make them ideally suited for use by BMP involved in European curriculum development initiatives for the HCP.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Biomedical physics; Curriculum development; Healthcare professions; Medical devices

A Kernel-based Framework for Intra-fractional Respiratory Motion Estimation in Radiation Therapy - Geimer, Tobias; Unberath, Mathias; Birlutiu, Adriana; Taubmann, Oliver; Wölfelschneider, Jens; Bert, Christoph; Maier, Andreas (Proceedings of the 2017 IEEE International Symposium on Biomedical Imaging, 2017)
In radiation therapy, tumor tracking allows to adjust the beam such that it follows the respiration-induced tumor motion. However, most clinical approaches rely on implanted fiducial markers to locate the tumor and, thus, only provide sparse information. Motion models have been investigated to estimate dense internal displacement fields from an external surrogate signal, such as range imaging. With increasing surrogate complexity, we propose a respiratory motion estimation framework based on kernel ridge regression to cope with high-dimensional domains. This approach was validated on five patient datasets, consisting of a planning 4DCT and a follow-up 4DCT for each patient. Mean residual error was at best 2.73 ± 0.25 mm, but varied greatly between patients.<br
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.akerne_4
Keywords: Motion Models; Range Imaging; Radiation Therapy; Kernel Trick; Active Shape Models

A Kernel Ridge Regression Model for Respiratory Motion Estimation in Radiotherapy - Geimer, Tobias; Birlutiu, Adriana; Unberath, Mathias; Taubmann, Oliver; Bert, Christoph; Maier, Andreas (Bildverarbeitung für die Medizin 2017 - Algorithmen - Systeme - Anwendungen, 2017)
This paper discusses a kernel ridge regression (KRR) model for motion estimation in radiotherapy. Using KRR, dense internal motion fields are estimated from high-dimensional surrogates without the need for prior dimensionality reduction. We compare the proposed model to a related approach with dimensionality reduction in the form of principal component analysis and principle component regression. Evaluation was performed in a simulation study based on nine 4D CT patient data sets achieving a mean estimation error of 0.84 ± 0.21 mm for our approach.<br
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.akerne_3

A multi-institution study: comparison of the heating patterns of five different MR-guided deep hyperthermia systems using an anthropomorphic phantom - Curto, Sergio; Mulder, Hendrik Thijmen; Aklan, Bassim; Mils, Oliver; Schmidt, Manfred; Lamprecht, Ulf; Peller, Michael; Wessalowski, Ruediger; Lindner, Lars H.; Fietkau, Rainer; Zips, Daniel; Van Holthe, Netteke; et al. (International Journal of Hyperthermia, 2020)
Introduction: Within the hyperthermia community, consensus exists that clinical outcome of the treatment radiotherapy and/or chemotherapy plus hyperthermia (i.e. elevating tumor temperature to 40 − 44 °C) is related to the applied thermal dose; hence, treatment quality is crucial for the success of prospective multi-institution clinical trials. Currently, applicator quality assurance (QA) measurements are implemented independently at each institution using basic cylindrical phantoms. A multi-institution comparison of heating quality using magnetic resonance thermometry (MRT) and anatomical representative anthropomorphic phantoms provides a unique opportunity to obtain novel QA insights to facilitate multi-institution trial evaluation. Objective: Perform a systematic QA procedure to compare the performance of MR-compatible hyperthermia systems in five institutions. Methods and materials: Anthropomorphic phantoms, including pelvic and spinal bones, were produced. Clinically relevant power of 600 watts was applied for ∼12 min to allow for 8 sequential MR-scans. The 3D-heating distribution, steering capabilities, and presence of off-target heating were analyzed. Results: The evaluated devices show comparable heating profiles for centric and eccentric targets. The differences observed in the 3D-heating profiles are the result of variations in the exact phantom positioning and applicator characteristics, whereby positioning of the phantom followed current ESHO-QA guidelines. Conclusion: Anthropomorphic phantoms were used to perform QA-measurements of MR-guided hyperthermia systems operating in MR-scanners of different brands. Comparable heating profiles are shown for the five evaluated institutions. Subcentimeter differences in position substantially affected the results when evaluating the heating patterns. Integration of advanced phantoms and precise positioning in QA-guidelines should be evaluated to guarantee the best quality patient care.
CRIS-Team Scopus Importer:2020-10-09
Keywords: anthropomorphic phantom; heating patterns; magnetic resonance (MR)-guided hyperthermia; magnetic resonance thermometry (MRT); Quality assurance (QA)

Analysis of Head and Neck Lymph Node Metastasis Distribution by using Deep Learning automated Lymph Node Level Contouring - Weissmann, Thomas; Huang, Yixing; Speer, Stefan; Semrau, Sabine; Bert, Christoph; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Analysis of the analgesic Effects of LDRT in Patients in the IMMO-LDRT01 Study - Fröhlich, Birgitta; Donaubauer, Anna-Jasmina; Weissmann, T.; Becker, Ina; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Analysis of the immune status from peripheral whole blood with a single-tube multicolor flow cytometry assay - Donaubauer, Anna-Jasmina; Becker, Ina; Rühle, Paul-Friedrich; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Methods in Enzymology, 2020)
Supplementation of standard cancer therapies (radiotherapy, chemotherapy, surgery) with immunotherapies has revolutionized cancer treatment. In order to include recent improvements of multimodal therapies into clinical routine, knowledge about the immune status, the immune dynamics and the detailed composition and activation of patient's immune system is required. The here presented single-tube multicolor flow cytometry assay allows the discrimination of 20 clinically relevant immune cell subsets and their activation status in peripheral whole blood. It includes 15 different antibodies and can be established on a common 3 laser and 10 color flow-cytometer. Furthermore, this assay is easy to set-up and to perform as well as fast with only 40 min of sample preparation time. Moreover, only 100 μL of whole blood are sufficient for this precise determination of the individual immune status. It is already applied in translational programs of clinical studies and trials and can further be adapted for future ones.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Immune status; Immunophenotyping; Multicolor flow-cytometry; Peripheral whole blood; Radioimmunotherapies

An Analysis of the Use Pattern of Hyperthermia (HT) in Combination with Radio(chemo)therapy or Chemotherapy in European HT Centers - Ademaj, A.; Veltsista, D. P.; Marder, D.; Haelg, R. A.; Puric, E.; Brunner, T. B.; Crezee, H.; Gabrys, D.; Franckena, M.; Gani, C.; Horsman, M. R.; Krempien, R.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Anatomical Distribution and relative Frequency of Lymph Node Metastases in Prostate Cancer: Creation of a three-dimensional Model of High-risk Regions with potential Implications for the adjuvant Radiotherapy - Filimonova, I.; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

An easily expandable multi-drug LC-MS assay for the simultaneous quantification of 57 oral antitumor drugs in human plasma - Kehl, Niklas; Schlichtig, Katja; Dürr, Pauline; Bellut, Laura; Dörje, Frank; Fietkau, Rainer; Pavel, Marianne Ellen; Mackensen, Andreas; Wullich, Bernd; Maas, Renke; Fromm, Martin; Geßner, Arne; et al. (Cancers, 2021)
Oral anticancer drugs have led to significant improvements in the treatment of multiple tumor entities. However, in patients undergoing oral antitumor therapy, plasma concentrations are highly variable, resulting in risks of reduced therapeutic effects or an increase in side effects. One important tool to reduce this variability is therapeutic drug monitoring. In this work we describe a method to simultaneously quantify the plasma concentrations of 57 oral antitumor agents. Quantification of these drugs was achieved using liquid chromatography coupled to an Orbitrap mass spectrometer. The method was fully validated according to the FDA guidelines and constitutes a simple and robust way for exposure monitoring of a wide variety of oral anticancer drugs. Applicability to clinical routine was demonstrated by the analysis of 71 plasma samples taken from 39 patients. In summary, this new multi-drug method allows simultaneous quantification of 57 oral antitumor drugs, which can be applied to exposure monitoring in clinical studies, taking into account the broad variety of oral antitumor drugs prescribed in clinical routine.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Exposure measurement; Kinase inhibitors; Liquid chromatography mass spectrometry; Oral antitumor drug; Orbitrap mass spectrometer

An Experimental Survey of Incremental Transfer Learning for Multicenter Collaboration - Huang, Yixing; Bert, Christoph; Gomaa, Ahmed; Fietkau, Rainer; Maier, Andreas; Putz, Florian (IEEE Access, 2024)
Keywords: Continual learning; multicenter collaboration; federated learning; data privacy; deep learning; peer-to-peer; domain incremental learning; incremental transfer learning

An Investigation of Feature-based Nonrigid Image Registration using Gaussian Process - Bayer, Siming; Spiske, Ute; Geimer, Tobias; Luo, Jie; Wells III, William M.; Ostermeier, Martin; Fahrig, Rebecca; Arya, Nabavi; Bert, Christoph; Eyüpoglu, Ilker Yasin; Maier, Andreas (Algorithmen – Systeme – Anwendungen. Proceedings des Workshops, 2020)
For a wide range of clinical applications, such as adaptive treatment planning or intraoperative image update, feature-based deformable registration (FDR) approaches are widely employed because of their simplicity and low computational complexity. FDR algorithms estimate a dense displacement field by interpolating a sparse field, which is given by the established correspondence between selected features. In this paper, we consider the deformation field as a Gaussian Process (GP), whereas the selected features are regarded as prior information on the valid deformations. Using GP, we are able to estimate the both dense displacement field and a corresponding uncertainty map at once. Furthermore, we evaluated the performance of different hyperparameter settings for squared exponential kernels with synthetic, phantom and clinical data respectively. The quantitative comparison shows, GP-based interpolation has performance on par with state-of-the-art B-spline interpolation. The greatest clinical benefit of GP-based interpolation is that it gives a reliable estimate of the mathematical uncertainty of the calculated dense displacement map.<br

An In Vitro Approach for Investigating the Safety of Lipotransfer after Breast-Conserving Therapy - Promny, Theresa; Kutz, Chiara-Sophia; Jost, Tina; Distel, Luitpold; Kadam, Sheetal; Schmid, Rafael; Arkudas, Andreas; Horch, Raymund E.; Kengelbach-Weigand, Annika (Journal of Personalized Medicine, 2022)
The application of lipotransfer after breast-conserving therapy (BCT) and irradiation in breast cancer patients is an already widespread procedure for reconstructing volume deficits of the diseased breast. Nevertheless, the safety of lipotransfer has still not been clarified yet due to contradictory data. The goal of this in vitro study was to further elucidate the potential effects of lipotransfer on the irradiated remaining breast tissue. The mammary epithelial cell line MCF-10A was co-cultured with the fibroblast cell line MRC-5 and irradiated with 2 and 5 Gy. Afterwards, cells were treated with conditioned medium (CM) from adipose-derived stem cells (ADSC), and the effects on the cellular functions of MCF-10A cells and on gene expression at the mRNA level in MCF-10A and MRC-5 cells were analyzed. Treatment with ADSC CM stimulated transmigration and invasion and decreased the surviving fraction of MCF-10A cells. Further, the expression of cytokines, extracellular, and mesenchymal markers was enhanced in mamary epithelial cells. Only an effect of ADSC CM on irradiated fibroblasts could be observed. The present data suggest epithelial–mesenchymal transition-like changes in the epithelial mammary breast cell line. Thus, the benefits of lipotransfer after BCT should be critically weighed against its possible risks for the affected patients.<br

Announcement of the scientific Awards to be awarded in 2020 - Bert, Christoph (Zeitschrift für Medizinische Physik, 2019)
EVALuna2:213673

A novel concept for CT with fixed anodes (FACT): Medical imaging based on the feasibility of thermal load capacity - Kellermeier, Markus; Bert, Christoph; Müller, Reinhold (Physica Medica, 2015)
Focussing primarily on thermal load capacity, we describe the performance of a novel fixed anode CT (FACT) compared with a 100 kW reference CT. Being a fixed system, FACT has no focal spot blurring of the X-ray source during projection. Monte Carlo and finite element methods were used to determine the fluence proportional to thermal capacity. Studies of repeated short-time exposures showed that FACT could operate in pulsed mode for an unlimited period. A virtual model for FACT was constructed to analyse various temporal sequences for the X-ray source ring, representing a circular array of 1160 fixed anodes in the gantry. Assuming similar detector properties at a very small integration time, image quality was investigated using an image reconstruction library. Our model showed that approximately 60 gantry rounds per second, i.e. 60 sequential targetings of the 1160 anodes per second, were required to achieve a performance level equivalent to that of the reference CT (relative performance, RP = 1) at equivalent image quality. The optimal projection duration in each direction was about 10 ?s. With a beam pause of 1 ?s between projections, 78.4 gantry rounds per second with consecutive source activity were thermally possible at a given thermal focal spot. The settings allowed for a 1.3-fold (RP = 1.3) shorter scan time than conventional CT while maintaining radiation exposure and image quality. Based on the high number of rounds, FACT supports a high image frame rate at low doses, which would be beneficial in a wide range of diagnostic and technical applications.
EVALuna2:18269

Antitumor immune responses induced by ionizing irradiation and further immune stimulation - Frey, Benjamin; Rubner, Yvonne; Kulzer, Lorenz; Werthmöller, Nina; Weiss, Eva-Maria; Fietkau, Rainer; Gaipl, Udo (Cancer Immunology Immunotherapy, 2014)
The therapy of cancer emerged as multimodal treatment strategy. The major mode of action of locally applied radiotherapy (RT) is the induction of DNA damage that triggers a network of events that finally leads to tumor cell cycle arrest and cell death. Along with this, RT modifies the phenotype of the tumor cells and their microenvironment. Either may contribute to the induction of specific and systemic antitumor immune responses. The latter are boosted when additional immune therapy (IT) is applied at distinct time points during RT. We will focus on therapy-induced necrotic tumor cell death that is immunogenic due to the release of damage-associated molecular patterns. Immune-mediated distant bystander (abscopal) effects of RT when combined with dendritic cell-based IT and the role of fractionation of radiation in the induction of immunogenic tumor cell death will be discussed. Autologous whole-tumor-cell-based vaccines generated by high hydrostatic pressure technology will be introduced and the influence of cytokines and the immune modulator AnnexinA5 on the ex vivo generated or in situ therapy-induced vaccine efficacy will be outlined. RT should be regarded as immune adjuvant for metastatic disease and as a tool for the generation of an in situ vaccine when applied at distinct fractionation doses or especially in combination with IT to generate immune memory against the tumor. To identify the most beneficial combination and chronology of RT with IT is presumably one of the biggest challenges of innovative tumor research and therapies.
EVALuna2:18146

Anti-tumor immune responses in primary and abscopal tumors differently depend on radiotherapy fractionation and immunotherapy modalities - Rueckert, M.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (2018)
EVALuna2:36507

A patterns of care analysis of hyperthermia in combination with radio(chemo)therapy or chemotherapy in European clinical centers - Ademaj, Adela; Veltsista, Paraskevi D.; Marder, Dietmar; Haelg, Roger A.; Puric, Emsad; Brunner, Thomas B.; Crezee, Hans; Gabrys, Dorota; Franckena, Martine; Gani, Cihan; Horsman, Michael R.; Krempien, Robert; et al. (Strahlentherapie und Onkologie, 2022)
Purpose The combination of hyperthermia (HT) with radio(chemo)therapy or chemotherapy (CT) is an established treatment strategy for specific indications. Its application in routine clinical practice in Europe depends on regulatory and local conditions. We conducted a survey among European clinical centers to determine current practice of HT. Methods A questionnaire with 22 questions was sent to 24 European HT centers. The questions were divided into two main categories. The first category assessed how many patients are treated with HT in combination with radio(chemo)therapy or CT for specific indications per year. The second category addressed which hyperthermia parameters are recorded. Analysis was performed using descriptive methods. Results The response rate was 71% (17/24) and 16 centers were included in this evaluation. Annually, these 16 centers treat approximately 637 patients using HT in combination with radio(chemo)therapy or CT. On average, 34% (range: 3-100%) of patients are treated in clinical study protocols. Temperature readings and the time interval between HT and radio(chemo)therapy or CT are recorded in 13 (81%) and 9 (56%) centers, respectively. The thermal dose quality parameter "cumulative equivalent minutes at 43 degrees C" (CEM43 degrees C) is only evaluated in five (31%) centers for each HT session. With regard to treatment sequence, 8 (50%) centers administer HT before radio(chemo)therapy and the other 8 in the reverse order. Conclusion There is a significant heterogeneity among European HT centers as to the indications treated and the recording of thermometric parameters. More evidence from clinical studies is necessary to achieve standardization of HT practice.
CRIS-Team WoS Importer:2022-09-09

A phase 1b randomised, placebo-controlled trial of nabiximols cannabinoid oromucosal spray with temozolomide in patients with recurrent glioblastoma - Twelves, Chris; Sabel, Michael; Checketts, Daniel; Miller, Sharon; Tayo, Bola; Jove, Maria; Brazil, Lucy; Short, Susan C.; McBain, Catherine; Haylock, Brian; Mulholland, Paul; Herbert, Christopher; et al. (British Journal of Cancer, 2021)
Background: Preclinical data suggest some cannabinoids may exert antitumour effects against glioblastoma (GBM). Safety and preliminary efficacy of nabiximols oromucosal cannabinoid spray plus dose-intense temozolomide (DIT) was evaluated in patients with first recurrence of GBM. Methods: Part 1 was open-label and Part 2 was randomised, double-blind, and placebo-controlled. Both required individualised dose escalation. Patients received nabiximols (Part 1, n = 6; Part 2, n = 12) or placebo (Part 2 only, n = 9); maximum of 12 sprays/day with DIT for up to 12 months. Safety, efficacy, and temozolomide (TMZ) pharmacokinetics (PK) were monitored. Results: The most common treatment-emergent adverse events (TEAEs; both parts) were vomiting, dizziness, fatigue, nausea and headache. Most patients experienced TEAEs that were grade 2 or 3 (CTCAE). In Part 2, 33% of both nabiximols- and placebo-treated patients were progression-free at 6 months. Survival at 1 year was 83% for nabiximols- and 44% for placebo-treated patients (p = 0.042), although two patients died within the first 40 days of enrolment in the placebo arm. There were no apparent effects of nabiximols on TMZ PK. Conclusions: With personalised dosing, nabiximols had acceptable safety and tolerability with no drug–drug interaction identified. The observed survival differences support further exploration in an adequately powered randomised controlled trial. Clinical trial registration: ClinicalTrials.gov: Part 1– NCT01812603; Part 2– NCT01812616.
CRIS-Team Scopus Importer:2021-03-05

App for the Early Detection of Side Effects of Immunotherapy - Goldbrunner, L.; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Appreciation for Prof. Rolf Sauer on the occasion of the transferral of the editorship of "Strahlentherapie und Onkologie" - Fietkau, Rainer; Wenz, Frederik (Strahlentherapie und Onkologie, 2015)
EVALuna2:18268

A Prospective Real-World Multi-Center Study to Evaluate Progression-Free and Overall Survival of Radiotherapy with Cetuximab and Platinum-Based Chemotherapy with Cetuximab in Locally Recurrent Head and Neck Cancer - Hecht, Markus; Hahn, Dennis; Wolber, Philipp; Hautmann, Matthias G.; Reichert, Dietmar; Weniger, Steffi; Belka, Claus; Bergmann, Tobias; Goehler, Thomas; Welslau, Manfred; Gross-Thie, Christina; Guntinas-Lichius, Orlando; et al. (Cancers, 2021)
Simple Summary Despite recent developments in immune checkpoint inhibitors, the treatment of locoregionally recurrent head and neck squamous cell cancer (HNSCC) remains challenging. Prospective data comparing re-irradiation with systemic treatment are not available. The SOCCER trial represents a prospective non-interventional multicenter trial that enrolled patients with locoregionally recurrent HNSCC treated with cetuximab in combination with re-radiotherapy or chemotherapy. A total of 192 patients were analyzed. Radiotherapy combined with cetuximab had superior progression-free and overall survival compared to chemotherapy with cetuximab. This highlights the high efficacy of local re-radiotherapy in combination with cetuximab in patients with locoregionally recurrent HNSCC. Treatment options of locoregional recurrent head and neck squamous cell cancer (HNSCC) include both local strategies as surgery or re-radiotherapy and systemic therapy. In this prospective, multi-center, non-interventional study, patients were treated either with platinum-based chemotherapy and cetuximab (CT + Cet) or re-radiotherapy and cetuximab (RT + Cet). In the current analysis, progression-free survival (PFS) and overall survival (OS) were compared in patients with locoregional recurrence. Four hundred seventy patients were registered in 97 German centers. After exclusion of patients with distant metastases, a cohort of 192 patients was analyzed (129 CT + Cet, 63 RT + Cet). Radiotherapy was delivered as re-irradiation to 70% of the patients. The mean radiation dose was 51.8 Gy, whereas a radiation dose of >= 60 Gy was delivered in 33% of the patients. Chemotherapy mainly consisted of cisplatin/5-flurouracil (40%) or carboplatin/5-flurouracil (29%). The median PFS was 9.2 months in the RT + Cet group versus 5.1 months in the CT + Cet group (hazard ratio for disease progression or death, 0.40, 95% CI, 0.27-0.57, p < 0.0001). Median OS was 12.8 months in the RT + Cet group versus 7.9 months in the CT + Cet group (hazard ratio for death, 0.50, 95% CI, 0.33-0.75, p = 0.0008). In conclusion, radiotherapy combined with cetuximab improved survival compared to chemotherapy combined with cetuximab in locally recurrent HNSCC.
CRIS-Team WoS Importer:2021-08-06

A semi-automatic Segmentation Pipeline for sequential Volumetric Analysis of intracranial Tumors - Putz, Florian; Knippen, S.; Fietkau, Rainer (2017)
EVALuna2:32900

Assessing Organ-at-risk Auto-contouring Solutions: Which Metrics are most predictive of clinical Time Savings? - Putz, Florian; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Lamrani, Allison; Sommer, P.; Fischer, S.; Srinivasan, A.; Frey, Benjamin; Gaipl, Udo; Ott, Oliver; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Assessment of segmentation dependence in macroscopic lung cavity extraction - Khdeir, Asmaa; Geimer, Tobias; Chen, Shuqing; Goppert, Eric; Dankbar, Maximilian; Bert, Christoph; Maier, Andreas (Informatik aktuell, 2018)
Training of respiratory motion models and population-based patient phantoms of the lung often requires the definition of the entire lung cavity region in the 4D-CT. To ease the workload of clinical experts, automatic selection is highly desirable. Many lung cavity extraction methods rely on a pre-segmented lung volume.
CRIS-Team Scopus Importer:2022-06-05

Assessment of the implant geometry in fractionated interstitial HDR breast brachytherapy using an electromagnetic tracking system - Kellermeier, Markus; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Brachytherapy, 2018)
PURPOSE: During the partial-breast treatment course by interstitial brachytherapy, electromagnetic tracking (EMT) was applied to measure the implant geometry. Implant-geometry variation, choice of reference data, and three registration methods were assessed. METHODS AND MATERIALS: The implant geometry was measured in 28 patients after catheter implantation (EMTbed), during CT imaging (EMTCT), and in each of up to n = 9 treatment fractions (EMTF(k), k = 1, 2,… n). EMTF(k) were registered to the planned implant reconstruction (CTplan) by using all dwell positions (DPs), the button centers, or three fiducial sensors on the patient's skin. Variation in implant geometry obtained from EMTF(k) was assessed for EMTbed, EMTCT, and CTplan. RESULTS: EMT was used to measure 3932 catheters. A duration of 6.5 ± 1.7 min was needed for each implant measurement (mean, 17 catheters) plus setup of the EMT system. Data registration based on the DP deviated significantly lower than registration on button centers or fiducial sensors. Within a registration group, there was a <0.5-mm difference in the choice of reference data. Using CTplan as reference for registration, the mean residual distance of DPs on EMT-derived DPs was found at 2.1 ± 1.6 mm (EMTbed), 1.3 ± 0.9 mm (EMTCT), and 2.5 ± 1.5 mm (EMTF(k)). CONCLUSIONS: EMT can assess the implant geometry in high-dose-rate interstitial brachytherapy breast treatments. EMTbed, EMTCT, and CTplan data can serve as reference for assessment of implant changes.
EVALuna2:36444

Association of Plane of Total Mesorectal Excision With Prognosis of Rectal Cancer: Secondary Analysis of the CAO/ARO/AIO-04 Phase 3 Randomized Clinical Trial - Kitz, Julia; Fokas, Emmanouil; Beissbarth, Tim; Stroebel, Philipp; Wittekind, Christian; Hartmann, Arndt; Rueschoff, Josef; Papadopoulos, Thomas; Roesler, Elisabeth; Ortloff-Kittredge, Peter; Kania, Ulrich; Schlitt, Hans; et al. (JAMA Surgery, 2018)
Importance: Previous retrospective studies have shown that surgical quality affects local control in rectal cancer.. Objective: In this secondary end point analysis, we evaluated the prognostic effect of the total mesorectal excision (TME) plane in the CAO/ARO/AIO-04 phase 3 randomized clinical trial. Design, Setting, and Participants: The CAO/ARO/AIO-04 trial enrolled 1236 patients with cT3-4 and/or node-positive rectal adenocarcinoma from 88 centers in Germany between July 25, 2006, and February 26, 2010. Interventions: Patients were randomized to receive treatment with standard fluorouracil-based preoperative chemoradiotherapy (CRT) alone (control arm) or oxaliplatin (experimental arm) followed by TME and adjuvant chemotherapy. Main Outcomes and Measures: The TME quality (mesorectal, intramesorectal, and muscularis propria plane) was prospectively assessed in 1152 operation specimens. An assessment was performed independently by pathologists and surgeons. The results were correlated with clinicopathologic data and the clinical outcome was tested, including multivariable analysis with the Cox regression model. Results: Of 1152 German Caucasian participants, 332 (28.8) were women and the mean age was 63 years. The plane of TME was mesorectal in 930 patients (80.7%), intramesorectal in 169 (14.7%), and muscularis propria in 53 (4.6%). In a univariable analysis, the TME plane was significantly associated with 3-year disease-free survival (mesorectal vs intramesorectal vs muscularis propria, 95% CI, 73.1-78.8 vs 61.6-76.0 vs 55.6-81.3, respectively; P = .01), cumulative incidence of local and distant recurrences (mesorectal vs intramesorectal vs muscularis propria, 95% CI, 2.0-4.5 vs 1.2-8.1 vs 2.5-20.5, respectively; P < .001; and mesorectal vs intramesorectal vs muscularis propria, 95% CI, 17.0-22.4 vs 18.3-32.0 vs 14.2-39.0, respectively; P = .03, respectively), and overall survival (mesorectal vs intramesorectal vs muscularis propria, 95% CI, 88.3-92.3 vs 79.7-91.0 vs 81.6-98.7, respectively; P = .02). In contrast to the pathologist-based evaluation, the assessment of TME plane by the operating surgeon failed to demonstrate prognostic significance for any of these clinical end points. In a multivariable analysis, the plane of surgery (mesorectal vs muscularis propria TME) constituted an independent factor for local recurrence (P = .002). Conclusions and Relevance: This phase 3 randomized clinical trial confirms the long-term clinical effect of TME plane quality on local recurrence, as initially reported in the MRC CR07 study. The data highlight the key role of pathologists and surgeons in the multidisciplinary management of rectal cancer. Trial Registration: ClinicalTrials.gov Identifier: NCT00349076.
EVALuna2:34814

A tool to automatically analyze electromagnetic tracking data from high dose rate brachytherapy of breast cancer patients - Goetz, Th. I.; Lahmer, Godehard; Strnad, Vratislav; Bert, Christoph; Hensel, Bernhard; Tome, A. M.; Lang, E. W. (PLoS ONE, 2017)
During High Dose Rate Brachytherapy (HDR-BT) the spatial position of the radiation source inside catheters implanted into a female breast is determined via electromagnetic tracking (EMT). Dwell positions and dwell times of the radiation source are established, relative to the patient's anatomy, from an initial X-ray-CT-image. During the irradiation treatment, catheter displacements can occur due to patient movements. The current study develops an automatic analysis tool of EMT data sets recorded with a solenoid sensor to assure concordance of the source movement with the treatment plan. The tool combines machine learning techniques such as multi-dimensional scaling (MDS), ensemble empirical mode decomposition (EEMD), singular spectrum analysis (SSA) and particle filter (PF) to precisely detect and quantify any mismatch between the treatment plan and actual EMT measurements. We demonstrate that movement artifacts as well as technical signal distortions can be removed automatically and reliably, resulting in artifact-free reconstructed signals. This is a prerequisite for a highly accurate determination of any deviations of dwell positions from the treatment plan.
EVALuna2:33034

Atrioventricular node ablation in Langendorff-perfused porcine hearts using carbon ion particle therapy: methods and an in vivo feasibility investigation for catheter-free ablation of cardiac arrhythmias - Lehmann, H. Immo; Richter, Daniel; Prokesch, Hannah; Graeff, Christian; Prall, Matthias; Simoniello, Palma; Fournier, Claudia; Bauer, Julia; Kaderka, Robert; Weymann, Alexander; Szabó, Gábor; Sonnenberg, Karin; et al. (Circulation-Arrhythmia and Electrophysiology, 2015)
Particle therapy, with heavy ions such as carbon-12 ((12)C), delivered to arrhythmogenic locations of the heart could be a promising new means for catheter-free ablation. As a first investigation, we tested the feasibility of in vivo atrioventricular node ablation, in Langendorff-perfused porcine hearts, using a scanned 12C beam.Intact hearts were explanted from 4 (30-40 kg) pigs and were perfused in a Langendorff organ bath. Computed tomographic scans (1 mm voxel and slice spacing) were acquired and (12)C ion beam treatment planning (optimal accelerator energies, beam positions, and particle numbers) for atrioventricular node ablation was conducted. Orthogonal x-rays with matching of 4 implanted clips were used for positioning. Ten Gray treatment plans were repeatedly administered, using pencil beam scanning. After delivery, positron emission tomography-computed tomographic scans for detection of ?(+) ((11)C) activity were obtained. A (12)C beam with a full width at half maximum of 10 mm was delivered to the atrioventricular node. Delivery of 130 Gy caused disturbance of atrioventricular conduction with transition into complete heart block after 160 Gy. Positron emission computed tomography demonstrated dose delivery into the intended area. Application did not induce arrhythmias. Macroscopic inspection did not reveal damage to myocardium. Immunostaining revealed strong ?H2AX signals in the target region, whereas no ?H2AX signals were detected in the unirradiated control heart.This is the first report of the application of a (12)C beam for ablation of cardiac tissue to treat arrhythmias. Catheter-free ablation using 12C beams is feasible and merits exploration in intact animal studies as an energy source for arrhythmia elimination.
EVALuna2:18308

Auswirkungen der Kombination des Ligase IV Inhibitors SCR7 mit ionisierender Strahlung auf HNO-Tumorzelllinien und Normalgewebszellen - Hildebrand, Laura; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Autologous whole tumor cell-based vaccines generated with high hydrostatic pressure bear immunogenic potential and act synergistically with radiotherapy to retard tumor growth - Frey, Benjamin; Seitz, C.; Weiss, E. M.; Rueckert, M.; Schlücker, Eberhard; Schaft, Niels; Fietkau, Rainer; Gaipl, Udo (2017)
EVALuna2:32864

Automated data processing and BigData in radiation therapy - Schmidt, O.; Ballmann, N.; Bert, Christoph; Fietkau, Rainer (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Automating implant reconstruction in interstitial brachytherapy of the breast: A hybrid approach combining electromagnetic tracking and image segmentation - Dürrbeck, Christopher; Sauer, Birte; Lotter, Michael; Kreppner, Stephan; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2022)
Background and purpose: To develop a method for automatic reconstruction of catheter implants in interstitial brachytherapy (iBT) of the breast by means of electromagnetic tracking (EMT) with the goal of making treatment planning as time-effective and accurate as possible. Materials and methods: The implant geometry of 64 patients was recorded using an afterloader prototype with EMT functionality immediately after the planning CT. EMT data were transferred to the CT image space by rigidly registering the catheter fixation buttons as landmarks. To further improve reconstruction accuracy, the EMT reconstruction points were used as starting points to define small regions of interest (ROI) in the CT image. Within these ROIs, the catheter track was segmented in the CT using image processing operations such as thresholding and blob detection, thus refining the reconstruction. The perpendicular distance between the refined EMT implant reconstruction points and the manually reconstructed catheters by an experienced treatment planner was calculated as a measure of their geometric agreement. Results: Geometrically, the refined EMT based implant reconstruction shows excellent agreement with the manual reconstruction. The median distance across all patients is 0.25 mm and the 95th percentile is 1 mm. Refinement takes approximately 0.5 s per reconstruction point and typically does not exceed 3 min per implant at no user interaction. Conclusion: The refined EMT based implant reconstruction proved to be extremely accurate and fast compared to manual reconstruction. The presented procedure can in principle be easily transferred to clinical routine and therefore has enormous potential to provide significant time savings in iBT treatment planning whilst improving reconstruction accuracy.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Breast cancer; Electromagnetic tracking; Implant reconstruction; Interstitial brachytherapy

Automation of Implant Reconstruction in Interstitial Brachytherapy of the Breast Using Electromagnetic Tracking - Dürrbeck, Christopher; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (MEDICAL PHYSICS, 2022)
CRIS-Team WoS Importer:2022-07-08

Automation of radiation treatment planning : Evaluation of head and neck cancer patient plans created by the Pinnacle3scripting and Auto-Planning functions - Speer, Stefan; Klein, Andreas; Kober, Lukas; Weiss, Alexander; Yohannes, Indra; Bert, Christoph (Strahlentherapie und Onkologie, 2017)
BACKGROUND: Intensity-modulated radiotherapy (IMRT) techniques are now standard practice. IMRT or volumetric-modulated arc therapy (VMAT) allow treatment of the tumor while simultaneously sparing organs at risk. Nevertheless, treatment plan quality still depends on the physicist's individual skills, experiences, and personal preferences. It would therefore be advantageous to automate the planning process. This possibility is offered by the Pinnacle3treatment planning system (Philips Healthcare, Hamburg, Germany) via its scripting language or Auto-Planning (AP) module. MATERIALS AND METHODS: AP module results were compared to in-house scripts and manually optimized treatment plans for standard head and neck cancer plans. Multiple treatment parameters were scored to judge plan quality (100 points = optimum plan). Patients were initially planned manually by different physicists and re-planned using scripts or AP. RESULTS AND DISCUSSION: Script-based head and neck plans achieved a mean of 67.0 points and were, on average, superior to manually created (59.1 points) and AP plans (62.3 points). Moreover, they are characterized by reproducibility and lower standard deviation of treatment parameters. Even less experienced staff are able to create at least a good starting point for further optimization in a short time. However, for particular plans, experienced planners perform even better than scripts or AP. Experienced-user input is needed when setting up scripts or AP templates for the first time. Moreover, some minor drawbacks exist, such as the increase of monitor units (+35.5% for scripted plans). CONCLUSION: On average, automatically created plans are superior to manually created treatment plans. For particular plans, experienced physicists were able to perform better than scripts or AP; thus, the benefit is greatest when time is short or staff inexperienced.
EVALuna2:33035

Automatisation of catheter reconstruction in interstitial breast BT using electromagnetic tracking - Dürrbeck, Christopher; Abu-Hossin, N.; Lotter, M.; Kreppner, Stephan; Lubgan, Dorota; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-07-15

Baseline Quality of Life of Physical Function Is Highly Relevant for Overall Survival in Advanced Rectal Cancer - Fitz, Tim; Sörgel, Christopher; Rutzner, Sandra; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (Healthcare, 2022)
In advanced rectal cancer, neoadjuvant radiochemotherapy and total mesorectal excision lead to long overall survival. The quality of life (QOL) of the patients is clearly related to the prognosis. Our question was whether the prognosis can be represented with only one question or one score from the QOL questionnaires. 360 consecutively recruited patients diagnosed with advanced rectal cancer were questioned during radiochemotherapy and a follow-up of 8 years. The questionnaires QLQ-C30 and QLQ-CR38 were used; 10 functional and 17 symptom scores were calculated. The functional score “physical function” and the symptom scores “fatigue”, “nausea and vomiting”, “pain” and “appetite loss” were highly prognostic (p < 0.001) for overall survival. “Physical function” was highly prognostic at all time points up to 1 year after starting therapy (p ≤ 0.001). The baseline “physical function” score divided the cohort into a favorable group with an 8-year overall survival rate of 70.4% versus an unfavorable group with 47.5%. In the multivariable analysis, baseline “physical function”, age and distant metastases were independent predictors of overall survival. The score “physical function” is a powerful unrelated risk factor for overall survival in patients with rectal cancer. Future analyses should study whether increased “physical function” after diagnosis could improve survival.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Age; Physical function; Quality of life; Radiochemotherapy; Rectal cancer

Behavioural effects of APH199, a selective dopamine D4 receptor agonist, in animal models - Chestnykh, Daria; Graßl, Fabian; Pfeifer, Conrad; Dülk, Jonas; Ebner, Chiara; Walters, Mona; von Hörsten, Stephan; Kornhuber, Johannes; Kalinichenko, Liubov; Heinrich, Markus; Müller, Christian P. (Psychopharmacology, 2023)
Rationale: The dopamine D4 receptors (DRD4) play a key role in numerous brain functions and are involved in the pathogenesis of various psychiatric disorders. DRD4 ligands have been shown to moderate anxiety, reward and depression-like behaviours, and cognitive impairments. Despite a series of promising but ambiguous findings, the therapeutic advantages of DRD4 stimulation remain elusive. Objectives: The investigation focused on the behavioural effects of the recently developed DRD4 agonist, APH199, to evaluate its impact on anxiety, anhedonia, behavioural despair, establishment and retrieval of alcohol reinforcement, and amphetamine (AMPH)-induced symptoms. Methods: Male C57BL/6 J mice and Sprague–Dawley rats were examined in five independent experiments. We assessed APH199 (0.1–5 mg/kg, i.p.) effects on a broad range of behavioural parameters in the open field (OF) test, conditioned place preference test (CPP), elevated plus maze (EPM), light–dark box (LDB), novelty suppressed feeding (NSF), forced swim test (FST), sucrose preference test (SPT), AMPH-induced hyperlocomotion test (AIH), and prepulse inhibition (PPI) of the acoustic startle response in AMPH-sensitized rats. Results: APH199 caused mild and sporadic anxiolytic and antidepressant effects in EPM and FST, but no remarkable impact on behaviour in other tests in mice. However, we found a significant increase in AMPH-induced hyperactivity, suggesting an exaggeration of the psychotic-like responses in the AMPH-sensitized rats. Conclusions: Our data challenged the hypothesis of the therapeutic benefits of DRD4 agonists, pointing out a possible aggravation of psychosis. We suggest a need for further preclinical studies to ensure the safety of antipsychotics with DRD4 stimulating properties.
CRIS-Team Scopus Importer:2023-03-10
Keywords: Alcohol; Anxiety; APH199; Depression; DRD4 agonist; Psychosis; Schizophrenia

Benchmarking ChatGPT-4 on a radiation oncology in-training exam and Red Journal Gray Zone cases: potentials and challenges for AI-assisted medical education and decision making in radiation oncology - Huang, Yixing; Gomaa, Ahmed; Semrau, Sabine; Haderlein, Marlen; Lettmaier, Sebastian; Weissmann, Thomas; Grigo, Johanna; Ben Tkhayat, Hassen; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Maier, Andreas; et al. (Frontiers in Oncology, 2023)
Keywords: Large language model; Radiotherapy; Natural language processing; Artificial intelligence; Gray Zone; Clinical decision support (CDS)

Bevacizumab Plus Irinotecan Versus Temozolomide in Newly Diagnosed O6-Methylguanine-DNA Methyltransferase Nonmethylated Glioblastoma: The Randomized GLARIUS Trial - Herrlinger, Ulrich; Schaefer, Niklas; Steinbach, Joachim P.; Weyerbrock, Astrid; Hau, Peter; Goldbrunner, Roland; Friedrich, Franziska; Rohde, Veit; Ringel, Florian; Schlegel, Uwe; Sabel, Michael; Ronellenfitsch, Michael W.; et al. (Journal of Clinical Oncology, 2016)
In patients with newly diagnosed glioblastoma that harbors a nonmethylated O(6)-methylguanine-DNA methyltransferase promotor, standard temozolomide (TMZ) has, at best, limited efficacy. The GLARIUS trial thus explored bevacizumab plus irinotecan (BEV+IRI) as an alternative to TMZ.In this phase II, unblinded trial 182 patients in 22 centers were randomly assigned 2:1 to BEV (10 mg/kg every 2 weeks) during radiotherapy (RT) followed by maintenance BEV (10 mg/kg every 2 weeks) plus IRI(125 mg/m(2) every 2 weeks) or to daily TMZ (75 mg/m(2)) during RT followed by six courses of TMZ (150-200 mg/m(2)/d for 5 days every 4 weeks). The primary end point was the progression-free survival rate after 6 months (PFS-6).In the modified intention-to-treat (ITT) population, PFS-6 was increased from 42.6% with TMZ (95% CI, 29.4% to 55.8%) to 79.3% with BEV+IRI (95% CI, 71.9% to 86.7%; P <.001). PFS was prolonged from a median of 5.99 months (95% CI, 2.7 to 7.3 months) to 9.7 months (95% CI, 8.7 to 10.8 months; P < .001). At progression, crossover BEV therapy was given to 81.8% of all patients who received any sort of second-line therapy in the TMZ arm. Overall survival (OS) was not different in the two arms: the median OS was 16.6 months (95% CI, 15.4 to 18.4 months) with BEV+IRI and was 17.5 months (95% CI, 15.1 to 20.5 months) with TMZ. The time course of quality of life (QOL) in six selected domains of the European Organisation for Research and Treatment of Cancer Quality-of-Life Questionnaire (QLQ) -C30 and QLQ-BN20 (which included cognitive functioning), of the Karnofsky performance score, and of the Mini Mental State Examination score was not different between the treatment arms.BEV+IRI resulted in a superior PFS-6 rate and median PFS compared with TMZ. However, BEV+IRI did not improve OS, potentially because of the high crossover rate. BEV+IRI did not alter QOL compared with TMZ.
EVALuna2:18349

Both Gender and Inflammatory Status play a Role in the low-dose Rontgen Therapy Effect on Synovial Fibroblasts - Völlings, Antonia; Piltz, Margaux; Titova, E.; Wolff, Teresa; Weissmann, Thomas; Fietkau, Rainer; Frey, Benjamin; Gaipla, U.; Deloch, Lisa (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Brachytherapy focal dose escalation using ultrasound based tissue characterization by patients with non-metastatic prostate cancer: Five-year results from single-center phase 2 trial - Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer (Brachytherapy, 2022)
PURPOSE: This prospective trial investigates side effects and efficacy of focal dose escalation with brachytherapy for patients with prostate cancer. METHODS AND MATERIALS: In the Phase II, monocentric prospective trial 101 patients with low-/intermediate- and high-risk prostate cancer were enrolled between 2011 and 2013. Patients received either PDR-/HDR-brachytherapy alone with 86–90 Gy (EQD2, α/β = 3 Gy) or PDR-/HDR-brachytherapy as boost after external beam radiation therapy up to a total dose of 91–96 Gy (EQD2, α/β = 3 Gy). Taking place brachytherapy all patients received the simultaneous integrated focal boost to the intra-prostatic tumor lesions visible in computer-aided ultrasonography (HistoScanning™) - up to a total dose of 108–119 Gy (EQD2, α/β = 3 Gy). The primary endpoint was toxicity. Secondary endpoints were cumulative freedom from local recurrence, PSA-free survival, distant metastases-free survival, and overall survival. This trial is registered with ClinicalTrials.gov, number NCT01409876. Results: Median follow-up was 65 months. Late toxicity was generally low with only four patients scoring urinary grade 3 toxicity (4/101, 4%). Occurrence of any grade of late rectal toxicities was very low. We did not register any grade ≥2 of late rectal toxicities. The cumulative 5 years local recurrence rate (LRR) for all patients was 1%. Five years- biochemical disease-free survival estimates according Kaplan-Meier were 98,1% and 81,3% for low-/intermediate-risk and high-risk patients, respectively. Five years metastases-free survival estimates according Kaplan-Meier were 98,0% and 83,3% for all patients, low-/intermediate-risk and high-risk patients, respectively. Conclusions: The 5 years-results from this Phase II Trial show that focal dose escalation with computer-aided ultrasonography and brachytherapy for patients with non-metastatic prostate cancer is safe and effective.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Brachytherapy; Focal dose escalation; Prostate cancer

Brain volume after whole-brain radiotherapy: prognostic relevance and protective factors - Putz, Florian; Hoffmann, Christian; Distel, Luitpold; Gryc, Thomas; Knippen, S.; Fietkau, Rainer (2017)
EVALuna2:32901

Brain volume reduction after whole-brain radiotherapy: quantification and prognostic relevance - Hoffmann, Christian; Distel, Luitpold; Knippen, Stefan; Gryc, Thomas; Schmidt, Manuel; Fietkau, Rainer; Putz, Florian (Neuro-Oncology, 2018)
Background: Recent studies have questioned the value of adding whole-brain radiotherapy (WBRT) to stereotactic radiosurgery (SRS) for brain metastasis treatment. Neurotoxicity, including radiation-induced brain volume reduction, could be one reason why not all patients benefit from the addition of WBRT. In this study, we quantified brain volume reduction after WBRT and assessed its prognostic significance. Methods: Brain volumes of 91 patients with cerebral metastases were measured during a 150-day period after commencing WBRT and were compared with their pretreatment volumes. The average daily relative change in brain volume of each patient, referred to as the "brain volume reduction rate," was calculated. Univariate and multivariate Cox regression analyses were performed to assess the prognostic significance of the brain volume reduction rate, as well as of 3 treatment-related and 9 pretreatment factors. A one-way analysis of variance was used to compare the brain volume reduction rate across recursive partitioning analysis (RPA) classes. Results: On multivariate Cox regression analysis, the brain volume reduction rate was a significant predictor of overall survival after WBRT (P < 0.001), as well as the number of brain metastases (P = 0.002) and age (P = 0.008). Patients with a relatively favorable prognosis (RPA classes 1 and 2) experienced significantly less brain volume decrease after WBRT than patients with a poor prognosis (RPA class 3) (P = 0.001). There was no significant correlation between delivered radiation dose and brain volume reduction rate (P = 0.147). Conclusion: In this retrospective study, a smaller decrease in brain volume after WBRT was an independent predictor of longer overall survival.
EVALuna2:36468

Breast brachytherapy - Strnad, Vratislav; Yashar, Catheryn (Brachytherapy, 2020)
Accelerated partial breast irradiation with brachytherapy is a treatment method with a very low risk profile. In fact, accelerated partial breast irradiation brachytherapy has been proven in randomized trials to have fewer late side effects than whole-breast irradiation. Notably, Grade 3 late side effects are extremely rare, and excellent to good cosmetic results are observed in well over 90% of patients. In this article, published side effects of breast brachytherapy are reviewed and appropriate management discussed.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Brachytherapy; Breast; Side effects

Broadband microwave spiral applicator (105–125 MHz) for in vitro examinations of hyperthermia-induced tumor cell death forms–first analyses with human breast cancer cells - Walter, Jannik; Hader, Michael; Sengedorj, Azzaya; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (International Journal of Hyperthermia, 2023)
Purpose: Local tumor heating with microwave applicators has been used in multimodal breast cancer therapies. This hyperthermia allows to target small regions while marginally affecting healthy tissue. However, most preclinical examinations only use simplified heating methods. Microwave applicators employed for deep heating to provide the greatest depth of penetration operate in the tens to hundreds frequency. Therefore, we aimed to adapt and test a clinically often used broadband spiral applicator (105–125 MHz) for hyperthermia with clinically wanted temperatures of 41 and 44 °C in in vitro settings with human breast cancer cell lines and with simulations. Material and Methods: A clinically used spiral-microwave applicator (105–125 MHz) was the basis for the construction, simulation, and optimization of the in vitro HT set-up under stationary conditions. Microwave effects on tumor cell death of two human breast cancer cell lines (hormone-receptor positive MCF-7 and triple-negative MDA-MB-231) were compared with conventional heating in a contact-heating chamber. Cell death forms were analyzed by AnnexinV/Propidium iodide staining. Results: An in vitro spiral applicator microwave-based heating system that is effective at applying heat directly to adherent breast cancer cells in cell culture flasks with medium was developed. Simulations with COMSOL proved appropriate heat delivery and an optimal energy coupling at a frequency of 111 ± 2.5 MHz. Apoptosis and necrosis induction and significantly higher cell death rates than conventional heating at both temperatures were observed, and MCF-7 showed higher death rates than MDA-MB-231 tumor cells. Conclusions: Well-characterized in vitro heating systems are mandatory for a better understanding of the biological effects of hyperthermia in tumor therapies and to finally determine optimized clinical treatment schemes.
CRIS-Team Scopus Importer:2023-10-20
Keywords: 105–125 MHz spiral applicator; breast cancer; cell death forms; microwave frequency; Microwave hyperthermia; multimodal tumor treatment

Cancer Cell Death-Inducing Radiotherapy: Impact on Local Tumour Control, Tumour Cell Proliferation and Induction of Systemic Anti-tumour Immunity - Frey, Benjamin; Derer, Anja; Scheithauer, Heike; Wunderlich, Roland; Fietkau, Rainer; Gaipl, Udo (Advances in Experimental Medicine and Biology, 2016)
Radiotherapy (RT) predominantly is aimed to induce DNA damage in tumour cells that results in reduction of their clonogenicity and finally in tumour cell death. Adaptation of RT with higher single doses has become necessary and led to a more detailed view on what kind of tumour cell death is induced and which immunological consequences result from it. RT is capable of rendering tumour cells immunogenic by modifying the tumour cell phenotype and the microenvironment. Danger signals are released as well as the senescence-associated secretory phenotype. This results in maturation of dendritic cells and priming of cytotoxic T cells as well as in activation of natural killer cells. However, RT on the other hand can also result in immune suppressive events including apoptosis induction and foster tumour cell proliferation. That's why RT is nowadays increasingly combined with selected immunotherapies.
EVALuna2:18359

Can clinicopathological parameters predict for lymph node metastases in ypT0-2 rectal carcinoma? Results of the CAO/ARO/AIO-94 and CAO/ARO/AIO-04 phase 3 trials - Von Den Gruen, Jens Mueller; Hartmann, Arndt; Fietkau, Rainer; Ghadimi, Michael; Liersch, Torsten; Hohenberger, Werner; Weitz, Jurgen; Sauer, Rolf; Wittekind, Christian; Stroebel, Philipp; Roedel, Claus; Fokas, Emmanouil (Radiotherapy and Oncology, 2018)
BACKGROUND: The advent of less radical surgical approaches has generated concern about leaving locoregional lymph node metastases (LNM) unresected that could lead to adverse outcome. We examined the prognostic role of clinicopathological factors for ypN-positivity in patients with ypT0-2 rectal carcinoma treated within the CAO/ARO/AIO-94 and CAO/ARO/AIO-04 randomized phase 3 trials. METHODS: The correlation of clinicopathological factors with ypN-status (ypN0 vs ypN1/2) was examined in n = 776 patients with ypT0-2 rectal carcinoma after preoperative CRT and total mesorectal excision surgery using Pearson's Chi-squared test for categorical variables and Kruskal-Wallis' test for continuous variables. Multivariable analysis was performed using binary logistic regression to identify independent prognosticators for ypN-positivity. RESULTS: Residual LNM (ypN+) were found in 6%, 20.8% and 21.4% of patients with ypT0, ypT1 and ypT2 carcinomas, respectively. Independent prognosticators for LNM were advanced ypT category (p = 0.002) and lymphatic invasion (p = 0.020). In a separate multivariable analysis performed upon exclusion of ypT-category due to multicollinearity with residual tumor diameter (RTD), lymphatic invasion (p = 0.015) and RTD ≥10 mm (p = 0.005) demonstrated strong correlation with LNM. CONCLUSION: Advanced ypT-stage, lymphatic invasion and RTD ≥10 mm were prognostic factors for LNM in patients ypT0-2 rectal carcinoma treated with CRT and surgery within both phase 3 trials. The high incidence of LNM in the ypT1-2 group needs to be taken into consideration in the context of oncological safety and indicate that LE should be advocated with great caution in this patient subgroup. The prognostic pathological factor identified here could help guide decision of LE vs TME after standard CRT.
EVALuna2:34854

Can local excision be safely recommended in patients with ypT0-2 rectal cancer after chemoradiotherapy? Clinicopathological results of the CAO/ARO/AIO-94 and CAO/ARO/AIO-04 randomized phase 3 trials - Von Den Gruen, Mueller J.; Hartmann, Arndt; Fietkau, Rainer; Ghadimi, M.; Liersch, T.; Stroebel, P.; Sauer, Rolf; Roedel, C.; Fokas, E. (2018)
EVALuna2:36508

Causes for the different Responses of Head and Neck Tumor and Normal Tissue Cell Lines to DNA-PK and mTor Inhibitors in Combination with ionizing Radiation - Klieber, N.; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

CBCT-based Detection and Analysis of the Positional Stability of implanted Gold Markers and Changes in the Shape of the Rectal Balloon during the Radiotherapy of the Prostate-Ca - Kallis, Karoline; Brandt, Tobias; Strnad, Vratislav; Lettmaier, S.; Fietkau, Rainer; Maier, Anne-Kathrin; Bert, Christoph (2017)
EVALuna2:32885

CD8+and Regulatory T cells Differentiate Tumor Immune Phenotypes and Predict Survival in Locally Advanced Head and Neck Cancer - Echarti, Alessia; Hecht, Markus; Büttner-Herold, Maike; Haderlein, Marlen; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cancers, 2019)
Background: The tumor immune status "inflamed", "immune excluded", and "desert" might serve as a predictive parameter. We studied these three cancer immune phenotypes while using a simple immunohistochemical algorithm. Methods: Pre-treatment tissue samples of 280 patients with locally advanced HNSCC treated with radiochemotherapy were analyzed. A double staining of CD8+ cytotoxic T cells (CTL) and FoxP3+ (Treg) was performed and the cell density was evaluated in the intraepithelial and stromal compartment of the tumor. Results: The classification of tumors as "immune desert" when stromal CTL were <= 50 cells/mm(2), "inflamed" when intraepithelial CTL were > 500 cells/mm(2), and as "excluded" when neither of these definitions met these cut off values allowed the best discrimination regarding overall survival. These groups had median OS periods of 37, 61, and 85 months, respectively. In "immune desert" and "immune excluded" tumors high Treg tended to worsen OS, but in "inflamed" tumors high Treg clearly improved OS. Conclusions: We propose that, in locally advanced HNSCC, the tumor immune state "inflamed", "immune excluded", and "immune desert" can be defined by intraepithelial and stromal CTL. Tregs can further subdivide these groups. The opposing effects of Tregs in the different groups might be the reason for the inconsistency of Tregs prognostic values published earlier.
CRIS-Team WoS Importer:2019-10-25

Cell-Cannibalism by Normal Tissue Cells as a Survival Benefit after Irradiation of Normal Tissue Cells leads to an Increase in their Activity as non-professional Phagocytes - Sonntag, T.; Distel, Luitpold; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Cell-in-cell phenomenon: leukocyte engulfment by non-tumorigenic cells and cancer cell lines - Bauer, Mareike; Hader, Michael; Hecht, Markus; Büttner-Herold, Maike; Fietkau, Rainer; Distel, Luitpold (BMC Molecular and Cell Biology, 2021)
Background Research on cell-in-cell (CIC) phenomena, including entosis, emperipolesis and cannibalism, and their biological implications has increased in recent years. Homotypic and heterotypic engulfment of various target cells by numerous types of host cells has been studied in vitro and in tissue sections. This work has identified proteins involved in the mechanism and uncovered evidence for CIC as a potential histopathologic predictive and prognostic marker in cancer. Our experimental study focused on non-professional phagocytosis of leukocytes. Results We studied the engulfment of peripheral blood mononuclear cells isolated from healthy donors by counting CIC structures. Two non-tumorigenic cell lines (BEAS-2B, SBLF-9) and two tumour cell lines (BxPC3, ICNI) served as host cells. Immune cells were live-stained and either directly co-incubated or treated with irradiation or with conventional or microwave hyperthermia. Prior to co-incubation, we determined leukocyte viability for each batch via Annexin V-FITC/propidium iodide staining. All host cells engulfed their targets, with uptake rates ranging from 1.0% +/- 0.5% in BxPC3 to 8.1% +/- 5.0% in BEAS-2B. Engulfment rates of the cancer cell lines BxPC3 and ICNI (1.6% +/- 0.2%) were similar to those of the primary fibroblasts SBLF-9 (1.4% +/- 0.2%). We found a significant negative correlation between leukocyte viability and cell-in-cell formation rates. The engulfment rate rose when we increased the dose of radiotherapy and prolonged the impact time. Further, microwave hyperthermia induced higher leukocyte uptake than conventional hyperthermia. Using fluorescent immunocytochemistry to descriptively study the proteins involved, we detected ring-like formations of diverse proteins around the leukocytes, consisting, among others, of alpha-tubulin, integrin, myosin, F-actin, and vinculin. These results suggest the involvement of actomyosin contraction, cell-cell adhesion, and the alpha-tubulin cytoskeleton in the engulfment process. Conclusions Both non-tumorigenic and cancer cells can form heterotypic CIC structures by engulfing leukocytes. Decreased viability and changes caused by microwave and X-ray irradiation trigger non-professional phagocytosis.
CRIS-Team WoS Importer:2021-08-13

Cell-in-cell structures are more potent predictors of outcome than senescence or apoptosis in head and neck squamous cell carcinomas - Schenker, Hannah; Buettner-Herold, Maike; Fietkau, Rainer; Distel, Luitpold (Radiation Oncology, 2017)
This study sheds light on cell inactivating processes with focus on the phenomenon of cell-in-cell (CIC). Cell-in-cell describes a cell process where one cell is being engulfed by another non-professional phagocyte. We determined frequency and prognostic impact of CIC structures (CICs) as well as of senescent and apoptotic cells in head and neck squamous cell carcinomas (HNSCC).These different forms of cell inactivation as well as the proportion of proliferating and tumor cells were assessed in 169 pre-radiochemotherapy biopsies and 32 post-therapy tumor resections by immunohistochemistry of tissue microarrays. Four consecutive cancer sections were stained with antibodies specific for E-cadherin for CIC detection, cleaved caspase-3 for apoptosis, H3K9Me for senescence and Ki67 as a proliferation marker. Positive events were quantified in corresponding tumor areas.CICs were found in 55.5%, senescent cells in 67.1% and apoptotic cells in 93.3% of samples. While no prognostic impact of apoptotic and senescent cells was observed, CICs turned out to significantly influence overall-survival (p = 0.016) with a lack of CICs being prognostically beneficial. There was no correlation between CICs and apoptosis and 98.9% of CICs were negative for cleaved caspase-3.CIC formation is a frequent event in HNSCC and a superior predictive marker compared to senescence and apoptosis. Independence of CIC and apoptosis and the adverse prognosis associated with numerous CICs lead to the assumption that CICs might take up necrotic rather than apoptotic cells preventing an adequate antitumoral immune response that would otherwise be initiated by necrotic cells through damage-associated molecular pattern molecules.
EVALuna2:25527

Cell-In-Cell Structures in Early Breast Cancer Are Prognostically Valuable - Bauer, Mareike; Hildebrand, Laura; Rosahl, Marie Charlotte; Erber, Ramona; Schnellhardt, Sören; Büttner-Herold, Maike; Putz, Florian; Ott, Oliver; Hack, Caroline; Fietkau, Rainer; Distel, Luitpold (Cells, 2023)
Cell-in-cell (CIC) structures in breast cancer have so far been studied in a small inhomogeneous patient population, suggesting the prognostic importance of CIC. In the present study, we focused on CIC in early hormone-sensitive breast cancer. With in vitro co-culture experiments, we compared the homotypic phagocytic capacity of two breast cancer cell lines to that of primary human fibroblasts. Afterward, we studied 601 tissue specimens from 147 patients participating in an institutional accelerated partial breast irradiation (APBI) phase II trial. Both breast cancer cell lines performed non-professional phagocytosis at a higher rate than primary human fibroblasts. In this study cohort, 93.2% of the patients had T1 tumours, and 6.8% had T2 tumours. CIC was found in 61.2% of the patients, with a CIC rate ranging from <1/mm2 to 556.5/mm2 with a mean of 30.9/mm2 ± 68.4/mm2. CIC structures were prognostically favourable for local recurrence-free survival and disease-free survival. Regarding metastasis-free survival, CIC-positive patients had an unfavourable prognosis. Subgroup analysis indicated a correlation between a high proliferation index and high CIC rates. CIC had the highest prognostic value in young breast cancer patients (p = 0.004). With this study, we provide further evidence of CIC as a prognostic marker in breast cancer.
CRIS-Team Scopus Importer:2023-01-20
Keywords: accelerated partial breast irradiation; breast cancer; cell-in-cell; ionizing radiation; non-professional phagocytosis; radiotherapy

Cell-to-cell distances between tumor-infiltrating inflammatory cells have the potential to distinguish functionally active from suppressed inflammatory cells - Nagl, Sandra; Haas, M.; Lahmer, Godehard; Buettner-Herold, M.; Grabenbauer, Gerhard; Fietkau, Rainer; Distel, Luitpold (OncoImmunology, 2016)
Beyond their mere presence, the distribution pattern of inflammatory cells is of special interest. Our hypothesis was that random distribution may be a clear indicator of being non-functional as a consequence of lack of interaction. Here, we have assessed the implication of cell-to-cell distances among inflammatory cells in anal squamous cell carcinoma and a possible association with survival data. Thirty-eight patients suffering from anal carcinoma were studied using tissue microarrays, double staining immunohistochemistry, whole slide scanning and image analysis software. Therapy consisted of concurrent radiochemotherapy. Numbers of stromal and intraepithelial tumor-infiltrating inflammatory cells (TIC) and the distances between cells were quantified. Double-staining of FoxP3(+) cells with either CD8(+), CD1a(+) or CD20(+) cells was performed. Measured cell-to-cell distances were compared to computer simulated cell-to-cell distances leading to the assumption of non-randomly distributed and therefore functional immune cells. Intraepithelial CD1a(+) and CD20(+) cells were randomly distributed and therefore regarded as non-functional. In contrary, stromal CD20(+) cells had a non-random distribution pattern. A non-random distance between CD20(+) and FoxP3(+) cells was associated with a clearly unfavorable outcome. Measured distances between FoxP3(+) cells were distinctly shorter than expected and indicate a functional active state of the regulatory T cells (Treg). Analysis of cell-to-cell distances between TIC has the potential to distinguish between suppressed non-functional and functionally active inflammatory cells. We conclude that in this tumor model most of the CD1a(+) cells are non-functional as are the intraepithelial CD20(+) cells, while stromal CD20(+) cells and FoxP3(+) cells are functional cells.
EVALuna2:18358

Cetuximab, fluorouracil and cisplatin with or without docetaxel for patients with recurrent and/or metastatic squamous cell carcinoma of the head and neck (CeFCiD): an open-label phase II randomised trial (AIO/IAG-KHT trial 1108) - Klinghammer, K.; Gauler, T.; Dietz, A.; Grünwald, V.; Stöhlmacher, J.; Knipping, S.; Schroeder, M.; Guntinas-Lichius, O.; Frickhofen, N.; Lindeman, H. W.; Fietkau, Rainer; Haxel, B.; et al. (European Journal of Cancer, 2019)
Background: The combination of cisplatin, 5-fluorouracil (5-FU) and cetuximab (PFC) is the reference first-line treatment for recurrent/metastatic (R/M) squamous cell carcinoma of the head and neck (SCCHN). We analysed whether treatment intensification by the addition of docetaxel to PFC improved efficacy in R/M SCCHN. Methods: A total of 180 patients with R/M SCCHN (1:1) were assigned to receive either cisplatin (40 mg/m2), docetaxel (40 mg/m2) and 5-FU (2000 mg/m2) at days 1 and 8 and cetuximab (400/250 mg/m2) at days 1, 8 and 15 (DPFC) or standard cisplatin (100 mg/m2) at day 1, 5-FU (1000 mg/m2) at days 1–4 and cetuximab (400/250 mg/m2) at days 1, 8 and 15 (PFC). Chemotherapy was repeated every 21 days and continued for a maximum of 6 cycles in absence of disease progression or limiting toxicity, followed by cetuximab maintenance (500 mg/m2 every 2 weeks). The primary end-point was progression-free survival (PFS). Results: A preplanned interim analysis for toxicity after 20 patients/arm revealed excessive grade 3 and 4 gastrointestinal (65%) and infectious toxicities (35%) in arm A, which led to dose reduction of cisplatin to 30 mg/m2 and 5-FU to 1000 mg/m2 for subsequent patients. With a median follow-up of 2 years, grade 4 toxicities were 21.3% vs. 30.8% for DPFC and PFC, respectively. More treatment-related deaths occurred with DPFC vs. PFC, with 11.2% and 6.6%, respectively. For DPFC and PFC, the median PFS was 6.3 vs. 6.4 months (hazard ratio [HR] = 0.97, p = 0.87), the median overall survival was 8.9 vs. 10.6 months (HR = 1.29 p = 0.1) and response rates were 38.2% vs. 31.9% (p = 0.9), respectively. Conclusions: DPFC failed to improve efficacy in R/M SCCHN. On the contrary, a high toxicity and mortality rate was detected in both arms, which underscores the vulnerability of patients with R/M SCCHN, and research on the need for further optimisation of the front-line chemotherapy backbone is ongoing.
CRIS-Team Scopus Importer:2019-10-18
Keywords: Cetuximab; Chemotherapy; Docetaxel; Head and neck cancer; Randomised trial

Cetuximab in combination with platinum-based chemotherapy or radiotherapy in patients with recurrent and/or metastatic SSCHN in clinical routine: Updated interim results of the prospective SOCCER study - Hecht, Markus; Hahn, D.; Wolber, P.; Hautmann, M.; Reichert, D.; Weniger, J.; Belka, C.; Bergmann, T.; Goehler, T.; Welslau, M. K.; Hofmann, D.; Fietkau, Rainer (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

Cetuximab in combination with platinum-based chemotherapy or radiotherapy in recurent and/or metastatic SCCHN in a non-selected patient cohort (interim analysis of the phase IV SOCCER trial) - Hecht, Markus; Hahn, D.; Beutner, D.; Reichert, D.; Goehler, T.; Wurm, R.; Welslau, M.; Renziehausen, L.; Balermpas, P.; Bergmann, T.; Assmann, M.; Belka, C.; et al. (2016)
EVALuna2:32920

Cetuximab in combination with platinum-based chemotherapy or radiotherapy in recurent and/or metastatic SCCHN in a non-selected patient cohort (interim analysis of the phase IV SOCCER trial) - Hecht, Markus; Hahn, D.; Beutner, D.; Reichert, D.; Goehler, T.; Wurm, R.; Welslau, M.; Renziehausen, L.; Balermpas, P.; Bergmann, T.; Assmann, M.; Belka, C.; et al. (2016)
EVALuna2:32919

Challenges of radiotherapy: report on the 4D treatment planning workshop 2013 - Knopf, Antje; Nill, Simeon; Yohannes, Indra; Graeff, Christian; Dowdell, Stephen; Kurz, Christopher; Sonke, Jan-Jakob; Biegun, Aleksandra K.; Lang, Stephanie; Mcclelland, Jamie; Champion, Benjamin; Fast, Martin; et al. (Physica Medica, 2014)
This report, compiled by experts on the treatment of mobile targets with advanced radiotherapy, summarizes the main conclusions and innovations achieved during the 4D treatment planning workshop 2013. This annual workshop focuses on research aiming to advance 4D radiotherapy treatments, including all critical aspects of time resolved delivery, such as in-room imaging, motion detection, motion managing, beam application, and quality assurance techniques. The report aims to revise achievements in the field and to discuss remaining challenges and potential solutions. As main achievements advances in the development of a standardized 4D phantom and in the area of 4D-treatment plan optimization were identified. Furthermore, it was noticed that MR imaging gains importance and high interest for sequential 4DCT/MR data sets was expressed, which represents a general trend of the field towards data covering a longer time period of motion. A new point of attention was work related to dose reconstructions, which may play a major role in verification of 4D treatment deliveries. The experimental validation of results achieved by 4D treatment planning and the systematic evaluation of different deformable image registration methods especially for inter-modality fusions were identified as major remaining challenges. A challenge that was also suggested as focus for future 4D workshops was the adaptation of image guidance approaches from conventional radiotherapy into particle therapy. Besides summarizing the last workshop, the authors also want to point out new evolving demands and give an outlook on the focus of the next workshop.
EVALuna2:18242

Change in the radio-oncological Treatment Concept for Brain Metastases through a dedicated Radiotherapy Planning MRI - Voigt, R.; Masitho, Siti; Grigo, Johanna; Reissig, L.; Uder, Michael; Semrau, Sabine; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Characteristics of the first 615 patients enrolled in Pacific R: A study of the first real-world data on unresectable stage III NSCLC patients treated with durvalumab after chemoradiotherapy - Girard, N.; Fietkau, Rainer; Garassino, M.; Garrido, Pilar; Field, J. K.; Peters, S.; Smit, H. J. M.; Perol, M.; Merle, P.; Sibille, A.; Markman, B.; Bouchaab, H.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-10-30

Chemoradiation Increases PD-L1 Expression in Certain Melanoma and Glioblastoma Cells - Derer, Anja; Spiljar, Martina; Baeumler, Monika; Hecht, Markus; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (Frontiers in Immunology, 2016)
Immunotherapy approaches currently make their way into the clinics to improve the outcome of standard radiochemotherapy (RCT). The programed cell death receptor ligand 1 (PD-L1) is one possible target that, upon blockade, allows T cell-dependent antitumor immune responses to be executed. To date, it is unclear which RCT protocol and which fractionation scheme leads to increased PD-L1 expression and thereby renders blockade of this immune suppressive pathway reasonable. We therefore investigated the impact of radiotherapy (RT), chemotherapy (CT), and RCT on PD-L1 surface expression on tumor cells of tumor entities with differing somatic mutation prevalence. Murine melanoma (B16-F10), glioblastoma (GL261-luc2), and colorectal (CT26) tumor cells were treated with dacarbazine, temozolomide, and a combination of irinotecan, oxaliplatin, and fluorouracil, respectively. Additionally, they were irradiated with a single dose [10 Gray (Gy)] or hypo-fractionated (2 × 5 Gy), respectively, norm-fractionated (5 × 2 Gy) radiation protocols were used. PD-L1 surface and intracellular interferon (IFN)-gamma expression was measured by flow cytometry, and IL-6 release was determined by ELISA. Furthermore, tumor cell death was monitored by AnnexinV-FITC/7-AAD staining. For firstin vivoanalyses, the B16-F10 mouse melanoma model was chosen. In B16-F10 and GL261-luc2 cells, particularly norm-fractionated and hypo-fractionated radiation led to a significant increase of surface PD-L1, which could not be observed in CT26 cells. Furthermore, PD-L1 expression is more pronounced on vital tumor cells and goes along with increased levels of IFN-gamma in the tumor cells. In melanoma cells CT was the main trigger for IL-6 release, while in glioblastoma cells it was norm-fractionated RT.In vivo, fractionated RT only in combination with dacarbazine induced PD-L1 expression on melanoma cells. Our results suggest a tumor cell-mediated upregulation of PD-L1 expression following in particular chemoradiation that is not only dependent on the somatic mutation prevalence of the tumor entity.
EVALuna2:32917
Keywords: fractionated radiotherapy; immunotherapy; checkpoint inhibitor; PD-L1; IFN-gamma; IL-6; melanoma; glioblastoma

Chemoradiotherapy plus hyperthermia (CRTH) versus chemoradiotherapy (CRT) alone in neoadjuvant treatment of soft tissue sarcoma: tumor response, treatment toxicity and disease control - Willner, Alexander; Agaimy, Abbas; Fechner, Katja; Ott, Oliver; Denz, Axel; Weissmann, Thomas; Meidenbauer, Norbert; Höfler, Daniel; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Haller, Florian; et al. (International Journal of Hyperthermia, 2023)
Introduction: Neoadjuvant chemotherapy and radiotherapy for the management of soft tissue sarcomas (STS) are still preferably delivered sequentially, with or without concurrent hyperthermia. Concurrent delivery of chemo-, radio- and thermotherapy may produce synergistic effects and reduce chemotherapy-free intervals. The few available studies suggest that concurrent chemoradiation (CRT) has a greater local effect. Data on the efficacy and toxicity of adding hyperthermia to CRT (CRTH) are sparse. Materials and methods: A cohort of 101 patients with STS of the extremities and trunk who received CRT (n = 33) or CRTH (n = 68) before resection of macroscopic tumor (CRT: n = 19, CRTH: n = 49) or re-resection following a non-oncological resection, so called ‘whoops procedure’, (CRT: n = 14, CRTH: n = 19) were included in this retrospective study. CRT consisted of two cycles of doxorubicine (50 mg/m2 on d2) plus ifosfamide (1500 mg/m2 on d1-5, q28) plus radiation doses of up to 60 Gy. Hyperthermia was delivered in two sessions per week. Results: All patients received the minimum dose of 50 Gy. Median doses of ifosfamide and doxorubicin were comparable between CRT (75%/95%) and CRTH (78%/97%). The median number of hyperthermia sessions was seven. There were no differences in acute toxicities. Major wound complications occurred in 15% (CRT) vs. 25% (CRTH) (p = 0.19). In patients with macroscopic disease, the addition of hyperthermia resulted in a tendency toward improved remission: regression ≥90% occurred in 21/48 (CRTH) vs. 4/18 (CRT) patients (p = 0.197). With a median postoperative follow-up of 72 months, 6-year local control and overall survival rates for CRTH vs. CRT alone were 85 vs. 78% (p = 0.938) and 79 vs. 71% (p = 0.215). Conclusions: Both CRT and CRTH are well tolerated with an expected rate of wound complications. The results suggest that adding hyperthermia may improve tumor response.
CRIS-Team Scopus Importer:2023-09-01
Keywords: chemoradiotherapy; chemotherapy; hyperthermia; neoadjuvant; radiotherapy; Sarcoma; soft-tissue sarcoma; toxicity

Chemoradiotherapy plus induction or consolidation chemotherapy as total neoadjuvant therapy for locally advanced rectal cancer: Final results of the CAO/ARO/AIO-12 randomized phase 2 trial - Fokas, E.; Schlenska-Lange, A.; Polat, B.; Klautke, G.; Grabenbauer, G.; Fietkau, Rainer; Kuhnt, T.; Staib, L.; Brunner, T.; Grosu, A. -L.; Kirste, S.; Jacobasch, L.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Chemoradiotherapy Plus Induction or Consolidation Chemotherapy as Total Neoadjuvant Therapy for Patients With Locally Advanced Rectal Cancer Long-term Results of the CAO/ARO/AIO-12 Randomized Clinical Trial - Fokas, Emmanouil; Schlenska-Lange, Anke; Polat, Buelent; Klautke, Gunther; Grabenbauer, Gerhard G.; Fietkau, Rainer; Kuhnt, Thomas; Staib, Ludger; Brunner, Thomas; Grosu, Anca-Ligia; Kirste, Simon; Jacobasch, Lutz; et al. (JAMA Oncology, 2021)
IMPORTANCE Total neoadjuvant therapy has been increasingly adopted for multimodal rectal cancer treatment. The optimal sequence of chemoradiotherapy (CRT) and chemotherapy needs to be established.
CRIS-Team WoS Importer:2021-12-10

Chemoradiotherapy plus induction versus consolidation chemotherapy as total neoadjuvant therapy for locally advanced rectal cancer: results of the German CAO/ARO/AIO-12 multicentre, open-label, randomised, phase 2 trial - Fokas, E.; Allgaeuer, M.; Polat, B.; Klautke, G.; Grabenbauer, G.; Fietkau, Rainer; Kuhnt, T.; Staib, L.; Brunner, T.; Grosu, A-L; Schmiegel, W.; Jacobasch, L.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Chemoradiotherapy with and without deep regional hyperthermia for squamous cell carcinoma of the anus - Ott, Oliver J.; Schmidt, Manfred; Semrau, Sabine; Strnad, Vratislav; Matzel, Klaus E.; Schneider, Ignaz Hans Friedrich; Raptis, Dimitrios; Uter, Wolfgang; Grützmann, Robert; Fietkau, Rainer (Strahlentherapie und Onkologie, 2018)
PURPOSE: To compare results after chemoradiotherapy with and without deep regional hyperthermia in patients with anal cancer. METHODS: Between 2000 and 2015, a total of 112 consecutive patients with UICC stage I-IV anal cancer received chemoradiotherapy with 5‑fluororuracil and mitomycin C (CRT). In case of insufficient tumor response 4-6 weeks after chemoradiotherapy, patients received an interstitial pulsed-dose-rate brachytherapy boost. Additionally, 50/112 patients received hyperthermia treatments (HCRT). RESULTS: Median follow-up was 41 (2-165) months. After 5 years follow-up, overall (95.8 vs. 74.5%, P = 0.045), disease-free (89.1 vs. 70.4%, P = 0.027), local recurrence-free (97.7 vs. 78.7%, P = 0.006), and colostomy-free survival rates (87.7 vs. 69.0%, P = 0.016) were better for the HCRT group. Disease-specific, regional failure-free, and distant metastasis-free survival rates showed no significant differences. The adjusted hazard ratios for death were 0.25 (95% CI, 0.07 to 0.92; P = 0.036) and for local recurrence 0.14 (95% CI, 0.02 to 1.09; P = 0.06), respectively. Grades 3-4 early toxicities were comparable with the exception of hematotoxicity, which was higher in the HCRT group (66 vs. 43%, P = 0.032). Incidences of late side effects were similar with the exception of a higher telangiectasia rate in the HCRT group (38.0 vs. 16.1%, P = 0.009). CONCLUSION: Additional regional hyperthermia improved overall survival, local control, and colostomy rates. Its potential beneficial role has to be confirmed in a prospective randomized setting. Therefore, the HyCAN trial has already been established by our group and is currently recruiting patients (Clinicaltrials.gov identifier: NCT02369939).
EVALuna2:36451

Chemoradiotherapy with and without deep regional hyperthermia for squamous cell carcinoma of the anus - Ott, O. J.; Schmidt, M.; Semrau, S.; Strnad, Vratislav; Matzel, K. E.; Schneider, I.; Raptis, D.; Uter, Wolfgang; Grützmann, Robert; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Chemo-RT plus induction or consolidation chemotherapy for rectal cancer: a randomised phase 2 trial - Fokas, E.; Allgaeuer, M.; Polat, B.; Klautke, G.; Grabenbauer, G.; Fietkau, Rainer; Kuhnt, T.; Staib, L.; Brunner, T.; Grosu, A. L.; Schmiegel, W.; Jacobasch, L.; et al. (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Choosing a reference phase for a dynamic tumor tracking treatment: A new degree of freedom? - Ziegler, Marc; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2019)
Purpose: With the introduction of dynamic tumor tracking in radiotherapy, it is possible to irradiate moving targets with minimal safety margins. However, most dynamic tumor tracking techniques rely on changing the beam geometry by, for example, adapting the multileaf collimator (MLC) positions or rotating the LINAC head. These changes are relative to a reference position which is determined by a specific breathing phase. Since these changes in the beam path also influence the delivered dose, choosing a different reference position based on a different breathing phase impacts the applied dose to the patient. This work investigates the influence of choosing different reference breathing phases on the dose distribution. Methods: The Vero system tracks the moving target by performing a pan and tilt rotation of the LINAC head. For 13 patients, the target position was extracted from every phase of a four-dimensional computed tomography (4DCT) and the pan and tilt values were determined with respect to three different reference phases. These reference phases were inspiration, expiration, and the midventilation. For all reference phases, a 4D dose calculation was performed on the 4DCT regarding the respective pan and tilt values. Furthermore, the applied dose to the target and surrounding organs at risk was calculated. To accumulate the dose distribution, weights from the actual patient breathing motion were determined. The weights were calculated from the breathing motions from different days to investigate the impact of daily variations in the breathing motion onto the accumulated dose distribution. All obtained values were then compared to the static treatment plan. Results: The mean and maximum doses applied to the target or surrounding organs at risk show no general behavior depending on the different reference phases. Nevertheless, for some patients, large differences (approx. 30%) in the applied dose to certain organs at risk could be observed, whereas the applied dose to the target shows no dependency on the different reference phases. However, the mean target dose is in all cases approx. 1.5% below the reference value from the static treatment plan. Conclusion: Although no general dependency of the applied dose on the selected reference phase could be found, the choice of the reference phase can have great impact on the organ at risk dose for some patients. Thus, the choice of the reference phase used for patient positioning should be considered during treatment planning since it can be seen as a new degree of freedom of a treatment based on tracking.
CRIS-Team Scopus Importer:2019-07-16
Keywords: 4D dose calculation; dynamic tumor tracking; liver cancer; lung cancer

Chromosomal radiosensitivity in oncological and non-oncological patients with rheumatoid arthritis and connective tissue diseases - Rzepka, Dinah; Schenker, Hannah; Geinitz, Hans; Silberberger, Elisabeth; Kaudewitz, Dorothee; Schuster, Barbara; Kuhlmann, Lukas; Schonath, Miriam; Ayala Gaona, Horacio; Aschacher, Bernhard; Fietkau, Rainer; Schett, Georg; et al. (Radiation Oncology, 2023)
Background: The risk of developing late radiotoxicity after radiotherapy in patients with high chromosomal radiosensitivity after radiotherapy could potentially be higher compared to the risk in patients with average radiosensitivity. In case of extremely high radiosensitivity, dose reduction may be appropriate. Some rheumatic diseases (RhD), including connective tissue diseases (CTDs) appear to be associated with higher radiosensitivity. The question arises as to whether patients with rheumatoid arthritis (RA) also generally have a higher radiosensitivity and whether certain parameters could indicate clues to high radiosensitivity in RA patients which would then need to be further assessed before radiotherapy. Methods: Radiosensitivity was determined in 136 oncological patients with RhD, 44 of whom were RA patients, and additionally in 34 non-oncological RA patients by three-colour fluorescence in situ hybridization (FiSH), in which lymphocyte chromosomes isolated from peripheral blood are analysed for their chromosomal aberrations of an unirradiated and an with 2 Gy irradiated blood sample. The chromosomal radiosensitivity was determined by the average number of breaks per metaphase. In addition, correlations between certain RA- or RhD-relevant disease parameters or clinical features such as the disease activity score 28 and radiosensitivity were assessed. Results: Some oncological patients with RhD, especially those with connective tissue diseases have significantly higher radiosensitivity compared with oncology patients without RhD. In contrast, the mean radiosensitivity of the oncological patients with RA and other RhD and the non-oncological RA did not differ. 14 of the 44 examined oncological RA-patients (31.8%) had a high radiosensitivity which is defined as ≥ 0.5 breaks per metaphase. No correlation of laboratory parameters with radiosensitivity could be established. Conclusions: It would be recommended to perform radiosensitivity testing in patients with connective tissue diseases in general. We did not find a higher radiosensitivity in RA patients. In the group of RA patients with an oncological disease, a higher percentage of patients showed higher radiosensitivity, although the average radiosensitivity was not high.
CRIS-Team Scopus Importer:2023-06-16
Keywords: Chromosomal aberrations; Collagen vascular disease; Connective tissue disease; Fluorescence in situ hybridisation; Radiation sensitivity; Radiosensitivity; Radiotherapy; Radiotoxicity; Rheumatism; Rheumatoid arthritis

Classification of primary cerebral lymphoma and glioblastoma featuring dynamic susceptibility contrast and apparent diffusion coefficient - Eisenhut, Felix; Schmidt, Manuel; Putz, Florian; Lettmaier, Sebastian; Fröhlich, Kilian; Arinrad, Soheil; Coras, Roland; Lücking, Hannes; Lang, Stefan; Fietkau, Rainer; Dörfler, Arnd (Brain Sciences, 2020)
This study aimed to differentiate primary central nervous system lymphoma (PCNSL) and glioblastoma (GBM) via multimodal MRI featuring radiomic analysis. MRI data sets of patients with histological proven PCNSL and GBM were analyzed retrospectively. Diffusion-weighted imaging (DWI) and dynamic susceptibility contrast (DSC) perfusion imaging were evaluated to differentiate contrast enhancing intracerebral lesions. Selective (contrast enhanced tumor area with the highest mean cerebral blood volume (CBV) value) and unselective (contouring whole contrast enhanced lesion) Apparent diffusion coefficient (ADC) measurement was performed. By multivariate logistic regression, a multiparametric model was compiled and tested for its diagnostic strength. A total of 74 patients were included in our study. Selective and unselective mean and maximum ADC values, mean and maximum CBV and ratioCBV as quotient of tumor CBV and CBV in contralateral healthy white matter were significantly larger in patients with GBM than PCNSL; minimum CBV was significantly lower in GBM than in PCNSL. The highest AUC for discrimination of PCNSL and GBM was obtained for selective mean and maximum ADC, mean and maximum CBV and ratioCBV. By integrating these five in a multiparametric model 100% of the patients were classified correctly. The combination of perfusion imaging (CBV) and tumor hot-spot selective ADC measurement yields reliable radiological discrimination of PCNSL from GBM with highest accuracy and is readily available in clinical routine.
CRIS-Team Scopus Importer:2020-12-04
Keywords: ADC; DSC; Glioblastoma; MRI; Multimodal; Primary central nervous system lymphoma

Classification of three prognostically different groups of head and neck cancer patients based on their metabolic response to induction chemotherapy (IC-1) - Semrau, Sabine; Schmidt, Daniela; Hecht, Markus; Haderlein, Marlen; Kitzsteiner, Christian; Müller, Susanna; Traxdorf, Maximilian; Agaimy, Abbas; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer (Oral Oncology, 2020)
Objectives: There exist no uniform decision criteria for conservative organ preservation treatments in head and neck cancer patients. Even with 18F-FDG-PET/CT after induction chemotherapy patient selection is challenging. This study correlated metabolic tumor response with treatment types and recurrence patterns. Materials and methods: Decrease in SUVmax in 18F-FDG-PET/CT was measured 21–28 days after IC-1 in 102 patients and correlated to cancer-specific endpoints. Results: Residual SUVmax (resSUVmax) values were uniformly distributed across five cut-off levels (0–0.2 vs. >0.2–0.4 vs. >0.4–0.6 vs. >0.6–0.8 vs. >0.8) containing 20%, 25% 25%, 15% and 15% of patients. Patients were stratified into three response categories according to residual SUVmax (Group A: 0–0.4 = high response Group B: >0.4–0.8 = moderate response, Group C > 0.8 = non-response), 5-year local control rates were 90.5% (Group A) vs. 78.9% (Group B; univariate p = 0.07, multivariate: HR: 3.6, p = 0.03) vs. 49.4% (Group C vs. B; univariate p = 0.04, multivariate: HR 5.5, p < 0.01). After IC-1, Group A received chemoradiotherapy (CRT) only. Group B received surgery plus either (chemo)radiotherapy (B_S + RT/CRT) or chemoradiotherapy (B_CRT), yielding local control rates of 100% and 74.2% (p = 0.11). Group C received surgery plus CRT or CRT alone; both achieved equally poor local control (p = 0.71). Group C had significantly worse distant metastasis-free survival and overall survival than Groups A and B (p < 0.05). Conclusion: Metabolic response after IC-1 differentiates HNC patients into three subgroups predicting local tumor control. Non-response was associated with a poor outcome.
CRIS-Team Scopus Importer:2019-12-03
Keywords: 18F-FDG PET/CT; Chemoradiation; Chemoselection; Head and neck cancer; Hypopharynx; Induction chemotherapy; Larynx; Metabolic response; Resection

Clearance of primary necrotic cells by non-professional phagocytes - Schwegler, Manuela; Wirsing, Anna Maria; Dollinger, Alena J.; Abendroth, Benjamin; Putz, Florian; Fietkau, Rainer; Distel, Luitpold (Biology of the Cell, 2015)
Homotypic internalisation of tumour cells has frequently been observed in tumour tissue sections. Events of non-professional phagocytosis, however, may also occur in normal tissue if the number of dying cells exceeds the phagocytic capacity of professional phagocytes such as macrophages and dendritic cells. The aim of this study was to investigate the molecular background of non-professional phagocytosis of primary necrotic cells by neighbouring tumour cells and normal skin fibroblasts.We demonstrate that homotypic and heterotypic uptake of necrotic cells is a feature common to various cell types. Investigating critical stimuli of necrotic cell clearance we found that non-professional phagocytes require cytoskeleton rearrangement, recognition of phosphatidylserine and GTPase activity of dynamin II, which is normally engaged in endocytosis. Additionally, we have observed an accumulation of adhesion molecule E-cadherin, phosphorylated actin-linker protein ezrin, lysosomal-associated membrane protein 1 and microtubule-associated protein 1 light chain 3 at the site of engulfment. Loss of membrane integrity and an increase in the intracellular level of heat-shock protein 70 in the necrotic cells have also been observed.Our results shed light on the mechanism of necrotic cell removal by tumour cells and normal skin fibroblasts in vitro. It is reasonable to assume that this process has a physiological relevance in inflammation and autoimmune disease in normal tissue as well as in tumours regarding immune cell infiltration. We conclude that necrotic cell clearance by non-professional phagocytes contributes to the phagocytic activity by macrophages and that this process may prevent release of proinflammatory damage-associated molecular pattern molecules.
EVALuna2:18281

Clinical application of breathing-adapted 4D CT: image quality comparison to conventional 4D CT - Werner, René; Szkitsak, Juliane; Madesta, Frederic; Büttgen, Laura; Wimmert, Lukas; Sentker, Thilo; Fietkau, Rainer; Haderlein, Marlen; Bert, Christoph; Gauer, Tobias; Hofmann, Christian (Strahlentherapie und Onkologie, 2023)
Purpose: 4D CT imaging is an integral part of 4D radiotherapy workflows. However, 4D CT data often contain motion artifacts that mitigate treatment planning. Recently, breathing-adapted 4D CT (i4DCT) was introduced into clinical practice, promising artifact reduction in in-silico and phantom studies. Here, we present an image quality comparison study, pooling clinical patient data from two centers: a new i4DCT and a conventional spiral 4D CT patient cohort. Methods: The i4DCT cohort comprises 129 and the conventional spiral 4D CT cohort 417 4D CT data sets of lung and liver tumor patients. All data were acquired for treatment planning. The study consists of three parts: illustration of image quality in selected patients of the two cohorts with similar breathing patterns; an image quality expert rater study; and automated analysis of the artifact frequency. Results: Image data of the patients with similar breathing patterns underline artifact reduction by i4DCT compared to conventional spiral 4D CT. Based on a subgroup of 50 patients with irregular breathing patterns, the rater study reveals a fraction of almost artifact-free scans of 89% for i4DCT and only 25% for conventional 4D CT; the quantitative analysis indicated a reduction of artifact frequency by 31% for i4DCT. Conclusion: The results demonstrate 4D CT image quality improvement for patients with irregular breathing patterns by breathing-adapted 4D CT in this first corresponding clinical data image quality comparison study.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 4D CT; 4D radiotherapy; Image artifacts; Image quality

Clinical Evidence for Thermometric Parameters to Guide Hyperthermia Treatment - Ademaj, Adela; Veltsista, Danai P.; Ghadjar, Pirus; Marder, Dietmar; Oberacker, Eva; Ott, Oliver; Wust, Peter; Puric, Emsad; Hälg, Roger A.; Rogers, Susanne; Bodis, Stephan; Fietkau, Rainer; et al. (Cancers, 2022)
Hyperthermia (HT) is a cancer treatment modality which targets malignant tissues by heating to 40–43 °C. In addition to its direct antitumor effects, HT potently sensitizes the tumor to radiotherapy (RT) and chemotherapy (CT), thereby enabling complete eradication of some tumor entities as shown in randomized clinical trials. Despite the proven efficacy of HT in combination with classic cancer treatments, there are limited international standards for the delivery of HT in the clinical setting. Consequently, there is a large variability in reported data on thermometric parameters, including the temperature obtained from multiple reference points, heating duration, thermal dose, time interval, and sequence between HT and other treatment modalities. Evidence from some clinical trials indicates that thermal dose, which correlates with heating time and temperature achieved, could be used as a predictive marker for treatment efficacy in future studies. Similarly, other thermometric parameters when chosen optimally are associated with increased antitumor efficacy. This review summarizes the existing clinical evidence for the prognostic and predictive role of the most important thermometric parameters to guide the combined treatment of RT and CT with HT. In conclusion, we call for the standardization of thermometric parameters and stress the importance for their validation in future prospective clinical studies.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Clinical evidence; Hyperthermia; Preclinical data; Thermometric parameters

Clinical experience with markerless tumor tracking - Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Clinical implementations of 4D pencil beam scanned particle therapy: Report on the 4D treatment planning workshop 2016 and 2017 - Trnkova, Petra; Knaeusl, Barbara; Actis, Oxana; Bert, Christoph; Biegun, Aleksandra K.; Boehlen, Till T.; Furtado, Hugo; Mcclelland, Jamie; Mori, Shinichiro; Rinaldi, Ilaria; Rucinski, Antoni; Knopf, Antje C. (Physica Medica, 2018)
In 2016 and 2017, the 8th and 9th 4D treatment planning workshop took place in Groningen (the Netherlands) and Vienna (Austria), respectively. This annual workshop brings together international experts to discuss research, advances in clinical implementation as well as problems and challenges in 4D treatment planning, mainly in spot scanned proton therapy. In the last two years several aspects like treatment planning, beam delivery, Monte Carlo simulations, motion modeling and monitoring, QA phantoms as well as 4D imaging were thoroughly discussed. This report provides an overview of discussed topics, recent findings and literature review from the last two years. Its main focus is to highlight translation of 4D research into clinical practice and to discuss remaining challenges and pitfalls that still need to be addressed and to be overcome.
EVALuna2:36473

Clinically Relevant Radiation Exposure Differentially Impacts Forms of Cell Death in Human Cells of the Innate and Adaptive Immune System - Falcke, Sylvia; Rühle, Paul-Friedrich; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (International Journal of Molecular Sciences, 2018)
In cancer treatments, especially high-dose radiotherapy (HDRT) is applied. Patients suffering from chronic inflammatory diseases benefit from low-dose radiation therapy (LDRT), but exposure to very low radiation doses can still steadily increase for diagnostic purposes. Yet, little is known about how radiation impacts on forms of cell death in human immune cells. In this study, the radiosensitivity of human immune cells of the peripheral blood was examined in a dose range from 0.01 to 60 Gy with regard to induction of apoptosis, primary necrosis, and secondary necrosis. Results showed that immune cells differed in their radiosensitivity, with monocytes being the most radioresistant. T cells mainly died by necrosis and were moderately radiosensitive. This was followed by B and natural killer (NK) cells, which died mainly by apoptosis. X-radiation had no impact on cell death in immune cells at very low doses (≤0.1 Gy). Radiation doses of LDRT (0.3⁻0.7 Gy) impacted on the more radiosensitive NK and B cells, which might contribute to attenuation of inflammation. Even single doses applied during RT of tumors did not erase the immune cells completely. These in vitro studies can be considered as the basis to optimize individual radiation therapy schemes in multimodal settings and to define suited time points for further inclusion of immunotherapies.
EVALuna2:36450

Clinically significant CMV (re)activation during or after radiotherapy/chemotherapy of the brain : Correlation with neurological deterioration and improvement upon antiviral treatment - Goerig, Nicole; Semrau, S.; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Dörfler, Arnd; Putz, Florian; Gaipl, Udo; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
For both patients with high-grade gliomas and multiple cerebral metastases, radio(chemo)therapy is the standard therapy. Neurological decline during treatment is rarely attributed to infections of the brain but to tumor progression or side effects of radiotherapy.We present 4 cases of cytomegalovirus (CMV) viremia associated with neurological deterioration, which occurred during or shortly after radiotherapy and/or chemotherapy of the brain (brain metastases 2, high-grade glioma 1, carcinoma infiltrating brain 1). In all cases, neurological decline was sudden and unexpected, and causes such as increased intracranial pressure or tumor progression could be excluded radiologically. Treatment with dexamethasone and mannitol had no or only very short-term effects. General infections were either excluded or receding before the neurological symptoms occurred. All patients presented with decreasing levels of thrombocytes. In all cases, CMV (re)activation could be proven using blood test for CMV-DNA. The anti-CMV-IgG status suggested reactivation rather than a primary infection. One patient died within 72 h of onset of the symptoms (results of CMV tests were received postmortem). Diagnosis of 3 patients allowed successful administration of antiviral treatment, which greatly improved the general and neurological conditions of the patients within 48 h.Neurological deterioration during RT is hardly ever attributed to viral infections. These cases suggest that CMV reactivation and subsequent infection might actually be causative and has to be considered and treated.Further prospective studies verifying and investigating this observation in terms of frequency and clinical relevance seem indicated.
EVALuna2:8302

Clinical outcome of concomitant vs interrupted BRAF inhibitor therapy during radiotherapy in melanoma patients - Hecht, Markus; Meier, Friedegund; Zimmer, Lisa; Polat, Bulent; Loquai, Carmen; Weishaupt, Carsten; Forschner, Andrea; Gutzmer, Ralf; Utikal, Jochen S.; Goldinger, Simone M.; Geier, Michael; Hassel, Jessica C.; et al. (British Journal of Cancer, 2018)
This corrects the article DOI: 10.1038/bjc.2017.85.
EVALuna2:34392

Clinical radiation oncology trials in Germany: Time for clarification and professionalization - Fietkau, Rainer; Wenz, Frederik (Strahlentherapie und Onkologie, 2015)
EVALuna2:18288

Clonogenicity-based radioresistance determines the expression of immune suppressive immune checkpoint molecules after hypofractionated irradiation of MDA-MB-231 triple-negative breast cancer cells - Gehre, Simon; Meyer, Felix; Sengedorj, Azzaya; Grottker, Fridolin; Reichardt, Clara; Alomo, Jannik; Borgmann, Kerstin; Frey, Benjamin; Fietkau, Rainer; Rückert, Michael; Gaipl, Udo (Frontiers in Oncology, 2023)
Only a subset of patients with triple-negative breast cancer (TNBC) benefits from a combination of radio- (RT) and immunotherapy. Therefore, we aimed to examine the impact of radioresistance and brain metastasizing potential on the immunological phenotype of TNBC cells following hypofractionated RT by analyzing cell death, immune checkpoint molecule (ICM) expression and activation of human monocyte-derived dendritic cells (DCs). MDA-MB-231 triple-negative breast cancer tumor cells were used as model system. Apoptosis was the dominant cell death form of brain metastasizing tumor cells, while Hsp70 release was generally significantly increased following RT and went along with necrosis induction. The ICMs PD-L1, PD-L2, HVEM, ICOS-L, CD137-L and OX40-L were found on the tumor cell surfaces and were significantly upregulated by RT with 5 x 5.2 Gy. Strikingly, the expression of immune suppressive ICMs was significantly higher on radioresistant clones compared to their respective non-radioresistant ones. Although hypofractionated RT led to significant cell death induction and release of Hsp70 in all tumor cell lines, human monocyte-derived DCs were not activated after co-incubation with RT-treated tumor cells. We conclude that radioresistance is a potent driver of immune suppressive ICM expression on the surface of TNBC MDA-MB-231 cells. This mechanism is generally known to predominantly influence the effector phase, rather than the priming phase, of anti-tumor immune responses.
CRIS-Team Scopus Importer:2023-05-19
Keywords: breast cancer; dendritic cells; immune checkpoint molecules; radioresistance; radiotherapy; tumor cell death

Combination of growth pattern and tumor regression identifies a high-risk group in neoadjuvant treated rectal cancer patients - Jeßberger, Jonas; Erlenbach-Wuensch, Katharina; Posselt, Rebecca; Haderlein, Marlen; Agaimy, Abbas; Fietkau, Rainer; Hartmann, Arndt; Distel, Luitpold (Journal of Digestive Diseases, 2017)
To analyze the prognostic effect of E-cadherin expression, the growth pattern of the tumor and the regression grade in a rectal cancer cohort treated with neoadjuvant radiochemotherapy (RCT).A total of 223 patients with rectal cancer treated with neoadjuvant RCT followed by surgery were included. Altogether 88 biopsies prior to RCT and 213 tumor resections in an average of 55 days post-RCT were investigated. Protein expression of E-cadherin and tumor growth pattern (solid glandular vs single-cell pattern) was assessed by staining tissue microarrays. The regression grade at the invasion front was determined according to the Dworak scale.There was a significant decrease of E-cadherin expression (P = 0.002) and a significant increased single-cell growth (P < 0.001) at the invasion front in tumor samples after RCT compared with primary biopsies of the tumor. A low E-cadherin expression in the biopsy was related to a longer metastasis-free survival (P = 0.033) and tumor-specific survival (P = 0.030). Post-RCT single-cell growth at the tumor invasion front was a prognostic factor for longer tumor-specific survival (P = 0.021). A combination of growth pattern and the Dworak regression grade was an independent prognostic parameter for tumor-specific survival (P = 0.015).Loss of E-cadherin protein expression in the pretreatment biopsy of rectal cancer is associated with fewer metastases and improved survival. Furthermore, the growth pattern in the post-RCT resection specimen has a prognostic value for survival. A combination of growth pattern and tumor regression score (the RegPat score) showed the highest discriminatory power to identify high-risk patients.
EVALuna2:6858

Combination of ionising radiation with hyperthermia increases the immunogenic potential of B16-F10 melanoma cells in vitro and in vivo - Werthmöller, Nina; Frey, Benjamin; Rueckert, Michael; Lotter, Michael; Fietkau, Rainer; Gaipl, Udo (International Journal of Hyperthermia, 2016)
Mild hyperthermia (HT) (41.5 °C for 30-60 min) has been shown in various cell culture systems, preclinical and clinical models to be a very potent radiosensitiser. Recent research suggests that local HT application in combination with standard tumour therapies such as radiotherapy (RT) and/or chemotherapy may not only improve local tumour control but also lead to systemic and immune mediated anti-tumour responses. Melanoma has been proven to be rather radioresistant and mostly only the addition of immunotherapy is capable of inducing beneficial anti-melanoma responses. This work therefore focuses on whether HT increases the immunogenic potential of B16-F10 mouse melanoma cells in combination with RT. The in vitro experiments revealed that combination of RT with HT resulted in an increased percentage of apoptotic and necrotic melanoma cells and an increased release of the danger signal heat shock protein 70 (Hsp70) and high mobility group box protein 1 (HMGB1). HT alone was also capable of inducing this release. We set up local irradiation and heating procedures of B16-F10 tumour-bearing C57/BL6 mice and revealed that the tumour growth of tumours treated with RT plus HT was significantly retarded compared to tumours treated only with RT. This combined treatment generated a beneficial tumour microenvironment by enhancing the infiltration of CD11c + /MHCII + /CD86+ dendritic cells, CD8+ T cells, and NK cells, and decreasing that of regulatory T cells and myeloid-derived suppressor cells. We conclude that HT in combination with RT has an immune-stimulating potential that might result in anti-tumour immunity.
EVALuna2:18340

Combination of Markerless Surrogates for Motion Estimation in Radiation Therapy - Geimer, Tobias; Unberath, Mathias; Taubmann, Oliver; Bert, Christoph; Maier, Andreas (Computer Assisted Radiology and Surgery (CARS) 2016: Proceedings of the 30th International Congress and Exhibition, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD5.combin_2
Keywords: Motion Modeling; X-ray; Range Imaging; Dimensionality Reduction; Regression

Combinations of radiotherapy with vaccination and immune checkpoint inhibition differently affect primary and abscopal tumor growth and the tumor microenvironment - Rückert, Michael; Deloch, Lisa; Frey, Benjamin; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo (Cancers, 2021)
Radiotherapy (RT) is known to have immune‐modulatory properties. We hypothesized that RT and inactivated whole tumor cell vaccines generated with high hydrostatic pressure (HHP) synergize to retard the tumor growth which can be additionally improved with anti‐PD‐1 treatment. In abscopal tumor models, we injected mice with B16‐F10 melanoma or TS/A mammary tumors. To evaluate the efficiency of RT in combination with HHP vaccines, we locally irradiated only one tumor with 2 × 8 Gy or 3 × 8 Gy. HHP vaccines further retarded the growth of locally irradiated (2 × 8 Gy) tumors. However, HHP vaccination combined with RT failed to induce abscopal anti‐tumor immune responses, namely those to non‐irradiated tumors, and even partly abrogated those which were induced with RT plus anti‐PD‐1. In the latter group, the abscopal effects were accompanied by an elevated infiltration of CD8+ T cells, monocytes/macrophages, and dendritic cells. 3 × 8 Gy failed to induce abscopal effects in association with increased expression of immunosuppressive checkpoint molecules compared to 2 × 8 Gy. We conclude that HHP vaccines induce anti‐tumor effects, but only if the tumor microenvironment was previously modulated by hypofractionated RT with not too many fractions, but failed to improve RT plus anti‐PD‐induced abscopal responses that are characterized by distinct immune alterations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Abscopal effect; High hydrostatic pressure; Immune checkpoint inhibition; Radiotherapy; Tumor microenvironment; Tumor‐infiltrating immune cells; Vaccination

Commercially Available Gene Expression Assays as Predictive Tools for Adjuvant Radiotherapy? A Critical Review - Krug, David; Baumann, René; Budach, Wilfried; Duma, Marciana Nona; Dunst, Jürgen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Hehr, Thomas; Piroth, Marc D.; Sedlmayer, Felix; et al. (Breast Care, 2020)
Background: Gene expression assays are increasingly used for decision-making regarding adjuvant chemotherapy in patients with hormone receptor-positive, HER2-negative breast cancer. There are some clinical situations in which there is also a need for better prognostic and predictive markers to better estimate the amount of benefit from adjuvant radiotherapy. The rising availability of gene expression analyses prompts the question whether their results can also be used to guide clinical decisions regarding adjuvant radiation. Summary: Multiple studies suggest a correlation between results from gene expression assays and locoregional recurrence rates. Only few publications addressed the predictive value of results from gene expression analysis for the role of adjuvant radiotherapy in different settings. Key Messages: To date, the available evidence on the possible predictive value of gene expression assays for radiotherapy does not support their inclusion into the decision-making process for adjuvant radiation. This is due to methodological weaknesses and limitations regarding patient selection, the nonrandomized design of all studies in terms of radiotherapy use, and limited availability of tissue from prospective trials. Thus, utilization of the present knowledge for clinical indication of radiotherapy should be very cautious.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Breast cancer; Gene expression assay; Oncotype DX; Predictive marker; Radiotherapy

Commissioning of an integrated platform for time-resolved treatment delivery in scanned ion beam therapy by means of optical motion monitoring - Fattori, Giovanni; Saito, N.; Seregni, M.; Kaderka, R.; Pella, A.; Constantinescu, A.; Riboldi, Marco; Steidl, P.; Cerveri, P.; Bert, Christoph; Durante, Marco; Baroni, G. (Technology in Cancer Research & Treatment, 2014)
The integrated use of optical technologies for patient monitoring is addressed in the framework of time-resolved treatment delivery for scanned ion beam therapy. A software application has been designed to provide the therapy control system (TCS) with a continuous geometrical feedback by processing the external surrogates tridimensional data, detected in real-time via optical tracking. Conventional procedures for phase-based respiratory phase detection were implemented, as well as the interface to patient specific correlation models, in order to estimate internal tumor motion from surface markers. In this paper, particular attention is dedicated to the quantification of time delays resulting from system integration and its compensation by means of polynomial interpolation in the time domain. Dedicated tests to assess the separate delay contributions due to optical signal processing, digital data transfer to the TCS and passive beam energy modulation actuation have been performed. We report the system technological commissioning activities reporting dose distribution errors in a phantom study, where the treatment of a lung lesion was simulated, with both lateral and range beam position compensation. The zero-delay systems integration with a specific active scanning delivery machine was achieved by tuning the amount of time prediction applied to lateral (14.61 ± 0.98 ms) and depth (34.1 ± 6.29 ms) beam position correction signals, featuring sub-millimeter accuracy in forward estimation. Direct optical target observation and motion phase (MPh) based tumor motion discretization strategies were tested, resulting in 20.3(2.3)% and 21.2(9.3)% median (IQR) percentual relative dose difference with respect to static irradiation, respectively. Results confirm the technical feasibility of the implemented strategy towards 4D treatment delivery, with negligible percentual dose deviations with respect to static irradiation.
EVALuna2:18207

Comparing local and systemic control between partial-and whole-breast radiotherapy in low-risk breast cancer—a meta-analysis of randomized trials - Haussmann, Jan; Budach, Wilfried; Strnad, Vratislav; Corradini, Stefanie; Krug, David; Schmidt, Livia; Tamaskovics, Bálint; Bölke, Edwin; Simiantonakis, Ioannis; Kammers, Kai; Matuschek, Christiane (Cancers, 2021)
Purpose/Objective: The standard treatment for localized low-risk breast cancer is breast-conserving surgery, followed by adjuvant radiotherapy and appropriate systemic therapy. As the majority of local recurrences occur at the site of the primary tumor, numerous trials have investigated partial-breast irradiation (PBI) instead of whole-breast treatment (WBI) using a multitude of irradiation techniques and fractionation regimens. This meta-analysis addresses the impact on disease-specific endpoints, such as local and regional control, as well as disease-free survival of PBI compared to that of WBI in published randomized trials. Material and Methods: We conducted a systematic literature review and searched for randomized trials comparing WBI and PBI in early-stage breast cancer with publication dates after 2009. The meta-analysis was based on the published event rates and the effect sizes for available oncological endpoints of at least two trials reporting on them. We evaluated in-breast tumor recurrences (IBTR), local recurrences at the primary site and elsewhere in the ipsilateral breast, regional recurrences (RR), distant metastasis-free interval (DMFI), disease-free survival (DFS), contralateral breast cancer (CBC), and second primary cancer (SPC). Furthermore, we aimed to assess the impact of different PBI techniques and subgroups on IBTR. We performed all statistical analyses using the inverse variance heterogeneity model to pool effect sizes. Results: For the intended meta-analysis, we identified 13 trials (overall 15,561 patients) randomizing between PBI and WBI. IBTR was significantly higher after PBI (OR = 1.66; CI-95%: 1.07–2.58; p = 0.024) with an absolute difference of 1.35%. We detected significant heterogeneity in the analysis of the PBI technique with intraoperative radiotherapy resulting in higher local relapse rates (OR = 3.67; CI-95%: 2.28–5.90; p < 0.001). Other PBI techniques did not show differences to WBI in IBTR. Both strategies were equally effective at the primary tumor site, but PBI resulted in statistically more IBTRs elsewhere in the ipsilateral breast. IBTRs after WBI were more likely to be located at the primary tumor bed, whereas they appeared equally distributed within the breast after PBI. RR was also more frequent after PBI (OR = 1.75; CI-95%: 1.07–2.88; p < 0.001), yet we did not detect any differences in DMFI (OR = 1.08; CI-95%:0.89–1.30; p = 0.475). DFS was significantly longer in patients treated with WBI (OR = 1.14; CI-95%: 1.02–1.27; p = 0.003). CBC and SPC were not different in the test groups (OR = 0.81; CI-95%: 0.65–1.01; p = 0.067 and OR = 1.09; CI-95%: 0.85–1.40; p = 0.481, respectively). Conclusion: Limiting the target volume to partial-breast radiotherapy appears to be appropriate when selecting patients with a low risk for local and regional recurrences and using a suitable technique.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Breast cancer; Local recurrence; Partial-breast treatment; Radiotherapy

Comparison of different CDK4/6 Kinase Inhibitors (Palbociclib, Ribociclib, Abemaciclib) and their Influence on the Effectiveness of simultaneous Radiation Therapy - Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Comparison of intelligent 4D CT sequence scanning and conventional spiral 4D CT: A first comprehensive phantom study - Werner, René; Szkitsak, Juliane; Sentker, Thilo; Madesta, Frederic; Schwarz, Annette; Fernolendt, Susanne; Vornehm, Marc; Gauer, Tobias; Bert, Christoph; Hofmann, Christian (Physics in Medicine and Biology, 2021)
4D CT imaging is a cornerstone of 4D radiotherapy treatment. Clinical 4D CT data are, however, often affected by severe artifacts. The artifacts are mainly caused by breathing irregularity and retrospective correlation of breathing phase information and acquired projection data, which leads to insufficient projection data coverage to allow for proper reconstruction of 4D CT phase images. The recently introduced 4D CT approach i4DCT (intelligent 4D CT sequence scanning) aims to overcome this problem by breathing signal-driven tube control. The present motion phantom study describes the first in-depth evaluation of i4DCT in a real-world scenario. Twenty-eight 4D CT breathing curves of lung and liver tumor patients with pronounced breathing irregularity were selected to program the motion phantom. For every motion pattern, 4D CT imaging was performed with i4DCT and a conventional spiral 4D CT mode. For qualitative evaluation, the reconstructed 4D CT images were presented to clinical experts, who scored image quality. Further quantitative evaluation was based on established image intensity-based artifact metrics to measure (dis)similarity of neighboring image slices. In addition, beam-on and scan times of the scan modes were analyzed. The expert rating revealed a significantly higher image quality for the i4DCT data. The quantitative evaluation further supported the qualitative: While 20% of the slices of the conventional spiral 4D CT images were found to be artifact-affected, the corresponding fraction was only 4% for i4DCT. The beam-on time (surrogate of imaging dose) did not significantly differ between i4DCT and spiral 4D CT. Overall i4DCT scan times (time between first beam-on and last beam-on event, including scan breaks to compensate for breathing irregularity) were, on average, 53% longer compared to spiral CT. Thus, the results underline that i4DCT significantly improves 4D CT image quality compared to standard spiral CT scanning in the case of breathing irregularity during scanning.
CRIS-Team Scopus Importer:2021-02-12
Keywords: 4D CT; I4DCT; Motion artifacts; Radiotherapy

Comparison of MRI coils and RT-positioning systems for optimal MRI scanning in SRS cases - Mengling, Veit; Perrin, R.; Putz, Florian; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Complete Remission with consecutive Pneumonitis in metastatic Bronchogenic Carcinoma after combination of Radiotherapy and Nivolumab - Immunological Correlate in peripheral Blood - Hecht, Markus; Donaubauer, Anna-Jasmina; Becker, I.; Rutzner, Sandra; Lubgan, Dorota; Lettmaier, S.; Haderlein, Marlen; Wolf, W.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Comprehensive Multimodal Deep Learning Survival Prediction Enabled by a Transformer Architecture: A Multicenter Study in Glioblastoma - Gomaa, Ahmed; Huang, Yixing; Hagag, Amr; Schmitter, Charlotte; Höfler, Daniel; Weissmann, Thomas; Breininger, Katharina; Schmidt, Manuel; Stritzelberger, Jenny; Delev, Daniel; Coras, Roland; Dörfler, Arnd; et al. (Neuro-Oncology Advances, 2024)
Keywords: Survival prediction; deep learning; glioblastoma; MR; prognosis; multimodal data

Cone-beam CT imaging with laterally enlarged field of view based on independently movable source and detector - Karius, Andre; Szkitsak, Juliane; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2023)
Background: CBCT imaging with field of views (FOVs) exceeding the size of scans acquired in the conventional imaging geometry, i.e. with opposing source and detector, is of high clinical importance for many medical fields. A novel approach for enlarged FOV scanning with one full-scan (EnFOV360) or two short-scans (EnFOV180) using an O-arm system arises from non-isocentric imaging based on independent source and detector rotations. Purpose: The presentation, description, and experimental validation of this novel approach and the novel scanning techniques EnFOV360 and EnFOV180 for an O-arm system forms the scope of this work. Methods: We describe the EnFOV360, EnFOV180, and non-isocentric imaging techniques for the acquisition of laterally extended FOVs. For their experimental validation, scans of dedicated quality assurance as well as anthropomorphic phantoms were acquired, with the phantoms being placed both within the tomographic plane and at the longitudinal FOV border with and without lateral shifts from the gantry center. Based on this, geometric accuracy, contrast-noise-ratio (CNR) of different materials, spatial resolution, noise characteristics, as well as CT number profiles were quantitatively assessed. Results were compared to scans performed with the conventional imaging geometry. Results: With EnFOV360 and EnFOV180, we increased the in-plane size of acquired FOVs from 250 × 250 mm2 obtained for the conventional imaging geometry to up to 400 × 400 mm2 for the performed measurements. Geometric accuracy was very high for all scanning techniques with mean values ≤0.21 ± 0.11 mm. CNR and spatial resolution were comparable between isocentric and non-isocentric full-scans as well as EnFOV360, whereas substantial image quality deteriorations in this respect were observed for EnFOV180. Image noise in the isocenter was lowest for conventional full-scans with 13.4 ± 0.2 HU. For laterally shifted phantom positions, noise increased for conventional scans and EnFOV360, whereas noise reductions were observed for EnFOV180. Considering the anthropomorphic phantom scans, both EnFOV360 and EnFOV180 were comparable to conventional full-scans. Conclusion: Both enlarged FOV techniques have high potential for imaging laterally extended FOVs. EnFOV360 revealed an image quality comparable to conventional full-scans in general. EnFOV180 showed an inferior performance particularly regarding CNR and spatial resolution.
CRIS-Team Scopus Importer:2023-05-26
Keywords: cone-beam computed tomography; extended field of view; independent gantry rotations

Consensus in determining the resectability of locally progressed pancreatic ductal adenocarcinoma - results of the Conko-007 multicenter trial - Wittel, U. A.; Lubgan, Dorota; Ghadimi, M.; Belyaev, O.; Uhl, W.; Bechstein, W. O.; Grützmann, Robert; Hohenberger, Werner; Schmid, Andrea; Jacobasch, L.; Croner, R. S.; Reinacher-Schick, A.; et al. (BMC Cancer, 2019)
BACKGROUND: One critical step in the therapy of patients with localized pancreatic cancer is the determination of local resectability. The decision between primary surgery versus upfront local or systemic cancer therapy seems especially to differ between pancreatic cancer centers. In our cohort study, we analyzed the independent judgement of resectability of five experienced high volume pancreatic surgeons in 200 consecutive patients with borderline resectable or locally advanced pancreatic cancer. METHODS: Pretherapeutic CT or MRI scans of 200 consecutive patients with borderline resectable or locally advanced pancreatic cancer were evaluated by 5 independent pancreatic surgeons. Resectability and the degree of abutment of the tumor to the venous and arterial structures adjacent to the pancreas were reported. Interrater reliability and dispersion indices were compared. RESULTS: One hundred ninety-four CT scans and 6 MRI scans were evaluated and all parameters were evaluated by all surgeons in 133 (66.5%) cases. Low agreement was observed for tumor infiltration of venous structures (κ = 0.265 and κ = 0.285) while good agreement was achieved for the abutment of the tumor to arterial structures (interrater reliability celiac trunk κ = 0.708 P < 0.001). In patients with vascular tumor contact indicating locally advanced disease, surgeons highly agreed on unresectability, but in patients with vascular tumor abutment consistent with borderline resectable disease, the judgement of resectability was less uniform (dispersion index locally advanced vs. borderline resectable p < 0.05). CONCLUSION: Excellent agreement between surgeons exists in determining the presence of arterial abutment and locally advanced pancreatic cancer. The determination of resectability in borderline resectable patients is influenced by additional subjective factors. TRIAL REGISTRATION: EudraCT:2009-014476-21 (2013-02-22) and NCT01827553 (2013-04-09).
CRIS-Team Scopus Importer:2019-10-29
Keywords: Borderline resectable; Determination of resectability; Locally advanced; Pancreatic cancer; Prospective randomized multicenter trial

Correction to expert consensus on re-irradiation for recurrent glioma - Krauze, Andra V.; Attia, Albert; Braunstein, Steve; Chan, Michael; Combs, Stephanie E.; Fietkau, Rainer; Fiveash, John; Flickinger, John; Grosu, Anca-Ligia; Howard, Steven; Nieder, Carsten; Niyazi, Maximilian; et al. (Radiation Oncology, 2018)
In the original publication [1] two author names were missing the middle names. The corrected versions can be found in this Erratum.
EVALuna2:32860

Correction to: Recent advances in Surface Guided Radiation Therapy (Radiation Oncology, (2020), 15, 1, (187), 10.1186/s13014-020-01629-w) - Freislederer, P.; Kügele, M.; Öllers, M.; Swinnen, A.; Sauer, Tim-Oliver; Bert, Christoph; Giantsoudi, D.; Corradini, S.; Batista, V. (Radiation Oncology, 2020)
Following publication of the original article [1], the authors identified an error in the order of Figs. 2 and 3. The correct representation of figures is provided below. The original article [1] has been corrected.
CRIS-Team Scopus Importer:2020-10-30

Corrigendum: Low Dose Radiation Therapy Induces Long-Lasting Reduction of Pain and Immune Modulations in the Peripheral Blood - Interim Analysis of the IMMO-LDRT01 Trial(Front. Immunol., (2021), 12, (740742), 10.3389/fimmu.2021.740742) - Donaubauer, Anna-Jasmina; Becker, Ina; Weissmann, Thomas; Fröhlich, Birgitta; Munoz, Luis Enrique; Gryc, Thomas; Denzler, Manuel; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2022)
In the original article, there was an error. The mistake is found in the sentence “While the total number of leukocytes remained unchanged in the peripheral blood, LDRT induced a slight reduction of eosinophils, basophils and plasmacytoid dendritic cells and an increase of B cells.” in the abstract of the article.
CRIS-Team Scopus Importer:2022-03-04
Keywords: chronic degenerative and inflammatory diseases; immune status; immunophenotyping; low dose radiation therapy (LDRT); subjective pain level; x-rays

Corrigendum to “European Association of Urology Guidelines on Muscle-invasive and Metastatic Bladder Cancer: Summary of the 2023 Guidelines” [Eur. Urol. 85 (2024) 17–31, (S0302283823030737), (10.1016/j.eururo.2023.08.016)] - Alfred Witjes, J.; Bruins, Harman Max; Carrión, Albert; Cathomas, Richard; Compérat, Eva; Efstathiou, Jason A.; Fietkau, Rainer; Gakis, Georgios; Lorch, Anja; Martini, Alberto; Mertens, Laura S.; Meijer, Richard P.; et al. (European Urology, 2024)
The authors regret the oversight in the initially published version of this article, where the name of Prof. Paramananthan Mariappan, along with his affiliation to the Edinburgh Bladder Cancer Surgery (EBCS), Western General Hospital, at The University of Edinburgh, Edinburgh, United Kingdom, was inadvertently omitted from the author list. This has now been updated. The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2024-05-24

Creation of an Electro-magnetic Heat Simulation for Planning Hyperthermia Treatments for Mice - Kahlert, B.; Bert, Christoph; Rückert, Michael; Hensel, Bernhard; Root, Konstantin; Vossiek, Martin; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Critical role of spatial interaction between CD8? and Foxp3? cells in human gastric cancer: the distance matters - Feichtenbeiner, Anita; Haas, Matthias; Büttner, Maike; Grabenbauer, Gerhard; Fietkau, Rainer; Distel, Luitpold (Cancer Immunology Immunotherapy, 2014)
In various cancer types, an abundance of FoxP3(+) regulatory T cells (Treg) has been associated with an unfavorable outcome. Yet, the role of Treg on cancer immunity has been shown to be complex. In single cell marker technique, other tumor-infiltrating lymphocytes (TILs) such as cytotoxic CD8(+) T cells (CTL) also influenced prognosis. This study for the first time investigates the concurrent spatial distribution pattern of CD8(+) and FoxP3(+) TILs and their prognostic impact in human gastric cancer.Tumor tissue microarrays of 50 patients with surgically treated adenocarcinoma of the cardia were studied. An immunohistochemical double staining of CD8(+) and FoxP3(+) TILs was performed. Cell counts and cell-to-cell distances in tumor epithelium and stroma were evaluated with image-processing software. Metastasis-free survival, no-evidence-of-disease survival, and overall survival were investigated (mean follow-up time 6.9 years).High intraepithelial infiltration of CD8(+) and FoxP3(+) TIL was associated with the improved 10-year metastasis-free survival (83 vs. 54%, p = 0.04 and 85 vs. 59%, p = 0.09, respectively). Considering cell-to-cell distance and comparing patients with functional (30-110 ?m) versus nonfunctional distances of CD8(+) and FoxP3(+) TILs, 10-year survival rates differed between 89 and 55% (p = 0.009), respectively.Prognostic influence of tumor-infiltrating immune cells in gastric cancer critically depends on their cell-to-cell distance. FoxP3(+) TILs must be located within a distance between 30 and 110 ?m of CD8(+) T cells to positively impact on prognosis.
EVALuna2:18176

Current controversies in radiotherapy for breast cancer - Krug, David; Baumann, Rene; Budach, Wilfried; Dunst, Juergen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Piroth, Marc D.; Sautter-Bihl, Marie-Luise; Sedlmayer, Felix; Souchon, Rainer; et al. (Radiation Oncology, 2017)
Multimodal treatment approaches have substantially improved the outcome of breast cancer patients in the last decades. Radiotherapy is an integral component of multimodal treatment concepts used in curative and palliative intention in numerous clinical situations from precursor lesions such as ductal carcinoma in situ (DCIS) to advanced breast cancer. This review addresses current controversial topics in radiotherapy with special consideration of DCIS, accelerated partial breast irradiation (APBI) and regional nodal irradiation (RNI) and provides an update on the clinical practice guidelines of the Breast Cancer Expert Panel of the German Society of Radiation Oncology (DEGRO).
EVALuna2:32913

Cytotoxic and immunogenic Potential of Iron (II) Clathrochelates and Irradiation on Lung Cancer Cell Lines - Becker, Ina; Denzler, M.; Heim, Lisanne; Klemt, Insa; Voloshin, Y. Z.; Selin, R.; Mokhir, Andriy; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Cytotoxic effect of Efavirenz in BxPC-3 pancreatic cancer cells is based on oxidative stress and is synergistic with ionizing radiation - Hecht, Markus; Harrer, Thomas; Koeber, Verena; Sarpong, Eric Opoku; Moser, Fabian; Fiebig, Nora; Schwegler, Manuela; Stürzl, Michael; Fietkau, Rainer; Distel, Luitpold (Oncology Letters, 2018)
The non-nucleoside reverse transcriptase inhibitor (NNRTI) Efavirenz is frequently used in human immunodeficiency virus treatment, but also efficient against cancer in mouse models. Its radiosensitizing effect makes it a promising drug for combination with radiotherapy. The efficacy of Efavirenz combined with irradiation was assessed with immunostaining of DNA-damage markers and colony formation assays in BxPC-3 pancreatic cancer cells. Gene expression and protein phosphorylation of the Efavirenz-sensitive BxPC-3 cells was compared to the resistant primary fibroblasts SBL-5. Oxidative stress, mitochondrial damage and cell death were studied with live-cell microscopy and flow cytometry. Combined Efavirenz and radiation significantly increased the number of γH2AX and phospho-ataxia telangiectasia mutated foci. Efavirenz and ionizing radiation had a synergistic effect using the clonogenic survival assay. Efavirenz selectively induced cell death in the BxPC-3 cells. The differing gene expression of cell cycle and apoptotic regulator genes in both cell cultures after Efavirenz treatment match with this selective effect against cancer cells. In the phosphoprotein array, an early phosphorylation of extracellular signal-related kinase 1/2 and p38 mitogen-activated protein kinase was notably detected in the cancer cells. The phosphorylation of AKT decreased in the cancer cells whereas it increased in the fibroblasts. Oxidative stress and mitochondrial membrane depolarization appeared in the cancer cells immediately after Efavirenz treatment, but not in the fibroblasts. Efavirenz has an anti-cancer effect against pancreatic cancer mainly by the induction of oxidative stress. The antitumor potential of Efavirenz and radiotherapy are additive.
EVALuna2:36443

Decoupling Respiratory and Angular Variation in Rotational X-ray Scans Using a Prior Bilinear Model - Geimer, Tobias; Keall, Paul; Breininger, Katharina; Caillet, Vincent; Dunbar, Michelle; Bert, Christoph; Maier, Andreas (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2019)
Data-driven respiratory signal extraction from rotational X-ray scans is a challenge as angular effects overlap with respiration-induced change in the scene. In this paper, we use the linearity of the X-ray transform to propose a bilinear model based on a prior 4D scan to separate angular and respiratory variation. The bilinear estimation process is supported by a B-spline interpolation using prior knowledge about the trajectory angle. Consequently, extraction of respiratory features simplifies to a linear problem. Though the need for a prior 4D CT seems steep, our proposed use-case of driving a respiratory motion model in radiation therapy usually meets this requirement. We evaluate on DRRs of 5 patient 4D CTs in a leave-one-phase-out manner and achieve a mean estimation error of 3.01% in the gray values for unseen viewing angles. We further demonstrate suitability of the extracted weights to drive a motion model for treatments with a continuously rotating gantry.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Bilinear model; Feature extraction; Motion model; Respiratory signal; X-ray projection

Deep Learning and Registration-Based Mapping for Analyzing the Distribution of Nodal Metastases in Head and Neck Cancer Cohorts: Informing Optimal Radiotherapy Target Volume Design - Weissmann, Thomas; Mansoorian, Sina; May, Matthias; Lettmaier, Sebastian; Höfler, Daniel; Deloch, Lisa; Speer, Stefan; Balk, Matthias; Frey, Benjamin; Gaipl, Udo; Bert, Christoph; Distel, Luitpold; et al. (Cancers, 2023)
We introduce a deep-learning- and a registration-based method for automatically analyzing the spatial distribution of nodal metastases (LNs) in head and neck (H/N) cancer cohorts to inform radiotherapy (RT) target volume design. The two methods are evaluated in a cohort of 193 H/N patients/planning CTs with a total of 449 LNs. In the deep learning method, a previously developed nnU-Net 3D/2D ensemble model is used to autosegment 20 H/N levels, with each LN subsequently being algorithmically assigned to the closest-level autosegmentation. In the nonrigid-registration-based mapping method, LNs are mapped into a calculated template CT representing the cohort-average patient anatomy, and kernel density estimation is employed to estimate the underlying average 3D-LN probability distribution allowing for analysis and visualization without prespecified level definitions. Multireader assessment by three radio-oncologists with majority voting was used to evaluate the deep learning method and obtain the ground-truth distribution. For the mapping technique, the proportion of LNs predicted by the 3D probability distribution for each level was calculated and compared to the deep learning and ground-truth distributions. As determined by a multireader review with majority voting, the deep learning method correctly categorized all 449 LNs to their respective levels. Level 2 showed the highest LN involvement (59.0%). The level involvement predicted by the mapping technique was consistent with the ground-truth distribution (p for difference 0.915). Application of the proposed methods to multicenter cohorts with selected H/N tumor subtypes for informing optimal RT target volume design is promising.<br
Keywords: deep learning; artificial intelligence; nodal metastasis; head and neck cancer; radiotherapy; target volume design; atlas; mapping; autosegmentation; lymph node level classification

Deep Learning-assisted delineation of brain metastases: a workflow focusing on AI-expert interaction - Putz, Florian; Szkitsak, Juliane; Grigo, Johanna; Masitho, Siti; Weissmann, Thomas; Frey, Benjamin; Gaipl, Udo; Fietkau, Rainer; Bert, Christoph; Huang, Yixing (Radiotherapy and Oncology, 2023)

Deep Learning-based Auto-contouring of Lymph Node Levels in Head and Neck Area - Weissmann, Thomas; Huang, Yixing; Sommer, Phillip; Roesch, Johannes; Mansoorian, Sina; Ayala, H.; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Haderlein, Marlen; Hecht, Markus; Speer, Stefan; Schweizer, Claudia; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Deep Learning-based automatic longitudinal volumetric Analysis in Acoustic Neuroma - Putz, Florian; Chen, Hui-fen; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Schmidt, M.; Semrau, Sabine; Lettmaier, Sebastian; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Deep Learning based fully automated volumetric Progression Assessment in Patients with Brain Metastases after stereotactic Radiotherapy - Putz, Florian; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Sommer, P.; Fischer, S.; Srinivasan, A.; Frey, Benjamin; Gaipl, Udo; Schmidt, M.; Semrau, Sabine; Bert, Christoph; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Deep Learning based Prediction of Glioma Growth by using "Growing Neural Cellular Automata" - Huang, Yixing; Maier, Andreas; Sommer, Philipp; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Deep Learning basierte Vorhersage von Gliomwachstum mittels Growing Neural Cellular Automata - Huang, Yixing; Maier, Andreas; Sommer, Phillip; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Strahlentherapie und Onkologie, 2022)
Keywords: deep learning; cellular automata; tumor growth

Deep learning for automatic head and neck lymph node level delineation provides expert-level accuracy - Weissmann, Thomas; Huang, Yixing; Fischer, Stefan; Roesch, Johannes; Mansoorian, Sina; Gaona, Horacio Ayala; Gostian, Antoniu-Oreste; Hecht, Markus; Lettmaier, Sebastian; Deloch, Lisa; Frey, Benjamin; Gaipl, Udo; et al. (Frontiers in Oncology, 2023)
Background: Deep learning-based head and neck lymph node level (HN_LNL) autodelineation is of high relevance to radiotherapy research and clinical treatment planning but still underinvestigated in academic literature. In particular, there is no publicly available open-source solution for large-scale autosegmentation of HN_LNL in the research setting. Methods: An expert-delineated cohort of 35 planning CTs was used for training of an nnU-net 3D-fullres/2D-ensemble model for autosegmentation of 20 different HN_LNL. A second cohort acquired at the same institution later in time served as the test set (n = 20). In a completely blinded evaluation, 3 clinical experts rated the quality of deep learning autosegmentations in a head-to-head comparison with expert-created contours. For a subgroup of 10 cases, intraobserver variability was compared to the average deep learning autosegmentation accuracy on the original and recontoured set of expert segmentations. A postprocessing step to adjust craniocaudal boundaries of level autosegmentations to the CT slice plane was introduced and the effect of autocontour consistency with CT slice plane orientation on geometric accuracy and expert rating was investigated. Results: Blinded expert ratings for deep learning segmentations and expert-created contours were not significantly different. Deep learning segmentations with slice plane adjustment were rated numerically higher (mean, 81.0 vs. 79.6, p = 0.185) and deep learning segmentations without slice plane adjustment were rated numerically lower (77.2 vs. 79.6, p = 0.167) than manually drawn contours. In a head-to-head comparison, deep learning segmentations with CT slice plane adjustment were rated significantly better than deep learning contours without slice plane adjustment (81.0 vs. 77.2, p = 0.004). Geometric accuracy of deep learning segmentations was not different from intraobserver variability (mean Dice per level, 0.76 vs. 0.77, p = 0.307). Clinical significance of contour consistency with CT slice plane orientation was not represented by geometric accuracy metrics (volumetric Dice, 0.78 vs. 0.78, p = 0.703). Conclusions: We show that a nnU-net 3D-fullres/2D-ensemble model can be used for highly accurate autodelineation of HN_LNL using only a limited training dataset that is ideally suited for large-scale standardized autodelineation of HN_LNL in the research setting. Geometric accuracy metrics are only an imperfect surrogate for blinded expert rating. <
Keywords: Deep learning; lymph node level; segmentation

Deep learning for brain metastasis detection and segmentation in longitudinal MRI data - Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Fietkau, Rainer; et al. (Medical Physics, 2022)
Keywords: Deep learning; brain metastasis; MRI; loss function; sensitivity specificity

Deep learning for perspective deformation correction in X-ray imaging - Huang, Yixing; Maier, Andreas; Fan, Fuxin; Kreher, Björn W.; Huang, Xiaolin; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Radiotherapy and Oncology, 2023)
Keywords: Deep learning; perspective deformation; X-ray imaging

Definition of a new blood cell count score for early survival prediction for non-small cell lung cancer patients treated with atezolizumab: Integrated analysis of four multicenter clinical trials - Zhou, Jian-Guo; Wong, Ada Hang-Heng; Wang, Haitao; Jin, Su-Han; Tan, Fangya; Chen, Yu-Zhong; He, Si-Si; Shen, Gang; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Carr, Shamus R.; et al. (Frontiers in Immunology, 2022)
Importance: Blood cell count test (BCT) is a robust method that provides direct quantification of various types of immune cells to reveal the immune landscape to predict atezolizumab treatment outcomes for clinicians to decide the next phase of treatment. Objective: This study aims to define a new BCTscore model to predict atezolizumab treatment benefits in non-small lung cell cancer (NSCLC) patients. Design, Setting, and Participants: This study analyzed four international, multicenter clinical trials (OAK, BIRCH, POPLAR, and FIR trials) to conduct post-hoc analyses of NSCLC patients undergoing atezolizumab (anti–PD-L1) single-agent treatment (n = 1,479) or docetaxel single-agent treatment (n = 707). BCT was conducted at three time points: pre-treatment (T1), the first day of treatment cycle 3 (T2), and first day of treatment cycle 5 (T3). Univariate and multivariate Cox regression analyses were conducted to identify early BCT biomarkers to predict atezolizumab treatment outcomes in NSCLC patients. Main Outcomes and Measures: Overall survival (OS) was used as the primary end point, whereas progression-free survival (PFS) according to Response Evaluation Criteria in Solid Tumors (RECIST), clinical benefit (CB), and objective response rate (ORR) were used as secondary end points. Results: The BCT biomarkers of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) at time point T3 and neutrophil-to-monocyte ratio (NMR) at time point T2 with absolute cutoff values of NLR_T3 = 5, PLR_T3 = 180, and NMR_T2 = 6 were identified as strong predictive biomarkers for atezolizumab (Ate)–treated NSCLC patients in comparison with docetaxel (Dtx)–treated patients regarding OS (BCTscore low risk: HR Ate vs. Dtx = 1.54 (95% CI: 1.04–2.27), P = 0.031; high risk: HR Ate vs. Dtx = 0.84 (95% CI: 0.62–1.12), P = 0.235). The identified BCTscore model showed better OS AUC in the OAK (AUC12month = 0.696), BIRCH (AUC12month = 0.672) and POPLAR+FIR studies (AUC12month = 0.727) than that of each of the three single BCT biomarkers. Conclusion and Relevance: The BCTscore model is a valid predictive and prognostic biomarker for early survival prediction in atezolizumab-treated NSCLC patients.
CRIS-Team Scopus Importer:2022-09-30
Keywords: atezolizumab; biomarker; blood cell count; clinical trial; NSCLC

Definitive chemoradiotherapy of locally advanced head and neck cancer in combination with immune checkpoint inhibition-new concepts required - Hecht, Markus; Fietkau, Rainer; Gaipl, Udo (Strahlentherapie und Onkologie, 2021)
CRIS-Team WoS Importer:2021-12-17

Defnitive Radiochemotherapy with and without regional Deep Hyperthermia of Bladder Carcinoma in elderly Patients - Siavooshhaghighi, H.; Putz, Florian; Gryc, Thomas; Mansoorian, S.; Filimonova, Irina; Fietkau, Rainer; Ott, Oliver (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

DEGRO guideline for personalized radiotherapy of brain metastases and leptomeningeal carcinomatosis in patients with breast cancer - Borm, Kai J.; Behzadi, Sophie T.; Hörner-Rieber, Juliane; Krug, David; Baumann, Rene; Corradini, Stefanie; Duma, Marciana Nona; Dunst, Jürgen; Fastner, Gerd; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; et al. (Strahlentherapie und Onkologie, 2024)
Purpose: The aim of this review was to evaluate the existing evidence for radiotherapy for brain metastases in breast cancer patients and provide recommendations for the use of radiotherapy for brain metastases and leptomeningeal carcinomatosis. Materials and methods: For the current review, a PubMed search was conducted including articles from 01/1985 to 05/2023. The search was performed using the following terms: (brain metastases OR leptomeningeal carcinomatosis) AND (breast cancer OR breast) AND (radiotherapy OR ablative radiotherapy OR radiosurgery OR stereotactic OR radiation). Conclusion and recommendations: Despite the fact that the biological subtype of breast cancer influences both the occurrence and relapse patterns of breast cancer brain metastases (BCBM), for most scenarios, no specific recommendations regarding radiotherapy can be made based on the existing evidence. For a limited number of BCBM (1–4), stereotactic radiosurgery (SRS) or fractionated stereotactic radiotherapy (SRT) is generally recommended irrespective of molecular subtype and concurrent/planned systemic therapy. In patients with 5–10 oligo-brain metastases, these techniques can also be conditionally recommended. For multiple, especially symptomatic BCBM, whole-brain radiotherapy (WBRT), if possible with hippocampal sparing, is recommended. In cases of multiple asymptomatic BCBM (≥ 5), if SRS/SRT is not feasible or in disseminated brain metastases (> 10), postponing WBRT with early reassessment and reevaluation of local treatment options (8–12 weeks) may be discussed if a HER2/Neu-targeting systemic therapy with significant response rates in the central nervous system (CNS) is being used. In symptomatic leptomeningeal carcinomatosis, local radiotherapy (WBRT or local spinal irradiation) should be performed in addition to systemic therapy. In patients with disseminated leptomeningeal carcinomatosis in good clinical condition and with only limited or stable extra-CNS disease, craniospinal irradiation (CSI) may be considered. Data regarding the toxicity of combining systemic therapies with cranial and spinal radiotherapy are sparse. Therefore, no clear recommendations can be given, and each case should be discussed individually in an interdisciplinary setting.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Craniospinal irradiation; Molecular profile; Neurocognitive side effects; Radiosurgery; Whole-brain radiotherapy

DEGRO practical guideline for central nervous system radiation necrosis part 1: classification and a multistep approach for diagnosis - Bernhardt, Denise; Koenig, Laila; Grosu, Anca-Ligia; Wiestler, Benedikt; Rieken, Stefan; Wick, Wolfgang; Gempt, Jens; Krieg, Sandro M.; Schmidt-Graf, Friederike; Sahm, Felix; Meyer, Bernhard; Krause, Bernd J.; et al. (Strahlentherapie und Onkologie, 2022)
Purpose: The Working Group for Neuro-Oncology of the German Society for Radiation Oncology in cooperation with members of the Neuro-Oncology Working Group of the German Cancer Society aimed to define a practical guideline for the diagnosis and treatment of radiation-induced necrosis (RN) of the central nervous system (CNS). Methods: Panel members of the DEGRO working group invited experts, participated in a series of conferences, supplemented their clinical experience, performed a literature review, and formulated recommendations for medical treatment of RN including bevacizumab in clinical routine. Conclusion: Diagnosis and treatment of RN requires multidisciplinary structures of care and defined processes. Diagnosis has to be made on an interdisciplinary level with the joint knowledge of a neuroradiologist, radiation oncologist, neurosurgeon, neuropathologist, and neuro-oncologist. A multistep approach as an opportunity to review as many characteristics as possible to improve diagnostic confidence is recommended. Additional information about radiotherapy (RT) techniques is crucial for the diagnosis of RN. Misdiagnosis of untreated and progressive RN can lead to severe neurological deficits. In this practice guideline, we propose a detailed nomenclature of treatment-related changes and a multistep approach for their diagnosis.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Bevacizumab; Brain metastases; Glioma; Radioation necrosis; Reirradiation

DEGRO practical guideline for central nervous system radiation necrosis part 2: treatment - Bernhardt, Denise; Koenig, Laila; Grosu, Anca-Ligia; Rieken, Stefan; Krieg, Sandro M.; Wick, Wolfgang; Wiestler, Benedikt; Schmidt-Graf, Friederike; Sahm, Felix; Gempt, Jens; Meyer, Bernhard; Krause, Bernd J.; et al. (Strahlentherapie und Onkologie, 2022)
Purpose The Working Group for Neurooncology of the German Society for Radiation Oncology (DEGRO; AG NRO) in cooperation with members of the Neurooncological Working Group of the German Cancer Society (DKG-NOA) aimed to define a practical guideline for the diagnosis and treatment of radiation-induced necrosis (RN) of the central nervous system (CNS). Methods Panel members of the DEGRO working group invited experts, participated in a series of conferences, supplemented their clinical experience, performed a literature review, and formulated recommendations for medical treatment of RN, including bevacizumab, in clinical routine. Conclusion Diagnosis and treatment of RN requires multidisciplinary structures of care and defined processes. Diagnosis has to be made on an interdisciplinary level with the joint knowledge of a neuroradiologist, radiation oncologist, neurosurgeon, neuropathologist, and neurooncologist. If the diagnosis of blood-brain barrier disruptions (BBD) or RN is likely, treatment should be initiated depending on the symptoms, location, and dynamic of the lesion. Multiple treatment options are available (such as observation, surgery, steroids, and bevacizumab) and the optimal approach should be discussed in an interdisciplinary setting. In this practice guideline, we offer detailed treatment strategies for various scenarios.
CRIS-Team WoS Importer:2022-09-09

DEGRO practical guideline for partial-breast irradiation - Strnad, Vratislav; Krug, D.; Sedlmayer, F.; Piroth, M. D.; Budach, W.; Baumann, R.; Feyer, P.; Duma, M. N.; Haase, W.; Harms, W.; Hehr, T.; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2020)
Purpose: This consensus statement from the Breast Cancer Working Group of the German Society for Radiation Oncology (DEGRO) aims to define practical guidelines for accelerated partial-breast irradiation (APBI). Methods: Recent recommendations for relevant aspects of APBI were summarized and a panel of experts reviewed all the relevant literature. Panel members of the DEGRO experts participated in a series of conferences, supplemented their clinical experience, performed a literature review, and formulated recommendations for implementing APBI in clinical routine, focusing on patient selection, target definition, and treatment technique. Results: Appropriate patient selection, target definition for different APBI techniques, and basic rules for appropriate APBI techniques for clinical routine outside of clinical trials are described. Detailed recommendations for APBI in daily practice, including dose constraints, are given. Conclusion: Guidelines are mandatory to assure optimal results of APBI using different techniques.
CRIS-Team Scopus Importer:2020-05-12
Keywords: APBI; Breast cancer; Early breast cancer; Guideline; Partial breast irradiation

DEGRO practical guidelines for radiotherapy of breast cancer IV: radiotherapy following mastectomy for invasive breast cancer - Wenz, Frederik; Sperk, Elena; Budach, Wilfried; Dunst, Juergen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Piroth, Marc D.; Sautter-Bihl, Marie-Luise; Sedlmayer, Felix; Souchon, Rainer; et al. (Strahlentherapie und Onkologie, 2014)
Since the last recommendations from the Breast Cancer Expert Panel of the German Society for Radiation Oncology (DEGRO) in 2008, evidence for the effectiveness of postmastectomy radiotherapy (PMRT) has grown. This growth is based on updates of the national S3 and international guidelines, as well as on new data and meta-analyses. New aspects were considered when updating the DEGRO recommendations.The authors performed a comprehensive survey of the literature. Data from recently published (meta-)analyses, randomized clinical trials and international cancer societies' guidelines yielding new aspects compared to 2008 were reviewed and discussed. New aspects were included in the current guidelines. Specific issues relating to particular PMRT constellations, such as the presence of risk factors (lymphovascular invasion, blood vessel invasion, positive lymph node ratio >20 %, resection margins <3 mm, G3 grading, young age/premenopausal status, extracapsular invasion, negative hormone receptor status, invasive lobular cancer, size >2 cm or a combination of >= 2 risk factors) and 1-3 positive lymph nodes are emphasized.The evidence for improved overall survival and local control following PMRT for T4 tumors, positive resection margins, >3 positive lymph nodes and in T3 N0 patients with risk factors such as lymphovascular invasion, G3 grading, close margins, and young age has increased. Recently identified risk factors such as invasive lobular subtype and negative hormone receptor status were included. For patients with 1-3 positive lymph nodes, the recommendation for PMRT has reached the 1a level of evidence.PMRT is mandatory in patients with T4 tumors and/or positive lymph nodes and/or positive resection margins. PMRT should be strongly considered in patients with T3 N0 tumors and risk factors, particularly when two or more risk factors are present.
EVALuna2:18211

DEGRO practical guidelines for radiotherapy of breast cancer VI: therapy of locoregional breast cancer recurrences - Harms, Wolfgang; Budach, W.; Dunst, J.; Feyer, P.; Fietkau, Rainer; Haase, W.; Krug, D.; Piroth, M. D.; Sautter-Bihl, Marie-Luise; Sedlmayer, F.; Souchon, R.; Wenz, F.; et al. (Strahlentherapie und Onkologie, 2016)
To update the practical guidelines for radiotherapy of patients with locoregional breast cancer recurrences based on the current German interdisciplinary S3 guidelines 2012.A comprehensive survey of the literature using the search phrases "locoregional breast cancer recurrence", "chest wall recurrence", "local recurrence", "regional recurrence", and "breast cancer" was performed, using the limits "clinical trials", "randomized trials", "meta-analysis", "systematic review", and "guidelines".Patients with isolated in-breast or regional breast cancer recurrences should be treated with curative intent. Mastectomy is the standard of care for patients with ipsilateral breast tumor recurrence. In a subset of patients, a second breast conservation followed by partial breast irradiation (PBI) is an appropriate alternative to mastectomy. If a second breast conservation is performed, additional irradiation should be mandatory. The largest reirradiation experience base exists for multicatheter brachytherapy; however, prospective clinical trials are needed to clearly define selection criteria, long-term local control, and toxicity. Following primary mastectomy, patients with resectable locoregional breast cancer recurrences should receive multimodality therapy including systemic therapy, surgery, and radiation +/- hyperthermia. This approach results in high local control rates and long-term survival is achieved in a subset of patients. In radiation-naive patients with unresectable locoregional recurrences, radiation therapy is mandatory. In previously irradiated patients with a high risk of a second local recurrence after surgical resection or in patients with unresectable recurrences, reirradiation should be strongly considered. Indication and dose concepts depend on the time interval to first radiotherapy, presence of late radiation effects, and concurrent or sequential systemic treatment. Combination with hyperthermia can further improve tumor control. In patients with isolated axillary or supraclavicular recurrence, durable disease control is best achieved with multimodality therapy including surgery and radiotherapy. Radiation therapy significantly improves local control and should be applied whenever feasible.
EVALuna2:18354

DEGRO practical guidelines for radiotherapy of breast cancer V: Therapy for locally advanced and inflammatory breast cancer, as well as local therapy in cases with synchronous distant metastases - Budach, Wilfried; Matuschek, Christiane; Bölke, Edwin; Dunst, Jürgen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Piroth, Marc D.; Sautter-Bihl, Marie-Luise; Sedlmayer, Felix; Souchon, Rainer; et al. (Strahlentherapie und Onkologie, 2015)
The purpose of this work is to give practical guidelines for radiotherapy of locally advanced, inflammatory and metastatic breast cancer at first presentation.A comprehensive survey of the literature using the search phrases "locally advanced breast cancer", "inflammatory breast cancer", "breast cancer and synchronous metastases", "de novo stage IV and breast cancer", and "metastatic breast cancer" and "at first presentation" restricted to "clinical trials", "randomized trials", "meta-analysis", "systematic review", and "guideline" was performed and supplemented by using references of the respective publications. Based on the German interdisciplinary S3 guidelines, updated in 2012, this publication addresses indications, sequence to other therapies, target volumes, dose, and fractionation of radiotherapy.International and national guidelines are in agreement that locally advanced, at least if regarded primarily unresectable and inflammatory breast cancer should receive neoadjuvant systemic therapy first, followed by surgery and radiotherapy. If surgery is not amenable after systemic therapy, radiotherapy is the treatment of choice followed by surgery, if possible. Surgery and radiotherapy should be administered independent of response to neoadjuvant systemic treatment. In patients with a de novo diagnosis of breast cancer with synchronous distant metastases, surgery and radiotherapy result in considerably better locoregional tumor control. An improvement in survival has not been consistently proven, but may exist in subgroups of patients.Radiotherapy is an important part in the treatment of locally advanced and inflammatory breast cancer that should be given to all patients regardless to the intensity and effect of neoadjuvant systemic treatment and the extent of surgery. Locoregional radiotherapy in patients with primarily distant metastatic disease should be prescribed on an individual basis.
EVALuna2:18270

DEGRO practical guidelines for radiotherapy of non-malignant disorders: Part I: physical principles, radiobiological mechanisms, and radiogenic risk - Reichl, Berthold; Block, Andreas; Schäfer, Ulrich; Bert, Christoph; Müller, Reinhold; Jung, Horst; Rödel, Franz (Strahlentherapie und Onkologie, 2015)
Synopsis of the introductory paragraph of the DEGRO consensus S2e-guideline recommendations for the radiotherapy of benign disorders, including physical principles, radiobiological mechanisms, and radiogenic risk.This work is based on the S2e-guideline recommendations published November 14, 2013. The basic principles of radiation physics and treatment delivery, evaluation of putative underlying radiobiological mechanisms, and the assessment of genetic and cancer risk following low-dose irradiation will be presented.Radiation therapy of benign diseases is performed according to similar physical principles as those governing treatment of malignant diseases in radiation oncology, using the same techniques and workflows. These methods comprise usage of orthovoltage X-ray units, gamma irradiation facilities, linear accelerators (LINACs), and brachytherapy. Experimental in vitro and in vivo models recently confirmed the clinically observed anti-inflammatory effect of low-dose X-irradiation, and implicated a multitude of radiobiological mechanisms. These include modulation of different immunological pathways, as well as the activities of endothelial cells, mono- and polymorphonuclear leukocytes, and macrophages. The use of effective dose for radiogenic risk assessment and the corresponding tumor incidence rate of 5.5%/Sv are currently controversially discussed. Some authors argue that the risk of radiation-induced cancers should be estimated on the basis of epidemiological data. However, such data are rarely available at present and associated with high variability.Current radiobiological studies clearly demonstrate a therapeutic effectiveness of radiation therapy used to treat benign diseases and implicate various molecular mechanisms. Radiogenic risks should be taken into account when applying radiation treatment for benign diseases.
EVALuna2:18282

DEGRO practical guidelines: radiotherapy of breast cancer III–radiotherapy of the lymphatic pathways - Sautter-Bihl, M. -L.; Sedlmayer, F.; Budach, W.; Dunst, Juergen; Feyer, P.; Sauer, Rolf; Fussl, C.; Haase, W.; Harms, W.; Piroth, M. D.; Souchon, R.; Wenz, F.; et al. (Strahlentherapie und Onkologie, 2014)
The purpose of this work is to update the practical guidelines for adjuvant radiotherapy of the regional lymphatics of breast cancer published in 2008 by the breast cancer expert panel of the German Society of Radiation Oncology (DEGRO).A comprehensive survey of the literature concerning regional nodal irradiation (RNI) was performed using the following search terms: "breast cancer", "radiotherapy", "regional node irradiation". Recent randomized trials were analyzed for outcome as well as for differences in target definition. Field arrangements in the different studies were reproduced and superimposed on CT slices with individually contoured node areas. Moreover, data from recently published meta-analyses and guidelines of international breast cancer societies, yielding new aspects compared to 2008, provided the basis for defining recommendations according to the criteria of evidence-based medicine. In addition to the more general statements of the German interdisciplinary S3 guidelines updated in 2012, this paper addresses indications, targeting, and techniques of radiotherapy of the lymphatic pathways after surgery for breast cancer.International guidelines reveal substantial differences regarding indications for RNI. Patients with 1-3 positive nodes seem to profit from RNI compared to whole breast (WBI) or chest wall irradiation alone, both with regard to locoregional control and disease-free survival. Irradiation of the regional lymphatics including axillary, supraclavicular, and internal mammary nodes provided a small but significant survival benefit in recent randomized trials and one meta-analysis. Lymph node irradiation yields comparable tumor control in comparison to axillary lymph node dissection (ALND), while reducing the rate of lymph edema. Data concerning the impact of 1-2 macroscopically affected sentinel node (SN) or microscopic metastases on prognosis are conflicting.Recent data suggest that the current restrictive use of RNI should be scrutinized because the risk-benefit relationship appears to shift towards an improvement of outcome.
EVALuna2:18194

DEGRO practical guidelines: radiotherapy of breast cancer II: radiotherapy of non-invasive neoplasia of the breast - Souchon, R.; Sautter-Bihl, M-L; Sedlmayer, Felix; Budach, W.; Dunst, Juergen; Feyer, P.; Fietkau, Rainer; Haase, W.; Harms, W.; Wenz, F.; Sauer, Rolf (Strahlentherapie und Onkologie, 2014)
To complement and update the 2007 practice guidelines of the breast cancer expert panel of the German Society of Radiation Oncology (DEGRO) for radiotherapy (RT) of breast cancer. Owing to its growing clinical relevance, in the current version, a separate paper is dedicated to non-invasive proliferating epithelial neoplasia of the breast. In addition to the more general statements of the German interdisciplinary S3 guidelines, this paper is especially focused on indication and technique of RT in addition to breast conserving surgery.The DEGRO expert panel performed a comprehensive survey of the literature comprising recently published data from clinical controlled trials, systematic reviews as well as meta-analyses, referring to the criteria of evidence-based medicine yielding new aspects compared to 2005 and 2007. The literature search encompassed the period 2008 to September 2012 using databases of PubMed and Guidelines International Network (G-I-N). Search terms were "non invasive breast cancer", "ductal carcinoma in situ, "dcis", "borderline breast lesions", "lobular neoplasia", "radiotherapy" and "radiation therapy". In addition to the more general statements of the German interdisciplinary S3 guidelines, this paper is especially focused on indications of RT and decision making of non-invasive neoplasia of the breast after surgery, especially ductal carcinoma in situ.Among different non-invasive neoplasia of the breast only the subgroup of pure ductal carcinoma in situ (DCIS; synonym ductal intraepithelial neoplasia, DIN) is considered for further recurrence risk reduction treatment modalities after complete excision of DCIS, particularly RT following breast conserving surgery (BCS), in order to avoid a mastectomy. About half of recurrences are invasive cancers. Up to 50 % of all recurrences require salvage mastectomy. Randomized clinical trials and a huge number of mostly observational studies have unanimously demonstrated that RT significantly reduces recurrence risks of ipsilateral DCIS as well as invasive breast cancer independent of patient age in all subgroups. The recommended total dose is 50 Gy administered as whole breast irradiation (WBI) in single fractions of 1.8 or 2.0 Gy given on 5 days weekly. Retrospective data indicate a possible beneficial effect of an additional tumor bed boost for younger patients. Prospective clinical trials of different dose-volume concepts (hypofractionation, accelerated partial breast irradiation, boost radiotherapy) are still ongoing.Postoperative radiotherapy permits breast conservation for the majority of women by halving local recurrence as well as reducing progression rates into invasive cancer. New data confirmed this effect in all patient subsets-even in low risk subgroups (LoE 1a).
EVALuna2:18150

Dense feature-based motion estimation in MV fluoroscopy during dynamic tumor tracking treatment: preliminary study on reduced aperture and partial occlusion handling - Serpa, Marco; Bert, Christoph (Physics in Medicine and Biology, 2020)
Quality assurance solutions to complement available motion compensation technologies are central for their safe routine implementation and success of treatment. This work presents a dense feature-based method for soft-tissue tumor motion estimation in megavoltage (MV) beam's-eye-view (BEV) projections for potential intra-treatment monitoring during dynamic tumor tracking (DTT). Dense sampling and matching principles were employed to track a gridded set of features landmarks (FLs) in MV-BEV projections and estimate tumor motion, capable to overcome reduced field aperture and partial occlusion challenges. The algorithm's performance was evaluated by retrospectively applying it to fluoroscopic sequences acquired at similar to 2 frames s(-1) (fps) for a dynamic phantom and two lung stereotactic body radiation therapy (SBRT) patients treated with DTT on the Vero SBRT system. First, a field-specific train image is initialized by sampling the tumor region at, S, pixel intervals on a grid using a representative frame from a stream of query frames. Sampled FLs are locally characterized in the form of descriptor vectors and geometric attributes representing the target. For motion tracking, subsequent query frames are likewise sampled, corresponding feature descriptors determined, and then patch-wise matched to the training set based on their descriptors and geometric relationships. FLs with high correspondence are pruned and used to estimate tumor displacement. In scenarios of partial occlusions, position is estimated from the set of correctly (visible) FLs on past observations. Reconstructed trajectories were benchmarked against ground-truth manual tracking using the root-mean-square (RMS) as a metric of positional accuracy. A total of 19 fluoroscopy sequences were analyzed. This included scenarios of field aperture obstruction during three-dimensional conformal, as well as step-and-shoot intensity modulated radiotherapy (IMRT) delivery assisted with DTT. The algorithm resolved target motion satisfactorily. The RMS was <1.2 mm and <1.8 mm for the phantom and the clinical dataset, respectively. Dense tracking showed promising results to overcome localization challenges at the field penumbra and partial obstruction by multi-leaf collimator (MLC). Motion retrieval was possible in similar to 66% of the control points studied. In addition to MLC obstruction, changes in the external/internal breathing dynamics and baseline drifts were a major source of estimation bias. Dense feature-based tracking is a viable alternative. The algorithm is rotation-/scale-invariant and robust to photometric changes. Tracking multiple features may help overcome partial occlusion challenges by the MLC. This in turn opens up new possibilities for motion detection and intra-treatment monitoring during IMRT and potentially VMAT.
CRIS-Team WoS Importer:2021-01-15

Detailed in vitro analyses of the impact of multimodal cancer therapy with hyperthermia and radiotherapy on the immune phenotype of human glioblastoma cells - Stoll, Eileen; Hader, Michael; Rückert, Michael; Weissmann, Thomas; Lettmaier, Sebastian; Putz, Florian; Hecht, Markus; Fietkau, Rainer; Rosin, Andreas; Frey, Benjamin; Gaipl, Udo (International Journal of Hyperthermia, 2022)
Purpose Improvements of heat-delivery systems have led to hyperthermia (HT) being increasingly recognized as an adjunct treatment modality also for brain tumors. But how HT affects the immune phenotype of glioblastoma cells is only scarcely known. Materials and Methods We therefore investigated the effect of in vitro HT, radiotherapy (RT), and the combination of both (RHT) on cell death modalities, immune checkpoint molecule (ICM) expression and release of the danger signal HSP70 of two human glioblastoma cell lines (U87 and U251) by using multicolor flow cytometry and ELISA. Hyperthermia was performed once or twice for 60-minute sessions reaching temperatures of 39 degrees C, 41 degrees C, and 44 degrees C, respectively. RT was administered with 5 x 2 Gy. Results A hyperthermia chamber for cell culture t-flasks regulating the temperature via a contact sensor was developed. While the glioblastoma cells were rather radioresistant, particularly in U251 cells, the combination of RT with HT significantly increased the percentage of apoptotic and necrotic cells for all temperatures examined and for both, single and double HT application. In line with that, an increased release of HSP 70 was seen only in U251 cells, mainly following treatment with HT at temperatures of 44 degrees C alone or in combination with RT. In contrast, immune suppressive (PD-L1, PD-L2, HVEM) and immune stimulatory (ICOS-L, CD137-L and Ox40-L) ICMs were significantly increased mostly on U87 cells, and particularly after RHT with 41 degrees C. Conclusions Individual assessment of the glioblastoma immune cell phenotype with regard to the planned treatment is mandatory to optimize multimodal radio-immunotherapy protocols including HT.
CRIS-Team WoS Importer:2022-06-24
Keywords: Hyperthermia; radiotherapy; immune checkpoint molecules; danger signals; glioblastoma; multimodal cancer therapy

Detection of Human Cytomegalovirus (HCMV) in monocytic Cells of the peripheral Blood in Glioma Patients during Radio (chemo) Therapy - Bäumler, Monika; Becker, Ina; Frey, Benjamin; Pohn, Anna; Winkler, Thomas; Fietkau, Rainer; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Deterioration of Health-Related Quality of Life Scores under Treatment Predicts Longer Survival - Jörling, Maike; Rutzner, Sandra; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (BioMed Research International, 2020)
Objectives: Baseline health-related quality of life (HRQoL) scores predict survival, which has already been demonstrated in various studies. However, we were interested in whether changes in baseline scores during treatment are also significant predictors of survival. Methods and Materials: We analysed the data of 400 consecutive cancer patients receiving radiochemotherapy. Leading diagnoses were head and neck cancer (34.5%), rectal cancer (24.5%), and lung cancer (13%). HRQoL was studied at baseline, six weeks after therapy and after each completed year after the start of therapy until drop out of the study using the EORTC QLQ-C30 questionnaire. The change score was calculated as the baseline score subtracted from the score after therapy. Statistics included Kaplan-Meier estimates and Cox regression. Results: High global health status (p = 0.005) and low pain scores (p = 0.040) at baseline were related to favourable overall survival. Change scores of role functioning (p = 0.027), global health status (p < 0.018), and pain (p < 0.001) were predictive of overall survival. Pain was the superior predictor of survival (p = 0.001) among all variables and QoL scores studied by multivariate analysis. A deterioration in pain was associated with a 2.8 times higher chance of survival (HR 0.36). Conclusions: Deterioration of HRQoL baseline pain score by cancer treatment is a favourable and superior prognostic factor for survival.
CRIS-Team Scopus Importer:2020-09-11

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

Deutsche Gesellschaft für Radioonkologie (DEGRO) mahnt stationäre strahlentherapeutische Versorgung an: Stellungnahme zu einem Urteil des Bundessozialgerichts vom 29.08.2023 zur Erbringung stationärer strahlentherapeutischer Leistungen - Fietkau, Rainer; Höller, Ulrike; van Kampen, Michael; Krause, Mechthild; Petersen, Cordula; Vordermark, Dirk (Strahlentherapie und Onkologie, 2023)
CRIS-Team Scopus Importer:2023-11-03

Development and clinical implementation of a digital system for risk assessments for radiation therapy - Kornek, Dominik; Menichelli, David; Leske, Jörg; Hofmann, Michael; Antkiewicz, David; Brandt, Tobias; Ott, Oliver; Lotter, Michael; Lang-Welzenbach, Marga; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2023)
Before introducing new treatment techniques, an investigation of hazards due to unintentional radiation exposures is a reasonable activity for proactively increasing patient safety. As dedicated software is scarce, we developed a tool for risk assessment to design a quality management program based on best practice methods, i.e., process mapping, failure modes and effects analysis and fault tree analysis. Implemented as a web database application, a single dataset was used to describe the treatment process and its failure modes. The design of the system and dataset allowed failure modes to be represented both visually as fault trees and in a tabular form. Following the commissioning of the software for our department, previously conducted risk assessments were migrated to the new system after being fully re-assessed which revealed a shift in risk priorities. Furthermore, a weighting factor was investigated to bring risk levels of the migrated assessments into perspective. The compensation did not affect high priorities but did re-prioritize in the midrange of the ranking. We conclude that the tool is suitable to conduct multiple risk assessments and concomitantly keep track of the overall quality management activities.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Failure modes and effects analysis (FMEA); Fault tree analysis (FTA); Process throughput; Radiation therapy; Risk analysis; Risk-based quality management

Development of Admission to Radiotherapy Departments in Germany: A Population-Based Study of DRG Data - Medenwald, D.; Fietkau, Rainer; Klautke, G.; Wuerschmidt, F.; Vordermark, D. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Development of a flow cytometry-based whole-blood prognostic immune signature in metastatic cancer patients treated with immune checkpoint inhibitors - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Eckstein, Markus; Sun, R.; Ma, H.; Schubert, Philipp; Schweizer, C.; Fietkau, Rainer; Deutsch, E.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Development of a Modular Assay for Detailed Immunophenotyping of Peripheral Human Whole Blood Samples by Multicolor Flow Cytometry - Rühle, Paul-Friedrich; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (International Journal of Molecular Sciences, 2016)
The monitoring of immune cells gained great significance in prognosis and prediction of therapy responses. For analyzing blood samples, the multicolor flow cytometry has become the method of choice as it combines high specificity on single cell level with multiple parameters and high throughput. Here, we present a modular assay for the detailed immunophenotyping of blood (DIoB) that was optimized for an easy and direct application in whole blood samples. The DIoB assay characterizes 34 immune cell subsets that circulate the peripheral blood including all major immune cells such as T cells, B cells, natural killer (NK) cells, monocytes, dendritic cells (DCs), neutrophils, eosinophils, and basophils. In addition, it evaluates their functional state and a few non-leukocytes that also have been associated with the outcome of cancer therapy. This DIoB assay allows a longitudinal and close-meshed monitoring of a detailed immune status in patients requiring only 2.0 mL of peripheral blood and it is not restricted to peripheral blood mononuclear cells. It is currently applied for the immune monitoring of patients with glioblastoma multiforme (IMMO-GLIO-01 trial, NCT02022384), pancreatic cancer (CONKO-007 trial, NCT01827553), and head and neck cancer (DIREKHT trial, NCT02528955) and might pave the way for immune biomarker identification for prediction and prognosis of therapy outcome.
EVALuna2:18363

Development of an immunological prognostic Signature in metastatic Patients who were treated with Immune Checkpoint Inhibitors as part of the ST-ICI Study - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Sun, R.; Ma, H.; Fietkau, Rainer; Deutsch, E.; Hecht, Markus; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Development of curative therapies for Ewing sarcomas by interdisciplinary cooperative groups in Europe - Boelling, T.; Braun-Munzinger, G.; Burdach, S.; Calaminus, G.; Craft, A.; Delattre, O.; Deley, M. -C. L.; Dirksen, U.; Dockhorn-Dworniczak, B.; Dunst, J.; Engel, S.; Faldum, Andreas; et al. (Klinische Pädiatrie, 2015)
Curative therapies for Ewing sarcoma have been developed within cooperative groups. Consecutive clinical trials have systematically assessed the impact and timing of local therapy and the activity of cytotoxic drugs and their combinations. They have led to an increase of long-term disease-free survival to around 70% in patients with localized disease. Translational research in ES remains an area in which interdisciplinary and international cooperation is essential for future progress. This article reviews current state-of-the art therapy, with a focus on trials performed in Europe, and summarizes novel strategies to further advance both the cure rates and quality of survival.
EVALuna2:18280

Development of Recurrence and Long-term Toxicity in Prostate Carcinoma after combined Radiotherapy with interstitial Brachytherapy Boost - Schweizer, Claudia; Strnad, Vratislav; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Die Bedeutung der Strahlentherapie im Kontext immer effektiver werdender Systemtherapien beim metastasierten NSCLC – Hinweise aus einer Rezidivanalyse nach Immuncheckpointinhibitoren - Schubert, Philipp; Fietkau, Rainer; Hecht, Markus (Strahlentherapie und Onkologie, 2021)
CRIS-Team Scopus Importer:2021-12-03

Differences and Similarities in the Pattern of Early Metabolic and Morphologic Response after Induction Chemo-Immunotherapy versus Induction Chemotherapy Alone in Locally Advanced Squamous Cell Head and Neck Cancer - Beck, Michael; Semrau, Sabine; Haderlein, Marlen; Gostian, Antoniu-Oreste; Hartwich, Julius; Müller, Sarina Katrin; Kallies, Annett; Geppert, Carol-Immanuel; Schonath, Miriam; Putz, Florian; Gaipl, Udo; Frey, Benjamin; et al. (Cancers, 2022)
Simple Summary There are differences and similarities when assessing the short-term therapeutic response of chemotherapy and chemotherapy plus immunotherapy using imaging techniques, which may be necessary to make treatment decisions in malignant head and neck tumors. After both chemo- and immunochemotherapy, remission becomes measurable in cross-sectional and metabolic diagnostics after only one cycle of therapy, with (18)FDG-PET/CT predicting complete remission of tumor cells in a representative biopsy better than MRI/CT examination in both therapeutic modalities. While complete tumor remission is highly likely (88%) after immunochemotherapy in tumors with low residual activity (<= 40% of initial SUV), this is less common after chemotherapy alone (65%). In metabolic nonresponse with more than 80% residual activity, the probability of complete remission nevertheless is low after chemotherapy alone (6%). After immunochemotherapy, these false nonresponders are common (35%), requiring additional diagnostics by deep biopsy. Cases of pseudoprogression with an increase of SUVmax of more than 125% of the baseline were not observed. Background: In head and neck cancer patients, parameters of metabolic and morphologic response of the tumor to single-cycle induction chemotherapy (IC) with docetaxel, cis- or carboplatin are used to decide the further course of treatment. This study investigated the effect of adding a double immune checkpoint blockade (DICB) of tremelimumab and durvalumab to IC on imaging parameters and their significance with regard to tumor cell remission. Methods: Response variables of 53 patients treated with IC+DICB (ICIT) were compared with those of 104 who received IC alone. Three weeks after one cycle, pathologic and, in some cases, clinical and endoscopic primary tumor responses were evaluated and correlated with a change in 18F-FDG PET and CT/MRI-based maximum-standardized uptake values (SUVmax) before (SUV(max)pre), after treatment (SUV(max)post) and residually (resSUV(max) in % of SUV(max)pre), and in maximum tumor diameter (D-max) before (D(max)pre) and after treatment (D(max)post) and residually (resD). Results: Reduction of SUVmax and D-max occurred in both groups; values were SUV(max)pre: 14.4, SUV(max)post: 6.6, D(max)pre: 30 mm and D(max)post: 23 mm for ICIT versus SUV(max)pre: 16.5, SUV(max)post: 6.4, D(max)pre: 21 mm, and D(max)post: 16 mm for IC alone (all p < 0.05). ResSUV(max) was the best predictor of complete response (IC: AUC: 0.77; ICIT: AUC: 0.76). Metabolic responders with resSUV(max) <= 40% tended to have a higher rate of CR to ICIT (88%; n = 15/17) than to IC (65%; n = 30/46; p = 0.11). Of the metabolic nonresponders (resSUV(max) > 80%), 33% (n = 5/15) achieved a clinical CR to ICIT versus 6% (n = 1/15) to IC (p = 0.01). Conclusions: ICIT and IC quickly induce a response and 18F-FDG PET is the more accurate modality for identifying complete remission. The rate of discrepant response, i.e., pCR with metabolic nonresponse after ICIT was >30%.
CRIS-Team WoS Importer:2022-10-21

Differences in and Prognostic Value of Quality of Life Data in Rectal Cancer Patients with and without Distant Metastases - Frank, Fabian; Hecht, Markus; Loy, Florian; Rutzner, Sandra; Fietkau, Rainer; Distel, Luitpold (Healthcare, 2021)
(1) Background: Individualization of treatment is a major challenge in oncology and requires a variety of predictive and prognostic parameters. In addition to tumor biology analyses, baseline health-related quality of life might be a valid tool to predict overall survival. This study was conducted to evaluate the prognostic relevance of baseline quality of life data in patients with rectal cancer. In this context, differences between patients with and without distant metastases were of particular interest. (2) Methods: Our cohort included 258 patients with rectal cancer treated in the radiotherapy department of the University Hospital Erlangen. Patients completed the European Organisation for Research and Treatment of Cancer (EORTC) core quality of life questionnaire (QLQ C30) and colorectal cancer questionnaire (CR38). Clinical and survival data were provided by the Giessener Tumor Documentation System (GTDS) of the Comprehensive Cancer Center Erlangen-EMN (CCC, Friedrich-Alexander University Erlangen-Nuremberg, Erlangen, Germany). Statistical analyses were performed using Kaplan-Meier analyses and univariate and multivariate Cox regression. (3) Results: A cohort of 258 patients with rectal adenocarcinoma was analyzed including 50 patients (19.4%) with metastatic disease. No differences were observed between patients with and without distant metastases in most areas of quality of life studied, with the exception of physical function, loss of appetite, chemotherapy side effects and weight loss. Gender, baseline physical function, sexual function, diarrhea, and weight loss over time had a prognostic value in the entire cohort. Appetite loss was an additional prognostic parameter in patients with distant metastases. (4) Conclusions: The quality of life of patients with metastatic disease differed only slightly from non-metastatic patients. Health-related quality of life data provide prognostic information for patients with rectal cancer.
CRIS-Team WoS Importer:2021-02-12

Differences in Dose Coverage and Uniformity in Fractionated High-Dose-Rate Interstitial Breast Brachytherapy Based on EMT Measurements - Kellermeier, Markus; Hofmann, B.; Strnad, Vratislav; Bert, Christoph (2016)
EVALuna2:33047

Differences of the immune phenotype of breast cancer cells after ex vivo hyperthermia by warm-water or microwave radiation in a closed-loop system alone or in combination with radiotherapy - Hader, Michael; Savcigil, Deniz Pinar; Rosin, Andreas; Ponfick, Philipp; Gekle, Stephan; Wadepohl, Martin; Bekeschus, Sander; Fietkau, Rainer; Frey, Benjamin; Schlücker, Eberhard; Gaipl, Udo (Cancers, 2020)
The treatment of breast cancer by radiotherapy can be complemented by hyperthermia. Little is known about how the immune phenotype of tumor cells is changed thereby, also in terms of a dependence on the heating method. We developed a sterile closed-loop system, using either a warm-water bath or a microwave at 2.45 GHz to examine the impact of ex vivo hyperthermia on cell death, the release of HSP70, and the expression of immune checkpoint molecules (ICMs) on MCF-7 and MDA-MB-231 breast cancer cells by multicolor flow cytometry and ELISA. Heating was performed between 39 and 44◦C. Numerical process simulations identified temperature distributions. Additionally, irradiation with 2 × 5 Gy or 5 × 2 Gy was applied. We observed a release of HSP70 after hyperthermia at all examined temperatures and independently of the heating method, but microwave heating was more effective in cell killing, and microwave heating with and without radiotherapy increased subsequent HSP70 concentrations. Adding hyperthermia to radiotherapy, dynamically or individually, affected the expression of the ICM PD-L1, PD-L2, HVEM, ICOS-L, CD137-L, OX40-L, CD27-L, and EGFR on breast cancer cells. Well-characterized pre-clinical heating systems are mandatory to screen the immune phenotype of tumor cells in clinically relevant settings to define immune matrices for therapy adaption.
CRIS-Team Scopus Importer:2020-05-08
Keywords: Breast cancer; Danger signals; EGFR; Hyperthermia; Immune checkpoint molecules; Immunogenic cancer cell phenotype; Immunotherapy; Microwave-heating; Multimodal tumor therapies; Radiotherapy

Different Impacts of DNA-PK and mTOR Kinase Inhibitors in Combination with Ionizing Radiation on HNSCC and Normal Tissue Cells - Klieber, Nina; Hildebrand, Laura; Faulhaber, Eva-Maria; Symank, Julia-Alice; Häck, Nicole; Härtl, Annamaria; Fietkau, Rainer; Distel, Luitpold (Cells, 2024)
Despite substantial advancements in understanding the pathomechanisms of head and neck squamous cell carcinoma (HNSCC), effective therapy remains challenging. The application of kinase inhibitors (KIs) in HNSCC, specifically mTOR and DNA-PK inhibitors, can increase radiosensitivity and therefore presents a promising strategy when used simultaneously with ionizing radiation (IR) in cancer treatment. Our study focused on the selective DNA-PK-inhibitor AZD7648; the selective mTOR-inhibitor Sapanisertib; and CC-115, a dual inhibitor targeting both mTOR and DNA-PK. The impact of these KIs on HNSCC and normal tissue cells was assessed using various analytical methods including cell death studies, cell cycle analysis, real-time microscopy, colony-forming assays and immunohistochemical staining for γH2AX and downstream mTOR protein p-S6. We detected a strong inhibition of IR-induced DNA double-strand break (DSB) repair, particularly in AZD7648-treated HNSCC, whereas normal tissue cells repaired DNA DSB more efficiently. Additionally, AZD7648 + IR treatment showed a synergistic decline in cell proliferation and clonogenicity, along with an elevated G2/M arrest and cell death in the majority of HNSCC cell lines. CC-115 + IR treatment led to an elevation in G2/M arrest, increased cell death, and a synergistic reduction in cell proliferation, though the effect was notably lower compared to the AZD7648 + IR- treated group. Sapanisertib led to a high cellular toxicity in both HNSCC and normal tissue cells, even in non-irradiated cells. Regarding cell proliferation and the induction of apoptosis and necrosis, Sapanisertib + IR was beneficial only in HPV+ HNSCC. Overall, this study highlights the potential of AZD7648 as a radiosensitizing agent in advanced-stage HPV-positive and negative HNSCC, offering a promising therapeutic strategy. However, the dual mTOR/DNA-PK-I CC-115 did not provide a distinct advantage over the use of selective KIs in our investigations, suggesting limited benefits for its application in KI + IR therapy. Notably, the selective mTOR-inhibitor Sapanisertib was only beneficial in HPV+ HNSCC and should not be applied in HPV− cases.
CRIS-Team Scopus Importer:2024-03-08
Keywords: AZD7648; cancer; CC-115; cell lines; DNA-PK; head and neck cancer; HNC: head and neck squamous cell carcinoma; HNSCC; ionizing radiation; kinase inhibitor; mTOR; PI3K; Sapanisertib; targeted therapy

Distinct increased outliers among 136 rectal cancer patients assessed by ?H2AX - Kroeber, Jana; Wenger, Barbara; Schwegler, Manuela; Daniel, Christoph; Schmidt, Manfred; Djuzenova, Cholpon S.; Polat, Buelent; Flentje, Michael; Fietkau, Rainer; Distel, Luitpold (Radiation Oncology, 2015)
In recent years attention has focused on ?H2AX as a very sensitive double strand break indicator. It has been suggested that ?H2AX might be able to predict individual radiosensitivity. Our aim was to study the induction and repair of DNA double strand breaks labelled by ?H2AX in a large cohort.In a prospective study lymphocytes of 136 rectal cancer (RC) patients and 59 healthy individuals were ex vivo irradiated (IR) and initial DNA damage was compared to remaining DNA damage after 2 Gy and 24 hours repair time and preexisting DNA damage in unirradiated lymphocytes. Lymphocytes were immunostained with anti-?H2AX antibodies and microscopic images with an extended depth of field were acquired. ?H2AX foci counting was performed using a semi-automatic image analysis software.Distinct increased values of preexisting and remaining ?H2AX foci in the group of RC patients were found compared to the healthy individuals. Additionally there are clear differences within the groups and there are outliers in about 12% of the RC patients after ex vivo IR.The ?H2AX assay has the capability to identify a group of outliers which are most probably patients with increased radiosensitivity having the highest risk of suffering radiotherapy-related late sequelae.
EVALuna2:18245

Distinguishing Progression and Radionecrosis in large progressive Brain Metastases after Stereotaxy by integrating Radiomics, Dose Radiomics and clinical Risk Factors - Sommer, Phillip; Huang, Yixing; Srinivasan, Aishwarya Lakshmi; Fischer, Stefan; Dörfler, Arnd; Schmidt, Manuel; Frey, Benjamin; Maier, Andreas; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Does a dedicated Radiation Planning MRI add Value to cranial Stereotaxy? - Mengling, Veit; Putz, Florian; Perrin, R.; Fietkau, Rainer; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Does the Planning MRI for cranial Stereotaxy have to be performed in the Irradiation Position? An Examination of Brain Tissue Deformations between MR Imaging in diagnostic and Radiation Positions - Putz, Florian; Mengling, Veit; Masitho, Siti; Perrin, R.; Roesch, Johannes; Weissmann, T.; Bäuerle, Tobias; Fietkau, Rainer; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Dose calculation and verification of the Vero gimbal tracking treatment delivery - Prasetio, Heru; Wölfelschneider, Jens; Ziegler, Marc; Serpa, M.; Witulla, Barbara; Bert, Christoph (Physics in Medicine and Biology, 2018)
The Vero linear accelerator delivers dynamic tumor tracking (DTT) treatment using a gimbal motion. However, the availability of treatment planning systems (TPS) to simulate DTT is limited. This study aims to implement and verify the gimbal tracking beam geometry in the dose calculation. Gimbal tracking was implemented by rotating the reference CT outside the TPS according to the ring, gantry, and gimbal tracking position obtained from the tracking log file. The dose was calculated using these rotated CTs. The geometric accuracy was verified by comparing calculated and measured film response using a ball bearing phantom. The dose was verified by comparing calculated 2D dose distributions and film measurements in a ball bearing and a homogeneous phantom using a gamma criterion of 2%/2 mm. The effect of implementing the gimbal tracking beam geometry in a 3D patient data dose calculation was evaluated using dose volume histograms (DVH). Geometrically, the gimbal tracking implementation accuracy was <0.94 mm. The isodose lines agreed with the film measurement. The largest dose difference of 9.4% was observed at maximum tilt positions with an isocenter and target separation of 17.51 mm. Dosimetrically, gamma passing rates were >98.4%. The introduction of the gimbal tracking beam geometry in the dose calculation shifted the DVH curves by 0.05%-1.26% for the phantom geometry and by 5.59% for the patient CT dataset. This study successfully demonstrates a method to incorporate the gimbal tracking beam geometry into dose calculations. By combining CT rotation and MU distribution according to the log file, the TPS was able to simulate the Vero tracking treatment dose delivery. The DVH analysis from the gimbal tracking dose calculation revealed changes in the dose distribution during gimbal DTT that are not visible with static dose calculations.
EVALuna2:33026

Dose-dependent deterioration of swallowing function after induction chemotherapy and definitive chemoradiotherapy for laryngopharyngeal cancer - Haderlein, Marlen; Semrau, S.; Ott, O.; Speer, S.; Bohr, Christopher; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
To evaluate the influence of clinical, treatment- and dose-dependent factors on posttreatment swallowing function after induction chemotherapy and definitive chemoradiotherapy in a group of homogeneously treated laryngopharyngeal cancer patients.From 28 May 2008 to 15 February 2013, 45 patients with borderline inoperable laryngopharyngeal cancer that had responded well to induction chemotherapy were treated with definitive chemoradiotherapy. Median follow-up was 22 months. Swallowing function and clinical data were prospectively analyzed using the EORTC QLQ-C30 questionnaire. Swallowing structures were retrospectively delineated on the original treatment planning CT. Dose-volume histograms were calculated for swallowing structures and Dmean, Dmax and V50-V64 values (in 2 Gy increments) were determined for each patient. Tumor volume and infiltration of the swallowing apparatus was defined by CT before induction chemotherapy.Of the 45 patients, 26 (57.8 %) fully regained swallowing function after chemoradiotherapy. A further 12 patients (26.7 %) were able to manage soft, pureed and/or liquid foods; the remaining 7 (15.6 %) were completely dependent on percutaneous endoscopic gastrostomy (PEG). Posttreatment swallowing function was significantly influenced by Dmean to the superior pharyngeal constrictor muscle (PCM, p = 0.041). Correlations between late dysphagia and dose-volume relationships in the superior PCM and soft palate were also observed, which were significant from V60 (p = 0.043) and V58 for the soft palate and superior PCM, respectively. Of the evaluated clinical and tumor-related factors, only alcohol abuse (p = 0.024) had an influence on posttreatment swallowing function.Almost 50 % of patients had deterioration of swallowing function after definitive chemoradiotherapy for laryngopharyngeal cancer. The dose to anatomical structures responsible for swallowing function appears to play a role. Therefore, in selected patients, target volume delineation for radiotherapy of laryngopharyngeal cancer should be optimized on an individual basis to spare the swallowing apparatus.
EVALuna2:18123

Dose Reduction in the Swallowing Area by De-intensification of Radiotherapy in Patients with Head and Neck Cancer in the postoperative Situation - first Plan Analyzes of the DIREKHT Study - Haderlein, Marlen; Speer, Stefan; Hecht, Markus; Merten, Ricarda; Scherl, C.; Semrau, S.; Ott, O.; Fietkau, Rainer (2018)
EVALuna2:36499

Dose reduction to the swallowing apparatus and the salivary glands by de-intensification of postoperative radiotherapy in patients with head and neck cancer: First (treatment planning) results of the prospective multicenter DIREKHT trial - Haderlein, Marlen; Speer, Stefan; Ott, Oliver; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Frey, Benjamin; Scherl, Claudia; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer (Cancers, 2020)
Aim: Evaluating radiotherapy treatment plans of the prospective DIREKHT trial (ClinicalTrials.gov, NCT02528955) investigating de-intensification of radiotherapy in patients with head and neck cancer. Patients and Methods: The first 30 patients from the DIREKHT trial of the leading study centre were included in this analysis. Standard treatment plans and study treatment plans derived from the protocol were calculated for each patient. Sizes of planning target volumes (PTVs) and mean doses to organs at risk were compared using the Student’s t-test with paired samples. Results: Mean PTV3 including primary tumor region and ipsilateral elective neck up to a dose of 50 Gy in the study treatment plans was 662 mL (+/− 165 mL standard deviation (SD)) and therefore significantly smaller than those of the standard treatment plans (1166 mL (+/− 266 mL SD). In the medial and inferior constrictor muscles, cricopharyngeal muscle, glottic and supraglottic laryngeal areas, arytenoid cartilages, contralateral major salivary glands highly significant dose reductions (p < 0.0001) of more than 10 Gy were achieved in study treatment plan compared to standard treatment plan. Conclusion: De-intensification of radiotherapy led to smaller planning target volumes and clinical relevant dose reductions in the swallowing apparatus and in the contralateral salivary glands.
CRIS-Team Scopus Importer:2020-03-06
Keywords: De-intensification; Head neck cancer; Ipsilateral elective neck irradiation only; Postoperative; Radiotherapy; Salivary glands; Swallowing apparatus

Dosimetric evaluation of 6-DOF intra-fraction motion for SGRT of breast cancer patients - Sauer, Tim-Oliver; Ott, O.; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-07-08

Dosimetry, Optimization and FMEA of Total Skin Electron Irradiation (TSEI) - Shariff, Maya; Stillkrieg, Willi; Lotter, Michael; Lohmann, Daniel; Weissmann, Thomas; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Purpose: Total Skin Electron Irradiation (TSEI) is a method for treating malignant cutaneous T-cell lymphomas. This work aims to implement and optimize the total skin technique established at Strahlenklinik Erlangen, Germany on two new linear accelerators and to quantify the risks using failure mode and effects (FMEA) analysis. Material and methods: TSEI is performed at a VersaHD accelerator (Elekta, Stockholm) with 6 MeV in the “high dose rate mode” HDRE and a nominal field size of 40 × 40 cm2. To reach the entire skin surface, the patients perform 6 different body positions at a distance of 330 cm behind an acrylic scatter plate, with two overlapping irradiation fields being radiated at 2 gantry angles per position. The irradiation technique was commissioned according to the recommendation of AAPM report 23. With the help of a reference profile at 270°, 2 gantry angles were calculated, which in total resulted in an optimal dose distribution. This was metrologically verified with ion-chamber measurements in the patient's longitudinal axis. The influence of the shape of the acrylic scatter plate and the distance between the acrylic scatter plate and patient was determined by measurements. The dose homogeneity was verified using an anthropomorphic disc phantom equipped with GafChromic films. The workflows and failure modes of the total skin technique were described in a process map and subsequently quantified with a FMEA analysis. Results: An optimal dose distribution is achieved at a distance of SSD = 330 cm, using the gantry angles 289° and 251°. The previously used segmented acrylic scatter plate was replaced by a flat plate (200 × 120 × 0.5 cm3), which is placed at a distance of 50 cm in front of the patient. The densitometric evaluation of the GafChromic films in the anthropomorphic disc phantom revealed an expected dose distribution of 3 Gy at a depth of up to 1.5 cm below the skin surface, with a homogeneity of ±10% over the phantom's longitudinal axis. By FMEA a maximum risk priority number of 30 was determined. Conclusion: Based on the calculations and measurements performed on the new accelerators as well as the risk analysis, we concluded that total skin therapy can be implemented clinically.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Dosimetry; FMEA; HDRE; Mycosis fungoides; Quality assurance; Total Skin Electron Irradiation (TSEI)

Downstage migration after neoadjuvant chemoradiotherapy for rectal cancer: the reverse of the Will Rogers phenomenon? - Fokas, Emmanouil; Liersch, Torsten; Fietkau, Rainer; Hohenberger, Werner; Hess, Clemens; Becker, Heinz; Sauer, Rolf; Wittekind, Christian; Roedel, Claus (Cancer, 2015)
Downstaging after neoadjuvant treatment is increasingly used as a prognostic factor and surrogate endpoint in clinical trials. However, in recent trials of neoadjuvant 5-fluorouracil-based chemoradiotherapy for rectal cancer, downstaging did not translate into a benefit with regard to either disease-free survival (DFS) or overall survival. By analyzing the 10-year outcome data of the German CAO/ARO/AIO-94 phase 3 trial, the authors demonstrated that significantly fewer patients had poor prognostic features (eg, ypT3-4, ypN1-2) after preoperative 5-fluorouracil-based chemoradiotherapy. Nevertheless, these patients with International Union for Cancer Control stage II disease were found to be at a higher risk of developing distant metastases and had poorer DFS compared with patients with corresponding TNM tumor (sub)groups in the postoperative treatment arm, whereas patients with International Union for Cancer Control stage III disease demonstrated a nonsignificant trend toward a worse outcome after preoperative treatment. Overall, DFS remained identical in both treatment arms. Thus, "downstage migration" after neoadjuvant treatment resembles the reverse of the Will Rogers phenomenon and therefore may not be a reliable endpoint for long-term outcomes.
EVALuna2:15194

Dual mtor/dna-pk inhibitor cc-115 induces cell death in melanoma cells and has radiosensitizing potential - Bürkel, Felix; Jost, Tina; Hecht, Markus; Heinzerling, Lucie; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2020)
CC-115 is a dual inhibitor of the mechanistic target of rapamycin (mTOR) kinase and the DNA-dependent protein kinase (DNA-PK) that is currently being studied in phase I/II clinical trials. DNA-PK is essential for the repair of DNA-double strand breaks (DSB). Radiotherapy is frequently used in the palliative treatment of metastatic melanoma patients and induces DSBs. Melanoma cell lines and healthy-donor skin fibroblast cell lines were treated with CC-115 and ionizing irradiation (IR). Apoptosis, necrosis, and cell cycle distribution were analyzed. Colony forming assays were conducted to study radiosensitizing effects. Immunofluorescence microscopy was performed to determine the activity of homologous recombination (HR). In most of the malign cell lines, an increasing concentration of CC-115 resulted in increased cell death. Furthermore, strong cytotoxic effects were only observed in malignant cell lines. Regarding clonogenicity, all cell lines displayed decreased survival fractions during combined inhibitor and IR treatment and supra-additive effects of the combination were observable in 5 out of 9 melanoma cell lines. CC-115 showed radiosensitizing potential in 7 out of 9 melanoma cell lines, but not in healthy skin fibroblasts. Based on our data CC-115 treatment could be a promising approach for patients with metastatic melanoma, particularly in the combination with radiotherapy.
CRIS-Team Scopus Importer:2020-12-25
Keywords: DNA repair; DNA-PK; Homologous recombination (HR); Kinase inhibitor; Melanoma; MTOR; Non-homologous end-joining (NHEJ); Radiosensitivity

Durvalumab improves prognosis of stage III non-small-cell lung cancer after definitive chemoradiotherapy - Hecht, Markus; Gaipl, Udo; Fietkau, Rainer (Strahlentherapie und Onkologie, 2018)
EVALuna2:33776

EARLY BLOOD CELL COUNT TEST (BCT) FOR SURVIVAL PREDICTION FOR NON-SMALL CELL LUNG CANCER PATIENTS TREATED WITH ATEZOLIZUMAB: INTEGRATED ANALYSIS OF 4 MULTICENTER CLINICAL TRIALS - Zhou, Jian-Guo; Wong, Ada Hang-Heng; Wang, Haitao; Jin, Su-Han; Tan, Fangya; Chen, Yu-Zhong; He, Si-Si; Shen, Gang; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Shen, Bo; et al. (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2021)
Immune checkpoint inhibitor (ICI) therapy is a major breakthrough for non-small cell lung cancer (NSCLC) treatment given its high efficacy and tolerable toxicity. Although pre-treatment PD-L1 expression levels and tumor mutation burden (TMB) may serve as prognostic biomarkers for patient stratification, effective predictive biomarkers are lacking. Blood cell count test (BCT) is a routine, regular blood test conducted before and during treatment to provide a direct overview of the immune landscape based on the counts of various types of immune cells (ICs). For instance, previous studies showed that neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) both indicate poor treatment outcomes of ICI therapy of NSCLC patients.<br
CRIS-Team WoS Importer:2022-04-15

Early Mortality of Brain Cancer Patients and its Connection to Cytomegalovirus Reactivation During Radiochemotherapy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Rühle, Paul-Friedrich; Putz, Florian; Semrau, Sabine; et al. (Clinical Cancer Research, 2020)
PURPOSE: If routine diagnostics are inconclusive, neurologic deterioration and death of patients with brain cancer are attributed to tumor or therapy. Therefore, diagnosing symptoms of encephalopathy caused by human cytomegalovirus (HCMV) reactivation remains uncommon. We investigated the role of HCMV reactivation in neurologic decline and clinical outcome after the start of radiochemotherapy. EXPERIMENTAL DESIGN: HCMV analyses and extended MRI studies including additional independent retrospective neuroradiologic evaluation were performed at predetermined intervals and in case of sudden neurologic decline for 118 adult patients: 63 histologically proven high-grade gliomas, 55 with brain metastases. Immunophenotyping from simultaneously taken whole-blood samples was carried out to detect immune cells serving as prognostic marker for HCMV-associated complications. Symptomatic viremia and overall survival (OS) were the endpoints. RESULTS: Twenty-four percent (28/118) of all patients (12/44 glioblastoma, 3/13 anaplastic astrocytoma; 8/31 non-small cell lung cancer (NSCLC), 13/24 other brain metastases) developed HCMV-viremia during or within 4 weeks after radiotherapy; 21 of 28 patients experienced concurrent major neurologic decline, reversible by antiviral treatment. Identified by immunophenotyping, pretherapeutically low basophil counts predicted a high-risk for HCMV-associated encephalopathy (glioblastoma: P = 0.002, NSCLC: P = 0.02). Median OS was substantially reduced after HCMV-associated encephalopathy without MRI signs of tumor progression [glioblastoma: 99 vs. 570 days (calculated 1-year OS: 22% vs. 69%; P = 0.01) and NSCLC: 47 vs. 219 days (calculated 1-year OS: 0% vs. 32%; P = 0.02)]. CONCLUSIONS: For patients with brain cancer, HCMV reactivation after the start of radiochemotherapy is a frequent risk for cognitively detrimental but treatable encephalopathy and premature death. Routinely performed HCMV diagnostics, assessing basophil counts and study-based anti-viral regimens, are necessary to combat this hidden threat.See related commentary by Lawler et al., p. 3077.
CRIS-Team Scopus Importer:2020-07-17

ECG-based 4D-dose reconstruction of cardiac arrhythmia ablation with carbon ion beams: application in a porcine model - Richter, Daniel; Lehmann, H. Immo; Eichhorn, Anna; Constantinescu, Anna M.; Kaderka, Robert; Prall, Matthias; Lugenbiel, Patrick; Takami, Mitsuru; Thomas, Dierk; Bert, Christoph; Durante, Marco; Packer, Douglas L.; et al. (Physics in Medicine and Biology, 2017)
Noninvasive ablation of cardiac arrhythmia by scanned particle radiotherapy is highly promising, but especially challenging due to cardiac and respiratory motion. Irradiations for catheter-free ablation in intact pigs were carried out at the GSI Helmholtz Center in Darmstadt using scanned carbon ions. Here, we present real-time electrocardiogram (ECG) data to estimate time-resolved (4D) delivered dose. For 11 animals, surface ECGs and temporal structure of beam delivery were acquired during irradiation. R waves were automatically detected from surface ECGs. Pre-treatment ECG-triggered 4D-CT phases were synchronized to the R-R interval. 4D-dose calculation was performed using GSI's in-house 4D treatment planning system. Resulting dose distributions were assessed with respect to coverage (D95 and V95), heterogeneity (HI = D5-D95) and normal tissue exposure. Final results shown here were performed offline, but first calculations were started shortly after irradiation The D95 for TV and PTV was above 95% for 10 and 8 out of 11 animals, respectively. HI was reduced for PTV versus TV volumes, especially for some of the animals targeted at the atrioventricular junction, indicating residual interplay effects due to cardiac motion. Risk structure exposure was comparable to static and 4D treatment planning simulations. ECG-based 4D-dose reconstruction is technically feasible in a patient treatment-like setting. Further development of the presented approach, such as real-time dose calculation, may contribute to safe, successful treatments using scanned ion beams for cardiac arrhythmia ablation.
EVALuna2:36481

Education, training and registration of Medical Physics Experts across Europe - Maas, Ad J.J.; Lammertsma, Adriaan A.; Agius, Sam; Bert, Christoph; Byrne, Brenda; Caruana, Carmel J.; Gilligan, Paddy; Koutsouveli, Efi; Pace, Eric; Brambilla, Marco (Physica Medica, 2021)
From its inception, EFOMP has pursued a policy to improve and coordinate education and training of medical physicists across all its participating European countries. Several EFOMP policy statements on education and training have been published and surveys have been held to get an overview of the actual situation. At the beginning of 2020 a new survey was distributed amongst the 36 National Member Organizations (NMOs), in which questions were based on recommendations published in the most recent policy statements. Thirty-three of the NMOs (91%) responded, of which 22 indicated having a National Registration Scheme (NRS) for Medical Physics Experts (MPEs) in place. Another 6 indicated considering such a scheme. Results of the questionnaire showed that there was good correspondence between education and training programmes, i.e. a division between a BSc phase, an MSc phase and a clinical phase after completion of the MSc. Differences between NRSs were primarily seen in the availability and composition of a supervising committee and in the availability of guidelines for handling professional misconduct. In addition, some differences were seen in the topics that were part of the education and training programme. The goal of a universal (registered) MPE accepted by all European countries is still far away despite the progress being made. The new procedure for approving an existing NRS, which fulfils all EFOMP criteria is seen as an important step forward. Exchange of experience, knowledge, ideas and, above all, MPE trainees between European countries is seen as the best approach to achieve this goal.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Education and training; European Federation of Organizations for Medical Physics; Medical Physics Expert; National registration scheme; Professional misconduct; Supervising committee

Efavirenz Has the Highest Anti-Proliferative Effect of Non-Nucleoside Reverse Transcriptase Inhibitors against Pancreatic Cancer Cells - Hecht, Markus; Erber, Sonja; Harrer, Thomas; Klinker, Hartwig; Roth, Thomas; Parsch, Hans; Fiebig, Nora; Fietkau, Rainer; Distel, Luitpold (PLoS ONE, 2015)
Cancer prevention and therapy in HIV-1-infected patients will play an important role in future. The non-nucleoside reverse transcriptase inhibitors (NNRTI) Efavirenz and Nevirapine are cytotoxic against cancer cells in vitro. As other NNRTIs have not been studied so far, all clinically used NNRTIs were tested and the in vitro toxic concentrations were compared to drug levels in patients to predict possible anti-cancer effects in vivo.Cytotoxicity was studied by Annexin-V-APC/7AAD staining and flow cytometry in the pancreatic cancer cell lines BxPC-3 and Panc-1 and confirmed by colony formation assays. The 50% effective cytotoxic concentrations (EC50) were calculated and compared to the blood levels in our patients and published data.The in vitro EC50 of the different drugs in the BxPC-3 pancreatic cancer cells were: Efavirenz 31.5 ?mol/l (= 9944 ng/ml), Nevirapine 239 ?mol/l (= 63,786 ng/ml), Etravirine 89.0 ?mol/l (= 38,740 ng/ml), Lersivirine 543 ?mol/l (= 168,523 ng/ml), Delavirdine 171 ?mol/l (= 78,072 ng/ml), Rilpivirine 24.4 ?mol/l (= 8941 ng/ml). As Efavirenz and Rilpivirine had the highest cytotoxic potential and Nevirapine is frequently used in HIV-1 positive patients, the results of these three drugs were further studied in Panc-1 pancreatic cancer cells and confirmed with colony formation assays. 205 patient blood levels of Efavirenz, 127 of Rilpivirine and 31 of Nevirapine were analyzed. The mean blood level of Efavirenz was 3587 ng/ml (range 162-15,363 ng/ml), of Rilpivirine 144 ng/ml (range 0-572 ng/ml) and of Nevirapine 4955 ng/ml (range 1856-8697 ng/ml). Blood levels from our patients and from published data had comparable Efavirenz levels to the in vitro toxic EC50 in about 1 to 5% of all patients.All studied NNRTIs were toxic against cancer cells. A low percentage of patients taking Efavirenz reached in vitro cytotoxic blood levels. It can be speculated that in HIV-1 positive patients having high Efavirenz blood levels pancreatic cancer incidence might be reduced. Efavirenz might be a new option in the treatment of cancer.
EVALuna2:13144

Effective local control of advanced soft tissue sarcoma with neoadjuvant chemoradiotherapy and surgery: A single institutional experience - Stubbe, Franziska; Agaimy, Abbas; Ott, O.; Lettmaier, S.; Vassos, N.; Croner, R.; Hohenberger, Werner; Fietkau, Rainer; Semrau, S. (Cancer Radiotherapie, 2016)
There is a sound theoretical basis but little clinical evidence substantiating the benefits of concurrent chemoradiotherapy with two-drug chemotherapy for locally advanced soft tissue sarcomas. Our five-year data on the feasibility and effectiveness of neoadjuvant chemoradiotherapy with systemically effective doses of adriamycin and ifosfamide combined is presented here.Between 2000 and 2011, 53 patients with UICC (2010) stage I (n=1, 1.9%), II (n=12, 22.7%) or III (n=40, 75.5%) nonmetastatic soft tissue sarcoma received neoadjuvant chemoradiotherapy with ifosfamide (1.5g/m(2)/day, d1-5, q28) and doxorubicin (50mg/m(2)/day, d3, q28) plus concurrent radiotherapy with a target dose of 50-64Gy (median 60Gy). The treatment of 34 patients (64.2%) was combined with hyperthermia.At five years, the local control rate was 89.9% (±5.7%), distant metastasis-free survival 66.6% (±7.6%), and survival 83.3% (±6%). The R0 resection rate was 81.1%. Radiotherapy was completed as planned in all patients and chemotherapy in 42/53 (70.2%). Grades III (n=21, 29.6%) and IV (n=18, 34%) leukopenia was the main acute adverse event. All acute and chronic non-hematologic toxicities were moderate.Neoadjuvant chemoradiotherapy for soft tissue sarcoma is associated with good feasibility, manageable acute and late toxicities, and high local efficacy.
EVALuna2:6741

Effective local control of vertebral metastases by simultaneous integrated boost radiotherapy: preliminary results - Lubgan, Dorota; Ziegaus, Anke; Semrau, Sabine; Lambrecht, Ulrike; Lettmaier, Sebastian; Fietkau, Rainer (Strahlentherapie und Onkologie, 2015)
The primary endpoint was to improve local tumour control of patients with metastatic spinal tumours by stereotactic body radiotherapy (SBRT) and dose escalation by simultaneous, integrated boost (PTV-boost). We used a whole vertebral body (PTV-elective) contouring approach. Secondary endpoints were severity of acute and chronic adverse effects and overall survival.In all, 33 patients with metastases of the vertebral column were treated at Erlangen University Hospital. SBRT was given in 12 or 10 fractions. The metastatic lesion (PTV-boost) received 3.6 Gy (range 3.0-4.51 Gy) per fraction for a total of 42.0 Gy (24.36-48.0 Gy) and the whole vertebra (PTV-elective) received 2.85 Gy (range 1.8-3.6 Gy) per fraction for a total of 32.39 Gy (range 21.60-38.0 Gy). Patients were followed up every 3 months.Local control rate of all patients was 93% at 12 and 24 months. The overall survival rate was 54% at 12 months, 38% at 24 months and 18% at 36 months. No radiation myelopathy occurred. The most frequently observed adverse events in 3 cases was oesophagitis grade 2.SBRT with simultaneous, integrated boost was associated with excellent local control of 93% after 24 months. This result shows the possibility of delivering escalated doses to the target while still keeping the incidence of side effects low. This study forms the basis for a future randomised controlled trial comparing conventional radiotherapy (10 fractions of 3 Gy) with hypofractionated dose intensified SBRT (12 fractions of 3 Gy + integrated boost 12 fractions of 4 Gy) for improvement of local tumour control and pain.
EVALuna2:18283

Effective long-term local results and prognostic factors after fractionated stereotactic radiotherapy of 257 intracranial meningeoma - Lubgan, Dorota; Rutzner, Sandra; Semrau, S.; Lambrecht, U.; Roessler, K.; Buchfelder, Michael; Fietkau, Rainer (2016)
EVALuna2:18329

Effectiveness of ablative Irradiation of all Metastases versus Irradiation of a singular Metastasis in Combination with Immunocheckpoint Inhibitors - clinical Evaluation of prospective STICI Study - Schubert, P.; Schweizer, C.; Roesch, Johannes; Haderlein, Marlen; Rutzner, Sandra; Semrau, Sabine; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Hecht, Markus (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Effective Radiosensitization of HNSCC Cell Lines by DNA-PKcs Inhibitor AZD7648 and PARP Inhibitors Talazoparib and Niraparib - Mentzel, Jacob; Hildebrand, Laura; Kuhlmann, Lukas; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2024)
(1) Head and neck squamous cell carcinoma (HNSCC) is common, while treatment is difficult, and mortality is high. Kinase inhibitors are promising to enhance the effects of radiotherapy. We compared the effects of the PARP inhibitors talazoparib and niraparib and that of the DNA-PKcs inhibitor AZD7648, combined with ionizing radiation. (2) Seven HNSCC cell lines, including Cal33, CLS-354, Detroit 562, HSC4, RPMI2650 (HPV-negative), UD-SCC-2 and UM-SCC-47 (HPV-positive), and two healthy fibroblast cell lines, SBLF8 and SBLF9, were studied. Flow cytometry was used to analyze apoptosis and necrosis induction (AnnexinV/7AAD) and cell cycle distribution (Hoechst). Cell inactivation was studied by the colony-forming assay. (3) AZD7648 had the strongest effects, radiosensitizing all HNSCC cell lines, almost always in a supra-additive manner. Talazoparib and niraparib were effective in both HPV-positive cell lines but only consistently in one and two HPV-negative cell lines, respectively. Healthy fibroblasts were not affected by any combined treatment in apoptosis and necrosis induction or G2/M-phase arrest. AZD7648 alone was not toxic to healthy fibroblasts, while the combination with ionizing radiation reduced clonogenicity. (4) In conclusion, talazoparib, niraparib and, most potently, AZD7648 could improve radiation therapy in HNSCC. Healthy fibroblasts tolerated AZD7648 alone extremely well, but irradiation-induced effects might occur. Our results justify in vivo studies.
CRIS-Team Scopus Importer:2024-06-21
Keywords: cell lines; DNA damage response inhibitor; DNA-PK inhibitor; HNSCC; ionizing radiation; kinase inhibitor; PARP inhibitor; radiosensitivity

Effect of Citrate- and Gold-Stabilized Superparamagnetic Iron Oxide Nanoparticles on Head and Neck Tumor Cell Lines during Combination Therapy with Ionizing Radiation - Schreiber, Christoph; Franzen, Tim; Hildebrand, Laura; Stein, René; Friedrich, Bernhard; Tietze, Rainer; Fietkau, Rainer; Distel, Luitpold (Bioengineering, 2022)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide. They are associated with alcohol and tobacco consumption, as well as infection with human papillomaviruses (HPV). Therapeutic options include radiochemotherapy, surgery or chemotherapy. Nanoparticles are becoming more and more important in medicine. They can be used diagnostically, but also therapeutically. In order to provide therapeutic alternatives in the treatment of HNSCC, the effect of citrate-coated superparamagnetic iron oxide nanoparticles (Citrate-SPIONs) and gold-coated superparamagnetic iron oxide nanoparticles (Au-SPIONs) in combination with ionizing irradiation (IR) on two HPV positive and two HPV negative HNSCC and healthy fibroblasts and keratinocytes cell lines were tested. Effects on apoptosis and necrosis were analyzed by using flow cytometry. Cell survival studies were performed with a colony formation assay. To better understand where the SPIONs interact, light microscopy images and immunofluorescence studies were performed. The HNSCC and healthy cell lines showed different responses to the investigated SPIONs. The cytotoxic effects of SPIONs, in combination with IR, are dependent on the type of SPIONs, the dose administered and the cell type treated. They are independent of HPV status. Reasons for the different cytotoxic effect are probably the different compositions of the SPIONs and the related different interaction of the SPIONs intracellularly and paramembranously, which lead to different strong formations of double strand breaks.
CRIS-Team WoS Importer:2023-01-13

Effect of hyperthermia and radiation therapy sequence on cell death and the immune phenotype of breast cancer cells - Sengedorj, Azzaya; Hader, Michael; Rückert, Michael; Frey, Benjamin; Fietkau, Rainer; Ott, Oliver; Scheidegger, S.; Barba, S. M.; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Effect of Radiotherapy and Chemotherapy on the Immunophenotype of Head and Neck Cancer Cells and the consecutive Activation of dendritic Cells - Grottker, F.; Frey, Benjamin; Gehre, S.; Reichardt, Clara; Sengedorj, Azzaya; Hecht, Markus; Fietkau, Rainer; Rieckmann, T.; Gostian, Antoniu-Oreste; Gaipl, Udo; Rückert, Michael (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Effect of the AMPA Receptor Inhibitor Perampanel in Combination Therapy with ionizing Radiation on Glioblastoma Cells and Fibroblasts - Knabe, A.; Stritzelberger, Jenny; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Effect of the kinase-inhibitor Palbociclib on radio-therapeutic treatment in a 3D cell culture model - Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36492

Effects of a Caregiver on the Quality of Life of Cancer Patients during Radiochemotherapy and Improvement Potential through Integration of the Caregiver in the Therapy - Wittenstein, Katharina; Fietkau, Rainer; Distel, Luitpold; Lebensqualitat, Studiengruppe (2017)
EVALuna2:32898

Effects of Combination Therapy of Kinase Inhibitors and ionizing Radiation on ENT Tumor Cell Lines and Normal Tissue Cells - Faulhaber, E. -M; Scheper, J.; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Effects of Hippocampal Sparing Radiotherapy on Brain Microstructure—A Diffusion Tensor Imaging Analysis - Dinkel, Johannes; Lahmer, Godehard; Mennecke, Angelika; Hock, Stefan; Richter-Schmidinger, Tanja; Fietkau, Rainer; Distel, Luitpold; Putz, Florian; Dörfler, Arnd; Schmidt, Manuel (Brain Sciences, 2022)
Hippocampal-sparing radiotherapy (HSR) is a promising approach to alleviate cognitive side effects following cranial radiotherapy. Microstructural brain changes after irradiation have been demonstrated using Diffusion Tensor Imaging (DTI). However, evidence is conflicting for certain parameters and anatomic structures. This study examines the effects of radiation on white matter and hippocampal microstructure using DTI and evaluates whether these may be mitigated using HSR. A total of 35 tumor patients undergoing a prospective randomized controlled trial receiving either conventional or HSR underwent DTI before as well as 6, 12, 18, 24, and 30 (±3) months after radiotherapy. Fractional Anisotropy (FA), Mean Diffusivity (MD), Axial Diffusivity (AD), and Radial Diffusivity (RD) were measured in the hippocampus (CA), temporal, and frontal lobe white matter (TL, FL), and corpus callosum (CC). Longitudinal analysis was performed using linear mixed models. Analysis of the entire patient collective demonstrated an overall FACC decrease and RDCC increase compared to baseline in all follow-ups; ADCC decreased after 6 months, and MDCC increased after 12 months (p ≤ 0.001, 0.001, 0.007, 0.018). ADTL decreased after 24 and 30 months (p ≤ 0.004, 0.009). Hippocampal FA increased after 6 and 12 months, driven by a distinct increase in ADCA and MDCA, with RDCA not increasing until 30 months after radiotherapy (p ≤ 0.011, 0.039, 0.005, 0.040, 0.019). Mean radiation dose correlated positively with hippocampal FA (p < 0.001). These findings may indicate complex pathophysiological changes in cerebral microstructures after radiation, insufficiently explained by conventional DTI models. Hippocampal microstructure differed between patients undergoing HSR and conventional cranial radiotherapy after 6 months with a higher ADCA in the HSR subgroup (p ≤ 0.034).
CRIS-Team Scopus Importer:2022-07-22
Keywords: cognitive impairment; cranial radiotherapy; diffusion tensor imaging; fractional anisotropy; hippocampal sparing radiotherapy; hippocampus

Effects of Radiotherapy on the Kinetics of Immune Checkpoint Molecule Expression in Tumor Cells and their radioresistant Clones - Siegert, Juliane; Rückert, Michael; Meyer, F.; Borgmann, K.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Effects of Radon-Spa-Therapy on Patients with musculoskeletal Diseases - Becker, Ina; Donaubauer, Anna-Jasmina; Klein, G.; Fournier, C.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Effects of serial radon spa therapy on pain and peripheral immune status in patients suffering from musculoskeletal disorders– results from a prospective, randomized, placebo-controlled trial - Donaubauer, Anna-Jasmina; Becker, Ina; Klein, Gerhart; Voll, Reinhard E.; Weikl, Lena; Klieser, Martin; Barzangi, Shakar; Zhou, Jianguo; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2024)
In this randomized, placebo-controlled cross-over trial we aimed to investigate if radon spa therapy exerts more pain relief than exposure to warm water alone. In addition, immunological parameters were assessed in both treatment groups. In the RAD-ON02 trial, 116 patients suffering from musculoskeletal disorders (MSDs) received either serial radon spa or solely warm water baths. Pain intensity was assessed by determination of different pain parameters on a visual analogue scale and by pressure point dolorimetry at baseline and at weeks 4, 12 and 24. The longitudinal immune status of the patients was analyzed by a flow cytometry-based assay from peripheral blood at the time points of pain assessments. There were no side effects attributable to radon exposure observed. However, radon spa was superior to warm water applications at week 4 in terms of pain reduction. Pain and morning stiffness at the time of assessment were significantly reduced after radon spa (p<0.001, p<0.01) but not after warm water baths. The dolorimetry resulted in a significantly higher exerted pressure strength in patients after radon spa (p<0.001), but not after warm water applications. During the long-term follow-up, both treatment modalities reduced pain to a similar degree and pain modulation was not distorted by the participants’ intake of analgesics. No significant changes in the immune status attributable specifically to radon were found, even though the increase in regulatory T cell counts occurs earlier after radon baths than after sole warm water baths and a higher level of significance is reached after radon spa at week 24. Serial radon spa has additive pain-relieving effects. The immunological parameters assessed in our study appear not to be directly linked to the pain reduction caused by radon exposure, at least in MSD patients with predominantly degenerative diseases. Clinical trial registration: https://www.clinicaltrialsregister.eu/ctr-search/search?query=rad-on02, identifier 2016-002085-31; https://drks.de/search/de/trial, identifier DRKS00016019.
CRIS-Team Scopus Importer:2024-03-01
Keywords: chronic degenerative and inflammatory diseases; chronic pain; musculoskeletal disorders; peripheral immune status; radon spa; randomized placebo-controlled trial

Effects of whole-body electromyostimulation combined with individualized nutritional support on body composition in patients with advanced cancer: a controlled pilot trial - Schink, Kristin; Herrmann, Hans J.; Schwappacher, Raphaela; Meyer, Julia; Orlemann, Till; Waldmann, Elisabeth; Wullich, Bernd; Kahlmeyer, Andreas; Fietkau, Rainer; Lubgan, Dorota; Beckmann, Matthias; Hack, Carolin; et al. (BMC Cancer, 2018)
BACKGROUND: Physical exercise and nutritional treatment are promising measures to prevent muscle wasting that is frequently observed in advanced-stage cancer patients. However, conventional exercise is not always suitable for these patients due to physical weakness and therapeutic side effects. In this pilot study, we examined the effect of a combined approach of the novel training method whole-body electromyostimulation (WB-EMS) and individualized nutritional support on body composition with primary focus on skeletal muscle mass in advanced cancer patients under oncological treatment. METHODS: In a non-randomized controlled trial design patients (56.5% male; 59.9 ± 12.7 years) with advanced solid tumors (UICC III/IV, N = 131) undergoing anti-cancer therapy were allocated to a usual care control group (n = 35) receiving individualized nutritional support or to an intervention group (n = 96) that additionally performed a supervised physical exercise program in form of 20 min WB-EMS sessions (bipolar, 85 Hz) 2×/week for 12 weeks. The primary outcome of skeletal muscle mass and secondary outcomes of body composition, body weight and hand grip strength were measured at baseline, in weeks 4, 8 and 12 by bioelectrical impedance analysis and hand dynamometer. Effects of WB-EMS were estimated by linear mixed models. Secondary outcomes of physical function, hematological and blood chemistry parameters, quality of life and fatigue were assessed at baseline and week 12. Changes were analyzed by t-tests, Wilcoxon signed-rank or Mann-Whitney-U-tests. RESULTS: Twenty-four patients of the control and 58 of the WB-EMS group completed the 12-week trial. Patients of the WB-EMS group had a significantly higher skeletal muscle mass (0.53 kg [0.08, 0.98]; p = 0.022) and body weight (1.02 kg [0.05, 1.98]; p = 0.039) compared to controls at the end of intervention. WB-EMS also significantly improved physical function and performance status (p < 0.05). No significant differences of changes in quality of life, fatigue and blood parameters were detected between the study groups after 12 weeks. CONCLUSIONS: Supervised WB-EMS training is a safe strength training method and combined with nutritional support it shows promising effects against muscle wasting and on physical function in advanced-stage cancer patients undergoing treatment. TRIAL REGISTRATION: ClinicalTrials.gov NCT02293239 (Date: November 18, 2014).
EVALuna2:35141

E-Field Patterns of Coaxial MW Antennas for Combined Thermo-Brachytherapy - Erb, J.; Engelbrecht, Rainer; Schaller, Gerhard; Ross, D.; Seegenschmiedt, Heinrich; Fietkau, Rainer; Sauer, R. (Deutsche Brachytherapie-Konferenz, 1993)
UnivIS-Import:2015-04-16:Pub.1993.tech.IE.LEH.efield

ELDORANDO - Pembrolizumab compared with methotrexate in elderly, frail or cisplatin-ineligible patients with relapsed or metastatic squamous cell carcinoma of the head and neck (RM-SCCHN) (ELDORANDO-AIO-KHT-0115) - Klinghammer, K.; Graeven, U.; Ivanyi, P.; Dietz, A.; Hahn, D.; Hackenberg, S.; Kasper, S.; Fietkau, Rainer; Moulin, J. -C; Pink, D.; Schaaf, M.; Grunwald, (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Electromagnetic tracking for treatment verification in interstitial brachytherapy - Bert, Christoph; Kellermeier, Markus; Tanderup, Kari (Journal of Contemporary Brachytherapy, 2016)
Electromagnetic tracking (EMT) is used in several medical fields to determine the position and orientation of dedicated sensors, e.g., attached to surgical tools. Recently, EMT has been introduced to brachytherapy for implant reconstruction and error detection. The manuscript briefly summarizes the main issues of EMT and error detection in brachytherapy. The potential and complementarity of EMT as treatment verification technology will be discussed in relation toin vivodosimetry and imaging.
EVALuna2:33051

Electromagnetic tracking in interstitial brachytherapy: A systematic review - Sauer, Birte; Dürrbeck, Christopher; Bert, Christoph (Frontiers in Physics, 2022)
Brachytherapy is a well-established treatment option for different cancer types. One treatment option, namely temporary afterloading brachytherapy, utilizes an encapsulated radioactive source, which is guided through implanted applicators to pre-defined dwell positions, to deliver highly conformal and concentrated doses to the target volume. However, treatment errors and uncertainties might still occur. The treatment therefore requires a stringent verification on an individual patient level, particularly in the form of applicator reconstruction. Electromagnetic tracking (EMT) is a possible verification option whose application neither relies on direct line of sight nor does it increase the radiation exposure. However, its systematic clinical application is not yet realized. This review will separate the concept of treatment verification through the use of electromagnetic tracking into four focus groups and categorize the relevant papers within said groups. The four focus groups are geometric assessment, applicator reconstruction, patient-individual quality assurance and adaptive treatment planning. The reviewed papers can be mainly sorted into the focus groups of geometric assessment and applicator reconstruction underlining the potential of EMT as an asset for reconstruction and localization. A smaller group of papers can be associated with patient-individual quality assurance where the detection of implant variations such as swaps within the connector cohort or single catheter shifts take center stage. The final focus group, adaptive treatment planning, is sparsely represented, yet the feasibility of an adaptive treatment course can be derived. This review will close with a discussion of possible improvements and illustrate the path ahead to clinical implementation.
CRIS-Team WoS Importer:2022-10-14

Electronic Support for Retrospective Analysis in the Field of Radiation Oncology: Proof of Principle Using an Example of Fractionated Stereotactic Radiotherapy of 251 Meningioma Patients - Rutzner, Sandra; Fietkau, Rainer; Ganslandt, Thomas; Prokosch, Hans-Ulrich; Lubgan, Dorota (Frontiers in Oncology, 2017)
The purpose of this study is to verify the possible benefit of a clinical data warehouse (DWH) for retrospective analysis in the field of radiation oncology.We manually and electronically (using DWH) evaluated demographic, radiotherapy, and outcome data from 251 meningioma patients, who were irradiated from January 2002 to January 2015 at the Department of Radiation Oncology of the Erlangen University Hospital. Furthermore, we linked the Oncology Information System (OIS) MOSAIQ(®) to the DWH in order to gain access to irradiation data. We compared the manual and electronic data retrieval method in terms of congruence of data, corresponding time, and personal requirements (physician, physicist, scientific associate).The electronically supported data retrieval (DWH) showed an average of 93.9% correct data and significantly (p = 0.009) better result compared to manual data retrieval (91.2%). Utilizing a DWH enables the user to replace large amounts of manual activities (668 h), offers the ability to significantly reduce data collection time and labor demand (35 h), while simultaneously improving data quality. In our case, work time for manually data retrieval was 637 h for the scientific assistant, 26 h for the medical physicist, and 5 h for the physician (total 668 h).Our study shows that a DWH is particularly useful for retrospective analysis in the radiation oncology field. Routine clinical data for a large patient group can be provided ready for analysis to the scientist and data collection time can be significantly reduced. Furthermore, linking multiple data sources in a DWH offers the ability to improve data quality for retrospective analysis, and future research can be simplified.
EVALuna2:173

Electrothermic effects of microwave heating on B16 melanoma cells - examinations with a semi-continuous plug flow-like reactor - Drescher, C.; Derer, Anja; Rosin, A.; Gerdes, T.; Willert-Porada, M.; Wadepohl, M.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2017)
EVALuna2:32880

Elucidation of the Application of Blood Test Biomarkers to Predict Immune-Related Adverse Events in Atezolizumab-Treated NSCLC Patients Using Machine Learning Methods - Zhou, Jian-Guo; Wong, Ada Hang-Heng; Wang, Haitao; Tan, Fangya; Chen, Xiaofei; Jin, Su-Han; He, Si-Si; Shen, Gang; Wang, Yun-Jia; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; et al. (Frontiers in Immunology, 2022)
BackgroundDevelopment of severe immune-related adverse events (irAEs) is a major predicament to stop treatment with immune checkpoint inhibitors, even though tumor progression is suppressed. However, no effective early phase biomarker has been established to predict irAE until now. MethodThis study retrospectively used the data of four international, multi-center clinical trials to investigate the application of blood test biomarkers to predict irAEs in atezolizumab-treated advanced non-small cell lung cancer (NSCLC) patients. Seven machine learning methods were exploited to dissect the importance score of 21 blood test biomarkers after 1,000 simulations by the training cohort consisting of 80%, 70%, and 60% of the combined cohort with 1,320 eligible patients. ResultsXGBoost and LASSO exhibited the best performance in this study with relatively higher consistency between the training and test cohorts. The best area under the curve (AUC) was obtained by a 10-biomarker panel using the XGBoost method for the 8:2 training:test cohort ratio (training cohort AUC = 0.692, test cohort AUC = 0.681). This panel could be further narrowed down to a three-biomarker panel consisting of C-reactive protein (CRP), platelet-to-lymphocyte ratio (PLR), and thyroid-stimulating hormone (TSH) with a small median AUC difference using the XGBoost method [for the 8:2 training:test cohort ratio, training cohort AUC difference = -0.035 (p < 0.0001), and test cohort AUC difference = 0.001 (p=0.965)]. ConclusionBlood test biomarkers currently do not have sufficient predictive power to predict irAE development in atezolizumab-treated advanced NSCLC patients. Nevertheless, biomarkers related to adaptive immunity and liver or thyroid dysfunction warrant further investigation.
CRIS-Team WoS Importer:2022-07-29

Enhancer hijacking activates oncogenic transcription factor NR4A3 in acinic cell carcinomas of the salivary glands - Haller, Florian; Bieg, Matthias; Will, Rainer; Koerner, Cindy; Weichenhan, Dieter; Bott, Alexander; Ishaque, Naveed; Lutsik, Pavlo; Moskalev, Evgeny; Müller, Susanna; Baehr, Marion; Woerner, Angelika; et al. (Nature Communications, 2019)
The molecular pathogenesis of salivary gland acinic cell carcinoma (AciCC) is poorly understood. The secretory Ca-binding phosphoprotein (SCPP) gene cluster at 4q13 encodes structurally related phosphoproteins of which some are specifically expressed at high levels in the salivary glands and constitute major components of saliva. Here we report on recurrent rearrangements [t(4;9)(q13;q31)] in AciCC that translocate active enhancer regions from the SCPP gene cluster to the region upstream of Nuclear Receptor Subfamily 4 Group A Member 3 (NR4A3) at 9q31. We show that NR4A3 is specifically upregulated in AciCCs, and that active chromatin regions and gene expression signatures in AciCCs are highly correlated with the NR4A3 transcription factor binding motif. Overexpression of NR4A3 in mouse salivary gland cells increases expression of known NR4A3 target genes and has a stimulatory functional effect on cell proliferation. We conclude that NR4A3 is upregulated through enhancer hijacking and has important oncogenic functions in AciCC.
EVALuna2:35381

Enhancing the Effect of Combination Therapy with the PARP Inhibitor Talazoparib and ionizing Radiation on Melanoma Cell Lines - Proebstle, Stephanie; Jost, Tina; Buerkel, F.; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36488

Erlangen Experience on radiosurgical Treatment for Trigeminal Neuralgia - Lettmaier, S.; Putz, Florian; Distel, Luitpold; Bischoff, B.; Bozhkov, Y.; Merkel, Andreas; Lambrecht, U.; Koca, S.; Fietkau, Rainer (2017)
EVALuna2:32886

Erlangen Experiences with Durvalumab Preservation Therapy after defnitive Radiochemotherapy in Patients with NSCLC: First Survival and Toxicity Data from clinical Routine - Lettmaier, Sebastian; Hecht, Markus; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Erratum to: DEGRO practical guidelines for radiotherapy of breast cancer V: Therapy for locally advanced and inflammatory breast cancer, as well as local therapy in cases with synchronous distant metastases - Budach, Wilfried; Matuschek, C.; Boelke, E.; Dunst, J.; Feyer, P.; Fietkau, Rainer; Haase, W.; Harms, W.; Piroth, Marc D.; Sautter-Bihl, M. -L.; Sedlmayer, F.; Souchon, R.; et al. (Strahlentherapie und Onkologie, 2015)
EVALuna2:18274

Erratum to: Primary glioblastoma multiforme tumors and recurrence: comparative analysis of the danger signals HMGB1, HSP70, and calreticulin - Muth, Carolin; Rubner, Yvonne; Semrau, Sabine; Rühle, Paul-Friedrich; Frey, Benjamin; Strnad, Annedore; Buslei, Rolf; Fietkau, Rainer; Gaipl, Udo (Strahlentherapie und Onkologie, 2016)
EVALuna2:7315

Error detection using an electromagnetic tracking system in multi-catheter breast interstitial brachytherapy - Masitho, Siti; Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Physics in Medicine and Biology, 2019)
The hybrid treatment delivery system (HTDS) has been proposed as a possible option for a quality assurance in the multi-catheter interstitial brachytherapy for breast cancer patients. The system, which consists out of a prototype afterloader with an integrated electromagnetic tracking (EMT) sensor and an EMT system, allows the automatic measurement of implanted catheters. To test the feasibility of the system for error detection, possible treatment planning errors and treatment delivery errors were simulated. Planning errors such as an incorrect offset value, an incorrect indexer length, tip/connector end swaps, and partial swaps, and; treatment delivery errors such as catheter shifts and catheter connection swaps were manually simulated using phantoms. An in-house Matlab routine was used to assess geometrical deviations between the dwell positions defined based on CT and EMT measurement. Additionally, the influence of implant motion on the detection ability of the system was assessed. An algorithm for the detection and specification of errors based on the error simulation results was developed. At the University Hospital Erlangen, a patient study is ongoing, where errors in patient data were analyzed using the proposed algorithm. All simulated planning errors were detected. Catheter connection swaps can be detected 100% of the time. A shift detection rate of >97% was observed for shifts larger than 1.1 mm, both in the static and the motion measurements. Catheter reconstruction uncertainties and catheter shifts <2 mm were found to be the most common treatment planning and delivery errors in patient data. HTDS proved to be a reliable method for error detection.
CRIS-Team Scopus Importer:2019-10-29

Error detection using an electromagnetic tracking system in multicatheter interstitial brachytherapy - Masitho, S.; Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Erste erfolgversprechende Ergebnisse der Kombination aus Strahlentherapie und Pembrolizumab beim metastasierten nichtkleinzelligen Lungenkarzinom - Hecht, Markus; Gaipl, Udo; Fietkau, Rainer (Strahlentherapie und Onkologie, 2020)
CRIS-Team Scopus Importer:2020-02-25

Essential role of radiation therapy for the treatment of pancreatic cancer : Novel study concepts and established treatment recommendations - Dobiasch, Sophie; Goerig, Nicole; Fietkau, Rainer; Combs, Stephanie E. (Strahlentherapie und Onkologie, 2018)
BACKGROUND: Pancreatic cancer is one of the most aggressive human tumors and the incidence has increased over the last 6 years. In the majority of cases the disease is already in an advanced stage at the time of diagnosis where surgery, the only curative treatment, is no longer an option and explains the still abysmal overall survival. The role of radiation therapy as treatment option for patients with pancreatic cancer is controversially discussed although radiation oncology has emerged as a central pillar in the combined oncological treatment. PURPOSE: The present manuscript gives an overview of advanced radiotherapeutic strategies in the context of chemotherapy and surgery according to the current American Society of Clinical Oncology (ASCO) guidelines in comparison with the German guidelines and to elucidate the role of radiation therapy for the treatment of pancreatic cancer. CONCLUSION: Advanced modern radiotherapeutic techniques in combination with individualized high-precision radiation concepts are new therapeutic approaches for pancreatic cancer in a multimodal setting with tolerable side effects. Several clinical studies together with experimental approaches are in process, to deliver further evidence and ultimately allow true personalized medicine.
EVALuna2:36445

Establishment of a FACS Assay for Screening of (TEMRA) Cells in Glioblastoma Patients - Scheer, I.; Becker, Ina; Donaubauer, Anna-Jasmina; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Establishment of a Multicolor Flow Cytometry Assay for Screening the NK Cells in Cancer Patients - Becker, Ina; Donaubauer, Anna-Jasmina; Multhoff, G.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Estimating follow-up CTs from geometric deformations of catheter implants in interstitial breast brachytherapy: A feasibility study using electromagnetic tracking - Dürrbeck, Christopher; Schulz, Moritz; Pflaum, Leonie; Kallis, Karoline; Geimer, Tobias; Abu-Hossin, Nadin; Strnad, Vratislav; Maier, Andreas; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2023)
Background: Electromagnetic tracking (EMT) systems have been shown to provide valuable information on the geometry of catheter implants in breast cancer patients undergoing interstitial brachytherapy (iBT). In the context of an extended patient-specific, pre-treatment verification, EMT can play a key role in determining the potential need and, if applicable, the appropriate time for treatment adaptation. To detect dosimetric shortcomings the relative position between catheters, and target volume and critical structures must be known. Since EMT cannot provide the anatomical context and standard imaging techniques such as cone-beam CT are not yet available in most brachytherapy suites, it is not possible to detect anatomic changes on a daily or fraction basis, so the need for adaptive planning cannot be identified. Purpose: The aim of this feasibility study is to develop and evaluate a technique capable of estimating follow-up CTs at any time based on the initial treatment planning CT (PCT) and surrogate information about changes of the implant geometry from an EMT system. Methods: A deformation vector field is calculated from two different implant reconstructions acquired in treatment position through EMT, the first immediately after the PCT and the second at another time point during the course of treatment. The calculation is based on discrete displacement vectors of pairs of control and target points. These are extrapolated by means of different radial basis functions in order to cover the entire CT volume. The adequate parameters for the calculation of the deformation field were identified. By warping the PCT according to the deformation field, one obtains an estimated CT (ECT) that reflects the geometric changes. For the proof of concept, ECTs were computed for the time point of the clinical follow-up CT (FCT) that is embedded in the treatment workflow after the fourth fraction. Results: ECT and clinical FCTs of 20 patients were compared to each other quantitatively in terms of absolute Hounsfield unit differences in the planning target volume (PTV) and in a convex hull (CH) enclosing the catheters. The median differences were 31.2 and 29.5 HU for the CH and the PTV, respectively. Conclusion: The proposed ECT approach was able to approximate the “anatomy of the day” and therefore, in principle, allows a dosimetric appraisal of the treatment plan quality before each fraction. In this way, it can contribute to a more detailed patient-specific quality assurance in iBT of the breast and help to identify the timing for a potential treatment adaptation.
CRIS-Team Scopus Importer:2023-08-25
Keywords: assurance; breast cancer; electromagnetic tracking; interstitial brachytherapy

Estimation of inter-fractional variations in interstitial multi-catheter breast brachytherapy using a hybrid treatment delivery system - Kallis, Karoline; Abu-Hossin, Nadin; Kreppner, Stephan; Lotter, Michael; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2019)
Purpose: Irradiation of the tumor bed using interstitial multi-catheter brachytherapy is one of the treatment options for breast cancer patients. In order to ensure the planned dose delivery an advanced quality intervention method using an electromagnetic tracking (EMT) system is presented. The system is used to assess inter-fractional variations within the framework of a patient study. Methods and materials: Until now 41 patients were included in the study for the evaluation and overall 355 EMT measurements were performed. The catheter traces are measured automatically and sequentially using an afterloader prototype (Flexitron, Elekta, Veenendaal, The Netherlands) equipped with an EMT sensor. The implant geometry is tracked directly after implantation, after CT imaging and after each irradiation fraction. The acquired data is rigidly registered to the catheter traces defined in the treatment plan and the dwell positions (DP) are reconstructed. DPs defined in treatment planning serve as reference. Breathing motion was corrected and recorded using three reference 6DoF sensors placed on the patients’ skin. The Euclidean distance between the planned and reconstructed DPs provides information about possible inter-fractional deviations. Further, the influence of various factors on the occurrence of large deviations was investigated, like the patients’ age, the length of the catheter, the breast volume, etc. Results: Over all patient measurements a median Euclidean distance of 2.19 mm was determined between the reconstructed DPs and the reference DPs. The median deviation combining all datasets was minimal (1.67 mm) at the measurement directly after CT imaging. The deviations between the different fractions have a median distance of 2.31 mm which could be improved to 2.05 mm by adapting the treatment plan according to the follow-up CT. No correlation between the distance to the skin, ribs, mammilla or the breast volume and the occurrences of large deviations was found. The largest deviations were determined in the upper inner quadrant of the breast. Conclusion: The afterloader prototype could be well integrated into the clinical routine and is beneficial for ensuring the quality of the brachytherapy. Overall, a small median DP deviation, lower than the used step size of 2.5 mm, was detected.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Breast cancer; Electromagnetic tracking; Inter-fractional variations; Interstitial multi-catheter brachytherapy

ESTRO-ACROP guideline on surface guided radiation therapy - Freislederer, P.; Batista, V.; Ollers, M.; Buschmann, Martin; Steiner, E.; Kugele, M.; Fracchiolla, F.; Corradini, S.; De Smet, M.; Moura, F.; Perryck, S.; Dionisi, F.; et al. (Radiotherapy and Oncology, 2022)
Surface guidance systems enable patient positioning and motion monitoring without using ionising radiation. Surface Guided Radiation Therapy (SGRT) has therefore been widely adopted in radiation therapy in recent years, but guidelines on workflows and specific quality assurance (QA) are lacking. This ESTROACROP guideline aims to give recommendations concerning SGRT roles and responsibilities and highlights common challenges and potential errors. Comprehensive guidelines for procurement, acceptance, commissioning, and QA of SGRT systems installed on computed tomography (CT) simulators, C-arm linacs, closed-bore linacs, and particle therapy treatment systems are presented that will help move to a consensus among SGRT users and facilitate a safe and efficient implementation and clinical application of SGRT. (c) 2022 The Author(s). Published by Elsevier B.V. Radiotherapy and Oncology xxx (2022) xxx-xxx This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
CRIS-Team WoS Importer:2022-07-29

European Association of Urology Guidelines on Muscle-invasive and Metastatic Bladder Cancer: Summary of the 2023 Guidelines - Alfred Witjes, J.; Max Bruins, Harman; Carrión, Albert; Cathomas, Richard; Compérat, Eva; Efstathiou, Jason A.; Fietkau, Rainer; Gakis, Georgios; Lorch, Anja; Martini, Alberto; Mertens, Laura S.; Meijer, Richard P.; et al. (European Urology, 2023)
Context: We present an overview of the updated 2023 European Association of Urology (EAU) guidelines for muscle-invasive and metastatic bladder cancer (MMIBC). Objective: To provide practical evidence-based recommendations and consensus statements on the clinical management of MMIBC with a focus on diagnosis and treatment. Evidence acquisition: A broad and comprehensive scoping exercise covering all areas of the MMIBC guidelines has been performed annually since 2017. Searches cover the Medline, EMBASE, and Cochrane Libraries databases for yearly guideline updates. A level of evidence and strength of recommendation are assigned. The evidence cutoff date for the 2023 MIBC guidelines was May 4, 2022. Evidence synthesis: Patients should be counselled regarding risk factors for bladder cancer. Pathologists should describe tumour and lymph nodes in detail, including the presence of histological subtypes. The importance of the presence or absence of urothelial carcinoma (UC) in the prostatic urethra is emphasised. Magnetic resonance imaging (MRI) of the bladder is superior to computed tomography (CT) for disease staging, specifically in differentiating T1 from T2 disease, and may lead to a change in treatment approach in patients at high risk of an invasive tumour. Imaging of the upper urinary tract, lymph nodes, and distant metastasis is performed with CT or MRI; the additional value of flurodeoxyglucose positron emission tomography/CT still needs to be determined. Frail and comorbid patients should be evaluated by a multidisciplinary team. Postoperative histology remains the most important prognostic variable, while circulating tumour DNA appears to be an interesting predictive marker. Neoadjuvant systemic therapy remains cisplatin-based. In motivated and selected women and men, sexual organ–preserving cystectomy results in better functional outcomes without compromising oncological outcomes. Robotic and open cystectomy have comparable outcomes and should be combined with (extended) lymph node dissection. The diversion type is an individual choice after taking patient and tumour characteristics into account. Radical cystectomy remains a highly complex procedure with considerable morbidity and risk of mortality, although lower rates are observed for higher hospital volumes (>20 cases/yr). With proper patient selection, trimodal therapy (chemoradiation) has comparable outcomes to radical cystectomy. Adjuvant chemotherapy after surgery improves disease-specific survival and overall survival (OS) in patients with high-risk disease who did not receive neoadjuvant treatment, and is strongly recommended. There is a weak recommendation for adjuvant nivolumab, as OS data are not yet available. Health-related quality of life should be assessed using validated questionnaires at baseline and after treatment. Surveillance is needed to monitor for recurrent cancer and functional outcomes. Recurrences detected on follow-up seem to have better prognosis than symptomatic recurrences. Conclusions: This summary of the 2023 EAU guidelines provides updated information on the diagnosis and treatment of MMIBC for incorporation into clinical practice. Patient summary: The European Association of Urology guidelines panel on muscle-invasive and metastatic bladder cancer has released an updated version of the guideline containing information on diagnosis and treatment of this disease. Recommendations are based on studies published up to May 4, 2022. Surgical removal of the bladder and bladder preservation are discussed, as well as updates on the use of chemotherapy and immunotherapy in localised and metastatic disease.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Bladder cancer; Evidenced-based; Guidelines; Metastatic; Muscle-invasive; Recommendations

Evaluating predictive modeling algorithms to assess patient eligibility for clinical trials from routine data - Köpcke, Felix; Lubgan, Dorota; Fietkau, Rainer; Scholler, Axel; Nau, Carla; Stürzl, Michael; Croner, Roland S.; Prokosch, Hans-Ulrich; Toddenroth, Dennis (BMC Medical Informatics and Decision Making, 2013)
Background: The necessity to translate eligibility criteria from free text into decision rules that are compatible with data from the electronic health record (EHR) constitutes the main challenge when developing and deploying clinical trial recruitment support systems. Recruitment decisions based on case-based reasoning, i.e. using past cases rather than explicit rules, could dispense with the need for translating eligibility criteria and could also be implemented largely independently from the terminology of the EHR's database. We evaluated the feasibility of predictive modeling to assess the eligibility of patients for clinical trials and report on a prototype's performance for different system configurations. Methods. The prototype worked by using existing basic patient data of manually assessed eligible and ineligible patients to induce prediction models. Performance was measured retrospectively for three clinical trials by plotting receiver operating characteristic curves and comparing the area under the curve (ROC-AUC) for different prediction algorithms, different sizes of the learning set and different numbers and aggregation levels of the patient attributes. Results: Random forests were generally among the best performing models with a maximum ROC-AUC of 0.81 (CI: 0.72-0.88) for trial A, 0.96 (CI: 0.95-0.97) for trial B and 0.99 (CI: 0.98-0.99) for trial C. The full potential of this algorithm was reached after learning from approximately 200 manually screened patients (eligible and ineligible). Neither block- nor category-level aggregation of diagnosis and procedure codes influenced the algorithms' performance substantially. Conclusions: Our results indicate that predictive modeling is a feasible approach to support patient recruitment into clinical trials. Its major advantages over the commonly applied rule-based systems are its independency from the concrete representation of eligibility criteria and EHR data and its potential for automation. © 2013 Köpcke et al.; licensee BioMed Central Ltd.
UnivIS-Import:2015-04-14:Pub.2013.tech.IMMD.infome.evalua_3

Evaluation of a dedicated Treatment Planning-MRI for Patients with cranial Stereotaxy - Grigo, Johanna; Masitho, Siti; Putz, Florian; Fietkau, Rainer; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Evaluation of a high-resolution 3D T2-SPACE-FLAIR Sequence in Comparison to the conventional 2D T2-FLAIR Sequence for the Contouring of low malignant Tumor Parts in cerebral Gliomas - Siavooshhaghighi, H.; Mengling, Veit; Masitho, Siti; Filimonova, Irina; Mansoorian, S.; Weissmann, T.; Bert, Christoph; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Evaluation of a markerless SGRT-only workflow for breast cancer patients - Sauer, Tim-Oliver; Popp, D.; Ott, O. J.; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-11-26

Evaluation of the influence of susceptibility-induced magnetic field distortions on the precision of contouring intracranial organs at risk for stereotactic radiosurgery - Mengling, Veit; Putz, Florian; Laun, Frederik Bernd; Perrin, Rosalind; Eisenhut, Felix; Dörfler, Arnd; Fietkau, Rainer; Bert, Christoph (Physics and Imaging in Radiation Oncology, 2020)
Background and purpose: Magnetic resonance imaging (MRI) is a crucial factor in optimal treatment planning for stereotactic radiosurgery. To further the awareness of possible errors in MRI, this work aimed to investigate the magnitude of susceptibility induced MRI distortions for intracranial organs at risk (OARs) and test the effectiveness of actively shimming these distortions. Materials and methods: Distortion maps for 45 exams of 42 patients (18 on a 1.5 T MRI scanner, 27 on a 3 T MRI scanner) were calculated based on a high-bandwidth double-echo gradient echo sequence. The investigated OARs were brainstem, chiasm, eyes, and optic nerves. The influence of active shimming was investigated by comparing unshimmed 1.5 T data with shimmed 3 T data and comparing the results to a model based prediction. Results: The median distortion for the different OARs was found to be between 0.13 and 0.18 mm for 1.5 T and between 0.11 and 0.13 mm for 3 T. The maximum distortion was found to be between 1.3 and 1.7 mm for 1.5 T and between 1.1 and 1.4 mm for 3 T. The variation of values was much higher for 1.5 T than for 3 T across all investigated OARs. Active shimming was found to reduce distortions by a factor of 2.3 to 2.9 compared to the expected values. Conclusions: Using a safety margin for OARs of 1 mm would have encompassed 99.8% of the distortions. Since distortions are inversely proportional to the readout bandwidth, they can be further reduced by increasing the bandwidth. Additional error sources like gradient nonlinearities need to be addressed separately.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Brain; MRI; PRV; Safety margins; Stereotactic; Susceptibility artifacts

Evaluation of the role of remission status in a heterogeneous limited disease small-cell lung cancer patient cohort treated with definitive chemoradiotherapy - Manapov, Farkhad; Niyazi, Maximilian; Gerum, Sabine; Roengvoraphoj, Olarn; Eze, Chukwuka; Li, Minglun; Hildebrandt, Guido; Fietkau, Rainer; Klautke, Gunther; Belka, Claus (BMC Cancer, 2016)
The role of remission status in limited disease (LD) small-cell lung cancer (SCLC) patients treated with definitive chemoradiotherapy (CRT) remains to be finally clarified.Individual data from 184 patients treated with definitive CRT concurrently or sequentially were retrospectively reviewed. Kaplan-Meier analysis as well as univariate and multivariate Cox regression models were used to describe survival within patient subgroups defined by remission status.71 (39%) patients were treated in the concurrent, 113 (61%) in the sequential CRT mode. Prophylactic cranial irradiation (PCI) was applied in 71 (39%) patients. 37 (20%) patients developed local, while 89 (48%) distant recurrence. 58 (32%) patients developed metachronous brain metastases. Complete, partial remission and non-response (defined as stable and progressive disease) were documented in 65 (35%), 77 (42%), and 37 (20%) patients, respectively. In complete responders median overall survival was 21.8 months (95CI: 18.6 - 25) versus 14.9 (95% CI: 11.7 - 18.2) (p = 0.041, log-rank test) and 11.5 months (95% CI: 8.9 - 15.0) (p < 0.001, log-rank test) in partial and non-responders, respectively. The same effect was documented for the time to progression and distant metastasis-free survival. In the multivariate analysis achievement of complete remission as a variable shows a trend for the prolonged time to progression (p = 0.1, HR 1.48) and distant metastasis-free survival (p = 0.06, HR 1.63) compared to partial responders and was highly significant compared to non-responders.In this treated heterogeneous LD SCLC patient cohort complete remission was associated with longer time to progression, distant metastasis-free and overall survival compared to the non- and especially partial responders.
EVALuna2:18335

Evidence for improved survival with bevacizumab treatment in recurrent high-grade gliomas: a retrospective study with ("pseudo-randomized") treatment allocation by the health insurance provider - Hofmann, Susanne; Schmidt, Manuel; Weissmann, Thomas; Eyüpoglu, Ilker Yasin; Strnad, Annedore; Semrau, Sabine; Fietkau, Rainer; Putz, Florian; Lettmaier, Sebastian (Journal of Neuro-Oncology, 2020)
Introduction Despite a large number of trials, the role of bevacizumab (BEV) in the treatment of recurrent high-grade gliomas is still controversial. Evidence regarding an effect on overall survival in this context is ultimately inconclusive. At the Department of Radiation Oncology at Erlangen, Germany we treated a large cohort of patients with recurrent gliomas where bevacizumab use was determined exclusively by the health care provider's approval of reimbursement. Methods 61 patients (between 06/2008 and 01/2014) with recurrent high-grade gliomas had reimbursement requests for BEV sent to their health insurance. 37 patients out of 61 (60.7%) had their requests approved and therefore received bevacizumab (BEV-arm) as part of their treatment. The remaining 24 (39.3%) patients received standard therapy without bevacizumab (non-BEV-arm). Survival endpoints were defined with reference to the first BEV request to the health insurance provider. Results Median overall survival (OS) for the whole cohort was 7.0 months. OS was significantly better for BEV vs. Non-BEV patients (median, 10.3 vs. 4.2 months, logrank p = 0.023). There was an increased BEV benefit in cases of higher-order recurrences (first order recurrence BEV vs. Non-BEV, 12.5 vs. 10.2 months, p = 0.578) (second or higher order of recurrence, 9.9 vs. 2.6 months, p = 0.010). On multivariate analysis for overall survival the prognostic impact of bevacizumab (HR = 0.43, p = 0.034) remained significant. Conclusion Our results suggest an influence of BEV on overall survival in a heavily pretreated patient population suffering from high-grade gliomas with BEV benefit being greatest in case of second or later recurrence.
CRIS-Team WoS Importer:2020-05-29

Examination of a deformable motion model for respiratory movements and 4D dose calculations using different driving surrogates - Wölfelschneider, Jens; Seregni, Matteo; Fassi, Aurora; Ziegler, Marc; Baroni, Guido; Fietkau, Rainer; Riboldi, Marco; Bert, Christoph (Medical Physics, 2017)
PURPOSE: The aim of this study was to evaluate a surrogate-driven motion model based on four-dimensional computed tomography that is able to predict CT volumes corresponding to arbitrary respiratory phases. Furthermore, the comparison of three different driving surrogates is examined and the feasibility of using the model for 4D dose re-calculation will be discussed. METHODS: The study is based on repeated 4DCTs of twenty patients treated for bronchial carcinoma and metastasis. The motion model was estimated from the planning 4DCT through deformable image registration. To predict a certain phase of a follow-up 4DCT, the model considers inter-fractional variations (baseline correction) and intra-fractional respiratory parameters (amplitude and phase) derived from surrogates. The estimated volumes resulting from the model were compared to ground-truth clinical 4DCTs using absolute HU differences in the lung region and landmarks localized using the Scale Invariant Feature Transform. Finally, the γ-index was used to evaluate the dosimetric effects of the intensity differences measured between the estimated and the ground-truth CT volumes. RESULTS: The results show absolute HU differences between estimated and ground-truth images with median value (± standard deviation) of (61.3 ± 16.7) HU. Median 3D distances, measured on about 400 matching landmarks in each volume, were (2.9 ± 3.0) mm. 3D errors up to 28.2 mm were found for CT images with artifacts or reduced quality. Pass rates for all surrogate approaches were above 98.9% with a γ-criterion of 2%/2 mm. CONCLUSION: The results depend mainly on the image quality of the initial 4DCT and the deformable image registration. All investigated surrogates can be used to estimate follow-up 4DCT phases, however, uncertainties decrease for volumetric approaches. Application of the model for 4D dose calculations is feasible.
EVALuna2:32902

Examination of Gold Marker Detection in Tracking Treatments of Liver Cancer Patients using Vero SBRT System - Ziegler, Marc; Brandt, Tobias; Lettmaier, S.; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (2018)
EVALuna2:36476

Examination of the automatic fiducial marker detection on the Vero system - Ziegler, Marc; Brandt, Tobias; Lettmaier, S.; Fietkau, Rainer; Bert, Christoph (2018)
EVALuna2:36478

Exclusive endocrine therapy or partial breast irradiation for women aged ≥70years with luminal A-like early stage breast cancer (NCT04134598 – EUROPA): Proof of concept of a randomized controlled trial comparing health related quality of life by patient reported outcome measures - Meattini, Icro; Poortmans, Philip M.P.; Marrazzo, Livia; Desideri, Isacco; Brain, Etienne; Hamaker, Marije; Lambertini, Matteo; Miccinesi, Guido; Russell, Nicola; Saieva, Calogero; Strnad, Vratislav; Visani, Luca; et al. (Journal of Geriatric Oncology, 2021)
Background: Postoperative radiation therapy after breast conserving surgery in the older adult population is a matter of debate; although radiation therapy was shown to benefit these patients concerning local disease control, the absolute benefit was small and potentially negligible. Partial breast irradiation has been introduced as an alternative treatment approach for low-risk patients. Older adult patients with early breast cancer constitute a unique population with regards to prognosis and potential comorbidities, thus minimizing treatment to maintain health-related quality of life (HRQoL) without compromising survival is extremely important. Estimates of the patient's risk of benefit and/or harm with treatment should be performed together with an assessment of baseline comorbidities, life expectancy, and care preferences. Published data suggest that radiation therapy or endocrine therapy alone resulted in excellent disease control in older women with early breast cancer, and that the combination of both treatments has less incremental benefit than expected. Conversely, the toxicity profile of endocrine therapy is well known, often significantly impacting long term HRQoL of these potentially frail patients. Methods: Patients older than 70 years receiving breast conserving surgery with T1N0, Luminal A-like tumors will be randomized to receive partial breast irradiation-alone or endocrine therapy-alone. The main objectives are to determine patient reported outcome measures in terms of HRQoL, as assessed by the EORTC QLQ-C30 using the global health status of patients, and to demonstrate a non-inferior local control rate between arms. Secondary endpoints are represented by individual scales from QLQ-C30 and module QLQ-BR45 scores; ELD14 questionnaire; geriatric COre DatasEt assessment; distant control rate, adverse events rates, breast cancer specific, and overall survival. Discussion: The EUROPA trial is a new randomized trial focused on older adults (≥70 years) affected by good prognosis primary breast cancer. Our assumption is that postoperative radiation therapy-alone avoids the long-term toxicity of endocrine therapy and favorably impacts on HRQoL in this population. In the current report we present the trial's background and methods, focusing on perspectives in the field of precision medicine. Trial registration: The trial is registered with ClinicalTrial.gov Identifier NCT04134598 / EUROPA trial.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Breast cancer; Endocrine therapy; Health-related quality of life; Older adult; Partial breast irradiation

Experience gained with Durvalumab Maintenance Therapy after definitive Chemoradiotherapy in Patients with NSCLC: Survival- and Toxicity Data from Routine clinical Practice - Lettmaier, S.; Hecht, Markus; Weissmann, Thomas; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Experimental investigation of irregular motion impact on 4D PET-based particle therapy monitoring. - Tian, Y.; Stuetzer, K.; Enghardt, W.; Priegnitz, M.; Helmbrecht, S.; Bert, Christoph; Fiedler, F. (Physics in Medicine and Biology, 2016)
Particle therapy positron emission tomography (PT-PET) is an in vivo and non-invasive imaging technique to monitor treatment delivery in particle therapy. The inevitable patient respiratory motion during irradiation causes artefacts and inaccurate activity distribution in PET images. Four-dimensional (4D) maximum likelihood expectation maximisation (4D MLEM) allows for a compensation of these effects, but has up to now been restricted to regular motion for PT-PET investigations. However, intra-fractional motion during treatment might differ from that during acquisition of the 4D-planning CT (e.g. amplitude variation, baseline drift) and therefore might induce inaccurate 4D PET reconstruction results. This study investigates the impact of different irregular analytical one-dimensional (1D) motion patterns on PT-PET imaging by means of experiments with a radioactive source and irradiated moving phantoms. Three sorting methods, namely phase sorting, equal amplitude sorting and event-based amplitude sorting, were applied to manage the PET list-mode data. The influence of these sorting methods on the motion compensating algorithm has been analysed. The event-based amplitude sorting showed a superior performance and it is applicable for irregular motions with ?4 mm amplitude elongation and drift. For motion with 10 mm baseline drift, the normalised root mean square error was as high as 10.5% and a 10 mm range deviation was observed.
EVALuna2:18310

Expert consensus on re-irradiation for recurrent glioma - Krauze, Andra; Attia, Albert; Braunstein, Steve; Chan, Michael; Combs, Stephanie; Fietkau, Rainer; Fiveash, John; Flickinger, John; Grosu, Anca-Ligia; Howard, Steven; Nieder, Carsten; Niyazi, Maximilian; et al. (Radiation Oncology, 2017)
PURPOSE: To investigate radiation oncologists' opinions on important considerations to offering re-irradiation (re-RT) as a treatment option for recurrent glioma. MATERIALS AND METHODS: A survey was conducted with 13 radiation oncologists involved in the care of central nervous system tumor patients. The survey was comprised of 49 questions divided into 2 domains: a demographic section (10 questions) and a case section (5 re-RT cases with 5 to 6 questions representing one or several re-RT treatment dilemmas as may be encountered in the clinic). Respondents were asked to rate the relevance of various factors to offering re-RT, respond to the cases with a decision to offer re-RT vs. not, volume to be treated, margins to be employed, dose/fractionation suggested and any additional comments with respect to rationale in each scenario. RESULTS: Sixty nine percent of responders have been practicing for greater than 10 years and 61% have re-RT 20 to 100 patients to date, with 54% seeing 2-5 re-RT cases per month and retreating 1-2 patients per month. Recurrent tumor volume, time since previous radiation therapy, previously administered dose to organs at risk and patient performance status were rated by the majority of responders (85%, 92%, 77%, and 69% respectively) as extremely relevant or very relevant to offering re-RT as an option. CONCLUSION: The experts' practice of re-RT is still heterogeneous, reflecting the paucity of high-quality prospective data available for decision-making. Nevertheless, practicing radiation oncologists can support own decisions by referring to the cases found suitable for re-RT in this survey.
EVALuna2:32866

Explainable convolutional neural networks for assessing head and neck cancer histopathology - Dörrich, Marion; Hecht, Markus; Fietkau, Rainer; Hartmann, Arndt; Iro, Heinrich; Gostian, Antoniu-Oreste; Eckstein, Markus; Kist, Andreas (Diagnostic Pathology, 2023)
Purpose: Although neural networks have shown remarkable performance in medical image analysis, their translation into clinical practice remains difficult due to their lack of interpretability. An emerging field that addresses this problem is Explainable AI. Methods: Here, we aimed to investigate the ability of Convolutional Neural Networks (CNNs) to classify head and neck cancer histopathology. To this end, we manually annotated 101 histopathological slides of locally advanced head and neck squamous cell carcinoma. We trained a CNN to classify tumor and non-tumor tissue, and another CNN to semantically segment four classes - tumor, non-tumor, non-specified tissue, and background. We applied Explainable AI techniques, namely Grad-CAM and HR-CAM, to both networks and explored important features that contributed to their decisions. Results: The classification network achieved an accuracy of 89.9% on previously unseen data. Our segmentation network achieved a class-averaged Intersection over Union score of 0.690, and 0.782 for tumor tissue in particular. Explainable AI methods demonstrated that both networks rely on features agreeing with the pathologist’s expert opinion. Conclusion: Our work suggests that CNNs can predict head and neck cancer with high accuracy. Especially if accompanied by visual explanations, CNNs seem promising for assisting pathologists in the assessment of cancer sections.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Classification; Explainable AI; Head and neck cancer; Histopathology; Semantic segmentation

Exploring the Capabilities and Limitations of Large Language Models for Radiation Oncology Decision Support - Putz, Florian; Haderlein, Marlen; Lettmaier, Sebastian; Semrau, Sabine; Fietkau, Rainer; Huang, Yixing (International Journal of Radiation Oncology Biology Physics, 2024)
Keywords: Large language model; GPT-4; Radiation Oncology

Expression of Immune Phenotypes in Rectal Cancer after neoadjuvant Chemoradiotherapy - Schnellhardt, Sören; Hirneth, Johannes; Büttner-Herold, Maike; Daniel, Christoph; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

External Beam Accelerated Partial Breast Irradiation in Early Breast Cancer and the Risk for Radiogenic Pneumonitis - Ott, Oliver; Stillkrieg, Wilhelm; Lambrecht, Ulrike; Sauer, Tim-Oliver; Schweizer, Claudia; Lamrani, Allison; Strnad, Vratislav; Hack, Caroline; Beckmann, Matthias; Uder, Michael; Fietkau, Rainer; Distel, Luitpold (Cancers, 2022)
Simple Summary Accelerated partial breast irradiation represents a well-established and safe treatment alternative for selected patients with early stage breast cancer after breast-conserving surgery. In a prospective trial on external beam partial breast irradiation, the risk for radiogenic pneumonitis is analyzed. After a median follow-up of 56 (1-129) months, radiogenic pneumonitis grade 2 appeared in only 1/170 (0.6%) patients. Compared to standard whole breast irradiation, the radiation doses applied to the lungs were very low. The patient with the radiogenic pneumonitis was found to have a generally increased radiation susceptibility. Using accelerated partial breast irradiation, the risk of radiogenic pneumonitis appeared quite low and may be limited to very exceptional cases associated with innate risk factors with an increased radiation susceptibility. In order to evaluate the risk for radiation-associated symptomatic pneumonitis in a prospective external beam accelerated partial breast irradiation (APBI) trial, between 2011 and 2021, 170 patients with early stage breast cancer were enclosed in the trial. Patients were eligible for study participation if they had a histologically confirmed breast cancer or an exclusive ductal carcinoma in situ (DCIS), a tumor size <= 3 cm, free safety margins >= 2 mm, no involved axillary lymph nodes, tumor bed clips, and were >= 50 years old. Patients received APBI with 38 Gy with 10 fractions in 10 consecutive working days. The trial was registered at the German Clinical Trials Registry, DRKS-ID: DRKS00004417. Median follow-up was 56 (1-129) months. Ipsilateral lung MLD, V20, and V30 were 4.3 +/- 1.4 Gy, 3.0 +/- 2.0%, and 1.0 +/- 1.0%, respectively. Radiogenic pneumonitis grade 2 appeared in 1/170 (0.6%) patients two months after radiotherapy. Ipsilateral MLD, V20, and V30 were 6.1 Gy, 7, and 3% in this patient. Additionally, individual radiosensitivity was increased in this specific patient. Compared to WBI, APBI leads to lower lung doses. Using APBI, the risk of symptomatic radiogenic pneumonitis is very low and may be limited, with an ipsilateral V20 < 3% to very exceptional cases associated with innate risk factors with an increased radiation susceptibility.
CRIS-Team WoS Importer:2022-08-12

External-Beam-Accelerated Partial-Breast Irradiation Reduces Organ-at-Risk Doses Compared to Whole-Breast Irradiation after Breast-Conserving Surgery - Ott, Oliver; Stillkrieg, Willy; Lambrecht, Ulrike; Schweizer, Claudia; Lamrani, Allison; Sauer, Tim-Oliver; Strnad, Vratislav; Bert, Christoph; Hack, Carolin; Beckmann, Matthias; Fietkau, Rainer (Cancers, 2023)
In order to evaluate organ-at-risk (OAR) doses in external-beam-accelerated partial-breast irradiation (APBI) compared to standard whole-breast irradiation (WBI) after breast-conserving surgery. Between 2011 and 2021, 170 patients with early breast cancer received APBI within a prospective institutional single-arm trial. The prescribed dose to the planning treatment volume was 38 Gy in 10 fractions on 10 consecutive working days. OAR doses for the contralateral breast, the ipsilateral, contralateral, and whole lung, the whole heart, left ventricle (LV), and the left anterior descending coronary artery (LAD), and for the spinal cord and the skin were assessed and compared to a control group with real-world data from 116 patients who underwent WBI. The trial was registered at the German Clinical Trials Registry, DRKS-ID: DRKS00004417. Compared to WBI, APBI led to reduced OAR doses for the contralateral breast (0.4 ± 0.6 vs. 0.8 ± 0.9 Gy, p = 0.000), the ipsilateral (4.3 ± 1.4 vs. 9.2 ± 2.5 Gy, p = 0.000) and whole mean lung dose (2.5 ± 0.8 vs. 4.9 ± 1.5 Gy, p = 0.000), the mean heart dose (1.6 ± 1.6 vs. 1.7 ± 1.4 Gy, p = 0.007), the LV V23 (0.1 ± 0.4 vs. 1.4 ± 2.6%, p < 0.001), the mean LAD dose (2.5 ± 3.4 vs. 4.8 ± 5.5 Gy, p < 0.001), the maximum spinal cord dose (1.5 ± 1.1 vs. 4.5 ± 5.7 Gy, p = 0.016), and the maximum skin dose (39.6 ± 1.8 vs. 49.1 ± 5.8 Gy, p = 0.000). APBI should be recommended to suitable patients to minimize the risk of secondary tumor induction and the incidence of consecutive major cardiac events.
CRIS-Team Scopus Importer:2023-08-25
Keywords: accelerated partial-breast irradiation; breast cancer; mean heart dose; mean lung dose; organs-at-risk

Extracranial temporal bone paragangliomas: Re-defining the role of otologic surgery within the scope of function-preserving multimodal concepts - Mantsopoulos, Konstantinos; Thimsen, Vivian; Eisenhut, Felix; Weissmann, Thomas; Putz, Florian; Fietkau, Rainer; Iro, Heinrich; Hornung, Joachim; Taha, Lava (American Journal of Otolaryngology, 2022)
Introduction: The aim of this study was to present our concept in the management of extracranial temporal bone paragangliomas and demonstrate the outcome after primary surgical management of the middle ear component, with an individualized indication for adjuvant radiotherapy. Materials and methods: The records of all patients treated for extracranial jugulotympanic paragangliomas by means of primary surgical management between 2010 and 2021 were studied retrospectively. Results: Twenty-nine patients made up our study sample (mean age 58.8 years). 15 cases were managed solely by means of surgery. Out of the remaining 14 cases with reduction of the middle ear component, adjuvant irradiation was performed in 11 cases, whereas a wait-and-scan strategy was adopted at the patient's request in three cases. No further growth was detected in our study cases. Conclusion: Our protocol seems to be associated with an acceptable quality of life and a satisfactory oncologic outcome.
CRIS-Team WoS Importer:2021-10-15

Ex Vivo Apoptosis in CD8+ Lymphocytes Predicts Rectal Cancer Patient Outcome - Winkler, Sebastian; Hoppe, Philipp; Haderlein, Marlen; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (Gastroenterology Research and Practice, 2016)
Background. Apoptotic rates in peripheral blood lymphocytes can predict radiation induced normal tissue toxicity. We studied whether apoptosis in lymphocytes has a prognostic value for therapy outcome. Methods. Lymphocytes of 87 rectal cancer patients were ex vivo irradiated with 2 Gy, 8 Gy, or a combination of 2 Gy ionizing radiation and Oxaliplatin. Cells were stained with Annexin V and 7-Aminoactinomycin D and apoptotic and necrotic rates were analyzed by multicolor flow cytometry. Results. After treatment, apoptotic and necrotic rates in CD8+ cells are consistently higher than in CD4+ cells, with lower corresponding necrotic rates. Apoptotic and necrotic rates of CD4+ cells and CD8+ cells correlated well within the 2 Gy, 8 Gy, and 2 Gy and Oxaliplatin arrangements (p <= 0.009). High apoptotic CD8+ rates after 2 Gy, 8 Gy, and 2 Gy + Oxaliplatin treatment were prognostically favorable for metastasis-free survival (p = 0.009, p = 0.038, and p = 0.009) and disease-free survival (p = 0.013, p = 0.098, and p = 0.013). Conclusions. Ex vivo CD8+ apoptotic rates are able to predict the patient outcome in regard to metastasis-free or disease-free survival. Patients with higher CD8+ apoptotic rates in the peripheral blood have a more favorable prognosis. In addition to the prediction of late-toxicity by utilization of CD4+ apoptotic rates, the therapy outcome can be predicted by CD8+ apoptotic rates.
EVALuna2:18338

Ex Vivo Chromosomal Radiosensitivity Testing in Patients with Pathological Germline Variants in Breast Cancer High-Susceptibility Genes BReast CAncer 1 and BReast CAncer 2 - Zuhair Kassem, Tara; Wunderle, Marius; Kuhlmann, Lukas; Rübner, Matthias; Hübner, Hanna; Hoyer, Juliane; Reis, André; Fasching, Peter; Beckmann, Matthias; Hack, Carolin; Fietkau, Rainer; Distel, Luitpold (Current Issues in Molecular Biology, 2023)
Background: Individual radiosensitivity is an important factor in the occurrence of undesirable consequences of radiotherapy. The potential for increased radiosensitivity has been linked to highly penetrant heterozygous mutations in DNA repair genes such as BRCA1 and BRCA2. By studying the chromosomal radiosensitivity of BRCA1/2 mutation carriers compared to the general population, we study whether increased chromosomal radiation sensitivity is observed in patients with BRCA1/2 variants. Methods: Three-color-fluorescence in situ hybridization was performed on ex vivo-irradiated peripheral blood lymphocytes from 64 female patients with a heterozygous germline BRCA1 or BRCA2 mutation. Aberrations in chromosomes #1, #2 and #4 were analyzed. Mean breaks per metaphase (B/M) served as the parameter for chromosomal radiosensitivity. The results were compared with chromosomal radiosensitivity in a cohort of generally healthy individuals and patients with rectal cancer or breast cancer. Results: Patients with BRCA1/2 mutations (n = 64; B/M 0.47) overall showed a significantly higher chromosomal radiosensitivity than general healthy individuals (n = 211; B/M 0.41) and patients with rectal cancer (n = 379; B/M 0.44) and breast cancer (n = 147; B/M 0.45) without proven germline mutations. Chromosomal radiosensitivity varied depending on the locus of the BRCA1/2 mutation. Conclusions: BRCA1/2 mutations result in slightly increased chromosomal sensitivity to radiation. A few individual patients have a marked increase in radiation sensitivity. Therefore, these patients are at a higher risk for adverse therapeutic consequences.
CRIS-Team Scopus Importer:2023-09-08
Keywords: BRCA1; BRCA2; breast cancer; chromosomal radiosensitivity; FISH assay; radiation oncology; radiation sensitivity testing; radiotherapy

Ex vivo Hyperthermia of B16 Melanoma and MCF-7/MDA-MB-231 Breast Cancer Cells by Hot Water or Microwave Irradiation in a Circulatory Process - Hader, Michael; Rosin, A.; Gekle, S.; Wadepohl, M.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Ex vivo radiosensitivity is increased in non-cancer patients taking valproate - Stritzelberger, Jenny; Lainer, Jennifer; Gollwitzer, Stefanie; Graf, Wolfgang; Jost, Tina; Lang, Johannes; Müller, Tamara; Schwab, Stefan; Fietkau, Rainer; Hamer, Hajo; Distel, Luitpold (BMC Neurology, 2020)
Background: Valproate (VPA) is a commonly prescribed antiepileptic drug for patients experiencing epileptic seizures due to brain tumors. VPA increases radiation sensitivity in various tumor cells in vitro due to complex mechanisms. This could make tumors more vulnerable to ionizing radiation or overcome radioresistance. Yet, clinical data on possible improvement of tumor control by adding VPA to tumor therapy is controversial. Potentially radiosensitizing effects of VPA on healthy tissue remain unclear. To determine individual radiosensitivity, we analyzed blood samples of individuals taking VPA. Methods: Ex vivo irradiated blood samples of 31 adult individuals with epilepsy were studied using 3-color fluorescence in situ hybridization. Aberrations in chromosomes 1, 2 and 4 were analyzed. Radiosensitivity was determined by the mean breaks per metaphase (B/M) and compared to age-matched (2:1) healthy donors. Results: The patient cohort (n = 31; female: 38.7%) showed an increase of their average B/M value compared to healthy individuals (n = 61; female: 56.9%; B/M: 0.480 ± 0.09 vs. 0.415 ± 0.07; p =.001). The portion of radiosensitive (B/M > 0.500) and distinctly radiosensitive individuals (B/M > 0.600) was increased in the VPA group (54.9% vs. 11.3 and 9.7% vs. 0.0%; p <.001). In 3/31 patients, radiosensitivity was determined prior to and after VPA treatment and radiosensitivity was increased by VPA-treatment. Conclusions: In our study, we confirmed that patients treated with VPA had an increased radiosensitivity compared to the control group. This could be considered in patients taking VPA prior to the beginning of radiotherapy to avoid toxic side effects of VPA-treatment.
CRIS-Team Scopus Importer:2020-11-06
Keywords: 3-colour fluorescence-in-situ-hybridization; Breaks per metaphase; Individual radiosensitivity; Valproate

F18-FDG PET/CT imaging early predicts pathologic complete response to induction chemoimmunotherapy of locally advanced head and neck cancer: preliminary single-center analysis of the checkrad-cd8 trial - Beck, Michael; Hartwich, J.; Eckstein, Markus; Schmidt, D.; Gostian, Antoniu-Oreste; Müller-Hübner, Sarina; Rutzner, Sandra; Gaipl, Udo; Von Der Gruen, J.; Illmer, T.; Hautmann, M. G.; Klautke, G.; et al. (Annals of Nuclear Medicine, 2022)
Aim: In the CheckRad-CD8 trial patients with locally advanced head and neck squamous cell cancer are treated with a single cycle of induction chemo-immunotherapy (ICIT). Patients with pathological complete response (pCR) in the re-biopsy enter radioimmunotherapy. Our goal was to study the value of F-18-FDG PET/CT in the prediction of pCR after induction therapy. Methods: Patients treated within the CheckRad-CD8 trial that additionally received FDG- PET/CT imaging at the following two time points were included: 3–14 days before (pre-ICIT) and 21–28 days after (post-ICIT) receiving ICIT. Tracer uptake in primary tumors (PT) and suspicious cervical lymph nodes (LN +) was measured using different quantitative parameters on EANM Research Ltd (EARL) accredited PET reconstructions. In addition, mean FDG uptake levels in lymphatic and hematopoietic organs were examined. Percent decrease (Δ) in FDG uptake was calculated for all parameters. Biopsy of the PT post-ICIT acquired after FDG-PET/CT served as reference. The cohort was divided in patients with pCR and residual tumor (ReTu). Results: Thirty-one patients were included. In ROC analysis, ΔSUVmax PT performed best (AUC = 0.89) in predicting pCR (n = 17), with a decline of at least 60% (sensitivity, 0.77; specificity, 0.93). Residual SUVmax PT post-ICIT performed best in predicting ReTu (n = 14), at a cutpoint of 6.0 (AUC = 0.91; sensitivity, 0.86; specificity, 0.88). Combining two quantitative parameters (ΔSUVmax ≥ 50% and SUVmax PT post-ICIT ≤ 6.0) conferred a sensitivity of 0.81 and a specificity of 0.93 for determining pCR. Background activity in lymphatic organs or uptake in suspected cervical lymph node metastases lacked significant predictive value. Conclusion: FDG-PET/CT can identify patients with pCR after ICIT via residual FDG uptake levels in primary tumors and the related changes compared to baseline. FDG-uptake in LN + had no predictive value. Trial registry: ClinicalTrials.gov identifier: NCT03426657.
CRIS-Team Scopus Importer:2022-05-20
Keywords: FDG-PET/CT; Head neck cancer; HNSCC; Immunotherapy; Induction therapy

Factors influencing downstaging after neoadjuvant long-course chemoradiotherapy in rectal carcinoma - Kohl, Valerie; Weber, Klaus; Brunner, Maximilian; Geppert, Carol-Immanuel; Fietkau, Rainer; Grützmann, Robert; Semrau, Sabine; Merkel, Susanne (International Journal of Colorectal Disease, 2022)
Purpose This single-centre cohort study was designed to identify factors that can predict primary tumour downstaging by neoadjuvant chemoradiotherapy (nCRT) in rectal carcinoma. Methods Prospectively collected data from 555 patients with clinical T category (cT) cT3-4 rectal carcinoma treated between 1995 and 2019 were retrospectively analysed. All patients received long-term neoadjuvant chemoradiotherapy followed by surgery with curative intent at the Department of Surgery, University Hospital Erlangen, Germany. Patient-, tumour- and treatment-related factors with a potential impact on the downstaging of rectal carcinoma to pathological T category (pT) ≤ ypT2 and ypT0 were analysed in univariate and multivariate logistic regression analyses. The prognosis of patients with and without downstaging of the primary tumour was compared. Results A total of 288 (51.9%) patients showed downstaging to ≤ ypT2. Eighty-six (15.5%) patients achieved clinical complete regression (ypT0). In the multivariate logistic regression analysis, the factors cT category, BMI, ECOG score, CEA, histological type, extension in the rectum and year of the start of treatment were found to be independent factors for predicting downstaging to ≤ ypT2 after neoadjuvant chemoradiotherapy. The year of treatment initiation also remained an independent significant predictor for pathological complete regression. The prognosis was superior in patients with downstaging to ≤ ypT2 in terms of locoregional and distant recurrence as well as disease-free and overall survival. Conclusion Factors predicting downstaging after long-term nCRT could be identified. This may be helpful for counselling patients and selecting the optimal treatment for patients with advanced rectal carcinoma.
CRIS-Team WoS Importer:2022-05-27
Keywords: Rectal carcinoma; Neoadjuvant chemoradiotherapy; Downstaging; Tumour regression; Prediction of pathological response; Prognostic factors

Fast optimization and dose calculation in scanned ion beam therapy - Hild, S.; Graeff, Christian; Trautmann, J.; Kraemer, M.; Zink, Klemens; Durante, Marco; Bert, Christoph (Medical Physics, 2014)
Particle therapy (PT) has advantages over photon irradiation on static tumors. An increased biological effectiveness and active target conformal dose shaping are strong arguments for PT. However, the sensitivity to changes of internal geometry complicates the use of PT for moving organs. In case of interfractionally moving objects adaptive radiotherapy (ART) concepts known from intensity modulated radiotherapy (IMRT) can be adopted for PT treatments. One ART strategy is to optimize a new treatment plan based on daily image data directly before a radiation fraction is delivered [treatment replanning (TRP)]. Optimizing treatment plans for PT using a scanned beam is a time consuming problem especially for particles other than protons where the biological effective dose has to be calculated. For the purpose of TRP, fast optimization and fast dose calculation have been implemented into the GSI in-house treatment planning system (TPS) TRiP98.This work reports about the outcome of a code analysis that resulted in optimization of the calculation processes as well as implementation of routines supporting parallel execution of the code. To benchmark the new features, the calculation time for therapy treatment planning has been studied.Compared to the original version of the TPS, calculation times for treatment planning (optimization and dose calculation) have been improved by a factor of 10 with code optimization. The parallelization of the TPS resulted in a speedup factor of 12 and 5.5 for the original version and the code optimized version, respectively. Hence the total speedup of the new implementation of the authors' TPS yielded speedup factors up to 55.The improved TPS is capable of completing treatment planning for ion beam therapy of a prostate irradiation considering organs at risk in this has been overseen in the review process. Also see below 6 min.
EVALuna2:18191

Fast SAR-Scans of Interstitial Microwave Dipole Antennas in a Muscle Equivalent Water Phantom - Erb, J.; Engelbrecht, Rainer; Schaller, Gerhard; Roos, D.; Seegenschmiedt, Heinrich; Fietkau, Rainer; Sauer, R. (41st Ann. Meeting of the Radiation Research Society and the 13th Annual Meeting of the North American Hyperthermia Society, 1993)
UnivIS-Import:2015-04-16:Pub.1993.tech.IE.LEH.fastsa

Favorable radiation field decrease in gastric marginal zone lymphoma Experience of the German Study Group on Gastrointestinal Lymphoma (DSGL) - Reinartz, Gabriele; Pyra, Regina P.; Lenz, Georg; Liersch, Rudiger; Stueben, Georg; Micke, Oliver; Willborn, Kay; Hess, Clemens F.; Probst, Andreas; Fietkau, Rainer; Jany, Ralf; Schultze, Juergen; et al. (Strahlentherapie und Onkologie, 2019)
Purpose Long-term impact of stage-adapted field reduction in a large cohort of gastric marginal zone lymphoma (gMZL) patients treated conservatively with curative radiation therapy (RT).
CRIS-Team WoS Importer:2019-06-07

Feasibility of artificial-intelligence-based synthetic computed tomography in a magnetic resonance-only radiotherapy workflow for brain radiotherapy: Two-way dose validation and 2D/2D kV-image-based positioning - Masitho, Siti; Szkitsak, Juliane; Grigo, Johanna; Fietkau, Rainer; Putz, Florian; Bert, Christoph (Physics and Imaging in Radiation Oncology, 2022)
Background and purpose: Magnetic Resonance Imaging (MRI)-only workflow eliminates the MRI-computed tomography (CT) registration inaccuracy, which degrades radiotherapy (RT) treatment accuracy. For an MRI-only workflow MRI sequences need to be converted to synthetic-CT (sCT). The purpose of this study was to evaluate a commercially available artificial intelligence (AI)-based sCT generation for dose calculation and 2D/2D kV-image daily positioning for brain RT workflow. Materials and methods: T1-VIBE DIXON was acquired at the 1.5 T MRI for 26 patients in RT setup for sCTs generation. For each patient, a volumetric modulated arc therapy (VMAT) plan was optimized on the CT, then recalculated on the sCT; and vice versa. sCT-based digitally reconstructed radiographs (DRRs) were fused with stereoscopic X-ray images recorded as image guidance for clinical treatments. Dosimetric differences between planned/recalculated doses and the differences between the calculated and recorded clinical couch shift/rotation were evaluated. Results: Mean ΔD50 between planned/recalculated doses for target volumes ranged between −0.2 % and 0.2 %; mean ΔD50 and ΔD0.01ccm were −0.6 % and 1.6 % and −1.4 % and 1.0 % for organ-at-risks, respectively. Differences were tested for clinical equivalence using intervals ±2 % (dose), ±1mm (translation), and ±1° (rotation). Dose equivalence was found using ±2 % interval (p < 0.001). The median differences between lat./long./vert. couch shift between CT-based/sCT-based DRRs were 0.3 mm/0.2 mm/0.3 mm (p < 0.05); median differences between lat./long./vert. couch rotation were −1.5°/0.1°/0.1° (after improvement of RT setup: −0.4°/−0.1°/−0.4°, p < 0.05). Conclusions: This in-silico study showed that the AI-based sCT provided equivalent results to the CT for dose calculation and daily stereoscopic X-ray positioning when using an optimal RT setup during MRI acquisition.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Artificial intelligence; Brain radiotherapy; kV-image-based positioning; MRI-only workflow; Synthetic CT

Feasibility of daily kV-Recording-based Positioning by using DRRs from an AI-based synthetic CT for MR-only intracranial Stereotactic Radiotherapy - Masitho, Siti; Grigo, Johanna; Szkitsak, Juliane; Reissig, L.; Fietkau, Rainer; Putz, Florian; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Feasibility Study on Cardiac Arrhythmia Ablation Using High-Energy Heavy Ion Beams - Lehmann, H. Immo; Graeff, Christian; Simoniello, Palma; Constantinescu, Anna; Takami, Mitsuru; Lugenbiel, Patrick; Richter, Daniel; Eichhorn, Anna; Prall, Matthias; Kaderka, Robert; Fiedler, Fine; Helmbrecht, Stephan; et al. (Scientific Reports, 2016)
High-energy ion beams are successfully used in cancer therapy and precisely deliver high doses of ionizing radiation to small deep-seated target volumes. A similar noninvasive treatment modality for cardiac arrhythmias was tested here. This study used high-energy carbon ions for ablation of cardiac tissue in pigs. Doses of 25, 40, and 55 Gy were applied in forced-breath-hold to the atrioventricular junction, left atrial pulmonary vein junction, and freewall left ventricle of intact animals. Procedural success was tracked by (1.) in-beam positron-emission tomography (PET) imaging; (2.) intracardiac voltage mapping with visible lesion on ultrasound; (3.) lesion outcomes in pathohistolgy. High doses (40-55 Gy) caused slowing and interruption of cardiac impulse propagation. Target fibrosis was the main mediator of the ablation effect. In irradiated tissue, apoptosis was present after 3, but not 6 months. Our study shows feasibility to use high-energy ion beams for creation of cardiac lesions that chronically interrupt cardiac conduction.
EVALuna2:33045

FEN1 Inhibition as a Potential Novel Targeted Therapy against Breast Cancer and the Prognostic Relevance of FEN1 - Berfelde, Johanna; Hildebrand, Laura; Kuhlmann, Lukas; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2024)
To improve breast cancer treatment and to enable new strategies for therapeutic resistance, therapeutic targets are constantly being studied. Potential targets are proteins of DNA repair and replication and genomic integrity, such as Flap Endonuclease 1 (FEN1). This study investigated the effects of FEN1 inhibitor FEN1-IN-4 in combination with ionizing radiation on cell death, clonogenic survival, the cell cycle, senescence, doubling time, DNA double-strand breaks and micronuclei in breast cancer cells, breast cells and healthy skin fibroblasts. Furthermore, the variation in the baseline FEN1 level and its influence on treatment prognosis was investigated. The cell lines show specific response patterns in the aspects studied and have heterogeneous baseline FEN1 levels. FEN1-IN-4 has cytotoxic, cytostatic and radiosensitizing effects, expressed through increasing cell death by apoptosis and necrosis, G2M share, senescence, double-strand breaks and a reduced survival fraction. Nevertheless, some cells are less affected by the cytotoxicity and fibroblasts show a rather limited response. In vivo, high FEN1 mRNA expression worsens the prognosis of breast cancer patients. Due to the increased expression in breast cancer tissue, FEN1 could represent a new tumor and prognosis marker and FEN1-IN-4 may serve as a new potent agent in personalized medicine and targeted breast cancer therapy.
CRIS-Team Scopus Importer:2024-03-08
Keywords: apoptosis; breast cancer cell lines; FEN1; FEN1 inhibition; FEN1-IN-4; ionizing radiation; necrosis; radiosensitivity; targeted therapy; TNBC

Fibroblast-like Synoviocytes show Gender and Inflammatory Status-specific Responses on the Treatment with low-dose X-ray Therapy - Deloch, Lisa; Rueckert, M.; Piltz, M.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

First clinical evaluation of breathing controlled four-dimensional computed tomography imaging - Szkitsak, Juliane; Werner, René; Fernolendt, Susanne; Schwarz, Annette; Ott, Oliver; Fietkau, Rainer; Hofmann, Christian; Bert, Christoph (Physics and Imaging in Radiation Oncology, 2021)
Background and Purpose: Four-dimensional computed tomography (4DCT) has become an essential part of radiotherapy planning but is often affected by artifacts. A new breathing controlled 4DCT (i4DCT) algorithm has been introduced. This study aims to present the first clinical data and to evaluate the achieved image quality, projection data coverage and beam-on time. Material & Methods: The analysis included i4DCT data for 129 scans of patients with thoracic tumors. Projection data coverage and beam-on time were evaluated. Additionally, image quality was exemplarily discussed and rated by ten clinical experts with a 5-score-scale for 30 patients with large variations in their breathing pattern (‘challenging subgroup’). Rated images were reconstructed amplitude- and phase-based. Results: Expert scoring revealed that 78% (amplitude-based) and 63% (phase-based) of the challenging subgroup were artifact-free (rating ≥4). For the entire cohort, average beam-on time per couch position was 4.9 ± 1.6 s. For the challenging subgroup, time increased slightly but not significantly compared to the remaining patients (5.1 s vs. 4.9 s; p = 0.64). Median projection data coverage was 93% and 94% for inhalation and exhalation, respectively, for the entire cohort. The comparison for the subgroup and the remaining patients revealed a small but significant decrease of the median coverage values for the challenging cases (inhalation: 90% vs. 94%, p = 0.02; exhalation: 93% vs. 94%, p = 0.02). Conclusions: This first clinical evaluation of i4DCT shows very promising results in terms of image quality and projection data coverage. The results agree with and support the results of previous i4DCT phantom studies.
CRIS-Team Scopus Importer:2021-11-12
Keywords: 4DCT; Motion artifacts; Respiratory motion

First clinical experience with a novel, mobile cone-beam CT system for treatment quality assurance in brachytherapy - Karius, Andre; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Bert, Christoph (Strahlentherapie und Onkologie, 2022)
Background and purpose: On-site cone-beam computed tomography (CBCT) has gained in importance in adaptive brachytherapy during recent years. Besides treatment planning, there is increased need particularly for image-guidance during interventional procedures and for image-guided treatment quality assurance (QA). For this purpose, an innovative CBCT device was rolled out at our hospital as the first site worldwide. We present the first clinical images and experiences. Materials and methods: The novel CBCT system is constructed of a 121 cm diameter ring gantry, and features a 43.2 × 43.2 cm2 flat-panel detector, wireless remote-control via tablet-PC, and battery-powered maneuverability. Within the first months of clinical operation, we performed CBCT-based treatment QA for a total of 26 patients (8 with breast, 16 with cervix, and 2 with vaginal cancer). CBCT scans were analyzed regarding potential movements of implanted applicators in-situ during the brachytherapy course. Results: With the presented device, treatment QA was feasible for the majority of patients. The CBCT scans of breast patients showed sufficient contrast between implanted catheters and tissue. For gynecologic patients, a distinct visualization of applicators was achieved in general. However, reasonable differentiations of organic soft tissues were not feasible. Conclusion: The CBCT system allowed basic treatment QA measures for breast and gynecologic patients. For image-guidance during interventional brachytherapy procedures, the current image quality is not adequate. Substantial performance enhancements are required for intraoperative image-guidance.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Adaptive brachytherapy; Gynecologic brachytherapy; Image-guidance; Mobile imaging; On-site computed tomography imaging

First Erlang Experience with Durvalumab Maintenance Therapy after definitive Radiochemotherapy in Patients with NSCLC - Lettmaier, S.; Hecht, Markus; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

First implementation of an innovative infra-red camera system integrated into a mobile CBCT scanner for applicator tracking in brachytherapy—Initial performance characterization - Karius, Andre; Leifeld, Lisa Marie; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2024)
Purpose: To enable a real-time applicator guidance for brachytherapy, we used for the first time infra-red tracking cameras (OptiTrack, USA) integrated into a mobile cone-beam computed tomography (CBCT) scanner (medPhoton, Austria). We provide the first description of this prototype and its performance evaluation. Methods: We performed assessments of camera calibration and camera-CBCT registration using a geometric calibration phantom. For this purpose, we first evaluated the effects of intrinsic parameters such as camera temperature or gantry rotations on the tracked marker positions. Afterward, calibrations with various settings (sample number, field of view coverage, calibration directions, calibration distances, and lighting conditions) were performed to identify the requirements for achieving maximum tracking accuracy based on an in-house phantom. The corresponding effects on camera-CBCT registration were determined as well by comparing tracked marker positions to the positions determined via CBCT. Long-term stability was assessed by comparing tracking and a ground-truth on a weekly basis for 6 weeks. Results: Robust tracking with positional drifts of 0.02 ± 0.01 mm was feasible using the system after a warm-up period of 90 min. However, gantry rotations affected the tracking and led to inaccuracies of up to 0.70 mm. We identified that 4000 samples and full coverage were required to ensure a robust determination of marker positions and camera-CBCT registration with geometric deviations of 0.18 ± 0.03 mm and 0.42 ± 0.07 mm, respectively. Long-term stability showed deviations of more than two standard deviations from the initial calibration after 3 weeks. Conclusion: We implemented for the first time a standalone combined camera-CBCT system for tracking in brachytherapy. The system showed high potential for establishing corresponding workflows.
CRIS-Team Scopus Importer:2024-05-03
Keywords: brachytherapy; combined camera-CT system; infra-red applicator tracking; system characterization

First Steps Toward Ultrasound-Based Motion Compensation for Imaging and Therapy: Calibration with an Optical System and 4D PET Imaging - Schwaab, Julia; Kurz, Christopher; Sarti, Cristina; Bongers, Andre; Schoenahl, Frederic; Bert, Christoph; Debus, Juergen; Parodi, Katia; Jenne, Juergen Walter (Frontiers in Oncology, 2015)
Target motion, particularly in the abdomen, due to respiration or patient movement is still a challenge in many diagnostic and therapeutic processes. Hence, methods to detect and compensate this motion are required. Diagnostic ultrasound (US) represents a non-invasive and dose-free alternative to fluoroscopy, providing more information about internal target motion than respiration belt or optical tracking. The goal of this project is to develop an US-based motion tracking for real-time motion correction in radiation therapy and diagnostic imaging, notably in 4D positron emission tomography (PET). In this work, a workflow is established to enable the transformation of US tracking data to the coordinates of the treatment delivery or imaging system - even if the US probe is moving due to respiration. It is shown that the US tracking signal is equally adequate for 4D PET image reconstruction as the clinically used respiration belt and provides additional opportunities in this concern. Furthermore, it is demonstrated that the US probe being within the PET field of view generally has no relevant influence on the image quality. The accuracy and precision of all the steps in the calibration workflow for US tracking-based 4D PET imaging are found to be in an acceptable range for clinical implementation. Eventually, we show in vitro that an US-based motion tracking in absolute room coordinates with a moving US transducer is feasible.
EVALuna2:18367

Four-dimensional patient dose reconstruction for scanned ion beam therapy of moving liver tumors - Richter, Daniel; Saito, Nami; Chaudhri, Naved; Haertig, Martin; Ellerbrock, Malte; Jaekel, Oliver; Combs, Stephanie E.; Habermehl, Daniel; Herfarth, Klaus; Durante, Marco; Bert, Christoph (International Journal of Radiation Oncology Biology Physics, 2014)
Estimation of the actual delivered 4-dimensional (4D) dose in treatments of patients with mobile hepatocellular cancer with scanned carbon ion beam therapy.Six patients were treated with 4 fractions to a total relative biological effectiveness (RBE)-weighted dose of 40 Gy (RBE) using a single field. Respiratory motion was addressed by dedicated margins and abdominal compression (5 patients) or gating (1 patient). 4D treatment dose reconstructions based on the treatment records and the measured motion monitoring data were performed for the single-fraction dose and a total of 17 fractions. To assess the impact of uncertainties in the temporal correlation between motion trajectory and beam delivery sequence, 3 dose distributions for varying temporal correlation were calculated per fraction. For 3 patients, the total treatment dose was formed from the fractional distributions using all possible combinations. Clinical target volume (CTV) coverage was analyzed using the volumes receiving at least 95% (V95) and 107% (V107) of the planned doses.4D dose reconstruction based on daily measured data is possible in a clinical setting. V95 and V107 values for the single fractions ranged between 72% and 100%, and 0% and 32%, respectively. The estimated total treatment dose to the CTV exhibited improved and more robust dose coverage (mean V95 > 87%, SD < 3%) and overdose (mean V107 < 4%, SD < 3%) with respect to the single-fraction dose for all analyzed patients.A considerable impact of interplay effects on the single-fraction CTV dose was found for most of the analyzed patients. However, due to the fractionated treatment, dose heterogeneities were substantially reduced for the total treatment dose. 4D treatment dose reconstruction for scanned ion beam therapy is technically feasible and may evolve into a valuable tool for dose assessment.
EVALuna2:18188

Fractionated LINAC-SBRT for Adrenal Gland Metatases: Dose-Dependence of Therapy Results - Knippen, S.; Burjakow, K.; Putz, Florian; Achterberg, N.; Lettmaier, S.; Fietkau, Rainer (2018)
EVALuna2:36502

Fractionated radiotherapy is the main stimulus for the induction of cell death and of Hsp70 release of p53 mutated glioblastoma cell lines - Rubner, Yvonne; Muth, Carolin; Strnad, Annedore; Derer, Anja; Sieber, Renate; Buslei, Rolf; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (Radiation Oncology, 2014)
Glioblastoma multiforme (GBM) is the most common primary brain tumor in adults. Despite a multimodal therapy consisting of resection followed by fractionated radiotherapy (RT) combined with the chemotherapeutic agent (CT) temozolomide (TMZ), its recurrence is almost inevitable. Since the immune system is capable of eliminating small tumor masses, a therapy should also aim to stimulate anti-tumor immune responses by induction of immunogenic cell death forms. The histone deacetylase inhibitor valproic acid (VPA) might foster this.Reflecting therapy standards, we applied in our in vitro model fractionated RT with a single dose of 2Gy and clinically relevant concentrations of CT. Not only the impact of RT and/or CT with TMZ and/or VPA on the clonogenic potential and cell cycle of the glioblastoma cell lines T98G, U251MG, and U87MG was analyzed, but also the resulting cell death forms and release of danger signals such as heat-shock protein70 (Hsp70) and high-mobility group protein B1 (HMGB1).The clonogenic assays revealed that T98G and U251MG, having mutated tumor suppressor protein p53, are more resistant to RT and CT than U87MG with wild type (WT) p53. In all glioblastoma cells lines, fractionated RT induced a G2 cell cycle arrest, but only in the case of U87MG, TMZ and/or VPA alone resulted in this cell cycle block. Further, fractionated RT significantly increased the number of apoptotic and necrotic tumor cells in all three cell lines. However, only in U87MG, the treatment with TMZ and/or VPA alone, or in combination with fractionated RT, induced significantly more cell death compared to untreated or irradiated controls. While necrotic glioblastoma cells were present after VPA, TMZ especially led to significantly increased amounts of U87MG cells in the radiosensitive G2 cell cycle phase. While CT did not impact on the release of Hsp70, fractionated RT resulted in significantly increased extracellular concentrations of Hsp70 in p53 mutated and WT glioblastoma cells.Our results indicate that fractionated RT is the main stimulus for induction of glioblastoma cell death forms with immunogenic potential. The generated tumor cell microenvironment might be beneficial to include immune therapies for GBM in the future.
EVALuna2:7235

Fractionated SBRT for adrenal metastasis: contributing to local tumor control with modest toxicity - Knippen, S.; Burjakow, K.; Putz, Florian; Knippen, A.; Achterberg, N.; Lettmaier, S.; Fietkau, Rainer (2018)
EVALuna2:36514

Fractionated stereotactic radiation therapy for adrenal metastases: contributing to local tumor control with low toxicity - Burjakow, Kim; Fietkau, Rainer; Putz, Florian; Achterberg, Nils; Lettmaier, Sebastian; Knippen, Stefan (Strahlentherapie und Onkologie, 2019)
PurposeTo report on the Erlangen (UK-Er) experience with linear accelerator stereotactic body radiation therapy (LINAC SBRT) for adrenal metastasis from various primary tumors.Materials and methods33patients were treated. Primary sites included lung (n=19), melanoma (n=8), colorectal (n=2), hepatocellular (n=1), esophageal (n=2), and breast cancer (n=1). 14patients were treated palliatively, 19patients were treated with local curative intent.Radiation treatmentTreatment planning was done based on an exhale, mid-ventilation, and inspiration CT series. Further planning CTs were done to check for the correctness of the breathing pattern. Irradiation was performed using aNOVALIS (Varian, Palo Alto, CA, USA; Brainlab AG, Munchen, Germany) linear accelerator. The isocenter was verified before each treatment session using the BrainLab ExacTrac (R) (BrainlabAG, Munchen, Germany) system to minimize setup errors. Dose was prescribed to the planning target volume (PTV) surrounding 90% isodose.Follow-upDepending on their overall performance status and prognosis, patients received clinical check-ups and radiological imaging. Median follow-up was 11months.Statistical analysisIBM SPSS v.24 was used for univariate analysis using Kaplan-Meier curves, nonparametric Kruskal-Wallis test, and the chi-square test for frequency distributions. Toxicity was graded according to NCI CTCAE v4.0. Depending on radiologic imaging, patients were classified as stable, regression, and progression.ResultsMedian survival was 11months, median PFS was 5months. Median local failure-free survival was 21months. Patients who were treated with curative intent showed abetter survival curve (p<0.0001) and PFS (p=0.004). BED ranged from 42 to 108.8Gy, median BED was 67.2Gy. Three BED groups were formed. Overall survival curves differed significantly (p=0.046), favoring the high-dose group. 21patients were free from any adverse events or discomfort. In 7cases, agradeI toxicity was noted.
CRIS-Team WoS Importer:2019-03-06

Frequent occurrence of therapeutically reversible CMV-associated encephalopathy during radiotherapy of the brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Ruehle, Paul F.; Putz, Florian; Semrau, Sabine; et al. (Neuro-Oncology, 2016)
Neurological decline during radio(chemo)therapy of the brain is often attributed to disease progression or side effects of radiotherapy. Diagnosis of opportunistic neurotropic infections such as cytomegalovirus (CMV) infections is uncommon, even though high-grade gliomas and some brain metastases are known to contain CMV particles. We prospectively examined the frequency of CMV encephalopathy during radiotherapy of the brain.Fifty patients requiring whole-brain radiotherapy for brain metastases (n = 27) or local radio(chemo)therapy of the brain for high-grade gliomas (n = 23) were observed in the prospective observational GLIO-CMV-01 study. MRIs and blood samples were obtained before, halfway through, and at the end of radiotherapy. MRIs were screened for disease progression or increased intracranial pressure. Blood was tested for anti-CMV immunoglobulin (Ig)M, anti-CMV IgG, and CMV DNA.Thirty-two of 50 (64%) patients were positive for anti-CMV IgG before radio(chemo)therapy. Fifteen of those 32 (48%) developed viremia during or up to 28 days after treatment. Thirteen of those 15 (87%) required treatment for CMV-associated encephalopathy. MRIs were negative for disease progression, edema, or bleeding. None of the patients negative for anti-CMV IgG developed viremia, suggesting a reactivation rather than a primary infection.In the group at risk consisting of anti-CMV IgG+ patients, age >65 (P = .004) and the amount of dexamethasone taken during radio(chemo)therapy (P = .004) were associated with an increased risk for CMV-associated encephalopathy. One hundred and fifty days after the start of radio(chemo)therapy, survival was 74% (14/19) (no encephalopathy) versus 54% (7/13) (encephalopathy) (odds ratio, 0.42; 95% CI, 0.03-1.86; P = .25).CMV reactivation frequently causes encephalopathy during radio(chemo)therapy of the brain. The unexpected high incidence of this infection makes it highly clinically relevant for every treating physician.
EVALuna2:8306

FSRT versus SRS for Patients with large Brain Metastases: A volume-based Analysis of local Control and Radionecrosis - Putz, Florian; Oft, D.; Lettmaier, S.; Weissmann, T.; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

FSRT vs. SRS in Brain Metastases—Differences in Local Control and Radiation Necrosis—A Volumetric Study - Putz, Florian; Weissmann, Thomas; Oft, Dominik; Schmidt, Manuel; Roesch, Johannes; Siavooshhaghighi, Hadi; Filimonova, Irina; Schmitter, Charlotte; Mengling, Veit; Bert, Christoph; Frey, Benjamin; Lettmaier, Sebastian; et al. (Frontiers in Oncology, 2020)
Background: While the role of stereotactic radiotherapy for brain metastases is increasing, evidence on the comparative efficacy and safety of fractionated stereotactic radiotherapy (FSRT) and single-session radiosurgery (SRS) is scarce. Methods: Longitudinal volumetric analysis was performed in a consecutive cohort of 120 patients and 190 brain metastases (>0.065 cm3 in volume / > 5 mm in diameter) treated exclusively with FSRT (n = 98) and SRS (n = 92), respectively. A total of 972 tumor segmentations was used, averaging 5.1 time points per metastasis. Progression was defined using a volumetric extension of the RANO-BM criteria. Local control and radionecrosis were compared for lesions treated with FSRT and SRS, respectively. Results: Metastases treated with FSRT were significantly larger at baseline (mean, 4.66 vs. 0.40 cm3, p < 0.001). Biologically effective dose (BED) for metastases (α/β = 12, linear-quadratic-cubic model) was significantly associated with local control, whereas BED for normal brain (α/β = 2, linear-quadratic model) was significantly associated with radionecrosis. Median time to local progression was 22.9 months in the FSRT group compared to 14.5 months in the SRS group (p = 0.022). Overall radionecrosis rate at 12 months was 3.4% for FSRT and 14.8% for SRS (p = 0.010). Radionecrosis °IV requiring resection with histologic proof of radiation necrosis also was significantly reduced in the FSRT group (FSRT 0.0% vs. SRS 3.9%, p = 0.041). In multivariate analysis, FSRT was associated with reduced risk of progression (HR 0.47, p = 0.015) and reduced risk of radionecrosis (HR 0.18, p = 0.045). Conclusions: This volumetric study provides initial evidence that the improvements in therapeutic ratio expected for FSRT in larger brain metastases, might equally extend into the domain of smaller metastases, traditionally less considered for fractionated treatment. FSRT might constitute an important tool to further increase local control and reduce radionecrosis risk in stereotactic radiotherapy for brain metastases, that should be assessed in randomized intervention trials.
CRIS-Team Scopus Importer:2020-10-30
Keywords: brain metastases; fractionated stereotactic radiotherapy; radiobiological aspects; segmentation; stereotactic radiosurgery (SRS); stereotactic radiotherapy (SRT); volumetric analysis

GEC-ESTRO multicenter phase 3-trial: Accelerated partial breast irradiation with interstitial multicatheter brachytherapy versus external beam whole breast irradiation: Early toxicity and patient compliance - Ott, Oliver J.; Strnad, Vratislav; Hildebrandt, Guido; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Lyczek, Jaroslaw; Luis Guinot, Jose; Dunst, Juergen; Gutierrez Miguelez, Cristina; Slampa, Pavel; Allgaeuer, Michael; et al. (Radiotherapy and Oncology, 2016)
To compare early side effects and patient compliance of accelerated partial breast irradiation (APBI) with multicatheter brachytherapy to external beam whole breast irradiation (WBI) in a low-risk group of patients with breast cancer.Between April 2004 and July 2009, 1328 patients with UICC stage 0-IIA breast cancer were randomized to receive WBI with 50Gy and a boost of 10Gy or APBI with either 32.0Gy/8 fractions, or 30.1Gy/7 fractions (HDR-brachytherapy), or 50Gy/0.60-0.80Gy per pulse (PDR-brachytherapy). This report focuses on early side-effects and patient compliance observed in 1186 analyzable patients. ClinicalTrials.gov identifier: NCT00402519.Patient compliance was excellent in both arms. Both WBI and APBI were well tolerated with moderate early side-effects. No grade 4 toxicity had been observed. Grade 3 side effects were exclusively seen for early skin toxicity (radiation dermatitis) with 7% vs. 0.2% (p<0.0001), and breast infection with 0% vs. 0.2% (p=n.s.) for patients treated with WBI and APBI. The incidence of grades 1-2 early side effects for WBI and APBI was 86% vs. 21% (p<0.0001) for skin toxicity, 2% vs. 20% (p<0.0001) for mild hematoma, and 2% vs. 5% (p=0.01) for mild breast infection rates, respectively. No differences had been found regarding grades 1-2 early breast pain (26% vs. 29%, p=0.23).APBI with interstitial multicatheter brachytherapy was tolerated very well and dramatically reduced early skin toxicity in comparison to standard WBI.
EVALuna2:5544

GILT - A randomised phase III study of oral vinorelbine and cisplatin with concomitant radiotherapy followed by either consolidation therapy with oral vinorelbine and cisplatin or best supportive care alone in stage III non-small cell lung cancer - Flentje, Michael; Huber, Rudolf M.; Engel-Riedel, Walburga; Andreas, Stefan; Kollmeier, Jens; Staar, Susanne; Dickgreber, Nicolas; Vaissiere, Nathalie; De Almeida, Cecilia; Edlich, Birgit; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
Concurrent chemoradiotherapy (CRT) is considered standard for inoperable stage III non-small cell lung cancer (NSCLC). Consolidation chemotherapy (CC) following CRT is intended to further improve outcomes, yet studies have shown discordant results. This phase III study assessed CRT followed by best supportive care (BSC) or consolidation with oral vinorelbine and cisplatin.Patients received two cycles of oral vinorelbine (50 mg/m(2) days 1, 8 and 15) + cisplatin (20 mg/m(2) days 1-4) q4w + radiotherapy (RT; 66 Gy). Patients with at least stable disease (SD) were randomised to either two cycles oral vinorelbine (60-80 mg/m(2) days 1 and 8) + cisplatin (80 mg/m(2) day 1) q3w + BSC or BSC alone. Primary endpoint was progression-free survival (PFS).A total of 279 patients were enrolled for CRT and 201 patients were randomised to CC or BSC. Both CRT and CC were well tolerated, with limited radiation-mediated grade 3/4 toxicities (CRT/CC/BSC: oesophagitis-related events 12.9 %/3.1 %/0 %; grade 3 pneumonitis 0 %/0 %/2 %) and chemotherapy-mediated grade 3/4 toxicities (CRT/CC: neutropenia 11.2 %/22.1 %; leukopenia 18.3 %/26.7 %; grade 3 nausea 5.0 %/2.3 %, grade 3 vomiting 3.2 %/3.5 %). Median PFS from randomisation was 6.4 (5.0-8.7) and 5.5 (3.8-7.4) months in the CC and BSC arms (hazard ratio, HR = 0.93 [0.69-1.26]; p = 0.63), respectively; median overall survival (OS) 20.8 (13.5-25.3) and 18.5 (13.6-24.7) months, respectively.Consolidation chemotherapy after concurrent CRT did not prolong PFS or OS. Concurrent RT with oral vinorelbine and cisplatin demonstrated a favourable safety profile and represents a suitable treatment regimen for inoperable stage III NSCLC.
EVALuna2:18353

GLIO-CMV-01: Identification of immune biomarkers for CMV-related encephalitis during radiotherapy of the brain - Donaubauer, Anna-Jasmina; Becker, I.; Rühle, Paul-Friedrich; Goerig, Nicole; Pohn, A.; Winkler, Thomas; Korn, Klaus; Überla, Klaus; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36498

GLIO-CMV-01: Identification of immune biomarkers for CMV related encephalitis during standard brain radiotherapy - Rühle, Paul-Friedrich; Goerig, Nicole; Korn, Klaus; Überla, Klaus; Wunderlich, Roland; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2017)
EVALuna2:32892

Good outcome of brain stem progressive multifocal leukoencephalopathy in an immunosuppressed renal transplant patient: Importance of early detection and rapid immune reconstitution - Sauer, Rolf; Gölitz, Philipp; Jacobi, Johannes; Schwab, Stefan; Linker, Ralf; Lee, De-Hyung (Journal of the Neurological Sciences, 2017)
Progressive multifocal leukoencephalopathy (PML) is a rare, opportunistic and often fatal disease of the CNS which may occur under immunosuppression in transplant patients. Brain stem PML is associated with a particularly bad prognosis. Here, we present a case of a renal transplant patient treated with mycophenolate mofetil (MMF) and tacrolimus who developed brain stem PML with limb ataxia, dysarthria and dysphagia. Diagnosis was established by typical MRI features and detection of JCV-DNA in the CSF. Immune reconstitution after stopping MMF and tacrolimus led to a complete and sustained remission of symptoms with improvement of the brain stem lesion over a follow-up over 20months. In summary, early detection of PML and consequent treatment may improve neurological outcomes even in brain stem disease with a notorious bad prognosis.
EVALuna2:22499

Head and neck tumor cells treated with hypofractionated irradiation die via apoptosis and are better taken up by M1-like macrophages - Wedekind, Hanna; Walz, Kristina; Buchbender, Mayte; Rieckmann, Thorsten; Strasser, Erwin; Grottker, Fridolin; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Rückert, Michael (Strahlentherapie und Onkologie, 2021)
Purpose: The incidence of head and neck squamous cell carcinomas (HNSCC) is increasing worldwide, especially when triggered by the human papilloma virus (HPV). Radiotherapy has immune-modulatory properties, but the role of macrophages present in HNSCC and having contact with irradiated tumor cells remains unclear. The influence of irradiated (2 × 5Gy) HNSCC cells on the (re-)polarization and phagocytosis of human macrophages, either non-polarized or with a more M1 or M2 phenotype, was therefore investigated. Methods: Human monocytes were differentiated with the hematopoietic growth factors M‑CSF (m) or GM-CSF (g) and additionally pre-polarized with either interleukin (IL)-4 and IL-10 or interferon (IFN)-γ and lipopolysaccharides (LPS), respectively. Subsequently, they were added to previously irradiated (2 × 5Gy) and mock-treated HPV-positive (UD-SCC-2) and HPV-negative (Cal33) HNSCC cells including their supernatants. Results: The HNSCC cells treated with hypofractionated irradiation died via apoptosis and were strongly phagocytosed by M0m and M2 macrophages. M0g and M1 macrophages phagocytosed the tumor cells to a lesser extent. Irradiated HNSCC cells were better phagocytosed by M1 macrophages compared to mock-treated controls. The polarization status of the macrophages was not significantly changed, except for the expression of CD206 on M2 macrophages, which was reduced after phagocytosis of irradiated HPV-negative cells. Further, a significant increase in the uptake of irradiated HPV-positive cells by M0g macrophages when compared to HPV-negative cells was observed. Conclusion: HNSCC cells treated with hypofractionated irradiation foster phagocytosis by anti-tumorigenic M1 macrophages. The data provide the first evidence on the impact of the HPV status of HNSCC cells on the modulation of the macrophage response to irradiated tumor cells.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Head and neck cancer; Human papilloma virus; Macrophage polarization; Phagocytosis; Radiotherapy

Heart-sparing radiotherapy techniques in breast cancer patients: a recommendation of the breast cancer expert panel of the German society of radiation oncology (DEGRO) - Duma, Marciana Nona; Baumann, René; Budach, Wilfried; Dunst, Jürgen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Hehr, Thomas; Krug, David; Piroth, Marc D.; Sedlmayer, Felix; et al. (Strahlentherapie und Onkologie, 2019)
Purpose: The aim of this review was to analyze the respective efficacy of various heart-sparing radiotherapy techniques. Material and methods: Heart-sparing can be performed in three different ways in breast cancer radiotherapy: by seeking to keep the heart out of treated volumes (i.e. by prone position or specific breathing techniques such as deep inspiration breath-hold [DIBH] and/or gating), by solely irradiating a small volume around the lumpectomy cavity (partial breast irradiation, PBI), or by using modern radiation techniques like intensity-modulated radiation therapy (IMRT), volumetric modulated arc therapy (VMAT) or protons. This overview presents the available data on these three approaches. Results: Studies on prone position are heterogeneous and most trials only refer to patients with large breasts; therefore, no definitive conclusion can be drawn for clinical routine. Nonetheless, there seems to be a trend toward better sparing of the left anterior descending artery in supine position even for these selected patients. The data on the use of DIBH for heart-sparing in breast cancer patients is consistent and the benefit compared to free-breathing is supported by several studies. In comparison with whole breast irradiation (WBI), PBI has an advantage in reducing the heart dose. Of note, DIBH and PBI with multicatheter brachytherapy are similar with regard to the dose reduction to heart structures. WBI by IMRT/VMAT techniques without DIBH is not an effective strategy for heart-sparing in breast cancer patients with “standard” anatomy. A combination of DIBH and IMRT may be used for internal mammary radiotherapy. Conclusion: Based on the available findings, the DEGRO breast cancer expert panel recommends the use of DIBH as the best heart-sparing technique. Nonetheless, depending on the treatment volume and localization, other techniques may be employed or combined with DIBH when appropriate.
CRIS-Team Scopus Importer:2019-07-26
Keywords: Breast cancer; DEGRO; Heart toxicities; Radiotherapy; Technique

Heart toxicity from breast cancer radiotherapy : Current findings, assessment, and prevention - Piroth, Marc D.; Baumann, Rene; Budach, Wilfried; Dunst, Juergen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Hehr, Thomas; Krug, David; Roeser, Arnd; Sedlmayer, Felix; et al. (Strahlentherapie und Onkologie, 2019)
BACKGROUND: Late cardiac toxicities caused by (particularly left-sided) breast radiotherapy (RT) are now recognized as rare but relevant sequelae, which has prompted research on risk structure identification and definition of threshold doses to heart subvolumes. The aim of the present review was to critically discuss the clinical evidence on late cardiac reactions based on dose-dependent outcome reports for mean heart doses as well as doses to cardiac substructures. METHODS: A literature review was performed to examine clinical evidence on radiation-induced heart toxicities. Mean heart doses and doses to cardiac substructures were focused upon based on dose-dependent outcome reports. Furthermore, an overview of radiation techniques for heart protection is given and non-radiotherapeutic aspects of cardiotoxicity in the multimodal setting of breast cancer treatment are discussed. RESULTS: Based on available findings, the DEGRO breast cancer expert panel recommends the following constraints: mean heart dose <2.5 Gy; DmeanLV (mean dose left ventricle) < 3 Gy; V5LV (volume of LV receiving ≥5 Gy) < 17%; V23LV (volume of LV receiving ≥23 Gy) < 5%; DmeanLAD (mean dose left descending artery) < 10 Gy; V30LAD (volume of LAD receiving ≥30 Gy) < 2%; V40LAD (volume of LAD receiving ≥40 Gy) < 1%. CONCLUSION: In addition to mean heart dose, breast cancer RT treatment planning should also include constraints for cardiac subvolumes such as LV and LAD. The given constraints serve as a clinicians' aid for ensuring adequate heart protection. The individual decision between sufficient protection of cardiac structures versus optimal target volume coverage remains in the physician's hand. The risk of breast cancer-specific mortality and a patient's cardiac risk factors must be individually weighed up against the risk of radiation-induced cardiotoxicity.
EVALuna2:36455

Heat Shock Protein 70 (Hsp70) Peptide Activated Natural Killer (NK) Cells for the Treatment of Patients with Non-Small Cell Lung Cancer (NSCLC) after Radiochemotherapy (RCTx) - From Preclinical Studies to a Clinical Phase II Trial - Specht, Hanno M.; Ahrens, Norbert; Blankenstein, Christiane; Duell, Thomas; Fietkau, Rainer; Gaipl, Udo; Guenther, Christine; Gunther, Sophie; Habl, Gregor; Hautmann, Hubert; Hautmann, Matthias; Huber, Rudolf Maria; et al. (Frontiers in Immunology, 2015)
Heat shock protein 70 (Hsp70) is frequently overexpressed in tumor cells. An unusual cell surface localization could be demonstrated on a large variety of solid tumors including lung, colorectal, breast, squamous cell carcinomas of the head and neck, prostate and pancreatic carcinomas, glioblastomas, sarcomas and hematological malignancies, but not on corresponding normal tissues. A membrane (m)Hsp70-positive phenotype can be determined either directly on single cell suspensions of tumor biopsies by flow cytometry using cmHsp70.1 monoclonal antibody or indirectly in the serum of patients using a novel lipHsp70 ELISA. A mHsp70-positive tumor phenotype has been associated with highly aggressive tumors, causing invasion and metastases and resistance to cell death. However, natural killer (NK), but not T cells were found to kill mHsp70-positive tumor cells after activation with a naturally occurring Hsp70 peptide (TKD) plus low dose IL-2 (TKD/IL-2). Safety and tolerability of ex vivo TKD/IL-2 stimulated, autologous NK cells has been demonstrated in patients with metastasized colorectal and non-small cell lung cancer (NSCLC) in a phase I clinical trial. Based on promising clinical results of the previous study, a phase II randomized clinical study was initiated in 2014. The primary objective of this multicenter proof-of-concept trial is to examine whether an adjuvant treatment of NSCLC patients after platinum-based radiochemotherapy (RCTx) with TKD/IL-2 activated, autologous NK cells is clinically effective. As a mHsp70-positive tumor phenotype is associated with poor clinical outcome only mHsp70-positive tumor patients will be recruited into the trial. The primary endpoint of this study will be the comparison of the progression-free survival of patients treated with ex vivo activated NK cells compared to patients who were treated with RCTx alone. As secondary endpoints overall survival, toxicity, quality-of-life, and biological responses will be determined in both study groups.
EVALuna2:18287

Hemicorporal paresthesias in a parvovirusinfection - Baltas, Dimos; Ladd, Mark E.; Fiebich, Martin; Bert, Christoph; Heufelder, Jens (Zeitschrift für Medizinische Physik, 2020)
CRIS-Team WoS Importer:2021-01-29

High Detection Accuracy of an optimized 3D Convolutional Neural Network for Auto Detection and Auto Segmentation of Brain Metastases - Putz, Florian; Weissmann, Thomas; Mansoorian, Sina; Schmitter, Charlotte; Semrau, Sabine; Lettmaier, Sebastian; Masitho, Siti; Grigo, Johanna; Schmidt, Manuel; Heiß, Rafael; Frey, Benjamin; Bert, Christoph; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

High-grade histology as predictor of early distant metastases and decreased disease-free survival in salivary gland cancer irrespective of tumor subtype - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Uter, Wolfgang; Neukam, Friedrich Wilhelm; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2016)
The purpose of this study was to evaluate risk factors that influence overall survival (OS)/disease-free survival (DFS)/locoregional recurrence-free survival (LRFS), and distant metastases-free survival (DMFS) in patients with high-risk primary salivary gland carcinoma who underwent surgery and postoperative (chemo)radiotherapy with curative intention.We reviewed data of 63 patients with high-risk primary salivary gland carcinoma in a retrospective single-center audit.At a median follow-up of 31 months (range, 5-145 months), cumulative OS and DFS were 91.7%, 77.6%, and 62.9%, and 82.1%, 65.6%, and 57.7%, respectively, after 1, 2, and 5 years. LRFS and DMFS were 92%, 86%, and 86%, and 83.4%, 70.4%, and 62.3% after 1, 2, and 5 years, respectively. Of all patient-related, tumor-related, and treatment-related factors, high-grade histology (G3) was the only factor in univariate and multivariate analysis that was predictive for a shorter DMFS (low/intermediate vs high-grade: 100%, 100%, and 89.4% vs 72.9%, 54.3%, and 42.8% after 1, 2, and 5 years, respectively) and a shorter DFS (low/intermediate vs high-grade: 100%, 90%, and 84.4% vs 71.2%, 50.1%, and 39.4% after 1, 2, and 5 years, respectively) and OS (low/intermediate vs high-grade: 100%, 100%, and 86.5% vs 86.5%, 63.2%, and 46.5% after 1, 2, and 5 years, respectively).High-grade tumor histology is a highly significant predictor of a shorter DMFS, OS, and DFS in salivary gland carcinoma, irrespective of histological subtype. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2041-E2048, 2016.
EVALuna2:5539

High-grade salivary gland cancer: is surgery followed by radiotherapy an adequate treatment to reach tumor control? Results from a tertiary referral centre focussing on incidence and management of distant metastases - Freitag, Viola; Lettmaier, Sebastian; Semrau, Sabine; Hecht, Markus; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina; Traxdorf, Maximilian; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer; Haderlein, Marlen (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose: Salivary Gland cancer (SGC) is a rare and heterogenous group of tumors. Standard therapeutic options achieve high local but poor distant control rates, especially in high-grade SGC. The aim of this monocentric study was to evaluate patterns of recurrence and its treatment options (local ablative vs. systemic) in a homogenously treated patient population with high-grade SGC after surgery and radio(chemo)therapy. Methods: Monocentric, retrospective study of patients with newly diagnosed high-grade salivary gland cancer. We retrospectively reviewed clinical reports from 69 patients with high-grade salivary gland cancer in a single-center audit. Survival rates were calculated using the Kaplan–Meier method and prognostic variables were analyzed (univariate analysis: log-rank test; multivariate analysis: Cox regression analysis). Results: The median time of follow-up was 31 months. After 5 years, the cumulative overall survival was 65.2%, cumulative incidence of local recurrence was 7.2%, whereas the cumulative incidence of distant metastases was 43.5% after 5 years. 30 of 69 patients developed distant metastases during the time of follow-up, especially patients with adenoid cystic carcinoma, salivary duct carcinoma, adenocarcinoma NOS and acinic cell carcinoma with high-grade transformation. The most common type of therapy therefore was chemotherapy (50%). 85.7% of patients with local ablative therapy of distant metastases show disease progression during follow-up afterwards. Conclusion: With surgery and radio-chemotherapy, a high rate of loco-regional control is reached, but over 40% of patients develop distant metastases in the further follow-up which usually present a diffuse pattern involving in a diffuse metastases. Therefore, in the future, intensified interdisciplinary combination therapies even in the first-line treatment in certain subtypes of high-grade SGC should be investigated.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Chemotherapy; Distant metastases; High-grade; Radiotherapy; Salivary gland cancer

Highlights from the 2021 ASCO and ESMO annual meetings on radiotherapy of head and neck cancer Highlights der ASCO- und ESMO-Jahrestagungen 2021 zur Strahlentherapie von Kopf-Hals-Tumoren - Hecht, Markus; von der Grün, Jens; Semrau, Sabine; Müller, Susanna; Weissmann, Thomas; Gaipl, Udo; Iro, Heinrich; Fietkau, Rainer; Gostian, Antoniu-Oreste (HNO, 2022)
At this year’s annual meetings of the American Society of Clinical Oncology (ASCO) and the European Society for Medical Oncology (ESMO), several studies on radiotherapy of locally advanced head and neck cancer were presented. For the indication of definitive radiochemotherapy, particularly the administration of immune checkpoint inhibitors concomitant to radiotherapy was investigated. In the phase III GORTEC-REACH trial, combined inhibition of epidermal growth factor receptor (EGFR) and programmed death-ligand (PD-L1) concomitant to radiotherapy of locally advanced head and neck cancer was inferior to platinum-based chemoradiotherapy. However, this therapeutic approach may be more efficient than radiotherapy with simultaneous EGFR inhibition alone. The concept of the phase II CheckRad-CD8 trial with induction chemoimmunotherapy followed by chemotherapy-free radioimmunotherapy after appropriate patient selection also proved to be highly efficient. In initial phase II trials, dose de-escalation of radiotherapy seems feasible for HPV-positive oropharyngeal cancer after appropriate patient selection both postoperatively (ECOG-ACRIN E3311 trial) and after induction therapy (Optima II trial). However, dose de-escalation should currently not be performed outside of clinical trials. In addition, first studies indicate a benefit of functional imaging (diffusion-weighted magnetic resonance imaging [MRI] or F‑fluoromisonidazole positron-emission tomography [FMISO-PET]) to establish personalized dose concepts in radiotherapy.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Chemoradiotherapy; Head and neck squamous cell carcinoma; Human papillomavirus; Immunotherapy; Oropharyngeal cancer

High locoregional Control Rates after Radio (chemo) Therapy in anaplastic Thyroid Carcinoma - a monocentric Analysis - Schmied, M.; Semrau, Sabine; Hecht, Markus; Lettmaier, Sebastian; Mantsopoulos, K.; Traxdorf, Maximilian; Iro, Heinrich; Denz, Axel; Grützmann, Robert; Fietkau, Rainer; Haderlein, Marlen (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

High stroma T-cell infiltration is associated with better survival in stage pT1 bladder cancer - Hülsen, Sabine; Lippolis, Eleonora; Ferrazzi, Fulvia; Otto, Wolfgang; Distel, Luitpold; Fietkau, Rainer; Denzinger, Stefan; Breyer, Johannes; Burger, Maximilian; Bertz, Simone; Eckstein, Markus; Ebner, Annette; et al. (International Journal of Molecular Sciences, 2020)
Stage pT1 bladder cancer (BC) shows highly diverse outcomes. Predictive markers are required to stratify patients for personalized treatment. The present study aimed to validate immune response quantification as a prognostic marker. Patients with pT1 BC (n = 167) treated by transurethral resection of the bladder (TURB) were enrolled. Formaldehyde-fixed paraffin-embedded material was stained for CD3 and CD8. Corresponding T cells were counted in three regions with the highest immune response. Numbers of tertiary lymphoid structures (TLS) and lymphocyte aggregates (LA) were quantified. High CD3+ stroma T-cell infiltration was associated with improved survival (p = 0.045), especially in the G3 subgroup (p = 0.01). Cluster with higher immune response showed less recurrence (p = 0.034) and favorable overall survival (OS) (p = 0.019). In contrast, higher CD3+ and CD8+ tumor T-cell infiltration seemed to have a negative impact on prognosis. TLS and LA were more frequently observed in G3 tumors, indicating an increased antitumoral immune response. We proved the role of immune cell infiltration and showed that higher infiltration numbers of CD3+ (not CD8+) lymphocytes in the stroma are associated with favorable outcome. Immune cell quantification could be used as a marker to help stratify patients’ risk and therefore, to optimize patients’ management and follow-up examination as well as possible therapies.
CRIS-Team Scopus Importer:2020-11-20
Keywords: CD8; Immunoscore; Progression; PT1 bladder cancer; Survival; Tumor-infiltrating lymphocytes (TILs); CD3

Histology-Depended Pattern of Patho-Histological Response After Induction Therapy in Locally Advanced Non-Small Cell Lung Cancer - Schreiner, Waldemar; Dudek, Wojciech; Rieker, Ralf; Fietkau, Rainer; Sirbu, Horia (JOURNAL OF THORACIC ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

How nescience may obscure evidence - Sautter-Bihl, M. -L.; Sedlmayer, F.; Budach, W.; Dunst, Juergen; Feyer, P.; Fietkau, Rainer; Haase, W.; Harms, W.; Piroth, M. D.; Souchon, R.; Wenz, F.; Sauer, Rolf (Strahlentherapie und Onkologie, 2014)
EVALuna2:18199

How Octogenarians with Bladder Cancer Are Treated in a Maximum-Care Hospital: The Real-Life Experience - Sikic, Danijel; Wach, Sven; Taubert, Helge; Richterstetter, Mario; Kunath, Frank; Lieb, Verena; Krause, F. Steffen; Merten, Ricarda; Ott, Oliver; Fietkau, Rainer; Wullich, Bernd; Keck, Bastian (Urologia Internationalis, 2016)
With increasing life expectancy, curative treatment of octogenarians with urothelial carcinoma of the bladder (UCB) becomes more important.The treatment modalities of 276 octogenarians with UCB who were treated at the University Hospital of Erlangen between 1982 and 2011 were assessed retrospectively.One hundred forty-six patients had non-muscle invasive bladder cancer (NMIBC) while 71 had muscle invasive bladder cancer (MIBC). No data was available for 59 patients. Eighty-five (58.2%) of the 146 patients with NMIBC received transurethral resection of the bladder tumor (TURBT) only, another 38 patients (26%) underwent additional intravesical therapy; and 8.9% were treated with radiochemotherapy (RCT), 4.1% with radiotherapy (RT), 1.4% with systemic chemotherapy and 1.4% with radical cystectomy (RC). Of the 71 patients suffering from MIBC, 39 (54.9%) received TURBT alone. A potentially curative therapy was performed on 31 of the 71 patients with MIBC (43.7%). Of these, 16 patients (51.6%) received RCT, 9 patients (29.0%) RT and 6 patients (19.4%) RC. In Kaplan-Meier analysis, patients with MIBC had better median overall survival with curative treatment compared to TURBT alone (28 vs. 9 months; p < 0.001, log-rank test).By offering a wide range of treatment options, over 43% of octogenarians with MIBC received a curative therapy at a maximum care hospital.
EVALuna2:16292

Hydrostatic High Pressure generated Whole Cell Tumor Vaccines in combination with Radiotherapy produce an immunogenic Tumor Microenvironment - Rueckert, M.; Seitz, C.; Weiss, E. -M; Utz, S.; Izydor, Marika; Ebel, Nina; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Deloch, Lisa (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Hyperthermia with 44 degrees C enhances danger signal-mediated activation of dendritic cells, while immune cell infiltration into tumors is particularly fostered by hyperthermia with lower temperatures - Vogl, P.; Frey, Benjamin; Rueckert, M.; Maueröder, Christian; Fietkau, Rainer; Gaipl, Udo; Derer, Anja (2017)
EVALuna2:32897

Hypofractionated Irradiation Has Immune Stimulatory Potential and Induces a Timely Restricted Infiltration of Immune Cells in Colon Cancer Tumors - Frey, Benjamin; Rueckert, Michael; Weber, Julia; Mayr, Xaver; Derer, Anja; Lotter, Michael; Bert, Christoph; Roedel, Franz; Fietkau, Rainer; Gaipl, Udo (Frontiers in Immunology, 2017)
In addition to locally controlling the tumor, hypofractionated radiotherapy (RT) particularly aims to activate immune cells in the RT-modified microenvironment. Therefore, we examined whether hypofractionated RT can activate dendritic cells (DCs), induce immune cell infiltration in tumors, and how the chronology of immune cell migration into tumors occurs to gain knowledge for future definition of radiation breaks and inclusion of immunotherapy. Colorectal cancer treatments offer only limited survival benefit, and immunobiological principles for additional therapies need to be explored with preclinical models. The impact of hypofractionated RT on CT26 colon cancer tumor cell death, migration of DCs toward supernatants (SN) of tumor cells, and activation of DCs by SN were analyzed. The subcutaneous tumor of a BALB/c-CT26 mouse model was locally irradiated with 2 × 5 Gy, the tumor volume was monitored, and the infiltration of immune cells in the tumor was determined by flow cytometry daily. Hypofractionated RT induced a mixture of apoptotic and necrotic CT26 cells, which is known to be in particular immunogenic. DCs that migrated toward SN of CT26 cells particularly upregulated the activation markers CD80 and CD86 when in contact with SN of irradiated tumor cells. After hypofractionated RT, the tumor outgrowth was significantly retarded and in the irradiated tumors an increased infiltration of macrophages (CD11bhigh/F4-80+) and DCs (MHC-II+), but only between day 5 and 10 after the first irradiation, takes place. While CD4+T cells migrated into non-irradiated and irradiated tumors, CD8+T cells were only found in tumors that had been irradiated and they were highly increased at day 8 after the first irradiation. Myeloid-derived suppressor cells and regulatory T cells show regular turnover in irradiated and non-irradiated tumors. Tumor cell-specific anti-IgM antibodies were enhanced in the serum of animals with irradiated tumors. We conclude that hypofractionated RT suffices to activate DCs and to induce infiltration of innate and adaptive immune cells into solid colorectal tumors. However, the presence of immune cells in the tumor which are beneficial for antitumor immune responses is timely restricted. These findings should be considered when innovative multimodal tumor treatment protocols of distinct RT with immune therapies are designed and clinically implemented.
EVALuna2:32906

Hypofractionated Irradiation increases the Expression of the Immune Checkpoint Molecule HVEM on TS/A, 4T1-luc and E0771 Breast Carcinoma Cells - Flohr, Ann-Sophie; Fietkau, Rainer; Rückert, Michael; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Hypofractionated Radiation increases the Expression of the Immune Checkpoint-Molecule HVEM on TS/A Breast Cancer- and B16 Melanoma Cells - Flohr, Ann-Sophie; Grün, A; Fietkau, Rainer; Rückert, Michael; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Hypofractionated Radiotherapy Upregulates Several Immune Checkpoint Molecules in Head and Neck Squamous Cell Carcinoma Cells Independently of the HPV Status While ICOS-L Is Upregulated Only on HPV-Positive Cells - Wimmer, Sebastian; Deloch, Lisa; Hader, Michael; Derer, Anja; Grottker, Fridolin; Weissmann, Thomas; Hecht, Markus; Gostian, Antoniu-Oreste; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (International Journal of Molecular Sciences, 2021)
While the treatment of squamous cell carcinoma of the head and neck (HNSCC) with radiotherapy (RT) is complemented more and more by immunotherapy in clinical trials, little is known about the impact of the human papillomavirus (HPV) status or the applied RT scheme on the immune phenotype of the tumor cells. Therefore, we aimed to examine the impact of the HPV status of four human HNSCC cell lines on cell death and the expression of immune checkpoint molecules (ICMs) after RT with either hypofractionation irradiation (5x3.0Gy) or a high single dose (1x19.3Gy) via multicolor flow cytometry and quantitative PCR at an early time point after therapy. In our study, 5x3.0Gy RT induced high numbers of early and late apoptotic cells independent of the HPV status, but necrosis was only increased in the HPV-positive UM-Scc-47 cells. Generally, the immune stimulatory ICMs (CD70, CD137-L, ICOS-L) were less affected by RT compared to the immune suppressive ones (PD-L1, PD-L2, and the herpesvirus entry mediator (HVEM)). A significant higher surface expression of the analyzed ICMs was found after hypofractionated RT compared to a single high dose; however, regardless of the HPV status, with the exception of ICOS-L. Here, HPV-positive HNSCC tumor cells showed a stronger response to 5x3.0Gy than HPV-negative ones. On the RNA level, only minor alterations of ICMs were observed following RT, with the exception of the HPV negative cell line CAL33 treated with 5x3.0Gy, where PD-L2, HVEM and CD70 were significantly increased. We conclude that the HPV status may not distinctly predict immunological responses following RT, and thus cannot be used as a single predictive marker for therapy responses in HNSCC. In contrast, the patient-specific individual expression of ICMs following RT is preferable for the targeted patient selection for immune therapy directed against distinct ICM.
CRIS-Team WoS Importer:2021-09-17

Idelalisib may have the potential to increase radiotherapy side effects - Gryc, Thomas; Putz, Florian; Goerig, Nicole; Ziegler, Sonia; Fietkau, Rainer; Distel, Luitpold; Schuster, Barbara (Radiation Oncology, 2017)
INTRODUCTION: Idelalisib is approved for the treatment of relapsed chronic lymphocytic leukemia together with Rituximab and for monotherapy of follicular B-cell non-Hodgkin's lymphoma and small lymphocytic lymphoma. It is a potent and selective phosphatidylinositol 3-kinase-δ (PI3K-δ) inhibitor. PI3K-δ primarily is expressed in B-cells and prevents effectively proliferation in malignant B-cells. METHODS: We provide a detailed report on treatment history and photo documentation of acute adverse effects of radiation therapy with simultaneous Idelalisib medication in one case of B-CLL. Radiosensitivity tests were performed for the index patient under Idelalisib and after the addition of Idelalisib to healthy individuals' blood. Radiosensitivity in human lymphocytes was analyzed with a three color in situ hybridization assay. Primary skin fibroblasts were studied after a treatment with Idelalisib for apoptosis, necrosis and cell cycle using flow cytometry. DNA double-strand break repair was analyzed by γH2AX immunostaining. RESULTS: The index patient presented a strong grade 2 radiodermatitis and grade 3 mucositis after irradiation with 20 Gy and a simultaneous intake of Idelalisib. Irradiations without Idelalisib medication were well tolerated and resulted in not more than grade 1 radiodermatitis. The index patient under Idelalisib had a radiosensitivity of 0.62 B/M which is in the range of clearly radiosensitive patients. A combined treatment of lymphocytes with 2 Gy and 10 nmol/l Idelalisib showed a tendency to an increased radiosensitivity. We found a clear increase of apoptosis as a result of the combined treatment in the Idelalisib dose range of 1 to 100 nmol/l compared to solely irradiated cells or solely Idelalisib treated cells (p = 0.05). CONCLUSION: A combined Idelalisib radiotherapy treatment has an increased risk of side effects. However, combined therapy seems to be feasible when patients are monitored closely.
EVALuna2:32873

Identification and characterization of circular RNAs as novel putative biomarkers to predict anti-PD-1 monotherapy response in metastatic melanoma patients – Knowledge from two independent international studies - Zhou, Jian Guo; Liang, Rui; Wang, Hai Tao; Jin, Su Han; Hu, Wei; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Ma, Hu; Gaipl, Udo (Neoplasia, 2023)
Melanoma is the most aggressive skin malignancy with high morbidity. Anti-programmed cell death protein 1 (PD-1) monotherapy has been applied in metastatic melanoma. However, still most of the patients do not respond to anti-PD-1 and the availability of the present approved biomarkers therefore is limited. Here we combined the transcriptomic and clinical data of 163 advanced melanoma patients receiving anti-PD-1 from NIH Melanoma Genome Sequencing Project (phs000452, 122 patients) as the training and internal validation cohort, and Melanoma Institute Australia cohort (PRJEB23709, 41 patients) as the external validation cohort, respectively. Circular RNAs (circRNAs) are an evolutionarily conserved novel class of noncoding endogenous RNAs (ncRNAs) found in the eukaryotic transcriptome and were used based on RNAseq data for our analyses. 74,243 circular RNAs (circRNAs) were identified with NCLscan and CIRCexplorer2. Thereof, 70 circRNAs significantly associated with progression-free survival and overall survival. Further, a prognostic circRNAs signature consisting of HSA_CIRCpedia_1497, HSA_CIRCpedia_12559, HSA_CIRCpedia_43640, HSA_CIRCpedia_43070, and HSA_CIRCpedia_21660 could be determined with LASSO regression. This signature was a prognostic factor of overall survival and progression-free survival among the analyzed advanced melanoma patients. The concordance indexes (C-index of OStraining: 0.61, C-index of PFStraining: 0.68) also confirmed its credibility and accuracy. First enrichment analysis indicated that immune response and pathways related to tumor immune microenvironment were enriched. In conclusion, we succeeded to construct and validate novel prognostic circRNAs signature for advanced melanoma patients treated with anti-PD-1 immunotherapy.
CRIS-Team Scopus Importer:2023-02-03
Keywords: Advanced melanoma; Anti-PD-1; circRNAs; Predictor; Survival benefit

Identification of 15 lncRNAs Signature for Predicting Survival Benefit of Advanced Melanoma Patients Treated with Anti-PD-1 Monotherapy - Zhou, Jian Guo; Liang, Bo; Liu, Jian Guo; Jin, Su Han; He, Si Si; Frey, Benjamin; Gu, Ning; Fietkau, Rainer; Hecht, Markus; Ma, Hu; Gaipl, Udo (Cells, 2021)
The blockade of programmed cell death protein 1 (PD-1) as monotherapy has been widely used in melanoma, but to identify melanoma patients with survival benefit from anti-PD-1 monotherapy is still a big challenge. There is an urgent need for prognostic signatures improving the prediction of immunotherapy responses of these patients. We analyzed transcriptomic data of pre-treatment tumor biopsies and clinical profiles in advanced melanoma patients receiving only anti-PD-1 monotherapy (nivolumab or pembrolizumab) from the PRJNA356761 and PRJEB23709 data sets as the training and validation cohort, respectively. Weighted gene co-expression network analysis was used to identify the key module, then least absolute shrinkage and selection operator was conducted to determine prognostic-related long noncoding RNAs (lncRNAs). Subsequently, the differentially expressed genes between different clusters were identified, and their function and pathway annotation were performed. In this investigation, 92 melanoma patients with complete survival information (51 from training cohort and 41 from validation cohort) were included in our analyses. We initiallyidentified the key module (skyblue) by weighted gene co-expression network analysis, and then identified a 15 predictive lncRNAs (AC010904.2, LINC01126, AC012360.1, AC024933.1, AL442128.2, AC022211.4, AC022211.2, AC127496.5, NARF-AS1, AP000919.3, AP005329.2, AC023983.1, AC023983.2, AC139100.1, and AC012615.4) signature in melanoma patients treated with anti-PD-1 monotherapy by least absolute shrinkage and selection operator in the training cohort. These results were then validated in the validation cohort. Finally, enrichment analysis showed that the functions of differentially expressed genes between two consensus clusters were mainly related to the immune process and treatment. In summary, the 15 lncRNAs signature is a novel effective predictor for prognosis in advanced melanoma patients treated with anti-PD-1 monotherapy.
CRIS-Team Scopus Importer:2021-05-28
Keywords: advanced melanoma; immune checkpoint inhibitor; LASSO; lncRNA; PD-1; predictor; survival benefit; WGCNA

Identification of an endogenous retroviral signature to predict anti-PD1 response in advanced clear cell renal cell carcinoma: an integrated analysis of three clinical trials - Zhou, Jianguo; Zeng, Yu; Wang, Haitao; Jin, Su-Han; Wang, Yun-Jia; He, Sisi; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Ma, Hu; Zhang, Wenchuan; Gaipl, Udo (Therapeutic Advances in Medical Oncology, 2022)
Background: Endogenous retrovirus (ERV) elements are genomic footprints of ancestral retroviral infections within the human genome. Previous studies have demonstrated that dysregulated ERV transcription level is associated with immune cell infiltration in cancers, but the association between ERV expression and programmed cell death protein 1 (PD-1) blockade response is currently unraveled for solid cancers, such as advanced clear cell renal cell carcinoma (ccRCC). Methods: ERV mRNA profiles were obtained from three clinical trials of ccRCC where the patients were treated with anti-PD-1 (CM-009, CM-010, CM-025, and TCGA-KIRC data). Patients treated with nivolumab were divided into training and test cohort, while the TCGA-KIRC cohort was used as an external validation. Univariate Cox regression analysis and least absolute shrinkage and selection operator regression were used to establish the signature. Immune cell infiltration analysis and gene set enrichment analysis were performed to explore potential biological mechanisms. Results: An ERV signature was established based on nine ERV expression patterns. In the training cohort, the median overall survival in the low- and high-risk group was 45.2 and 19.6 months [hazard ratio (HR) = 0.49, 0.32-0.75, p < 0.001], respectively. The results were confirmed in the test (HR = 0.41, 0.20-0.83, p = 0.013), and in the TCGA-KIRC cohort (HR = 0.55, 0.34-0.90, p = 0.017). Moreover, in the CM-025 cohort, the low-risk group that received nivolumab had a more favorable survival compared with those that received the mTOR inhibitor everolimus, while no significant differences were observed in the high-risk group. CD8+ T cells were enriched in the low-risk group, while immune suppressive pathways were suppressed. Conclusion: The newly identified ERV signature is not only a prognostic, but also a predictive biomarker for advanced ccRCC patients who received anti-PD-1 therapy, which can guide personalized treatment in cancer patients in the future.
CRIS-Team WoS Importer:2022-10-14

Identification of High-risk Metastases in MRI Follow-up after Stereotaxic by using Radiomics and Delta Radiomics - Sommer, Phillip; Huang, Yixing; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Dörfler, Arnd; Schmidt, M.; Frey, Benjamin; Maier, Andreas; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Immobilization for carbon ion beam ablation of cardiac structures in a porcine model - Prall, Matthias; Eichhorn, Anna; Richter, Daniel; Lehmann, H. Immo; Constantinescu, Anna; Kaderka, Robert; Lugenbiel, Patrick; Thomas, Dierk; Bert, Christoph; Packer, Douglas L.; Durante, Marco; Graeff, Christian (Physica Medica, 2017)
INTRODUCTION: Whereas hadron therapy of static targets is clinically established, treatment of moving organs remains a challenge. One strategy is to minimize motion of surrounding tissue mechanically and to mitigate residual motion with an appropriate irradiation technique. In this technical note, we present and characterize such an immobilization technique for a novel noncancerous application: the irradiation of small targets in hearts with scanned carbon ion beams in a porcine model for elimination of arrhythmias. MATERIAL AND METHODS: A device for immobilization was custom-built. Both for the treatment planning 4D-CT scan and for irradiation, breath-hold at end-exhale was enforced using a remotely-controlled respirator. Target motion was thus reduced to heartbeat only. Positioning was verified by orthogonal X-rays followed by couch shift if necessary. Reproducibility of bony anatomy, diaphragm, and heart position after repositioning and between repeated breath-hold maneuvers was evaluated on X-rays and cardiac-gated 4D-CTs. Treatment was post hoc simulated on sequential 4D-CTs for a subset of animals, after immediate repositioning and after a delay of one week, similar to the delay between imaging and irradiation. RESULTS: Breath-hold without repositioning was highly reproducible with an RMS deviation of at most one millimeter. 4D-CTs showed larger deformations in soft tissue, but treatment simulation on sequential images resulted in full target coverage (V95 >95%). CONCLUSION: The method of immobilization permitted reproducible positioning of mobile, thoracic targets for range-sensitive particle therapy. The presented immobilization strategy could be a reasonable approach for future animal investigations with the ultimate goal of translation to therapy in men.
EVALuna2:33031

IMMO-LDRT01: Immunophenotyping of patients suffering from chronic degenerative joint diseases and receiving local low-dose radiation therapy - Harrer, A.; Rühle, Paul-Friedrich; Gryc, Thomas; Ott, O. J.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2017)
EVALuna2:32884

IMMO-LDRT01 TRIAL: IMMUNOMODULATORY EFFECTS OF LOW DOSE RADIATION THERAPY OF CHRONIC DEGENERATIVE AND INFLAMMATORY DISEASES - Donaubauer, Anna-Jasmina; Gryc, Thomas; Becker, I.; Ott, O. J.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Immune biological rationales for the design of combined radio- and immunotherapies - Hader, Michael; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Gaipl, Udo (Cancer Immunology, Immunotherapy, 2020)
Cancer immunotherapies are promising treatments for many forms of cancer. Nevertheless, the response rates to, e.g., immune checkpoint inhibitors (ICI), are still in low double-digit percentage. This calls for further therapy optimization that should take into account combination of immunotherapies with classical tumor therapies such as radiotherapy. By designing multimodal approaches, immune modulatory properties of certain radiation schemes, additional immune modulation by immunotherapy with ICI and hyperthermia, as well as patient stratification based on genetic and immune constitutions have to be considered. In this context, both the tumor and its microenvironment including cells of the innate and adaptive immune system have to be viewed in synopsis. Knowledge of immune activation and immune suppression by radiation is the basis for well-elaborated addition of certain immunotherapies. In this review, the focus is set on additional immune stimulation by hyperthermia and restoration of an immune response by ICI. The impact of radiation dose and fractionation on immune modulation in multimodal settings has to be considered, as the dynamics of the immune response and the timing between radiotherapy and immunotherapy. Another big challenge is the patient stratification that should be based on matrices of biomarkers, taking into account genetics, proteomics, radiomics, and "immunomics". One key aim is to turn immunological "cold" tumors into "hot" tumors, and to eliminate barriers of immune-suppressed or immune-excluded tumors. Comprehensive knowledge of immune alterations induced by radiation and immunotherapy when being applied together should be utilized for patient-adapted treatment planning and testing of innovative tumor therapies within clinical trials.
CRIS-Team WoS Importer:2020-01-31

Immune-modulating properties of ionizing radiation: rationale for the treatment of cancer by combination radiotherapy and immune checkpoint inhibitors - Derer, Anja; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (Cancer Immunology Immunotherapy, 2016)
Radiotherapy (RT) utilizes the DNA-damaging properties of ionizing radiation to control tumor growth and ultimately kill tumor cells. By modifying the tumor cell phenotype and the tumor microenvironment, it may also modulate the immune system. However, out-of-field reactions of RT mostly assume further immune activation. Here, the sequence of the applications of RT and immunotherapy is crucial, just as the dose and fractionation may be. Lower single doses may impact on tumor vascularization and immune cell infiltration in particular, while higher doses may impact on intratumoral induction and production of type I interferons. The induction of immunogenic cancer cell death seems in turn to be a common mechanism for most RT schemes. Dendritic cells (DCs) are activated by the released danger signals and by taking up tumor peptides derived from irradiated cells. DCs subsequently activate T cells, a process that has to be tightly controlled to ensure tolerance. Inhibitory pathways known as immune checkpoints exist for this purpose and are exploited by tumors to inhibit immune responses. Cytotoxic T lymphocyte antigen 4 (CTLA-4) and programmed cell death protein 1 (PD-1) on T cells are two major checkpoints. The biological concepts behind the findings that RT in combination with anti-CTLA-4 and/or anti-PD-L1 blockade stimulates CD8+ T cell-mediated anti-tumor immunity are reviewed in detail. On this basis, we suggest clinically significant combinations and sequences of RT and immune checkpoint inhibition. We conclude that RT and immune therapies complement one another.
EVALuna2:18336

Immune modulation by low dose radiation therapy-results from 70 patients followed up in the IMMO-LDRT01 study - Donaubauer, Anna-Jasmina; Gryc, Thomas; Becker, I.; Harrer, A.; Rühle, Paul-Friedrich; Ott, O. J.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36497

Immune modulatory effects of radiotherapy as basis for well-reasoned radioimmunotherapies - Rueckert, Michael; Fietkau, Rainer; Frey, Benjamin; Hecht, Markus; Gaipl, Udo; Deloch, Lisa (Strahlentherapie und Onkologie, 2018)
BACKGROUND: Radiotherapy (RT) has been known for decades as a local treatment modality for malign and benign disease. In order to efficiently exploit the therapeutic potential of RT, an understanding of the immune modulatory properties of ionizing radiation is mandatory. These should be used for improvement of radioimmunotherapies for cancer in particular. METHODS: We here summarize the latest research and review articles about immune modulatory properties of RT, with focus on radiation dose and on combination of RT with selected immunotherapies. Based on the knowledge of the manifold immune mechanisms that are triggered by RT, thought-provoking impulse for multimodal radioimmunotherapies is provided. RESULTS: It has become obvious that ionizing radiation induces various forms of cell death and associated processes via DNA damage initiation and triggering of cellular stress responses. Immunogenic cell death (ICD) is of special interest since it activates the immune system via release of danger signals and via direct activation of immune cells. While RT with higher single doses in particular induces ICD, RT with a lower dose is mainly responsible for immune cell recruitment and for attenuation of an existing inflammation. The counteracting immunosuppression emanating from tumor cells can be overcome by combining RT with selected immunotherapies such as immune checkpoint inhibition, TGF-β inhibitors, and boosting of immunity with vaccination. CONCLUSION: In order to exploit the full power of RT and thereby develop efficient radioimmunotherapies, the dose per fraction used in RT protocols, the fractionation, the quality, and the quantity of certain immunotherapies need to be qualitatively and chronologically well-matched to the individual immune status of the patient.
EVALuna2:36465

Immune suppressive properties of Glioblastoma cells might result in part from radiation-induced increased expression of inhibitory immune checkpoint molecules - Langenfelder, E.; Derer, Anja; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36504

Immunological basis of abscopal antitumor responses induced with radio-immunotherapy - Rueckert, M.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (2017)
EVALuna2:32891

Immunological basis of local and abscopal antitumor responses induced with radio-immunotherapy - Rueckert, M.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (2017)
EVALuna2:32863

Immunomodulation by ionizing radiation-impact for design of radio-immunotherapies and for treatment of inflammatory diseases - Frey, Benjamin; Rueckert, Michael; Rühle, Paul-Friedrich; Derer, Anja; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (Immunological Reviews, 2017)
Ionizing radiation is often regarded as an element of danger. But, danger responses on the cellular and molecular level are often beneficial with regard to the induction of anti-tumor immunity and for amelioration of inflammation. We outline how in dependence of radiation dose and fraction, radiation itself-and especially in combination with immune modulators-impacts on the innate and adaptive immune system. Focus is set on radiation-induced changes of the tumor cell phenotype and the cellular microenvironment including immunogenic cancer cell death. Mechanisms how anti-tumor immune responses are triggered by radiotherapy in combination with hyperthermia, inhibition of apoptosis, the adjuvant AnnexinA5, or vaccination with high hydrostatic pressure-killed autologous tumor cells are discussed. Building on this, feasible multimodal radio-immunotherapy concepts are reviewed including overcoming immune suppression by immune checkpoint inhibitors and by targeting TGF-β. Since radiation-induced tissue damage, inflammation, and anti-tumor immune responses are interconnected, the impact of lower doses of radiation on amelioration of inflammation is outlined. Closely meshed immune monitoring concepts based on the liquid biopsy blood are suggested for prognosis and prediction of cancer and non-cancer inflammatory diseases. Finally, challenges and visions for the design of cancer radio-immunotherapies and for treatment of benign inflammatory diseases are given.
EVALuna2:32867

Immunomodulatory and analgesic Effects of serial Radon-Baths in Patients with musculoskeletal Diseases: Investigations in the RAD-ON02 Study - Donaubauer, Anna-Jasmina; Becker, Ina; Weikl, Lena; Klein, Gerhart; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Strahlentherapie und Onkologie, 2021)
CRIS-Team WoS Importer:2021-07-16

Immunophanotype modulating Properties of Ferrous Clathrochelates and Irradiation in Lung Cancer Cells - Alomo, Jannik; Becker, I.; Roessel, T.; Denzler, M.; Heim, L.; Mokhir, Andriy; Klemt, Insa; Voloshin, Y.; Selin, R.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Impact of age on the efficacy of oxaliplatin in the preoperative chemoradiotherapy and adjuvant chemotherapy of rectal cancer: a post hoc analysis of the CAO/ARO/AIO-04 phase III trial - Hofheinz, R. -D.; Arnold, D.; Fokas, E.; Kaufmann, M.; Hothorn, T.; Folprecht, G.; Fietkau, Rainer; Hohenberger, Werner; Ghadimi, M.; Liersch, T.; Grabenbauer, G. G.; Sauer, Rolf; et al. (Annals of Oncology, 2018)
Background: The German rectal cancer trial CAO/ARO/AIO-04 has shown a significant benefit in 3-year disease-free survival (DFS) of adding oxaliplatin to a standard preoperative 5-fluorouracil (5-FU)-based chemoradiotherapy (CRT) and adjuvant chemotherapy in patients with locally advanced rectal cancer. The use of oxaliplatin as adjuvant treatment in elderly patients with colon cancer is controversial. We therefore investigated the impact of age on clinical outcome in the CAO/ARO/AIO-04 phase III trial. Patients and methods: We carried out a post hoc analysis of the CAO/ARO/AIO-04 phase III trial evaluating primary and secondary end points according to age. Patient and tumor characteristics, NCI CTC adverse events grades 3-4 (version 3.0), dose intensities as well as survival and recurrence data were analyzed in three specified age groups (<60, 60-70, and ≥70 years). The influence of age as a continuous variable on DFS was modeled using a subpopulation treatment effect pattern plot (STEPP) analysis. Results: A total of 1232 patients were assessable. With the exception of Eastern Cooperative Oncology Group status (P < 0.001), no differences in patient and tumor characteristics were noticed between age groups. Likewise, toxicity pattern, dose intensities of CRT and surgical results were similar in all age groups. After a median follow-up of 50 months, in patients aged <60 years a significant benefit of adding oxaliplatin to 5-FU-based CRT and adjuvant chemotherapy was observed for local (P = 0.013) and systemic recurrences (P = 0.023), DFS (P = 0.011), and even overall survival (OS; P = 0.044). The STEPP analysis revealed improved hazard ratios for DFS in patients aged 40-70 years compared with elderly patients treated with oxaliplatin. Conclusion: The addition of oxaliplatin significantly improved DFS and OS in younger patients aged <60 years with advanced rectal cancer. Patients aged ≥70 years had no benefit. Clinical Trials Number: NCT00349076.
EVALuna2:36460

Impact of Citrate-stabilized superparamagnetic Iron Oxide-Nanoparticles on Head and Neck Tumor Cell Lines in Combination Therapy with ionizing Radiation - Schreiber, C.; Franzen, T.; Fietkau, Rainer; Tietze, Rainer; Stein, René; Friedrich, Bernhard; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Impact of COVID-19 on Quality of Life in Long-Term Advanced Rectal Cancer Survivors - Blasko, Daniel; Schweizer, Claudia; Fitz, Tim; Schröter, Christoph; Sörgel, Christopher; Kallies, Annett; Fietkau, Rainer; Distel, Luitpold (Healthcare, 2023)
Colorectal cancer remains one of the most commonly diagnosed cancers. Advanced rectal cancer patients receive neoadjuvant radiochemotherapy as well as surgery and suffer from reduced health-related quality of life due to various side effects. We were interested in the role of the COVID-19 pandemic and how it affected those patients’ quality of life. A total of 489 advanced rectal cancer patients from the University Hospital Erlangen in Germany were surveyed between May 2010 and March 2022 and asked to fill out the EORTC QLQ-C30 and QLQ-CR38 questionnaires over eight different time points: at the beginning, during and after radiochemotherapy, right before surgery, and in yearly intervals after surgery for up to four years. Answers were converted to scores to compare the COVID-19 period to the time before March 2020, focusing on the follow-ups, the developments over time—including by sex and age—and the influence of the TNM cT-stage. Overall, a trend of impaired functional and symptom scores was found across all surveys with few significances (body image −10.6 percentage points (pp) after one year; defecation problems +13.5 pp, insomnia +10.2 pp and weight loss +9.8 pp after three years; defecation problems +11.3 pp after four years). cT4-stage patients lost significantly more weight than their cT1-3-stage counterparts (+10.7 to 13.7 pp). Further studies should be conducted to find possible causes and develop countermeasures for future major infectious diseases.
CRIS-Team Scopus Importer:2023-08-11
Keywords: COVID-19; pandemic; quality of life; radiochemotherapy; rectal cancer

Impact of fractionation and number of fields on dose homogeneity for intra-fractionally moving lung tumors using scanned carbon ion treatment - Woelfelschneider, Jens; Friedrich, Thomas; Luechtenborg, Robert; Zink, Klemens; Scholz, Michael; Dong, Lei; Durante, Marco; Bert, Christoph (Radiotherapy and Oncology, 2016)
Scanned particle beam therapy may result in over and under dosages within the target volume. This study quantifies how CTV dose coverage improves with number of fractions and fields.Based on 4DCTs of nine lung tumor patients, treatment plans were optimized separately for four different fields using an ITV approach. 4D RBE-weighted dose distributions were calculated for varying motion parameters and fraction numbers. The total RBE-weighted dose was determined for one and four-field application per fraction. DVHs were analyzed for the tumor and interpreted based on statistical modeling.Dose homogeneity within the CTV increased with the fraction number, but depends significantly on the tumor motion amplitude. For single-field schedules and amplitudes >6mm, the dose coverage indices (V95min=90.7% and V107max=0.4%) differed to the stationary case even after 40 fractions. Target coverage for a four-field approach followed a proposed model and homogeneous dose distributions could be achieved 6-times faster than single-field treatments.Fractionated delivery improves dose homogeneity in scanned ion beam therapy of moving targets. The achievable homogeneity depends mainly on tumor volume and motion amplitude. The outcome of multiple-field irradiations can be predicted based on single-field results and accelerates the achievement of homogeneous dose distributions.
EVALuna2:18345

Impact of hypo- and normofractionated radiation on cell death and senescence of HNSCC-cells of different HPV-Status - Wild, Kristina; Peitz, L.; Rieckmann, T.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
EVALuna2:36510

Impact of inter- and intra-observer variabilities of catheter reconstruction on multi-catheter interstitial brachytherapy of breast cancer patients - Kallis, Karoline; Kaltsas, Theodoros; Kreppner, Stephan; Lotter, Michael; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2019)
Purpose: The aim of this study was to evaluate inter- and intra-observer variabilities of catheter reconstruction and its dosimetric impact for multi-catheter interstitial breast cancer patients. Methods and materials: In order to evaluate inter-observer variabilities (IOV) three medical physicists reconstructed the catheter traces of 13 patients. These manual reconstructions were further compared to the automatic reconstruction algorithm integrated into the planning system and one on purpose imprecise manual reconstruction. For intra-observer variabilities (IAV) repeated reconstructions of two physicists were compared for 13 patients. In total 426 catheters were considered. Keeping dwell times, dwell positions, the optimization and the normalization relative points constant the geometrical deviations between the corresponding dwell positions of the reference data set and the investigated reconstructions were evaluated. Also, the effect on the quality indices, such as coverage index (CI), dose non-uniformity ratio (DNR) or conformal index (COIN), and the exposure of the organs at risk were analyzed. Results: Over all patients and all different catheter reconstructions considered for IOV a mean deviation between the corresponding dwell positions of 0.60 ± 0.35 mm was detected. The first observer had a mean deviation of 0.54 ± 0.32 mm, whereas the second observer yielded a mean deviation of 0.58 ± 0.37 mm. The length of the catheter traces varied in the mean by 0.51 ± 0.45 mm. The mean relative deviation of the CI, DNR, COIN, mean heart dose and mean lung dose varied by 0.27 ± 0.31%, 0.0027 ± 0.0025, 0.0036 ± 0.0033, 0.024 ± 0.019%, 0.05 ± 0.11%, respectively. The skin dose (D 0.2ccm ) changed in the maximum 8.52%. On average IAV reached a deviation between the corresponding dwell positions of 0.49 ± 0.30 mm. IOVs and IAVs proved to be significantly different (Wilcoxon's test p < 0.01). Conclusions: The study proved that a repeated reconstruction of the catheter traces does not lead to large geometrical deviations or to a significant change in the dose exposure. But the lack of ground truth makes the estimation of the quality of the reconstruction challenging. A precise reconstruction mapping the reality is a necessity for the planned dose delivery. With all considered reconstruction techniques reliable quality indices for the target and the organs at risk could be obtained.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Breast cancer; Inter-observer variability; Interstitial multi-catheter brachytherapy

Impact of patient positioning on interstitial multicatheter HDR brachytherapy of the breast - Abu-Hossin, N.; Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-18

Impact of postoperative radiotherapy and HER2/new overexpression in salivary duct carcinoma : A monocentric clinicopathologic analysis - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Hecht, Markus; Erber, Ramona; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
Retrospective Investigation of the prognostic relevance of clinicopathologic parameters in patients with salivary duct carcinoma (SDC).An experienced pathologist reviewed 67 patients with de novo SDC or SDC ex pleomorphic adenoma. Paraffin-embedded tumor samples were examined by immunohistochemistry for expression of HER2/neu, androgen (AR), progesterone (PR), estrogen (ER), epidermal growth factor (EGFR) and programmed death ligand 1 (PD-L1-R) receptor. In 45 patients who had cM0 and follow-up data available, survival rates were calculated (Kaplan-Meier method) and prognostic variables were analyzed (univariate analysis: log-rank test; multivariate analysis: Cox-regression analysis).Overexpression of HER2/neu, AR, ER, PR, EGFR, PD-L1-R was found in 25.4%, 84%, 0%, 0%, 17.9%, 16.4% of patients. Overall (OS), disease-free (DFS), distant-metastases-free survival (DMFS) and locoregional control (LRC) were 92.3/72.4/56.9%, 78.2/58.1/58.1%, 85.4/65.2/65.2% and 89.7/81.9/81.9% after 1/3/5 years (medial follow-up 26 months). In univariate analysis a positive resection margin (p = 0.008) and no postoperative radiotherapy (p = 0.001) predict an increased locoregional recurrence rate. In multivariate analysis only postoperative radiotherapy is statistically significant (p = 0.004). Presence of lymph node metastases, a lymph node density >4 and HER2/neu overexpression predict decreased DFS and DMFS. In multivariate HER2/neu overexpression was the only significant predictor for reduced DFS (p = 0.04) and DMFS (p = 0.02).Postoperative radiotherapy is the only significant predictor for LRC. HER2/neu receptor expression is an independent prognostic factor for decreased DFS and DMFS in patients with SDC. In addition to radio(chemo)therapy, intensified first-line treatment regimens should also be evaluated in the future.
EVALuna2:6895

Impact of radio(chemo)therapy on expression of immune checkpoint ligands PD-L1 and PD-L2 on murine and human melanoma cells - Riegel, Dania; Bäumler, Monika; Spiljar, Martina; Rückert, Michael; Frey, Benjamin; Fietkau, Rainer; Derer, Anja; Gaipl, Udo (DEGRO - Deutsche Gesellschaft für Radioonkologie e.V., 2017)
EVALuna2:32890

Impact of radiotherapy and chemotherapy on PD-L1 and EGF-R expression in melanoma and glioblastoma cells - Bäumler, Monika; Spiljar, Martina; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Derer, Anja (DEGRO - Deutsche Gesellschaft dür Radioonkologie e.V., 2016)

Impact of radon and combinatory radon/carbon dioxide spa on pain and hypertension: Results from the explorative RAD-ON01 study - Rühle, Paul-Friedrich; Klein, Gerhart; Rung, Tatiana; Phan, Hong Tiep; Fournier, Claudia; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Modern Rheumatology, 2019)
OBJECTIVES: Therapies with low doses of radon have beneficial effects on patients suffering from chronic painful degenerative and inflammatory diseases. We already showed that this is accompanied by systemic immune modulations. We here focus on pain-reducing effects of very low doses of radon by adding carbon dioxide water and its impact on heart rate variability (HRV), blood pressure and free radicals. METHODS: 97 of 103 patients receiving radon spa (1.200 Bq/l at 34 °C or 600 Bq/l, 1 g/l CO2 at 34 °C) were monitored before and at three different time points after therapy. Individual pain perception was analyzed and the capability to process radicals. At each time point, the hypertensive patients (n = 46) were examined over 24 h for blood pressure and HRV. RESULTS: Long-term pain reduction was observed in the majority of patients. A modulation of superoxide dismutase was identified, presumably representing a priming effect for lowering radiation stress. Further, lowering of blood pressure, especially in those patients who additionally received carbon dioxide, was seen. Radon did in particular impact on HRV implying lasting relaxation effects. CONCLUSION: Radon/carbon dioxide spa efficiently reduces pain. In particular, patients simultaneously suffering from painful and cardiovascular diseases should be treated by combination of radon and CO2.
EVALuna2:36466

IMPACT OF RADON SPA ON PAIN AND THE IMMUNE SYSTEM OF PATIENTS WITH MUSCULOSKELETAL DISORDERS - Becker, I.; Donaubauer, Anna-Jasmina; Klein, G.; Fournier, C.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Impaired renal function in stroke patients with atrial fibrillation - Sauer, Eva-Maria; Sauer, Rolf; Kallmuenzer, Bernd; Blinzler, Christian; Breuer, Lorenz; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2014)
Stroke patients with atrial fibrillation (AF) are prone to have comorbidities such as impaired renal function. Because poly-pharmacotherapy is often required in those patients, renal function is important to consider in light of renally cleared medications such as direct oral anticoagulants. In this study, we analyzed frequency and predictors for impaired renal function and its impact on functional outcome in stroke patients with underlying AF.We analyzed 272 patients with acute ischemic stroke and AF of our prospective, observational stroke database. Estimated glomerular filtration rate (eGFR) was calculated on admission and during hospitalization from the equation of the Modification Diet for Renal Disease. Outcome measures included mortality and functional outcome at 90 days, assessed as modified Rankin Scale (mRS) score.On admission, impaired renal function was found in 41.5% (n = 113) and was associated with worse 90-day outcome (mRS score <= 2: 26.5% versus 45.9%, P = .001) and a higher mortality rate (23.9% versus 14.5%, P = .043). Multivariate logistic regression identified older age and history of myocardial infarction as independent predictors of renal dysfunction on admission (P < .05). Normalization of eGFR during hospitalization was achieved in 55.8%.In patients with acute ischemic stroke and AF, impaired renal function on admission is frequent and associated with worse outcome. Normalization of eGFR can often be achieved during hospitalization, but in everyday life, fluctuations of renal function because of infection or dehydration have to be considered. Careful monitoring of renal status is indispensable and should influence drug treatment decisions.
EVALuna2:22248

Implant-based CT estimation towards adaptive breast brachytherapy - Dürrbeck, Christopher; Pflaum, L.; Schulz, M.; Kallis, Karoline; Geimer, Tobias; Abu-Hossin, N.; Strnad, Vratislav; Maier, Andreas; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-18

Implementation and validation of 2-D-array based tests in routine linac quality assurance - Valenta, Jiří; Schmidt, Manfred; Bert, Christoph (Zeitschrift für Medizinische Physik, 2024)
Purpose: In medical linac quality assurance (QA), to replace film dosimetry with low-resolution 2-D ionization chamber array measurements, to validate the procedures, and to perform a comprehensive sensitivity analysis. Methods: A 2-D ionization chamber array with a spatial resolution of 7.62 mm was deployed to perform the following tests: Junction tests, MLC transmission test, beam profile constancy vs. gantry angle test, beam profile constancy vs. low dose delivery test, and beam energy constancy vs. low dose delivery test. Test validation and sensitivity analyses based on short- and long-term statistics of the test results were performed. Results: All selected mechanical and dosimetry tests could be successfully performed with a 2-D array. Considering the tolerance limits recommended by the AAPM Task Group 142 report (2009), sensitivities of 99.0% or better and specificities ranging from 99.5% to 99.9% could be achieved in all tests when the proper metrics were chosen. Conclusions: The results showed that a low-resolution 2-D ionization chamber array could replace film dosimetry without having to sacrifice high test sensitivity. Its implementation in the routine clinical linac QA program may involve considerable QA time savings.
CRIS-Team Scopus Importer:2024-03-22
Keywords: 2-D array; Linear accelerator quality assurance; Test sensitivity; Test specificity

Implementation of a dedicated 1.5 T MR scanner for radiotherapy treatment planning featuring a novel high-channel coil setup for brain imaging in treatment position - Mengling, Veit; Bert, Christoph; Perrin, Rosalind; Masitho, Siti; Weissmann, Thomas; Mansoorian, Sina; Siavooshhaghighi, Hadi; Janka, Rolf Matthias; Doussin, Sylvain; Habatsch, Melanie; Fietkau, Rainer; Putz, Florian (Strahlentherapie und Onkologie, 2020)
Purpose: To share our experiences in implementing a dedicated magnetic resonance (MR) scanner for radiotherapy (RT) treatment planning using a novel coil setup for brain imaging in treatment position as well as to present developed core protocols with sequences specifically tuned for brain and prostate RT treatment planning. Materials and methods: Our novel setup consists of two large 18-channel flexible coils and a specifically designed wooden mask holder mounted on a flat tabletop overlay, which allows patients to be measured in treatment position with mask immobilization. The signal-to-noise ratio (SNR) of this setup was compared to the vendor-provided flexible coil RT setup and the standard setup for diagnostic radiology. The occurrence of motion artifacts was quantified. To develop magnetic resonance imaging (MRI) protocols, we formulated site- and disease-specific clinical objectives. Results: Our novel setup showed mean SNR of 163 ± 28 anteriorly, 104 ± 23 centrally, and 78 ± 14 posteriorly compared to 84 ± 8 and 102 ± 22 anteriorly, 68 ± 6 and 95 ± 20 centrally, and 56 ± 7 and 119 ± 23 posteriorly for the vendor-provided and diagnostic setup, respectively. All differences were significant (p > 0.05). Image quality of our novel setup was judged suitable for contouring by expert-based assessment. Motion artifacts were found in 8/60 patients in the diagnostic setup, whereas none were found for patients in the RT setup. Site-specific core protocols were designed to minimize distortions while optimizing tissue contrast and 3D resolution according to indication-specific objectives. Conclusion: We present a novel setup for high-quality imaging in treatment position that allows use of several immobilization systems enabling MR-only workflows, which could reduce unnecessary dose and registration inaccuracies.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Immobilization; MR-only treatment planning; Prostate; Simulation; Stereotactic radiosurgery

Implementation of an analytical model for leakage neutron equivalent dose in a proton radiotherapy planning system - Eley, John; Newhauser, Wayne; Homann, Kenneth; Howell, Rebecca; Schneider, Christopher; Durante, Marco; Bert, Christoph (Cancers, 2015)
Equivalent dose from neutrons produced during proton radiotherapy increases the predicted risk of radiogenic late effects. However, out-of-field neutron dose is not taken into account by commercial proton radiotherapy treatment planning systems. The purpose of this study was to demonstrate the feasibility of implementing an analytical model to calculate leakage neutron equivalent dose in a treatment planning system. Passive scattering proton treatment plans were created for a water phantom and for a patient. For both the phantom and patient, the neutron equivalent doses were small but non-negligible and extended far beyond the therapeutic field. The time required for neutron equivalent dose calculation was 1.6 times longer than that required for proton dose calculation, with a total calculation time of less than 1 h on one processor for both treatment plans. Our results demonstrate that it is feasible to predict neutron equivalent dose distributions using an analytical dose algorithm for individual patients with irregular surfaces and internal tissue heterogeneities. Eventually, personalized estimates of neutron equivalent dose to organs far from the treatment field may guide clinicians to create treatment plans that reduce the risk of late effects.
EVALuna2:18366

Implementation of double immune checkpoint blockade increases response rate to induction chemotherapy in head and neck cancer - Semrau, Sabine; Gostian, Antoniu Oreste; Traxdorf, Maximilian; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Hautmann, Matthias; Klautke, Gunther; Laban, Simon; Brunner, Thomas; Tamaskovics, Bálint; et al. (Cancers, 2021)
To determine whether a single dose of double immune checkpoint blockade (induction chemoimmunotherapy (ICIT)) adds benefit to induction single-cycle platinum doublet (induction chemotherapy (IC)) in locally advanced head and neck squamous cell carcinoma (HNSCC), patients treated with cisplatin 30 mg/m2 d1-3 and docetaxel 75 mg/m2 d1 combined with durvalumab 1500 mg fixed dose d5 and tremelimumab 75 mg fixed dose d5 (ICIT) within the CheckRad-CD8 trial were compared with a retrospective cohort receiving the same chemotherapy (IC) without immunotherapy. The endpoint of this analysis was the complete response rate (CR). A total of 53 patients were treated with ICIT and 104 patients with IC only. CR rates were 60.3% for ICIT and 40.3% for IC (p = 0.018). In the total population (n = 157), the most important predictor to achieve a CR was treatment type (OR: 2.21 for ICIT vs. IC; p = 0.038, multivariate analysis). The most diverse effects in CR rates between ICIT and IC were observed in younger (age ≤ 60) patients with HPV-positive OPSCCs (82% vs. 33%, p = 0.176), while there was no difference in older patients without HPV-positive OPSCCs (53% vs. 48%). The analysis provides initial evidence that ICIT could result in higher CR rates than IC. Young patients with HPV-positive OPSCCs may have the greatest benefit from additional immune checkpoint inhibitors.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Combined modality therapy; Double immune checkpoint inhibition; Head and neck neoplasms; HPV-positive OPSCC; Immunotherapy; Induction therapy; Organ preservation

Implementation of registration quality assurance - Anderle, K.; Brandt, Tobias; Wölfelschneider, Jens; Bert, Christoph; Graeff, C. (2018)
EVALuna2:36477

Implementation of Whole Skin Therapy: Dosimetry, Optimization and FMEA Analysis - Shariff, Maya; Lotter, M.; Stillkrieg, W.; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Improved outcome of adult Burkitt lymphoma/leukemia with rituximab and chemotherapy: report of a large prospective multicenter trial - Hoelzer, Dieter; Walewski, Jan; Doehner, Hartmut; Viardot, Andreas; Hiddemann, Wolfgang; Spiekermann, Karsten; Serve, Hubert; Duehrsen, Ulrich; Huettmann, Andreas; Thiel, Eckhard; Dengler, Jolanta; Kneba, Michael; et al. (Blood, 2014)
This largest prospective multicenter trial for adult patients with Burkitt lymphoma/leukemia aimed to prove the efficacy and feasibility of short-intensive chemotherapy combined with the anti-CD20 antibody rituximab. From 2002 to 2011, 363 patients 16 to 85 years old were recruited in 98 centers. Treatment consisted of 6 5-day chemotherapy cycles with high-dose methotrexate, high-dose cytosine arabinoside, cyclophosphamide, etoposide, ifosphamide, corticosteroids, and triple intrathecal therapy. Patients >55 years old received a reduced regimen. Rituximab was given before each cycle and twice as maintenance, for a total of 8 doses. The rate of complete remission was 88% (319/363); overall survival (OS) at 5 years, 80%; and progression-free survival, 71%; with significant difference between adolescents, adults, and elderly patients (OS rate of 90%, 84%, and 62%, respectively). Full treatment could be applied in 86% of the patients. The most important prognostic factors were International Prognostic Index (IPI) score (0-2 vs 3-5; P = .0005), age-adjusted IPI score (0-1 vs 2-3; P = .0001), and gender (male vs female; P = .004). The high cure rate in this prospective trial with a substantial number of participating hospitals demonstrates the efficacy and feasibility of chemoimmunotherapy, even in elderly patients. This trial was registered at www.clinicaltrials.gov as #NCT00199082.
EVALuna2:18183

Improved survival for elderly married glioblastoma patients : Better treatment delivery, less toxicity, and fewer disease complications - Putz, Florian; Putz, Tobias; Goerig, Nicole; Knippen, Stefan; Gryc, Thomas; Eyüpoglu, Ilker Yasin; Roessler, Karl; Semrau, Sabine; Lettmaier, Sebastian; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
OBJECTIVES: Marital status is a well-described prognostic factor in patients with gliomas but the observed survival difference is unexplained in the available population-based studies. METHODS: A series of 57 elderly glioblastoma patients (≥70 years) were analyzed retrospectively. Patients received radiotherapy or chemoradiation with temozolomide. The prognostic significance of marital status was assessed. Disease complications, toxicity, and treatment delivery were evaluated in detail. RESULTS: Overall survival was significantly higher in married than in unmarried patients (median, 7.9 vs. 4.0 months; p = 0.006). The prognostic significance of marital status was preserved in the multivariate analysis (HR, 0.41; p = 0.011). Married patients could receive significantly higher daily temozolomide doses (mean, 53.7 mg/m² vs. 33.1 mg/m²; p = 0.020), were more likely to receive maintenance temozolomide (45.7 % vs. 11.8 %; p = 0.016), and had to be hospitalized less frequently during radiotherapy (55.0 % vs. 88.2 %; p = 0.016). Of the patients receiving temozolomide, married patients showed significantly lower rates of hematologic and liver toxicity. Most complications were infectious or neurologic in nature. Complications of any grade were more frequent in unmarried patients (58.8 % vs. 30.0 %; p = 0.041) with the incidence of grade 3-5 complications being particularly elevated (47.1 % vs. 15.0 %; p = 0.004). CONCLUSION: We found poorer treatment delivery as well as an unexpected severe increase in toxicity and disease complications in elderly unmarried glioblastoma patients. Marital status may be an important predictive factor for clinical decision-making and should be addressed in further studies.
EVALuna2:32918

Improvement of Deep Learning-based Auto-detection of Brain Metastases by Integrating previous MRI Images - Dörfler, Arnd; Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Maier, Andreas; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Increased Radiation Sensitivity in Patients with Phelan-McDermid Syndrome - Jesse, Sarah; Kuhlmann, Lukas; Hildebrand, Laura; Magelssen, Henriette; Schmaus, Martina; Timmermann, Beate; Andres, Stephanie; Fietkau, Rainer; Distel, Luitpold (Cells, 2023)
Phelan-McDermid syndrome is an inherited global developmental disorder commonly associated with autism spectrum disorder. Due to a significantly increased radiosensitivity, measured before the start of radiotherapy of a rhabdoid tumor in a child with Phelan-McDermid syndrome, the question arose whether other patients with this syndrome also have increased radiosensitivity. For this purpose, the radiation sensitivity of blood lymphocytes after irradiation with 2Gray was examined using the G0 three-color fluorescence in situ hybridization assay in a cohort of 20 patients with Phelan-McDermid syndrome from blood samples. The results were compared to healthy volunteers, breast cancer patients and rectal cancer patients. Independent of age and gender, all but two patients with Phelan-McDermid syndrome showed significantly increased radiosensitivity, with an average of 0.653 breaks per metaphase. These results correlated neither with the individual genetic findings nor with the individual clinical course, nor with the respective clinical severity of the disease. In our pilot study, we saw a significantly increased radiosensitivity in lymphocytes from patients with Phelan-McDermid syndrome, so pronounced that a dose reduction would be recommended if radiotherapy had to be performed. Ultimately, the question arises as to the interpretation of these data. There does not appear to be an increased risk of tumors in these patients, since tumors are rare overall. The question, therefore, arose as to whether our results could possibly be the basis for processes, such as aging/preaging, or, in this context, neurodegeneration. There are no data on this so far, but this issue should be pursued in further fundamentally based studies in order to better understand the pathophysiology of the syndrome.
CRIS-Team Scopus Importer:2023-03-24
Keywords: atypical teratoid rhabdoid tumor; chromosomal aberrations; Phelan McDermid syndrome; radiation sensitivity; SHANK3 deficiency

Increased skin and mucosal toxicity in the combination of vemurafenib with radiation therapy - Merten, Ricarda; Hecht, Markus; Haderlein, Marlen; Distel, Luitpold; Fietkau, Rainer; Heinzerling, Lucie; Semrau, Sabine (Strahlentherapie und Onkologie, 2014)
Palliative radiotherapy is often required for patients with metastatic malignant melanoma in the case of bone or brain metastases. Since BRAF inhibitor therapy is highly efficient in V600-mutated melanomas, there is hesitation to stop it during radiotherapy. Consequently, radiotherapy under simultaneous vemurafenib treatment is frequently needed.We report the case of a patient receiving palliative radiotherapy of spinal bone metastases before and during vemurafenib therapy. The skin reactions were quantitatively scored using computer-assisted digital image evaluation.Radiotherapy without vemurafenib was tolerated very well, whereas radiotherapy under simultaneous vemurafenib treatment resulted in accentuated skin reactions. Furthermore, the patient developed dysphagia and had to be hospitalized for parenteral nutrition. In the quantitative analysis, there was a twofold increase in pigmentation and erythema of the irradiated skin area of the thoracic spine when vemurafenib was combined with radiotherapy compared with radiotherapy treatment alone. This is the first reported case of a patient showing no complications during radiotherapy without vemurafenib but remarkable skin and mucosal toxicity under concurrent vemurafenib therapy. Thus, a genetically conditioned individually elevated radiosensitivity can definitely be excluded. Compared with other reported cases, radiosensitization was not limited to the skin, but also affected the esophageal mucosa.Vemurafenib is a strong radiosensitizer. Patients receiving radiotherapy under simultaneous vemurafenib treatment should be monitored very closely.
EVALuna2:18209

Increase in non-professional phagocytosis during the progression of cell cycle - Hofmann, Alexander; Putz, Florian; Büttner-Herold, Maike; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (PLoS ONE, 2021)
Homotypic or heterotypic internalization of another, either living or necrotic cell is currently in the center of research interest. The active invasion of a living cell called entosis and cannibalism of cells by rapidly proliferating cancers are prominent examples. Additionally, normal healthy tissue cells are capable of non-professional phagocytosis. This project studied the relationship between non-professional phagocytosis, individual proliferation and cell cycle progression. Three mesenchymal and two epithelial normal tissue cell lines were studied for homotypic non-professional phagocytosis. Homotypic dead cells were co-incubated with adherent growing living cell layers. Living cells were synchronized by mitotic shake-off as well as Aphidicolin-treatment and phagocytotic activity was analyzed by immunostaining. Cell cycle phases were evaluated by flow cytometry. Mesenchymal and epithelial normal tissue cells were capable of internalizing dead cells. Epithelial cells had much higher non-professional phagocytotic rates than mesenchymal cells. Cells throughout the entire cell cycle were able to phagocytose. The phagocytotic rate significantly increased with progressing cell cycle phases. Mitotic cells regularly phagocytosed dead cells, this was verified by Nocodazole and Colcemid treatment. Taken together, our findings indicate the ability of human tissue cells to phagocytose necrotic neighboring cells in confluent cell layers. The origin of the cell line influences the rate of cell-in-cell structure formation. The higher cell-in-cell structure rates during cell cycle progression might be influenced by cytoskeletal reorganization during this period or indicate an evolutionary anchorage of the process. Recycling of nutrients during cell growth might also be an explanation. ?2021 Hofmann et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
CRIS-Team Scopus Importer:2021-02-19

Individualization of post-mastectomy radiotherapy and regional nodal irradiation based on treatment response after neoadjuvant chemotherapy for breast cancer : A systematic review - Krug, David; Baumann, Rene; Budach, Wilfried; Dunst, Juergen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Hehr, Thomas; Piroth, Marc D.; Sedlmayer, Felix; Souchon, Rainer; et al. (Strahlentherapie und Onkologie, 2018)
PURPOSE: To review the evidence regarding post-mastectomy radiotherapy (PMRT) and regional nodal irradiation (RNI) after neoadjuvant chemotherapy (NACT) for breast cancer, with a special focus on individualization of adjuvant radiotherapy based on treatment response. METHODS: A systematic literature search using the PubMed/Medline database was performed. We included prospective and retrospective reports with a minimum of 10 patients that had been published since 1st January 2000, and provided clinical outcome data analyzed by treatment response and radiotherapy. RESULTS: Out of 763 articles identified via PubMed/Medline and hand search, 68 full text-articles were assessed for eligibility after screening of title and abstract. 13 studies were included in the systematic review, 9 for PMRT and 5 for RNI. All included studies were retrospective reports. CONCLUSIONS: There is a considerable lack of evidence regarding the role of adjuvant radiotherapy and its individualization based on treatment response after NACT. Results of prospective randomized trials such as NSABP B‑51/RTOG 1304 and Alliance A11202 are eagerly awaited.
EVALuna2:36467

Individual Radiation Sensitivity of Tumor Patients with Rheumatoid Arthritis - Rzepka, Dinah; Schuster, Barbara; Geinitz, H.; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Induction chemoimmunotherapy followed by CD8+ immune cell-based patient selection for chemotherapy-free radioimmunotherapy in locally advanced head and neck cancer - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias Günther; Brunner, Thomas B.; Tamaskovics, Bálint; Hinke, Axel; Zhou, Jianguo; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Purpose The first aim of the trial is to study feasibility of combined programmed death protein ligand 1/cytotoxic T-lymphocyte-associated protein 4 inhibition concomitant to radiotherapy. In addition, efficacy of the entire treatment scheme consisting of induction chemoimmunotherapy followed by chemotherapy-free radioimmunotherapy (RIT) after intratumoral CD8 +immune cell-based patient selection will be analyzed. Methods Patients with stage III-IVB head and neck squamous cell carcinoma were eligible for this multicenter phase II trial. Treatment consisted of a single cycle of cisplatin 30 mg/m² days 1-3, docetaxel 75 mg/m² day 1, durvalumab 1500 mg fix dose day 5 and tremelimumab 75 mg fix dose day 5. Patients with increased intratumoral CD8 +immune cell density or pathological complete response (pCR) in the rebiopsy entered RIT up to a total dose of 70 Gy. Patients received further three cycles of durvalumab/tremelimumab followed by eight cycles of durvalumab mono (every 4 weeks). The intended treatment for patients not meeting these criteria was standard radiochemotherapy outside the trial. Primary endpoint was a feasibility rate of patients entering RIT to receive treatment until at least cycle 6 of immunotherapy of ≥80%. Results Between September 2018 and May 2020, 80 patients were enrolled (one excluded). Out of these, 23 patients had human papilloma virus (HPV)-positive oropharyngeal cancer. Median follow-up was 17.2 months. After induction chemoimmunotherapy 41 patients had pCR and 31 had increased intratumoral CD8 +immune cells. Of 60 patients entering RIT (primary endpoint cohort), 10 experienced imiting toxic (mainly hepatitis) and four discontinued for other reasons, resulting in a feasibility rate of 82%. The RIT cohort (n=60) had a progression-free survival (PFS) rate at one and 2 years of 78% and 72%, respectively, and an overall survival rate at one and 2 years of 90% and 84%, respectively. Patients with HPV-positive oropharyngeal cancers had greater benefit from RIT with a 2-year PFS rate of 94% compared with 64% for HPV-negative oropharyngeal cancers and other locations. In the entire study cohort (n=79) the 2-year PFS rate was 68% (91% for HPV-positive oropharynx vs 59% for others). Toxicity grade 3-4 mainly consisted of dysphagia (53%), leukopenia (52%) and infections (32%). Conclusions The trial met the primary endpoint feasibility of RIT. Induction chemo-immunotherapy followed by chemotherapy-free RIT after intratumoral CD8 +immune cell-based patient selection has promising PFS. Trial registration number The trial was registered with ClinicalTrials.gov (identifier: NCT03426657). The trial was conducted as investigator-sponsored trial (IST).
CRIS-Team Scopus Importer:2022-02-11
Keywords: radioimmunotherapy

Induction of Senescence in Head and Neck Tumor Cells by Combination of Irradiation and DNA Repair Inhibitors - Dobler, Clara; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Inflammatory cells infiltrating HPV positive and negative head and neck squamous cell carcinoma - Distel, Luitpold; Farhoumand, D.; Haderlein, Marlen; Fietkau, Rainer (2018)
EVALuna2:36493

Inflammatory Cells in HPV positive and negative Head and Neck Tumors - Distel, Luitpold; Haderlein, Marlen; Farhoumand, D.; Fietkau, Rainer; Hecht, Markus (2018)
EVALuna2:36483

Influence and compensation of patient motion in electromagnetic tracking based quality assurance in interstitial brachytherapy of the breast - Dürrbeck, Christopher; Gulde, Sarah; Abu-Hossin, Nadin; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Medical Physics, 2022)
Purpose: Electromagnetic tracking (EMT) is a versatile and viable technique for various quality assurance (QA) tasks in interstitial brachytherapy (iBT). As the duration of EMT measurements in iBT is on the order of minutes, they can be strongly affected by patient motion, especially breathing, which gives rise to motion artefacts. Since the centrepiece of EMT-related QA in iBT is to assess the geometry of the iBT implant or applicator, the absence of adequate motion compensation techniques could impede the use of EMT for QA purposes. A common way to compensate for this is to reference the data to either external or internal reference sensors (ERS, IRS) which are fixated on the patient's body or inside the applicator and therefore move with the patient. The purpose of the presented study is to provide a quantitative and in-depth analysis on the use of reference sensors for motion compensation. Methods: First, the need for adequate motion compensation is identified both qualitatively and quantitatively using a phantom subjected to simulated breathing motion. An evaluation routine is developed to assess the influence of motion compensation using reference sensors on the acquired EMT data. The evaluation metric is based on the observed displacement of the EMT sensor from its mean position while dwelling at a dwell position (DP) for a dwell time of 1 s. After that, the routine is applied to a cohort of 54 breast cancer patients treated with iBT, and the quality of an ERS based compensation approach is assessed. In a subgroup of four patients, an IRS is inserted into the iBT implant and IRS-based compensation is compared to the ERS-based approach. Moreover, a correlation analysis of the ERS and IRS approach is performed, also including respiratory signals derived from the trajectories of the different reference sensors. Results: It was found that motion compensation with ERS effectively reduced the mean sensor displacement per DP to median values as low as 0.11 mm in both phantom and patient measurements, which is below the precision of the EMT system (0.48 mm). Compensation using the IRS yielded comparable results and was as good as compensation with ERS. The results obtained from both approaches showed a strong correlation. Also the respiratory signals calculated from the different reference sensors were well correlated in most cases. Conclusion: These results indicate that motion compensation with ERS can effectively remove motion artefacts in EMT data. While compensation with an IRS leads to comparable results, the IRS occupies one catheter whose geometry hence cannot be assessed. The use of ERS has proven to be both effective and practical in clinical routine.
CRIS-Team Scopus Importer:2022-03-04
Keywords: breast cancer; breathing motion; electromagnetic tracking; interstitial brachytherapy; quality assurance

Influence and mechanistic principles of radio(chemo) therapy on PD-L1 and EGF-R expression on melanoma and glioblastoma cells - Baeumler, M.; Spiljar, M.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Derer, Anja (DEGRO - Deutsche Gesellschaft für Radioonkologie e.V., 2017)
EVALuna2:32877

Influence of alectinib and crizotinib on ionizing radiation - in vitro analysis of ALK/ROS1-wildtype lung tissue cells - Jost, Tina; Schultz, Ann Kristin; Frey, Benjamin; Vu, Jennifer; Fietkau, Rainer; Distel, Luitpold; Hecht, Markus (Neoplasia, 2022)
(1) Background: Just little is known about the interaction of ALK/ROS1-targeting kinase inhibitors with ionizing radiation (IR), particularly regarding side effects. We investigated the toxicity in two different lung cell lines both ALK/ROS1 wildtype (healthy and tumor origin) as representatives for normal lung tissue; (2) Methods: Human lung cell line BEAS-2B and malignant A549 lung cancer cells (ALK/ROS1 wt) were treated with alectinib or crizotinib, 2 Gy irradiation or a combination of KI and IR. Cell toxicity was analyzed by cell death (Annexin, 7AAD), colony forming, migration assay and live-cell imaging (TMRM, DRAQ7, Caspase3/7). Cell cycle (Hoechst) were analyzed by flow cytometry; (3) Results: Crizotinib led to higher cell death rates than alectinib, when cells were treated with 10 µM KI. Alectinib induced a more intense growth inhibition of colonies. Both inhibitors showed additive effects in combination with irradiation. Combination treatment (IR + KI) does not lead to synergistic effect on neither cell death nor colony forming; (4) Conclusions: The influence of simultaneous KI and IR was studied in non-mutated ALK/ROS1 cell lines. Both KIs seems to be well tolerated in combination with thoracic radiotherapy and lacked synergistic reinforcement in cellular toxicity. This supports the feasibility of ALK/ROS1 inhibition in combination with thoracic irradiation in future clinical trials.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Alectinib; Crizotinib; Lung cells; Normal tissue; Radiotherapy; Side effects

Influence of CDK4/6 Inhibitors and Ionizing Radiation on Senescence in Breast Cancer Cells - Quarz, L.; Jost, Tina; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Influence of ex vivo Hyperthermia caused by Warm Water or Microwave Irradiation in a Circulatory System and/or Irradiation on the immunogenic Potential of B16 Melanoma and MCF-7 / MDA-MB-231 Breast Cancer Cells - Hader, Michael; Savcigil, D. P.; Rosin, A.; Gekle, S.; Wadepohl, M.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Influence of fractional Radio(chemo)therapy on the Expression Patterns of immunocheckpoint Molecules on Glioblastoma Cell Lines - Ladinig, A.; Schatz, Johannes; Fischer, R.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Derer, Anja (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Influence of gender on radiosensitivity during radiochemotherapy of advanced rectal cancer - Schuster, Barbara; Hecht, Markus; Schmidt, Manfred; Haderlein, Marlen; Jost, Tina; Büttner-Herold, Maike; Weber, Klaus; Denz, Axel; Grützmann, Robert; Hartmann, Arndt; Geinitz, Hans; Fietkau, Rainer; et al. (Cancers, 2022)
Gender is increasingly recognized as an important factor in medicine, although it has long been neglected in medical research in many areas. We have studied the influence of gender in advanced rectal cancer with a special focus on radiosensitivity. For this purpose, we studied a cohort of 495 men (84.1% ≥ T3, 63.6% N1, 17.6%, M1) and 215 women (84.2% ≥ T3, 56.7% N1, 22.8%, M1) who all suffered from advanced rectal cancer and were treated with radiochemotherapy. The energy deposited, DNA double-strand break (dsb) repair, occurrence of chromosomal aberrations, duration of therapy, tumor regression and tumor-infiltrating lymphocytes, laboratory parameters, quality of life and survival were assessed. The residual DNA dsb damage 24 h after irradiation in lymphocytes was identical in both sexes. Furthermore, chromosomal aberrations accurately reflecting radiosensitivity, were similar in both sexes. There were no gender-dependent differences in tumor regression, tumor-infiltrating lymphocytes and outcome indicating no differences in the radiosensitivity of cancer cells. The irradiated tumor volume in women was slightly lower than in men, related to body weight, no difference was observed. However, when the total energy deposited was calculated and related to the body weight, women were exposed to higher amounts of ionizing radiation. During radiochemotherapy, decreases in blood lymphocyte counts and albumin and several quality-of-life parameters such as nausea and vomiting, loss of appetite, and diarrhea were significantly worse in women. There is no difference in radiation sensitivity between men and women in both normal tissue and tumors. During radiochemotherapy, the quality of life deteriorates more in women than in men. However, women also recover quickly and there are no long-term differences in quality of life.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Blood values; Deposited energy; DNA double-strand breaks; Gender; Quality of life; Radiochemotherapy; Radiosensitivity; Radiosensitivity; Rectal cancer

Influence of MRI Distortion Correction on the local Control of stereotactically irradiated Brain Metastases - Putz, Florian; Siavooshhaghighi, Hadi; Grigo, Johanna; Masitho, Siti; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Schmidt, Manfred; Semrau, Sabine; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Influence of neoadjuvant Radiation Therapy on the Quality of Life in Patients with advanced Rectal Cancer over a Period of 5 Years - Sörgel, Celena; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Influence of p16 status on indication and outcome of salvage neck dissection in oropharyngeal cancer - Müller, Sarina Katrin; Mantsopoulos, Konstantinos; Semrau, Sabine; Agaimy, Abbas; Eckstein, Markus; Traxdorf, Maximilian; Gostian, Antoniu Oreste; Goncalves, Miguel; Sievert, Matti; Haderlein, Marlen; Grundtner, Philipp; Hecht, Markus; et al. (Acta Oto-Laryngologica, 2020)
Background: Human papillomavirus (HPV)+ and HPV– oropharyngeal squamous cell carcinomas (OPSCC) are separate tumor entities. Aims/Objectives: The aim of this study was to examine if the p16 status influences the need and outcome of a salvage neck dissection (SND) after primary radiochemotherapy (pRCT). Material and methods: Retrospective study of 164 patients (n = 108 p16–, n = 56 p16+) who underwent pRCT for OPSCC between 2009 and 2016. HPV status was defined via p16 immunohistochemical staining. Clinical nodal status was assessed using ultrasound and computed tomography of the neck with contrast. Results: Of the 56 p16+ patients, 17 (30.4%) patients were given an indication for a SND after pRCT with 4 (23.5%) patients showing persistent malignant nodes. Of the 108 p16– patients, 24 (22.2%) patients underwent a SND with 8 (33.3%) patients showing persistent malignant nodes. There was no significant association of the p16 status and neither the indication for SND (p(Chi2(two-sided)-Test) = 0.25, ϕ = 0.34) nor the occurrence of positive nodes (p(Chi2(two-sided)-Test) = 0.74, ϕ = 0.50). The probability for persistence of the ypN + nodal status independent of HPV-status was 29.2%(12/41). Conclusions and significance: There was neither a significant association between the p16 status and the indication for a SND nor for persistent malignant nodal disease after pRCT.
CRIS-Team Scopus Importer:2020-11-06
Keywords: de-escalation; HPV; Oropharyngeal cancer; p16; radiochemotherapy

Influence of patient mispositioning on SAR distribution and simulated temperature in regional deep hyperthermia - Aklan, Bassim; Gierse, Pia; Hartmann, Josefin; Ott, Oliver J.; Fietkau, Rainer; Bert, Christoph (Physics in Medicine and Biology, 2017)
Patient positioning plays an important role in regional deep hyperthermia to obtain a successful hyperthermia treatment. In this study, the influence of possible patient mispositioning was systematically assessed on specific absorption rate (SAR) and temperature distribution. With a finite difference time domain approach, the SAR and temperature distributions were predicted for six patients at 312 positions. Patient displacements and rotations as well as the combination of both were considered inside the Sigma-Eye applicator. Position sensitivity is assessed for hyperthermia treatment planning -guided steering, which relies on model-based optimization of the SAR and temperature distribution. The evaluation of the patient mispositioning was done with and without optimization. The evaluation without optimization was made by creating a treatment plan for the patient reference position in the center of the applicator and applied for all other positions, while the evaluation with optimization was based on creating an individual plan for each position. The parameter T90 was used for the temperature evaluation, which was defined as the temperature that covers 90% of the gross tumor volume (GTV). Furthermore, the hotspot tumor quotient (HTQ) was used as a goal function to assess the quality of the SAR and temperature distribution. The T90 was shown considerably dependent on the position within the applicator. Without optimization, the T90 was clearly decreased below 40 °C by patient shifts and the combination of shifts and rotations. However, the application of optimization for each positon led to an increase of T90 in the GTV. Position inaccuracies of less than 1 cm in the X-and Y-directions and 2 cm in the Z-direction, resulted in an increase of HTQ of less than 5%, which does not significantly affect the SAR and temperature distribution. Current positioning precision is sufficient in the X (right-left)-direction, but position accuracy is required in the Y-and Z-directions.
EVALuna2:32875

Influence of radiotherapy-induced reactive oxygen species on the immunogenic potential of HPV+ in comparison to HPV- HNSCC - Peitz, L.; Frey, Benjamin; Rieckmann, T.; Fietkau, Rainer; Gaipl, Udo (2017)
EVALuna2:32888

Influence of radiotherapy-induced reactive oxygen species on the immunogenic potential of HPV plus in comparison to HPV-HNSCC - Peitz, L.; Frey, Benjamin; Rieckmann, T.; Fietkau, Rainer; Gaipl, Udo (2018)
EVALuna2:36505

Influence of the ALK Kinase Inhibitors Crizotinib and Alectinib on healthy and malignant Lung Cell Lines in a Combination Therapy with ionizing Radiation - Schultz, A. -K; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Influence of the ATR and ATM Kinase Inhibitors VE822 and AZD0156 on Melanoma Cell Lines in Combination Therapy with ionizing Radiation - Scheper, J. S. S.; Jost, Tina; Faulhaber, E. -M; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Influence of the Kinase Inhibitor Palbociclib on the Migration of malignant and non-malignant Cells under Irradiation - Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Infrared camera based thermometry for quality assurance of superficial hyperthermia applicators - Müller, Johannes; Hartmann, Josefin; Bert, Christoph (Physics in Medicine and Biology, 2016)
The purpose of this work was to provide a feasible and easy to apply phantom-based quality assurance (QA) procedure for superficial hyperthermia (SHT) applicators by means of infrared (IR) thermography. The VarioCAM hr head (InfraTec, Dresden, Germany) was used to investigate the SA-812, the SA-510 and the SA-308 applicators (all: Pyrexar Medical, Salt Lake City, UT, USA). Probe referencing and thermal equilibrium procedures were applied to determine the emissivity of the muscle-equivalent agar phantom. Firstly, the disturbing potential of thermal conduction on the temperature distribution inside the phantom was analyzed through measurements after various heating times (5-50 min). Next, the influence of the temperature of the water bolus between the SA-812 applicator and the phantom's surface was evaluated by varying its temperature. The results are presented in terms of characteristic values (extremal temperatures, percentiles and effective field sizes (EFS)) and temperature-area-histograms (TAH). Lastly, spiral antenna applicators were compared by the introduced characteristics. The emissivity of the used phantom was found to be ? = 0.91 ± 0.03, the results of both methods coincided. The influence of thermal conduction with regard to heating time was smaller than expected; the EFS of the SA-812 applicator had a size of (68.6 ± 6.7) cm(2), averaged group variances were ±3.0 cm(2). The TAHs show that the influence of the water bolus is mostly limited to depths of <3 cm, yet it can greatly enhance or reduce heat generation in this regime: at a depth of 1 cm, measured maximal temperature rises were 14.5 °C for T Bolus = 30 °C and 8.6 °C for T Bolus = 21 °C, respectively. The EFS was increased, too. The three spiral antenna applicators generated similar heat distributions. Generally, the procedure proved to yield informative insights into applicator characteristics, thus making the application of an IR camera a very useful tool in SHT technical QA.
EVALuna2:18343

In head and neck cancer the number of dissected lymph nodes predicts mortality - Haderlein, Marlen; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
EVALuna2:32916

Initial needle tracking with the first standalone combined infrared camera – CT system for brachytherapy—analysis of tracking accuracy and uncertainties - Karius, Andre; Leifeld, Lisa Marie; Strnad, Vratislav; Schweizer, Claudia; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2024)
Purpose: A prototype infrared camera – cone-beam computed tomography (CBCT) system for tracking in brachytherapy has recently been developed. We evaluated for the first time the corresponding tracking accuracy and uncertainties, and implemented a tracking-based prediction of needles on CBCT scans. Methods: A marker tool rigidly attached to needles was 3D printed. The precision and accuracy of tool tracking was then evaluated for both static and dynamic scenarios. Euclidean distances between the tracked and CBCT-derived markers were assessed as well. To implement needle tracking, ground truth models of the tool attached to 200 mm and 160 mm needles were matched to the tracked positions in order to project the needles into CBCT scans. Deviations between projected and actual needle tips were measured. Finally, we put our results into perspective with simulations of the system’s tracking uncertainties. Results: For the stationary scenario and dynamic movements, we achieved tool-tracking precision and accuracy of 0.04 ± 0.06 mm and 0.16 ± 0.18 mm, respectively. The tracked marker positions differed by 0.52 ± 0.18 mm from the positions determined via CBCT. In addition, the predicted needle tips in air deviated from the actual tip positions by only 1.62 ± 0.68 mm (200 mm needle) and 1.49 ± 0.62 mm (160 mm needle). The simulated tracking uncertainties resulted in tip variations of 1.58 ± 0.91 mm and 1.31 ± 0.69 mm for the 200 mm and 160 mm needles, respectively. Conclusion: With the innovative system it was possible to achieve a high tracking and prediction accuracy of marker tool and needles. The system shows high potential for applicator tracking in brachytherapy.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Adaptive treatments; Gynecologic brachytherapy; Needle navigation; Optical tracking; Patient-specific implantations

In memory of Professor Dr. György Nemeth (1935-2014) - Loevey, Jozsef; Sauer, Rolf (Strahlentherapie und Onkologie, 2014)
EVALuna2:18201

In regard to “The Italian association of radiotherapy and oncology recommendation for breast tumor recurrence: grades of recommendation, assessment, development and evaluation criteria” - Hannoun-Levi, Jean-Michel; Gutierrez, Cristina; Polgar, Csaba; Strnad, Vratislav (Journal of Breast Cancer, 2021)
CRIS-Team Scopus Importer:2021-07-16

In Reply - Raptis, Dimitrios; Schneider, Ignaz Hans Friedrich; Matzel, Klaus E.; Hohenberger, Werner; Ott, Oliver; Fietkau, Rainer (Deutsches Ärzteblatt international, 2015)
EVALuna2:15209

Integration of a Halcyon Accelerator with ARIA in a Mosaiq - Environment - Risk Analysis Procedure - Shariff, Maya; Lotter, M.; Lambrecht, U.; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Integration of radiation oncology teaching in medical studies by German medical faculties due to the new licensing regulations: An overview and recommendations of the consortium academic radiation oncology of the German Society for Radiation Oncology (DEGRO) - Dapper, H.; Belka, C.; Bock, F.; Budach,; Budach, W.; Christiansen, H.; Debus, J.; Distel, Luitpold; Dunst, J.; Eckert, F.; Eich, H.; Eicheler, W.; et al. (Strahlentherapie und Onkologie, 2021)
The new Medical Licensing Regulations 2025 (Ärztliche Approbationsordnung, ÄApprO) will soon be passed by the Federal Council (Bundesrat) and will be implemented step by step by the individual faculties in the coming months. The further development of medical studies essentially involves an orientation from fact-based to competence-based learning and focuses on practical, longitudinal and interdisciplinary training. Radiation oncology and radiation therapy are important components of therapeutic oncology and are of great importance for public health, both clinically and epidemiologically, and therefore should be given appropriate attention in medical education. This report is based on a recent survey on the current state of radiation therapy teaching at university hospitals in Germany as well as the contents of the National Competence Based Learning Objectives Catalogue for Medicine 2.0 (Nationaler Kompetenzbasierter Lernzielkatalog Medizin 2.0, NKLM) and the closely related Subject Catalogue (Gegenstandskatalog, GK) of the Institute for Medical and Pharmaceutical Examination Questions (Institut für Medizinische und Pharmazeutische Prüfungsfragen, IMPP). The current recommendations of the German Society for Radiation Oncology (Deutsche Gesellschaft für Radioonkologie, DEGRO) regarding topics, scope and rationale for the establishment of radiation oncology teaching at the respective faculties are also included.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Medical studies; New licensing regulations; Radiation oncology teaching

Interaction of Radiotherapy and Hyperthermia with the Immune System: a Brief Current Overview - Sengedorj, Azzaya; Hader, Michael; Frey, Benjamin; Fietkau, Rainer; Ott, Oliver; Gaipl, Udo; Rückert, Michael (Current Stem Cell Reports, 2022)
Purpose of Review This review focuses on the opposing effects on the immune system of radiotherapy (RT) and the consequences for combined cancer treatment strategies of RT with immunotherapies, including hyperthermia (HT). How RT and HT might affect cancer stem cell populations is also briefly outlined in this context.
CRIS-Team WoS Importer:2022-07-29

Interactions between radiotherapy and immunotherapy - Rueckert, Michael; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (Onkologe, 2017)
Background. Radiotherapy (RT) acts not only locally on cells but is also capable of inducing systemic reactions. What are the immunological foundations for radiation-induced systemic reactions and how can this knowledge be exploited for the design of multimodal radioimmunotherapy? Ionizing radiation can induce many forms of tumor cell death via DNA damage responses, which have different influences on the immune system. Immunogenic cancer cell death (ICD) is mainly characterized by the release of immune-activating danger signals. Particularly RT with higher single doses induces ICD and thereby triggers anti-tumor immune responses. Lower doses of ionizing radiation foster immune cell infiltration into the tumor; however, RT also ameliorates inflammation and has immune suppressive properties in that the release of transforming growth factor beta (TGF-beta) is increased after RT and immune checkpoint molecules, such as PD-L1 are upregulated. This calls for additional immunotherapies to exploit the properties of RT to act as an in situ vaccine and to subsequently induce local and systemic, abscopal, anti-tumor immune reactions. For the development of efficient radioimmunotherapies, a timely well-reasoned combination of the individual therapies based on knowledge of the immune-modulating modes of action of ionizing radiation has to be worked out. It might be inevitable in the future to develop radiation concepts with differing single doses in one therapy setting to exploit the maximum anti-tumor effect of the immune system.
EVALuna2:32869

Interaktionen von Strahlen- und Immuntherapie - Rueckert, Michael; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; et al. (Onkologe, 2017)
Background: Radiotherapy (RT) acts not only locally on cells but is also capable of inducing systemic reactions. Objective: What are the immunological foundations for radiation-induced systemic reactions and how can this knowledge be exploited for the design of multimodal radioimmunotherapy? Results: Ionizing radiation can induce many forms of tumor cell death via DNA damage responses, which have different influences on the immune system. Immunogenic cancer cell death (ICD) is mainly characterized by the release of immune-activating danger signals. Particularly RT with higher single doses induces ICD and thereby triggers anti-tumor immune responses. Lower doses of ionizing radiation foster immune cell infiltration into the tumor; however, RT also ameliorates inflammation and has immune suppressive properties in that the release of transforming growth factor β (TGF-β) is increased after RT and immune checkpoint molecules, such as PD-L1 are upregulated. This calls for additional immunotherapies to exploit the properties of RT to act as an in situ vaccine and to subsequently induce local and systemic, abscopal, anti-tumor immune reactions. Conclusion: For the development of efficient radioimmunotherapies, a timely well-reasoned combination of the individual therapies based on knowledge of the immune-modulating modes of action of ionizing radiation has to be worked out. It might be inevitable in the future to develop radiation concepts with differing single doses in one therapy setting to exploit the maximum anti-tumor effect of the immune system.
Created from Fastlane, Scopus look-up
Keywords: Immune checkpoint inhibition; Immunogenic cancer cell death; In situ vaccine; Inflammation; Radioimmunotherapy

Inter-observer effects in needle reconstruction for temporary prostate brachytherapy: Dosimetric implications and adaptive CBCT-TRUS registration solutions - Karius, Andre; Kreppner, Stephan; Strnad, Vratislav; Schweizer, Claudia; Lotter, Michael; Fietkau, Rainer; Bert, Christoph (Brachytherapy, 2024)
PURPOSE: To investigate geometric and dosimetric inter-observer variability in needle reconstruction for temporary prostate brachytherapy. To assess the potential of registrations between transrectal ultrasound (TRUS) and cone-beam computed tomography (CBCT) to support implant reconstructions. METHODS AND MATERIALS: The needles implanted in 28 patients were reconstructed on TRUS by three physicists. Corresponding geometric deviations and associated dosimetric variations to prostate and organs at risk (urethra, bladder, rectum) were analyzed. To account for the found inter-observer variability, various approaches (template-based, probe-based, marker-based) for registrations of CBCT to TRUS were investigated regarding the respective needle transfer accuracy in a phantom study. Three patient cases were examined to assess registration accuracy in-vivo. RESULTS: Geometric inter-observer deviations >1 mm and >3 mm were found for 34.9% and 3.5% of all needles, respectively. Prostate dose coverage (changes up to 7.2%) and urethra dose (partly exceeding given dose constraints) were most affected by associated dosimetric changes. Marker-based and probe-based registrations resulted in the phantom study in high mean needle transfer accuracies of 0.73 mm and 0.12 mm, respectively. In the patient cases, the marker-based approach was the superior technique for CBCT-TRUS fusions. CONCLUSION: Inter-observer variability in needle reconstruction can substantially affect dosimetry for individual patients. Especially marker-based CBCT-TRUS registrations can help to ensure accurate reconstructions for improved treatment planning.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Cone-beam computed tomography; Image registration; Inter-observer variation; Needle reconstruction; Temporary prostate brachytherapy; Transrectal ultrasound

Interstitial brachytherapy as a boost to patients with anal carcinoma and poor response to chemoradiation: Single-institution long-term results - Gryc, Thomas; Ott, Oliver; Putz, Florian; Knippen, Stefan; Raptis, Dimitrios; Fietkau, Rainer; Strnad, Vratislav (Brachytherapy, 2016)
To analyze the efficacy of a protocol-based brachytherapy (BT) boost after external beam radiation therapy (EBRT) with simultaneous chemotherapy in patients with anal carcinoma.About 190 patients have been analyzed. Around 143 patients were identified with a good clinical response at the end of EBRT. Another 47 patients received an additional BT boost to the residual tumor at 6 weeks after end of chemoradiation.The 5-year incidence of local recurrence was 24% in patients with BT boost and 19% in patients without BT boost (p = 0.238). The 5-year disease-free survival rate, overall survival rate, and colostomy-free survival rate were 64% and 75% and 76.1% in the BT group and 69% (p = 0.212), 72% (p = 0.924), and 82.7% (p = 0.488) in the non-BT group. We found no differences in late toxicity between the groups.For patients with anal cancer with not a good response to 50-59 Gy EBRT with simultaneous chemotherapy, the further dose escalation using the BT boost up to a mean of 67.5 Gy seems to improve the clinical outcome to the same level as observed in patients with a good response to ERBT, without an increase in late side effects.
EVALuna2:15265

Interstitial PDR-brachytherapy alone or in combination with EBRT for malignancies of the vulvar area: the UK Erlangen experience - Knippen, S.; Kreppner, Stephan; Lotter, M.; Fietkau, Rainer; Strnad, Vratislav (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

In the Case of Radiochemotherapy of advanced Rectal Cancer, there is only slight gender-related Differences, none in terms of Radiation Sensitivity! - Schuster, Barbara; Hecht, Markus; Schmidt, Manfred; Haderlein, Marlen; Jost, Tina; Geinitz, H.; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Introduction of a hybrid treatment delivery system used for quality assurance in multi-catheter interstitial brachytherapy - Kallis, Karoline; Kreppner, Stephan; Lotter, Michael; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Physics in Medicine and Biology, 2018)
Multi-catheter interstitial brachytherapy (iBT) is a treatment option for breast cancer patients after breast conserving surgery. Typically, only a few additional quality interventions after the first irradiation have been introduced to ensure the planned treatment delivery. Therefore, the purpose of this study is to show the possibilities of an electromagnetic tracking (EMT) system integrated into the afterloader for quality assurance (QA) in high-dose rate (HDR) iBT of patients with breast cancer. The hybrid afterloader system equipped with an electromagnetic sensor was used for all phantom and patient measurements. Phantom measurements were conducted to estimate the quality of different evaluation schemes. After a coherent point drift registration of the EMT traces to the reconstructed catheters based on computed tomograms the dwell positions (DP) were defined. Different fitting and interpolation methods were analyzed for the reconstruction of DPs. All estimated DPs were compared to the DPs defined in treatment planning. Until now, the implant geometry of 20 patients treated with HDR brachytherapy was acquired and explored. Regarding the reconstruction techniques, both fitting and interpolation were able to detect manually introduced shifts and swaps. Nonetheless, interpolation showed superior results (RMSE = 1.27 mm), whereas fitting seemed to be more stable to distortion and motion. The EMT system proved to be beneficial for QA in brachytherapy and furthermore, clinical feasibility was proven.
EVALuna2:36464

Investigating a Correlation between Chemoradiotherapy Schedule Parameters and Overall Survival in a real-life LD SCLC Patient Cohort - Manapov, Farkhad; Eze, Chukwuka; Niyazi, Maximilian; Roengvoraphoj, Olarn; Li, Minglun; Hegemann, Nina-Sophie; Hildebrandt, Guido; Fietkau, Rainer; Belka, Claus (Journal of Cancer, 2016)
Background : Chemoradiotherapy (CRT) is a treatment standard in limited disease (LD) small cell lung cancer (SCLC). Currently, the timing of thoracic radiation therapy (TRT) remains the subject of randomised trials and meta-analyses. To investigate a correlation between CRT schedule parameters and overall survival (OS) in a real-life patient cohort, a temporal analysis was performed.Methods: 182 LD SCLC patients successfully treated with definitive CRT were retrospectively reviewed. TRT was applied concurrently or sequentially. Impact of the treatment mode and interval of simultaneous treatment (IST) (an interval in days when chemotherapy and TRT were applied simultaneously, including time between chemotherapy cycles and weekends) on OS was analysed.Results: 71 (39%) patients were treated with concurrent and 111 (61%) with sequential CRT. Median overall survival (MS) for the entire cohort was 534 days (95%CI 461 - 607) without any significant difference between the concurrent and sequential groups (589: 95%CI 358 - 820 vs. 533: 95%CI 446 - 620 days, p=0.746, log-rank test). IST was 0 days in 111 (61%) patients treated sequentially whereas in the concurrent group, 20 (11%) and 51 (28%) patients showed an IST < 35 and > 35 days, respectively. Patients with IST > 0 and < 35 days demonstrated a trend to improved overall survival (MS: IST 0 vs. > 35 vs. < 35 was 533 vs. 448 vs. 1169 days, p=0.109, log-rank test). When patients treated with sequential CRT (IST 0) were excluded from the analysis, statistical difference in overall survival according to the IST subgroups (IST > 35 vs. < 35) became significant (p=0.021, log-rank test). On multivariate analysis of patients treated with concurrent CRT, IST > 0 and < 35 days remained a variable that significantly correlated with better overall survival (p=0.039, HR 0.38).Conclusion: In this real-life LD SCLC patient cohort, improved overall survival was achieved in patients treated with CRT schedule according to the IST > 0 and < 35-day concept. By exceeding the 35-day interval, we have seen deterioration in survival.
EVALuna2:32925

Investigating the impact of breast positioning control on physical treatment parameters in multi-catheter breast brachytherapy - Karius, Andre; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2023)
Purpose: To assess the effects of a workflow for reproducible patient and breast positioning on implant stability during high-dose-rate multi-catheter breast brachytherapy. Methods: Thirty patients were treated with our new positioning control workflow. Implant stability was evaluated based on a comparison of planning-CTs to control-CTs acquired halfway through the treatment. To assess geometric stability, button–button distance variations as well as Euclidean dwell position deviations were evaluated. The latter were also quantified within various separated regions within the breast to investigate the location-dependency of implant alterations. Furthermore, dosimetric variations to target volume and organs at risk (ribs, skin) as well as isodose volume changes were analyzed. Results were compared to a previously treated cohort of 100 patients. Results: With the introduced workflow, the patient fraction affected by button–button distance variations > 5 mm and by dwell position deviations > 7 mm were reduced from 37% to 10% and from 30% to 6.6%, respectively. Implant stability improved the most in the lateral to medial breast regions. Only small stability enhancements were observed regarding target volume dosimetry, but the stability of organ at risk exposure became substantially higher. D0.2ccm skin dose variations > 12.4% and D0.1ccm rib dose variations > 6.7% were reduced from 11% to 0% and from 16% to 3.3% of all patients, respectively. Conclusion: Breast positioning control improved geometric and dosimetric implant stability for individual patients, and thus enhanced physical plan validity in these cases.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Adaptive brachytherapy; Computed tomography; Implant stability; Treatment quality; Treatment re-planning

Investigation of a radioprotective Effect of the Kinase Inhibitor Palbociclib on Melanoma Cells in a 3D Cell Culture Model - Jost, Tina; Buerkel, F.; Proebstle, Stephanie; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36487

Investigation of daily Activity, Sleep and neurocognitive Function in Glioblastoma Patients using TTFields Therapy in Routine clinical Care in Germany - the TIGER PRO-Active Study - Glas, M.; Tabatabai, G.; Fietkau, Rainer; Goldbrunner, R.; Baehr, O. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Investigation of Long Term Survival in Metastatic NSCLC with Driver Mutations under Molecular Targeted Therapy and Local Radiotherapy of all Tumor Manifestations - Weissmann, T.; Semrau, S.; Lettmaier, S.; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

In Vitro Analysis of Superparamagnetic Iron Oxide Nanoparticles Coated with APTES as Possible Radiosensitizers for HNSCC Cells - Emer, Clara; Hildebrand, Laura; Friedrich, Bernhard; Tietze, Rainer; Fietkau, Rainer; Distel, Luitpold (Nanomaterials, 2023)
Superparamagnetic iron oxide nanoparticles (SPION) are being investigated for many purposes, e.g., for the amplification of ionizing radiation and for the targeted application of therapeutics. Therefore, we investigated SPIONs coated with (3-Aminopropyle)-Triethoxysilane (SPION-APTES) for their influence on different head and neck squamous cell carcinoma (HNSCC) cell lines, as well as for their suitability as a radiosensitizer. We used 24-well microscopy and immunofluorescence microscopy for cell observation, growth curves to determine cytostatic effects, and colony formation assays to determine cytotoxicity. We found that the APTES-SPIONs were very well taken up by the HNSCC cells. They generally have a low cytotoxic effect, showing no significant difference in clonogenic survival between the control group and cells treated with 20 µg Fe/mL (p > 0.25) for all cell lines. They have a cytostatic effect on some cell lines cells (e.g., Cal33) that is visible across different radiation doses (1, 2, 8 Gy, p = 0.05). In Cal33, e.g., SPION-APTES raised the doubling time at 2 Gy from 24.53 h to 41.64 h. Importantly, these findings vary notably between the cell lines. However, they do not significantly alter the radiation effect: only one out of eight cell lines treated with SPION-APTES showed a significantly reduced clonogenic survival after ionizing radiation with 2 Gy, and only two showed significantly reduced doubling times. Thus, although the APTES-SPIONs do not qualify as a radiosensitizer, we were still able to vividly demonstrate and analyze the effect that the APTES-SPIONs have on various cell lines as a contribution to further functionalization.
CRIS-Team Scopus Importer:2023-02-03
Keywords: cell survival; doubling time; head and neck cancer cell lines; HNSCC; nanoparticles; SPION; time lapse

In Vitro Examinations of Cell Death Induction and the Immune Phenotype of Cancer Cells Following Radiative-Based Hyperthermia with 915 MHz in Combination with Radiotherapy - Hader, Michael; Streit, Simon; Rosin, Andreas; Gerdes, Thorsten; Wadepohl, Martin; Bekeschus, Sander; Fietkau, Rainer; Frey, Benjamin; Schlücker, Eberhard; Gekle, Stephan; Gaipl, Udo (Cells, 2021)
Multimodal tumor treatment settings consisting of radiotherapy and immunomodulating agents such as immune checkpoint inhibitors are more and more commonly applied in clinics. In this context, the immune phenotype of tumor cells has a major influence on the anti-tumor immune response as well as the composition of the tumor microenvironment. A promising approach to further boost anti-tumor immune responses is to add hyperthermia (HT), i.e., heating the tumor tissue between 39 degrees C to 45 degrees C for 60 min. One key technique is the use of radiative hyperthermia systems. However, knowledge is limited as to how the frequency of the used radiative systems affects the immune phenotype of the treated tumor cells. By using our self-designed in vitro hyperthermia system, we compared cell death induction and expression of immune checkpoint molecules (ICM) on the tumor cell surface of murine B16 melanoma and human MDA-MB-231 and MCF-7 breast cancer cells following HT treatment with clinically relevant microwaves at 915 MHz or 2.45 GHz alone, radiotherapy (RT; 2 x 5 Gy or 5 x 2 Gy) alone or in combination (RHT). At 44 degrees C, HT alone was the dominant cell death inductor with inactivation rates of around 70% for B16, 45% for MDA-MB-231 and 35% for MCF-7 at 915 MHz and 80%, 60% and 50% at 2.45 GHz, respectively. Additional RT resulted in 5-15% higher levels of dead cells. The expression of ICM on tumor cells showed time-, treatment-, cell line- and frequency-dependent effects and was highest for RHT. Computer simulations of an exemplary spherical cell revealed frequency-dependent local energy absorption. The frequency of hyperthermia systems is a newly identified parameter that could also affect the immune phenotype of tumor cells and consequently the immunogenicity of tumors.
CRIS-Team WoS Importer:2021-07-09

Ion beam tracking using ultrasound motion detection - Prall, M.; Kaderka, R.; Saito, N.; Graeff, Christian; Bert, Christoph; Durante, Marco; Parodi, K.; Schwaab, J.; Sarti, C.; Jenne, J. (Medical Physics, 2014)
The use of motion mitigation techniques such as tracking and gating in particle therapy requires real-time knowledge of tumor position with millimeter precision. The aim of this phantom-based study was to evaluate the option of diagnostic ultrasound (US) imaging (sonography) as real-time motion detection method for scanned heavy ion beam irradiation of moving targets.For this pilot experiment, a tumor surrogate was moved inside a water bath along two-dimensional trajectories. A rubber ball was used for this purpose. This ball was moved by a robotic arm in two dimensions lateral to the heavy ion beam. Trajectories having a period of 3 s and peak to peak amplitude of 20 mm were used. Square radiation fields of[Formula: see text] were irradiated on radiosensitive films with a 200 MeV/u beam of calcium ions having a FWHM of 6 mm. Pencil beam scanning and beam tracking were employed. The films were attached on the robotic arm and thus moved with the rubber ball. The position of the rubber ball was continuously measured by a US tracking system (Mediri GmbH, Heidelberg) and sent to the GSI therapy control system (TCS). This position was used as tracking vector. Position reconstruction from the US tracking system and data communication introduced a delay leading to a position error of several millimeters. An artificial neural network (ANN) was implemented in the TCS to predict motion from US measurements and thus to compensate for the delay.Using ANN delay compensation and large motion amplitudes, the authors could produce irradiation patterns with a few percent inhomogeneity and about 1 mm geometrical conformity.This pilot experiment suggests that diagnostic US should be further investigated as dose-free, high frame-rate, and model-independent motion detection method for scanning heavy ion beam irradiation of moving targets.
EVALuna2:18309

Ionizing radiation reduces the capacity of activated macrophages to induce T-cell proliferation, but does not trigger dendritic cell-mediated non-targeted effects - Wunderlich, Roland; Rühle, Paul-Friedrich; Roedel, Franz; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Deloch, Lisa (International Journal of Radiation Biology, 2019)
PURPOSE: Previous investigations revealed influences of irradiation up to 2Gy on the cytokine secretion profile of inflammatory and peritoneal mouse macrophages (pMФ). This raised the question if those alterations impact on dendritic cells and consecutive T-cell responses. Further, the impact of irradiation directly on pMФ capacity to induce T-cell responses was analyzed. MATERIALS AND METHODS: pMФ were LPS-activated, irradiated and the expression of activation markers was assessed. Treated pMФ were co-incubated with T-cells to investigate proliferation. To verify modulating properties of pMФ supernatants isolated 24 h after irradiation, bone marrow-derived dendritic cells (BMDC) were co-incubated with supernatants and activation markers as well as the BMDC-induced proliferation of T-cells were measured. RESULTS: pMФ showed a highly significantly decreased major histocompatibility complexII (MHCII) expression within a dose range from 0.7-2Gy. Further, the proliferation rate of cluster of differentiation 4+ (CD4+) T-cells was decreased after co-incubation particularly with 2 Gy irradiated pMФ. The co-incubation of BMDC with supernatants of activated, irradiated pMФ significantly reduced the CD40 expression, but did not impact on the BMDC-derived induction of T-cell proliferation. CONCLUSIONS: Inflammatory macrophages being exposed to irradiation have the potential to modulate consecutive adaptive immune reactions. But supernatants of irradiated macrophages do not influence the dendritic cells (DC)-mediated induction of T cell proliferation.
EVALuna2:36459

Ion therapy of prostate cancer: daily rectal dose reduction by application of spacer gel - Rucinski, Antoni; Brons, Stephan; Richter, Daniel; Habl, Gregor; Debus, Juergen; Bert, Christoph; Haberer, Thomas; Jaekel, Oliver (Radiation Oncology, 2015)
Ion beam therapy represents a promising approach to treat prostate cancer, mainly due to its high conformity and radiobiological effectiveness. However, the presence of prostate motion, patient positioning and range uncertainties may deteriorate target dose and increase exposure of organs at risk. Spacer gel injected between prostate and rectum may increase the safety of prostate cancer (PC) radiation therapy by separating the rectum from the target dose field. The dosimetric impact of the application of spacer gel for scanned carbon ion therapy of PC has been analyzed at Heidelberg Ion-Beam Therapy Center (HIT).The robustness of ion therapy treatment plans was investigated by comparison of two data sets of patients treated with and without spacer gel. A research treatment planning system for ion therapy was used for treatment plan optimization and calculation of daily dose distributions on 2 to 9 Computed Tomography (CT) studies available for each of the 19 patients. Planning and daily dose distributions were analyzed with respect to target coverage, maximal dose to the rectum (excluding 1 ml of the greatest dose; Dmax-1 ml) and the rectal volume receiving dose greater than 90% of prescribed target dose (V90Rectum), respectively.The application of spacer gel did substantially diminish rectum dose. Dmax-1 ml on the treatment planning CT was on average reduced from 100.0 ± 1.0% to 90.2 ± 4.8%, when spacer gel was applied. The robustness analysis performed with daily CT studies demonstrated for all analyzed patient cases that application of spacer gel results in a decrease of the daily V90Rectum index, which calculated over all patient cases and CT studies was 10.2 ± 10.4 [ml] and 1.1 ± 2.1 [ml] for patients without and with spacer gel, respectively.The dosimetric benefit of increasing the distance between prostate and rectum using spacer gel for PC treatment with carbon ion beams has been quantified. Application of spacer gel substantially reduced rectal exposure to high treatment dose and, therefore, can reduce the hazard of rectal toxicity in ion beam therapy of PC. The results of this study enable modifications of the PC ion therapy protocol such as dose escalation or hypofractionation.
EVALuna2:18312

Irradiation of the locoregional Lymphatic Drainage Pathways of Breast Cancer: Is the prescribed Dose actually applied? A Planning Study by the DEGRO Breast Cancer Working Group - Duma, M. N.; Piroth, M.; Fastner, G.; Baumann, R.; Combs, S.; Dunst, J.; Feyer, P.; Fietkau, Rainer; Haase, W.; Harms, W.; Hehr, T.; Krug, D.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Is adaptive treatment planning in multi-catheter interstitial breast brachytherapy necessary? - Kallis, Karoline; Ziegler, Marc; Lotter, Michael; Kreppner, Stephan; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2019)
Purpose: For 55 patients treated with interstitial multi-catheter breast brachytherapy the need for adaptive treatment planning was assessed. Methods and materials: For all patients a treatment planning computed tomography (CT) and a follow-up CT were acquired and used for the retrospective evaluation. Keeping dwell time and dwell positions constant, the treatment plan assessed directly after catheter implantation was compared to the situation 48 h after implantation. Both manual catheter reconstructions, based on the planning and follow-up CT, were rigid registered to each other and the resulting deviations analyzed, like the difference between corresponding dwell positions (ΔDP) or the discrete Fréchet distance. Further, the dosimetric changes, e.g., coverage index (ΔCI), conformal index (ΔCOIN) and dose non-uniformity ratio (ΔDNR) were considered for a deformed planning target volume (PTV) and the rigid warped PTV structure. The PTV was deformed according to the vector field estimated between the two acquired CTs. Results: Over all patients with rigid aligned CTs a mean ΔDP, ΔCI, ΔCOIN and ΔDNR were determined to 2.41 ± 1.73 mm, 3.10 ± 3.17%, 0.009 ± 0.007 and 0.036 ± 0.040, respectively. Considering the deformed PTV ΔCI was estimated to 5.05 ± 4.14 %. Conclusion: In conclusion, in 4% of the cases re-planning would have been beneficial to ensure the planned dose delivery. Large PTV changes or large DP deviations were found to be the main reasons for dosimetric variations.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Adaptive treatment planning; Breast cancer; Deformable image registration; Interstitial brachytherapy

Is in vivo and ex vivo irradiation equally reliable for individual Radiosensitivity testing by three colour fluorescence in situ hybridization? - Mayo, Theresa; Haderlein, Marlen; Schuster, Barbara; Wiesmueller, Anna; Hummel, Christian; Bachl, Maximilian; Schmidt, Manfred; Fietkau, Rainer; Distel, Luitpold (Radiation Oncology, 2019)
Background Individual radiosensitivity is influencing the outcome of radiation therapy. A general ex vivo testing is very work-intensive. It is of interest to see if a significant prediction concerning the sensitivity can be made by in vivo irradiation during radiation treatment. Methods Blood samples of 274 patients with rectal cancer and 43 lung cancer patients receiving radiotherapy were examined after 2 Gy ex vivo and in vivo ionizing radiation. Chromosomes # 1, 2 and 4 were stained by the 3-color-fluorescence in situ hybridization. Chromosomal aberrations were analyzed as breaks per metaphase (B/M). The deposited energy per session was calculated for each patient. Results Weak correlation could be found between the chromosomal aberrations ex and in vivo. Though receiving significantly smaller deposited energy during radiation therapy (RT) the lung cancer cohort displayed B/M values similar to the rectal cancer cohort. Considering the individual deposit energy differences improved slightly the correlation. Conclusions As various factors influence the induction of chromosomal aberrations it seems not feasible to estimate individual radiosensitivity via in vivo irradiation. An ex vivo estimation of individual radiosensitivity should be preferred.
CRIS-Team WoS Importer:2020-01-10

Is there a patient population with squamous cell carcinoma of the head and neck region who might benefit from de-intensification of postoperative radiotherapy? - Onbasi, Yonca; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2019)
PURPOSE: The aim of this retrospective study was to evaluate the clinical outcome of a previously defined low-risk patient population with completely resected (R0) squamous cell carcinoma of the oral cavity, oropharynx, larynx (pT1-3, pN0-pN2b), hypopharynx (pT1-2, pN0-pN1), and the indication for postoperative radio(chemo)therapy. PATIENTS AND METHODS: According to predefined criteria, 99 patients with head and neck squamous cell carcinoma (SCC) who were treated at our institution from January 1, 2005 to December 31, 2014, were available for analysis. The Kaplan-Meier method was used for calculating survival and incidence rates. For univariate comparative analysis, the log-rank test was used for analyzing prognostic clinicopathologic parameters. RESULTS: Median follow-up was 67 months. Cumulative overall (OS) and disease-free survival (DFS) were 97.9%/94.7%/88.0% and 96.9%/92.6%/84.7% after 1, 2, and 5 years, respectively. Cumulative incidence of loco-regional recurrence (LRR), distant metastases (DM), and second cancer (SC) were 1.0%/1.0%/4.9%, 0.0%/3.4%/5.8%, and 2.1%/4.2%/13.1%, respectively. In univariate comparative analysis, location of the primary tumor in the oropharynx was a significant predictor for increased OS (p = 0.043) and DFS (p = 0.048). CONCLUSION: Considering the low disease relapse rates and high rates of therapy-induced late side effects, as well as the increased risk of developing SC, a prospective multicentric trial investigating de-escalation of radiotherapy in this clearly defined low-risk patient population was started and is still recruiting patients (DIREKHT-Trial, NCT02528955).
EVALuna2:184476

Is there a patient population with squamous cell carcinoma of the head and neck region who might benefit from de-intensification of postoperative radiotherapy? - Onbasi, Yonca; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2019)
Purpose: The aim of this retrospective study was to evaluate the clinical outcome of a previously defined low-risk patient population with completely resected (R0) squamous cell carcinoma of the oral cavity, oropharynx, larynx (pT1–3, pN0–pN2b), hypopharynx (pT1–2, pN0–pN1), and the indication for postoperative radio(chemo)therapy. Patients and methods: According to predefined criteria, 99 patients with head and neck squamous cell carcinoma (SCC) who were treated at our institution from January 1, 2005 to December 31, 2014, were available for analysis. The Kaplan–Meier method was used for calculating survival and incidence rates. For univariate comparative analysis, the log-rank test was used for analyzing prognostic clinicopathologic parameters. Results: Median follow-up was 67 months. Cumulative overall (OS) and disease-free survival (DFS) were 97.9%/94.7%/88.0% and 96.9%/92.6%/84.7% after 1, 2, and 5 years, respectively. Cumulative incidence of loco-regional recurrence (LRR), distant metastases (DM), and second cancer (SC) were 1.0%/1.0%/4.9%, 0.0%/3.4%/5.8%, and 2.1%/4.2%/13.1%, respectively. In univariate comparative analysis, location of the primary tumor in the oropharynx was a significant predictor for increased OS (p = 0.043) and DFS (p = 0.048). Conclusion: Considering the low disease relapse rates and high rates of therapy-induced late side effects, as well as the increased risk of developing SC, a prospective multicentric trial investigating de-escalation of radiotherapy in this clearly defined low-risk patient population was started and is still recruiting patients (DIREKHT-Trial, NCT02528955).
CRIS-Team Scopus Importer:2019-06-04
Keywords: Disease-free survival; Late side effect; Overall survival; Radio(chemo)therapy; Second cancer

Kinase Inhibitor Palbociclib shows differential Effects upon Irradiation on Normal Tissue and Cancer Cell Lines - Jost, Tina; Proebstle, Stephanie; Buerkel, F.; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36486

Kinase inhibitors increase individual radiation sensitivity in normal cells of cancer patients - Jost, Tina; Schuster, Barbara; Heinzerling, Lucie; Weissmann, Thomas; Fietkau, Rainer; Distel, Luitpold; Hecht, Markus (Strahlentherapie und Onkologie, 2022)
Purpose Kinase inhibitors (KI) are known to increase radiosensitivity, which can lead to increased risk of side effects. Data about interactions of commonly used KI with ionizing radiation on healthy tissue are rare. Patients and methods Freshly drawn blood samples were analyzed using three-color FISH (fluorescence in situ hybridization) to measure individual radiosensitivity via chromosomal aberrations after irradiation (2 Gy). Thresholds of 0.5 and 0.6 breaks/metaphase (B/M) indicate moderate or clearly increased radiosensitivity. Results The cohorts consisted of healthy individuals (NEG, n = 219), radiosensitive patients (POS, n = 24), cancer patients (n = 452) and cancer patients during KI therapy (n = 49). In healthy individuals radiosensitivity (>= 0.6 B/M) was clearly increased in 5% of all cases, while in the radiosensitive cohort 79% were elevated. KI therapy increased the rate of sensitive patients (>= 0.6 B/M) to 35% significantly compared to 19% in cancer patients without KI (p = 0.014). Increased radiosensitivity of peripheral blood mononuclear cells (PBMCs) among patients occurred in six of seven KI subgroups. The mean B/M values significantly increased during KI therapy (0.47 +/- 0.20 B/M without compared to 0.50 +/- 0.19 B/M with KI, p = 0.047). Conclusions Kinase inhibitors can intensify individual radiosensitivity of PBMCs distinctly in 85% of tested drugs.
CRIS-Team WoS Importer:2022-05-13

Kinase Inhibitors increase the individual Radiation Sensitivity of Normal Tissue in Cancer Patients - Jost, Tina; Schuster, Barbara; Heinzerling, L.; Weissmann, Thomas; Fietkau, Rainer; Distel, Luitpold; Hecht, Markus (Strahlentherapie und Onkologie, 2022)
CRIS-Team WoS Importer:2022-06-03

Kinase Inhibitors of DNA-PK, ATM and ATR in Combination with Ionizing Radiation Can Increase Tumor Cell Death in HNSCC Cells While Sparing Normal Tissue Cells - Faulhaber, Eva-Maria; Jost, Tina; Symank, Julia-Alice; Scheper, Julian; Burkel, Felix; Fietkau, Rainer; Hecht, Markus; Distel, Luitpold (Genes, 2021)
(1) Kinase inhibitors (KI) targeting components of the DNA damage repair pathway are a promising new type of drug. Combining them with ionizing radiation therapy (IR), which is commonly used for treatment of head and neck tumors, could improve tumor control, but could also increase negative side effects on surrounding normal tissue. (2) The effect of KI of the DDR (ATMi: AZD0156; ATRi: VE-822, dual DNA-PKi/mTORi: CC-115) in combination with IR on HPV-positive and HPV-negative HNSCC and healthy skin cells was analyzed. Cell death and cell cycle arrest were determined using flow cytometry. Additionally, clonogenic survival and migration were analyzed. (3) Studied HNSCC cell lines reacted differently to DDRi. An increase in cell death for all of the malignant cells could be observed when combining IR and KI. Healthy fibroblasts were not affected by simultaneous treatment. Migration was partially impaired. Influence on the cell cycle varied between the cell lines and inhibitors; (4) In conclusion, a combination of DDRi with IR could be feasible for patients with HNSCC. Side effects on healthy cells are expected to be limited to normal radiation-induced response. Formation of metastases could be decreased because cell migration is impaired partially. The treatment outcome for HPV-negative tumors tends to be improved by combined treatment.
CRIS-Team WoS Importer:2021-07-09

Kinase Inhibitors of DNA-PK, ATM and ATR in Combination with Ionizing Radiation Can Increase Tumor Cell Death in HNSCC Cells While Sparing Normal Tissue Cells - Jost, Tina; Faulhaber, Eva-Maria; Symank, Julia-Alice; Scheper, Julian; Bürkel, Felix; Fietkau, Rainer; Hecht, Markus; Distel, Luitpold (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Late side-effects and cosmetic results of accelerated partial breast irradiation with interstitial brachytherapy versus whole-breast irradiation after breast-conserving surgery for low-risk invasive and in-situ carcinoma of the female breast: 5-year results of a randomised, controlled, phase 3 trial - Polgar, Csaba; Ott, Oliver J.; Hildebrandt, Guido; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Lyczek, Jaroslaw; Guinot, Jose Luis; Dunst, Jurgen; Miguelez, Cristina Gutierrez; Slampa, Pavel; Allgaeuer, Michael; et al. (Lancet Oncology, 2017)
BACKGROUND: We previously confirmed the non-inferiority of accelerated partial breast irradiation (APBI) with interstitial brachytherapy in terms of local control and overall survival compared with whole-breast irradiation for patients with early-stage breast cancer who underwent breast-conserving surgery in a phase 3 randomised trial. Here, we present the 5-year late side-effects and cosmetic results of the trial. METHODS: We did this randomised, controlled, phase 3 trial at 16 centres in seven European countries. Women aged 40 years or older with stage 0-IIA breast cancer who underwent breast-conserving surgery with microscopically clear resection margins of at least 2 mm were randomly assigned 1:1, via an online interface, to receive either whole-breast irradiation of 50 Gy with a tumour-bed boost of 10 Gy or APBI with interstitial brachytherapy. Randomisation was stratified by study centre, menopausal status, and tumour type (invasive carcinoma vs ductal carcinoma in situ), with a block size of ten, according to an automated dynamic algorithm. Patients and investigators were not masked to treatment allocation. The primary endpoint of our initial analysis was ipsilateral local recurrence; here, we report the secondary endpoints of late side-effects and cosmesis. We analysed physician-scored late toxicities and patient-scored and physician-scored cosmetic results from the date of breast-conserving surgery to the date of onset of event. Analysis was done according to treatment received (as-treated population). This trial is registered with ClinicalTrials.gov, number NCT00402519. FINDINGS: Between April 20, 2004, and July 30, 2009, we randomly assigned 1328 women to receive either whole-breast irradiation (n=673) or APBI with interstitial brachytherapy (n=655); 1184 patients comprised the as-treated population (551 in the whole-breast irradiation group and 633 in the APBI group). At a median follow-up of 6·6 years (IQR 5·8-7·6), no patients had any grade 4 toxities, and three (<1%) of 484 patients in the APBI group and seven (2%) of 393 in the whole-breast irradiation group had grade 3 late skin toxicity (p=0·16). No patients in the APBI group and two (<1%) in the whole-breast irradiation group developed grade 3 late subcutaneous tissue toxicity (p=0·10). The cumulative incidence of any late side-effect of grade 2 or worse at 5 years was 27·0% (95% CI 23·0-30·9) in the whole-breast irradiation group versus 23·3% (19·9-26·8) in the APBI group (p=0·12). The cumulative incidence of grade 2-3 late skin toxicity at 5 years was 10·7% (95% CI 8·0-13·4) in the whole-breast irradiation group versus 6·9% (4·8-9·0) in the APBI group (difference -3·8%, 95% CI -7·2 to 0·4; p=0·020). The cumulative risk of grade 2-3 late subcutaneous tissue side-effects at 5 years was 9·7% (95% CI 7·1-12·3) in the whole-breast irradiation group versus 12·0% (9·4-14·7) in the APBI group (difference 2·4%; 95% CI -1·4 to 6·1; p=0·28). The cumulative incidence of grade 2-3 breast pain was 11·9% (95% CI 9·0-14·7) after whole-breast irradiation versus 8·4% (6·1-10·6) after APBI (difference -3·5%; 95% CI -7·1 to 0·1; p=0·074). At 5 years' follow-up, according to the patients' view, 413 (91%) of 454 patients had excellent to good cosmetic results in the whole-breast irradiation group versus 498 (92%) of 541 patients in the APBI group (p=0·62); when judged by the physicians, 408 (90%) of 454 patients and 503 (93%) of 542 patients, respectively, had excellent to good cosmetic results (p=0·12). No treatment-related deaths occurred, but six (15%) of 41 patients (three in each group) died from breast cancer, and 35 (85%) deaths (21 in the whole-breast irradiation group and 14 in the APBI group) were unrelated. INTERPRETATION: 5-year toxicity profiles and cosmetic results were similar in patients treated with breast-conserving surgery followed by either APBI with interstitial brachytherapy or conventional whole-breast irradiation, with significantly fewer grade 2-3 late skin side-effects after APBI with interstitial brachytherapy. These findings provide further clinical evidence for the routine use of interstitial multicatheter brachytherapy-based APBI in the treatment of patients with low-risk breast cancer who opt for breast conservation. FUNDING: German Cancer Aid.
EVALuna2:32911

LDRT induces long-lasting Pain and Immunomodulating Effects in chronic degenerative and inflammatory Diseases - Results from the IMMO-LDRT01 Study - Donaubauer, Anna-Jasmina; Weissmann, Thomas; Fröhlich, Birgitta; Becker, Ina; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Lethal outcome after pelvic salvage radiotherapy in a patient with prostate cancer due to increased radiosensitivity : Case report and literature review - Fahrig, Antje; Koch, T.; Lenhart, M.; Rieckmann, P.; Fietkau, Rainer; Distel, Luitpold; Schuster, Barbara (Strahlentherapie und Onkologie, 2018)
BACKGROUND: In general, late side effects after salvage radiotherapy (RT) for prostate cancer are below 10%. Patients with impaired DNA repair ability and genetic instability can have significantly increased reactions after RT. CASE, CLINICAL FOLLOW-UP, AND EXAMINATION: We present a patient who experienced severe side effects after additive RT for prostate cancer and died from the complications 25 months after RT. Imaging (MR) is shown as well as three-color fluorescence in situ hybridization. The blood sample testing revealed that radiosensitivity was increased by 35-55%. We undertook a review of the literature to give an overview over the tests established that are currently considered useful. CONCLUSION: This case highlights that the identification of patients with increased radiosensitivity is an important task in radiation protection. Groups of patients who should be screened have to be found and corresponding research facilities have to be set up.
EVALuna2:32861

Leukocytosis and Neutrophilia as independent prognostic Biomarkers for clinical Outcome in the randomized Phase III CAO/ARO/AIO-04 Rectal Cancer Study - Diefenhardt, M.; Hofheinz, R-D; Martin, D.; Beissbarth, T.; Arnold, D.; Hartmann, Arndt; Von Der Grun, J.; Grützmann, Robert; Liersch, T.; Stroebel, P.; Grabenbauer, G. G.; Rieger, M.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Leukocytosis and neutrophilia as independent prognostic immunological biomarkers for clinical outcome in the CAO/ARO/AIO-04 randomized phase 3 rectal cancer trial - Diefenhardt, Markus; Hofheinz, Ralf Dieter; Martin, Daniel; Beißbarth, Tim; Arnold, Dirk; Hartmann, Arndt; von der Grün, Jens; Grützmann, Robert; Liersch, Torsten; Ströbel, Philipp; Grabenbauer, Gerhard G.; Rieger, Michael; et al. (International Journal of Cancer, 2019)
Peripheral blood leukocytosis and neutrophilia reflect cancer inflammation and have been proposed as prognostic immunological biomarkers in various malignancies. However, previous studies were limited by their retrospective nature and small patient numbers. Baseline peripheral blood leukocytes, neutrophils, hemoglobin, platelets, lactate dehydrogenase and carcinoembryonic antigen (CEA) were correlated with clinicopathologic characteristics, and clinical outcome in 1236 patients with rectal cancer treated with 5-FU-based preoperative chemoradiotherapy (CRT) alone or with oxaliplatin followed by surgery and adjuvant chemotherapy within the CAO/ARO/AIO-04 randomized phase 3 trial. Multivariable analyses were performed using Cox regression models. After a median follow-up of 50 months, baseline leukocytosis remained an independent adverse prognostic factor for disease-free survival (DFS; HR 1.457; 95% CI 1.163–1.825; p = 0.001), distant metastasis (HR 1.696; 95% CI 1.266–2.273; p < 0.001) and overall survival (OS; HR 1.716; 95% CI 1.264–2.329; p = 0.001) in multivariable analysis. Similar significant findings were observed for neutrophilia and high CEA levels. Conversely, treatment-induced leukopenia correlated with favorable DFS (p = 0.037), distant metastasis (p = 0.028) and OS (p = 0.012). Intriguingly, addition of oxaliplatin to 5-FU CRT resulted in a significant DFS improvement only in patients with neutrophilia and leukocytosis (p = 0.028 and p = 0.002). Our findings have important clinical implications and provide high-level evidence on the adverse prognostic role of leukocytes and neutrophils, and the impact of chemotherapy in the context of these biomarkers. These data could help guide patient stratification and should be further validated within prospective studies.
CRIS-Team Scopus Importer:2019-05-07
Keywords: clinical radiotherapeutic studies; clinical trials; colorectal cancer; molecular markers of metastasis and progression; radiochemotherapy

Lipiodol injections for optimization of target volume delineation in a patient with a second tumor of the oropharynx: A case report - Haderlein, Marlen; Merten, Ricarda; Stojanovic, Andrea; Speer, Stefan; Scherl, Claudia; Fietkau, Rainer; Ott, Oliver J. (Strahlentherapie und Onkologie, 2015)
Lipiodol injections were administered in the head and neck area to improve gross tumor volume (GTV) definition for small-volume re-irradiation of a 63-year-old previously irradiated patient with a second tumor of the oropharynx in the posterior wall with longitudinal ligament infiltration (cT4cN0cM0).The patient had dialysis-depending renal failure. On diagnostic computed tomography (CT), which was performed with intravenous contrast agent, the tumor in the oropharynx was not detectable. Because of dialysis-depending renal failure comorbidity, no contrast agent was applied in the planning CT and in the diagnostic magnetic resonance imaging (MRI) study. In each cross-sectional imaging study performed, the GTV, especially in craniocaudal extensions, was not safely delineable. Therefore, craniocaudal tumor margins were pharyngoscopically marked with Lipiodol injections, an iodine-containing contrast agent.In a second planning CT, the GTV could be defined with the help of the Lipiodol marks and small-volume re-irradiation was performed. No Lipiodol-associated side effects occurred in the patient.In the present case, the use of Lipiodol injections at the tumor margins facilitated the definition of the GTV.
EVALuna2:18277

Localization of reference points in electromagnetic tracking data and their application for treatment error detection in interstitial breast brachytherapy - Dürrbeck, Christopher; Schuster, Sabrina; Sauer, Birte; Abu-Hossin, Nadin; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Medical Physics, 2023)
Background: Electromagnetic tracking (EMT) is a promising technology that holds great potential to advance patient-specific pre-treatment verification in interstitial brachytherapy (iBT). It allows easy determination of the implant geometry without line-of-sight restrictions and without dose exposure to the patient. What it cannot provide, however, is a link to anatomical landmarks, such as the exit points of catheters or needles on the skin surface. These landmarks are required for the registration of EMT data with other imaging modalities and for the detection of treatment errors such as incorrect indexer lengths, and catheter or needle shifts. Purpose: To develop an easily applicable method to detect reference points in the positional data of the trajectory of an EMT sensor, specifically the exit points of catheters in breast iBT, and to apply the approach to pre-treatment error detection. Methods: Small metal objects were attached to catheter fixation buttons that rest against the breast surface to intentionally induce a local, spatially limited perturbation of the magnetic field on which the working principle of EMT relies. This perturbation can be sensed by the EMT sensor as it passes by, allowing it to localize the metal object and thus the catheter exit point. For the proof-of-concept, different small metal objects (magnets, washers, and bushes) and EMT sensor drive speeds were used to find the optimal parameters. The approach was then applied to treatment error detection and validated in-vitro on a phantom. Lastly, the in-vivo feasibility of the approach was tested on a patient cohort of four patients to assess the impact on the clinical workflow. Results: All investigated metal objects were able to measurably perturb the magnetic field, which resulted in missing sensor readings, that is two data gaps, one for the sensor moving towards the tip end and one when retracting from there. The size of the resulting data gaps varied depending on the choice of gap points used for calculation of the gap size; it was found that the start points of the gaps in both directions showed the smallest variability. The median size of data gaps was ⩽8 mm for all tested materials and sensor drive speeds. The variability of the determined object position was ⩽0.5 mm at a speed of 1.0 cm/s and ⩽0.7 mm at 2.5 cm/s, with an increase up to 2.3 mm at 5.0 cm/s. The in-vitro validation of the error detection yielded a 100% detection rate for catheter shifts of ≥2.2 mm. All simulated wrong indexer lengths were correctly identified. The in-vivo feasibility assessment showed that the metal objects did not interfere with the routine clinical workflow. Conclusions: The developed approach was able to successfully detect reference points in EMT data, which can be used for registration to other imaging modalities, but also for treatment error detection. It can thus advance the automation of patient-specific, pre-treatment quality assurance in iBT.
CRIS-Team Scopus Importer:2023-07-28
Keywords: brachytherapy; electromagnetic tracking; error detection; quality assurance

LOCAL LOW DOSE RADIATION INDUCES SYSTEMIC IMMUNE ALTERATIONS IN TWO EXPERIMENTAL MODELS OF INFLAMMATORY ARTHRITIS - Deloch, Lisa; Rückert, Michael; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Local X-ray Therapy induces systemic Immune Modulations in an experimental Model of rheumatoid Arthritis - Deloch, Lisa; Rueckert, M.; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-09-25

Locoregional recurrence in anal cancer: risk factors and management strategies - Gryc, Thomas; Putz, Florian; Merten, Ricarda; Goerig, Nicole; Fietkau, Rainer; Strnad, Vratislav (2017)
EVALuna2:32883

Longitudinal C-reactive protein (CRP) as an individualized dynamic predictor for metastatic cancer patients treated with immune checkpoint inhibitors: Findings from the prospective ST-ICI cohort. - Zhou, Jian-Guo; Ma, Hu; Gaipl, Udo; Frey, Benjamin; Hecht, Markus; Fietkau, Rainer (CANCER RESEARCH, 2021)
CRIS-Team WoS Importer:2021-09-03

Longitudinal Spread Analysis of Patients with Glioblastoma: high Prevalence of discontinuous Tumor Foci with no strong Relation to the Fibrous Tract System - Schmitter, Charlotte; Weissmann, Thomas; Mansoorian, Sina; Lettmaier, Sebastian; Semrau, Sabine; Schmidt, Manfred; Heiß, Rafael; Frey, Benjamin; Bert, Christoph; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Long-term control with chemoradiation of initially metastatic mixed adenoneuroendocrine carcinoma of the rectum: A case report - Semrau, S.; Agaimy, Abbas; Pavel, Marianne Ellen; Lubgan, Dorota; Schmidt, Daniela; Golcher, H.; Grützmann, Robert; Fietkau, Rainer; Cavallaro, Alexander Josef (Journal of Medical Case Reports, 2019)
Background: Mixed adenoneuroendocrine carcinomas are highly malignant tumors with both adenocarcinomatous and neuroendocrine components. They can originate in any organ but are more common in the rectum. Due to their rarity, current treatment recommendations for mixed adenoneuroendocrine carcinoma are based on limited data and follow general guidelines for the management of adenocarcinomas and neuroendocrine neoplasms. Uncertainty regarding the efficacy of the available local and systemic treatment strategies is a compounding issue. Even those patients with locally limited disease have a relatively short life expectancy. In this report, we describe a case of deep rectal mixed adenoneuroendocrine carcinoma with long survival after chemoradiation. Case presentation: A 48-year-old Caucasian woman was diagnosed with a grade 3 rectal adenocarcinoma combined with a poorly differentiated large cell neuroendocrine carcinoma component and synchronous metastases (cT3cN1cM1) in both lobes of the liver in 2012. She received concomitant chemoradiotherapy followed by four additional cycles of cisplatin plus irinotecan. Initial treatment induced complete remission of the rectal tumor and liver metastases. Consequently, it was not necessary to surgically resect the primary tumor or any of the metastases. Three months after the end of treatment, one metastasis in the first segment of the liver showed regrowth, and stereotactic body radiotherapy of the metastasis and chemotherapy resulted in a clinical complete response. The patient has been recurrence-free for more than 5 years. Conclusions: Extended long-term control of a poorly differentiated metastatic (stage IV) mixed adenoneuroendocrine carcinoma is rare. The multimodal first- and second-line regimens of radiotherapy and chemotherapy described in this case report represent a new therapeutic approach. Encouraged by the results in this case, we compiled a review of the literature on mixed adenoneuroendocrine carcinoma.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Chemoradiation; MANEC; Rectum; SBRT

Long-Term Experience of Chemoradiotherapy Combined with Deep Regional Hyperthermia for Organ Preservation in High-Risk Bladder Cancer (Ta, Tis, T1, T2) - Merten, Ricarda; Ott, Oliver; Haderlein, Marlen; Bertz, Simone; Hartmann, Arndt; Wullich, Bernd; Keck, Bastian; Kühn, Reinhard; Rödel, Claus Michael; Weiss, Christian; Gall, Christine; Uter, Wolfgang; et al. (Oncologist, 2019)
Background: The aim of this study was to evaluate the efficacy and safety of chemoradiotherapy (RCT) combined with regional deep hyperthermia (RHT) of high-risk bladder cancer after transurethral resection of bladder tumor (TUR-BT). Materials and methods: Between 1982 and 2016, 369 patients with pTa, pTis, pT1, and pT2 cN0–1 cM0 bladder cancer were treated with a multimodal treatment after TUR-BT. All patients received radiotherapy (RT) of the bladder and regional lymph nodes. RCT was administered to 215 patients, RCT + RHT was administered to 79 patients, and RT was used in 75 patients. Treatment response was evaluated 4–6 weeks after treatment with TUR-BT. Results: Complete response (CR) overall was 83% (290/351), and in treatment groups was RT 68% (45/66), RCT 86% (178/208), and RCT + RHT 87% (67/77). CR was significantly improved by concurrent RCT compared with RT (odds ratio [OR], 2.32; 95% confidence interval [CI], 1.05–5.12; p =.037), less influenced by hyperthermia (OR, 2.56; 95% CI, 0.88–8.00; p =.092). Overall survival (OS) after RCT was superior to RT (hazard ratio [HR], 0.7; 95% CI, 0.50–0.99; p =.045). Five-year OS from unadjusted Kaplan-Meier estimates was RCT 64% versus RT 45%. Additional RHT increased 5-year OS to 87% (HR, 0.32; 95% CI, 0.18–0.58; p =.0001). RCT + RHT compared with RCT showed a significantly better bladder-preservation rate (HR, 0.13; 95% CI, 0.03–0.56; p =.006). Median follow-up was 71 months. The median number of RHT sessions was five. Conclusion: The multimodal treatment consisted of a maximal TUR-BT followed by RT; concomitant platinum-based chemotherapy combined with RHT in patients with high-grade bladder cancer improves local control, bladder-preservation rate, and OS. It offers a promising alternative to surgical therapies like radical cystectomy. Implications for Practice: Radical cystectomy with appropriate lymph node dissection has long represented the standard of care for muscle-invasive bladder cancer in medically fit patients, despite many centers reporting excellent long-term results for bladder preserving strategies. This retrospective analysis compares different therapeutic modalities in bladder-preservation therapy. The results of this study show that multimodal treatment consisting of maximal transurethral resection of bladder tumor followed by radiotherapy, concomitant platinum-based chemotherapy combined with regional deep hyperthermia in patients with Ta, Tis, T1–2 bladder carcinomas improves local control, bladder-preservation rate, and survival. More importantly, these findings offer a promising alternative to surgical therapies like radical cystectomy. The authors hope that, in the future, closer collaboration between urologists and radiotherapists will further improve treatments and therapies for the benefit of patients.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Bladder cancer; Bladder preservation; Chemoradiotherapy; Hyperthermia; Radiotherapy

Long‐term follow‐up of patients receiving neoadjuvant treatment modalties for soft tissue sarcomas of the extremities - Rauch, Miriam; Agaimy, Abbas; Semrau, Sabine; Willner, Alexander; Ott, Oliver; Fietkau, Rainer; Hohenberger, Werner; Croner, Roland S.; Grützmann, Robert; Fechner, Katja; Vassos, Nikolaos (Cancers, 2021)
Background: Neoadjuvant treatment modalities in soft tissue sarcoma (STS) of the extremities have become more popular in recent years, but because of the rarity and heterogeneity of STS, there are yet few studies on the long‐term impact of neoadjuvant treatment modalities, especially in terms of neoadjuvant radiochemotherapy. Methods: The study enrolled 136 patients with primary STS of the extremities who underwent surgery with curative intent or neoadjuvant therapy, followed by surgery in a 15‐year period. Neoadjuvant treatment consisted of radiotherapy (RT) with 60 Gy and in most cases simultaneous chemotherapy (CTx) with ifosfamide (1.5 g/m2/d, d1–5, q28) and doxorubicine (50 mg/m2/d, d3, q28). We investigated the clinical, (post)‐operative and histopathological data and the oncological follow‐up as well. The median follow‐up period was 82 months (range 6–202). Results: A total of 136 patients (M:F = 73:63) with a mean age of 62 years (range; 21–93) was observed. Seventy‐four patients (54.4%) received neoadjuvant therapy (NT), 62 patients (45.6%) received primary surgery (PS). When receiving NT, patients with high‐risk STS had a lower risk to develop distant metastasis (p = 0.025). Age, histological type, tumor size and surgical margins (R0 vs. R1) had no influence on any survival rates. There was an association between NT and the occurrence of postoperative complications (p = 0.001). The 5‐year local recurrence free survival (LRFS), metastasis free survival (MFS), disease free survival (DFS) and overall survival (OS) rate of the whole cohort was 89.9%, 77.0%, 70.6% and 72.6%; whereas the 5‐year LRFS, MFS, DFS and OS rate was 90.5%, 67.2%, 64.1% and 62.8% for the NT group and 89.5%, 88.3%. 78.4% and 83.8% for the PS group. Conclusion: Multimodal treatment strategies in patients with STS of extremities lead to excellent oncological outcomes. Patients with high‐risk STS had a significantly better MFS when receiving NT than patients with low‐risk STS. NT was associated with a higher probability of postoperative but well‐manageable complications.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Extremity; Neoadjuvant therapy; Radiation; Radiochemotherapy; Soft tissue sarcoma

Long-term prognostic impact of surgical complications in the German Rectal Cancer Trial CAO/ARO/AIO-94 - Sprenger, T.; Beissbarth, T.; Sauer, Rolf; Tschmelitsch, J.; Fietkau, Rainer; Liersch, T.; Hohenberger, Werner; Staib, L.; Gaedcke, J.; Raab, H. -R.; Roedel, C.; Ghadimi, M. (British Journal of Surgery, 2018)
BACKGROUND: The influence of postoperative complications on survival in patients with locally advanced rectal cancer undergoing combined modality treatment is debatable. This study evaluated the impact of surgical complications on oncological outcomes in patients with locally advanced rectal cancer treated within the randomized CAO/ARO/AIO-94 (Working Group of Surgical Oncology/Working Group of Radiation Oncology/Working Group of Medical Oncology of the Germany Cancer Society) trial. METHODS: Patients were assigned randomly to either preoperative chemoradiotherapy (CRT) followed by total mesorectal excision (TME) or postoperative CRT between 1995 and 2002. Anastomotic leakage and wound healing disorders were evaluated prospectively, and their associations with overall survival, and distant metastasis and local recurrence rates after a long-term follow-up of more than 10 years were determined. Medical complications (such as cardiopulmonary events) were not analysed in this study. RESULTS: A total of 799 patients were included in the analysis. Patients who had anterior or intersphincteric resection had better 10-year overall survival than those treated with abdominoperineal resection (63·1 versus 51·3 per cent; P < 0·001). Anastomotic leakage was associated with worse 10-year overall survival (51 versus 65·2 per cent; P = 0·020). Overall survival was reduced in patients with impaired wound healing (45·7 versus 62·2 per cent; P = 0·009). At 10 years after treatment, patients developing any surgical complication (anastomotic leakage and/or wound healing disorder) had impaired overall survival (46·6 versus 63·8 per cent; P < 0·001), a lower distant metastasis-free survival rate (63·2 versus 72·0 per cent; P = 0·030) and more local recurrences (15·5 versus 6·4 per cent; P < 0·001). In a multivariable Cox regression model, lymph node metastases (P < 0·001) and surgical complications (P = 0·008) were the only independent predictors of reduced overall survival. CONCLUSION: Surgical complications were associated with adverse oncological outcomes in this trial.
EVALuna2:36462

Long-term results of a protocol-based ultrasound-guided salvage brachytherapy as re-irradiation for local recurrent prostate cancer - Schönle, Nicole; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer (Radiotherapy and Oncology, 2020)
Background and purpose: To assess the long-term results of protocol-based ultrasound-guided salvage pulsed-dose rate brachytherapy in locally recurrent prostate cancer following previous radiation therapy. Materials and methods: A total of 82 patients (median age 69 years) with locally recurrent prostate cancer after previous external beam radiation therapy (43/82, 52.4%), prostatectomy and adjuvant radiation therapy (24/82, 29.3%) or brachytherapy (15/82, 18.3%) were treated with sole salvage interstitial pulsed-dose rate brachytherapy (PDR-BT). The treatment regimen consisted of two PDR-BT sections with 30 Gy (single pulse dose 0.6 Gy/h, 24 h per day) each up to a total reference dose of 60 Gy (EQD2 = 71.5 Gy-eq). The endpoints of the present analysis are cumulative local recurrence-rate, PSA-free survival, overall survival and the treatment-associated late toxicity according to the “Common Toxicity Criteria” with a median follow-up of 49 months (range, 12–129 months). Results: The 5-y. overall cumulative local recurrence rate was 17.7% with no significant differences between low, intermediate and high-risk groups. Differences in PSA-free survival were marginally non-significant, at 67.3%, 70.4% and 63.8% for low, intermediate and high risk group, respectively. No grade 3 gastrointestinal late side effects have been observed. The most common late side effect was urinary incontinence grade 1–3 and urinary frequency/urgency grade 1–3 in 18.3% (15/82) and 17.1% (14/82) of patients, respectively. Conclusion: PDR salvage brachytherapy in local recurrent previously irradiated prostate cancer is efficient with low late toxicity. Salvage-brachytherapy represents a valuable therapeutic option for the treatment of previously irradiated locally recurrent prostate cancer.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Prostate cancer; Re-irradiation; Salvage-brachytherapy

Long-term Results of oligometastatic Head and Neck Tumors after local Treatment of all Metastases - Weissmann, T.; Höfler, Daniel; Semrau, S.; Lettmaier, S.; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Long-Term Results of the TARGIT-A Trial: More Questions than Answers - Piroth, Marc D.; Strnad, Vratislav; Krug, David; Fastner, Gerd; Baumann, Rene; Combs, Stephanie E.; Duma, Marciana Nona; Dunst, Juergen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; et al. (Breast Care, 2021)
Background: During the last decade, partial breast irradiation (PBI) has gained traction as a relevant treatment option for patients with early-stage low-risk breast cancer after breast-conserving surgery. The TARGIT-A prospective randomized trial compared a "risk-adapted" intraoperative radiotherapy (IORT) approach with 50-kv X-rays (INTRABEAM (R)) as the PBI followed by optional whole-breast irradiation (WBI) and conventional adjuvant WBI in terms of observed 5-year in-breast recurrence rates. Recently, long-term data were published. Since the first publication of the TARGIT-A trial, a broad debate has been emerged regarding several uncertainties and limitations associated with data analysis and interpretation. Our main objective was to summarize the data, with an emphasis on the updated report and the resulting implications. Summary: From our point of view, the previously unresolved questions still remain and more have been added, especially with regard to the study design, a change in the primary outcome measure, the significant number of patients lost to follow-up, and the lack of a subgroup analysis according to risk factors and treatment specifications. Key Message: Taking into account the abovementioned limitations of the recently published long-term results of the TARGIT-A trial, the German Society of Radiation Oncology (DEGRO) Breast Cancer Expert Panel adheres to its recently published recommendations on PBI: "the 50-kV system (INTRABEAM) cannot be recommended for routine adjuvant PBI treatment after breast-conserving surgery."
CRIS-Team WoS Importer:2021-04-23

Long-Term Survival after Salvage Surgery for Local Failure after Definitive Chemoradiation Therapy for Locally Advanced Non-small Cell Lung Cancer - Schreiner, Waldemar; Dudek, Wojciech; Lettmaier, Sebastian; Fietkau, Rainer; Sirbu, Horia (Thoracic and Cardiovascular Surgeon, 2018)
BACKGROUND: The incidence of local failure and residual tumor after definitive chemoradiation therapy (dCRT) for locally advanced non-small-cell lung cancer remains high, irrespective of applied radiation dose (>59 Gy). So-called salvage surgery has been suggested as a feasible treatment option after failure of definitive chemoradiation for locally advanced non-small cell lung cancer (NSCLC). Experience with salvage lung surgery (SLS) is limited, and long-term survival is rarely reported. Patient selection criteria for surgical lung salvage are not defined. The aim of this study was to assess postoperative survival and perioperative morbidity/mortality to identify prognostic factors and to define patient selection criteria. PATIENTS AND METHODS: Records of 13 consecutive patients with locally advanced NSCLC, who underwent SLS at a single institution between March 2011 and November 2016, were reviewed. Descriptive statistics were applied for patient characteristics and surgical and oncological outcome. Survival rates were calculated using the Kaplan-Meier method and were compared with the long-rank test. RESULTS: All patients initially received curative-intent definitive chemoradiation with median radiation doses of 66 Gy (range 59.4-72) and concurrent platinum-based chemotherapy. Clinical tumor stage before definitive chemoradiation was IIIA in 9, IIIB in 3, IV in 1 patients. Median interval between definitive chemoradiation and salvage surgery was 6.7 months. Perioperative morbidity and 30-days-mortality was 38% and 7.7%, respectively. The median postoperative survival and estimated 5-year survival rate were 29.7 months and 46%, respectively. CONCLUSION: SLS in patients with locally advanced non-small cell lung surgery following dCRT is feasible, prolongs long-term survival and allows local tumor control. Selection criteria remain undefined and patients should be considered surgical candidates during multidisciplinary team conference.
EVALuna2:35734

Low and moderate doses of ionizing radiation up to 2 Gy modulate transmigration and chemotaxis of activated macrophages, provoke an anti-inflammatory cytokine milieu, but do not impact upon viability and phagocytic function - Wunderlich, Roland; Ernst, A.; Roedel, F.; Fietkau, Rainer; Ott, O.; Lauber, K.; Frey, Benjamin; Gaipl, Udo (Clinical and Experimental Immunology, 2015)
Benign painful and inflammatory diseases have been treated for decades with low/moderate doses of ionizing radiation (LD-X-irradiation). Tissue macrophages regulate initiation and resolution of inflammation by the secretion of cytokines and by acting as professional phagocytes. Having these pivotal functions, we were interested in how activated macrophages are modulated by LD-X-irradiation, also with regard to radiation protection issues and carcinogenesis. We set up an ex-vivo model in which lipopolysaccharide pre-activated peritoneal macrophages (pM?) of radiosensitive BALB/c mice, mimicking activated macrophages under inflammatory conditions, were exposed to X-irradiation from 0·01 Gy up to 2 Gy. Afterwards, the viability of the pM?, their transmigration and chemotaxis, the phagocytic behaviour, the secretion of inflammatory cytokines and underlying signalling pathways were determined. Exposure of pM? up to a single dose of 2 Gy did not influence their viability and phagocytic function, an important fact regarding radiation protection. However, significantly reduced migration, but increased chemotaxis of pM? after exposure to 0·1 or 0·5 Gy, was detected. Both might relate to the resolution of inflammation. Cytokine analyses revealed that, in particular, the moderate dose of 0·5 Gy applied in low-dose radiotherapy for inflammatory diseases results in an anti-inflammatory cytokine microenvironment of pM?, as the secretion of the proinflammatory cytokine interleukin (IL)-1? was reduced and that of the anti-inflammatory cytokine transforming growth factor (TGF)-? increased. Further, the reduced secretion of IL-1? correlated with reduced nuclear translocation of nuclear factor (NF)-?B p65, starting at exposure of pM? to 0·5 Gy of X-irradiation. We conclude that inflammation is modulated by LD-X-irradiation via changing the inflammatory phenotype of macrophages.
EVALuna2:18185

Low cytoplasmic and nuclear KPNA2 expression in radiotherapy-treated head and neck squamous cell cancer is associated with an adverse outcome - Erben, Pia; Brunner, Kathrin; Hecht, Markus; Haderlein, Marlen; Buettner-Herold, Maike; Agaimy, Abbas; Fietkau, Rainer; Hartmann, Arndt; Distel, Luitpold (International Journal of Clinical and Experimental Pathology, 2015)
KPNA2 has effects on carcinogenesis, cell differentiation and transcriptional regulation. KPNA2 has been linked to DNA damage repair by its role to import the DNA double strand break repair complex MRN into the nucleus. The aim of our study was to evaluate the prognostic value of KPNA2 expression in both cytoplasmic and nuclear location in patients with HNSCC treated with radio(chemo)therapy.225 patients with HNSCC treated with neoadjuvant, definitive or adjuvant radio(chemo)therapy were included. Immunohistochemical staining was performed on tissue micro arrays to evaluate nuclear and cytoplasmic KPNA2 expression.The median fraction of tumor cells with nuclear KPNA2 expression was 15%. 47% of tumor samples showed positive cytoplasmic staining. Patients with low nuclear as well as negative cytoplasmic expression tended to have an unfavorable prognosis. There was no correlation between nuclear and cytoplasmic KPNA2 expression. Low nuclear combined with negative cytoplasmic KPNA2 had a clearly unfavorable prognostic effect in local failure-free survival (P=0.014), metastasis-free survival (P=0.001) and no evidence of disease (P=0.008). A combination of low nuclear/negative cytoplasmic with high nuclear/high cytoplasmic KPNA2 expression was prognostically unfavorable with regard to tumor specific survival (P=0.021) and to a lower extent to overall survival (P=0.18). In multivariate analysis low nuclear/negative cytoplasmic versus any high KPNA2 (P=0.008) and T-category (P=0.002) proved as independent prognostic variables.The combination of nuclear and cytoplasmic KPNA2 expression is a potential excellent prognostic parameter in HNSCC treated with radio(chemo)therapy.
EVALuna2:6796

Low dose ionising radiation leads to a NF-?B dependent decreased secretion of active IL-1? by activated macrophages with a discontinuous dose-dependency - Lödermann, Barbara; Wunderlich, Roland; Frey, Silke; Schorn, Christine; Stangl, Sonja; Roedel, Franz; Keilholz, Ludwig; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (International Journal of Radiation Biology, 2012)
Therapy with low doses of ionising radiation (X-rays) exerts anti-inflammatory effects. Little is known about whether and how low doses of X-ray treatment modulate the inflammatory phenotype of macrophages, especially the secretion of Interleukin-1beta (IL-1?).Macrophages were differentiated from human THP-1 monocytes, activated with lipopolysaccharide (LPS), treated with distinct low doses of X-rays, and co-activated with monosodium urate crystals (MSU) to induce inflammasome activation. Secretion of IL-1? was analysed by an enzyme-linked immunosorbent assay (ELISA) and Western blot. Furthermore, we analysed the intracellular amounts of the serine/threonine protein kinase B (named: Akt), mitogen-activated protein kinase p38 (p38), the v-rel reticuloendotheliosis viral oncogene homolog A (RelA), and pro- and cleaved IL-1?.Low dose X-rays led to decreased secretion of active IL-1? in a manner discontinuous with dose which was most pronounced after 0.5 or 0.7 Gy. Passive release of lactate dehydrogenase (LDH) was not influenced by X-rays. The decreased secretion of IL-1? correlated with reduced translocation of RelA, being part of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-?B) complex, into the nucleus. After 0.5 or 0.7 Gy of X-rays, the intracellular protein amounts of up (p38) and downstream molecules (Akt) of NF-?B were reduced in activated macrophages, as were the pro- and cleaved forms of IL-1?.Distinct low doses of X-rays induce an anti-inflammatory phenotype of activated macrophages by lowering the amount of secreted IL-1? in a NF-?B dependent manner.
EVALuna2:12777

Low-Dose Irradiation Differentially Impacts Macrophage Phenotype in Dependence of Fibroblast-Like Synoviocytes and Radiation Dose - Fuchs, Jana; Rueckert, Michael; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (Journal of Immunology Research, 2019)
Rheumatoid arthritis (RA) is a multifactorial autoimmune disease whose main hallmark is inflammation and destruction of the joints. Two cell types within the synovium that play an important role in RA are fibroblast-like synoviocytes (FLS) and macrophages. The latter innate immune cells show a high plasticity in their phenotype and are central in inflammatory processes. Low-dose radiotherapy (LD-RT) with particularly a single dose of 0.5 Gy has been demonstrated to have a positive impact on pain, inflammation, and bone in inflamed joints. We now examined for the first time how LD-RT influences FLS and bone marrow-derived macrophages in co-culture systems of an experimental model of RA to reveal further mechanisms of immune modulatory effects of low and intermediate dose of ionizing radiation. For this, the bone marrow of hTNF-alpha tg mice was differentiated either with cytokines to obtain key macrophage phenotypes (M0, M1, and M2) or with supernatants (SN) of untreated or irradiated FLS. Flow cytometry analyses were used to analyse the impact of radiation (0.1, 0.5, 1.0, and 2.0 Gy) on the phenotype of macrophages in the presence or absence of SN of FLS. LD-RT had no impact on cytokine-mediated macrophage polarization in M0, M1, or M2 macrophages. However, SN of irradiated FLS particularly reduced CD206 expression on macrophages. Macrophage phenotype was stable when being in contact with SN of nonirradiated FLS, but significantly increased surface expression of CD206 and slightly decreased CD80 and CD86 expression were observed when macrophage themselves were irradiated with 0.5 Gy under these microenvironmental conditions, again highlighting discontinuous dose dependencies in the low and intermediate dose range. One can conclude that FLS-dependent microenvironmental conditions have a slight influence on the modulation of macrophage phenotype under radiation exposure conditions. Future studies are needed to reveal the impact of radiation exposure on the functions of treated macrophages under such microenvironmental conditions.
CRIS-Team WoS Importer:2019-09-13

Low-dose irradiation has an impact on bone metabolism as well as on local and systemic immune cell-mediated inflammation - Deloch, Lisa; Rückert, Michael; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
EVALuna2:36495

Low-dose irradiation reduces fibroblast-like synoviocytes and impacts on bone metabolism in dependence of the inflammatory state - Liberg, J.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (2017)
EVALuna2:32878

Low-dose irradiation shifts macrophages to a more immune suppressive phenotype in a clinically relevant setting together with inflammatory fibroblast-like synoviocytes - Liberg, J.; Rueckert, M.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (2017)
EVALuna2:32887

Low dose radiation alters the inflammatory phenotype of fibroblast-like synoviocytes and impacts on bone metabolism - Frey, Benjamin; Liberg, J.; Derer, Anja; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (2017)
EVALuna2:32862

LOW DOSE RADIATION ALTERS THE INFLAMMATORY PHENOTYPE OF FIBROBLAST-LIKE SYNOVIOCYTES AND MACROPHAGES AND STIMULATES OSTEOBLASTS - Deloch, Lisa; Liberg, Jana; Rückert, Michael; Hueber, Axel; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2017)
EVALuna2:32907

LOW DOSE RADIATION HAS A POSITIVE IMPACT ON BONE METABOLISM IN AN EXPERIMENTAL MODEL OF INFLAMMATORY ARTHRITIS - Deloch, Lisa; Rückert, Michael; Hueber, Axel; Herrmann, Martin; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
EVALuna2:36516

Low Dose Radiation Therapy Induces Long-Lasting Reduction of Pain and Immune Modulations in the Peripheral Blood - Interim Analysis of the IMMO-LDRT01 Trial - Donaubauer, Anna-Jasmina; Becker, Ina; Weissmann, Thomas; Fröhlich, Birgitta; Munoz, Luis Enrique; Gryc, Thomas; Denzler, Manuel; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2021)
The treatment of chronic inflammatory and degenerative diseases by low dose radiation therapy (LDRT) is promising especially for patients who were refractory for classical therapies. LDRT aims to reduce pain of patients and to increase their mobility. Although LDRT has been applied since the late 19th century, the immunological mechanisms remain elusive. Within the prospective IMMO-LDRT01 trial (NCT02653079) the effects of LDRT on the peripheral blood immune status, as well as on pain and life quality of patients have been analyzed. Blood is taken before and after every serial irradiation with a single dose per fraction of 0.5Gy, as well as during follow-up appointments in order to determine a detailed longitudinal immune status by multicolor flow cytometry. Here, we report the results of an interim analysis of 125 patients, representing half the number of patients to be recruited. LDRT significantly improved patients' pain levels and induced distinct systemic immune modulations. While the total number of leukocytes remained unchanged in the peripheral blood, LDRT induced a slight reduction of eosinophils, basophils and plasmacytoid dendritic cells and an increase of B cells. Furthermore, activated immune cells were decreased following LDRT. Especially cells of the monocytic lineage correlated to LDRT-induced improvements of clinical symptoms, qualifying these immune cells as predictive biomarkers for the therapeutic success. We conclude that LDRT improves pain of the patients by inducing systemic immune modulations and that immune biomarkers could be defined for prediction by improved patient stratification in the future.
CRIS-Team WoS Importer:2021-11-12

Low dose radiation therapy, particularly with 0.5 gy, improves pain in degenerative joint disease of the fingers: Results of a retrospective analysis - Donaubauer, Anna-Jasmina; Zhou, Jianguo; Ott, Oliver J.; Putz, Florian; Fietkau, Rainer; Keilholz, Ludwig; Gaipl, Udo; Frey, Benjamin; Weissmann, Thomas (International Journal of Molecular Sciences, 2020)
Low-dose radiation therapy (LDRT) has been successfully established for decades as an alternative analgesic treatment option for patients suffering from chronic degenerative and inflammatory diseases. In this study, 483 patients were undergoing LDRT for degenerative joint disease of the fingers and thumb at the University Hospital Erlangen between 2004 and 2019. Radiotherapy was applied according to the German guidelines for LDRT. Several impact factors on therapeutic success, such as the age and gender, the number of affected fingers, the single and cumulative dose, as well as the number of series, were investigated. In summary, 70% of the patients showed an improvement of their pain following LDRT. No significant impact was found for the factors age, gender, the number of series or the cumulative dosage. Patients with an involvement of the thumb showed a significantly worse outcome compared to patients with an isolated affection of the fingers. In this cohort, patients receiving a single dose of 0.5 Gy reported a significantly better outcome than patients receiving 1.0 Gy, strongly suggesting a reduction in the total dose. In summary, LDRT is a good alternative treatment option for patients suffering from degenerative and inflammatory joint disease of the fingers.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Chronic degenerative and inflammatory diseases; Degenerative joint disease of the fingers; LDRT; Low-dose radiation therapy; Osteoarthritis; Subjective pain level

Low-Dose Radiotherapy Ameliorates Advanced Arthritis in hTNF-α tg Mice by Particularly Positively Impacting on Bone Metabolism - Deloch, Lisa; Derer, Anja; Hueber, Axel; Herrmann, Martin; Schett, Georg; Wölfelschneider, Jens; Hahn, Jonas; Rühle, Paul-Friedrich; Stillkrieg, Willy; Fuchs, Jana; Fietkau, Rainer; Frey, Benjamin; et al. (Frontiers in Immunology, 2018)
Inflammation and bone erosion are central in rheumatoid arthritis (RA). Even though effective medications for control and treatment of RA are available, remission is only seen in a subset of patients. Treatment with low-dose radiotherapy (LD-RT) which has been already successfully used for amelioration of symptoms in benign diseases should be a promising approach to reduce pain, inflammation, and particularly bone erosion in patients with RA. Even though anti-inflammatory effects of LD-RT are already described with non-linear dose response relationships, and pain-reducing effects have been clinically observed, the underlying mechanisms are widely unknown. Besides immune cells many other cell types, such as fibroblast-like synoviocytes (FLS), osteoclasts, and osteoblast are present in the affected joint and might be modulated by LD-RT. For this study, these cell types were obtained from human tumor necrosis factor-α transgenic (hTNF-α tg) mice and were consecutively exposed to different doses of ionizing radiation (0.1, 0.5, 1.0, and 2.0 Gy, respectively) in vitro. In order to study the in vivo effects of LD-RT within the arthritic joint, hind paws of arthritic hTNF-α tg mice were locally irradiated with 0.5 Gy, a single dose per fraction that is known for good clinical responses. Starting at a dose of 0.5 Gy, proliferation of FLS was reduced and apoptosis significantly enhanced with no changes in necrosis. Further, expression of RANK-L was slightly reduced following irradiation with particularly 0.5 Gy. Starting from 0.5 Gy, the numbers of differentiated osteoclasts were significantly reduced, and a lower bone resorbing activity of treated osteoclasts was also observed, as monitored via pit formation and Cross Laps presence. LD-RT had further a positive effect on osteoblast-induced mineralization in a discontinuous dose response relationship with 0.5 Gy being most efficient. An increase of the gene expression ratio of OPG/RANK-L at 0.1 and 0.5 Gy and of production of OPG at 0.5 and 1.0 Gy was observed. In vivo, LD-RT resulted in less severe arthritis in arthritic hTNF-α tg mice and in significant reduction of inflammatory and erosive area with reduced osteoclasts and neutrophils. Locally applied LD-RT can, therefore, induce a beneficial micro-environment within arthritic joints by predominantly positively impacting on bone metabolism.
EVALuna2:34663
Keywords: rheumatoid arthritis; inflammation; low-dose radiotherapy; bone metabolism; synovial-like fibroblasts; osteoclasts; osteoblasts

Low-dose Radiotherapy for painful Finger Joint Arthrosis - Weissmann, T.; Ott, Oliver; Putz, Florian; Becker, Ina; Fietkau, Rainer; Donaubauer, Anna-Jasmina; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-09-25

Low-Dose Radiotherapy Has No Harmful Effects on Key Cells of Healthy Non-Inflamed Joints - Deloch, Lisa; Rückert, Michael; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (International Journal of Molecular Sciences, 2018)
Low-dose radiotherapy (LD-RT) for benign inflammatory and/or bone destructive diseases has been used long. Therefore, mechanistic investigations on cells being present in joints are mostly made in an inflammatory setting. This raises the question whether similar effects of LD-RT are also seen in healthy tissue and thus might cause possible harmful effects. We performed examinations on the functionality and phenotype of key cells within the joint, namely on fibroblast-like synoviocytes (FLS), osteoclasts and osteoblasts, as well as on immune cells. Low doses of ionizing radiation showed only a minor impact on cytokine release by healthy FLS as well as on molecules involved in cartilage and bone destruction and had no significant impact on cell death and migration properties. The bone resorbing abilities of healthy osteoclasts was slightly reduced following LD-RT and a positive impact on bone formation of healthy osteoblasts was observed after in particular exposure to 0.5 Gray (Gy). Cell death rates of bone-marrow cells were only marginally increased and immune cell composition of the bone marrow showed a slight shift from CD8⁺ to CD4⁺ T cell subsets. Taken together, our results indicate that LD-RT with particularly a single dose of 0.5 Gy has no harmful effects on cells of healthy joints.
EVALuna2:36453

Low-Dose Radiotherapy is highly effective in the Treatment of painful Finger Polyarthrosis - Weissmann, Thomas; Gaipl, Udo; Putz, Florian; Hecht, Markus; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Fietkau, Rainer; Ott, Oliver; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low-dose Radiotherapy is highly effective in the Treatment of Patients with painful Ankle Arthrosis - Weissmann, Thomas; Putz, Florian; Hecht, Markus; Zhou, Jianguo; Donaubauer, Anna-Jasmina; Fietkau, Rainer; Gaipl, Udo; Ott, Oliver; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low-Dose Radiotherapy Leads to a Systemic Anti-Inflammatory Shift in the Pre-Clinical K/BxN Serum Transfer Model and Reduces Osteoarthritic Pain in Patients - Weissmann, Thomas; Rückert, Michael; Zhou, Jianguo; Seeling, Michaela; Lettmaier, Sebastian; Donaubauer, Anna-Jasmina; Nimmerjahn, Falk; Ott, Oliver; Hecht, Markus; Putz, Florian; Fietkau, Rainer; Frey, Benjamin; et al. (Frontiers in Immunology, 2022)
Osteoarthritis (OA) is the leading degenerative joint disease in the western world and leads, if left untreated, to a progressive deterioration of joint functionality, ultimately reducing quality of life. Recent data has shown, that especially OA of the ankle and foot are among the most frequently affected regions. Current research in OA points towards a complex involvement of various cell and tissue types, often accompanied by inflammation. Low-dose radiotherapy (LDRT) is widely used for the treatment of degenerative and inflammatory diseases. While the reported analgesic effects are well known, the underlying molecular mechanisms are only poorly understood. We therefore correlated a clinical approach, looking at pain reduction in 196 patients treated with LDRT with a pre-clinical approach, utilizing the K/BxN serum transfer mouse model using flow cytometry and multiplex ELISA for analysis. While an improvement of symptoms in the majority of patients was found, patients suffering from symptoms within the tarsi transversa show a significantly lower level of improvement. Further, a significant impact of therapy success was detected depending on whether only one or both feet were affected. Further, patients of younger age showed a significantly better outcome than older ones while needing fewer treatment series. When looking on a cellular level within the mouse model, a systemic alteration of immune cells namely a shift from CD8+ to CD4+ T cells and reduced numbers of DCs was observed. A general reduction of inflammatory cytokines was detected, with significant alterations in IL-4 and IL-17 levels, all of which could potentially be responsible for the highly effective clinical improvement in patients. Taken together our data indicate that LDRT can be regarded as a highly effective treatment option for patients suffering from OA of the foot and ankle, in terms of analgesic effects, especially in younger patients. Furthermore, the observed effects are mediated by an interplay of cellular and soluble immune factors, as observed in the K/BxN serum transfer model. With this interdisciplinary approach we aim to encourage the usage of LDRT as an additive treatment strategy not only as a last resort, but also earlier in the course of disease.
CRIS-Team Scopus Importer:2022-01-28
Keywords: foot; K/BxN serum transfer; low-dose radiotherapy; mouse model; osteoarthritis; pain; rheumatoid arthritis; X-rays

Low-dose radiotherapy of osteoarthritis: from biological findings to clinical effects-challenges for future studies - Weissmann, Thomas; Rückert, Michael; Putz, Florian; Donaubauer, Anna-Jasmina; Hecht, Markus; Schnellhardt, Sören; Schubert, Philipp; Roesch, Johannes; Höfler, Daniel; Ott, Oliver; Haderlein, Marlen; Lettmaier, Sebastian; et al. (Strahlentherapie und Onkologie, 2023)

Low-dose Radiotherapy with X-rays and Radon leads to different immunological Changes in a Mouse Model for Rheumatoid Arthritis - Deloch, Lisa; Rückert, Michael; Maier, A.; Hinrichs, A.; Weissmann, T.; Seeling, Michaela; Nimmerjahn, Falk; Flohr, A. -S.; Eckert, D.; Fournier, C.; Fietkau, Rainer; Frey, Benjamin; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Low-dose-rate Prostate Brachytherapy: Characterization of Seeds Dynamics within the Prostate - Karius, Andre; Lotter, M.; Kreppner, Stephan; Lubgan, Dorota; Grigo, Johanna; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Low-dose X-Rays influence the Macrophage Polarization interacting with Synovial Fibroblasts in an anti-inflammatory Manner - Fuchs, J.; Rueckert, M.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Low-grade (polymorphous) adenocarcinoma of the middle ear mimicking a jugulotympanic paraganglioma - Mantsopoulos, Konstantinos; Fietkau, Rainer; Hornung, Joachim; Agaimy, Abbas; Iro, Heinrich; Taha, Lava (HNO, 2021)
A 64-year-old female patient presented with otalgia and hearing loss in the right ear. On otoscopy, the right tympanic membrane was highly vascularized and bulged into the anteroinferior quadrant. High-resolution computed tomography revealed an osteolytic lesion with occupation of the hypotympanum extending into the petrous apex and right parapharyngeal space as well as infiltration of the wall of the right internal carotid artery. MRI strengthened the suspicion of a jugulotympanic paraganglioma. The biopsy material obtained through exploratory tympanotomy was assessed as a low-grade polymorphic adenocarcinoma. The tumor was treated with definitive chemoradiotherapy. Posttherapeutic imaging after 4 months did not show any evidence of tumor progression.
CRIS-Team WoS Importer:2021-06-18

Low-grade (polymorphous) adenocarcinoma of the middle ear mimicking a jugulotympanic paraganglioma. German version - Mantsopoulos, Konstantinos; Fietkau, Rainer; Hornung, Joachim; Agaimy, Abbas; Iro, Heinrich; Taha, Lava (HNO, 2021)
A 64-year-old female patient presented with otalgia and hearing loss in the right ear. On otoscopy, the right tympanic membrane was highly vascularized and bulged into the anteroinferior quadrant. High-resolution computed tomography revealed an osteolytic lesion with occupation of the hypotympanum extending into the petrous apex and right parapharyngeal space as well as infiltration of the wall of the right internal carotid artery. MRI strengthened the suspicion of a jugulotympanic paraganglioma. The biopsy material obtained through exploratory tympanotomy was assessed as a low-grade polymorphic adenocarcinoma. The tumor was treated with definitive chemoradiotherapy. Posttherapeutic imaging after 4 months did not show any evidence of tumor progression.
CRIS-Team WoS Importer:2021-05-07

Low- vs. high-dose radiotherapy in Graves’ ophthalmopathy: a retrospective comparison of long-term results - Weissmann, Thomas; Lettmaier, Sebastian; Donaubauer, Anna-Jasmina; Bert, Christoph; Schmidt, Manfred; Kruse, Friedrich; Ott, Oliver; Hecht, Markus; Fietkau, Rainer; Frey, Benjamin; Putz, Florian (Strahlentherapie und Onkologie, 2021)
Purpose: Radiotherapy represents an effective treatment option in Graves’ ophthalmopathy (GO), leading to palliation of clinical symptoms. However, there are only a limited number of trials comparing the effectiveness of low- vs. high-dose radiotherapy. Methods: We analyzed 127 patients treated with radiotherapy for stage 3/4 GO (NOSPECS classification). Patients were treated with single doses of 2.0 Gy (cumulative dose 20 Gy) until 2007, afterwards a single dose of 0.8 Gy (cumulative dose 4.8 Gy) was applied. With a median follow-up-time of 9.0 years, the treatment efficacy (overall improvement, sense of eye pressure, lid edema, ocular motility, exophthalmos, subjective vision, and diplopia) and adverse effects were analyzed by a standardized survey. Results: Overall, 63.8% described improvement of symptoms after radiotherapy. No significant differences in overall treatment response and improvement of main outcome measures between low- or high-dose radiotherapy treatments are detectable, while low-dose radiotherapy leads significantly more often to retreatment (13.1% vs. 1.7%, p = 0.016). The main independent predictor of treatment response is the presence of lid edema (odds ratio, OR, 3.53; p = 0.006). Conclusion: At long-term follow-up, the majority of patients reported palliation of symptoms with limited adverse effects, suggesting clinical effectiveness of radiotherapy for amelioration of GO symptoms independent of low- or high-dose radiotherapy.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Exophthalmos; Graves’ ophthalmopathy; Low dose radiation therapy; Radiotherapy; Thyroid eye disease

Lung Resection after Definitive and Neo-Adjuvant Chemoradiation for Stage IIIA/B Locally Advanced Non-Small Cell Lung Cancer: a Retrospective Analysis - Schreiner, Waldemar; Gavrychenkova, Sofiia; Dudek, Wojciech; Lettmaier, Sebastian; Rieker, Ralf; Fietkau, Rainer; Sirbu, Horia (Zentralblatt für Chirurgie, 2018)
BACKGROUND: The outcomes of so called "salvage" resections after definitive chemoradiation vs. curative resections after neoadjuvant chemoradiation therapy (IT-resection) in patients with stage IIIA/B locally advanced non-small cell lung cancer have rarely been compared. The aim of our study was to compare perioperative results, postoperative and recurrence-free survival and to identify relevant prognostic survival factors for both therapy strategies. PATIENTS AND METHODS: Between June 2008 and May 2017, 43 patients underwent pulmonary resection following induction therapy (group 1) and 14 patients underwent salvage resection after definitive chemoradiation (group 2). Retrospective analysis was performed of demographic factors, tumour stage and location, initial therapy, preoperative regression status, perioperative morbidity and mortality, postoperative and recurrence-free survival. RESULTS: In group 2, significantly higher radiation dose was applied (p < 0.001) and the interval between chemoradiation and lung resection was significantly longer (p = 0.02). In addition, significantly higher perioperative blood loss and more frequent blood transfusions were noted (p = 0.003 and 0.005, respectively). Perioperative morbidity and mortality were statistically comparable in the two groups (p = 0.72 and 0.395, respectively). Postoperative 5 year survival in group 1 was 55%, in group 2 48% (log-rank p = 0.353). Five year recurrence-free survival in group 1 was 53%, in group 2 42% (log-rank p = 0.180). Diffuse metastasis occurred mostly in group 2, whereas in group 1 oligometastasis was more frequently noted. CONCLUSION: Postoperative outcome after salvage resection seems statistically comparable to results following curative resection after induction therapy. Diffuse distant metastasis is frequently noted. Careful patient selection is required.
EVALuna2:35732

Machine Learning-assisted immunophenotyping of peripheral blood identifies innate immune cells as best predictor of response to induction chemo-immunotherapy in head and neck squamous cell carcinoma – knowledge obtained from the CheckRad-CD8 trial - Hecht, Markus; Frey, Benjamin; Gaipl, Udo; Tianyu, Xie; Eckstein, Markus; Donaubauer, Anna-Jasmina; Klautke, Gunther; Illmer, Thomas; Fleischmann, Maximilian; Laban, Simon; Hautmann, Matthias G.; Tamaskovics, Bálint; et al. (Neoplasia, 2024)
Purpose: Individual prediction of treatment response is crucial for personalized treatment in multimodal approaches against head-and-neck squamous cell carcinoma (HNSCC). So far, no reliable predictive parameters for treatment schemes containing immunotherapy have been identified. This study aims to predict treatment response to induction chemo-immunotherapy based on the peripheral blood immune status in patients with locally advanced HNSCC. Methods: The peripheral blood immune phenotype was assessed in whole blood samples in patients treated in the phase II CheckRad-CD8 trial as part of the pre-planned translational research program. Blood samples were analyzed by multicolor flow cytometry before (T1) and after (T2) induction chemo-immunotherapy with cisplatin/docetaxel/durvalumab/tremelimumab. Machine Learning techniques were used to predict pathological complete response (pCR) after induction therapy. Results: The tested classifier methods (LDA, SVM, LR, RF, DT, and XGBoost) allowed a distinct prediction of pCR. Highest accuracy was achieved with a low number of features represented as principal components. Immune parameters obtained from the absolute difference (lT2-T1l) allowed the best prediction of pCR. In general, less than 30 parameters and at most 10 principal components were needed for highly accurate predictions. Across several datasets, cells of the innate immune system such as polymorphonuclear cells, monocytes, and plasmacytoid dendritic cells are most prominent. Conclusions: Our analyses imply that alterations of the innate immune cell distribution in the peripheral blood following induction chemo-immuno-therapy is highly predictive for pCR in HNSCC.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Chemotherapy; HNSCC; Immune phenotyping; Immunotherapy; Induction therapy

Machine learning based on blood biomarkers predicts fast progression in advanced NSCLC patients treated with immunotherapy - Zhou, J-G.; Yang, J.; Wang, H.; Wong, A. H-H.; Tan, F.; Chen, X.; He, S.; Shen, G.; Wang, Y-J.; Frey, B.; Fietkau, Rainer; Hecht, Markus; et al. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-04-29

Machine learning based on blood test biomarkers predicts fast progression in advanced NSCLC patients treated with immunotherapy - Zhou, Jian Guo; Yang, Jie; Wang, Haitao; Wong, Ada Hang Heng; Tan, Fangya; Chen, Xiaofei; He, Si Si; Shen, Gang; Wang, Yun Jia; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; et al. (BMJ Oncology, 2024)
Objective Fast progression (FP) represents a desperate situation for advanced non-small cell lung cancer (NSCLC) patients undergoing immune checkpoint inhibitor therapy. We aimed to develop a predictive framework based on machine learning (ML) methods to identify FP in advanced NSCLC patients using blood test biomarkers. Methods and analysis We extracted data of 1546 atezolizumab-treated patients from four multicentre clinical trials. In this study, patients from the OAK trial were taken for model training, whereas patients from the other trials were used for independent validations. The FP prediction model was developed using 21 pretreatment blood test variables in seven ML approaches. Prediction performance was evaluated by the receiver operating characteristic (ROC) curve. Results The prevalence of FP was 7.6% (118 of 1546) in all atezolizumab-treated patients. The most important variables for the prediction model were: C reactive protein, neutrophil count, lactate dehydrogenase and alanine transaminase. The Support Vector Machine (SVM) algorithm applied to these four blood test parameters demonstrated good performance: the area under the ROC curve obtained from the training cohort (OAK), validation cohort 1 (BIRCH) and cohort 2 (merged POPLAR and FIR) were 0.908, 0.666 and 0.776, respectively. In addition, the absolute difference in median survival between the SVM-predicted FP and non-FP groups was significant in both progression-free survival and overall survival (p<0.001). Conclusion SVM trained using a 4-biomarker panel has good performance in predicting the occurrence of FP regardless of programmed cell death ligand 1 expression, hence providing evidence for decision-making in single-agent atezolizumab immunotherapy for patients with advanced NSCLC.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Biomarkers; Immunotherapy; Lung cancer (non-small cell)

Machine Learning-Supported Diagnosis of Small Blue Round Cell Sarcomas Using Targeted RNA Sequencing. - Schlieben, Lea D.; Carta, Maria Giulia; Moskalev, Evgeny; Stöhr, Robert; Metzler, Markus; Besendörfer, Manuel; Meidenbauer, Norbert; Semrau, Sabine; Janka, Rolf Matthias; Grützmann, Robert; Wiemann, Stefan; Hartmann, Arndt; et al. (Journal of Molecular Diagnostics, 2024)
Small blue round cell sarcomas (SBRCSs) are a heterogeneous group of tumors with overlapping morphologic features but markedly varying prognosis. They are characterized by distinct chromosomal alterations, particularly rearrangements leading to gene fusions, whose detection currently represents the most reliable diagnostic marker. Ewing sarcomas are the most common SBRCSs, defined by gene fusions involving EWSR1 and transcription factors of the ETS family, and the most frequent non-EWSR1-rearranged SBRCSs harbor a CIC rearrangement. Unfortunately, currently the identification of CIC::DUX4 translocation events, the most common CIC rearrangement, is challenging. Here, we present a machine-learning approach to support SBRCS diagnosis that relies on gene expression profiles measured via targeted sequencing. The analyses on a curated cohort of 69 soft-tissue tumors showed markedly distinct expression patterns for SBRCS subgroups. A random forest classifier trained on Ewing sarcoma and CIC-rearranged cases predicted probabilities of being CIC-rearranged >0.9 for CIC-rearranged-like sarcomas and <0.6 for other SBRCSs. Testing on a retrospective cohort of 1335 routine diagnostic cases identified 15 candidate CIC-rearranged tumors with a probability >0.75, all of which were supported by expert histopathologic reassessment. Furthermore, the multigene random forest classifier appeared advantageous over using high ETV4 expression alone, previously proposed as a surrogate to identify CIC rearrangement. Taken together, the expression-based classifier can offer valuable support for SBRCS pathologic diagnosis.
EVALuna2:565265

Magnetic resonance imaging for brain stereotactic radiotherapy - A review of requirements and pitfalls - Putz, Florian; Mengling, Veit; Perrin, Rosalind; Masitho, Siti; Weissmann, Thomas; Roesch, Johannes; Bäuerle, Tobias; Janka, Rolf Matthias; Uder, Michael; Amarteifio, Patrick; Doussin, Sylvain; Schmidt, Manuel; et al. (Strahlentherapie und Onkologie, 2020)
Due to its superior soft tissue contrast, magnetic resonance imaging (MRI) is essential for many radiotherapy treatment indications. This is especially true for treatment planning in intracranial tumors, where MRI has a long-standing history for target delineation in clinical practice. Despite its routine use, care has to be taken when selecting and acquiring MRI studies for the purpose of radiotherapy treatment planning. Requirements on MRI are particularly demanding for intracranial stereotactic radiotherapy, where accurate imaging has a critical role in treatment success. However, MR images acquired for routine radiological assessment are frequently unsuitable for high-precision stereotactic radiotherapy as the requirements for imaging are significantly different for radiotherapy planning and diagnostic radiology. To assure that optimal imaging is used for treatment planning, the radiation oncologist needs proper knowledge of the most important requirements concerning the use of MRI in brain stereotactic radiotherapy. In the present review, we summarize and discuss the most relevant issues when using MR images for target volume delineation in intracranial stereotactic radiotherapy.
CRIS-Team WoS Importer:2020-04-10

Magnetic Resonance thermometry images of hyperthermia treatments of sarcomas for prediction of therapy responses-need of data reprocessing and cleaning - Khatun, Rupali; Hader, Michael; Schmidt, Manfred; Bert, Christoph; Wadepohl, Martin; Fietkau, Rainer; Ott, Jessica; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Major Pathologic Response after Induction Therapy Has a Long-Term Impact on Survival and Tumor Recurrence in Stage IIIA/B Locally Advanced NSCLC - Schreiner, Waldemar; Dudek, Wojciech; Rieker, Ralf; Lettmaier, Sebastian; Fietkau, Rainer; Sirbu, Horia (Thoracic and Cardiovascular Surgeon, 2019)
BACKGROUND: Major pathologic response (MPR) determines favorable outcome in locally advanced non-small cell lung cancer after induction therapy (IT) followed by lung resection. The aim of this retrospective study was to identify the prognostic relevance of MPR in long-term interval. METHODS: In 55 patients, the survival rate according to MPR and non-MPR was estimated by Kaplan-Meier method and compared using log-rank, Breslow, and Tarone-Ware tests. RESULTS: The IT included chemoradiation with 50.4 Gy (range: 45-56.4 Gy) combined with platinum-based chemotherapy in 52 patients (94.5%) and platinum-based chemotherapy in 3 patients (5.5%). Perioperative morbidity and 30-day mortality were 36 and 3.6%, respectively. The estimated 5-year postoperative and progressive-free survivals were statistically significantly improved in MPR versus non-MPR with 53.5 versus 18% and 49.4 versus 18.5%, respectively. According to the log-rank, Breslow, and Tarone-Ware tests, the MPR demonstrates prognostic significance in early, long-term, and whole postoperative interval. CONCLUSION: MPR is associated with a robust correlation to long-term postoperative and recurrence-free survival improvement, and can potentially simplify the multidisciplinary debate and allow further stratification of adjuvant treatment in multimodality therapy.
EVALuna2:207414

Management of advanced hypopharyngeal and laryngeal cancer with and without cartilage invasion - Scherl, Claudia; Mantsopoulos, Konstantinos; Semrau, Sabine; Fietkau, Rainer; Kapsreiter, Markus; Koch, Michael; Traxdorf, Maximilian; Grundtner, Philipp; Iro, Heinrich (Auris Nasus Larynx, 2016)
To compare efficacy, in terms of disease control/survival in advanced hypopharyngeal and laryngeal lesions, according to treatment strategy (primary surgery, PS or primary chemoradiotherapy, CRT) and invasion pattern (cartilage, CAI or soft tissue involvement, STI).Records from 463 patients with T3 and T4a carcinoma with CAI (n=221) or STI (n=242) treated at a university clinic over 18 years were retrospectively reviewed.Disease-specific survival (DSS) for the CAI group was 70.1% (PS) and 38.4% (CRT), and 76.6% and 46% for the STI group, respectively. Overall survival (OS) for STI was 56.4% (PS) and 30.6% (CRT), and for CAI 51.1% (PS) and 28.5% (CRT) respectively. Positive resection margins and regional neck metastases reduced survival. T3 lesions treated non-operatively still had significantly improved survival versus T4a by >20%.Surgery remains an indispensable part of treatment in local advanced hypopharyngeal and laryngeal cancer with high survival results. It should be part of a concept that includes adjuvant (C)RT. For T3 lesions, primary CRT is also acceptable and CAI is not a contraindication for primary CRT. Regional disease is a strong prognostic factor. In spite of adjuvant treatment, DSS deteriorates by about 20% in cases with positive resection margins.
EVALuna2:18360

Management of organ motion in scanned ion beam therapy - Bert, Christoph; Herfarth, Klaus (Radiation Oncology, 2017)
Scanned ion beam therapy has special demands for treatment of intra-fractionally moving tumors such as lesions in lung or liver. Interplay effects between beam and organ motion can in those settings lead to under-dosage of the target volume. Dedicated treatment techniques such as gating or abdominal compression are required. In addition 4D treatment planning should be used to determine strategies for patient specific treatment planning such as an increased beam focus or the use of internal target volumes incorporating range changes.Several work packages of the Clinical Research Units 214 and 214/2 funded by the German Research Council investigated the management of organ motion in scanned ion beam therapy. A focus was laid on 4D treatment planning using TRiP4D and the development of motion mitigation strategies including their quality assurance. This review focuses on the activity in the second funding period covering adaptive treatment planning strategies, 4D treatment plan optimization, and the application of motion management in pre-clinical research on radiation therapy of cardiac arrhythmias.
EVALuna2:33030

Measures of infection prevention and incidence of SARS-CoV-2 infections in cancer patients undergoing radiotherapy in Germany, Austria and Switzerland - Matuschek, Christiane; Fischer, Johannes C.; Combs, Stephanie E.; Fietkau, Rainer; Corradini, Stefanie; Zaenker, Kurt; Boelke, Edwin; Djiepmo-Njanang, Freddy-Joel; Tamaskovics, Bálint; Fischer, Joachim E.; Stuschke, Martin; Poettgen, Christoph; et al. (Strahlentherapie und Onkologie, 2020)
Purpose: COVID-19 infection has manifested as a major threat to both patients and healthcare providers around the world. Radiation oncology institutions (ROI) deliver a major component of cancer treatment, with protocols that might span over several weeks, with the result of increasing susceptibility to COVID-19 infection and presenting with a more severe clinical course when compared with the general population. The aim of this manuscript is to investigate the impact of ROI protocols and performance on daily practice in the high-risk cancer patients during this pandemic. Methods: We addressed the incidence of positive COVID-19 cases in both patients and health care workers (HCW), in addition to the protective measures adopted in ROIs in Germany, Austria and Switzerland using a specific questionnaire. Results: The results of the questionnaire showed that a noteworthy number of ROIs were able to complete treatment in SARS-CoV‑2 positive cancer patients, with only a short interruption. The ROIs reported a significant decrease in patient volume that was not impacted by the circumambient disease incidence, the type of ROI or the occurrence of positive cases. Of the ROIs 16.5% also reported infected HCWs. About half of the ROIs (50.5%) adopted a screening program for patients whereas only 23.3% also screened their HCWs. The range of protective measures included the creation of working groups, instituting home office work and protection with face masks. Regarding the therapeutic options offered, curative procedures were performed with either unchanged or moderately decreased schedules, whereas palliative or benign radiotherapy procedures were more often shortened. Most ROIs postponed or cancelled radiation treatment for benign indications (88.1%). The occurrence of SARS-CoV‑2 infections did not affect the treatment options for curative procedures. Non-university-based ROIs seemed to be more willing to change their treatment options for curative and palliative cases than university-based ROIs. Conclusion: Most ROIs reported a deep impact of SARS-CoV‑2 infections on their work routine. Modification and prioritization of treatment regimens and the application of protective measures preserved a well-functioning radiation oncology service and patient care.
CRIS-Team Scopus Importer:2020-09-25
Keywords: COVID-19; Oncology; Pandemic; Patient care; Radiation oncoloy

Mechanism of necrotic Cell Clearance by non-professional Phagocytes - Hofmann, Andrea; Seeberg, J.; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36484

Medication safety in patients treated with new oral antitumor agents: A prospective, randomized investigation on the impact of intensified clinical pharmaceutical/clinical pharmacological care on patient safety, patient knowledge and patient well-being (AMBORA). Supported by the German Cancer Aid within the Comprehensive Cancer Center Erlangen-EMN - Schlichtig, Katja; Lechner, P.; Grafe, Carolin; Ferstl, B.; Fuchs, F.; Hein, Alexander; Meidenbauer, N.; Sell, C.; Semrau, S.; Pavel, Marianne Ellen; Wullich, Bernd; Neurath, Markus; et al. (2018)
EVALuna2:33795

Metabolic Response of Short-term Induction Chemotherapy (IC) for Therapy Selection as well as Prediction of long-term local and systemic Therapy Success for Head and Neck cancer. The Results of 100 Patients - Semrau, S.; Haderlein, Marlen; Schmidt, Daniela; Waldfahrer, F.; Scherl, C.; Lettmaier, S.; Kuwert, Torsten; Iro, Heinrich; Fietkau, Rainer (2017)
EVALuna2:32895

Method for a motion model based automated 4D dose calculation - Ziegler, Marc; Brandt, Tobias; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Physics in Medicine and Biology, 2019)
The Vero system can treat intra-fractionally moving tumors with gimbaled dynamic tumor tracking (DTT) by rotating the treatment beam so that it follows the motion of the tumor. However, the changes in the beam geometry and the constant breathing motion of the patient influence the dose applied to the patient. This study aims to perform a full 4D dose reconstruction for thirteen patients treated with DTT at the Vero system at the Universitätsklinikum Erlangen and investigates the temporal resolution required to perform an accurate 4D dose reconstruction. For all patients, a 4DCT was used to train a 4D motion model, which is able to calculate pseudo-CT images for arbitrary breathing phases. A new CT image was calculated for every 100 ms of treatment and a dose calculation was performed according to the current beam geometry (i.e. the rotation of the treatment beam at this moment in time) by rotating according to the momentary beam rotation, which is extracted from log-files. The resulting dose distributions were accumulated on the planning CT and characteristic parameters were extracted and compared. [Formula: see text]-evaluations of dose accumulations with different spatial-temporal resolutions were performed to determine the minimal required resolution. In total 173 700 dose calculations were performed. The accumulated 4D dose distributions show a reduced mean GTV dose of 0.77% compared to the static treatment plan. For some patients larger deviations were observed, especially in the presence of a poor 4DCT quality. The [Formula: see text]-evaluation showed that a temporal resolution of 500 ms is sufficient for an accurate dose reconstruction. If the tumor motion is regarded as well, a spatial-temporal sampling of 1400 ms and 2 mm yields accurate results, which reduces the workload by 84%.
CRIS-Team Scopus Importer:2019-11-26

Micropapillary morphology is an indicator of poor prognosis in patients with urothelial carcinoma treated with transurethral resection and radiochemotherapy - Bertz, Simone; Wach, S.; Taubert, Helge; Merten, Ricarda; Krause, F. S.; Schick, S.; Ott, O. J.; Weigert, E.; Dworak, O.; Roedel, C.; Fietkau, Rainer; Wullich, Bernd; et al. (Virchows Archiv, 2016)
Purpose of this study was to evaluate prognostic impact of rare variants of urothelial bladder cancer (BC) after treatment with combined radiochemotherapy (RCT). To this end tumour tissue of 238 patients with urothelial carcinoma (UC) treated with transurethral resection of the bladder (TUR-B) and RCT with curative intent was collected. Histomorphological analysis included re-evaluation and semi-quantitative assessment of rare UC subtypes. Additionally, human epidermal growth factor receptor 2 (HER2) chromogenic in situ hybridisation (CISH) was performed in tumours with a micropapillary component exceeding 30 %. Long-term follow-up was available for 200 patients (range 3-282 months). Variant UC histology was found in 45 of 238 tumours, most frequently micropapillary UC (N = 17) including cases with a small fraction of tumour with micropapillary morphology. The mere presence of micropapillary morphology did not affect prognosis. In tumours with extensive (>=30 %) micropapillary morphology (N = 8) Kaplan-Meier analysis revealed significantly worse cancer specific survival (CSS) (P = 0.002) compared to conventional UC (mean survival times 97 months and 229 months, respectively). Univariate Cox regression analysis of cases with >=30 % micropapillary morphology revealed a hazard ratio of 4.726 (95 % CI 1.629-13.714) for CSS (P = 0.004). CISH revealed HER2 gene amplification in 3/10 tumours with >=30 % micropapillary component. In conclusion, for BC treated with TUR-B and RCT, the presence of micropapillary morphology in more than 30 % of the tumour is an adverse prognostic factor. Further studies are needed to evaluate a potential benefit of different, especially multimodal treatment strategies for micropapillary UC and also other subtypes of UC. Her2 represents a promising therapeutic target in a subset of micropapillary UC.
EVALuna2:6800

Minutes of the General Meeting of the German Society for Medical Physics e.V. 2019 - Ladd, Mark E.; Bert, Christoph (Zeitschrift für Medizinische Physik, 2019)
EVALuna2:213674

Moderate hypofractionation remains the standard of care for whole-breast radiotherapy in breast cancer: Considerations regarding FAST and FAST-Forward - Krug, David; Baumann, René; Combs, Stephanie E.; Duma, Marciana Nona; Dunst, Jürgen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Hehr, Thomas; Piroth, Marc D.; Sedlmayer, Felix; et al. (Strahlentherapie und Onkologie, 2021)
Moderate hypofractionation is the standard of care for adjuvant whole-breast radiotherapy after breast-conserving surgery for breast cancer. Recently, 10-year results from the FAST and 5‑year results from the FAST-Forward trial evaluating adjuvant whole-breast radiotherapy in 5 fractions over 5 weeks or 1 week have been published. This article summarizes recent data for moderate hypofractionation and results from the FAST and FAST-Forward trial on ultra-hypofractionation. While the FAST trial was not powered for comparison of local recurrence rates, FAST-Forward demonstrated non-inferiority for two ultra-hypofractionated regimens in terms of local control. In both trials, the higher-dose experimental arms resulted in elevated rates of late toxicity. For the lower dose experimental arms of 28.5 Gy over 5 weeks and 26 Gy over 1 week, moderate or marked late effects were similar in the majority of documented items compared to the respective standard arms, but significantly worse in some subdomains. The difference between the standard arm and the 26 Gy of the FAST-Forward trial concerning moderate or marked late effects increased with longer follow-up in disadvantage of the experimental arm for most items. For now, moderate hypofractionation with 40–42.5 Gy over 15–16 fractions remains the standard of care for the majority of patients with breast cancer who undergo whole-breast radiotherapy without regional nodal irradiation after breast-conserving surgery.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Breast cancer; Hypofractionation; Late toxicity; Local recurrence; Radiotherapy

Modern Radiotherapy Concepts and the Impact of Radiation on Immune Activation - Derer, Anja; Hartmann, Josefin; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (Frontiers in Oncology, 2016)
Even though there is extensive research carried out in radiation oncology, most of the clinical studies focus on the effects of radiation on the local tumor tissue and deal with normal tissue side effects. The influence of dose fractionation and timing particularly with regard to immune activation is not satisfactorily investigated so far. This review, therefore, summarizes current knowledge on concepts of modern radiotherapy (RT) and evaluates the potential of RT for immune activation. Focus is set on radiation-induced forms of tumor cell death and consecutively the immunogenicity of the tumor cells. The so-called non-targeted, abscopal effects can contribute to anti-tumor responses in a specific and systemic manner and possess the ability to target relapsing tumor cells as well as metastases. The impact of distinct RT concepts on immune activation is outlined and pre-clinical evidence and clinical observations on RT-induced immunity will be discussed. Knowledge on the radiosensitivity of immune cells as well as clinical evidence for enhanced immunity after RT will be considered. While stereotactic ablative body radiotherapy seem to have a beneficial outcome over classical RT fractionation in pre-clinical animal models, in vitro model systems suggest an advantage for classical fractionated RT for immune activation. Furthermore, the optimal approach may differ based on the tumor site and/or genetic signature. These facts highlight that clinical trials are urgently needed to identify whether high-dose RT is superior to induce anti-tumor immune responses compared to classical fractionated RT and in particular how the outcome is when RT is combined with immunotherapy in selected tumor entities.
EVALuna2:18361

Modulation of the peripheral immune system after low-dose radon spa therapy: Detailed longitudinal immune monitoring of patients within the RAD-ON01 study - Rühle, Paul-Friedrich; Wunderlich, Roland; Fournier, Claudia; Maier, Andreas; Klein, Gerhart; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Deloch, Lisa (Autoimmunity, 2017)
The pain-relieving effects of low-dose radon therapies on patients suffering from chronic painful inflammatory diseases have been described for centuries. Even though it has been suggested that low doses of radiation may attenuate chronic inflammation, the underlying mechanisms remain elusive. Thus, the RAD-ON01 study was initiated to examine the effects of radon spa therapy and its low doses of alpha radiation on the human immune system. In addition to an evaluation of pain parameters, blood was drawn from 100 patients suffering from chronic painful degenerative musculoskeletal diseases before as well as 6, 12, 18, and 30 weeks after the start of therapy. We verified significant long-term pain reduction for the majority of patients which was accompanied by modulations of the peripheral immune cells. Detailed immune monitoring was performed using a multicolor flow cytometry-based whole blood assay. After therapy, the major immune cells were only marginally affected. Nevertheless, a small but long-lasting increase in T cells and monocytes was observed. Moreover, neutrophils, eosinophils and, in particular, dendritic cells were temporarily modulated after therapy. Regarding the immune cell subsets, cytotoxic T and NK cells, in particular, were altered. However, the most prominent effects were identified in a strong reduction of the activation marker CD69 on T, B, and NK cells. Simultaneously, the percentage of HLA-DR+T cells was elevated after therapy. The RAD-ON01 study showed for the first time a modulation of the peripheral immune cells following standard radon spa therapy. These modulations are in line with attenuation of inflammation.
EVALuna2:32908

Modulations in the Peripheral Immune System of Glioblastoma Patient Is Connected to Therapy and Tumor Progression-A Case Report from the IMMO-GLIO-01 Trial - Rühle, Paul-Friedrich; Goerig, Nicole; Wunderlich, Roland; Fietkau, Rainer; Gaipl, Udo; Strnad, Annedore; Frey, Benjamin (Frontiers in Neurology, 2017)
Immune responses are important for efficient tumor elimination, also in immune privileged organs such as the brain. Fostering antitumor immunity has therefore become an important challenge in cancer therapy. This cannot only be achieved by immunotherapies as already standard treatments such as radiotherapy and chemotherapy modify the immune system. Consequently, the understanding of how the tumor, the tumor microenvironment, and immune system are modulated by cancer therapy is required for prognosis, prediction, and therapy adaption. The prospective, explorative, and observational IMMO-GLIO-01 trial was initiated to examine the detailed immune status and its modulation of about 50 patients suffering from primary glioblastoma multiforme (GBM) or anaplastic astrocytoma during standard therapy. Prior to the study, a flow cytometry-based assay was established allowing the analysis of 34 immune cell subsets and their activation state. Here, we present the case of the first and longest accompanied patient, a 53-year-old woman suffering from GBM in the front left lobe. In context of tumor progression and therapy, we describe the modulation of the peripheral immune status over 17 months. Distinct immune modulations that were connected to therapy response or tumor progression were identified.Inter alia, a shift of CD4:CD8 ratio was observed that correlated with tumor progression. Twice we observed a unique composition of peripheral immune cells that correlated with tumor progression. Thus, following up these immune modulations in a closely-meshed manner is of high prognostic and predictive relevance for supporting personalized therapy and increasing therapy success.Clinical Trial registration: ClinicalTrials.gov, identifier NCT02022384 (registered retrospectively on 13th of December, 2013).
EVALuna2:32874

MRI-Based Treatment of Rectal Cancer: Is Prognostication of the Recurrence Risk Solid Enough to Render Radiation Redundant? - Sautter-Bihl, Marie-Luise; Hohenberger, Werner; Fietkau, Rainer; Roedel, Claus; Schmidberger, Heinz; Sauer, Rolf (Annals of Surgical Oncology, 2014)
Most current guidelines recommend neoadjuvant short course radiotherapy (sRT) or radio-chemotherapy (nRCT) for rectal cancer stage II and III. After the introduction of total mesorectal excision (TME) and magnetic resonance imaging (MRI), this proceeding has been questioned and omission of neoadjuvant treatment according to preoperative MRI-criteria has been propagated. Aim of the present paper is to review the state of evidence regarding MRI-based treatment decision depending on the predicted width of the circumferential resection margin (CRM).A comprehensive survey of the literature was performed using the search terms "rectal cancer", "radiotherapy", "radio-chemotherapy", "MRI-based therapy", "circumferential resection margin". Data from lately published observational studies were compared to results from randomized trials and outcome analyses of the Norwegian national cancer registry.Only one observational study using MRI-based treatment according to the anticipated CRM provided 5 year local recurrence data, however only for 65 patients. The second study did not yet evaluate recurrence rates. Two randomized trials comparing sRT to primary TME showed significantly worse outcome for non-irradiated patients. Data from the Norwegian rectal cancer registry demonstrate that TME alone is associated with higher LRR than achievable with preoperative RT.Current evidence does not support the omission of neoadjuvant treatment for stage II-III rectal cancer on the basis of an MRI-predicted negative CRM. Randomized studies are warranted to clarify whether and for which subgroups TME alone is safe in terms of local recurrences.
EVALuna2:15138

Multicenter clinical trial on functional evaluation of transoral laser microsurgery for supraglottic laryngeal carcinomas - Ambrosch, Petra; Fazel, Asita; Dietz, Andreas; Fietkau, Rainer; Tostmann, Ralf; Borzikowsky, Christoph (Laryngo-Rhino-Otologie, 2024)
Background Transoral laser microsurgery (TLM) is an accepted and effective treatment strategy for supraglottic carcinomas. Data on oncologic and to a lesser extent functional outcomes have been published by mainly European specialized single institutions. TLM for supraglottic carcinomas has never been tested in a multicenter trial on its applicability as surgical standard at every hospital. Objectives To test the efficacy of TLM supraglottic laryngectomy (TLM-SGL) in terms of swallowing function, oncologic outcome parameters, morbidity, complications of treatment, and quality of life in a multicenter setting. Methods The study is designed as a multicenter (approximately 25 centers), non-randomized, single-arm study with a targeted number of 200 previously untreated patients with squamous cell carcinomas (SCC) of the supraglottic larynx T2/T3 N0-3 M0; UICC stage II-IVa. The surgical treatment consists of TLM-SGL and elective or therapeutic uni- or bilateral selective neck dissection (SND). After pathologic risk stratification adjuvant radio- (RT) or radiochemotherapy (RCT) is indicated. Patients are followed-up for 2 years post surgically. Swallowing function is assessed by fibreoptic endoscopic evaluation of swallowing (FEES). The primary endpoint is aspiration-free swallowing at 12 months as established using FEES and defined as grade < 6 of penetration-aspiration scale (PAS). Secondary endpoints include local control, larynx preservation, overall and disease-free survival, complications and side effects of treatment, prevalence of tracheostomy and percutaneous endoscopic gastrostomy (PEG)-tube-feeding, and dysphagia-specific quality of life (QoL) assessed by the MD Anderson Dysphagia Inventory (MDADI) as well as voice-related QoL assessed by the Voice Handicap Index (VHI).
CRIS-Team Scopus Importer:2024-07-05
Keywords: FEES; functional outcomes; health service research; larynx preservation; Multicenter clinical trial; oncologic outcomes; supraglottic laryngeal carcinoma; transoral laser microsurgery

Multicenter privacy-preserving model training for deep learning brain metastases autosegmentation - Huang, Yixing; Khodabakhshi, Zahra; Gomaa, Ahmed; Schmidt, Manuel; Fietkau, Rainer; Guckenberger, Matthias; Andratschke, Nicolaus; Bert, Christoph; Tanadini-Lang, Stephanie; Putz, Florian (Radiotherapy and Oncology, 2024)
Keywords: Continual learning; Learning without forgetting; Brain metastasis; Multicenter collaboration; Data privacy; Data heterogeneity

Multicenter quality assurance evaluation of MR-guided deep hyperthermia systems - Curto, S.; Mulder, T.; Aklan, B.; Mils, O.; Schmidt, Manfred; Lamprecht, U.; Peller, M.; Wessalowski, R.; Lindern, L.; Fietkau, Rainer; Zips, D.; Paulides, M.; et al. (2018)
EVALuna2:36512

Multigating, a 4D optimized beam tracking in scanned ion beam therapy - Graeff, Christian; Constantinescu, Anna; Luechtenborg, Robert; Durante, Marco; Bert, Christoph (Technology in Cancer Research & Treatment, 2014)
The treatment of moving tumors with a scanned ion beam is challenging due to interplay effects and changing beam range. We propose multigating, as a method for 4D-treatment optimization and delivery. In 3D beam tracking, tracking vectors are added during delivery to beam spot positions based on the detected motion phase. This has the disadvantage of dose errors in case of complex motion patterns and an uncertain out-of-target dose distribution. In multigating, the motion phase for each beam spot is predefined, which allows to add the tracking vector prior to beam weight optimization on all motion phases. The synchronization of delivery and target motion is assured by fast gating. The feasibility of the delivery was shown in a film experiment and required only minor software modification to the treatment planning system. In a treatment planning study in 4 lung cancer patients, target coverage could be restored to the level of a static reference plan by multigating (V95 > 99%) but not by standard beam tracking (V95 < 95%). The conformity of the multigating plans was only slightly lower than those of the static plan, with a conformity number of 72.0% (median, range 64.6-76.6%) compared to 75.8% (70.8-81.5%) in spite of target motion of up to 22 mm. In conclusion, we showed the technical feasibility of multigating, a 4D-optimization and delivery method using scanned beams that allows for conformal and homogeneous dose delivery to moving targets also in case of complex motion.
EVALuna2:18193

NAR score as surrogate for disease-free survival in the CAO/ARO/AIO-04 phase 3 rectal cancer trial - Fokas, E.; Fietkau, Rainer; Hartmann, Arndt; Hohenberger, Werner; Grützmann, Robert; Ghadimi, M.; Liersch, T.; Stroebel, P.; Grabenbauer, G.; Wittekind, C.; Sauer, Rolf; Kaufmann, M.; et al. (2018)
EVALuna2:36513

Neoadjuvant chemoradiation combined with regional hyperthermia in locally advanced or recurrent rectal cancer - Ott, Oliver; Gani, Cihan; Lindner, Lars H.; Schmidt, Manfred; Lamprecht, Ulf; Abdel-Rahman, Sultan; Hinke, Axel; Weissmann, Thomas; Hartmann, Arndt; Issels, Rolf D.; Zips, Daniel; Belka, Claus; et al. (Cancers, 2021)
Background: To prospectively analyze feasibility and pathological complete response (pCR) rates of neoadjuvant chemoradiotherapy combined with regional hyperthermia (RHT) in patients with locally advanced (LARC) or recurrent (LRRC) rectal cancer. Methods: between 2012 and 2018, 111 patients with UICC stage IIB-IV or any locally recurrent rectal cancer were included (HyRec-Trial, ClinicalTrials.gov Identifier: NCT01716949). Patients received radiotherapy with concurrent 5-Fluororuracil (5-FU)/Capecitabine and Oxaliplatin, and RHT. Stage 1 feasibility analysis evaluated dose-limiting toxicities (DLT) after 19 patients, stage 2 after 59 evaluable patients. Analysis of the pCR rate was based on histopathological reports. Results: the feasibility rates for stages 1 and 2 were 90% (17/19) and 73% (43/59), respectively. In the intention-to-treat population the pCR rate was 19% (20/105; 90% confidence interval (CI) 13.0–26.5). In the per-protocol-analysis, complete tumor regression was seen in 28% (18/64) and 38% (3/8) of the patients with LARC and LRRC, respectively. Complete resection rates (R0) among patients with LARC and LRRC who received surgery were 99% (78/84) and 67% (8/12). Conclusions: the intensified neoadjuvant and multimodality treatment schedule was feasible and led to comparable early toxicity rates as described by other trials that used the similar chemoradiation protocol. The presented treatment regimen resulted in a very high pCR rate and appears as a promising option for patients with LRRC.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Complete remission rate; Concurrent chemoradiation; Locally advanced rectal cancer; Locally recurrent rectal cancer; Regional hyperthermia; Tumor regression grading

Neoadjuvant chemoradiation therapy with gemcitabine/cisplatin and surgery versus immediate surgery in resectable pancreatic cancer : Results of the first prospective randomized phase II trial - Golcher, Henriette; Brunner, Thomas; Witzigmann, Helmut; Marti, Lukas; Bechstein, Wolf-Otto; Bruns, Christiane; Jungnickel, Henry; Schreiber, Stefan; Grabenbauer, Gerhard; Meyer, Thomas; Merkel, Susanne; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2015)
In nonrandomized trials, neoadjuvant treatment was reported to prolong survival in patients with pancreatic cancer. As neoadjuvant chemoradiation is established for the treatment of rectal cancer we examined the value of neoadjuvant chemoradiotherapy in pancreatic cancer in a randomized phase II trial. Radiological staging defining resectability was basic information prior to randomization in contrast to adjuvant therapy trials resting on pathological staging.Patients with resectable adenocarcinoma of the pancreatic head were randomized to primary surgery (Arm A) or neoadjuvant chemoradiotherapy followed by surgery (Arm B), which was followed by adjuvant chemotherapy in both arms. A total of 254 patients were required to detect a 4.33-month improvement in median overall survival (mOS).The trial was stopped after 73 patients; 66 patients were eligible for analysis. Twenty nine of 33 allocated patients received chemoradiotherapy. Radiotherapy was completed in all patients. Chemotherapy was changed in 3 patients due to toxicity. Tumor resection was performed in 23 vs. 19 patients (A vs. B). The R0 resection rate was 48 % (A) and 52 % (B, P = 0.81) and (y)pN0 was 30 % (A) vs. 39 % (B, P = 0.44), respectively. Postoperative complications were comparable in both groups. mOS was 14.4 vs. 17.4 months (A vs. B; intention-to-treat analysis; P = 0.96). After tumor resection, mOS was 18.9 vs. 25.0 months (A vs. B; P = 0.79).This worldwide first randomized trial for neoadjuvant chemoradiotherapy in pancreatic cancer showed that neoadjuvant chemoradiation is safe with respect to toxicity, perioperative morbidity, and mortality. Nevertheless, the trial was terminated early due to slow recruiting and the results were not significant. ISRCTN78805636; NCT00335543.
EVALuna2:15177

Neoadjuvant chemotherapy for breast cancer-background for the indication of locoregional treatment - Krug, David; Baumann, Rene; Budach, Wilfried; Dunst, Juergen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Hehr, Thomas; Piroth, Marc D.; Sedlmayer, Felix; Souchon, Rainer; et al. (Strahlentherapie und Onkologie, 2018)
Neoadjuvant chemotherapy (NACT) has been widely adopted into the multidisciplinary management of breast cancer. The prognostic impact of treatment response has been clearly demonstrated. However, the impact of treatment response on the indication for adjuvant radiotherapy is unclear. This review summarizes important implications of NACT and treatment response on the risk of recurrence and locoregional multidisciplinary management from the standpoint of radiation oncology.
EVALuna2:36457

Neoadjuvant concurrent chemoradiotherapy with and without hyperthermia in retroperitoneal sarcomas: feasibility, efficacy, toxicity, and long-term outcome - Willner, Alexander; Fechner, Katja; Agaimy, Abbas; Haller, Florian; Eckstein, Markus; Ott, Oliver; Putz, Florian; Gaipl, Udo; Kersting, S.; Meidenbauer, Norbert; Grützmann, Robert; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2021)
Purpose Retroperitoneal (RPS) sarcomas are associated with poor local and abdominal tumor control. However, the benefit of preoperative radio- or chemotherapy alone for these entities is currently unclear. Moreover, as intermediate- and high-grade sarcomas have a tendency toward early metastasis, exploration of neoadjuvant strategies is of high importance. This analysis reports the results of our 20-year single-institution experience with preoperative neoadjuvant concurrent chemoradiation. Methods From 2000-2019, 27 patients with intermediate- or high-grade RPS (12 dedifferentiated liposarcoma, 10 leiomyosarcoma, 5 others) were treated with radiotherapy (median dose: 50.4 Gy; range 45-75 Gy) and two cycles of chemotherapy (doxorubicin 50 mg/m(2) BSA/d3 q28 and ifosfamide 1.5 g/m(2) BSA/d1-5 q28) in neoadjuvant intent. Chemotherapy consisted of doxorubicin alone in two cases and ifosfamide alone in one case. Fifteen patients (56%) additionally received deep regional hyperthermia. Results The median follow-up time was 53 months (+/- 56.7 months). 92% of patients received two cycles of chemotherapy as planned and 92% underwent surgery. At 5 and 10 years, abdominal-recurrence-free survival was 74.6% (+/- 10.1%) and 66.3% (+/- 11.9%), distant metastasis-free survival was 67.2% (+/- 9.7%) and 59.7% (+/- 11.1%), and overall survival was 60.3% (+/- 10.5%) and 60.3% (+/- 10.5%), respectively. CTC grade III and IV toxicities were leukocytopenia (85%), thrombocytopenia (33%), and anemia (11%). There were no treatment-related deaths. Conclusion Neoadjuvant chemoradiotherapy with and without hyperthermia for retroperitoneal sarcomas is feasible and provided high local control of intermediate- and high-grade sarcoma.
CRIS-Team WoS Importer:2021-11-12

Neoadjuvant Radiochemotherapy Followed by Curative Resection in Patients with Advanced Non-Small Cell Lung Cancer in Stage IIIA/IIIB: Prognostic Factors and Results - Schreiner, Waldemar; Dudek, Wojciech; Lettmaier, S.; Gavrychenkova, S.; Rieker, R.; Fietkau, Rainer; Sirbu, Horia (Zentralblatt für Chirurgie, 2016)
The role of surgical lung resection following neo-adjuvant radio-chemotherapy (RCT) in patients with locally advanced non-small cell lung cancer (NSCLC) is yet not clearly defined. The aim of our study was to analyze the postoperative survival and to identify relevant prognostic factors. 46 patients underwent curative resections after neo-adjuvant RCT for locally advanced NSCLC (IIIA/IIIB) between February 2008 and February 2015. A retrospective data analysis regarding preoperative regression status, perioperative mortality, postoperative survival, patho-histological remission, relapse pattern and other prognostic factors was performed. A neo-adjuvant RCT with a median radiation dose of 50.4 [range, 45-60] Gy was performed in 44 (96 %) patients. Partial and/or complete regression was observed in 32 (70 %) patients. R0-resection was achieved in 44 (96 %) patients. The 30-day mortality was 4 % and the perioperative morbidity was 37 %. The overall and progression free 5-year survival rate was 47 % and respectively 45 % [in median 58 months]. The 5-year survival rate of 64 % in the "responder"-group was significantly better when compared with 24 % in the "non-responder"-group (p = 0.038). The tri-modality therapy improved the prognosis in patients with locally advanced NSCLC (stage IIIA/IIIB). The complete patho-histological remission is an important prognostic factor for better long term survival. Dividing the patients in "responder" and "non-responder" after neo-adjuvant RCT may have large therapeutically consequences in the future.
EVALuna2:6809

Neoadjuvant rectal score as individual-level surrogate for disease-free survival in rectal cancer in the CAO/ARO/AIO-04 randomized phase III trial - Fokas, E.; Fietkau, Rainer; Hartmann, Arndt; Hohenberger, Werner; Grützmann, Robert; Ghadimi, M.; Liersch, T.; Stroebel, P.; Grabenbauer, G. G.; Graeven, U.; Hofheinz, R-D; Koehne, C-H; et al. (Annals of Oncology, 2018)
Background: Surrogate end points in rectal cancer after preoperative chemoradiation are lacking as their statistical validation poses major challenges, including confirmation based on large phase III trials. We examined the prognostic role and individual-level surrogacy of neoadjuvant rectal (NAR) score that incorporates weighted cT, ypT and ypN categories for disease-free survival (DFS) in 1191 patients with rectal carcinoma treated within the CAO/ARO/AIO-04 phase III trial. Patients and methods: Cox regression models adjusted for treatment arm, resection status, and NAR score were used in multivariable analysis. The four Prentice criteria (PC1-4) were used to assess individual-level surrogacy of NAR for DFS. Results: After a median follow-up of 50 months, the addition of oxaliplatin to fluorouracil-based chemoradiotherapy (CRT) significantly improved 3-year DFS [75.9% (95% confidence interval [CI] 72.30% to 79.50%) versus 71.3% (95% CI 67.60% to 74.90%); P = 0.034; PC 1) and resulted in a shift toward lower NAR groups (P = 0.034, PC 2) compared with fluorouracil-only CRT. The 3-year DFS was 91.7% (95% CI 88.2% to 95.2%), 81.8% (95% CI 78.4% to 85.1%), and 58.1% (95% CI 52.4% to 63.9%) for low, intermediate, and high NAR score, respectively (P < 0.001; PC 3). NAR score remained an independent prognostic factor for DFS [low versus high NAR: hazard ratio (HR) 4.670; 95% CI 3.106-7.020; P < 0.001; low versus intermediate NAR: HR 1.971; 95% CI 1.303-2.98; P = 0.001] in multivariable analysis. Notwithstanding the inherent methodological difficulty in interpretation of PC 4 to establish surrogacy, the treatment effect on DFS was captured by NAR, supporting satisfaction of individual-level PC 4. Conclusion: Our study validates the prognostic role and individual-level surrogacy of NAR score for DFS within a large randomized phase III trial. NAR score could help oncologists to speed up response-adapted therapeutic decision, and further large phase III trial data sets should aim to confirm trial-level surrogacy.
EVALuna2:34609

Neoadjuvant short-course radiotherapy followed by chemotherapy or simultaneous radiochemotherapy for local unresectable rectal cancer - Klautke, G.; Sauer, Rolf (Strahlentherapie und Onkologie, 2014)
EVALuna2:18203

Neoadjuvant Therapy for Resectable Pancreatic Cancer A New Standard of Care. Pooled Data From 3 Randomized Controlled Trials - Birrer, Dominique L.; Golcher, Henriette; Casadei, Riccardo; Haile, Sarah R.; Fritsch, Ralph; Hussung, Saskia; Brunner, Thomas B.; Fietkau, Rainer; Meyer, Thomas; Grützmann, Robert; Merkel, Susanne; Ricci, Claudio; et al. (Annals of Surgery, 2021)
Objective: The aim of this study was to pool data from randomized controlled trials (RCT) limited to resectable pancreatic ductal adenocarcinoma (PDAC) to determine whether a neoadjuvant therapy impacts on disease-free survival (DFS) and surgical outcome. Summary Background Data: Few underpowered studies have suggested benefits from neoadjuvant chemo (+/- radiation) for strictly resectable PDAC without offering conclusive recommendations. Methods: Three RCTs were identified comparing neoadjuvant chemo (+/- radio) therapy vs. upfront surgery followed by adjuvant therapy in all cases. Data were pooled targeting DFS as primary endpoint, whereas overall survival (OS), postoperative morbidity, and mortality were investigated as secondary endpoints. Survival endpoints DFS and OS were compared using Cox proportional hazards regression with study-specific baseline hazards. Results: A total of 130 patients were randomized (56 in the neoadjuvant and 74 in the control group). DFS was significantly longer in the neoadjuvant treatment group compared to surgery only [hazard ratio (HR) 0.6, 95% confidence interval (CI) 0.4-0.9] (P = 0.01). Furthermore, DFS for the subgroup of R0 resections was similarly longer in the neoadjuvant treated group (HR 0.6, 95% CI 0.35-0.9, P = 0.045). Although postoperative complications (Comprehensive Complication Index, CCI(R)) occurred less frequently (P = 0.008), patients after neoadjuvant therapy experienced a higher toxicity, but without negative impact on oncological or surgical outcome parameters. Conclusion: Neoadjuvant therapy can be offered as an acceptable standard of care for patients with purely resectable PDAC. Future research with the advances of precision oncology should now focus on the definition of the optimal regimen.
CRIS-Team WoS Importer:2022-02-11

Neuropilin-2 and its ligand VEGF-C predict treatment response after transurethral resection and radiochemotherapy in bladder cancer patients - Keck, Bastian; Wach, S.; Taubert, Helge; Zeiler, S.; Ott, O. J.; Kunath, F.; Hartmann, Arndt; Bertz, Simone; Weiss, C.; Hoenscheid, P.; Schellenburg, S.; Roedel, C.; et al. (International Journal of Cancer, 2015)
The standard treatment for invasive bladder cancer is radical cystectomy. In selected patients, bladder-sparing therapy can be performed by transurethral resection (TURBT) and radio-chemotherapy (RCT) or radiotherapy (RT). Our published in vitro data suggest that the Neuropilin-2 (NRP2)/VEGF-C axis plays a role in therapy resistance. Therefore, we studied the prognostic impact of NRP2 and VEGF-C in 247 bladder cancer patients (cN0M0) treated with TURBT and RCT (n = 198) or RT (n = 49) and a follow-up time up to 15 years. A tissue microarray was analyzed by immunohistochemistry. NRP2 expression emerged as a prognostic factor in overall survival (OS; HR: 3.42; 95% CI: 1.48 - 7.86; p = 0.004) and was associated with a 3.85-fold increased risk of an early cancer specific death (95% CI: 0.91 - 16.24; p = 0.066) in multivariate analyses. Cancer specific survival (CSS) dropped from 166 months to 85 months when NRP2 was highly expressed (p = 0.037). Patients with high VEGF-C expression have a 2.29-fold increased risk of shorter CSS (95% CI: 1.03-5.35; p = 0.043) in univariate analysis. CSS dropped from 170 months to 88 months in the case of high VEGF-C expression (p = 0.041). Additionally, NRP2 and VEGF-C coexpression is a prognostic marker for OS in multivariate models (HR: 7.54; 95% CI: 1.57-36.23; p = 0.012). Stratification for muscle invasiveness (T1 vs. T2-T4) confirmed the prognostic role of NRP2 and NRP2/VEGF-C co-expression in patients with T2-T4 but also with high risk T1 disease. In conclusion, immunohistochemistry for NRP2 and VEGF-C has been determined to predict therapy outcome in bladder cancer patients prior to TURBT and RCT.
EVALuna2:6641

Neutrophilia as prognostic factor for outcome in the CAO/ARO/ALO-04 phase 3 rectal cancer trial - Diefenhardt, M.; Hofheinz, R.; Beissbarth, T.; Arnold, D.; Von Den Gruen, J. Mueller; Liersch, T.; Stroebel, P.; Grabenbauer, G.; Fietkau, Rainer; Weitz, J.; Ghadimi, M.; Roedel, C.; et al. (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Neutrophils in HNSCC Can Be Associated with Both a Worse or Favorable Prognosis - Brunkhorst, Hendrik; Schnellhardt, Sören; Büttner-Herold, Maike; Daniel, Christoph; Fietkau, Rainer; Distel, Luitpold (Biomolecules, 2024)
The prognostic significance of tumor-infiltrating neutrophils in head and neck squamous cell carcinoma (HNSCC) is poorly understood. It is unclear how the presence of neutrophils affects prognosis due to their polarization into cytotoxic N1 or immunosuppressive N2. Therefore, we determined the number of CD66b+ neutrophil granulocytes separately in the stromal and epithelial compartments in cancer tissues from 397 patients with HNSCC. Tumor samples from six historical patient groups were processed into tissue microarrays and stained immunohistochemically. In total, 21.9% were HPV positive (p16+). Neutrophil counts were much lower in the stromal compartment (372 ± 812) than in the epithelial cancer compartment (1040 ± 1477) (p < 0.001), with large differences between groups. In three groups with high neutrophil infiltration, high rates were associated with a favorable prognosis, whereas in two groups, high rates were a negative prognostic factor. In p16- oropharyngeal and hypopharyngeal cancer high infiltration was associated with a favorable prognosis. Cancers with an exclusion of neutrophils in the epithelial compartment were associated with improved prognosis. In oropharyngeal and hypopharyngeal HPV-negative cancer high neutrophil infiltration rates were clearly associated with prolonged survival. Neutrophil granulocytes in HNSCC may contribute to a favorable or unfavorable prognosis.
CRIS-Team Scopus Importer:2024-03-08
Keywords: CD66b+; head and neck cancer; HNSCC; hypopharynx; larynx; neutrophils; oral cavity; oropharynx; prognosis; tumor-associated neutrophils

Neutrophils seeking new neighbors: radiotherapy affects the cellular framework and the spatial organization in a murine breast cancer model - Reichardt, Clara; Munoz Becerra, Marco; Rius Rigau, Aleix; Rückert, Michael; Fietkau, Rainer; Schett, Georg; Gaipl, Udo; Frey, Benjamin; Munoz Becerra, Luis (Cancer Immunology, Immunotherapy, 2024)
Neutrophils are known to contribute in many aspects of tumor progression and metastasis. The presence of neutrophils or neutrophil-derived mediators in the tumor microenvironment has been associated with poor prognosis in several types of solid tumors. However, the effects of classical cancer treatments such as radiation therapy on neutrophils are poorly understood. Furthermore, the cellular composition and distribution of immune cells in the tumor is of increasing interest in cancer research and new imaging technologies allow to perform more complex spatial analyses within tumor tissues. Therefore, we aim to offer novel insight into intra-tumoral formation of cellular neighborhoods and communities in murine breast cancer. To address this question, we performed image mass cytometry on tumors of the TS/A breast cancer tumor model, performed spatial neighborhood analyses of the tumor microenvironment and quantified neutrophil-extracellular trap degradation products in serum of the mice. We show that irradiation with 2 × 8 Gy significantly alters the cellular composition and spatial organization in the tumor, especially regarding neutrophils and other cells of the myeloid lineage. Locally applied radiotherapy further affects neutrophils in a systemic manner by decreasing the serum neutrophil extracellular trap concentrations which correlates positively with survival. In addition, the intercellular cohesion is maintained due to radiotherapy as shown by E-Cadherin expression. Radiotherapy, therefore, might affect the epithelial–mesenchymal plasticity in tumors and thus prevent metastasis. Our findings underscore the growing importance of the spatial organization of the tumor microenvironment, particularly with respect to radiotherapy, and provide insight into potential mechanisms by which radiotherapy affects epithelial–mesenchymal plasticity and tumor metastasis.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Cancer; Cellular neighborhood; Image mass cytometry; Neutrophil; Radiotherapy

New, mobile CBCT-System (ImagingRing m) for image-guided Brachytherapy - Quality Assurance - Karius, Andre; Strnad, Vratislav; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

NNRTI-based antiretroviral therapy may increase risk of radiation induced side effects in HIV-1-infected patients - Keller, Ulrike; Hecht, Markus; Harrer, Thomas; Harrer, Ellen; Schuster, Barbara; Fietkau, Rainer; Distel, Luitpold (Radiotherapy and Oncology, 2015)
As the incidence of cancer is rising in HIV-1-infected patients, radiotherapy is used more frequently in this patient group. Strong radiation induced side effects have been reported in single patients on antiretroviral therapy. Thus we investigated whether HIV-1 itself or antiretroviral drugs could enhance radiosensitivity in patients.Radiosensitivity after in vitro irradiation of blood lymphocytes was tested in 196 individuals (80 HIV-1-infected patients and 116 healthy controls and cancer patients) using a three color fluorescence in situ hybridization approach to analyze chromosomal aberrations (B/M). Additionally, the NNRTI efavirenz and the NRTIs tenofovir and emtricitabine were tested for radiosensitizing effects in vitro.Lymphocytes from HIV-1-infected patients in the NNRTI + NRTI group were significantly more sensitive to ionizing radiation than in the other groups (patients without treatment or with NRTI + PI or HIV-negative controls). In vitro the triple medication efavirenz, tenofovir and emtricitabine leads to a reduced survival fraction and an increased activation of the DNA repair proteins H2AX, Nbs, Atm and 53BP1 in combination with ionizing radiation.HIV-1 treatment with NNRTI containing therapy regimes possibly sensitizes a subgroup of patients to ionizing radiation. Individual radiosensitivity of HIV-1-infected patients on HAART including NNRTI should be tested before starting radiotherapy.
EVALuna2:13258

No gender-specific Differences in the Radiation Sensitivity of Rectal Cancer Patients - Schuster, B.; Geinitz, H.; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Noncurated Data Lead to Misinterpretation of Treatment Outcomes in Patients With Prostate Cancer After Salvage or Palliative Radiotherapy - Rutzner, Sandra; Ganslandt, Oliver Thomas; Fietkau, Rainer; Prokosch, Hans-Ulrich; Lubgan, Dorota (JCO Clinical Cancer Informatics, 2019)
PURPOSE: Clinical data warehouses (cDWHs) and cancer registry databases have enabled researchers to conduct clinical analytics with structured electronic health record data. However, these secondary electronic health record sources are often limited in scope because they do not capture the clinical information needed to understand complex clinical questions. Thus, we evaluated the effect of additional curation of data. MATERIALS AND METHODS: Clinical data sets of 149 patients with prostate cancer with biochemical recurrence after radical prostatectomy treated with salvage or palliative radiotherapy between 2008 and 2017 from our institutional cDWH and Gießener Tumor Documentation System (GTDS) were linked (data warehouse [DWH] population) for analyzing treatment outcomes. The linked data sets were manually curated (manual postprocessing [MPP], eg, incorporate data from established urologists). The primary outcomes were the impact on data quality of treatment outcomes and the time spent on data curation. RESULTS: We obtained significantly more information on disease progression and patient survival (nonsignificant) when using curated data; the biochemical progression-free survival rate at 5 years for the DWH and DWH plus MPP populations was 63% v 30% (P ≤ .001) and the overall survival rate was 84% v 81% (P = .479), respectively. The median deviation of completeness and the median concordance of clinical data values were 21.47% (range, 55.38%-100%) and 95.00% (range, 63.40%-100%), respectively. We spent 121 hours, 42 minutes on data curation, with most time required for laboratory values, accounting, for a total of 45 hours, 20 minutes (37.26%). CONCLUSION: Our analysis indicates that time-to-event outcomes for patients with prostate cancer cannot be extracted using secondary data sources (cDWH plus GTDS) only. Outcomes data differed between the electronic data (DWH) and the second manual extraction (DWH plus MPP) because of a lack of follow-up data. When using such unique database resources, only baseline characteristics can reliably be extracted.
EVALuna2:209482

Noninvasive cardiac arrhythmia ablation with particle beams - Graeff, Christian; Bert, Christoph (Medical Physics, 2018)
Cardiac arrhythmias are a major health burden, associated with reduced quality of life and substantial morbidity and mortality. Current therapy includes moderately effective medication and catheter-based ablation of arrhythmogenic substrates in the heart. Catheter interventions frequently have to be repeated due to recurrent arrhythmia, can have rare but severe side-effects and are less suited especially for potentially lethal left ventricular tachycardia. Noninvasive alternatives are therefore warranted. Photon and ion beam radiotherapy has been studied in animal models and first patient cases have been reported using photons. Ion beams might offer the possibility to greatly reduce dose to surrounding healthy tissue, including critical cardiac substructures. Based on a recently conducted animal study, we report advantages and disadvantages of 4D-ion beam therapy, and strategies necessary for a clinical transition. Motion management of both respiration and heartbeat are discussed, as well as range uncertainty resulting from both regular motion and interfractional anatomic changes. Image guidance both in 3D and 4D has to be employed for a safe irradiation, but also population-based data on motion variability and time behavior of interfractional changes are necessary. Range verification could play a crucial role at least during development of clinical protocols. For clinical realization, it appears necessary to suppress or conformally mitigate the large respiratory motion to avoid normal tissue complications. Cardiac motion has to be incorporated into treatment planning, either through adequate range-considering internal margins or through more conformal strategies such as ECG-based gating or even 4D-optimization. The latter strategies would necessitate online 4D image guidance.
EVALuna2:36472

Non-professional Phagocytes can phagocytize Necrotic Cells at any Stage of the Cell Cycle - Hofmann, Andrea; Seeberg, Jacob; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Non-professional phagocytosis: a general feature of normal tissue cells - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2019)
Non-professional phagocytosis by cancer cells has been described for decades. Recently, non-professional phagocytosis by normal tissue cells has been reported, which prompted us to take a closer look at this phenomenon. Non-professional phagocytosis was studied by staining cultured cells with live-cell staining dyes or by staining paraffin-embedded tissues by immunohistochemistry. Here, we report that each of 21 normal tissue cell lines from seven different organs was capable of phagocytosis, including ex vivo cell cultures examined before the 3rd passage as well as the primary and virus-transformed cell lines. We extended our analysis to an in vivo setting, and we found the occurrence of non-professional phagocytosis in healthy skin biopsies immediately after resection. Using dystrophin immunohistochemistry for membrane staining, human post-infarction myocardial tissue was assessed. We found prominent signs of non-professional phagocytosis at the transition zone of healthy and infarcted myocardia. Taken together, our findings suggest that non-professional phagocytosis is a general feature of normal tissue cells.
CRIS-Team Scopus Importer:2019-08-27

Non-Professional Phagocytosis Increases in Melanoma Cells and Tissues with Increasing E-Cadherin Expression. - Unseld, Luzie Helene; Hildebrand, Laura; Putz, Florian; Büttner-Herold, Maike; Daniel, Christoph; Fietkau, Rainer; Distel, Luitpold (Current Oncology, 2023)
Non-professional phagocytosis in cancer has been increasingly studied in recent decades. In malignant melanoma metastasis, cell-in-cell structures have been described as a sign of cell cannibalism. To date, only low rates of cell-in-cell structures have been described in patients with malignant melanoma. To investigate these findings further, we examined twelve primary melanoma cell lines in both adherent and suspended co-incubation for evidence of engulfment. In addition, 88 malignant melanoma biopsies and 16 healthy tissue samples were evaluated. E-cadherin levels were determined in the cell lines and tissues. All primary melanoma cell lines were capable of phagocytosis, and phagocytosis increased when cells were in suspension during co-incubation. Cell-in-cell structures were also detected in most of the tissue samples. Early T stages and increasingly advanced N and M stages have correspondingly lower rates of cell-in-cell structures. Non-professional phagocytosis was also present in normal skin tissue. Non-professional phagocytosis appears to be a ubiquitous mechanism in malignant melanoma. The absence of phagocytosis in metastases may be one reason for the high rate of metastasis in malignant melanoma.
EVALuna2:539840

Norm- and hypo-fractionated radiotherapy is capable of activating human dendritic cells - Kulzer, Lorenz; Rubner, Yvonne; Deloch, Lisa; Allgäuer, Andrea; Frey, Benjamin; Fietkau, Rainer; Dörrie, Jan; Schaft, Niels; Gaipl, Udo (Journal of Immunotoxicology, 2014)
Abstract Despite the transient immunosuppressive properties of local radiotherapy (RT), this classical treatment modality of solid tumors is capable of inducing immunostimulatory forms of tumor-cell death. The resulting 'immunotoxicity' in the tumor, but not in healthy tissues, may finally lead to immune-mediated destruction of the tumor. However, little is known about the best irradiation scheme in this setting. This study examines the immunological effects of differently irradiated human colorectal tumor cells on human monocyte-derived dendritic cells (DC). Human SW480 tumor cells were irradiated with a norm-fractionation scheme (5 × 2 Gy), a hypo-fractionated protocol (3 × 5 Gy), and with a high single irradiation dose (radiosurgery; 1 × 15 Gy). Subsequently, human immature DC (iDC) were co-incubated with supernatants (SN) of these differently treated tumor cells. Afterwards, DC were analyzed regarding the expression of maturation markers, the release of cytokines, and the potential to stimulate CD4(+) T-cells. The co-incubation of iDC with SN of tumor cells exposed to norm- or hypo-fractionated RT resulted in a significantly increased secretion of the immune activating cytokines IL-12p70, IL-8, IL-6, and TNF?, compared to iDC co-incubated with SN of tumor cells that received a high single irradiation dose or were not irradiated. In addition, DC-maturation markers CD80, CD83, and CD25 were also exclusively elevated after co-incubation with the SN of fractionated irradiated tumor cells. Furthermore, the SN of tumor cells that were irradiated with norm- or hypo-fractionated RT triggered iDC to stimulate CD4(+) T-cells not only in an allogenic, but also in an antigen-specific manner like mature DC. Collectively, these results demonstrate that norm- and hypo-fractionated RT induces a fast human colorectal tumor-cell death with immunogenic potential that can trigger DC maturation and activation in vitro. Such findings may contribute to the improvement of irradiation protocols for the most beneficial induction of anti-tumor immunity.
EVALuna2:18178

Normofractionated irradiation and not temozolomide modulates the immunogenic and oncogenic phenotype of human glioblastoma cell lines - Schatz, Julia; Ladinig, Alexandra; Fietkau, Rainer; Putz, Florian; Gaipl, Udo; Frey, Benjamin; Derer, Anja (Strahlentherapie und Onkologie, 2022)
Purpose Glioblastoma multiforme (GBM) is the most aggressive primary brain tumor, with an overall poor prognosis after diagnosis. Conventional treatment includes resection, chemotherapy with temozolomide (TMZ), and concomitant radiotherapy (RT). The recent success of immunotherapy approaches in other tumor entities, particularly with immune checkpoint inhibitors, could not be clinically transferred to GBM treatment so far. Therefore, preclinical analyses of the expression of both immune-suppressive and immune-stimulatory checkpoint molecules following treatment of human glioblastoma cells with RT and/or temozolomide is needed to design feasible radio(chemo)immunotherapy trials for GBM in the future. Methods Five human glioblastoma cell lines (H4, HROG-06, U118, U138, U251) were analyzed regarding their clonogenic survival and cell death forms after chemotherapy (CT) with TMZ and/or normofractionated RT (5 x 2 Gy) via multicolor flow cytometry. Further, the tumor cell surface expression of immune-activating (OX40L, CD137L, CD70, and ICOSL) and immune-suppressive (PD-L1, PD-L2, HVEM) checkpoint molecules and of an oncogenic molecule (EGFR) were measured via multicolor flow cytometry after CT and RT alone or after RCT. Results Normofractionated RT and not TMZ was the trigger of induction of predominantly necrosis in the glioblastoma cells. Notably, clonogenicity did not correlate with cell death induction by RT. The basal expression level of immune-suppressive PD-L1, PD-L2, and HVEM varied in the analyzed glioblastoma cells. RT, but not TMZ, resulted in a significant upregulation of PD-L1 and PD-L2 in all tumor cells investigated. Also, the expression of HVEM was increased after RT in most of the GBM cell lines. In contrast, normofractionated RT individually modulated expression of the stimulating immune checkpoint molecules CD70, CD137L, OX40L, and ICOSL1. The oncogenic factor EGFR was significantly increased by irradiation in all examined cell lines, albeit to a different extent. None of the investigated molecules were downregulated after the treatments. Conclusion Normofractionated radiotherapy modulates the immunogenic as well as the oncogenic phenotype of glioblastoma cells, partly individually. Therefore, not only PD-L1 and PD-L2, but also other immunogenic molecules expressed on the surface of glioblastoma cells could serve as targets for immune checkpoint blockade in combination with RT in the future.
CRIS-Team WoS Importer:2022-12-23

Novel technique for high-precision stereotactic irradiation of mouse brains - Hartmann, Josefin; Wölfelschneider, Jens; Stache, Christina; Buslei, R.; Derer, Anja; Schwarz, Martin; Bäuerle, Tobias; Fietkau, Rainer; Gaipl, Udo; Bert, Christoph; Hoelsken, A.; Frey, Benjamin (Strahlentherapie und Onkologie, 2016)
Small animal irradiation systems were developed for preclinical evaluation of tumor therapy closely resembling the clinical situation. Mostly only clinical LINACs are available, so protocols for small animal partial body irradiation using a conventional clinical system are essential. This study defines a protocol for conformal brain tumor irradiations in mice.CT and MRI images were used to demarcate the target volume and organs at risk. Three 6 MV photon beams were planned for a total dose of 10 fractions of 1.8 Gy. The mouse position in a dedicated applicator was verified by an X-ray patient positioning system before each irradiation. Dosimetric verifications (using ionization chambers and films) were performed. Irradiation-induced DNA damage was analyzed to verify the treatment effects on the cellular level.The defined treatment protocol and the applied fractionation scheme were feasible. The in-house developed applicator was suitable for individual positioning at submillimeter accuracy of anesthetized mice during irradiation, altogether performed in less than 10 min. All mice tolerated the treatment well. Measured dose values perfectly matched the nominal values from treatment planning. Cellular response was restricted to the target volume.Clinical LINAC-based irradiations of mice offer the potential to treat orthotopic tumors conformably. Especially with respect to lateral penumbra, dedicated small animal irradiation systems exceed the clinical LINAC solution.
EVALuna2:7317

Older Patients Are Less Affected by Radiochemotherapeutic Treatment than Younger - Welling, Max J.; Losensky, Wencke; Wächter, Katharina; Schilling, Teresa; Frank, Friedrich; Haas, Matthias; Fietkau, Rainer; Distel, Luitpold; Weiß, Stephanie (BioMed Research International, 2018)
Purpose: The general assumption is that cancer therapy impairs the quality of life in elderly patients more than in younger ones. We were interested in the effects of radiochemotherapeutic treatment on the quality of life of elderly patients compared to younger patients and compared to normative data of a general German population. Methods and Materials: A total of 465 patients completed the EORTC QLQ-C30 questionnaire. Repetitive completion of the questionnaire over time led to 1407 datasets. Our patient cohort contained 197 (42.4%) patients with colorectal cancer followed by 109 (23.4%) patients with head and neck cancer, 43 (9.2%) patients with lung cancer, and 116 (25%) with other types of cancer. Patients were categorized into five age groups, the respective cut-offs being 40, 50, 60, and 70 years. Normative data were drawn from a population study of a general German population. Results: Functional scores and symptom scores were approximately stable between the different age groups. Our data does not suggest a significant difference between the investigated age groups. Advancing age evened out the differences between the normative data of the general German population and the cancer patients in 11 of 15 scores. Conclusions: The general belief about younger patients having fewer physical and psychological problems related to radiochemotherapy needs to be reconsidered. Overall resilience of older patients is apparently underestimated.
EVALuna2:36461

Older patients with inoperable non-small cell lung cancer: long-term survival after concurrent chemoradiotherapy - Semrau, Sabine; Zettl, Heike; Hildebrandt, Guido; Klautke, Gunther; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
Considering the various comorbidities associated with aging, the feasibility and usefulness of concurrent chemoradiotherapy (CRT) in older patients with inoperable non-small cell lung cancer (NSCLC) is a controversial issue. Here, we compared the feasibility of CRT and the effects of various comorbidities on the prognosis of a minimally selected population of inoperable NSCLC patients aged 60-77 years.The study comprised 161 patients with inoperable NSCLC who received CRT with a target radiation dose greater than 60 Gy and platinum-based chemotherapy from 1998 to 2007. The total population included 69 patients aged 60-69 years and 53 aged 70-77 years. These two age cohorts were included in the study with a follow-up of a median 14.5 months.The two groups showed no differences in long-term survival, as reflected by the 5-year survival rates of 13.0 ± 4.1 % (60- to 69-year-olds) and 14.4 ± 4.9 % (70- to 77-year-olds). During the treatment phase, the groups were comparable in terms of toxicity and the feasibility of chemotherapy. Compared to patients in their 60s, the septuagenarians had more pulmonary comorbidities (p = 0.02), diabetes mellitus (p = 0.04), cardiac comorbidities (p = 0.08), and previous cancer disease (p = 0.08) that exerted a negative effect on survival. In patients without comorbidities, there were no differences between the age groups.Age is not a contraindication for concurrent CRT per se, because elderly patients do not have a worse long-term prognosis than younger seniors. However, "elderly patients" (>= 70-77 years) have more concomitant diseases associated with shorter survival than "moderately aged patients" (>= 60-69 years).
EVALuna2:18190

Oligometastasis in breast cancer—current status and treatment options from a radiation oncology perspective - Piroth, Marc D.; Krug, David; Feyer, Petra; Baumann, Rene; Combs, Stephanie; Duma, Marciana-Nona; Dunst, Juergen; Fastner, Gerd; Fietkau, Rainer; Guckenberger, Matthias; Haase, Wulf; Harms, Wolfgang; et al. (Strahlentherapie und Onkologie, 2022)
Evidence from a few small randomized trials and retrospective cohorts mostly including various tumor entities indicates a prolongation of disease free survival (DFS) and overall survival (OS) from local ablative therapies in oligometastatic disease (OMD). However, it is still unclear which patients benefit most from this approach. We give an overview of the several aspects of stereotactic body radiotherapy (SBRT) in extracranial OMD in breast cancer from a radiation oncology perspective. A PubMed search referring to this was conducted. An attempt was made to relate the therapeutic efficacy of SBRT to various prognostic factors. Data from approximately 500 breast cancer patients treated with SBRT for OMD in mostly in small cohort studies have been published, consistently indicating high local tumor control rates and favorable progression-free (PFS) and overall survival (OS). Predictors for a good prognosis after SBRT are favorable biological subtype (hormone receptor positive, HER2 negative), solitary metastasis, bone-only metastasis, and long metastasis-free interval. However, definitive proof that SBRT in OMD breast cancer prolongs DFS or OS is lacking, since, with the exception of one small randomized trial (n = 22 in the SBRT arm), none of the cohort studies had an adequate control group. Further studies are needed to prove the benefit of SBRT in OMD breast cancer and to define adequate selection criteria. Currently, the use of local ablative SBRT should always be discussed in a multidisciplinary tumor board.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Breast cancer; Oligometastases; OMD; Radiotherapy; Stereotactic body radiotherapy

Oligometastatic head and neck cancer: Which patients benefit from radical local treatment of all tumour sites? - Weissmann, Thomas; Höfler, Daniel; Hecht, Markus; Semrau, Sabine; Haderlein, Marlen; Filimonova, Irina; Frey, Benjamin; Bert, Christoph; Lettmaier, Sebastian; Mantsopoulos, Konstantinos; Iro, Heinrich; Fietkau, Rainer; et al. (Radiation Oncology, 2021)
Background: There is a large lack of evidence for optimal treatment in oligometastatic head and neck cancer and it is especially unclear which patients benefit from radical local treatment of all tumour sites. Methods: 40 patients with newly diagnosed oligometastatic head and neck cancer received radical local treatment of all tumour sites from 14.02.2008 to 24.08.2018. Primary endpoint was overall survival. Time to occurrence of new distant metastases and local control were evaluated as secondary endpoints as well as prognostic factors in univariate und multivariate Cox’s regression analysis. To investigate the impact of total tumour volume on survival, all tumour sites were segmented on baseline imaging. Results: Radical local treatment included radiotherapy in 90% of patients, surgery in 25% and radiofrequency ablation in 3%. Median overall survival from first diagnosis of oligometastatic disease was 23.0 months, 2-year survival was 48%, 3-year survival was 37%, 4-year survival was 24% and 5-year survival was 16%. Median time to occurrence of new distant metastases was 11.6 months with freedom from new metastases showing a tail pattern after 3 years of follow-up (22% at 3, 4- and 5-years post-treatment). In multivariate analysis, better ECOG status, absence of bone and brain metastases and lower total tumour volume were significantly associated with improved survival, whereas the number of metastases and involved organ sites was not. Conclusions: Radical local treatment in oligometastatic head and neck cancer shows promising outcomes and needs to be further pursued. Patients with good performance status, absence of brain and bone metastases and low total tumour volume were identified as optimal candidates for radical local treatment in oligometastatic head and neck cancer and should be considered for selection in future prospective trials.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Head and neck cancer; Local treatment; Oligometastatic disease; Radiotherapy; SBRT

Oligometastatic non-small cell lung cancer–surgical options and therapy strategies - Schreiner, Waldemar; Semrau, S.; Fietkau, Rainer; Sirbu, Horia (Zentralblatt für Chirurgie, 2014)
The therapeutic strategies for oligometastatic non-small cell lung cancer have changed over the last decade from palliative to curative intent. The role of surgery in this multimodal treatment in selected patients remains a subject for open discussion.Data of 34 patients with one or two metastases treated from January 1998 to January 2013 were retrospectively analysed.The mean age was 59.7 (± 10.1) years. The male vs. female ratio was 20 vs. 14. Adenocarcinoma was the most common histological type (58.8 %). The synchronous metastases were present in 15 patients, the metachronous in 19 patients. Single metastases were present in 27 patients, two metastases in 7 patients. The most frequently involved organs were brain (58.8 %) and the lungs (23.6 %). The primary tumour resection was achievable in 20 patients as R0 and in 2 patients as R1. The median overall survival, the local and the systemic disease-free survivals in the entire group were 40, 38 and 25 months, respectively. The 5 year overall survival, the 5 year local and systemic disease-free survivals were 29.2, 26.9 and 16.5 %, respectively. The treatment strategies including surgery for primary tumour as well as for pulmonary metastases site, combined with the lymph node dissection and the resection of the extracerebral and cerebral metastases, were identified as independent prognostic factors for long-term survival.Surgery in oligometastatic non-small cell lung carcinoma is feasible for primary tumour and for metastases. It is an effective option in the multimodal treatment in highly selected patients. The lymph node dissection should remain an important integral part of the surgical treatment.
EVALuna2:18244

Oncological Patients with systemic Lupus Erythematosus have a clear risk of increased Radiation Sensitivity - Schenker, Hannah; Schuster, B.; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

One-tube multicolor flow cytometry assay (OTMA) for comprehensive immunophenotyping of peripheral blood - Donaubauer, Anna-Jasmina; Rühle, Paul-Friedrich; Becker, Ina; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Human Monoclonal Antibodies, 2019)
Recent improvements in the flow cytometry technology allow the determination of the general immune status through the development of multicolor immunofluorescence panels. The one-tube multicolor flow cytometry assay (OTMA) that is presented here identifies 20 different, clinically relevant immune cell subsets and three common activation markers. Thereby, a comprehensive immune status that covers all major immune cells is easily obtained. The assay is suitable for every common three lasers and 10 color flow cytometer and includes the application of 15 different antibodies. Furthermore, the assay requires only 100 μL of EDTA-treated whole-blood and less than 40 min for sample preparation. By being easily adaptable to individual requirements and by additionally determining absolute cell counts, the assay is well-suited for translational research in clinical trials.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Absolute cell count; Antibody; Gating strategy; Human whole-blood; Immune status; Immunophenotyping; Multicolor flow cytometry; One-tube measurement

One year survival of brain tumor patients is closely linked to symptomatic CMV-encephalopathy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, Florian; et al. (2017)
EVALuna2:32882

On PTV definition for glioblastoma based on fiber tracking of diffusion tensor imaging data - Witulla, Barbara; Goerig, Nicole; Putz, Florian; Frey, Benjamin; Engelhorn, Tobias; Dörfler, Arnd; Uder, Michael; Fietkau, Rainer; Bert, Christoph; Laun, Frederik Bernd (PLoS ONE, 2020)
Radiotherapy (RT) is commonly applied for the treatment of glioblastoma multiforme (GBM). Following the planning target volume (PTV) definition procedure standardized in guidelines, a 20% risk of missing non-local recurrences is present. Purpose of this study was to evaluate whether diffusion tensor imaging (DTI)-based fiber tracking may be beneficial for PTV definition taking into account the prediction of distant recurrences. 56 GBM patients were examined with magnetic resonance imaging (MRI) including DTI performed before RT after resection of the primary tumor. Follow-up MRIs were acquired in three month intervals. For the seven patients with a distant recurrence, fiber tracking was performed with three algorithms and it was evaluated whether connections existed from the primary tumor region to the distant recurrence. It depended strongly on the used tracking algorithm and the used tracking parameters whether a connection was observed. Most of the connections were weak and thus not usable for PTV definition. Only in one of the seven patients with a recurring tumor, a clear connection was present. It seems unlikely that DTI-based fiber tracking can be beneficial for predicting distant recurrences in the planning of PTVs for glioblastoma multiforme.
CRIS-Team Scopus Importer:2020-01-21

On the Death of our Honorary Member, Prof. Seymour Levitt MD, has works published, Radiologist in Minneapolis - Sauer, Rolf (Strahlentherapie und Onkologie, 2017)
EVALuna2:33029

On the implant stability in adaptive multi-catheter breast brachytherapy: Establishment of a decision-tree for treatment re-planning - Karius, Andre; Szkitsak, Juliane; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Schubert, Philipp; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2023)
Background and purpose: To assess implant stability and identify causes of implant variations during high-dose-rate multi-catheter breast brachytherapy. Materials and methods: Planning-CTs were compared to control-CTs acquired halfway through the treatment for 100 patients. For assessing geometric stability, Fréchet-distance and button-to-button distance changes of all catheters as well as variations of Euclidean distances and convex hulls of all dwell positions were determined. The CTs were inspected to identify the causes of geometric changes. Dosimetric effects were evaluated by target volume transfers and re-contouring of organs at risk. The dose non-uniformity ratio (DNR), 100% and 150% isodose volumes (V100 and V150), coverage index (CI), and organ doses were calculated. Correlations between the examined geometric and dosimetric parameters were assessed. Results: Fréchet-distance and dwell position deviations >2.5 mm as well as button-to-button distance changes >5 mm were detected for 5%, 2%, and 6.3% of catheters, but for 32, 17, and 37 patients, respectively. Variations occurred enhanced in the lateral breast and close to the ribs, e.g. due to different arm positions. Only small dosimetric effects with median DNR, V100, and CI variations of −0.01 ± 0.02, (−0.5 ± 1.3)ccm, and (–1.4 ± 1.8)% were observed in general. Skin dose exceeded recommended levels for 12 of 100 patients. Various correlations between geometric and dosimetric implant stability were found, based on which decision-tree regarding treatment re-planning was established. Conclusion: Multi-catheter breast brachytherapy shows a high implant stability in general, but considering skin dose changes is important. To increase implant stability for individual patients, we plan to investigate patient immobilization aids during treatments.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Adaptive brachytherapy; CT imaging; Imaging-based treatment planning; Implant stability; Multi-catheter breast brachytherapy; Treatment quality assurance

On the use of multi-dimensional scaling and electromagnetic tracking in high dose rate brachytherapy - Goetz, Th I.; Ermer, M.; Salas-Gonzalez, Diego; Kellermeier, Markus; Strnad, Vratislav; Bert, Christoph; Hensel, Bernhard; Tome, A. M.; Lang, E. W. (Physics in Medicine and Biology, 2017)
High dose rate brachytherapy affords a frequent reassurance of the precise dwell positions of the radiation source. The current investigation proposes a multi-dimensional scaling transformation of both data sets to estimate dwell positions without any external reference. Furthermore, the related distributions of dwell positions are characterized by uni-or bi-modal heavy-tailed distributions. The latter are well represented by α-stable distributions. The newly proposed data analysis provides dwell position deviations with high accuracy, and, furthermore, offers a convenient visualization of the actual shapes of the catheters which guide the radiation source during the treatment.
EVALuna2:33032

On the use of particle filters for electromagnetic tracking in high dose rate brachytherapy - Goetz, Th I.; Lahmer, Godehard; Brandt, Tobias; Kallis, Karoline; Strnad, Vratislav; Bert, Christoph; Hensel, Bernhard; Tome, A. M.; Lang, E. W. (Physics in Medicine and Biology, 2017)
Modern radiotherapy of female breast cancers often employs high dose rate brachytherapy, where a radioactive source is moved inside catheters, implanted in the female breast, according to a prescribed treatment plan. Source localization relative to the patient's anatomy is determined with solenoid sensors whose spatial positions are measured with an electromagnetic tracking system. Precise sensor dwell position determination is of utmost importance to assure irradiation of the cancerous tissue according to the treatment plan. We present a hybrid data analysis system which combines multi-dimensional scaling with particle filters to precisely determine sensor dwell positions in the catheters during subsequent radiation treatment sessions. Both techniques are complemented with empirical mode decomposition for the removal of superimposed breathing artifacts. We show that the hybrid model robustly and reliably determines the spatial positions of all catheters used during the treatment and precisely determines any deviations of actual sensor dwell positions from the treatment plan. The hybrid system only relies on sensor positions measured with an EMT system and relates them to the spatial positions of the implanted catheters as initially determined with a computed x-ray tomography.
EVALuna2:33033

Optimization of Single Voxel MR Spectroscopy Sequence Parameters and Data Analysis Methods for Thermometry in Deep Hyperthermia Treatments - Hartmann, Josefin; Gellermann, J.; Brandt, Tobias; Schmidt, M.; Pyatykh, S.; Hesser, J.; Ott, O.; Fietkau, Rainer; Bert, Christoph (Technology in Cancer Research & Treatment, 2016)
The difference in the resonance frequency of water and methylene moieties of lipids quantifies in magnetic resonance spectroscopy the absolute temperature using a predefined calibration curve. The purpose of this study was the investigation of peak evaluation methods and the magnetic resonance spectroscopy sequence (point-resolved spectroscopy) parameter optimization that enables thermometry during deep hyperthermia treatments.Different Lorentz peak-fitting methods and a peak finding method using singular value decomposition of a Hankel matrix were compared. Phantom measurements on organic substances (mayonnaise and pork) were performed inside the hyperthermia 1.5-T magnetic resonance imaging system for the parameter optimization study. Parameter settings such as voxel size, echo time, and flip angle were varied and investigated.Usually all peak analyzing methods were applicable. Lorentz peak-fitting method in MATLAB proved to be the most stable regardless of the number of fitted peaks, yet the slowest method. The examinations yielded an optimal parameter combination of 8 cm(3) voxel volume, 55 millisecond echo time, and a 90° excitation pulse flip angle.The Lorentz peak-fitting method in MATLAB was the most reliable peak analyzing method. Measurements in homogeneous and heterogeneous phantoms resulted in optimized parameters for the magnetic resonance spectroscopy sequence for thermometry.
EVALuna2:18362

Oral cavity carcinomas as primary manifestation of telomere maintenance disorders (telomeropathies) - Beier, F.; Schmitt, K.; Bouillon, A. -S; Hasenbank, C.; Vankann, L.; Ambrosch, P.; Hoffmann, T.; Fietkau, Rainer; Panse, J.; Bruemmendorf, T. H. (2016)
EVALuna2:32921

Organ-sparing treatment of penile cancer with interstitial pulsed-dose-rate brachytherapy - Seibold, Johannes; Strnad, Vratislav; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
To assess the efficacy and toxicity profile of protocol-based interstitial pulsed-dose-rate (PDR) brachytherapy for penile carcinoma.From August 2002 to February 2014, 13 men with penile cancer were treated by interstitial brachytherapy. The tumor stage was T1 for eight patients, T2 for four patients, and T3 for one patient. The tumor grade was well differentiated for five patients and moderately differentiated for seven patients, while it was unknown for one patient. Lymph node staging was positive for three of 13 patients. All patients were treated using interstitial PDR brachytherapy with dose specifications according to the Paris system. For data collection of erectile dysfunction, the International Index of Erectile Function questionnaire was used, supplemented by the follow-up data.The median follow-up was 54.0 months (range, 13-155 months). Only one patient (1/13, 7.7 %) with local failure was documented. At 5 and 10 years, the local cumulative recurrence rate, disease-free survival, and the cancer-specific survival rates were 12.5 % (95 % CI, 80.4-119.6), 80.8 % (95 % CI, 75.2-124.8), and 77.9 % (95 % CI, 74.3-125.7), respectively. At the time of analysis, nine of 13 men were alive; two of 13 men died of distant metastases from the tumor and two for other reasons with no sign of cancer disease. Serious late side effects such as soft tissue necrosis occurred in four of 13 patients (30 %) and all were successfully treated with medication. Mutilating salvage surgery was not necessary in any of the cases. Urethral stenosis was documented for two of 13 (15.4 %) and dysuria occurred in four of 13 patients (30.8 %). Eight of 11 men (72.7 %) never or only sometimes had erectile dysfunction.In selected patients, interstitial PDR brachytherapy of penile cancer is effective as an organ-sparing treatment. It yields satisfactory results for the conservation of sexual function.
EVALuna2:18347

Osteoimmunological Effects of Radon Therapy on Patients with chronic degenerative and/or inflammatory Diseases - Becker, I.; Donaubauer, Anna-Jasmina; Klein, G.; Cheremina, O.; Fournier, C.; Cucu, A.; Rapp, F.; Kraft, D.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Outcome and management of rare high-grade “salivary” adenocarcinoma: the important role of adjuvant (chemo)radiotherapy - Scherl, Claudia; Haderlein, Marlen; Agaimy, Abbas; Mantsopoulos, Konstantinos; Koch, Michael; Traxdorf, Maximilian; Fietkau, Rainer; Grundtner, Philipp; Iro, Heinrich (Strahlentherapie und Onkologie, 2019)
Purpose: To determine survival and management strategies for high-grade adenocarcinoma of salivary glands (ASG). Methods: A retrospective analysis of cases diagnosed between 1998 and 2015 from our single tertiary referral center was performed. Multivariable logistic regression was used to determine factors associated with survival. Results: Thirty-eight cases of high-grade ASG were identified. Most patients were men (68.4%) with a median age of 65.5 years (range 23–84 years). Most tumors were T3 and T4 (65.8%). Regional metastases were common (55.2%), and 42.1% developed distant metastases. The mean follow-up was 60.5 months. All patients received surgery as primary treatment, with 84.2% of patients receiving adjuvant radiation therapy or chemoradiotherapy ([C]RT). Cumulative overall survival was 89.1%, 50.9%, and 20.7% after 1, 5, and 10 years, respectively. Disease-specific survival was 94.4%, 69.8%, and 42.8%, and distant-metastases-free survival (DMFS) was 80.5%, 50.1%, and 40.1% after 1, 5, and 10 years. On multivariable analysis, advanced T status correlated with DMFS (hazard ratio 2.75, 95% CI 0.93–8.16). Postsurgical (C)RT reduced the locoregional recurrence rate by 23.9%, and it improved the locoregional-recurrence-free survival by 39% (p = 0.094). Conclusion: High-grade ASG is considered to have an unfavorable prognosis. Adjuvant (C)RT reduces the rate of locoregional recurrences. Distant metastases are common, and an advanced T stage has increased prognostic value for development of early distant lesions.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Head and neck cancer; Salivary gland cancer; Salivary gland malignancy; Survival salivary gland cancer; Treatment salivary gland cancer

Oxaliplatin added to fluorouracil-based preoperative chemoradiotherapy and postoperative chemotherapy of locally advanced rectal cancer (the German CAO/ARO/AIO-04 study): final results of the multicentre, open-label, randomised, phase 3 trial - Roedel, Claus; Graeven, Ullrich; Fietkau, Rainer; Hohenberger, Werner; Hothorn, Torsten; Arnold, Dirk; Hofheinz, Ralf-Dieter; Ghadimi, Michael; Wolff, Hendrik A.; Lang-Welzenbach, Marga; Raab, Hans-Rudolf; Wittekind, Christian; et al. (Lancet Oncology, 2015)
Preoperative chemoradiotherapy with infusional fluorouracil, total mesorectal excision surgery, and postoperative chemotherapy with fluorouracil was established by the German CAO/ARO/AIO-94 trial as a standard combined modality treatment for locally advanced rectal cancer. Here we compare the previously established regimen with an investigational regimen in which oxaliplatin was added to both preoperative chemoradiotherapy and postoperative chemotherapy.In this multicentre, open-label, randomised, phase 3 study we randomly assigned patients with rectal adenocarcinoma, clinically staged as cT3-4 or any node-positive disease, to two groups: a control group receiving standard fluorouracil-based combined modality treatment, consisting of preoperative radiotherapy of 50·4 Gy in 28 fractions plus infusional fluorouracil (1000 mg/m(2) on days 1-5 and 29-33), followed by surgery and four cycles of bolus fluorouracil (500 mg/m(2) on days 1-5 and 29); or to an investigational group receiving preoperative radiotherapy of 50·4 Gy in 28 fractions plus infusional fluorouracil (250 mg/m(2) on days 1-14 and 22-35) and oxaliplatin (50 mg/m(2) on days 1, 8, 22, and 29), followed by surgery and eight cycles of oxaliplatin (100 mg/m(2) on days 1 and 15), leucovorin (400 mg/m(2) on days 1 and 15), and infusional fluorouracil (2400 mg/m(2) on days 1-2 and 15-16). Randomisation was done with computer-generated block-randomisation codes stratified by centre, clinical T category (cT1-3 vs cT4), and clinical N category (cN0 vs cN1-2) without masking. The primary endpoint was disease-free survival, defined as the time between randomisation and non-radical surgery of the primary tumour (R2 resection), locoregional recurrence after R0/1 resection, metastatic disease or progression, or death from any cause, whichever occurred first. Survival and cumulative incidence of recurrence analyses followed the intention-to-treat principle; toxicity analyses included all patients treated. Enrolment of patients in this trial is completed and follow-up is ongoing. This study is registered with ClinicalTrials.gov, number NCT00349076.Of the 1265 patients initially enrolled, 1236 were assessable (613 in the investigational group and 623 in the control group). With a median follow-up of 50 months (IQR 38-61), disease-free survival at 3 years was 75·9% (95% CI 72·4-79·5) in the investigational group and 71·2% (95% CI 67·6-74·9) in the control group (hazard ratio [HR] 0·79, 95% CI 0·64-0·98; p=0·03). Preoperative grade 3-4 toxic effects occurred in 144 (24%) of 607 patients who actually received fluorouracil and oxaliplatin during chemoradiotherapy and in 128 (20%) of 625 patients who actually received fluorouracil chemoradiotherapy. Of 445 patients who actually received adjuvant fluorouracil and leucovorin and oxaliplatin, 158 (36%) had grade 3-4 toxic effects, as did 170 (36%) of 470 patients who actually received adjuvant fluorouracil. Late grade 3-4 adverse events in patients who received protocol-specified preoperative and postoperative treatment occurred in 112 (25%) of 445 patients in the investigational group, and in 100 (21%) of 470 patients in the control group.Adding oxaliplatin to fluorouracil-based neoadjuvant chemoradiotherapy and adjuvant chemotherapy (at the doses and intensities used in this trial) significantly improved disease-free survival of patients with clinically staged cT3-4 or cN1-2 rectal cancer compared with our former fluorouracil-based combined modality regimen (based on CAO/ARO/AIO-94). The regimen established by CAO/ARO/AIO-04 can be deemed a new treatment option for patients with locally advanced rectal cancer.German Cancer Aid (Deutsche Krebshilfe).
EVALuna2:15201

P22-2-jD Mit hydrostatischem Hochdruck generierte Ganzzell- Tumorvakzine erzeugen in Kombination mit Strahlentherapie ein immunogenes Tumor-Mikromilieu - Rückert, Michael; Seitz, Christoph; Deloch, Lisa; Weiss, Eva-Maria; Utz, S; Izydor, Marika; Ebel, Nina; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2019)

PACIFIC-R: First real-world study of patients with unresectable, stage III NSCLC treated with durvalumab after chemoradiotherapy - Girard, N.; Mornex, F.; Christoph, D. C.; Fietkau, Rainer; Filippi, A. R.; Field, J.; Garrido Lopez, P.; Mcdonald, F.; Peters, S.; Klein, A. B.; Licour, M.; Garassino, M. C. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-08-13

PACIFIC-R real-world study: Treatment duration and interim analysis of progression-free survival in unresectable stage III NSCLC patients treated with durvalumab after chemoradiotherapy - Girard, N.; Smit, H. J. M.; Sibille, A.; Mcdonald, F.; Mornex, F.; Garassino, M. C. C.; Filippi, A. R.; Peters, S.; Field, J. K.; Christoph, D. C.; Fietkau, Rainer; Haakensen, V. D.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-10-15

Paediatric and adult soft tissue sarcomas with NTRK1 gene fusions: a subset of spindle cell sarcomas unified by a prominent myopericytic/haemangiopericytic pattern - Haller, Florian; Knopf, Jasmin; Ackermann, Andreas; Bieg, Matthias; Kleinheinz, Kortine; Schlesner, Matthias; Moskalev, Evgeny; Will, Rainer; Satir, Ali Abdel; Abdelmagid, Ibtihalat E.; Giedl, Josef; Carbon, Roman; et al. (Journal of Pathology, 2016)
Neoplasms with a myopericytomatous pattern represent a morphological spectrum of lesions encompassing myopericytoma of the skin and soft tissue, angioleiomyoma, myofibromatosis/infantile haemangiopericytoma and putative neoplasms reported as malignant myopericytoma. Lack of reproducible phenotypic and genetic features of malignant myopericytic neoplasms have prevented the establishment of myopericytic sarcoma as an acceptable diagnostic category. Following detection of a LMNA-NTRK1 gene fusion in an index case of paediatric haemangiopericytoma-like sarcoma by combined whole-genome and RNA sequencing, we identified three additional sarcomas harbouring NTRK1 gene fusions, termed 'spindle cell sarcoma, NOS with myo/haemangiopericytic growth pattern'. The patients were two children aged 11 months and 2 years and two adults aged 51 and 80 years. While the tumours of the adults were strikingly myopericytoma-like, but with clear-cut atypical features, the paediatric cases were more akin to infantile myofibromatosis/haemangiopericytoma. All cases contained numerous thick-walled dysplastic-like vessels with segmental or diffuse nodular myxohyaline myo-intimal proliferations of smooth muscle actin-positive cells, occasionally associated with thrombosis. Immunohistochemistry showed variable expression of smooth muscle actin and CD34, but other mesenchymal markers, including STAT6, were negative. This study showed a novel variant of myo/haemangiopericytic sarcoma with recurrent NTRK1 gene fusions. Given the recent introduction of a novel therapeutic approach targeting NTRK fusion-positive neoplasms, recognition of this rare but likely under-reported sarcoma variant is strongly encouraged.
EVALuna2:6792

Palbociclib Induces Senescence in Melanoma and Breast Cancer Cells and Leads to Additive Growth Arrest in Combination With Irradiation - Jost, Tina; Heinzerling, Lucie; Fietkau, Rainer; Hecht, Markus; Distel, Luitpold (Frontiers in Oncology, 2021)
Introduction: Several kinase inhibitors (KI) bear the potential to act as radiosensitizers. Little is known of the radiosensitizing effects of a wide range of other KI like palbociclib, which is approved in ER+/HER2- metastatic breast cancer. Method: In our study, we used healthy donor fibroblasts and breast cancer and skin cancer cells to investigate the influence of a concomitant KI + radiation therapy. Cell death and cell cycle distribution were studied by flow cytometry after Annexin-V/7-AAD and Hoechst staining. Cellular growth arrest was studied in colony-forming assays. Furthermore, we used C12-FDG staining (senescence) and mRNA expression analysis (qPCR) to clarify cellular mechanisms. Results: The CDK4/6 inhibitor palbociclib induced a cell cycle arrest in the G0/G1 phase. Cellular toxicity (cell death) was only slightly increased by palbociclib and not enhanced by additional radiotherapy. As the main outcome of the colony formation assays, we found that cellular growth arrest was induced by palbociclib and improved by radiotherapy in an additive manner. Noticeably, palbociclib treatment clearly induced senescence not only in breast cancer and partly in melanoma cells, but also in healthy fibroblasts. According to these findings, the downregulation of senescence-related FOXM1 might be an involved mechanism of the senescence-induction potential of palbociclib. Conclusion: The effect on cellular growth arrest of palbociclib and radiotherapy is additive. Palbociclib induces permanent G0/G1 cell cycle arrest by inducing senescence in fibroblasts, breast cancer, and melanoma cells. Direct cell death induction is only a minor secondary mechanism of action. Concomitant KI and radiotherapy is a strategy worth studying in clinical trials.
CRIS-Team Scopus Importer:2021-11-12
Keywords: breast cancer; kinase inhibitor; melanoma; palbociclib; radiotherapy; senescence

Paragangliomas of the Head and Neck: Local Control and Functional Outcome Following Fractionated Stereotactic Radiotherapy - Weissmann, Thomas; Lettmaier, Sebastian; Roesch, Johannes; Mengling, Veit; Bert, Christoph; Iro, Heinrich; Hornung, Joachim; Janka, Rolf Matthias; Semrau, Sabine; Fietkau, Rainer; Putz, Florian (American Journal of Clinical Oncology-Cancer Clinical Trials, 2019)
Objectives: To investigate local control and functional outcome following state-of-the-art fractionated stereotactic radiotherapy (FSRT) for paragangliomas of the head and neck. Methods: In total, 40 consecutive patients with paragangliomas of the head and neck received conventionally FSRT from 2003 to 2016 at the Department of Radiation Oncology of the University Hospital Erlangen. Local control, toxicities, and functional outcome were examined during follow-up. In total, 148 magnetic resonance imaging studies were subjected to longitudinal volumetric analysis using whole tumor segmentation in a subset of 22 patients. Results: A total of 80.0% (32/40) of patients received radiotherapy as part of their primary treatment. In 20.0% (8/40) of patients, radiation was used as salvage treatment after tumor recurrence in patients initially treated with surgery alone. The median dose applied was 54.0 Gy (interdecile range, 50.4 to 56.0 Gy) in single doses of 1.8 or 2 Gy. Local control was 100% after a median imaging follow-up of 52.2 months (range, 0.8 to 152.9 mo). The volumetric analysis confirmed sustained tumor control in a subset of 22 patients and showed transient enlargement (range, 129.6% to 151.2%) in 13.6% of cases (3/22). After a median volumetric follow-up of 24.6 months mean tumor volume had diminished to 86.1% compared with initial volume. In total, 52.5% (21/40) of patients reported improved symptoms after radiotherapy, 40% (16/40) observed no subjective change with only 7.5% (3/40) reporting significant worsening. Conclusions: State-of-the-art FSRT provides excellent control and favorable functional outcome in patients with paragangliomas of the head and neck. The volumetric analysis provides improved evidence for sustained tumor control.
CRIS-Team Scopus Importer:2019-10-22
Keywords: fractionated stereotactic radiotherapy; functional outcomes; paraganglioma; tumor control; volumetric analysis

Paragangliomas of the head and neck-local control and functional outcomes following stereotactic radiotherapy - Weissmann, T.; Semrau, S.; Fietkau, Rainer; Putz, Florian (2018)
EVALuna2:36509

PARP inhibitors combined with ionizing radiation induce different effects in melanoma cells and healthy fibroblasts - Weigert, Verena; Jost, Tina; Hecht, Markus; Knippertz, Ilka; Heinzerling, Lucie; Fietkau, Rainer; Distel, Luitpold (BMC Cancer, 2020)
BACKGROUND: PARP inhibitors niraparib and talazoparib are FDA approved for special cases of breast cancer. PARP is an interesting repair protein which is frequently affected in cancer cells. We studied the combined action of talazoparib or niraparib with ionizing radiation in melanoma cells and healthy fibroblasts. METHODS: Homologous recombination (HR) status in six different melanoma cell lines and healthy fibroblasts was assessed. Cell cultures were treated with PARP inhibitors talazoparib or niraparib and ionizing radiation (IR). Apoptosis, necrosis and cell cycle distribution was analyzed via flow cytometry. Cell migration was studied by scratch assays. RESULTS: Studied melanoma cell cultures are HR deficient. Studied healthy fibroblasts are HR proficient. Talazoparib and niraparib have congruent effects within the same cell cultures. In all cell cultures, combined treatment increases cell death and G2/M arrest compared to IR. Combined treatment in melanoma cells distinctly increases G2/M arrest. Healthy fibroblasts are less affected by G2/M arrest. Treatment predominantly decelerates or does not modify migration. In two cell cultures migration is enhanced under the inhibitors. CONCLUSIONS: Although the two PARP inhibitors talazoparib and niraparib appear to be suitable for a combination treatment with ionizing radiation in our in vitro studies, a combination treatment cannot generally be recommended. There are clear interindividual differences in the effect of the inhibitors on different melanoma cells. Therefore, the effect on the cancer cells should be studied prior to a combination therapy. Since melanoma cells increase more strongly than fibroblasts in G2/M arrest, the fractional application of combined treatment should be further investigated.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Cell cycle; Cell death; Homologous recombination; Ionizing radiation; Kinase inhibitor; PARP1/PARP2; Radiosensitivity

PARP Inhibitors Talazoparib and Niraparib Sensitize Melanoma Cells to Ionizing Radiation - Jonuscheit, Stephanie; Jost, Tina; Gajdošová, Fritzi; Wrobel, Maximilian; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (Genes, 2021)
(1) Background: Niraparib and Talazoparib are poly (ADP-ribose) polymerase (PARP) 1/2 inhibitors. It is assumed that combining PARP inhibitors with radiotherapy could be beneficial for cancer treatment. In this study, melanoma cells were treated with Niraparib and Talazoparib in combination with ionizing radiation (IR). (2) Methods: The effects of Talazoparib and Niraparib in combination with IR on cell death, clonogenicity and cell cycle arrest were studied in healthy primary fibroblasts and primary melanoma cells. (3) Results: The melanoma cells had a higher PARP1 and PARP2 content than the healthy fibroblasts, and further increased their PARP2 content after the combination therapy. PARP inhibitors both sensitized fibroblasts and melanoma cells to IR. A clear supra-additive effect of KI+IR treatment was detected in two melanoma cell lines analyzing the surviving fraction. The cell death rate increased in the healthy fibroblasts, but to a larger extent in melanoma cells after combined treatment. Finally, a lower percentage of cells in the radiosensitive G2/M phase is present in the healthy fibroblasts compared to the melanoma cells. (4) Conclusions: Both PARP inhibitors sensitize melanoma cells to IR. Healthy tissue seems to be less affected than melanoma cells. However, the great heterogeneity of the results suggests prior testing of the tumor cells in order to personalize the treatment.
CRIS-Team Scopus Importer:2021-06-18
Keywords: ionizing radiation; kinase inhibitors; PARP

Particle radiosurgery: a new frontier of physics in medicine - Bert, Christoph; Durante, Marco (Physica Medica, 2014)
Radiosurgery was introduced over half a century ago for treatment of intracranial lesions. In more recent years, stereotactic radiotherapy has rapidly advanced and is now commonly used for treatments of both cranial and extracranial lesions with high doses delivered in a few, down to a single fraction. The results of a workshop on Particle radiosurgery: A new frontier of physics in medicine held at Obergurgl, Austria during August 25-29 2013 are summarized in this issue with an overview presented in this paper. The focus was laid on particle radiosurgery but the content also includes current practice in x-ray radiosurgery and the overarching research in radiobiology and motion management for extracranial lesions. The results and discussions showed that especially research in radiobiology of high-dose charged-particles and motion management are necessary for the success of particle radiosurgery.
EVALuna2:18241

Pathologic complete response after induction therapy and surgery is an independed long-term survival prognostic factor in locally advanced non-small cell lung cancer - Schreiner, Waldemar; Dudek, Wojciech; Lettmaier, S.; Rieker, Ralf; Fietkau, Rainer; Sirbu, Horia (2018)
EVALuna2:35736

Pathologic complete response after induction therapy-the role of surgery in stage IIIA/B locally advanced non-small cell lung cancer - Schreiner, Waldemar; Gavrychenkova, Sofiia; Dudek, Wojciech; Rieker, Ralf; Lettmaier, Sebastian; Fietkau, Rainer; Sirbu, Horia (Journal of Thoracic Disease, 2018)
Background: Pathologic complete response (pCR) is dominant prognostic factor determining favorable outcome in locally advanced non-small cell lung cancer (NSCLC) after induction therapy (IT). There is no non-operative diagnostics that adequately estimates the pCR. Aim of this retrospective study was to assess the correlation between clinical and pathological factors in patients with pCR. Methods: Twenty-five patients with pCR after curative lung resection following IT were assessed using univariate and multivariate Cox regression and descriptive analysis. The survival rate was estimated by Kaplan-Meier method. Results: The IT included chemoradiation with median doses of 50.4 Gy (range, 45-59.4 Gy) combined with platinum-based chemotherapy in 23 patients (92%) and induction platinum-based chemotherapy in 2 patients (8%). Clinical tumor stage before IT was IIIA in 21, IIIB in 4 patients. Mean interval between IT and surgery was 8.1±3.0 weeks. Perioperative morbidity and 30-day mortality was 32% and 4%, respectively. There was no significant correlation of pCR and different clinical and pathological factors. The estimated 5-year long-term survival (LTS) and progressive-free survival (PFS) was 57% and 54%, respectively. The median LTS and PFS was not reached. Conclusions: pCR in patients with locally advanced NSCLC following IT is an independent prognostic factor, without correlation with pathological and clinical factors. Non-operative accurate assessment of pCR is currently impossible. Surgical resection enables secure identification of pCR and might improve the patient stratification for additive therapy.
EVALuna2:35733

Pathologic response after induction chemo-immunotherapy with single or double immune checkpoint inhibition in locally advanced head and neck squamous cell carcinoma (HNSCC): Expansion cohorts of the CheckRad-CD8 trial. - Hecht, Markus; Eckstein, Markus; Kallies, Annett; Klautke, Gunther; Illmer, Thomas; von der Grün, Jens; Laban, Simon; Hautmann, Matthias; Tamaskovics, Bálint; Hinke, Axel; Brunner, Thomas; Frey, Benjamin; et al. (JOURNAL OF CLINICAL ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-11-04

Patients with Lupus Erythematosus often have increased Radiosensitivity - Schuster, Barbara; Schenker, Hannah; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Patterns of care analysis for salivary gland cancer: a survey within the German Society of Radiation Oncology (DEGRO) and recommendations for daily practice - von der Grün, Jens; Roedel, Claus; Semrau, Sabine; Balermpas, Panagiotis; Martin, Daniel; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2021)
Background Salivary gland cancer (SGC) is rare and a heterogeneous type of cancer. Prospective randomized trials are lacking. No guideline focusing on standard procedures of radiotherapy (RT) in the treatment of SGC exists. Therefore, we surveyed the members of the German Society of Radiation Oncology (DEGRO) to gain information about current therapeutic strategies of SGC. Methods An anonymous questionnaire was designed and made available on the online platform umfrageonline.com. The corresponding link was sent to all DEGRO members who provided their user data for contact purposes. Alternatively, a PDF printout version was sent. Frequency distributions of responses for each question were calculated. The data were also analyzed by type of institution. Results Sixty-seven responses were received, including answers from 21 university departments, 22 non-university institutions, and 24 radiation oncology practices. Six participants reported that their departments (practice: n = 5, non-university hospital: n = 1) did not treat SGC, and therefore the questionnaire was not completed. Concerning radiation techniques, target volume definition, and concomitant chemotherapy, treatment strategies varied greatly among the participants. Comparing university vs. non-university institutions, university hospitals treat significantly more patients with SGC per year and initiated more molecular pathological diagnostics. Conclusion SGC represents a major challenge for clinicians, as reflected by the inhomogeneous survey results regarding diagnostics, RT approaches, and systemic therapy. Future prospective, multicenter clinical trials are warranted to improve and homogenize treatment of SGC and to individualize treatment according to histologic subtypes and risk factors.
CRIS-Team WoS Importer:2021-09-03

Patterns of lymph node involvement in prostate cancer patients presenting for pelvic and paraaortic stereotactic radiotherapy of nodal metastases - Filimonova, Irina; Weissmann, T.; Mansoorian, S.; Bert, Christoph; Frey, Benjamin; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

PD-L1 is upregulated by radiochemotherapy in rectal adenocarcinoma patients and associated with a favourable prognosis - Hecht, Markus; Buettner-Herold, Maike; Erlenbach-Wuensch, Katharina; Haderlein, Marlen; Croner, Roland; Grützmann, Robert; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (European Journal of Cancer, 2016)
The influence of neoadjuvant radiochemotherapy (RCT) on programmed death-ligand 1 (PD-L1) expression, a predictive marker for programmed cell death protein 1 (PD-1) inhibitor therapy, was studied on tumour and inflammatory cells in rectal adenocarcinoma patients along with its prognostic value.PD-L1 immunohistochemistry was performed on tissue microarrays of 103 pre-RCT biopsies and 159 post-RCT surgical specimens (central tumour, invasive front and normal tissue) of 199 patients. In 63 patients, both samples were available. Proportion and maximum intensity of PD-L1-positive (PD-L1+) cells were evaluated.RCT increased the proportion of PD-L1-expressing cancer cells from 2.1% to 7.8% in the central tumour (p < 0.001) or 9.3% in the invasive front (p < 0.001). Cancer cell PD-L1 on its own could not predict prognosis. High PD-L1 expression on pre-RCT inflammatory cells (maximum intensity: p = 0.048) and post-RCT invasive front inflammatory cells (p = 0.010) correlated with improved no evidence of disease survival. In multivariate analysis, the combination of low PD-L1 in cancer and inflammatory cells was an independent negative prognostic marker for overall survival (OS) pre-RCT (Cox's proportional hazard ratio 0.438, p = 0.045) and in the invasive front post-RCT (Cox's proportional hazard ratio 0.257, p = 0.030).Neoadjuvant RCT is associated with an increased PD-L1 expression in rectal adenocarcinoma patients, which should prompt clinical trials combining radiotherapy and PD-1/PD-L1 pathway blockade. Combined low PD-L1 expression on tumour and inflammatory cells is an independent negative prognostic marker for OS in RCT of rectal adenocarcinoma.
EVALuna2:6814

Penile bulb sparing in prostate cancer radiotherapy: Dose analysis of an in-house MRI system to improve contouring - Boeckelmann, F.; Hammon, Matthias; Lettmaier, S.; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Strahlentherapie und Onkologie, 2019)
ObjectiveThis study aimed to assess the reduction in dose to the penile bulb (PB) achieved by MRI-based contouring following drinking and endorectal balloon (ERB) instructions.Patients and methodsA total of 17prostate cancer patients were treated with intensity-modulated radiation therapy (IMRT) and interstitial brachytherapy (IBT). CT and MRI datasets were acquired back-to-back based on a65cm(3) air-filled ERB and drinking instructions. After rigid co-registration of the imaging data, the CT-based planning target volume (PTV) used for treatment planning was retrospectively compared to an MRI-based adaptive PTV and the dose to the PB was determined in each case. The adapted PTV encompassed acaudally cropped CT-based PTV which was defined on the basis of the MRI-based prostate contour plus an additional 5mm safety margin.ResultsIn the seven-field IMRT treatment plans, the MRI-based adapted PTV achieved mean (D-mean) and maximum (D-max) doses to the PB which were significantly lower (by 7.6Gy and 10.9Gy, respectively; p<0.05) than those of the CT-contoured PTV. For 6patients, the estimated PB D-max (seven-field IMRT and IBT) for the adapted PTV was <70Gy, whereas only 1patient fulfilled this criterium with the CT-based PTV.ConclusionMRI-based contouring and seven-field IMRT-based treatment planning achieved dose sparing to the PB. Whereas the comparison of MRI and CT contouring only relates to external beam radiotherapy (EBRT) sparing, considering EBRT and IBT shows the improvement in PB sparing for the total treatment. ZusammenfassungZielZiel war es, eine Dosisreduktion an der Peniswurzel auf Grundlage einer Magnetresonanztomographie-(MRT-)unterstutzten Konturierung unter Einhaltung eines Trink- und Rektalballonprotokolls (ERB) zu erreichen.Patienten und MethodenInsgesamt wurden 17Patienten mit Prostatakrebs intensitatsmoduliert bestrahlt (IMRT) und erhielten anschlie ss end eine interstitielle Brachytherapie (IBT). Computertomographie- (CT) und MRT-Datensatze wurden kurz nacheinander auf Basis eines 65-cm(3)-ERB- und Trinkprotokolls akquiriert und danach rigide registriert. In beiden Datensatzen wurde jeweils die Peniswurzeldosis bestimmt. Ein CT-basiertes Planungszielvolumen (PTV) wurde fur die Bestrahlungsplanung verwendet und retrospektiv mit einem MRT-basierten adaptiven PTV verglichen. Das adaptive PTV umfasst ein kaudal gekurztes CT-basiertes PTV, welches auf Grundlage einer MRT-basierten Prostatakontur und einem zusatzlichen 5-mm-Sicherheitsraum definiert wurde.ErgebnisseDas MRT-basierte adaptive PTV erzielte bei der 7-Felder-IMRT-Planung 7,6Gy (D-mean) und 10,9Gy (D-max) weniger Dosis an der Peniswurzel als das CT-konturierte PTV. Fur 6Patienten, geplant mit dem adaptiven PTV, war die abgeschatzte Maximaldosis D-max (7-Felder-IMRT+IBT) an der Peniswurzel <70Gy, wohingegen beim CT-basierten PTV nur 1Patient das Kriterium erfullte.SchlussfolgerungDie MRT-basierte Konturierung und die 7-Felder-IMRT-Planung reduzierte die Peniswurzeldosis. Die Gesamtdosis der Peniswurzel bestehend aus der 7-Felder-IMRT- und IBT-Planung zeigte sich reduziert, wobei die MRT- und CT- Konturierungsanalyse nur auf die externe 7-Felder-Bestrahlungsplanung basiert.
CRIS-Team WoS Importer:2019-02-21

Performance of gimbal-based dynamic tumor tracking for treating liver carcinoma - Ziegler, Marc; Brandt, Tobias; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Radiation Oncology, 2018)
BACKGROUND: Since the introduction of tumor tracking in radiotherapy, it is possible to ensure a precise irradiation of moving targets. To follow the tumor movement, most systems rely on the detection of implanted markers and correlation models between the internal and external patient movement. This study reports the clinical workflow and first results of the dynamic tumor tracking (DTT) performance for patients with liver carcinoma at the Vero SBRT system of the University Hospital Erlangen regarding the detection of the internal marker and the changes of the determined correlation models. METHODS: So far 13 liver patients were treated with DTT. For each patient, two fiducial markers (FM), which are monitored with X-rays during treatment, were implanted in the vicinity of the tumor. All patients received a fraction dose of 4-6 Gy with 8 to 12 fractions. Treatment and patient data is evaluated by processing the acquired log-files of the DTT treatment. Based on this, the marker detection and the changes of the correlation model between the internal and external movement is investigated. RESULTS: The median treatment time was 19:42 min. During treatment a median of 173 X-ray stereoscopic images were acquired. The marker detection was successful in 64.6% of the images. The FM detection is independent of the relative angle between the marker and the imager, but shows a dependency on the average intensity surrounding the FM position within the kV images. The number of correlation models needed during treatment increases in the presence of baseline shifts. The comparison of the correlation models shows large differences in the internal-external correlation between the different models acquired for one patient. CONCLUSION: Thirteen liver patients were treated with DTT at the Vero SBRT system and the marker detection was analyzed. Furthermore, the importance of regularly monitoring the internal target motion could be shown, since the correlation between the internal and external motion changes considerably over the course of the treatment.
EVALuna2:36448

Performance of Makerless Tracking for Gimbaled Dynamic Tumor Tracking - Ziegler, Marc; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2019)
Background and Purpose: The purpose of this work is to report the workflow and the accuracy of the new markerless dynamic tumor tracking (MLDTT) method of the Vero 4DRT system introduced with ExacTrac 3.6.1. Material and Methods: Phantom measurements were performed to assess the accuracy of the MLDTT algorithm by using the QA-tool which is provided by the vendor. A patient breathing curve was used as the motion trajectory of the phantom and the target positions detected by the MLDTT algorithm were compared to the defined positions. Furthermore, eight patients have been treated with MLDTT between May 2018 and July 2019. A log-file analysis is used to evaluate MLDTT treatment data. Results: The accuracy of the MLDTT detection is 0.12 mm ± 0.12 mm, 0.12 mm ± 0.11 mm, 0.20 mm ± 0.21 mm for the x-, y-, z-direction, respectively. These values are comparable to the accuracy of marker based DTT at the Vero system. The median treatment time was 21 min 34 seconds and 175 kV images were acquired during treatment for monitoring the target motion. Conclusion: The accuracy of the MLDTT algorithm is comparable to the marker based approach and the accuracy reported for the XSight Lung of the CyberKnife. Eight patients were treated successfully using MLDTT and the treatment times are comparable to a standard DTT treatment.
CRIS-Team Scopus Importer:2019-12-27
Keywords: NSCLC; Real-time monitoring; Stereotactic body radiation therapy; Tumor Tracking

Performance of Marker-less Tracking for Gimbaled Dynamic Tumor Tracking - Ziegler, Marc; Lettmaier, S.; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Permanent LDR prostate brachytherapy: Comprehensive characterization of seed-dynamics within the prostate on a seed-only level - Karius, Andre; Lotter, Michael; Kreppner, Stephan; Schaller, Verena; Lubgan, Dorota; Grigo, Johanna; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Brachytherapy, 2022)
PURPOSE: Seed brachytherapy is a well-established treatment modality for prostate cancer. However, there is still a lack of profound characterizations of seed motions within the prostate. We assessed these dynamics between day 0 and day 30 of brachytherapy. METHODS: We considered 45 patients with 2408 implanted seeds, and performed a 1:1 assignment between their positions on post-plan CT (nominal day 30) and intraoperative ultrasound (day 0). Geometric seed arrangement changes were measured for each patient and the entire collective. The impact of seed strand-lengths and implant regions was investigated. Correlations with patient characteristics were evaluated. We determined corresponding dosimetric effects by calculating common dose metrics. RESULTS: We found a median seed displacement of 4.3 mm [interquartile range: 3.1–6.9 mm], occurring preferentially in superior-inferior direction. Single and double strands moved significantly stronger than strands of higher lengths. Seed dynamics was more pronounced in base (5.6 mm [3.7–10.7 mm]) and apex (6.5 mm [4.1–15.0 mm]) than in the mid-gland (3.8 mm [2.7–5.0 mm]), and less pronounced in peripheral (4.3 mm [3.0–6.7 mm]) than in urethra-near (5.5 mm [3.5–10.7 mm]) regions. Correlations of seed dynamics with prostate volume changes and the number of implanted seeds and needles were found. D90 (dose that 90% of the prostate receives) varied by a median of 3 Gy [-6 to 15 Gy] between treatment plan and post-plan, but >40 Gy for individual patients. CONCLUSIONS: Reducing seed dynamics is important to ensure a high treatment quality. For this, strands containing ≥3 seeds may be useful, implantations in base-, apex-, and urethra-near zone should be avoided, and the number of needles and seeds may be minimized where possible.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Adaptive Brachytherapy; Low-dose-rate prostate brachytherapy; Prostate Cancer; Seed brachytherapy; Seed displacements

Phagocytosis by non-professional Phagocytes - Seeberg, J. C.; Loibl, Monika; Fietkau, Rainer; Distel, Luitpold (2017)
EVALuna2:32894

Phase II Study: Accelerated Partial Breast Irradiation (APBI) on a Linear Accelerator - Ott, Oliver; Schweizer, Claudia; Strnad, Vratislav; Stillkrieg, W.; Lambrecht, U.; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Physical Fitness in Combination with Age is an overwhelming prognostic Factor in Patients with advanced Rectal Cancer - Fitz, Tim; Sörgel, Christopher; Rutzner, Sandra; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Pilot Project for App-based Patient Connection in outpatient Tumor Therapy - Hecht, Markus; Goldbrunner, L.; Kaul, F.; Winkler, S.; Ploner, N.; Lettmaier, Sebastian; Haderlein, Marlen; Kallies, Annett; Pirschel, Wiebke; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Plan robustness analysis for threshold determination of SGRT-based intrafraction motion control in 3DCRT breast cancer radiation therapy - Sauer, Tim-Oliver; Stillkrieg, Willy; Ott, Oliver; Fietkau, Rainer; Bert, Christoph (Radiation Oncology, 2023)
Purpose: The goal of this study was to obtain maximum allowed shift deviations from planning position in six degrees of freedom (DOF), that can serve as threshold values in surface guided radiation therapy (SGRT) of breast cancer patients. Methods: The robustness of conformal treatment plans of 50 breast cancer patients against 6DOF shifts was investigated. For that, new dose distributions were calculated on shifted computed tomography scans and evaluated with respect to target volume and spinal cord dose. Maximum allowed shift values were identified by imposing dose constraints on the target volume dose coverage for 1DOF, and consecutively, for 6DOF shifts using an iterative approach and random sampling. Results: Substantial decreases in target dose coverage and increases of spinal cord dose were observed. Treatment plans showed highly differing robustness for different DOFs or treated area. The sensitivity was particularly high if clavicular lymph nodes were irradiated, for shifts in lateral, vertical, roll or yaw direction, and showed partly pronounced asymmetries. Threshold values showed similar properties with an absolute value range of 0.8 mm to 5 mm and 1.4° to 5°. Conclusion: The robustness analysis emphasized the necessity of taking differences between DOFs and asymmetrical sensitivities into account when evaluating the dosimetric impact of position deviations. It also highlighted the importance of rotational shifts, especially if clavicular lymph nodes were irradiated. A practical approach of determining 6DOF shift limits was introduced and a set of threshold values applicable for SGRT based patient motion control was identified.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Intrafraction motion; Probabilistic dose evaluation; Surface guided radiation therapy; Treatment plan robustness

PML-nuclear bodies decrease with age and their stress response is impaired in aged individuals - Wenger, Barbara; Schwegler, Manuela; Brunner, Michaela; Daniel, Christoph; Schmidt, Manfred; Fietkau, Rainer; Distel, Luitpold (BMC Geriatrics, 2014)
Promyelocytic leukemia nuclear bodies (PML-NBs) have been depicted as structures which are involved in processing cell damages and DNA double-strand break repairs. The study was designed to evaluate differences in patients' PML-NBs response to stress factors like a cancerous disease and ionizing radiation exposure dependent on age.In order to clarify the role of PML-NBs in the aging process, we examined peripheral blood monocytes of 134 cancer patients and 41 healthy individuals between 22 and 92 years of age, both before and after in vitro irradiation. Additionally, we analyzed the samples of the cancer patients after in vivo irradiation. Cells were immunostained and about 1600 cells per individual were analyzed for the presence of PML- and ?H2AX foci.The number of existing PML-NBs per nucleus declined with age, while the number of ?H2AX foci increased with age. There was a non-significant trend that in vivo irradiation increased the number of PML-NBs in cells of young study participants, while in older individuals PML-NBs tended to decrease. It can be assumed that PML-NBs decrease in number during the process of aging.The findings suggest that there is a dysfunctional PML-NBs stress response in aged cells.
EVALuna2:18179

Positive factors on survival of head and neck cancer of unknown primary: what the clinician can do - Khalil, Firas; Koch, Michael; Iro, Heinrich; Sievert, Matti; Haderlein, Marlen; Semrau, Sabine; Fietkau, Rainer; Agaimy, Abbas; Scherl, Claudia (Acta Oto-Laryngologica, 2023)
Background: Management of patients with head and neck cancer of unknown primary (HNCUP) is challenging. Aims/Objectives: To provide a long-term analysis focusing on protective survival factors for clinical decision-making. Furthermore, the prognostic value of the current N classification system was evaluated. Material and methods: We retrospectively analyzed patients with HNCUP between 2003 and 2016. Univariate and multivariate analyses were used to investigate predictors of overall survival (OS). Results: A primary tumor was found in 67 of 290 patients with suspected HNCUP, leaving after exclusion 141 HNCUP cases for analysis, who received multi-step therapy (MST) (n = 108) or single therapy (n = 28). Chemotherapy (CT) (n = 101), curative MST, ≤3 positive lymph nodes (LN) (n = 33), squamous cell carcinoma (SCC) (n = 123), HPV+ (n = 21), M0 (n = 70) increased OS by 21.8%, 24.4%, 12.7%, 6.8%, 18.7%, 29.6%, respectively. 5- and 10-year OS was 78.1%/66.6%. The number of metastatic LNs predicted OS is better than N classification. Conclusion and significance: Aspects for clinical decision-making: Curative MST and SCC histology were the most significant predictors for improved OS. Categorizing LN into 1, 2-3, and >3 LNs was more significant than the traditional N classification. The addition of CT to curative MST has a stronger impact on survival than HPV and N classifications.
CRIS-Team Scopus Importer:2023-10-27
Keywords: cancer; cancer of unknown primary; CUP; head and neck; hNCUP; hNSCC; squamous cell carcinoma; survival

Possibilities of a Seed Control after the Implantation by using MRI and Deep Learning-based QSM Reconstruction - Grigo, Johanna; Karius, Andre; Hanspach, Jannis; Weissmann, Thomas; Laun, Frederik Bernd; Strnad, Vratislav; Putz, Florian; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Post-neoadjuvant treatment with capecitabine and trastuzumab emtansine in breast cancer patients—sequentially, or better simultaneously? - Piroth, Marc D.; Krug, David; Sedlmayer, Felix; Duma, Marciana Nona; Baumann, René; Budach, Wilfried; Dunst, Jürgen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Hehr, Thomas; et al. (Strahlentherapie und Onkologie, 2020)
Purpose: Following neoadjuvant chemotherapy for breast cancer, postoperative systemic therapy, also called post-neoadjuvant treatment, has been established in defined risk settings. We reviewed the evidence for sequencing of postoperative radiation and chemotherapy, with a focus on a capecitabine and trastuzumab emtansine (T-DM1)-based regimen. Methods: A systematic literature search using the PubMed/MEDLINE/Web of Science database was performed. We included prospective and retrospective reports published since 2015 and provided clinical data on toxicity and effectiveness. Results: Six studies were included, five of which investigated capecitabine-containing regimens. Of these, four were prospective investigations and one a retrospective matched comparative analysis. One randomized prospective trial was found for T‑DM1 and radiotherapy. In the majority of these reports, radiation-associated toxicities were not specifically addressed. Conclusion: Regarding oncologic outcome, the influence of sequencing radiation therapy with maintenance capecitabine chemotherapy in the post-neoadjuvant setting is unclear. Synchronous administration of capecitabine is feasible, but reports on possible excess toxicities are partially conflicting. Dose reduction of capecitabine should be considered, especially if normofractionated radiotherapy is used. In terms of tolerance, hypofractionated schedules seem to be superior in terms of toxicity in concurrent settings. T‑DM1 can safely be administered concurrently with radiotherapy.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Breast cancer; Capecitabine; Radiochemotherapy; Radiotherapy; T‑DM1

Pradictive Character of Immunophenotyping in peripheral Blood in Patients treated with PD-1 Immunocheckpoint Inhibitors with and without Radiotherapy (Prospective Phase IV Study ST-ICI) - Hecht, Markus; Donaubauer, Anna-Jasmina; Harrer, A.; Rutzner, Sandra; Becker, I.; Lettmaier, S.; Haderlein, Marlen; Wolf, W.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36500

Predictive character of peripheral blood immunophenotype before and during treatment with PD-1 immune checkpoint inhibitors (interim analysis of the prospective phase IV ST-ICI trial) - Hecht, Markus; Harrer, A.; Rutzner, Sandra; Lettmaier, S.; Wolf, W.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
EVALuna2:33777

Predictive Value of Multiparametric MRI for Response to Single-Cycle Induction Chemo-Immunotherapy in Locally Advanced Head and Neck Squamous Cell Carcinoma - Hellwig, Konstantin; Ellmann, Stephan; Eckstein, Markus; Wiesmüller, Marco; Rutzner, Sandra; Semrau, Sabine; Frey, Benjamin; Gaipl, Udo; Hartmann, Arndt; Iro, Heinrich; Fietkau, Rainer; Uder, Michael; et al. (Frontiers in Oncology, 2021)
Objectives
CRIS-Team WoS Importer:2021-11-19

Predictors for occlusion of cerebral AVMs following radiation therapy : Radiation dose and prior embolization, but not Spetzler-Martin grade - Knippen, Stefan; Putz, Florian; Semrau, Sabine; Lambrecht, Ulrike; Knippen, Arzu; Buchfelder, Michael; Schlaffer, Sven-Martin; Struffert, Tobias; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
BACKGROUND: Intracranial arteriovenous malformations (AVMs) may show a harmful development. AVMs are treated by surgery, embolization, or radiation therapy. OBJECTIVE: This study investigated obliteration rates and side effects in patients with AVMs treated by radiation therapy. METHODS: A total of 40 cases treated between 2005 and 2013 were analyzed. Single-dose stereotactic radiosurgery (SRS) was received by 13 patients and 27 received hypofractionated stereotactic radiation therapy (HSRT). In 20 patients, endovascular embolization had been performed prior to irradiation and 24 patients (60 %) had a history of previous intracranial hemorrhage. RESULTS: Treatment resulted in complete obliteration (CO) in 23/40 cases and partial obliteration in 8/40. CO was achieved in 85 % of patients receiving SRS compared to 44 % of those receiving HSRT. In the HSRT group, a first indication of an influence of AVM volume on obliteration rate was found. Equivalent 2 Gy fraction doses (EQD2) >70 Gy showed an obliteration rate of 50 %. Prior embolization was significantly associated with a higher portion of CO (p = 0.032). Median latency period (24.2 vs. 26 months) until CO was similar in both groups (SRS vs. HSRT). The rate of intracranial hemorrhage in patients with no prior bleeding events was 0 %. CONCLUSION: Excellent obliteration rates were achieved by SRS. Consistent with the literature, this data analysis suggests that the results of HSRT are volume-dependent. Furthermore, regimens with EQD2 doses >70 Gy appear more likely to achieve obliteration than schemes with lower doses. The findings indicate that radiation therapy does not increase the risk of bleeding. Prior embolization may have a good prognostic impact.
EVALuna2:32909

Predictors of long-term survival following radical treatment of oligometastatic NSCLC with cerebral metastases - Hirschmann, Eva; Zoske, Hanno; Weissmann, T.; Lettmaier, S.; Filimonova, I.; Fietkau, Rainer; Putz, Florian (2018)
EVALuna2:36501

Preoperative chemoradiotherapy and postoperative chemotherapy with fluorouracil and oxaliplatin versus fluorouracil alone in locally advanced rectal cancer: initial results of the German CAO/ARO/AIO-04 randomised phase 3 trial - Roedel, Claus; Liersch, Torsten; Becker, Heinz; Fietkau, Rainer; Hohenberger, Werner; Hothorn, Torsten; Graeven, Ullrich; Arnold, Dirk; Lang-Welzenbach, Marga; Raab, Hans-Rudolf; Suelberg, Heiko; Wittekind, Christian; et al. (Lancet Oncology, 2012)
BACKGROUND: Preoperative chemoradiotherapy, total mesorectal excision surgery, and adjuvant chemotherapy with fluorouracil is the standard combined modality treatment for rectal cancer. With the aim of improving disease-free survival (DFS), this phase 3 study (CAO/ARO/AIO-04) integrated oxaliplatin into standard treatment. METHODS: This was a multicentre, open-label, randomised, phase 3 study in patients with histologically proven carcinoma of the rectum with clinically staged T3-4 or any node-positive disease. Between July 25, 2006, and Feb 26, 2010, patients were randomly assigned to two groups: a control group receiving standard fluorouracil-based combined modality treatment, consisting of preoperative radiotherapy of 50·4 Gy plus infusional fluorouracil (1000 mg/m(2) days 1-5 and 29-33), followed by surgery and four cycles of bolus fluorouracil (500 mg/m(2) days 1-5 and 29; fluorouracil group); and an experimental group receiving preoperative radiotherapy of 50·4 Gy plus infusional fluorouracil (250 mg/m(2) days 1-14 and 22-35) and oxaliplatin (50 mg/m(2) days 1, 8, 22, and 29), followed by surgery and eight cycles of adjuvant chemotherapy with oxaliplatin (100 mg/m(2) days 1 and 15), leucovorin (400 mg/m(2) days 1 and 15), and infusional fluorouracil (2400 mg/m(2) days 1-2 and 15-16; fluorouracil plus oxaliplatin group). Randomisation was done with computer-generated block-randomisation codes stratified by centre, clinical T category (cT1-4 vs cT4), and clinical N category (cN0 vs cN1-2) without masking. DFS is the primary endpoint. Secondary endpoints, including toxicity, compliance, and histopathological response are reported here. Safety and compliance analyses included patients as treated, efficacy endpoints were analysed according to the intention-to-treat principle. This study is registered with ClinicalTrials.gov, number NCT00349076. FINDINGS: Of the 1265 patients initially enrolled, 1236 were evaluable (613 in the fluorouracil plus oxaliplatin group and 623 in the fluorouracil group). Preoperative grade 3-4 toxic effects occurred in 140 (23%) of 606 patients who actually received fluorouracil and oxaliplatin during chemoradiotherapy and in 127 (20%) of 624 patients who actually received fluorouracil chemoradiotherapy. Grade 3-4 diarrhoea was more common in those who received fluorouracil and oxaliplatin during chemoradiotherapy than in those who received fluorouracil during chemoradiotherapy (73 patients [12%] vs 52 patients [8%]), as was grade 3-4 nausea or vomiting (23 [4%] vs nine [1%]). 516 (85%) of the 606 patients who received fluorouracil and oxaliplatin-based chemoradiotherapy had the full dose of chemotherapy, and 571 (94%) had the full dose of radiotherapy; as did 495 (79%) and 601 (96%) of 624 patients who received fluorouracil-based chemoradiotherapy, respectively. A pathological complete response was achieved in 103 (17%) of 591 patients who underwent surgery in the fluorouracil and oxaliplatin group and in 81 (13%) of 606 patients who underwent surgery in the fluorouracil group (odds ratio 1·40, 95% CI 1·02-1·92; p=0·038). In the fluorouracil and oxaliplatin group, 352 (81%) of 435 patients who began adjuvant chemotherapy completed all cycles (with or without dose reduction), as did 386 (83%) of 463 patients in the fluorouracil group. INTERPRETATION: Inclusion of oxaliplatin into modified fluorouracil-based combined modality treatment was feasible and led to more patients achieving a pathological complete response than did standard treatment. Longer follow-up is needed to assess DFS. FUNDING: German Cancer Aid (Deutsche Krebshilfe).
EVALuna2:5332

Prerequisites for the clinical implementation of a markerless SGRT-only workflow for the treatment of breast cancer patients - Sauer, Tim-Oliver; Ott, Oliver; Lahmer, Godehard; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2022)
Purpose: A markerless workflow for the treatment of breast cancer patients has been introduced and evaluated retrospectively. It includes surface-guided radiation therapy (SGRT)-only positioning for patients with small cone beam CT (CBCT) position corrections during the first five fractions. Prerequisites and the frequency of its clinical application were evaluated, as well as potential benefits in terms of treatment time and dose savings, the frequency of CBCT scans, and the accuracy of the positioning. Methods: A group of 100 patients treated with the new workflow on two Versa HD linacs has been compared to a matched control group of patients treated with the former workflow, which included prepositioning with skin markings and lasers, SGRT and daily CBCT. The comparison was based on the evaluation of logfiles. Results: Of the patients treated with the new workflow, 40% did not receive daily CBCT scans. This resulted in mean time savings of 97 s, 166 s and 239 s per fraction for the new workflow, for patients treated without daily CBCT and for SGRT-only fractions, respectively, when compared to the old workflow. Dose savings amounted to a weighted computed tomography dose index reduction of CTDIW = 2.56 cGy on average for normofractionated treatment and weekly CBCTs, while for patients not treated with daily CBCT, SGRT-based positioning accuracy was 5.2 mm for the mean translational magnitude, as evaluated by CBCT. Conclusion: For 40% of the patients, after five fractions with small CBCT corrections, the workflow could be changed to SGRT-only positioning with weekly CBCT. This leads to imaging dose and time savings and thus also reduced intrafraction motion, potentially increased patient throughput and patient comfort, while assuring appropriate positioning accuracy.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Breast neoplasms; Interfraction motion management; Intrafraction motion management; Markerless radiation therapy; Surface-guided radiation therapy

Pretreatment vitamin D levels are associated with improved overall survival following combined chemoradiotherapy - Putz, Florian; Distel, Luitpold; Lettmaier, S.; Weissmann, T.; Filimonova, I.; Fietkau, Rainer (2018)
EVALuna2:36489

Primary glioblastoma multiforme tumors and recurrence : Comparative analysis of the danger signals HMGB1, HSP70, and calreticulin - Muth, Carolin; Ruebner, Yvonne; Semrau, Sabine; Rühle, Paul-Friedrich; Frey, Benjamin; Strnad, Annedore; Buslei, Rolf; Fietkau, Rainer; Gaipl, Udo (Strahlentherapie und Onkologie, 2016)
Glioblastoma multiforme (GBM) is the most common and aggressive brain tumor. Despite improved multimodal therapies, the tumor recurs in most cases. Diverging patient survival suggests great tumor heterogeneity and different therapy responses. Danger signals such as high-mobility group box protein 1 (HMGB1), heat shock protein 70 (HSP70), and calreticulin (CRT) are biomarker candidates, due to their association with tumor progression versus induction of antitumor immune responses. Overexpression of these danger signals has been reported for various types of tumors; however, their role in GBM is still elusive. A direct comparison of their expression in the primary tumor versus the corresponding relapse is still lacking for most tumor entities.We therefore performed an expression analysis by immunohistochemistry of the danger signals HMGB1, HSP70, and CRT in primary tumors and the corresponding relapses of 9 patients with de novo GBM.HMGB1 was highly expressed in primary tumors with a significant reduction in the respective relapse. The extracellular HSP70 expression was significantly increased in the relapse compared to the primary tumor. CRT was generally highly expressed in the primary tumor, with a slight increase in the relapse.The combination of a decreased expression of HMGB1, an increased expression of extracellular HSP70, and an increased expression of CRT in the relapse seems to be beneficial for patient survival. HMGB1, extracellular HSP70, and CRT could be taken into concerted consideration as potential biomarkers for the prognosis of patients with GBM.
EVALuna2:7316

Primary results of the phase II CheckRad-CD8 trial: First-line treatment of locally advanced head and neck squamous cell carcinoma (HNSCC) with double checkpoint blockade and radiotherapy dependent on intratumoral CD8+T-cell infiltration. - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias G.; Brunner, Thomas; Tamaskovics, Bálint; Hinke, Axel; Frey, Benjamin; et al. (ASCO 2021 Annual Meeting, 2021)
CRIS-Team WoS Importer:2021-11-26

Primary Results of the phase II CheckRad-CD8 Trial: First-Line Treatment of locally advanced Head and Neck Tumors with double Checkpoint Blockade and Radiotherapy dependent on intratumoral CD8+T-Cell Infiltration - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; Von Der Gruen, J.; Illmer, T.; Klautke, G.; Laban, S.; Hautmann, M.; Brunner, T.; Tamaskovics, B.; Hinke, A.; Frey, Benjamin; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Process failure mode and effects analysis for external beam radiotherapy: Introducing a literature-based template and a novel action priority - Kornek, Dominik; Bert, Christoph (Zeitschrift für Medizinische Physik, 2024)
Purpose: The first aim of the study was to create a general template for analyzing potential failures in external beam radiotherapy, EBRT, using the process failure mode and effects analysis (PFMEA). The second aim was to modify the action priority (AP), a novel prioritization method originally introduced by the Automotive Industry Action Group (AIAG), to work with different severity, occurrence, and detection rating systems used in radiation oncology. Methods and materials: The AIAG PFMEA approach was employed in combination with an extensive literature survey to develop the EBRT-PFMEA template. Subsets of high-risk failure modes found through the literature survey were added to the template where applicable. Our modified AP for radiation oncology (RO AP) was defined using a weighted sum of severity, occurrence, and detectability. Then, Monte Carlo simulations were conducted to compare the original AIAG AP, the RO AP, and the risk priority number (RPN). The results of the simulations were used to determine the number of additional corrective actions per failure mode and to parametrize the RO AP to our department's rating system. Results: An EBRT-PFMEA template comprising 75 high-risk failure modes could be compiled. The AIAG AP required 1.7 additional corrective actions per failure mode, while the RO AP ranged from 1.3 to 3.5, and the RPN required 3.6. The RO AP could be parametrized so that it suited our rating system and evaluated severity, occurrence, and detection ratings equally to the AIAG AP. Conclusions: An adjustable EBRT-PFMEA template is provided which can be used as a practical starting point for creating institution-specific templates. Moreover, the RO AP introduces transparent action levels that can be adapted to any rating system.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Action priority (AP); External beam radiation therapy (EBRT); Process failure mode and effects analysis (PFMEA); Prospective risk assessment; Template

Prof. Dr. med. Thomas G. Wendt Director of the Department of Radiation Oncology at the University Hospital Jena on his 65th birthday - Wiezorek, Tilo; Grabenbauer, Gerhard G.; Sauer, Rolf (Strahlentherapie und Onkologie, 2014)
EVALuna2:18210

Profound survival benefit with concurrent chemotherapy: insights from a Chinese phase III trial in older patients with esophageal cancer - Schweizer, Claudia; Fietkau, Rainer; Putz, Florian (Strahlentherapie und Onkologie, 2022)
CRIS-Team WoS Importer:2022-04-01

Prognostic and predictive value of PD-L1 expression and tumour infiltrating lymphocytes (TiLs) in locally advanced NSCLC treated with simultaneous radiochemotherapy in the randomized, multicenter, phase III German Intergroup lung Trial (GILT) - Tufman, Amanda; Neumann, Jens; Manapov, Farkhad; Sellmer, Laura; Jung, Andreas; Kauffmann-Guerrero, Diego; Kahnert, Kathrin; Mertsch, Pontus; Borgmeier, Astrid; Semrau, Sabine; Rittmeyer, Achim; Ulm, Bernhard; et al. (Lung Cancer, 2021)
Objectives: Immune checkpoint inhibition after radiochemotherapy (RTCT) has become a new standard of care for locally advanced non-small cell lung cancer with programmed death-ligand 1 (PD-L1) expression. However, little is known about the prognostic role of immune response markers in this setting. We analysed PD-L1 expression and tumour infiltrating lymphocytes (TiLs) in tumour biopsies from the multicenter German Intergroup Lung Trial (GILT), which previously randomised patients with stage III NSCLC to RTCT with or without consolidation chemotherapy. Materials and methods: We retrospectively analyzed tumour biopsies from patients treated in the GILT trial. PD-L1 expression was analysed using the Ventana SP263 assay and TiL score (low, intermediate, high) and pattern (excluded, inflamed, desert) were assessed. The primary endpoint of the biomarker analysis was PFS in patients with PD-L1 ≥ 1% vs. PD-L1 < 1% NSCLC. Secondary endpoints explored the prognostic relevance of additional PD-L1 expression levels and TiL score and pattern. Results: Biopsies were available from 92 patients treated with RTCT. Patients with available tumor tissue did not differ significantly from the whole study population. PD-L1 scores from 78 samples were available for analysis. There was no difference in PFS in the PD-L1 < 1% vs. PD-L1 ≥ 1% subgroups. TiL score was available in 66 patients. Patients with high TiL score showed favourable overall survival compared to the low TiL subgroup. This trend was most pronounced in those patients treated with consolidative chemotherapy. Conclusion: In this analysis, PD-L1 expression did not correlate with PFS following RTCT. However, patients with TiLs > 10% were found to have longer overall survival, especially for those patients treated with consolidation chemotherapy after the end of RTCT. Further analyses to explore the prognostic and predictive relevance of TiLs in the context of consolidative checkpoint inhibition with durvalumab are required.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Checkpoint inhibition; Chemoradiotherapy; PDL1; Prognostic factors; TiLs

Prognostic Importance of the CD8-based Immune Status Inflamed, immune-Excluded, and immune Desert in Head and Neck Cancer Patients can be further subdivided by regulatory T Cells - Echarti, A.; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Prognostic role of patient gender in limited-disease small-cell lung cancer treated with chemoradiotherapy - Roengvoraphoj, Olarn; Eze, Chukwuka; Niyazi, Maximilian; Li, Minglun; Hildebrandt, Guido; Fietkau, Rainer; Belka, Claus; Manapov, Farkhad (Strahlentherapie und Onkologie, 2017)
BACKGROUND: Previous studies have demonstrated that female gender could be a prognostic factor in limited-disease (LD) small-cell lung cancer (SCLC), but the correlation between patient gender and survival parameters remains unclear. PATIENTS AND METHODS: Data from 179 LD SCLC patients treated with definitive chemoradiotherapy (CRT) were reviewed. Influence of patient gender on time to progression (TTP), local control (LC), brain metastasis-free (BMFS), distant metastasis-free (DMFS) and overall survival (OS) was analysed. RESULTS: Definitive CRT was completed by 179 (110 men/69 women) patients. Of these, 68 (38%; 34 men/34 women) patients were treated in concurrent and 111 (62%; 76 men/35 women) in sequential mode. Prophylactic cranial irradiation (PCI) was subsequently applied in 70 (39%; 36 men/34 women) patients with partial or complete response after CRT. Median OS was 20 (95% confidence interval [CI] 10-22) and 14 (95% CI 10-18) months in female and male patients, respectively (p = 0.021). In subgroups defined by remission status (complete and partial response) after CRT, an OS benefit for females compared to males was also detected. There was no correlation between patient gender and TTP, LC or DMFS, and no difference in OS in the female and male subgroups treated with PCI. The incidence of metachronous brain metastases (BMs) in the male and female subgroups differed significantly (40/110 men vs. 18/69 women, p = 0.03). Also, mean BMFS was significantly longer in women (p = 0.023). Patient gender also significantly correlated with OS on multivariate analysis after adjustment for other prognostic factors (p = 0.04, HR 1.38, 95% CI 1.08-1.92). CONCLUSION: In this heterogeneous LD SCLC patient cohort treated with definitive CRT, female gender was significantly associated with longer BMFS and OS, as well as with a lower incidence of metachronous brain failure.
EVALuna2:32912

Prognostic Significance of CD8-Based Immune Status Inflamed, Immune-Excluded and Immune Desert in Head and Neck Tumors can be Further Subdivided by Regulatory T Cells - Distel, Luitpold; Echarti, Alessia; Fietkau, Rainer; Hecht, Markus (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Prognostic Significance of immune-associated Side Effects under Radioimmunotherapy and Immunotherapy alone in Patients of the prospective ST-ICI Study - Schweizer, C.; Schubert, P.; Haderlein, Marlen; Rutzner, Sandra; Semrau, Sabine; Donaubauer, Anna-Jasmina; Becker, Ina; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Hecht, Markus (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Prognostic subdivision of ypT3 rectal tumours according to extension beyond the muscularis propria - Merkel, Susanne; Weber, K.; Schellerer, Vera; Göhl, Jonas; Fietkau, Rainer; Agaimy, Abbas; Hohenberger, Werner; Hermanek, Peter (British Journal of Surgery, 2014)
The subdivision of T3 in rectal carcinoma according to the depth of invasion into perirectal fat has been recommended in the TNM Supplement since 1993. This study assessed the prognostic impact of this pathological staging in tumours removed after neoadjuvant chemoradiotherapy (ypT3).Data from patients with ypT3 rectal carcinoma (less than 12 cm from the anal verge) treated with neoadjuvant chemoradiation and total mesorectal excision were analysed. Tumour category ypT3 was subdivided into ypT3a (5 mm or less) and ypT3b (more than 5 mm), based on histological measurements of maximal tumour invasion beyond the outer border of the muscularis propria.Important differences between ypT3a (81 patients) and ypT3b (43) were found in 5-year rates of locoregional recurrence (7 versus 18 per cent; P = 0·049), distant metastasis (20 versus 41 per cent; P = 0·002), disease-free survival (73 versus 47 per cent; P = 0·001), overall survival (79 versus 74 per cent; P = 0·036) and cancer-related survival (81 versus 74 per cent; P = 0·007). In Cox regression analyses, the ypT3 subclassification was identified as an independent prognostic factor for disease-free (ypT3b: hazard ratio (HR) 2·13, 95 per cent confidence interval 1·16 to 3·89; P = 0·014), observed (ypT3b: HR 2·02, 1·05 to 3·87; P = 0·035) and cancer-related (ypT3b: HR 2·46, 1·20 to 5·04; P = 0·014) survival. Extramural venous invasion was found to be an additional prognostic factor, but the pathological node category after chemoradiotherapy (ypN) did not influence survival.In ypT3 rectal carcinomas, the proposed subclassification is superior to ypN in predicting prognosis.
EVALuna2:6571

Prognostic Value of Homotypic Cell Internalization by Nonprofessional Phagocytic Cancer Cells - Schwegler, Manuela; Wirsing, Anna Maria; Schenker, Hannah; Ott, Laura; Ries, Johannes; Buettner-Herold, Maike; Fietkau, Rainer; Putz, Florian; Distel, Luitpold (BioMed Research International, 2015)
Background. In this study, we investigated the prognostic role of homotypic tumor cell cannibalism in different cancer types. Methods. The phenomenon of one cell being internalized into another, which we refer to as "cell-in-cell event," was assessed in 416 cases from five head and neck cancer cohorts, as well as one anal and one rectal cancer cohort. The samples were processed into tissue microarrays and immunohistochemically stained for E-cadherin and cleaved caspase-3 to visualize cell membranes and apoptotic cell death. Results. Cell-in-cell events were found in all of the cohorts. The frequency ranged from 0.7 to 17.3 cell-in-cell events per mm(2). Hardly any apoptotic cells were found within the cell-in-cell structures, although apoptotic cell rates were about 1.6 to two times as high as cell-in-cell rates of the same tissue sample. High numbers of cell-in-cell events showed adverse effects on patients' survival in the head and neck and in the rectal cancer cohorts. In multivariate analysis, high frequency was an adverse prognostic factor for overall survival in patients with head and neck cancer (p = 0.008). Conclusion. Cell-in-cell events were found to predict patient outcomes in various types of cancer better than apoptosis and proliferation and might therefore be used to guide treatment strategies.
EVALuna2:18246

Progress Patterns under Radioimmunotherapy - clinical Evaluation of the prospective STICI Study - Schubert, Philipp; Schweizer, Claudia; Roesch, Johannes; Haderlein, Marlen; Rutzner, Sandra; Semrau, Sabine; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Hecht, Markus (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Proliferating non-professional Phagocytes are able to generate Cell-in-Cell Structures - Hofmann, Andrea; Seeberg, J.; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36485

Proliferating non-professional Phagocytes to generate Cell-in-Cell Structures - Hofmann, Andrea; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Prospective Assessment of the Inflammation Parameters in Blood Counts and Blood Serum as prognostic/predictive Parameters for Treatment with Immune Checkpoint-Inhibitors - Schweizer, Claudia; Haderlein, Marlen; Schubert, Philipp; Zhou, Jianguo; Semrau, Sabine; Rutzner, Sandra; Gostian, Antoniu-Oreste; Frey, Benjamin; Donaubauer, Anna-Jasmina; Eckstein, Markus; Becker, Ina; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Prospective development and validation of a liquid immune profile-based signature (LIPS) to predict response of patients with recurrent/metastatic cancer to immune checkpoint inhibitors - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Eckstein, Markus; Sun, Roger; Ma, Hu; Schubert, Philipp; Schweizer, Claudia; Fietkau, Rainer; Deutsch, Eric; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background The predictive power of novel biological markers for treatment response to immune checkpoint inhibitors (ICI) is still not satisfactory for the majority of patients with cancer. One should identify valid predictive markers in the peripheral blood, as this is easily available before and during treatment. The current interim analysis of patients of the ST-ICI cohort therefore focuses on the development and validation of a liquid immune profile-based signature (LIPS) to predict response of patients with metastatic cancer to ICI targeting the programmed cell death protein 1 (PD-1)/programmed cell death-ligand 1 (PD-L1) axis. Methods A total of 104 patients were prospectively enrolled. 54 immune cell subsets were prospectively analyzed in patients' peripheral blood by multicolor flow cytometry before treatment with ICI (pre-ICI; n=89), and after the first application of ICI (n=65). Pre-ICI, patients were randomly allocated to a training (n=56) and a validation cohort (n=33). Univariate Cox proportional hazards regression analysis and least absolute shrinkage and selection operator Cox model were used to create a predictive immune signature, which was also checked after the first ICI, to consider the dynamics of changes in the immune status. Results Whole blood samples were provided by 89 patients pre-ICI and by 65 patients after the first ICI. We identified a LIPS which is based on five immune cell subtypes: CD14 high monocytes, CD8+/PD-1 + T cells, plasmacytoid dendritic cells, neutrophils, and CD3 + /CD56 + /CD16 + natural killer (NK)T cells. The signature achieved a high accuracy (C-index 0.74 vs 0.71) for predicting overall survival (OS) benefit in both the training and the validation cohort. In both cohorts, the low-risk group had significantly longer OS than the high-risk group (HR 0.26, 95% CI 0.12 to 0.56, p=0.00025; HR 0.30, 95% CI 0.10 to 0.91, p=0.024, respectively). Regarding the whole cohort, LIPS also predicted progression-free survival (PFS). The identified LIPS was not affected by clinicopathological features with the exception of brain metastases. NKT cells and neutrophils of the LIPS can be used as dynamic predictive biomarkers for OS and PFS after first administration of the ICI. Conclusion Our study identified a predictive LIPS for survival of patients with cancer treated with PD-1/PD-L1 ICI, which is based on immune cell subsets in the peripheral whole blood. Trial registration number NCT03453892.
CRIS-Team Scopus Importer:2021-03-05
Keywords: biomarkers; immunotherapy; programmed cell death 1 receptor; tumor; tumor biomarkers; tumor microenvironment

Prospective Evaluation of All-lesion Versus Single-lesion Radiotherapy in Combination With PD-1/PD-L1 Immune Checkpoint Inhibitors - Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Frey, Benjamin; Schweizer, Claudia; Haderlein, Marlen; Lettmaier, Sebastian; Semrau, Sabine; Gostian, Antoniu Oreste; Zhou, Jianguo; Gaipl, Udo; Fietkau, Rainer; et al. (Frontiers in Oncology, 2020)
Background: Local ablative treatments improve survival in patients with oligometastatic disease in addition to chemotherapy. The application of immune checkpoint inhibitors prolonged patients’ survival in different tumor entities. This raises the question if patients still benefit from intensified local treatments in combination with a more efficient systemic treatment with immune checkpoint inhibitors. Methods: The prospective non-interventional ST-ICI trial investigates treatment with PD-1/PD-L1 (Programmed cell death protein 1/Programmed cell death 1 ligand 1) immune checkpoint inhibitors and radiotherapy in different tumor entities. Patients who started radiotherapy and immunotherapy concomitantly were included in this interim analysis. In this cohort patients with all-lesion radiotherapy (all tumor lesions irradiated, al-RT) were compared to patients with radiotherapy to only a single of their tumor lesions (single-lesion radiotherapy, sl-RT). Endpoints of the interim analysis were progression-free survival (PFS), overall survival (OS) and time to progression (TTP). Results: A total of 104 patients were registered between April 2017 and August 2019. Fifty patients started immune checkpoint inhibitor treatment and radiotherapy concomitantly and were included. Most frequent tumor entities were non-small cell lung cancer (62%) followed by head and neck squamous cell cancer (26%). Most frequent location of radiotherapy was lung (34%) and central nervous system (20%). Median duration of follow-up was 8.6 months beginning with first administration of the immune-checkpoint-inhibitor. Median PFS was 9.2 months (95% CI, 5.8 – 12.6) in the al-RT group and 3.0 months (95% CI, 2.5 – 3.5) in the sl-RT group (p<0.001). Median OS was 11.6 months (95% CI, 8.1 - 15.1) in the al-RT group and 4.2 months (95% CI, 3.0 - 5.4) in the sl-RT group (p=0.007). Median TTP was not reached in the al-RT group compared to 4.6 months (95% CI, 1.1–8.0) in the sl-RT group (p=0.028). Univariate Cox regression analyses computed tumor entity, histology, central nervous system metastases, immunotherapy drug and al-RT as predictors of OS (with an effect p-value of ≤ 0.1). In the multivariable analysis only tumor entity and al-RT remained prognostic factors for OS. Conclusion: Patients with PD-1/PD-L1 immune checkpoint inhibitor therapy benefit from local radiotherapy to all known lesions compared to single-lesion radiotherapy regarding PFS and OS.
CRIS-Team Scopus Importer:2020-11-20
Keywords: all-lesion; immune checkpoint inhibitors; immunotherapy; oligometastatic; radiotherapy; single-lesion

Prospective Evaluation of CD45RA+/CCR7- Effector Memory T (TEMRA) Cell Subsets in Patients with Primary and Secondary Brain Tumors during Radiotherapy of the Brain within the Scope of the Prospective Glio-CMV-01 Clinical Trial - Scheer, Ilka; Becker, Ina; Schmitter, Charlotte; Semrau, Sabine; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Donaubauer, Anna-Jasmina (Cells, 2023)
Radiotherapy (RT) of the brain is a common treatment for patients with high-grade gliomas and brain metastases. It has previously been shown that reactivation of cytomegalovirus (CMV) frequently occurs during RT of the brain. This causes neurological decline, demands antiviral treatment, and is associated with a worse prognosis. CMV-specific T cells are characterized by a differentiated effector memory phenotype and CD45RA+ CCR7- effector memory T (TEMRA) cells were shown to be enriched in CMV seropositive individuals. In this study, we investigated the distribution of TEMRA cells and their subsets in the peripheral blood of healthy donors and, for the first time, prospectively within the scope of the prospective Glio-CMV-01 clinical trial of patients with high-grade glioma and brain metastases during radiation therapy as a potential predictive marker. First, we developed a multicolor flow cytometry-based assay to monitor the frequency and distribution of TEMRA cells in a longitudinal manner. The CMV serostatus and age were considered as influencing factors. We revealed that patients who had a reactivation of CMV have significantly higher amounts of CD8+ TEMRA cells. Further, the distribution of the subsets of TEMRA cells based on the expression of CD27, CD28, and CD57 is highly dependent on the CMV serostatus. We conclude that the percentage of CD8+ TEMRA cells out of all CD8+ T cells has the potential to serve as a biomarker for predicting the risk of CMV reactivation during RT of the brain. Furthermore, this study highlights the importance of taking the CMV serostatus into account when analyzing TEMRA cells and their subsets.
CRIS-Team Scopus Importer:2023-03-17
Keywords: brain metastases; cytomegalovirus (CMV); glioblastoma; infection; radiotherapy; T

Prospective evaluation of the prognostic value of immune-related adverse events in patients with non-melanoma solid tumour treated with PD-1/PD-L1 inhibitors alone and in combination with radiotherapy - Schweizer, Claudia; Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Haderlein, Marlen; Lettmaier, Sebastian; Semrau, Sabine; Gostian, Antoniu Oreste; Frey, Benjamin; Gaipl, Udo; Zhou, Jianguo; Fietkau, Rainer; et al. (European Journal of Cancer, 2020)
Background: Prospective data about the prognostic value of immune-related adverse events (irAEs) in non-melanoma solid tumours are rare. The prognostic value of irAEs in patients treated with combined radiotherapy and immunotherapy is currently unknown. Patients and methods: The prospective non-interventional ST-ICI trial investigates treatment response of tumour patients to anti–programmed cell death-ligand 1 (PD-L1) immune checkpoint inhibitors alone and in combination with radiotherapy and possible predictive markers. Patients undergoing immunotherapy or immunoradiotherapy were surveyed for irAEs. Results: A total of 104 patients were included of whom 29 patients (28%) developed irAEs. Additional radiotherapy was performed in 50 patients (48%). Main tumour entities within the entire cohort were non–small cell lung cancer (NSCLC) (44%) and head and neck squamous cell carcinoma (42%). The rate of irAEs did not differ in patients with and without radiotherapy (p = 0.668). Patients who developed irAEs had longer overall survival (OS) (median: 22.8 months versus 9.0 months without irAEs, p = 0.001) and progression-free survival (PFS) (median: 7.8 months versus 3.2 months without irAEs, p = 0.002). In the subgroup with combined radiotherapy, patients with irAEs also had longer OS (median: 22.8 months versus 7.1 months without irAEs, p = 0.005) and PFS (median: 8.8 months versus 3.0 months without irAEs, p = 0.005). On multivariate analysis only PD-L1 on tumour cells (p = 0.049) and irAEs (p = 0.001) remained independent predictors of OS. Conclusion: The development of irAEs represents a favourable prognostic parameter in patients undergoing immunotherapy and immunoradiotherapy for solid tumours.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Immune checkpoint inhibitors; Immune-related adverse events; Non-melanoma solid tumours; Prognostic parameters; Radiotherapy

QAMaster: A new software framework for phantom-based computed tomography quality assurance - Karius, Andre; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2022)
The regular evaluation of imaging performance of computed tomography (CT) scanners is essential for CT quality assurance. For automation of this process, the software QAMaster was developed at the Universitätsklinikum Erlangen, which provides based on CT scans of the CatPhan® 504 (The Phantom Laboratory, Salem, USA) automated image quality analysis and documentation by evaluating CT number accuracy, spatial linearity, uniformity, contrast-noise-ratio, spatial resolution, noise, and slice thickness. Dose assessment is supported by calculations of the weighted computed tomography dose index (CTDIw) and weighted cone beam dose index (CBDIw). QAMaster was tested with CatPhan® 504 scans and compared to manual evaluations of these scans, whereby high consistency of the respective results was observed. The CT numbers, spatial linearity, uniformity, contrast-noise-ratio, noise, and slice thickness deviated by only (0.13 ± 0.25) HU, (0.02 ± 0.05) mm, (−0.01 ± 0.03)%, 0.8 ± 1.8, (0.131 ± 0.05) HU, and (0.004 ± 0.005) mm between both evaluations, respectively. The QAMaster results for spatial resolution did not differ significantly (p = 0.34) from the CatPhan® 504 based manual resolution assessment. Dose computations were fully consistent between QAMaster and manual calculations. Thus, QAMaster proved to be a comprehensive and functional software for performing an automated CT quality assurance routine. QAMaster will be open-source after its release.
CRIS-Team Scopus Importer:2022-03-25
Keywords: computed tomography; cone beam computed tomography; image quality assurance; phantom-based software framework

QOL After APBI (Multicatheter Brachytherapy) Versus WBI: 5-Year Results, Phase 3 GEC-ESTRO Trial - Schaefer, R.; Strnad, Vratislav; Polgar, C.; Uter, Wolfgang; Hildebrandt, G.; Ott, O. J.; Kauer-Dorner, D.; Knauerhase, H.; Major, T.; Lyczek, J.; Guinot, J. L.; Dunst, J.; et al. (2018)
EVALuna2:36515

QoL after multimodal treatment of rectal cancer with/without oxaliplatin (phase 3, CAO/ARO/AIO-04) - Kosmala, R.; Fokas, E.; Flentje, M.; Sauer, Rolf; Liersch, T.; Graeven, U.; Fietkau, Rainer; Hohenberger, Werner; Arnold, D.; Hofheinz, R.; Ghadimi, M.; Raab, H.; et al. (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Quality assurance and long-term stability of a novel 3-in-1 X-ray system for brachytherapy - Karius, Andre; Szkitsak, Juliane; Boronikolas, Vasilios; Fietkau, Rainer; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2022)
Purpose A novel, mobile 3-in-1 X-ray system featuring radiography, fluoroscopy, and cone-beam computed tomography (CBCT) has been launched for brachytherapy recently. Currently, there is no quality assurance (QA) procedure explicitly applicable to this system equipped with innovative technologies such as dynamic jaws and motorized lasers. We developed a dedicated QA procedure and, based on its performance for a duration of 6 months, provide an assessment of the device's stability over time. Methods With the developed QA procedure, we assessed the system's planar and CBCT-imaging performance by investigating geometric accuracy, CT-number stability, contrast-noise-ratio, uniformity, spatial resolution, low-contrast detectability, dynamic range, and X-ray exposure using dedicated phantoms. Furthermore, we evaluated geometric stability by using the flexmap-approach and investigated the device's laser- and jaw-positioning accuracy with an in-house test phantom. CBCT- and planar-imaging protocols for pelvis, breast, and abdomen imaging were examined. Results Planar- and CBCT-imaging performances were widely stable with a geometric accuracy <= 1 mm, CT-number stability of up to 46 HU, and uniformity variations of up to 48 HU over time. For planar imaging, low-contrast detectability and dynamic range exceeded current recommendations. Although geometric stability was considered tolerable, partly substantial positioning inaccuracies of up to more than 120 mm and -13 mm were obtained for lasers and jaws, respectively. X-ray exposure showed small variations of <= 0.56 mu Gy and <= 0.76 mGy for planar- and CBCT-imaging, respectively. The conductance of the QA procedure allowed a smooth evaluation of the system's overall performance. Conclusion We developed a QA workflow for a novel 3-in-1 X-ray system allowing to assess the device's imaging and hardware performance. The system showed in general a reasonable imaging performance and stability over time, whereas improvements regarding laser and jaw accuracy are strictly required.
CRIS-Team WoS Importer:2022-07-29

Quality Assurance by electromagnetic Tracking in Interstitial multi-catheter HDR Brachytherapy Using a hybrid Afterloading System - Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (2018)
EVALuna2:36475

Quality assurance for dynamic tumor tracking - Witulla, Barbara; Ziegler, Marc; Brandt, Tobias; Prasetio, Heru; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2021)
The purpose of this work was to develop a treatment plan verification routine for a linear accelerator dedicated to SBRT treatments with gimbal based dynamic tumor tracking using three commercially available phantoms. The accelerator system has two special features: It operates with a rotation of the ring shaped gantry instead of a couch rotation and target motion can be compensated for via a gimbal system (dynamic tumor tracking, DTT). DTT plans were each measured with the three different phantoms. Afterwards the measured dose distribution was compared with the calculated dose distribution via global Gamma Index analysis (3 mm / 3%, threshold: 10%). The global gamma pass rates were on average (93.5 ± 7.2) % for ArcCHECK, (98.0 ± 2.6) % for OCTAVIUS® 4D and (98.4 ± 4.2) % for MatriXX Evolution. All three systems could be used for quality assurance with ring rotations and DTT, however, each with limitations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Intensity modulated radiation therapy; quality assurance; Stereotactic body radiation therapy; Tumor Tracking

Quality assurance for interstitial brachytherapy using an EMT system integrated into an afterloader - Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (2018)
EVALuna2:36479

Quality assurance guidelines for superficial hyperthermia clinical trials: I. Clinical requirements - Trefna, Hana Dobsicek; Crezee, Hans; Schmidt, Manfred; Marder, Dietmar; Lamprecht, Ulf; Ehmann, Michael; Hartmann, Josefin; Nadobny, Jacek; Gellermann, Johanna; Van Holthe, Netteke; Ghadjar, Pirus; Lomax, Nicoletta; et al. (International Journal of Hyperthermia, 2017)
Quality assurance guidelines are essential to provide uniform execution of clinical trials and treatment in the application of hyperthermia. This document provides definitions for a good hyperthermia treatment and identifies the clinical conditions where a certain hyperthermia system can or cannot adequately heat the tumour volume. It also provides brief description of the characteristics and performance of the current electromagnetic (radiative and capacitive), ultrasound and infra-red heating techniques. This information helps to select the appropriate heating technique for the specific tumour location and size, and appropriate settings of the water bolus and thermometry. Finally, requirements of staff training and documentation are provided. The guidelines in this document focus on the clinical application and are complemented with a second, more technical quality assurance document providing instructions and procedure to determine essential parameters that describe heating properties of the applicator for superficial hyperthermia. Both sets of guidelines were developed by the ESHO Technical Committee with participation of senior STM members and members of the Atzelsberg Circle.
EVALuna2:33043

Quality Assurance in interstitial multi-catheter Brachytherapy using an electromagnetic Tracking System - Abu-Hossin, Nadin; Kallis, Karoline; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Quality assurance of a breathing controlled four-dimensional computed tomography algorithm - Szkitsak, Juliane; Karius, Andre; Hofmann, Christian; Fietkau, Rainer; Bert, Christoph; Speer, Stefan (Physics and Imaging in Radiation Oncology, 2022)
Background & purpose: Four-dimensional computed tomography (4DCT) scans are standardly used for radiotherapy planning of tumors subject to respiratory motion. Based on online analysis and automatic adaption of scan parameters to the patient's individual breathing pattern, a new breathing-controlled 4DCT (i4DCT) algorithm attempts to counteract irregular breathing and thus prevent artifacts. The aim of this study was to perform an initial quality assurance for i4DCT. Material & methods: To validate the i4DCT algorithm, phantom measurements were performed to evaluate geometric accuracy (diameter, volume, eccentricity), image quality (dose-normalized contrast-noise-ratio, CT number accuracy), and correct representation of motion amplitude of simulated tumor lesions. Furthermore, the impact of patient weight and resulting table flexion on the measurements was investigated. Static three-dimensional CT (3DCT) scans were used as ground truth. Results: The median volume deviation magnitude between 4DCT and 3DCT was < 2% (<0.2 cm3). The volume differences ranged from –8% (–1.0 cm3) to 3% (0.4 cm3). Median tumor diameter deviation magnitudes were < 2% (<0.7 mm) for regular and < 3.5% (<1.0 mm) for irregular breathing. For eccentricity, a median deviation magnitude of < 0.05 for regular and < 0.08 for irregular breathing curves was found. The respiratory amplitude was represented with a median accuracy of < 0.5 mm. CT numbers and dose-normalized contrast-noise-ratio showed no clinically relevant difference between 4DCT and 3DCT. Table flexion proved to have no clinically relevant impact on geometric accuracy. Conclusions: The breathing-controlled algorithm provides in general good results regarding image quality, geometric accuracy, and correct depiction of motion amplitude for regular and irregular breathing.
CRIS-Team Scopus Importer:2022-07-22
Keywords: 4DCT; Quality assurance; Respiratory motion

Quality assurance of curved catheter paths in interstitial brachytherapy using a constructed phantom - Abu-Hossin, N.; Gulde, S.; Dürrbeck, Christopher; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-18

Quality of life in rectal cancer patients with or without oxaliplatin in the randomised CAO/ARO/AIO-04 phase 3 trial - Kosmala, Rebekka; Fokas, Emmanouil; Flentje, Michael; Sauer, Rolf; Liersch, Torsten; Graeven, Ullrich; Fietkau, Rainer; Hohenberger, Werner; Arnold, Dirk; Hofheinz, Ralf Dieter; Ghadimi, Michael; Ströbel, Philipp; et al. (European Journal of Cancer, 2021)
Background: The CAO/ARO/AIO trial has shown that oxaliplatin added to preoperative chemoradiotherapy and postoperative chemotherapy significantly improved disease-free survival in locally advanced rectal cancer (LARC). Here, we present a post-hoc analysis of quality of life (QoL) in disease-free patients. Patients and methods: Between 2006 and 2010, 1236 patients with LARC were randomly assigned either to preoperative chemoradiotherapy followed by total mesorectal excision and postoperative chemotherapy (N = 623) or combined with oxaliplatin (N = 613). QoL questionnaires (EORTC QLQ-C30, colorectal module CR38) were completed at baseline, after postoperative chemotherapy and during follow-up. Analysis was performed according intent-to-treat. Results: Available questionnaires (baseline) were 82% (N = 512) in the control and 84% (N = 513) in the investigational group. Response rates were 49% (533 of 1086) at 1 year and 43% (403 of 928) at 3 years. Global health status (GHS) for disease-free patients was stable in both groups (range 0–100). At baseline: standard arm 62.0 (mean, SD 21.6; N = 491) versus oxaliplatin arm 63.2 (mean, SD 22; N = 503); at 3 years: 69.4 (SD 19.3; N = 187) versus 65.4 (SD 22.2; N = 202). After treatment and at 3 years, no significant differences (≥10 points) between groups were found in QoL subscales. Disease-free patients experiencing neurotoxic side-effects (grade 1–4) showed reduced GHS at 3 years versus patients without neurotoxicity (mean 59.2 versus 69.3; P < 0.001), while grade 3–4 rate was low. Conclusion: The addition of oxaliplatin was not associated with worse overall QoL. This information is of interest to patients in many ongoing rectal cancer trials. Trial registration information: NCT00349076.
CRIS-Team Scopus Importer:2021-01-08
Keywords: Chemoradiotherapy; Oxaliplatin; Quality of life; Rectal neoplasms

Quality of Life of Patients with Head and Neck Cancer Receiving Cetuximab, Fluorouracil, Cisplatin Comparing to Cetuximab, Fluorouracil, Cisplatin, and Docetaxel within the CEFCID Trial - Goerling, Ute; Gauler, Thomas; Dietz, Andreas; Grünwald, Viktor; Knipping, Stephan; Guntinas-Lichius, Orlando; Frickhofen, Norbert; Lindeman, Hans Walter; Fietkau, Rainer; Haxel, Boris; Große-Thie, Christina; Maschmeyer, Georg; et al. (Oncology Research and Treatment, 2022)
Introduction: CeFCiD was a multicenter phase II study comparing the efficacy of cetuximab (C), 5-flourouracil, and cisplatin with the same regimen adding docetaxel (D) in recurrent/metastatic head and neck cancer. The primary analysis trial did not demonstrate survival benefit from therapy intensification in first-line recurrent and/or metastatic squamous cell carcinoma of the head and neck (SCCHN). The current analysis of the trial assessed the impact of treatment on quality of life (QoL). Methods: The European Organization for Research and Treatment of Cancer Quality of life Questionnaire QLQ-C30 and the tumor-specific module for head and neck cancer (QLQ-H&N35) were used to assess QoL at baseline (visit 1), after 2 (visit 3), 4 (visit 5), and 6 (visit 7) cycles of chemotherapy. Results: Of 180 patients included in this study, 86 patients (47.8%) completed the questionnaires at baseline. Considering selected scores over treatment time, there was no difference in global QoL, dyspnea, swallowing, and speech between the treatment arms in the course. For fatigue, a significant increase from baseline to visit 3 (p = 0.02), visit 5 (p = 0.002), and to visit 7 (p = 0.003) was observed for patients receiving D, cisplatin or carboplatin (P), 5-fluorouracil (F), and C. At the end of chemotherapy, the manifestation of fatigue was similar compared in the 2 treatment arms. Discussion/Conclusion: Therapy intensification not adversely affects selected scores of QoL of patients with recurrent and/or metastatic SCCHN. Nevertheless, fatigue seems to be pronounced in patients treated with D.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Docetaxel; Head and neck cancer; Quality of life; Recurrent and metastatic; Therapy intensification

Quality of life of patients with newly diagnosed glioblastoma during TTFields therapy in routine clinical care: first results of the TIGER study - Baehr, O.; Tabatabai, G.; Fietkau, Rainer; Goldbrunner, R.; Glas, M. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Quality-of-life results for accelerated partial breast irradiation with interstitial brachytherapy versus whole-breast irradiation in early breast cancer after breast-conserving surgery (GEC-ESTRO): 5-year results of a randomised, phase 3 trial - Schaefer, Rebekka; Strnad, Vratislav; Polgar, Csaba; Uter, Wolfgang; Hildebrandt, Guido; Ott, Oliver J.; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Lyczek, Jaroslaw; Guinot, Jose Luis; Dunst, Juergen; et al. (Lancet Oncology, 2018)
BACKGROUND: Previous results from the GEC-ESTRO trial showed that accelerated partial breast irradiation (APBI) using multicatheter brachytherapy in the treatment of early breast cancer after breast-conserving surgery was non-inferior to whole-breast irradiation in terms of local control and overall survival. Here, we present 5-year results of patient-reported quality of life. METHODS: We did this randomised controlled phase 3 trial at 16 hospitals and medical centres in seven European countries. Patients aged 40 years or older with 0-IIA breast cancer were randomly assigned (1:1) after breast-conserving surgery (resection margins ≥2 mm) to receive either whole-breast irradiation of 50 Gy with a boost of 10 Gy or APBI using multicatheter brachytherapy. Randomisation was stratified by study centre, tumour type, and menopausal status, with a block size of ten and an automated dynamic algorithm. There was no masking of patients or investigators. The primary endpoint of the trial was ipsilateral local recurrence. Here, we present 5-year results of quality of life (a prespecified secondary endpoint). Quality-of-life questionnaires (European Organisation for Research and Treatment of Cancer QLQ-C30, breast cancer module QLQ-BR23) were completed before radiotherapy (baseline 1), immediately after radiotherapy (baseline 2), and during follow-up. We analysed the data according to treatment received (as-treated population). Recruitment was completed in 2009, and long-term follow-up is continuing. The trial is registered at ClinicalTrials.gov, number NCT00402519. FINDINGS: Between April 20, 2004, and July 30, 2009, 633 patients had accelerated partial breast irradiation and 551 patients had whole-breast irradiation. Quality-of-life questionnaires at baseline 1 were available for 334 (53%) of 663 patients in the APBI group and 314 (57%) of 551 patients in the whole-breast irradiation group; the response rate was similar during follow-up. Global health status (range 0-100) was stable in both groups: at baseline 1, APBI group mean score 65·5 (SD 20·6) versus whole-breast irradiation group 64·6 (19·6), p=0·37; at 5 years, APBI group 66·2 (22·2) versus whole-breast irradiation group 66·0 (21·8), p=0·94. The only moderate, significant difference (difference of 10-20 points) between the groups was found in the breast symptoms scale. Breast symptom scores were significantly higher (ie, worse) after whole-breast irradiation than after APBI at baseline 2 (difference of means 13·6, 95% CI 9·7-17·5; p<0·0001) and at 3-month follow-up (difference of means 12·7, 95% CI 9·8-15·6; p<0·0001). INTERPRETATION: APBI with multicatheter brachytherapy was not associated with worse quality of life compared with whole-breast irradiation. This finding supports APBI as an alternative treatment option after breast-conserving surgery for patients with early breast cancer. FUNDING: German Cancer Aid.
EVALuna2:35671

Quality requirements for MRI simulation in cranial stereotactic radiotherapy: a guideline from the German Taskforce “Imaging in Stereotactic Radiotherapy” - Putz, Florian; Bock, Michael; Schmitt, Daniela; Bert, Christoph; Blanck, Oliver; Ruge, Maximilian I.; Hattingen, Elke; Karger, Christian P.; Fietkau, Rainer; Grigo, Johanna; Schmidt, Manuel; Bäuerle, Tobias; et al. (Strahlentherapie und Onkologie, 2024)
Accurate Magnetic Resonance Imaging (MRI) simulation is fundamental for high-precision stereotactic radiosurgery and fractionated stereotactic radiotherapy, collectively referred to as stereotactic radiotherapy (SRT), to deliver doses of high biological effectiveness to well-defined cranial targets. Multiple MRI hardware related factors as well as scanner configuration and sequence protocol parameters can affect the imaging accuracy and need to be optimized for the special purpose of radiotherapy treatment planning. MRI simulation for SRT is possible for different organizational environments including patient referral for imaging as well as dedicated MRI simulation in the radiotherapy department but require radiotherapy-optimized MRI protocols and defined quality standards to ensure geometrically accurate images that form an impeccable foundation for treatment planning. For this guideline, an interdisciplinary panel including experts from the working group for radiosurgery and stereotactic radiotherapy of the German Society for Radiation Oncology (DEGRO), the working group for physics and technology in stereotactic radiotherapy of the German Society for Medical Physics (DGMP), the German Society of Neurosurgery (DGNC), the German Society of Neuroradiology (DGNR) and the German Chapter of the International Society for Magnetic Resonance in Medicine (DS-ISMRM) have defined minimum MRI quality requirements as well as advanced MRI simulation options for cranial SRT.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Brain metastases; DEGRO; DGMP; DGNC; DGNR; DS-ISMRM; Guideline; Meningioma; MRI simulation; Pituitary adenoma; Stereotactic radiosurgery; Stereotactic radiotherapy; Trigeminal neuralgia; Vestibular schwannoma

Quantification of an external motion surrogate for quality assurance in lung cancer radiation therapy - Wölfelschneider, Jens; Brandt, Tobias; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (BioMed Research International, 2014)
The purpose of this work was to validate the stability of the end exhale position in deep expiration breath hold (DEBH) technique for quality assurance in stereotactic lung tumor radiation therapy. Furthermore, a motion analysis was performed for 20 patients to evaluate breathing periods and baseline drifts based on an external surrogate. This trajectory was detected using stereo infrared (IR) cameras and reflective body markers. The respiratory waveform showed large interpatient differences in the end exhale position during irradiation up to 18.8 mm compared to the global minimum. This position depends significantly on the tumor volume. Also the baseline drifts, which occur mostly in posterior direction, are affected by the tumor size. Breathing periods, which depend mostly on the patient age, were in a range between 2.4 s and 7.0 s. Fifteen out of 20 patients, who showed a reproducible end exhale position with a deviation of less than 5 mm, might benefit from DEBH due to smaller planning target volumes (PTV) compared to free breathing irradiation and hence sparing of healthy tissue. Patients with larger uncertainties should be treated with more complex motion compensation techniques.
EVALuna2:18182

Quantification of pretherapeutic Changes in Brain Metastases before stereotactic Radiotherapy - Putz, Florian; Görnert, Caroline; Voigt, R.; Grigo, Johanna; Masitho, Siti; Reissig, L.; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Schmidt, M.; Semrau, Sabine; Bert, Christoph; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Quantitative, multi-institutional evaluation of MR thermometry accuracy for deep-pelvic MR-hyperthermia systems operating in multi-vendor MR-systems using a new anthropomorphic phantom - Curto, Sergio; Aklan, Bassim; Mulder, Tim; Mils, Oliver; Schmidt, Manfred; Lamprecht, Ulf; Peller, Michael; Wessalowski, Ruediger; Lindner, Lars H.; Fietkau, Rainer; Zips, Daniel; Bellizzi, Gennaro G.; et al. (Cancers, 2019)
Clinical outcome of hyperthermia depends on the achieved target temperature, therefore target conformal heating is essential. Currently, invasive temperature probe measurements are the gold standard for temperature monitoring, however, they only provide limited sparse data. In contrast, magnetic resonance thermometry (MRT) provides unique capabilities to non–invasively measure the 3D–temperature. This study investigates MRT accuracy for MR–hyperthermia hybrid systems located at five European institutions while heating a centric or eccentric target in anthropomorphic phantoms with pelvic and spine structures. Scatter plots, root mean square error (RMSE) and Bland–Altman analysis were used to quantify accuracy of MRT compared to high resistance thermistor probe measurements. For all institutions, a linear relation between MRT and thermistor probes measurements was found with R2 (mean ± standard deviation) of 0.97 ± 0.03 and 0.97 ± 0.02, respectively for centric and eccentric heating targets. The RMSE was found to be 0.52 ± 0.31 °C and 0.30 ± 0.20 °C, respectively. The Bland–Altman evaluation showed a mean difference of 0.46 ± 0.20 °C and 0.13 ± 0.08 °C, respectively. This first multi–institutional evaluation of MR-hyperthermia hybrid systems indicates comparable device performance and good agreement between MRT and thermistor probes measurements. This forms the basis to standardize treatments in multi–institution studies of MR–guided hyperthermia and to elucidate thermal dose–effect relations.
CRIS-Team Scopus Importer:2019-11-15
Keywords: Anthropomorphic phantom; Magnetic resonance imaging–guided hyperthermia; Magnetic resonance thermometry; Quality assurance; Radiofrequency hyperthermia; Thermistor probe

Questionnaire-based detection of immune-related adverse events in cancer patients treated with PD-1/PD-L1 immune checkpoint inhibitors - Griewing, Luisa Maria; Schweizer, Claudia; Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Frey, Benjamin; Haderlein, Marlen; Weissmann, Thomas; Semrau, Sabine; Gostian, Antoniu Oreste; Müller, Sarina Katrin; Traxdorf, Maximilian; et al. (BMC Cancer, 2021)
Background: Immune checkpoint inhibitors (ICI) have become standard treatment in different tumor entities. However, safe treatment with ICI targeting the PD-1/PD-L1 axis requires early detection of immune-related adverse events (irAE). There exist different questionnaires of drug manufacturers for the detection of irAE that have not been validated so far. Methods: The prospective non-interventional ST-ICI trial studied treatment with PD-1/PD-L1 ICI alone or combined with radiotherapy. In the current analysis, the detection rate of self-reported irAE with a patient questionnaire containing 41 different questions was compared to clinician-reported irAE. Results: Between April 2017 and August 2019, a total of 104 patients were prospectively enrolled. NSCLC (44%) and HNSCC (42%) were the most frequent tumor entities. A total of 784 questionnaires were collected. A total of 29 irAE were reported by clinicians. The most frequent irAE was hypothyroidism (9%), followed by skin reactions (5%), hepatitis (4%), diarrhea (3%), and pneumonitis (3%). Questions that became significantly more often positive at time points of clinician-reported irAE were “weight change”, “difficulty to grip things”, “bloody or mucous stool” and “insomnia”. Self-reported organ-specific questions detected at least 50% of clinician-reported irAE of gastrointestinal, lung, endocrine, and skin irAE. It was not possible to detect hepatic irAE with the questionnaire. Conclusion: Questionnaires can help to detect gastrointestinal, lung, endocrine, or skin irAE, but not hepatic irAE. Questions on “weight change” and “insomnia” may help to increase the detection rate of irAE, besides organ-specific questions. These results are a valuable contribution to the future development of a specific and practicable questionnaire for early self-reported detection of irAE during ICI therapy in cancer patients. Trial registration: ClinicalTrials.gov, NCT03453892. Registered on 05 March 2018.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Immune checkpoint inhibitors; Immune-related adverse events; Patient-reported irAE; PD-1; PD-L1; Questionnaire; Side effects; Solid tumors; Toxicity

R0 resection following chemo (radio)therapy improves survival of primary inoperable pancreatic cancer patients. Interim results of the German randomized CONKO-007± trial - Fietkau, Rainer; Grützmann, Robert; Wittel, U. A.; Croner, R. S.; Jacobasch, L.; Neumann, U. P.; Reinacher-Schick, A.; Imhoff, D.; Boeck, S.; Keilholz, L.; Oettle, H.; Hohenberger, Werner; et al. (Strahlentherapie und Onkologie, 2020)
Purpose: Chemotherapy with or without radiotherapy is the standard in patients with initially nonmetastatic unresectable pancreatic cancer. Additional surgery is in discussion. The CONKO-007 multicenter randomized trial examines the value of radiotherapy. Our interim analysis showed a significant effect of surgery, which may be relevant to clinical practice. Methods: One hundred eighty patients received induction chemotherapy (gemcitabine or FOLFIRINOX). Patients without tumor progression were randomized to either chemotherapy alone or to concurrent chemoradiotherapy. At the end of therapy, a panel of five independent pancreatic surgeons judged the resectability of the tumor. Results: Following induction chemotherapy, 126/180 patients (70.0%) were randomized to further treatment. Following study treatment, 36/126 patients (28.5%) underwent surgery; (R0: 25/126 [19.8%]; R1/R2/Rx [n = 11/126; 6.1%]). Disease-free survival (DFS) and overall survival (OS) were significantly better for patients with R0 resected tumors (median DFS and OS: 16.6 months and 26.5 months, respectively) than for nonoperated patients (median DFS and OS: 11.9 months and 16.5 months, respectively; p = 0.003). In the 25 patients with R0 resected tumors before treatment, only 6/113 (5.3%) of the recommendations of the panel surgeons recommended R0 resectability, compared with 17/48 (35.4%) after treatment (p < 0.001). Conclusion: Tumor resectability of pancreatic cancer staged as unresectable at primary diagnosis should be reassessed after neoadjuvant treatment. The patient should undergo surgery if a resectability is reached, as this significantly improves their prognosis.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Neoadjuvant chemoradiotherapy; Pancreatic adenocarcinoma; Prospective randomized multicenter trial; Surgery; Tumor resectability

Radiation and checkpoint Blockade in the treatment of metastases - Hirschmann, Eva; Gaipl, Udo; Fietkau, Rainer; Distel, Luitpold; Hecht, Markus (2018)
EVALuna2:33778

Radiation Immunotherapy has different effects on the immunological Composition of the Tumor Microenvironment in primary and abscopic Murine Tumors - Rueckert, M.; Deloch, Lisa; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Radiation Sensitivity in Patients with Prostate Cancer - Altmann, J. -M.; Schuster, Barbara; Geinitz, H.; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Radiation therapy in Graves'-opthalmopathy - Weissmann, T.; Semrau, S.; Ott, O. J.; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Radio(chemo)therapy does differently impact on PD-L1 and PD-L2 expression in human melanoma cell lines - Derer, Anja; Riegel, D.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (2018)
EVALuna2:36496

Radio(chemo)therapy in anaplastic thyroid cancer—high locoregional but low distant control rates—a monocentric analysis of a tertiary referral center - Schmied, Matthias; Lettmaier, Sebastian; Semrau, Sabine; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina; Iro, Heinrich; Denz, Axel; Grützmann, Robert; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2022)
Background: Anaplastic thyroid cancer (ATC) is a lethal disease with highly aggressive disease progression. This study analyses the influence of radio(chemo)therapy, R(C)T, on disease control, survival rates and predictors for survival. Patients and methods: A total of 33 patients with ATC, treated at a tertiary referral center between May 2001 and April 2020 were included. Univariate and multivariate analysis were used to investigate correlates of R(C)T and predictors on disease control and survival rates. Results: Median follow-up was 4 months. In UICC stage IVA and IVB median overall survival (OS) was 8 months, median progression-free survival (PFS) was 6 months. Patients with UICC stage IVA and IVB and patients being irradiated with a radiation dose of more than 60 Gy showed increased OS. Of these patients, 3 were alive and free from disease. All of them receiving cisplatin-based radiochemotherapy and a minimum radiation dose of 66 Gy. UICC stage IVC showed a median OS of 2.5 months and a median PFS of 1 month. Only 2 of 16 patients had local failure. Conclusion: Depending on UICC stage, RT with high radiation dose can lead to improved OS or at least higher locoregional control. A limiting factor is the high incidence of distant metastases; therefore modern systemic treatment options should be integrated into multimodal therapy concepts.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Anaplastic thyroid cancer; Chemotherapy; Multimodal treatment; Radiation dose; Radiotherapy

Radiochemotherapy with or without cetuximab for unresectable esophageal cancer: final results of a randomized phase 2 trial (LEOPARD-2) - Rades, Dirk; Bartscht, Tobias; Hunold, Peter; Schmidberger, Heinz; König, Laila; Debus, Jürgen; Belka, Claus; Homann, Nils; Spillner, Patrick; Petersen, Cordula; Kuhnt, Thomas; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2020)
Purpose: To investigate the efficacy and toxicity of cetuximab when added to radiochemotherapy for unresectable esophageal cancer. Methods: This randomized phase 2 trial (clinicaltrials.gov, identifier NCT01787006) compared radiochemotherapy plus cetuximab (arm A) to radiochemotherapy (arm B) for unresectable esophageal cancer. Primary objective was 2‑year overall survival (OS). Arm A was considered insufficiently active if 2‑year OS was ≤40% (null hypothesis = H0), and promising if the lower limit of the 95% confidence interval was >45%. If that lower limit was >40%, H0 was rejected. Secondary objectives included progression-free survival (PFS), locoregional control (LC), metastases-free survival (MFS), response, and toxicity. The study was terminated early after 74 patients; 68 patients were evaluable. Results: Two-year OS was 71% in arm A (95% CI: 55–87%) vs. 53% in arm B (95% CI: 36–71%); H0 was rejected. Median OS was 49.1 vs. 24.1 months (p = 0.147). Hazard ratio (HR) for death was 0.60 (95% CI: 0.30–1.21). At 2 years, PFS was 56% vs. 44%, LC 84% vs. 72%, and MFS 74% vs. 54%. HRs were 0.51 (0.25–1.04) for progression, 0.43 (0.13–1.40) for locoregional failure, and 0.43 (0.17–1.05) for distant metastasis. Overall response was 81% vs. 69% (p = 0.262). Twenty-six and 27 patients, respectively, experienced at least one toxicity grade ≥3 (p = 0.573). A significant difference was found for grade ≥3 allergic reactions (12.5% vs. 0%, p = 0.044). Conclusion: Given the limitations of this trial, radiochemotherapy plus cetuximab was feasible. There was a trend towards improved PFS and MFS. Larger studies are required to better define the role of cetuximab for unresectable esophageal cancer.
CRIS-Team Scopus Importer:2020-06-19
Keywords: Definitive treatment; Efficacy; EGFR antibody; Esophageal cancer; Feasibility

Radio-Immunotherapy-Induced Immunogenic Cancer Cells as Basis for Induction of Systemic Anti-Tumor Immune Responses - Pre-Clinical Evidence and Ongoing Clinical Applications - Derer, Anja; Deloch, Lisa; Rubner, Yvonne; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (Frontiers in Immunology, 2015)
Radiotherapy (RT) primarily aims to locally destroy the tumor via the induction of DNA damage in the tumor cells. However, the so-called abscopal, namely systemic and immune-mediated, effects of RT move over more and more in the focus of scientists and clinicians since combinations of local irradiation with immune therapy have been demonstrated to induce anti-tumor immunity. We here summarize changes of the phenotype and microenvironment of tumor cells after exposure to irradiation, chemotherapeutic agents, and immune modulating agents rendering the tumor more immunogenic. The impact of therapy-modified tumor cells and damage-associated molecular patterns on local and systemic control of the primary tumor, recurrent tumors, and metastases will be outlined. Finally, clinical studies affirming the bench-side findings of interactions and synergies of radiation therapy and immunotherapy will be discussed. Focus is set on combination of radio(chemo)therapy (RCT) with immune checkpoint inhibitors, growth factor inhibitors, and chimeric antigen receptor T-cell therapy. Well-deliberated combination of RCT with selected immune therapies and growth factor inhibitors bear the great potential to further improve anti-cancer therapie
EVALuna2:18276

Radioimmuntherapie - Hecht, Markus; Gaipl, Udo; Fietkau, Rainer (Onkologe, 2021)
Background: Radiotherapy is used to achieve local tumor control in the irradiated area. In the last decade, there has been increasing evidence that radiotherapy has immunomodulatory properties in addition to killing tumor cells. Purpose: Essential principles of the immunomodulatory effects of radiotherapy are explained and, in particular, the clinical benefits of radiotherapy in combination with immune checkpoint inhibitors are presented. Results: Radiotherapy can trigger tumor-specific immune responses by inducing immunogenic cell death of tumor cells and alterations of the tumor microenvironment. However, clinical relevance of such systemic immunologic effects of local irradiation has been observed only very rarely in the past, which is probably due to the fact that irradiation can also induce immunosuppressive effects. By combining local radiotherapy with immune checkpoint inhibitors, antitumor immune responses can be enhanced and immunosuppressive effects can be counteracted. Such therapeutic strategies are currently being investigated in numerous clinical trials and have achieved remarkable results in non-small cell lung cancer (stage III) with the PD-L1 inhibitor durvalumab after definitive radiochemotherapy. Conclusion: The combination of radiotherapy with immune checkpoint inhibitors is an efficient concept that is currently being investigated in numerous studies and has already entered clinical routine in non-small cell lung cancer.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Immune checkpoint inhibitors; Immunogenic cell death; Immunotherapy; PD‑1; Radiotherapy

Radiomics for selection of patients treated with immuno-radiotherapy: pooled analysis from 6 studies - Sun, R.; Sundahl, N.; Hecht, Markus; Putz, Florian; Lancia, A.; Milic, M.; Carre, A.; Lerousseau, M.; Theo, E.; Battistella, E.; Andres, E. Alvarez; Louvel, G.; et al. (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Radiomics to predict outcomes and abscopal response of patients with cancer treated with immunotherapy combined with radiotherapy using a validated signature of CD8 cells - Sun, Roger; Sundahl, Nora; Hecht, Markus; Putz, Florian; Lancia, Andrea; Rouyar, Angela; Milic, Marina; Carré, Alexandre; Battistella, Enzo; Alvarez Andres, Emilie; Niyoteka, Stéphane; Romano, Edouard; et al. (Journal for ImmunoTherapy of Cancer, 2020)
BACKGROUND: Combining radiotherapy (RT) with immuno-oncology (IO) therapy (IORT) may enhance IO-induced antitumor response. Quantitative imaging biomarkers can be used to provide prognosis, predict tumor response in a non-invasive fashion and improve patient selection for IORT. A biologically inspired CD8 T-cells-associated radiomics signature has been developed on previous cohorts. We evaluated here whether this CD8 radiomic signature is associated with lesion response, whether it may help to assess disease spatial heterogeneity for predicting outcomes of patients treated with IORT. We also evaluated differences between irradiated and non-irradiated lesions. METHODS: Clinical data from patients with advanced solid tumors in six independent clinical studies of IORT were investigated. Immunotherapy consisted of 4 different drugs (antiprogrammed death-ligand 1 or anticytotoxic T-lymphocyte-associated protein 4 in monotherapy). Most patients received stereotactic RT to one lesion. Irradiated and non-irradiated lesions were delineated from baseline and the first evaluation CT scans. Radiomic features were extracted from contrast-enhanced CT images and the CD8 radiomics signature was applied. A responding lesion was defined by a decrease in lesion size of at least 30%. Dispersion metrices of the radiomics signature were estimated to evaluate the impact of tumor heterogeneity in patient's response. RESULTS: A total of 94 patients involving multiple lesions (100 irradiated and 189 non-irradiated lesions) were considered for a statistical interpretation. Lesions with high CD8 radiomics score at baseline were associated with significantly higher tumor response (area under the receiving operating characteristic curve (AUC)=0.63, p=0.0020). Entropy of the radiomics scores distribution on all lesions was shown to be associated with progression-free survival (HR=1.67, p=0.040), out-of-field abscopal response (AUC=0.70, p=0.014) and overall survival (HR=2.08, p=0.023), which remained significant in a multivariate analysis including clinical and biological variables. CONCLUSIONS: These results enhance the predictive value of the biologically inspired CD8 radiomics score and suggests that tumor heterogeneity should be systematically considered in patients treated with IORT. This CD8 radiomics signature may help select patients who are most likely to benefit from IORT.
CRIS-Team Scopus Importer:2020-11-27
Keywords: radioimmunotherapy; translational medical research; tumor biomarkers; tumor microenvironment

Radioresistance shapes the immunogenic Properties of Triple-negative Breast Cancer Cells - Gehre, S.; Rückert, Michael; Sengedorj, Azzaya; Grottker, F.; Reichardt, Clara; Meyer, F.; Borgmann, K.; Fietkau, Rainer; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Radiosensitization by BRAF inhibitor therapy-mechanism and frequency of toxicity in melanoma patients - Hecht, Markus; Zimmer, L.; Loquai, C.; Weishaupt, C.; Gutzmer, R.; Schuster, B.; Gleisner, S.; Schulze, B.; Goldinger, S. M.; Berking, C.; Forschner, A.; Clemens, P.; et al. (Annals of Oncology, 2015)
Recent evidence suggests that ionizing radiation may be associated with unexpected side-effects in melanoma patients treated with concomitant BRAF inhibitors. A large multicenter analysis was carried out to generate reliable safety data and elucidate the mechanism.A total of 161 melanoma patients from 11 European skin cancer centers were evaluated for acute and late toxicity, of whom 70 consecutive patients received 86 series of radiotherapy with concomitant BRAF inhibitor therapy. To further characterize and quantify a possible radiosensitization by BRAF inhibitors, blood samples of 35 melanoma patients were used for individual radiosensitivity testing by fluorescence in situ hybridization of chromosomal breaks after ex vivo irradiation.With radiotherapy and concomitant BRAF inhibitor therapy the rate of acute radiodermatitis >=2° was 36% and follicular cystic proliferation was seen in 13% of all radiotherapies. Non-skin toxicities included hearing disorders (4%) and dysphagia (2%). Following whole-brain radiotherapy, rates of radiodermatitis >=2° were 44% and 8% (P < 0.001) for patients with and without BRAF inhibitor therapy, respectively. Concomitant treatment with vemurafenib induced acute radiodermatitis >=2° more frequently than treatment with dabrafenib (40% versus 26%, P = 0.07). In line with these findings, analysis of chromosomal breaks ex vivo indicated significantly increased radiosensitivity for patients under vemurafenib (P = 0.004) and for patients switched from vemurafenib to dabrafenib (P = 0.002), but not for patients on dabrafenib only. No toxicities were reported after stereotactic treatment.Radiotherapy with concomitant BRAF inhibitor therapy is feasible with an acceptable increase in toxicity. Vemurafenib is a more potent radiosensitizer than dabrafenib.
EVALuna2:18285

Radiosensitizing and radioprotecting effect of kinase-inhibitor Palbociclib in different normal tissue and cancer cell lines - Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36494

Radiotherapy after skin-sparing mastectomy with immediate breast reconstruction in intermediate-risk breast cancer - Hehr, Thomas; Baumann, René; Budach, Wilfried; Duma, Marciana Nona; Dunst, Jürgen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; Krug, David; Piroth, Marc D.; Sedlmayer, Felix; et al. (Strahlentherapie und Onkologie, 2019)
Background: Skin-sparing (SSME) and nipple-sparing mastectomy (NSME) were developed to improve the cosmetic results for breast cancer (BC) patients, both allowing for immediate breast reconstruction. Recommendations for post-mastectomy radiotherapy (PMRT) are primarily derived from trials where patients were treated by standard mastectomies. Due to their more conservative character, SSME and especially NSME potentially leave more glandular tissue at risk for subclinical disease. Methods: Rates and sites of locoregional failures following SSME and NSME plus/minus reconstruction were analyzed regarding tumor stage and biological risk factors. In particular, the role of PMRT in “intermediate”-risk and early stage high-risk breast cancer patients was revisited. Implications on targeting and dose delivery of PMRT were critically reviewed. Results: The value of PMRT in stage III BC remains undisputed. For node-negative BC patients, the majority of reports classify clinical and biological features such as tumor size, close surgical margins, premenopausal status, multicentricity, lymphangiosis, triple-negativity, HER2-overexpression, and poor tumor grading as associated with higher rates of locoregional relapse, thus, building an “intermediate” risk group. Surveys revealed that the majority of radiation oncologists use risk-adaptive models also considering the number of coinciding factors for the estimation of recurrence probability following SSME and NSME. Constellations with a 10-year locoregional recurrence risk of >10% are usually triggering the indication for PMRT. There was no common belief that the amount of residual tissue, e.g., tissue thickness over flaps, serves as additional decision aid. Modern treatment planning can ensure optimal dose distribution for PMRT in almost all patients with SSME. There are no reliable data supporting a reduction of the treatment volume from the CTV chest wall, e.g., to the nipple-areola complex, to the dorsal aspect behind the implant volume, the pectoralis muscle, nor the regional interpectoral, axillary, or complete regional lymph nodes only. The omission of a skin bolus in intermediate-risk BC does not compromise oncological safety. Conclusions: For intermediate-risk as well as early stage high-risk BC patients, the DEGRO Breast Cancer Expert Panel recommends the use of PMRT following SSME and NSME when a 10-year locoregional recurrence risk is likely to be greater than 10%, as estimated by clinical and biological risk factors. Subvolume-only radiation is discouraged outside of trials. The impact of adequate systemic treatment and the value of radiotherapy on optimal locoregional tumor control, with the goal of less than 5% LRR at 10-years follow-up, has to be verified in prospective trials.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Intermediate-risk breast cancer; Local recurrence; Nipple-sparing mastectomy; PMRT; Post-mastectomy radiotherapy; Skin-sparing mastectomy

Radiotherapy combined with docetaxel alters the immune phenotype of HNSCC cells and results in increased surface expression of CD137 and release of HMGB1 of specifically HPV-positive tumor cells - Grottker, Fridolin; Gehre, Simon; Reichardt, Clara; Sengedorj, Azzaya; Jost, Tina; Rieckmann, Thorsten; Hecht, Markus; Gostian, Antoniu-Oreste; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Rückert, Michael (Neoplasia, 2023)
Purpose: Human papilloma virus (HPV) positive head and neck squamous cell carcinoma (HNSCC) tumors respond significantly better to anticancer treatments. It is assumed to be due to a better response to radiotherapy (RT), and presumably to an increased immunogenicity. However, little is known how the immune phenotype of HNSCC tumor cells is modulated by standard treatment, namely by radiochemotherapy (RCT). Methods: Therefore, we aimed to examine the impact of the HPV status on the immune phenotype of HNSCC cell lines following RCT with 5 × 3Gy or 1 × 19.3Gy and/or docetaxel, by analyzing cell death, release of damage-associated molecular patterns (DAMPs), surface expression of immune checkpoint molecules (ICMs) and the impact on activation of human monocyte-derived dendritic cells (hmDCs). Results: Cell death induction and Hsp70 release following RCT was independent of the HPV status, and RCT significantly increased the expression of the immune suppressive ICMs PD-L1, PD-L2 and HVEM. An immune stimulatory ICM, CD137, was significantly increased following RCT only on HPV-positive cell lines, as well as the release of HMGB1. Although the treatment increased cell death and modulated ICM expression in HNSCC, the hmDCs were not activated after co-incubation with treated tumor cells. Conclusion: Our data with the HPV-dependent release of HMGB1 and increased expression of CD137 following RCT provide a hint for increased immunogenicity underlining the better prognosis for HPV positive tumors following RCT.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Anti-tumor immunity; Dendritic cells; Docetaxel; Head and neck squamous cell carcinoma; HMGB1; HPV status; Immune checkpoint molecules; Radiotherapy

Radiotherapy for benign achillodynia. Long-term results of the Erlangen Dose Optimization Trial - Ott, Oliver J.; Jeremias, Carolin; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Fietkau, Rainer (Strahlentherapie und Onkologie, 2015)
The aim of this study was to evaluate the long-term efficacy of two dose-fractionation schedules for radiotherapy of achillodynia.Between February 2006 and February 2010, 112 evaluable patients were recruited for this prospective trial. All patients received orthovoltage radiotherapy. One course consisted of 6 fractions/3 weeks. In the case of insufficient remission of pain after 6 weeks, a second series was performed. Patients were randomly assigned to receive either single doses of 0.5 or 1.0 Gy. The endpoint was pain reduction. Pain was measured before, right after (early response), 6 weeks after (delayed response), and approximately 2 years after radiotherapy (long-term response) with a questionnaire-based visual analogue scale (VAS) and a comprehensive pain score (CPS).The median follow-up was 24 months (range, 11-56). The overall early, delayed, and long-term response rates for all patients were 84 %, 88 %, and 95 %, respectively. The mean VAS values before treatment for early, delayed, and long-term responses for the 0.5-Gy and 1.0-Gy groups were 55.7 ± 21.0 and 58.2 ± 23.5 (p = 0.53), 38.0 ± 23.2 and 30.4 ± 22.6 (p = 0.08), 35.5 ± 25.9 and 30.9 ± 25.4 (p = 0.52), and 11.2 ± 16.4 and 15.3 ± 18.9 (p = 0.16), respectively. The mean CPS values before treatment for early, delayed, and long-term responses were 8.2 ± 3.0 and 8.9 ± 3.3 (p = 0.24), 5.6 ± 3.1 and 5.4 ± 3.3 (p = 0.76), 4.4 ± 2.6 and 5.3 ± 3.8 (p = 0.58), and 2.2 ± 2.9 and 2.8 ± 3.3 (p = 0.51), respectively. No significant differences in long-term response quality between the two arms was found (p = 0.73).Radiotherapy is a very effective treatment for the management of benign achillodynia. For radiation protection, the dose for a radiotherapy series should not exceed 3.0 Gy.
EVALuna2:18279

Radiotherapy for benign calcaneodynia: long-term results of the Erlangen Dose Optimization (EDO) trial - Ott, Oliver J.; Jeremias, Carolin; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
The goal of this work was to evaluate the long-term efficacy of two dose-fractionation schedules for radiotherapy of calcaneodynia.Between February 2006 and February 2010, 457 evaluable patients were recruited for this prospective trial. All patients received orthovoltage radiotherapy. One course consisted of 6 fractions/3 weeks. In case of insufficient remission of pain after 6 weeks a second series was performed. Patients were randomly assigned to receive either single doses of 0.5 or 1.0 Gy. Endpoint was pain reduction. Pain was measured before, right after (early response), 6 weeks (delayed response), and approximately 2.5 years after radiotherapy (long-term response) with a questionnaire-based visual analogue scale (VAS) and a comprehensive pain score (CPS).The median follow-up was 32 months (range 9-57 months). The overall early, delayed, and long-term response rates for all patients were 87, 88, and 95%. The mean VAS values before treatment, for early, delayed, and long-term response for the 0.5 and 1.0 Gy groups were 65.5 ± 22.1 and 64.0 ± 20.5 (p = 0.19), 34.8 ± 24.7 and 39.0 ± 26.3 (p = 0.12), 25.1 ± 26.8 and 28.9 ± 26.8 (p = 0.16), and 16.3 ± 24.3 and 14.1 ± 19.7 (p = 0.68). The mean CPS values before treatment, for early, delayed, and log-term response were 10.1 ± 2.7 and 10.0 ± 3.0 (p = 0.78), 5.6 ± 3.7 and 6.0 ± 3.9 (p = 0.34), 4.0 ± 4.1 and 4.3 ± 3.6 (p = 0.26), and 2.1 ± 3.3 and 2.3 ± 3.2 (p = 0.34), respectively. No significant differences in long-term response quality between the two arms were found (p = 0.50).Radiotherapy is a very effective treatment for the management of benign calcaneodynia. For radiation protection reasons, the dose for a RT series should not exceed 3.0 Gy.
EVALuna2:18187

Radiotherapy for the elderly Patient with Head and Neck Squamous Cell Carcinoma - Experience of a Center for ENT-Tumors - Winkler, Leah-Sophie; Lettmaier, Sebastian; Semrau, Sabine; Müller, Sarina Katrin; Traxdorf, Maximilian; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Haderlein, Marlen (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Radiotherapy with paclitaxel/cisplatin vs. fluorouracil/cisplatin for head and neck cancer - Fietkau, Rainer; Hecht, Markus; Hofner, Benjamin; Iro, Heinrich; Gefeller, Olaf; Roedel, C.; Hautmann, M.; Koelbl, O.; Salay, A.; Ruebe, C.; Breinl, P.; Krings, W.; et al. (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

RAD-ON01 study: modulation of the peripheral immune system following a sequential radon spa therapy - Rühle, Paul-Friedrich; Kullmann, M.; Frey, Benjamin; Klein, G.; Fournier, Claudia; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (2017)
EVALuna2:32893

Radon affects Immune Cells ex vivo as well as in vivo in an Animal Model of experimental Arthritis - Deloch, Lisa; Rückert, Michael; Maier, A.; Hinrichs, A.; Flohr, Ann-Sophie; Eckert, D.; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Fournier, C.; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Radon Improves Clinical Response in an Animal Model of Rheumatoid Arthritis Accompanied by Increased Numbers of Peripheral Blood B Cells and Interleukin-5 Concentration - Deloch, Lisa; Hehlgans, Stephanie; Rückert, Michael; Maier, Andreas; Hinrichs, Annika; Flohr, Ann-Sophie; Eckert, Denise; Weissmann, Thomas; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Rödel, Franz; et al. (Cells, 2022)
Radon treatment is used as an established therapy option in chronic painful inflammatory diseases. While analgesic effects are well described, little is known about the underlying molecular effects. Among the suspected mechanisms are modulations of the anti-oxidative and the immune system. Therefore, we aimed for the first time to examine the beneficial effects of radon exposure on clinical outcome as well as the underlying mechanisms by utilizing a holistic approach in a controlled environment of a radon chamber with an animal model: K/BxN serum-induced arthritic mice as well as isolated cells were exposed to sham or radon irradiation. The effects on the anti-oxidative and the immune system were analyzed by flow-cytometry, qPCR or ELISA. We found a significantly improved clinical disease progression score in the mice, alongside significant increase of peripheral blood B cells and IL-5. No significant alterations were visible in the anti-oxidative system or regarding cell death. We conclude that neither cell death nor anti-oxidative systems are responsible for the beneficial effects of radon exposure in our preclinical model. Rather, radon slightly affects the immune system. However, more research is still needed in order to fully understand radon-mediated effects and to carry out reasonable risk-benefit considerations.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Anti-oxidative system; B cells; Immune system; Inflammation; Macrophages; Monocytes; Radon therapy; Rheumatoid arthritis; Serum transfer arthritis; T cells

Randomized phase 2 trial of chemoradiotherapy plus induction or consolidation chemotherapy as total neoadjuvant therapy for locally advanced rectal cancer: CAO/ARO/AIO-12 - Hofheinz, R.; Fokas, E.; Allgaeuer, M.; Polat, B.; Klautke, G.; Grabenbauer, G.; Fietkau, Rainer; Kuhnt, T.; Staib, L.; Brunner, T.; Grosu, A.; Schmiegel, W.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-08-09

Randomized phase-III-trial of concurrent chemoradiation for locally advanced head and neck cancer comparing dose reduced radiotherapy with paclitaxel/cisplatin to standard radiotherapy with fluorouracil/cisplatin: The PacCis-trial - Fietkau, Rainer; Hecht, Markus; Hofner, Benjamin; Lubgan, Dorota; Iro, Heinrich; Gefeller, Olaf; Rödel, Claus; Hautmann, Matthias G.; Kölbl, Oliver; Salay, Attila; Rübe, Christian; Melchior, Patrick; et al. (Radiotherapy and Oncology, 2020)
Background and purpose: This multicenter, phase 3 trial investigates whether the incorporation of concurrent paclitaxel and cisplatin together with a reduced total dose of radiotherapy is superior to standard fluorouracil–cisplatin based CRT. Materials and methods: Patients with SCCHN, stage III–IVB, were randomized to receive paclitaxel/cisplatin (PacCis)–CRT (arm A; paclitaxel 20 mg/m2 on days 2, 5, 8, 11 and 25, 30, 33, 36; cisplatin 20 mg/m2, days 1–4 and 29–32; RT to a total dose of 63.6 Gy) or fluorouracil/cisplatin (CisFU)–CRT (arm B; fluorouracil 600 mg/m2; cisplatin 20 mg/m2, days 1–5 and 29–33; RT: 70.6 Gy). Endpoint was 3-year-disease free survival (3y-DFS). Results: A total of 221 patients were enrolled between 2010 and 2015. With a median follow-up of 3.7 years, 3y-DFS in the CisFU arm and PacCis arm was 58.2% and 48.4%, respectively (HR 0.82, 95% CI 0.56–1.21, p = 0.52). The 3y-OS amounted to 64.6% in the CisFU arm, and to 59.2% in the PacCis arm (HR 0.82, 95% CI 0.54–1.24, p = 0.43). In the subgroup of p16-positive oropharyngeal carcinomas, 3y-DFS and 3y-OS was 84.6% vs 83.9% (p = 0.653), and 92.3% vs. 83.5% (p = 0.76) in arm A and B, respectively. Grade 3–4 hematological toxicities were significantly reduced in arm A (anemia, p = 0.01; leukocytopenia, p = 0.003), whereas grade 3 infections were reduced in arm B (p = 0.01). Conclusion: Paclitaxel/cisplatin–CRT with a reduced RT-dose is not superior to standard fluorouracil/cisplatin–CRT. Subgroup analyses indicate that a reduced radiation dose seems to be sufficient for p16+ oropharyngeal cancer or non-smokers. Clinical trial information: NCT01126216; EudraCT Number 2005-003484-23.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Chemoradiotherapy; Cisplatin; Fluorouracil; Head and neck cancer; Paclitaxel

Randomized Phase II Trial of Chemoradiotherapy Plus Induction or Consolidation Chemotherapy as Total Neoadjuvant Therapy for Locally Advanced Rectal Cancer: CAO/ARO/AIO-12 - Fokas, Emmanouil; Allgäuer, Michael; Polat, Bülent; Klautke, Gunther; Grabenbauer, Gerhard G.; Fietkau, Rainer; Kuhnt, Thomas; Staib, Ludger; Brunner, Thomas; Grosu, Anca-Ligia; Schmiegel, Wolff; Jacobasch, Lutz; et al. (Journal of Clinical Oncology, 2019)
PURPOSE: Total neoadjuvant therapy is a new paradigm for rectal cancer treatment. Optimal scheduling of preoperative chemoradiotherapy (CRT) and chemotherapy remains to be established. PATIENTS AND METHODS: We conducted a multicenter, randomized, phase II trial using a pick-the-winner design on the basis of the hypothesis of an increased pathologic complete response (pCR) of 25% after total neoadjuvant therapy compared with standard 15% after preoperative CRT. Patients with stage II or III rectal cancer were assigned to group A for induction chemotherapy using three cycles of fluorouracil, leucovorin, and oxaliplatin before fluorouracil/oxaliplatin CRT (50.4 Gy) or to group B for consolidation chemotherapy after CRT. Secondary end points included toxicity, compliance, and surgical morbidity. RESULTS: Of the 311 patients enrolled, 306 patients were evaluable (156 in group A and 150 in group B). CRT-related grade 3 or 4 toxicity was lower (37% v 27%) and compliance with CRT higher in group B (91%, 78%, and 76% v 97%, 87%, and 93% received full-dose radiotherapy, concomitant fluorouracil, and concomitant oxaliplatin in groups A and B, respectively); 92% versus 85% completed all induction/consolidation chemotherapy cycles, respectively. The longer interval between completion of CRT and surgery in group B (median 90 v 45 days in group A) did not increase surgical morbidity. A pCR in the intention-to-treat population was achieved in 17% in group A and in 25% in group B. Thus, only group B (P < .001), but not group A (P = .210), fulfilled the predefined statistical hypothesis. CONCLUSION: Up-front CRT followed by chemotherapy resulted in better compliance with CRT but worse compliance with chemotherapy compared with group A. Long-term follow-up will assess whether improved pCR in group B translates to better oncologic outcome.
CRIS-Team Scopus Importer:2019-12-10

Rate of individuals with clearly increased radiosensitivity rise with age both in healthy individuals and in cancer patients - Schuster, Barbara; Ellmann, Anna; Mayo, Theresa; Auer, Judith; Haas, Matthias; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (BMC Geriatrics, 2018)
BACKGROUND: The question of an age dependence of individual radiosensitivity has only marginally been studied so far. Therefore, we analyzed blood samples of healthy individuals and cancer patients of different ages to determine individual radiosensitivity. METHODS: Ex vivo irradiated blood samples of 595 individuals were tested. Chromosomes 1, 2 and 4 were stained by 3-color fluorescence in situ hybridization and aberrations were analyzed. Radiosensitivity was determined by the mean breaks per metaphase (B/M). RESULTS: Healthy individuals (mean age 50.7 years) had an average B/M value of 0.42 ± 0.104 and an increase of 0.0014B/M per year. The patients (mean age 60.4 years) had an average B/M value of 0.44 ± 0.150 and radiosensitivity did not change with age. In previous studies we found that from a value of 0.6B/M on an individual is considered to be distinctly radiosensitive. The portion of radiosensitive individuals (B/M > 0.6) increased in both cohorts with age. CONCLUSION: Individual radiosensitivity rises continuously with age, yet with strong interindividual variation. No age related increase of radiosensitivity can be demonstrated in patients due to the strong interindividual variation. However among old cancer patients there is a higher probability to have patients with clearly increased radiosensitivity than at younger age.
EVALuna2:36463

Reactivation of HCMV during RT of the brain results in critical illness and early mortality - Frey, Benjamin; Goerig, Nicole; Becker, Ina; Donaubauer, Anna-Jasmina; Korn, Klaus; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Putz, Florian; Semrau, Sabine; et al. (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Real-Time Respiratory Motion Analysis Using 4-D Shape Priors - Wasza, Jakob; Fischer, Peter; Leutheuser, Heike; Oefner, Tobias; Bert, Christoph; Maier, Andreas; Hornegger, Joachim (IEEE Transactions on Biomedical Engineering, 2016)
Respiratory motion analysis based on range imaging (RI) has emerged as a popular means of generating respiration surrogates to guide motion management strategies in computer-assisted interventions. However, existing approaches employ heuristics, require substantial manual interaction, or yield highly redundant information. In this paper, we propose a framework that uses preprocedurally obtained 4-D shape priors from patient-specific breathing patterns to drive intraprocedural RI-based real-time respiratory motion analysis. As the first contribution, we present a shape motion model enabling an unsupervised decomposition of respiration induced high-dimensional body surface displacement fields into a low-dimensional representation encoding thoracic and abdominal breathing. Second, we propose a method designed for GPU architectures to quickly and robustly align our models to high-coverage multiview RI body surface data. With our fully automatic method, we obtain respiration surrogates yielding a Pearson correlation coefficient (PCC) of 0.98 with conventional surrogates based on manually selected regions on RI body surface data. Compared to impedance pneumography as a respiration signal that measures the change of lung volume, we obtain a PCC of 0.96. Using off-the-shelf hardware, our framework enables high temporal resolution respiration analysis at 50 Hz.
Keywords: Graphics processing unit (GPU); radiation therapy; range imaging (RI); respiratory motion

Real-world outcomes with durvalumab after chemoradiotherapy in patients with unresectable stage III NSCLC: interim analysis of overall survival from PACIFIC-R - Filippi, A. R.; Bar, J.; Chouaid, C.; Christoph, D. C.; Field, J. K.; Fietkau, Rainer; Garassino, M. C.; Garrido, P.; Haakensen, V. D.; Kao, S.; Markman, B.; McDonald, F.; et al. (ESMO Open, 2024)
Background: Based on the findings of the PACIFIC trial, consolidation durvalumab following platinum-based chemoradiotherapy (CRT) is a global standard of care for patients with unresectable, stage III non-small-cell lung cancer (NSCLC). An earlier analysis from the ongoing PACIFIC-R study (NCT03798535) demonstrated the effectiveness of this regimen in terms of progression-free survival (PFS). Here, we report the first planned overall survival (OS) analysis. Patients and methods: PACIFIC-R is an observational/non-interventional, retrospective study of patients with unresectable, stage III NSCLC who started durvalumab (10 mg/kg intravenously every 2 weeks) within an AstraZeneca-initiated early access program between September 2017 and December 2018. Primary endpoints are OS and investigator-assessed PFS, estimated using the Kaplan–Meier method. Results: By 30 November 2021, the full analysis set included 1154 participants from 10 countries (median follow-up in censored patients: 38.7 months). Median OS was not reached, and the 3-year OS rate was 63.2% (95% confidence interval 60.3% to 65.9%). Three-year OS rates were numerically higher among patients with programmed death-ligand 1 (PD-L1) expression on ≥1% versus <1% of tumor cells (TCs; 67.0% versus 54.4%) and patients who received concurrent CRT (cCRT) versus sequential CRT (sCRT) (64.8% versus 57.9%). Conclusions: PACIFIC-R data continue to provide evidence for the effectiveness of consolidation durvalumab after CRT in a large, diverse, real-world population. Better outcomes were observed among patients with PD-L1 TCs ≥1% and patients who received cCRT. Nevertheless, encouraging outcomes were still observed among patients with TCs <1% and patients who received sCRT, supporting use of consolidation durvalumab in a broad population of patients with unresectable, stage III NSCLC.
CRIS-Team Scopus Importer:2024-06-14
Keywords: durvalumab; immunotherapy; locally advanced NSCLC; PD-L1; real-world evidence

Recent advanced in Surface Guided Radiation Therapy - Freislederer, P.; Kügele, M.; Öllers, M.; Swinnen, A.; Sauer, Tim-Oliver; Bert, Christoph; Giantsoudi, D.; Corradini, S.; Batista, V. (Radiation Oncology, 2020)
The growing acceptance and recognition of Surface Guided Radiation Therapy (SGRT) as a promising imaging technique has supported its recent spread in a large number of radiation oncology facilities. Although this technology is not new, many aspects of it have only recently been exploited. This review focuses on the latest SGRT developments, both in the field of general clinical applications and special techniques.SGRT has a wide range of applications, including patient positioning with real-time feedback, patient monitoring throughout the treatment fraction, and motion management (as beam-gating in free-breathing or deep-inspiration breath-hold). Special radiotherapy modalities such as accelerated partial breast irradiation, particle radiotherapy, and pediatrics are the most recent SGRT developments.The fact that SGRT is nowadays used at various body sites has resulted in the need to adapt SGRT workflows to each body site. Current SGRT applications range from traditional breast irradiation, to thoracic, abdominal, or pelvic tumor sites, and include intracranial localizations.Following the latest SGRT applications and their specifications/requirements, a stricter quality assurance program needs to be ensured. Recent publications highlight the need to adapt quality assurance to the radiotherapy equipment type, SGRT technology, anatomic treatment sites, and clinical workflows, which results in a complex and extensive set of tests.Moreover, this review gives an outlook on the leading research trends. In particular, the potential to use deformable surfaces as motion surrogates, to use SGRT to detect anatomical variations along the treatment course, and to help in the establishment of personalized patient treatment (optimized margins and motion management strategies) are increasingly important research topics. SGRT is also emerging in the field of patient safety and integrates measures to reduce common radiotherapeutic risk events (e.g. facial and treatment accessories recognition).This review covers the latest clinical practices of SGRT and provides an outlook on potential applications of this imaging technique. It is intended to provide guidance for new users during the implementation, while triggering experienced users to further explore SGRT applications.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Deep-inspiration breath-hold; Intra-fractional motion mitigation; Motion management; Patient positioning; Patient safety; SGRT; Surface guided radiation therapy

Recurrent glioblastoma: who receives tumor specific treatment and how often? - Steffens, Rieke; Semrau, Sabine; Lahmer, Godehard; Putz, Florian; Lettmaier, Sebastian; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Fietkau, Rainer (Journal of Neuro-Oncology, 2016)
The recurrence of glioblastoma (rGBM) is inevitable and often short-term. Therefore, information on the prognosis and effectiveness of tumor-specific versus purely palliative approaches should be more in-depth than a mere list of available treatment options for patients in this situation. However, follow-up data on the course of the disease in unselected patient populations after completion of primary treatment are scarce. This single-center analysis investigated the rate and number of glioblastoma recurrences after initial radiotherapy in 189 consecutive GM patients, focusing on the incidence of early death and the frequency of tumor-specific treatment (TST) versus best-supportive care (BSC) as well as the outcomes for the different approaches. In 61 % of initial population first recurrence (rGBM) could be determined by histology or imaging. 47 % received TST. 58 % of the patients with rGBM and TST were diagnosed with a second recurrence. Up to five recurrences were treated. 35-45 % of patients died before undergoing imaging studies to confirm the next recurrence. Multivariate analysis identified male sex and KPS score as independent factors (p < 0.01) for the choice of TST over BSC. Median overall survival from the diagnosis of first recurrence was 267 days in the TST group versus 65 days in patients receiving BSC (p < 0.0001). Nearly half of all rGBM patients received second-line TST, but a remarkably high proportion died early. Gender and KPS played a role in the choice of TST over BSC for recurrence treatment.
EVALuna2:18351

Reduction of elective radiotherapy treatment volume in definitive treatment of locally advanced head and neck cancer—comparison of a prospective trial with a revised simulated contouring approach - Weissmann, Thomas; Speer, Stefan; Putz, Florian; Lettmaier, Sebastian; Schubert, Philipp; Shariff, Maya; Semrau, Sabine; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Müller, Sarina Katrin; Eckstein, Markus; Hautmann, Matthias; et al. (Journal of Clinical Medicine, 2021)
Definitive radiochemotherapy of locally advanced head and neck squamous cell cancer (HNSCC) achieves high locoregional tumor control rates; but is frequently associated with long-term toxicity. A future direction could be a de-escalation strategy focusing on treated volume rather than radiotherapy dose. This analysis evaluates radiotherapy dose and volume parameters of patients treated with a standard contouring approach in a clinical trial context compared with a revised volume-reduced contouring approach. In this case, 30 consecutive patients from the CheckRad-CD8 trial treated at a single study center were included in this analysis. Treatment toxicity and quality of life were assessed at the end of radiotherapy. Standard treatment plans (ST) following state of the art contouring guidelines that were used for patient treatment and volume reduced treatment plans (VRT) according to a revised simulated approach were calculated for each patient. Planning target volumes (PTV) and mean doses to 38 organs-at-risk structures were compared. At the end of radiotherapy patients reported high rates of mucositis; dysphagia and xerostomia. In addition; patient reported quality of life as assessed by the EORTC QLQ-HN35 questionnaire deteriorated. Comparing the two contouring approaches; the elective PTV_56 Gy and the high risk PTV_63 Gy (shrinking field) were significantly smaller in the VRT group. Significant reduction of mean dose to structures of the oral cavity; the larynx as well as part of the swallowing muscles and the submandibular glands was achieved in the simulated VRT-plan. Treatment de-intensification by reduction of the irradiated volume could potentially reduce treatment volume and mean doses to organs at risk. The proposed contouring approach should be studied further in the context of a clinical trial.
CRIS-Team Scopus Importer:2021-10-22
Keywords: De-intensification; Definitive treatment; Head neck cancer; Radiotherapy; Salivary glands; Swallowing function; Volume reduc-tion

Regional deep hyperthermia: impact of observer variability in CT-based manual tissue segmentation on simulated temperature distribution - Aklan, Bassim; Hartmann, Josefin; Zink, Diana; Siavooshhaghighi, Hadi; Merten, Ricarda; Putz, Florian; Ott, Oliver; Fietkau, Rainer; Bert, Christoph (Physics in Medicine and Biology, 2017)
The aim of this study was to systematically investigate the influence of the inter- and intra-observer segmentation variation of tumors and organs at risk on the simulated temperature coverage of the target. CT scans of six patients with tumors in the pelvic region acquired for radiotherapy treatment planning were used for hyperthermia treatment planning. To study the effect of inter-observer variation, three observers manually segmented in the CT images of each patient the following structures: fat, muscle, bone and the bladder. The gross tumor volumes (GTV) were contoured by three radiation oncology residents and used as the hyperthermia target volumes. For intra-observer variation, one of the observers of each group contoured the structures of each patient three times with a time span of one week between the segmentations. Moreover, the impact of segmentation variations in organs at risk (OARs) between the three inter-observers was investigated on simulated temperature distributions using only one GTV. The spatial overlap between individual segmentations was assessed by the Dice similarity coefficient (DSC) and the mean surface distance (MSD). Additionally, the temperatures T90/T10 delivered to 90%/10% of the GTV, respectively, were assessed for each observer combination. The results of the segmentation similarity evaluation showed that the DSC of the inter-observer variation of fat, muscle, the bladder, bone and the target was 0.68 ± 0.12, 0.88 ± 0.05, 0.73 ± 0.14, 0.91 ± 0.04 and 0.64 ± 0.11, respectively. Similar results were found for the intra-observer variation. The MSD results were similar to the DSCs for both observer variations. A statistically significant difference (p < 0.05) was found for T90 and T10 in the predicted target temperature due to the observer variability. The conclusion is that intra- and inter-observer variations have a significant impact on the temperature coverage of the target. Furthermore, OARs, such as bone and the bladder, may essentially influence the homogeneity of the simulated target temperature distribution.
EVALuna2:32876

Regional hyperthermia with cisplatin added to gemcitabine versus gemcitabine in patients with resected pancreatic ductal adenocarcinoma: The HEAT randomised clinical trial - Issels, Rolf D.; Boeck, Stefan; Pelzer, Uwe; Mansmann, Ulrich; Ghadjar, Pirus; Lindner, Lars H.; Albertsmeier, Markus; Angele, Martin K.; Schmidt, Michael; Xu, Yujun; Bahra, Marcus; Pratschke, Johann; et al. (European Journal of Cancer, 2023)
Background: Regional hyperthermia (RHT) with cisplatin added to gemcitabine showed efficacy in gemcitabine-pre-treated patients with advanced pancreatic ductal adenocarcinoma. We conducted a randomised clinical trial to investigate RHT with cisplatin added to gemcitabine (GPH) compared with gemcitabine (G) in the adjuvant setting of resected pancreatic ductal adenocarcinoma. Methods: This randomised, multicentre, open-label trial randomly assigned patients to either GPH (gemcitabine 1000 mg/m2 on day 1, 15 and cisplatin 25 mg/m2 with RHT on day 2, 3 and 15,16) or to G (gemcitabine 1000 mg/m2 on day 1,8,15), four-weekly over six cycles. Disease-free survival (DFS) was the primary end-point. Secondary end-points included overall survival (OS) and safety. Results: A total of 117 eligible patients (median age, 63 years) were randomly allocated to treatment (57 GPH; 60 G). With a follow-up time of 56.6 months, the median DFS was 12.7 compared to 11.2 months for GPH and G, respectively (p = 0.394). Median post-recurrence survival was significantly prolonged in the GPH-group (15.3 versus 9.8 months; p = 0.031). Median OS reached 33.2 versus 25.2 months (p = 0.099) with 5-year survival rates of 28.4% versus 18.7%. Excluding eight patients who received additional capecitabine in the G-arm (investigators choice), median OS favoured GPH (p = 0.052). Adverse events CTCAE (Common Terminology Criteria for Adverse Events) grade ≥3 occurred in 61.5% (GPH) versus 63.6% (G) of patients. Two patients in the G-group died because of treatment-related toxic effects. Conclusions: The randomised controlled Hyperthermia European Adjuvant Trial study failed to demonstrate a significant difference in DFS. However, it suggests a difference in post-recurrence survival and a trend for improved OS. ClinicalTrials: gov, number NCT01077427.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Adjuvant chemotherapy; Cisplatin; Gemcitabine; HEAT study; Pancreatic cancer; Randomised clinical trial; Regional hyperthermia

Region of interest optimization for radiation therapy of breast cancer - Sauer, Tim-Oliver; Ott, Oliver; Lahmer, Godehard; Fietkau, Rainer; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2021)
Purpose: The goal of this study was to investigate how the choice of the region of interest (ROI) affects the registration results of surface imaging for daily positioning of breast cancer patients. Methods: The AlignRT system (VisionRT, London) and the XVI Cone beam CT (CBCT; Elekta, Stockholm) installed on two Versa HD linacs (Elekta) were used in this study, which included 28 patients (160 fractions). In the clinical workflow, patients were prepositioned with AlignRT and then shifted in 6 degrees of freedom (DOF) according to the CBCT. A new reference capture was taken immediately afterward. Retrospectively, the surface capture resulting from prepositioning was registered to the latest reference capture. By varying the ROI used for registration, the surface-based results were optimized in terms of minimizing the deviation to the clinically applied CBCT shifts. Two sets of ROIs were used: one obtained by applying a variable margin to the breast surface, another by combining ROIs of anatomical structures, including the sternum and contralateral breast. Results: Registration results showed significant differences from one ROI to another. Generally, the results improved with increasing ROI size, especially for rotational DOFs. ROIs, including the axilla or supraclavicular lymph drainage region, did not yield an improved registration result. On the other hand, an ROI comprising the breast surface, sternum, and a belt caudal to the breasts decreased the average magnitude of the translational and rotational deviations by 6.6% and 30.8% (p < 0.01), respectively, compared to the breast surface only results. Conclusion: The influence of the ROI choice on surface imaging registration results was analyzed and the surface-based shifts were compared to clinically applied CBCT shifts. An optimal ROI for the treatment of breast cancer patients, consisting of the breast surface, sternum, and a belt, was identified.
CRIS-Team Scopus Importer:2021-10-01
Keywords: breast cancer; radiation therapy; surface guided radiation therapy

Regulatory T cells and cytotoxic T cells close to the epithelial–stromal interface are associated with a favorable prognosis - Rudolf, Julian; Büttner-Herold, Maike; Erlenbach-Wuensch, Katharina; Posselt, Rebecca; Jeßberger, Jonas; Haderlein, Marlen; Hecht, Markus; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (OncoImmunology, 2020)
Cytotoxic T cells and regulatory T cells play a crucial role in the outcome of cancer patients. Besides the density of these cells, it was shown recently that the spatial distribution is equally important. Here, we specifically analyzed the spatial distribution of these T cell subtypes at the epithelial–stromal interface in a rectal cancer cohort and its relevance for prognosis. We studied a cohort of 191 patients with advanced rectal cancer treated by radiochemotherapy (RCT). Tissue microarrays were immunohistochemical double-stained by FoxP3+ and CD+. Cell densities were analyzed in the stromal and epithelial compartment. Additionally, an image analysis software calculated the distances of lymphocytes to the epithelial–stromal interface (ESI). CD8+ and FoxP3+ cell counts decreased clearly after RCT with the decrease of FoxP3+ being more pronounced than of CD8+ cells. In the invasive front, short distances of the ESI to CD8+ and to FoxP3+ cells were associated with improved overall survival. Cell counts in the stromal compartment had no influence on prognosis. No correlation between stromal and epithelial lymphocyte densities was observed. The distance of epithelial–stromal interface to CD8+ and FoxP3+ cells was more accurate in predicting prognosis in the stromal compartment of rectal cancer patients than mere cell counts and could thereby be means of better stratifying patients for therapy. This observation will have to be validated in future prospective studies with regard to other tumor entities and its implications for the responsiveness of tumors to new therapeutic modalities.
CRIS-Team Scopus Importer:2020-04-28
Keywords: epithelial–stromal interface; rectal cancer; regulatory T cells; spatial distribution; ﻿cytotoxic T cells

Reirradiation for recurrent head and neck cancer with salvage interstitial pulsed-dose-rate brachytherapy: Long-term results - Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer (Strahlentherapie und Onkologie, 2015)
To assess the long-term results of protocol-based interstitial pulsed-dose-rate (PDR) brachytherapy as reirradiation combined with simultaneous chemotherapy and interstitial hyperthermia in selected patients with recurrent head and neck tumors.A total of 104 patients with biopsy-proven recurrent head and neck cancer were treated with interstitial PDR brachytherapy. Salvage surgery had also been undergone by 53/104 (51%) patients (R1 or R2 resection in > 80% of patients). Salvage brachytherapy alone was administered in 81 patients (78%), with a median total dose of 56.7 Gy. Salvage brachytherapy in combination with external beam radiotherapy (EBRT) was performed in 23/104 patients (32%), using a median total dose of DREF = 24 Gy. Simultaneously to PDR brachytherapy, concomitant chemotherapy was administered in 58/104 (55.8%) patients. A single session of interstitial hyperthermia was also used to treat 33/104 (31.7%) patients. The analysis was performed after a median follow-up of 60 months.Calculated according to Kaplan-Meier, local tumor control rates after 2, 5, and 10 years were 92.5, 82.4, and 58.9%, respectively. Comparing results of salvage PDR brachytherapy with or without simultaneous chemotherapy, the 10-year local control rates were 76 vs. 39% (p = 0014), respectively. No other patient- or treatment-related parameters had a significant influence on treatment results. Soft tissue necrosis or bone necrosis developed in 18/104 (17.3%) and 11/104 (9.6%) patients, respectively, but only 3% of patients required surgical treatment.PDR interstitial brachytherapy with simultaneous chemotherapy is a very effective and, in experienced hands, also a safe treatment modality in selected patients with head and neck cancer in previously irradiated areas.
EVALuna2:18289

Reirradiation of recurent glioblastomas: High prognostic significance of contrast-enhancing tumor volume - Mansoorian, Sina; Coras, Roland; Weissmann, Thomas; Lettmaier, Sebastian; Semrau, Sabine; Frey, Benjamin; Bert, Christoph; Schmidt, M.; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Re-irradiation of the chest wall for local breast cancer recurrence : Results of salvage brachytherapy with hyperthermia - Auoragh, A.; Strnad, Vratislav; Ott, O. J.; Beckmann, Matthias; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
Following mastectomy and adjuvant external beam radiation therapy in patients with breast cancer, the incidence of local or locoregional recurrence is approximately 9 % (2-20 %). Alongside the often limited possibilities of surgical treatment, radiation therapy combined with superficial hyperthermia is the most effective local therapy. In the present work, a retrospective analysis of salvage brachytherapy combined with superficial hyperthermia for chest wall recurrences is presented.Between 2004 and 2011, 18 patients with a total of 23 target volumes resulting from chest wall recurrences after previously mastectomy and external beam radiation therapy (median 56 Gy, range 50-68 Gy) were treated with superficial brachytherapy as salvage treatment: 8 patients (44 %) had macroscopic tumor, 3 (17 %) had microscopic tumor (R1), and 7 (39 %) had undergone R0 resection and were treated due to risk factors. A dose of 50 Gy was given (high-dose rate [HDR] and pulsed-dose rate [PDR] procedures). In all, 5 of 23 patients (22 %) received additional concurrent chemotherapy, and in 20 of 23 (87 %) target volumes additional superficial hyperthermia was carried out twice weekly.The 5-year local recurrence-free survival was 56 %, the disease-free survival was 28 %, and a 5-year overall survival was 22 %. Late side effects Common Toxicity Criteria (CTC) grade 3 were reported in 17 % of the patients: 2 of 18 (11 %) had CTC grade 3 fibrosis, and 1 of 18 (6 %) had a chronic wound healing disorder.Re-irradiation as salvage brachytherapy with superficial hyperthermia for chest wall recurrences is a feasible and safe treatment with good local control results and acceptable late side effects.
EVALuna2:18364

Re-irradiation with interstitial pulsed-dose-rate brachytherapy for unresectable recurrent head and neck carcinoma - Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer (Brachytherapy, 2014)
To assess the long-term results of protocol-based interstitial pulsed-dose-rate (PDR) brachytherapy combined with simultaneous chemotherapy in selected patients with recurrent head and neck tumors not amenable to salvage surgery.A total of 51 patients with recurrent head and neck cancer were treated with interstitial PDR brachytherapy. Forty patients (78%) had salvage brachytherapy alone using a median total dose of 60 Gy. Salvage brachytherapy in combination with external beam therapy was performed in 11 patients (22%) using a median total dose of DREF=27 Gy. Simultaneously with the PDR brachytherapy, a concomitant chemotherapy was administered in 35/51 (69%) of patients. The analysis was performed after a median followup of 58 months.Local control rates calculated according to Kaplan-Meier after 2 and 5 years were 71% and 57%, respectively. Comparing results of salvage PDR brachytherapy with or without simultaneous chemotherapy, the 5-year local recurrence-free survival rates were 78.9% vs. 38.5% (p=0.01), respectively. No other patient or treatment-related parameters had a significant influence on treatment results. A total of 9/51 (17.7%) and 6/51 (11.8%) patients developed soft-tissue necrosis or bone necrosis, respectively, but only 2% of patients required surgical treatment.PDR interstitial brachytherapy with pulse doses between 0.4 and 0.7 Gy/h/24 h with simultaneous chemotherapy is an effective and safe option for curative therapy in selected patients with head and neck cancer in previously irradiated areas, which are not suitable for salvage surgery.
EVALuna2:18174

Relevance of the time interval between surgery and adjuvant radio (chemo) therapy in HPV-negative and advanced head and neck carcinoma of unknown primary (CUP) - Balk, Matthias; Rupp, Robin; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Müller-Hübner, Sarina; Traxdorf, Maximilian; Eckstein, Markus; Speer, Stefan; Semrau, Sabine; Fietkau, Rainer; Iro, Heinrich; et al. (BMC Cancer, 2021)
Introduction In contrast to head and neck squamous cell carcinoma (HNSCC), the effect of treatment duration in HNSCC-CUP has not been thoroughly investigated. Thus, this study aimed to assess the impact of the time interval between surgery and adjuvant therapy on the oncologic outcome, in particular the 5-year overall survival rate (OS), in advanced stage, HPV-negative CUPs at a tertiary referral hospital. 5-year disease specific survival rate (DSS) and progression free survival rate (PFS) are defined as secondary objectives. Material and methods Between January 1st, 2007, and March 31st, 2020 a total of 131 patients with CUP were treated. Out of these, 59 patients with a confirmed negative p16 analysis were referred to a so-called CUP-panendoscopy with simultaneous unilateral neck dissection followed by adjuvant therapy. The cut-off between tumor removal and delivery of adjuvant therapy was set at the median, i.e. patients receiving adjuvant therapy below or above the median time interval. Results Depending on the median time interval of 55 days (d) (95% CI 51.42-84.52), 30 patients received adjuvant therapy within 55 d (mean 41.69 d, SD = 9.03) after surgery in contrast to 29 patients at least after 55 d (mean 73.21 d, SD = 19.16). All patients involved in the study were diagnosed in advanced tumor stages UICC III (n = 4; 6.8%), IVA (n = 27; 45.8%) and IVB (n = 28; 47.5%). Every patient was treated with curative neck dissection. Adjuvant chemo (immune) radiation was performed in 55 patients (93.2%), 4 patients (6.8%) underwent adjuvant radiation only. The mean follow-up time was 43.6 months (SD = 36.7 months). The 5-year OS rate for all patients involved was 71% (95% CI 0.55-0.86). For those patients receiving adjuvant therapy within 55 d (77, 95% CI 0.48-1.06) the OS rate was higher, yet not significantly different from those with delayed treatment (64, 95% CI 0.42-0.80; X-(1)(2) = 1.16, p = 0.281). Regarding all patients, the 5-year DSS rate was 86% (95% CI 0.75-0.96). Patients submitted to adjuvant treatment in less than 55 d the DSS rate was 95% (95% CI 0.89-1.01) compared to patients submitted to adjuvant treatment equal or later than 55 d (76% (95% CI 0.57-0.95; X-(1)(2) = 2.32, p = 0.128). The 5-year PFS rate of the entire cohort was 72% (95% CI 0.59-0.85). In the group < 55 d the PFS rate was 78% (95% CI 0.63-0.94) and thus not significantly different from 65% (95% CI 0.45-0.85) of the group >= 55 d; (X-(1)(2) = 0.29, p = 0.589). Conclusions The results presented suggest that the oncologic outcome of patients with advanced, HPV-negative CUP of the head and neck was not significantly affected by a prolonged period between surgery and adjuvant therapy. Nevertheless, oncologic outcome tends to be superior for early adjuvant therapy.
CRIS-Team WoS Importer:2021-12-03

Relevance of the time interval between surgery and adjuvant radio (chemo) therapy in HPV-negative and advanced head and neck carcinoma of unknown primary (CUP) - Balk, Matthias; Rupp, Robin; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Müller, Sarina Katrin; Traxdorf, Maximilian; Eckstein, Markus; Speer, Stefan; Semrau, Sabine; Fietkau, Rainer; Iro, Heinrich; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Reliability of determining the resectability of locally progressed pancreatic ductal adenocarcinomas - results from the CONKO-007 multicenter randomized controlled trial (EudraCT:2009-014476-21) - Wittel, U. A.; Golcher, H.; Gruetzmann, R.; Bechstein, W. O.; Belyaev, O.; Uhl, W.; Ghadimi, M.; Hopt, U.; Pirkl, A.; Lubgan, Dorota; Hohenberger, Werner; Oettle, H.; et al. (2018)
EVALuna2:36518

Repeating of local therapy of distant metastases increases overall survival in patients with synchronous metastasized rectal cancer-a monocentric analysis - Haderlein, Marlen; Lettmaier, Sebastian; Langheinrich, Melanie; Schmid, Axel; Semrau, Sabine; Hecht, Markus; Beck, Michael; Schmidt, Daniela; Grützmann, Robert; Fietkau, Rainer; Denz, Axel (International Journal of Colorectal Disease, 2018)
PURPOSE: The aim was to evaluate the outcome of treatment-naive patients with synchronous metastatic rectal cancer after chemotherapy with FOLFOXIRI followed by local therapeutic procedures of all tumor lesions as complete as possible. METHODS: We reviewed data of 30 patients with synchronous distant metastatic rectal cancer who underwent chemotherapy with FOLFOXIRI and subsequent local therapy in our institution. RESULTS: Median follow-up was 28 months (range: 8; 74). Cumulative overall survival (OS) and progression-free survival (PFS) was 93.3, 76.9, 55.6% and 46.2, 29.7, 29.7% after 1, 2, 4 years. Non-response to chemotherapy with FOLFOXIRI was associated with a highly significant decreased OS (p < 0.0001). The consistent use of local ablative procedures led to a statistically significant increase in OS (p < 0.0001), but not in PFS (p = 0.635). Patients with ≤ 4 distant metastases showed a better OS (p = 0.033). CONCLUSIONS: Response to intensified first-line chemotherapy with FOLFOXIRI, treatment of the primary rectal tumor, and repeated thorough local ablative procedures in patients with synchronous metastasized rectal cancer may lead to long-term survival, even in a subset of patients with unresectable disease at initial diagnosis.
EVALuna2:36458

Reporting and Evaluation System for Incidents in the Radiation Therapy to increase Patient Safety, Treatment Quality and the Efficiency of Process Flows - Kornek, Dominik; Lang-Welzenbach, Marga; Beck, A.; Reinhardt, A.; Brandt, Tobias; Bert, Christoph (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Required transition from research to clinical application: Report on the 4D treatment planning workshops 2014 and 2015 - Knopf, Antje-Christin; Stuetzer, Kristin; Richter, Christian; Rucinski, Antoni; Da Silva, Joakim; Phillips, Justin; Engelsman, Martijn; Shimizu, Shinichi; Werner, Rene; Jakobi, Annika; Goksel, Orcun; Zhang, Ye; et al. (Physica Medica, 2016)
Since 2009, a 4D treatment planning workshop has taken place annually, gathering researchers working on the treatment of moving targets, mainly with scanned ion beams. Topics discussed during the workshops range from problems of time resolved imaging, the challenges of motion modelling, the implementation of 4D capabilities for treatment planning, up to different aspects related to 4D dosimetry and treatment verification. This report gives an overview on topics discussed at the 4D workshops in 2014 and 2015. It summarizes recent findings, developments and challenges in the field and discusses the relevant literature of the recent years. The report is structured in three parts pointing out developments in the context of understanding moving geometries, of treating moving targets and of 4D quality assurance (QA) and 4D dosimetry. The community represented at the 4D workshops agrees that research in the context of treating moving targets with scanned ion beams faces a crucial phase of clinical translation. In the coming years it will be important to define standards for motion monitoring, to establish 4D treatment planning guidelines and to develop 4D QA tools. These basic requirements for the clinical application of scanned ion beams to moving targets could e.g. be determined by a dedicated ESTRO task group. Besides reviewing recent research results and pointing out urgent needs when treating moving targets with scanned ion beams, the report also gives an outlook on the upcoming 4D workshop organized at the University Medical Center Groningen (UMCG) in the Netherlands at the end of 2016.
EVALuna2:33049

Residual motion mitigation in scanned carbon ion beam therapy of liver tumors using enlarged pencil beam overlap - Richter, Daniel; Graeff, Christian; Jaekel, Oliver; Combs, Stephanie E.; Durante, Marco; Bert, Christoph (Radiotherapy and Oncology, 2014)
Interplay effects may limit the applicability of scanned ion beam therapy for moving tumors even if the motion amplitude is reduced by techniques such as gating or abdominal compression (AC). We investigate the potential of enhanced pencil beam overlap to mitigate residual motion interplay effects in scanned ion beam therapy.Eight patients with hepato cellular carcinoma were selected who were either treated under AC (5 clinical target volumes (CTVs)) or with gating (6 CTVs). We performed 4D dose calculations for treatment plans with variable beam parameters (lateral raster spacing, beam full-width-at-half-maximum (FWHM), iso-energy slice spacing, gating window (GW)) and assessed under- and overdose (V95 and V107), dose homogeneity (HI=D5-D95), and dose volume histograms. The influence of the beam parameters on HI was studied by multivariate regression models.Motion amplitude and FWHM had the largest impact on dose homogeneity, while decreased iso-energy slice spacing and lateral raster spacing had a much smaller or no significant effect, respectively. The multivariate regression models including FWHM, motion amplitude, and IES-spacing explained 86%, 42%, and 71% of the observed variance for AC, 30% and 50% GW, respectively.Residual motion in scanned carbon ion therapy of liver tumors can lead to considerable dose heterogeneities. Using an increased beam spot size dose degradation can be significantly mitigated. Especially for large tumors, increasing the beam spot size is an efficient motion mitigation option readily available at most scanning facilities.
EVALuna2:18311

Respiratory Deformation Estimation in X-Ray-Guided IMRT Using a Bilinear Model - Geimer, Tobias; Ploner, Stefan; Keall, Paul; Bert, Christoph; Maier, Andreas (Informatik aktuell, 2019)
Driving a respiratory motion model in X-ray guided radiotherapy can be challenging in treatments with continuous rotation such as VMAT, as data-driven respiratory signal extraction suffers from angular effects overlapping with respiratory changes in the projection images. Compared to a linear model trained on static acquisition angles, the bilinear model gains flexibility in terms of handling multiple viewpoints at the cost of accuracy. In this paper, we evaluate both models in the context of serving as the surrogate input to a motion model. Evaluation is performed on the 20 patient 4D CTs in a leave-one-phase-out approach yielding a median accuracy drop of only 0.14mm in the 3D error of estimated vector fields of the bilinear model compared to the linear one.
CRIS-Team Scopus Importer:2019-05-14

Response to 6 cycles of chemotherapy with FOLFIRINOX is predictive of overall survival in patients with locally advanced unresectable pancreatic cancer - Haderlein, Marlen; Lubgan, Dorota; Lettmaier, S.; Semrau, S.; Wolf, W.; Golcher, H.; Hohenberger, Werner; Fietkau, Rainer (2016)
EVALuna2:15236

Results of a randomized phase II study comparing pembrolizumab with methotrexate in elderly, frail or cisplatin-ineligible patients with relapsed or metastatic squamous cell carcinoma of the head and neck (RM-SCCHN) (ELDORANDO-AIO-KHT-0115) - Gruenwald, V.; Graeven, U.; Ivanyi, P.; Dietz, A.; Hahn, D.; Hackenberg, S.; Kasper, S.; Fietkau, Rainer; Moulin, J-C.; Pink, D.; Schaaf, M.; Klinghammer, K. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-10-15

Results of brachytherapy trials - Strnad, Vratislav (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-18

Results of Re-Chemoradiotherapy in Patients with relapsed Glioblastoma WHO IV - Mansoorian, S.; Lettmaier, S.; Goerig, Nicole; Weissmann, T.; Semrau, S.; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Risk analysis for radiotherapy at the Universitätsklinikum Erlangen - Lohmann, Daniel; Lang-Welzenbach, Marga; Feldberger, Lorenz; Sommer, Ellen; Bücken, Stefan; Lotter, Michael; Ott, Oliver; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Purpose: Risk analysis is required by various laws and regulations in Germany and has an impact on each department of a large clinic. We provide an overview of the relevant laws and regulations in Germany and present the technical and organizational experience of introducing risk analysis in the Department of Radiation Oncology at the Universitätsklinikum Erlangen. Methods: Risk analysis was performed with an in-house developed extension of our intranet platform and ticketing system. Risks were classified according to occurrence and severity, each on a 5-level scale resulting into a risk matrix. An interdisciplinary team of six experienced members formed the core meeting weekly. Results: A total of 38 risks and 50 measures have been identified in 41 1 h-meetings corresponding to approx. 260 working hours. Risk was distributed 8/20/13 to the categories critical (n = 8), monitoring (n = 20), and conditionally acceptable (n = 13). Risk analysis has been evaluated before and after introducing measures. Conclusion: The risk analysis method introduced has been successfully used in routine operations for over a year. Risk analysis takes time and effort. However, because experts from different disciplines meet each other every week, the overall workflow of the radiation oncology department can be improved efficiently and continuously.
CRIS-Team Scopus Importer:2022-04-01
Keywords: GBA; Radiation therapy; Risk analysis; Strahlenschutzverordnung

Risk management in radiation-based therapies - Bert, Christoph (Zeitschrift für Medizinische Physik, 2024)
CRIS-Team Scopus Importer:2024-06-21

ROI optimisation for surface guided radiation therapy - Sauer, Tim-Oliver; Popp, D.; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Role of tumor cell senescence in non-professional phagocytosis and cell-in-cell structure formation - Gottwald, Dorian; Putz, Florian; Hohmann, Nora; Büttner-Herold, Maike; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (BMC Molecular and Cell Biology, 2020)
Background: Non-professional phagocytosis is usually triggered by stimuli such as necrotic cell death. In tumor therapy, the tumors often disappear slowly and only long time after the end of therapy. Here, tumor therapy inactivates the cells by inducing senescence. Therefore, study focused whether senescence is a stimulus for non-professional phagocytosis or whether senescent cells themselves phagocytize non-professionally. Results: Senescence was induced in cell lines by camptothecin and a phagocytosis assay was performed. In tissue of a cohort of 192 rectal cancer patients senescence and non-professional phagocytosis was studied by anti-histone H3K9me3 and anti-E-cadherin staining. Senescent fibroblasts and pancreas carcinoma cells phagocytize necrotic cells but are not phagocytized. In the tissue of rectal carcinoma, senescent cells can phagocytize and can be phagocytized. A high number of senescent cells and, at the same time, high numbers of non-professional phagocytizing cells in the rectal carcinoma tissue lead to an extremely unfavorable prognosis regarding overall survival. Conclusion: Senescent cells can be non-professionally phagocytized and at the same time they can non-professionally phagocytize in vivo. In vitro experiments indicate that it is unlikely that senescence is a strong trigger for non-professional phagocytosis. Combined high rates of non-professional phagocytosis and high rates of senescence are an extremely poor prognostic factor for overall survival.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Camptothecin; Cannibalism; Cell-in-cell; Entosis; Non-professional phagocytosis; Prognostic factor and survival; Rectal cancer; Senescence

Rolle der Radiotherapie beim Pankreaskarzinom - Goerig, Nicole; Fietkau, Rainer (Onkologe, 2019)
Background: Pancreatic cancer is a tumor with a worldwide incidence of approximately 340,000 newly diagnosed patients per year. With a 5-year overall survival of 2–6% the prognosis is very poor. At the time of diagnosis, resection is the only curative option primarily possible for approximately 30% of the patients. Chemoradiotherapy is a treatment option for achieving resectability of primarily unresectable tumors, improving the results of surgery and also for increasing survival of definitively inoperable patients with advanced states of the disease. Objective: This article gives a current overview on the role of radiotherapy for treatment of pancreatic cancer. Material and methods: Literature analysis of fundamental studies, original and review articles and of current trials. Results: Data from prospective and retrospective analyses show that neoadjuvant chemoradiotherapy of pancreatic cancer increases the number of resectable patients and improves the overall survival. There are comparable data for adjuvant chemoradiotherapy of resected patients with additional risk factors (R1, N +). In cases where resection is definitively impossible, chemoradiotherapy also contributes to local tumor control and improving therapy-free intervals, potentially even to the prognosis. In the palliative setting, irradiation can be used for local pain management. Discussion: The role of radiotherapy as part of multimodal treatment concepts for pancreatic cancer is currently under discussion; however, there are a number of retrospective and prospective studies clearly suggesting the benefits of radiotherapy in addition to surgery and chemotherapy. Prospective studies are necessary for further verification using modern techniques for radiotherapy, such as stereotactic and intensity-modulated radiotherapy. The use of older studies, with inadequate irradiation techniques and obsolete doses from today’s point of view, for evaluating the effects of radiotherapy is not acceptable.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Adjuvant; Chemoradiotherapy; Inoperability; Neoadjuvant; Relapse therapy

Romancing the Boost - the Higher, the Better? - Sedlmayer, Felix; Sautter-Bihl, Marie-Luise; Sauer, Rolf (Breast Care, 2015)
EVALuna2:18278

Safety and efficacy of single cycle induction treatment with cisplatin/docetaxel/ durvalumab/tremelimumab in locally advanced HNSCC: first results of CheckRad-CD8 - Hecht, Markus; Gostian, Antoniu Oreste; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Hautmann, Matthias Günther; Klautke, Gunther; Laban, Simon; Brunner, Thomas; Hinke, Axel; Becker, Ina; et al. (Journal for ImmunoTherapy of Cancer, 2020)
BACKGROUND: To determine safety and efficacy of single cycle induction treatment with cisplatin/docetaxel and durvalumab/tremelimumab in stage III-IVB head and neck cancer. METHODS: Patients received a single cycle of cisplatin 30 mg/m² on days 1-3 and docetaxel 75 mg/m² on day 1 combined with durvalumab 1500 mg fix dose on day 5 and tremelimumab 75 mg fix dose on day 5. Patients with pathologic complete response (pCR) in the rebiopsy after induction treatment or at least 20% increase of intratumoral CD8+ cell density in the rebiopsy compared with baseline entered radioimmunotherapy with concomitant durvalumab/tremelimumab. The objective of this interim analysis was to analyze safety and efficacy of the chemoimmunotherapy-induction treatment before radioimmunotherapy. RESULTS: A total of 57 patients were enrolled, 56 were treated. Median pretreatment intratumoral CD8+ cell density was 342 cells/mm². After induction treatment, 27 patients (48%) had a pCR in the rebiopsy and further 25 patients (45%) had a relevant increase of intratumoral CD8+ cells (median increase by a factor of 3.0). Adverse event (AE) grade 3-4 appeared in 38 patients (68%) and mainly consisted of leukopenia (43%) and infections (29%). Six patients (11%) developed grade 3-4 immune-related AE. Univariate analysis computed p16 positivity, programmed death ligand 1 immune cell area and intratumoral CD8+ cell density as predictors of pCR. On multivariable analysis, intratumoral CD8+ cell density predicted pCR independently (OR 1.0012 per cell/mm², 95% CI 1.0001 to 1.0022, p=0.016). In peripheral blood CD8+ cells, the coexpression of programmed death protein 1 significantly increased especially in patients with pCR. CONCLUSIONS: Single cycle induction treatment with cisplatin/docetaxel and durvalumab/tremelimumab is feasible and achieves a high biopsy-proven pCR rate.
CRIS-Team Scopus Importer:2020-10-23
Keywords: CD8-Positive T-lymphocytes; clinical trials; combined modality therapy; head and neck neoplasms; Phase II as topic; radioimmunotherapy

Salivary gland carcinoma (SGC) with perineural spread and/or positive resection margin - High locoregional control rates after photon (chemo) radiotherapy - Experience from a monocentric analysis - Haderlein, Marlen; Scherl, Claudia; Semrau, Sabine; Lettmaier, Sebastian; Hecht, Markus; Putz, Florian; Iro, Heinrich; Agaimy, Abbas; Fietkau, Rainer (Radiation Oncology, 2019)
Background: The aim was to evaluate the outcome, especially locoregional control of patients with locally advanced salivary gland carcinoma (SGC) with perineural spread (Pn1) and/or positive resection margins (R1/2) after postoperative photon (chemo) radiotherapy in a single centre. Methods: We retrospectively reviewed data of 65 patients with newly diagnosed locally advanced SGC without distant metastases who underwent radio (chemo) therapy in the department of radiation oncology of the university hospital of Erlangen from January 2000 until April 2017. Kaplan Meier method was used to calculate survival and recurrence rates. In univariate analysis the log-rank test was used to correlate patient-/tumor- and treatment-related parameters to survival and recurrence rates. Results: Median follow-up was 45 months (range: 6; 215). After 1, 3, 5 years cumulative incidence of local and locoregional failure was 3.1, 7.0, 7.0% and 3.1, 9.7, 12.9%, whereas cumulative incidence of distant metastases (DM) was 15.6, 36.0, 44.0%. After 1,3, 5 years cumulative Overall (OS) and Disease-free survival (DFS) was 90.5, 74.9, 63.9% and 83.0, 54.8, 49.4%. The only significant predictor for decreased local and locoregional control was a macroscopic resection margin(R2) (p = 0.002 and p = 0.04). High-grade histology (p = 0.006), lymph node metastases with extracapsular spread (p = 0.044) and an advanced T-stage (p = 0.031) were associated with an increased rate of DM. High-grade histology was the only factor predicting for a decreased DFS (p = 0.014). Conclusion: Photon radiotherapy leads to high local and locoregional control rates in a high-risk patient population with SGC with microscopically positive resection margins and/or perineural spread. The most common site of disease recurrence was distant metastases. Therefore the real challenge for the future should be to prevent distant metastases.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Locoregional control; Perineural spread; Photon radiotherapy; Positive resection margin; Salivary gland cancer

Salvage external beam radiation therapy of biochemical relapse after radical prostatectomy: Results and potential role of PET/CT - Rutzner, Sandra; Lubgan, Dorota; Wullich, Bernd; Kuehn, R.; Kuwert, Torsten; Fietkau, Rainer (2018)
EVALuna2:35905

Salvage HDR/PDR brachytherapy combined with interstitial hyperthermia in locally recurrent prostate adenocarcinoma after previous irradiation - actual status of multicenter phase II study - Kukielka, A.; Strnad, Vratislav; Dabkowski, M. (2018)
EVALuna2:36541

Salvage-radiation therapy and regional hyperthermia for biochemically recurrent prostate cancer after radical prostatectomy (Results of the planned interim analysis) - Beck, Marcus; Ghadjar, Pirus; Mehrhof, Felix; Zips, Daniel; Paulsen, Frank; Wegener, Daniel; Burock, Susen; Kaul, David; Stromberger, Carmen; Nadobny, Jacek; Ott, Oliver; Fietkau, Rainer; et al. (Cancers, 2021)
Efforts to improve the outcome of prostate cancer (PC) patients after radical prostatectomy (RP) include adjuvant or salvage radiation therapy (SRT), but still up to 50% of patients develop a disease progression after radiotherapy (RT). Regional hyperthermia (HT) is well-known to improve tumor sensitivity to RT in several entities. Here we report on a planned interim analysis of tolera-bility and feasibility after recruitment of the first 50 patients of a trial combining SRT and HT. We conducted a prospective multicenter non-randomized Phase-II-Trial (HTProstate-NCT04159051) in-vestigating the implementation of combined moderate-dose escalated SRT (70 Gy in 35 fractions) and locoregional deep HT (7–10 HT sessions). The primary endpoints were the rate of acute genito-urinary (GU), gastrointestinal (GI), and HT-related toxicities, completed HT sessions (≥7), and SRT applications per protocol (≥95% of patients). The two-step design included a planned interim analysis for acute GU-, GI-and HT-specific toxicities to ensure patients’ safety. Between November 2016 and December 2019, 52 patients entered into the trial. After 50 patients completed therapy and three months of follow-up, we performed the planned interim analysis. 10% of patients developed acute grade 2 GU and 4% grade 2 GI toxicities. No grade ≥3 GU or GI toxicities occurred. HT-specific symptoms grade 2 and 3 were observed in 4% and 2% of all patients. Thus, the pre-specified criteria for safety and continuation of recruitment were met. Moreover, ≥7 HT treatments were applicable, indicating the combination of SRT + HT to be feasible. Evaluation of early QoL showed no significant changes. With its observed low rate of GU and GI toxicities, moderate and manageable rates of HT-specific symptoms, and good feasibility, the combined SRT + HT seems to be a promising treatment approach for biochemical recurrence after RP in PC patients.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Dose-escalation; Hyperthermia; Postoperative; Prostate cancer; Radiosensitiza-tion; Salvage radiation therapy

SAR Measurements of Coaxial Antennas in a Muscle Equivalent Water Phantom - Erb, J.; Engelbrecht, Rainer; Schaller, Gerhard; Seegenschmiedt, Heinrich; Fietkau, Rainer; Sauer, R.; Ross, D. (Hyperthermia in Clinical Oncology - In Memory of Dr. Mildred Scheel, 1993)
UnivIS-Import:2015-04-16:Pub.1993.tech.IE.LEH.sarmea_0

SAR Measurements of Coaxial Antennas Used for Interstitial/Endocavitary HT. - Erb, J.; Engelbrecht, Rainer; Schaller, Gerhard; Ross, D.; Seegenschmiedt, Heinrich; Fietkau, Rainer; Sauer, R. (13^th Meeting of the Europ. Soc. Hyperthermia Oncology ESHO, 1993)
UnivIS-Import:2015-04-16:Pub.1993.tech.IE.LEH.sarmea

Scanned ion beam therapy for prostate carcinoma: Comparison of single plan treatment and daily plan-adapted treatment - Hild, Sebastian; Graeff, Christian; Rucinski, Antoni; Zink, Klemens; Habl, Gregor; Durante, Marco; Herfarth, Klaus; Bert, Christoph (Strahlentherapie und Onkologie, 2016)
Intensity-modulated particle therapy (IMPT) for tumors showing interfraction motion is a topic of current research. The purpose of this work is to compare three treatment strategies for IMPT to determine potential advantages and disadvantages of ion prostate cancer therapy.Simulations for three treatment strategies, conventional one-plan radiotherapy (ConvRT), image-guided radiotherapy (IGRT), and online adaptive radiotherapy (ART) were performed employing a dataset of 10 prostate cancer patients with six CT scans taken at one week intervals. The simulation results, using a geometric margin concept (7-2 mm) as well as patient-specific internal target volume definitions for IMPT were analyzed by target coverage and exposure of critical structures on single fraction dose distributions.All strategies led to clinically acceptable target coverage in patients exhibiting small prostate motion (mean displacement <4 mm), but IGRT and especially ART led to significant sparing of the rectum. In 20% of the patients, prostate motion exceeded 4 mm causing insufficient target coverage for ConvRT (V95mean = 0.86, range 0.63-0.99) and IGRT (V95mean = 0.91, range 0.68-1.00), while ART maintained acceptable target coverage.IMPT of prostate cancer demands consideration of rectal sparing and adaptive treatment replanning for patients exhibiting large prostate motion.
EVALuna2:18350

Scleroderma and Radiation Sensitivity - Schenker, Hannah; Schuster, Barbara; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

“sCT-Feasibility” - a feasibility study for deep learning-based MRI-only brain radiotherapy - Grigo, Johanna; Szkitsak, Juliane; Höfler, Daniel; Fietkau, Rainer; Putz, Florian; Bert, Christoph (Radiation Oncology, 2024)
Background: Radiotherapy (RT) is an important treatment modality for patients with brain malignancies. Traditionally, computed tomography (CT) images are used for RT treatment planning whereas magnetic resonance imaging (MRI) images are used for tumor delineation. Therefore, MRI and CT need to be registered, which is an error prone process. The purpose of this clinical study is to investigate the clinical feasibility of a deep learning-based MRI-only workflow for brain radiotherapy, that eliminates the registration uncertainty through calculation of a synthetic CT (sCT) from MRI data. Methods: A total of 54 patients with an indication for radiation treatment of the brain and stereotactic mask immobilization will be recruited. All study patients will receive standard therapy and imaging including both CT and MRI. All patients will receive dedicated RT-MRI scans in treatment position. An sCT will be reconstructed from an acquired MRI DIXON-sequence using a commercially available deep learning solution on which subsequent radiotherapy planning will be performed. Through multiple quality assurance (QA) measures and reviews during the course of the study, the feasibility of an MRI-only workflow and comparative parameters between sCT and standard CT workflow will be investigated holistically. These QA measures include feasibility and quality of image guidance (IGRT) at the linear accelerator using sCT derived digitally reconstructed radiographs in addition to potential dosimetric deviations between the CT and sCT plan. The aim of this clinical study is to establish a brain MRI-only workflow as well as to identify risks and QA mechanisms to ensure a safe integration of deep learning-based sCT into radiotherapy planning and delivery. Discussion: Compared to CT, MRI offers a superior soft tissue contrast without additional radiation dose to the patients. However, up to now, even though the dosimetrical equivalence of CT and sCT has been shown in several retrospective studies, MRI-only workflows have still not been widely adopted. The present study aims to determine feasibility and safety of deep learning-based MRI-only radiotherapy in a holistic manner incorporating the whole radiotherapy workflow. Trial registration: NCT06106997.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Artificial intelligence; Deep learning; MRI; MRI-only workflow; MRonly; Radiotherapy; sCT; Stereotactic radiotherapy; Synthetic CT

Secondary Tracheoesophageal Puncture After Laryngectomy Increases Complications With Shunt and Voice Prosthesis - Scherl, Claudia; Kauffels, Julia; Schützenberger, Anne; Döllinger, Michael; Bohr, Christopher; Dürr, Stephan; Fietkau, Rainer; Haderlein, Marlen; Koch, Michael; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Müller, Sarina Katrin; et al. (Laryngoscope, 2020)
Objectives/Hypothesis To evaluate the demographics, clinical features, management, and prognostic indicators of tracheoesophageal puncture complications in patients undergoing placement of voice prosthesis following cancer treatment.
CRIS-Team WoS Importer:2020-02-21

Seed-displacements in the immediate post-implant phase in permanent prostate brachytherapy - Karius, Andre; Schweizer, Claudia; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Lamrani, Allison; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2023)
Purpose: To investigate differences in seed-displacements between the immediate post-implant phase (day 0–1) and the time to post-plan computed tomography (CT) (day 1–30) in seed prostate brachytherapy. Materials and methods: Seed positions were identified on the intra-operatively created ultrasound-based treatment plan (day 0) and CT scans of day 1 and 30 for 33 patients. The day 1 (30) seed arrangement was registered onto the day 0 (1) arrangement using a seed-only approach. Based on a 1:1 assignment of seeds via the Kuhn-Munkres algorithm, seed-displacements were analyzed. Displacements were evaluated depending on strand-length and anatomical implant location. Resulting dosimetric effects were calculated. Results: Seed-displacements in the immediate post-implant phase (median displacements: 3.8 ± 3.6 mm) were stronger than in the time to post-plan CT (2.1 ± 2.6 mm) and enhanced along the superior-inferior direction. From day 0 to 1, strands containing one (7.3 ± 5.4 mm) or two (8.1 ± 5.8 mm) seeds showed larger displacements than strands of higher lengths (up to 4.2 ± 7.0 mm), whereas no length-dependency was found to day 30. Seeds implanted in base and apex tended to move towards the prostate midzone during both time periods. D90 (dose that 90% of prostate receives) was with variations of 2 ± 15 Gy more stable from day 1 to 30 than in the immediate post-implant phase (−18 ± 11 Gy). Conclusion: Seed-displacements in the immediate post-implant phase was enhanced compared to day 1–30. This may result from uncertainties in the gold-standard ultrasound-based treatment planning and implantation. Adaptive implantation workflows appear useful for ensuring high implant stability from the beginning.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Adaptive implantation; Permanent implant; Prostate brachytherapy; Prostate cancer; Seed brachytherapy; Seed displacements

Selection of appropriate end-points (pCR vs 2yDFS) for tailoring treatments with prediction models in locally advanced rectal cancer - Valentini, Vincenzo; Van Stiphout, Ruud G. P. M.; Lammering, Guido; Gambacorta, Maria A.; Barba, Maria C.; Bebenek, Marek; Bonnetain, Franck; Bosset, Jean F.; Bujko, Krzysztof; Cionini, Luca; Gerard, Jean P.; Rödel, Claus; et al. (Radiotherapy and Oncology, 2015)
Personalized treatments based on predictions for patient outcome require early characterization of a rectal cancer patient's sensitivity to treatment. This study has two aims: (1) identify the main patterns of recurrence and response to the treatments (2) evaluate pathologic complete response (pCR) and two-year disease-free survival (2yDFS) for overall survival (OS) and their potential to be relevant intermediate endpoints to predict.Pooled and treatment subgroup analyses were performed on five large European rectal cancer trials (2795 patients), who all received long-course radiotherapy with or without concomitant and/or adjuvant chemotherapy. The ratio of distant metastasis (DM) and local recurrence (LR) rates was used to identify patient characteristics that increase the risk of recurrences.The DM/LR ratio decreased to a plateau in the first 2 years, revealing it to be a critical follow-up period. According to the patterns of recurrences, three patient groups were identified: 5-15% had pCR and were disease free after 2 years (excellent prognosis), 65-75% had no pCR but were disease free (good prognosis) and 15-30% had neither pCR nor 2yDFS (poor prognosis).Compared with pCR, 2yDFS is a stronger predictor of OS. To adapt treatment most efficiently, accurate prediction models should be developed for pCR to select patients for organ preservation and for 2yDFS to select patients for more intensified treatment strategies.
EVALuna2:18273

Senescence Induction by Combined Ionizing Radiation and DNA Damage Response Inhibitors in Head and Neck Squamous Cell Carcinoma Cells - Dobler, Clara; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (Cells, 2020)
DNA damage response inhibitors (DDRi) may selectively enhance the inactivation of tumor cells in combination with ionizing radiation (IR). The induction of senescence may be the key mechanism of tumor cell inactivation in this combinatorial treatment. In the current study the effect of combined IR with DDRi on the induction of senescence was studied in head and neck squamous cell carcinoma (HNSCC) cells with different human papilloma virus (HPV) status. The integrity of homologous recombination (HR) was assessed in two HPV positive, two HPV negative HNSCC, and two healthy fibroblast cell cultures. Cells were treated with the DDRi CC-115 (DNA-dependent protein kinase, DNA-pK; dual mammalian target of rapamycin, mTor), VE-822 (ATR; ataxia telangiectasia and Rad3-related kinase), and AZD0156 (ATM; ataxia telangiectasia mutated kinase) combined with IR. Effects on senescence, apoptosis, necrosis, and cell cycle were analyzed by flow cytometry. The fibroblast cell lines generally tolerated IR or combined treatment better than the tumor cell lines. The ATM and ATR inhibitors were effectively inducing senescence when combined with IR. The DNA-PK inhibitor was not an important inductor of senescence. HPV status and HR activity had a limited influence on the efficacy of DDRi. Induction of senescence and necrosis varied individually among the cell lines due to molecular heterogeneity and the involvement of DNA damage response pathways in senescence induction.
CRIS-Team Scopus Importer:2020-10-30
Keywords: ATM; ATR; DNA damage response inhibitor; DNAPK; HNSCC; homologous recombination; ionizing radiation; kinase inhibitor; radiosensitivity; senescence

Serial Radon Baths induce Immune and pain modulating Effects - Results of the Placebo-controlled RAD-ON02 Study - Donaubauer, Anna-Jasmina; Becker, Ina; Weikl, Lena; Klein, G.; Fournier, C.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Shifts in Macrophage as a prognostic Biomarker in Patients with luminal Breast Cancer - A Confirmatory Study - Schnellhardt, Sören; Segelhorst, Sarah; Erber, Ramona; Daniel, Christoph; Hartmann, Arndt; Fasching, Peter; Beckmann, Matthias; Fietkau, Rainer; Distel, Luitpold; Rübner, Matthias (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Should salvage surgery be considered for local recurrence after definitive chemoradiation in locally advanced non-small cell lung cancer? - Schreiner, Waldemar; Dudek, Wojciech; Lettmaier, Sebastian; Fietkau, Rainer; Sirbu, Horia (Journal of Cardiothoracic Surgery, 2016)
Incidence of local relapse after definitive chemoradiation (>59 Gy) for locally advanced non-small-cell lung cancer (NSCLC) is high, irrespective of high dose radiation applied. Experience with salvage lung resections in patients with locally relapsed NSCLC after definitive chemoradiation is limited. We present our series of salvage lung resections for local NSCLC relapse after curative-intent chemoradiation for locally advanced tumor.Nine consecutive patients with local tumor recurrence or persistence following definitive chemoradiation were reviewed. Kaplan-Meier analysis was used to assess patient survival.All patients received definitive radiation (median dose 66.2 Gy) with concurrent chemotherapy. Tumor stage prior to chemoradiation was IIIA in 8 patients and IV in 1. In 4 patients tumor invaded the chest wall, in 2 the spine and in 1 the aorta. Median interval between chemoradiation and salvage resection was 30.2 weeks. Nine patients underwent 9 resections (6 lobectomies, 1 bilobectomy, 1 pneumonectomy and 1 bi-segmentectomy). One death occurred on the 12th postoperative day. Median overall survival was 23 months; postoperative 3-year survival was 47 %. Median progression-free survival was 21 months.Salvage lung resection for locally recurrent or persisted NSCLC in selected patients with locally advanced NSCLC following definitive chemoradiation is a worthwhile treatment option.
EVALuna2:18249

Simultaneous amniotic membrane patch in high-risk keratoplasty - Seitz, Berthold; Das, Sujata; Sauer, Rolf; Hofmann-Rummelt, Carmen; Beckmann, Matthias; Kruse, Friedrich (Cornea, 2011)
To analyze the short- and intermediate-term results of simultaneous transplantation of amniotic membrane with high-risk keratoplasty.Between January 2002 and February 2004, a simultaneous amniotic membrane patch was transplanted with penetrating keratoplasty in 16 eyes of 16 patients. In 13 eyes, a soft contact lens was applied afterward. Corneal perforation was present in 10 of 14 eyes with emergency keratoplasty. Five patients received systemic immunosuppressive medication for 4-6 months after penetrating keratoplasty.The amniotic membrane patch fell off after 8 ± 3 (range: 4-14) days without residual tissue except in 1 case. In 15 of 16 eyes, the epithelium was completely closed after 10 ± 8 (range: 4-30) days. In 3 eyes, recurrence of the epithelial defect occurred after 3-6 months. During a follow-up period of 18 ± 6 months, 13 of 16 corneal grafts were clear.Simultaneous amniotic membrane transplantation and penetrating keratoplasty may improve the prognosis of corneal graft in eyes with risk of epithelial healing problems.
EVALuna2:17178

Single-cycle induction chemotherapy before chemoradiotherapy or surgery in functionally inoperable head and neck squamous cell carcinoma: 10-year results - Breheret, Marius; Lubgan, Dorota; Haderlein, Marlen; Hecht, Markus; Traxdorf, Maximilian; Schmidt, Daniela; Müller, Sarina Katrin; Kitzsteiner, Christian; Kuwert, Torsten; Iro, Heinrich; Fietkau, Rainer; Semrau, Sabine (European Archives of Oto-Rhino-Laryngology, 2019)
Introduction The response to induction chemotherapy (IC) predicts local control after conservative treatment of laryngeal, meso- and hypopharyngeal head and neck squamous cell carcinoma (HNSCC) and can thus help to avoid surgery. Single-cycle induction chemotherapy may help to maintain a low local recurrence rate while keeping the overall toxicity manageable. However, long-term data on single-cycle IC response by tumor location is lacking. Methods N = 102 patients with functionally inoperable primary HNSCC of the larynx (n = 43), hypopharynx (n = 42) or mesopharynx/tongue (n = 17) received one cycle of docetaxel (75 mg/m(2), d1) plus cisplatin (30 mg/m(2), d1-3) or carboplatin (AUC 1.5, d1-3) and a response evaluation 3 weeks later. Responders (>= 30% tumor size reduction and >= 20% SUVmax decrease in F-18-FDG PET/CT) were recommended chemoradiotherapy (CRT), and non-responders surgery. Results The overall response rate was 72.5%. All 74 responders and 10 non-responders received primary CRT, and 18 patients received primary surgery after single-cycle IC. Overall 10-year local recurrence-free survival (LRFS) was 73.7%. Three-year LRFS was 88.2% (mesopharynx/tongue), 88.2% (larynx), and 73.3% (hypopharynx); p = 0.17. 3-year distant metastasis-free survival (DMFS) was 94.1% (mesopharynx/tongue), 88.0% (larynx) and 76.4% (hypopharynx); p > 0.05. This influenced the 3-year cancer-specific survival (CSS) for larynx (91.2%) vs. hypopharynx tumors (60.8%); p = 0.003, but CSS was not different to tumors in the mesopharynx/tongue (81.4%); p > 0.05. Conclusions A single-cycle induction chemotherapy for HNSCC enables surgery plus adjuvant therapy as well as chemoradiotherapy. The long-term local and distant disease control was good but varied between tumors in the larynx and mesopharynx/tongue vs. hypopharynx.
CRIS-Team WoS Importer:2019-10-18

Single-cycle induction chemotherapy followed by chemoradiotherapy or surgery in patients with head and neck cancer: What are the best predictors of remission and prognosis? - Semrau, Sabine; Haderlein, Marlen; Schmidt, Daniela; Lell, Michael; Wolf, Walburga; Waldfahrer, Frank; Uder, Michael; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer (Cancer, 2015)
There is controversy over the concept of function and organ preservation by chemotherapy/chemoradiation instead of surgery in locally advanced cancer of the larynx or pharynx. Tumor response to induction chemotherapy (ICT) can help in choosing between conservative and surgical treatment. This study compared 3 methods of assessing response to ICT: endoscopy, computed tomography, and (18) F-FDG-PET/CT.Primary response to 1 cycle of ICT with docetaxel plus platinum was assessed by the aforementioned methods in 62 laryngopharyngeal cancer patients. Endoscopic response was the deciding factor for selecting further treatment: surgery for endoscopic nonresponders (<30% tumor response) versus chemoradiotherapy for endoscopic responders.ICT achieved endoscopic response in 48 of 62 patients (77%). Individual relative residual tumor activity of standardized uptake value (resSUVmax ) in (18) F-FDG-PET/CT was a median 0.38 of baseline (0.09-1.71), whereas residual tumor extent in CT (resCT) was 0.75 of baseline (0.32-1.20). Endoscopic responders and nonresponders differed significantly in SUVmax after ICT (postSUVmax , 6.0 vs 14.5; P < .001), resSUVmax (0.34 vs 0.81, P < .001), and resCT (0.71 vs 0.87, P = .004), but not in maximum tumor diameter after ICT (14 vs 20 mm, P = .11). resSUVmax <0.8 and absolute postSUVmax <10 provided the best discriminatory power for long-term success criteria (tumor-free survival, overall survival).Metabolic tumor response showed very good correlation with clinical tumor response to ICT. The value of metabolic response detected by (18) F-FDG-PET/CT should be explored in a prospective clinical trial. Cancer 2015;121:1214-1222. © 2014 American Cancer Society.
EVALuna2:13821

Single cycle induction treatment with cisplatin/docetaxel plus durvalumab/tremelimumab in stage III-IVB head and neck squamous cell cancer (CheckRad-CD8 trial) - Hecht, Markus; Gostian, A-O.; Eckstein, Markus; Rutzner, Sandra; Von Der Gruen, J.; Illmer, T.; Hautmann, M. G.; Brunner, T.; Laban, S.; Klautke, G.; Tamaskovics, B.; Frey, Benjamin; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

SMARCB1(INI1)-deficient sinonasal basaloid carcinoma: a novel member of the expanding family of SMARCB1-deficient neoplasms - Agaimy, Abbas; Koch, Michael; Lell, Michael; Semrau, Sabine; Dudek, Wojciech; Wachter, David; Knöll, Antje; Iro, Heinrich; Haller, Florian; Hartmann, Arndt (American Journal of Surgical Pathology, 2014)
Poorly differentiated sinonasal carcinomas are a heterogenous group of aggressive neoplasms that encompasses squamous cell carcinoma including basaloid variant, lymphoepithelial carcinoma, sinonasal undifferentiated carcinoma, and neuroendocrine-type small cell carcinoma. We herein describe 3 cases of a hitherto unreported variant combining features of basaloid carcinoma with variable intermingled rhabdoid cells. Patients were 2 women (aged 28 and 35) and a man (52 y) who presented with sinonasal masses. All had advanced local disease with bone involvement (pT4). None had a history of irradiation or a family history of rhabdoid tumors. Treatment was surgery and adjuvant chemoradiation. One patient developed liver, lung, pleural, and pericardial metastases (63 mo) and is currently (70 mo) alive under palliative treatment. Another developed recurrent cervical lymph node metastases and died of disease 8.5 years later. The youngest patient was disease-free at last follow-up 7 years later. Histologic features were very similar in all 3 cases and showed intimate admixture of compact basaloid cell nests with peripheral palisading, perivascular pseudorosettes, and a few scattered rhabdoid cells. Rhabdoid cells were more extensive in the metastasis in 1 case but formed a minor inconspicuous component in the primary tumors in all cases. Striking features common to all cases were (1) basaloid "blue" appearance at low power, (2) papilloma-like exophytic component, (3) extensive pagetoid surface growth with prominent denuding features, and (4) replacement of underlying mucous glands mimicking an inverted papilloma. Clear-cut origin from benign papilloma and overt squamous differentiation were lacking. Diffuse (2) or partial (1) p16 expression was noted, but all cases lacked human papillomavirus DNA by molecular tests. In situ hybridization was negative for Epstein-Barr virus. Immunohistochemistry showed diffuse expression of pancytokeratin. CK5 and vimentin showed intermingling of CK5/vimentin basaloid and CK5/vimentin rhabdoid cells. Complete loss of nuclear SMARCB1 expression was seen in all cases including also the denuding carcinoma in situ-like surface lesions. To our knowledge, this variant of sinonasal carcinoma has not been reported before. The identical features in all 3 cases suggest a specific disease rather than a nonspecific dedifferentiated phenotype. Awareness of this rare variant and thus reporting of additional cases is necessary for defining its full morphologic and biological spectrum.
EVALuna2:6600

SMARCB1 (INI-1)-deficient Sinonasal Carcinoma: A Series of 39 Cases Expanding the Morphologic and Clinicopathologic Spectrum of a Recently Described Entity - Agaimy, Abbas; Hartmann, Arndt; Antonescu, Cristina R.; Chiosea, Simion I.; El-Mofty, Samir K.; Geddert, Helene; Iro, Heinrich; Lewis, James S.; Markl, Bruno; Mills, Stacey E.; Riener, Marc-Oliver; Robertson, Thomas; et al. (American Journal of Surgical Pathology, 2017)
To more fully characterize the clinical and pathologic spectrum of a recently described tumor entity of the sinonasal tract characterized by loss of nuclear expression of SMARCB1 (INI1), we analyzed 39 SMARCB1-deficient sinonasal carcinomas collected from multiple medical centers. The tumors affected 23 males and 16 females with an age range of 19 to 89 years (median, 52). All patients presented with locally advanced disease (T3, n=5; T4, n=27) involving the sinuses (mainly ethmoid) with variable involvement of the nasal cavity. Thirty patients received surgery and/or radiochemotherapy with curative intent. At last follow-up, 56% of patients died of disease 0 to 102 months after diagnosis (median, 15), 2 were alive with disease, and 1 died of an unrelated cause. Only 9 patients (30%) were alive without disease at last follow-up (range, 11 to 115 mo; median, 26). The original diagnosis of retrospectively identified cases was most often sinonasal undifferentiated carcinoma (n=14) and nonkeratinizing/basaloid squamous cell carcinoma (n=5). Histologically, most tumors displayed either a predominantly basaloid (61%) or plasmacytoid/rhabdoid morphology (36%). The plasmacytoid/rhabdoid form consisted of sheets of tumor cells with abundant, eccentrically placed eosinophilic cytoplasm, whereas similar cells were typically rare and singly distributed in the basaloid variant. Glandular differentiation was seen in a few tumors. None of the cases showed squamous differentiation or surface dysplasia. By immunohistochemistry, the tumors were positive for pancytokeratin (97%), CK5 (64%), p63 (55%), and CK7 (48%); and they were negative for NUT (0%). Epstein-Barr virus and high-risk human papillomavirus was not detected by in situ hybridization. Immunohistochemical loss of SMARCB1 (INI1) expression was confirmed for all 39 tumors. Investigation of other proteins in the SWI/SNF complex revealed co-loss of SMARCA2 in 4 cases, but none were SMARCA4 deficient or ARID1A deficient. Of 27 tumors with SMARCB1 fluorescence in situ hybridization analysis, 14 showed homozygous (biallelic) deletions and 7 showed heterozygous (monoallelic) deletions. SMARCB1-deficient sinonasal carcinoma represents an emerging poorly differentiated/undifferentiated sinonasal carcinoma that (1) cannot be better classified as another specific tumor type, (2) has consistent histopathologic findings (albeit with some variability) with varying proportions of plasmacytoid/rhabdoid cells, and (3) demonstrates an aggressive clinical course. This entity should be considered in any difficult-to-classify sinonasal carcinoma, as correct diagnosis will be mandatory for optimizing therapy and for further delineation of this likely underdiagnosed disease.
EVALuna2:6856

Spatial distribution of FoxP3+ and CD8+ tumour infiltrating T cells reflects their functional activity - Posselt, Rebecca; Erlenbach-Wuensch, Katharina; Haas, Matthias; Jeßberger, Jonas; Buettner-Herold, Maike; Haderlein, Marlen; Hecht, Markus; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Oncotarget, 2016)
Regulatory and cytotoxic T cells are key players in the host's anticancer immune response. We studied the spatial distribution of FoxP+ and CD8+ cells to identify potential interactions.In 202 patients 103 pre-radiochemotherapy biopsies and 153 post-radiochemotherapy tumour specimens of advanced rectal cancer were available and an immunohistochemical double staining of FoxP3+ and CD8+ tumour-infiltrating lymphocytes was performed to investigate cell density and cell-to-cell distances.FoxP3+ cells decreased after radiochemotherapy by a factor of 3 while CD8+ cells remained nearly unchanged. High epithelial (p=0.033) and stromal (p=0.009) FoxP3+ cell density was associated with an improved overall survival. Cell-to-cell distances of randomly distributed cells were simulated and compared to observed cell-to-cell distances. Observed distances shorter than the simulated, random distances were hypothesized to represent FoxP3+ cells actively interacting with CD8+ cells. Epithelial short distances were associated with a favourable prognosis while the opposite was true for the stromal compartment.The analysis of cell-to-cell distances may offer a tool to predict outcome, maybe by identifying functionally active, interacting infiltrating inflammatory cells in different tumour compartments.
EVALuna2:6815

Spatial Distribution of Inflammatory Cells and their Interactions in Pancreatic Carcinoma Tissues of 63 Patients - Distel, Luitpold; Zoske, Hanno; Fietkau, Rainer; Hecht, Markus (2017)
EVALuna2:32879

Specific Effect of BRAF-Inhibitors on a BRAF-mutant and a Wild-type Cell Line of Malignant Melanoma - Steck, M.; Grabenbauer, Maximilian; Fünfle, Ruben; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2017)
EVALuna2:32896

Stage-Dependent Frequency of Lymph Node Metastases in Patients With Rectal Carcinoma After Preoperative Chemoradiation: Results from the CAO/ARO/AIO-94 Trial and From a Comparative Prospective Evaluation With Extensive Pathological Workup - Sprenger, Thilo; Rothe, Hilka; Conradi, Lena-Christin; Beissbarth, Tim; Kauffels, Anne; Kitz, Julia; Homayounfar, Kia; Wolff, Hendrik; Stroebel, Philipp; Ghadimi, Michael; Wittekind, Christian; Sauer, Rolf; et al. (Diseases of the colon & rectum, 2016)
For patients with ycT1/2 rectal carcinomas after neoadjuvant chemoradiotherapy, local excision instead of radical surgery has increasingly been discussed as a way to avoid postoperative morbidity associated with radical surgery.The purpose of this study was to determine the incidence of lymph node metastases in total mesorectal excision specimens with ypT0, ypT1/2, and ypT3/4 rectal cancers.This is a prospective and retrospective cohort study.This study was conducted in tertiary referral hospitals that are part of the German Rectal Cancer Study Group.A total of 479 patients with stage II and III rectal cancers treated within phase III trials of the German Rectal Cancer Study Group were evaluated. Specimens from 81 patients treated in the Working Group of Surgical Oncology/Working Group of Radiation Oncology/Working Group of Medical Oncology of the Germany Cancer Society (CAO/ARO/AIO-04) trial were prospectively studied with extensive microscopic screening of the entire mesorectum. The frequency and localization of nodal metastases were specified and compared with those of 398 patients having received neoadjuvant chemoradiation within the CAO/ARO/AIO-94 trial.Frequency and localization of mesorectal lymph node metastases in patients with ypT0, ypT1/2, or ypT3/4 cancer were measured.A mean number of 28.0 ± 13.7 nodes were detected per specimen within the prospective group. A total of 25% of patients in the ypT1/2 group had nodal metastases compared with 40% in the ypT3/4 group. Patients with node-positive ypT1/2 had a mean number of 2.2 metastases, and 55% of these metastases were located far from the primary lesion in the proximal mesorectum. Within the CAO/ARO/AIO-94 cohort (n = 398), 19% of patients with ypT1/2 (ypT1 = 22%; ypT2 = 18%) had ypN+ status compared with 43% with ypT3/4 cancers (ypT3 = 40%; ypT4 = 73%).Low numbers of patients with ypT0 limited the evaluation of nodal metastases in pathologic complete responders.Even in good responders (ypT1/2), >20% of rectal carcinomas still harbored residual lymph node metastases. Local excision for patients with ycT1/2 rectal cancers would, thus, miss metastases in a considerable percentage and might involve the risk of significant undertreatment in a number of patients.
EVALuna2:18337

Status epilepticus in patients with glioblastoma: Clinical characteristics, risk factors, and epileptological outcome - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Balk, Stefanie; Reindl, Caroline; Madzar, Dominik; Uhl, Martin; Welte, Tamara; Brandner, Sebastian; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; et al. (Seizure-European Journal of Epilepsy, 2023)
Purpose: Epilepsy is a common comorbidity in patients with glioblastoma, however, clinical data on status epilepticus (SE) in these patients is sparse. We aimed to investigate the risk factors associated with the occurrence and adverse outcomes of SE in glioblastoma patients. Methods: We retrospectively analysed electronic medical records of patients with de-novo glioblastoma treated at our institution between 01/2006 and 01/2020 and collected data on patient, tumour, and SE characteristics. Results: In the final cohort, 292/520 (56.2 %) patients developed seizures, with 48 (9.4 % of the entire cohort and 16.4 % of patients with epilepsy, PWE) experiencing SE at some point during the course of their disease. SE was the first symptom of the tumour in 6 cases (1.2 %) and the first manifestation of epilepsy in 18 PWE (6.2 %). Most SE episodes occurred postoperatively (n = 37, 77.1 %). SE occurrence in PWE was associated with postoperative seizures and drug-resistant epilepsy. Adverse outcome (in-house mortality or admission to palliative care, 10/48 patients, 20.8 %), was independently associated with higher status epilepticus severity score (STESS) and Charlson Comorbidity Index (CCI), but not tumour progression. 32/48 SE patients (66.7 %) were successfully treated with first- and second-line agents, while escalation to third-line agents was successful in 6 (12.5 %) cases. Conclusion: Our data suggests a link between the occurrence of SE, postoperative seizures, and drug-resistant epilepsy. Despite the dismal oncological prognosis, SE was successfully treated in 79.2 % of the cases. Higher STESS and CCI were associated with adverse SE outcomes.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Glioblastoma; Status epilepticus; Status epilepticus severity score (STESS)

Stereotactic radiotherapy as primary definitive or postoperative treatment of intracranial meningioma of WHO grade II and III leads to better disease control than stereotactic radiotherapy of recurrent meningioma - Lubgan, Dorota; Rutzner, Sandra; Lambrecht, Ulrike; Roessler, Karl; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Fietkau, Rainer; Semrau, Sabine (Journal of Neuro-Oncology, 2017)
The aim of this study was to evaluate long-term clinical outcome, prognostic factors and quality of life after adjuvant or definitive fractionated stereotactic radiotherapy (SRT) of meningioma WHO grade II and III or at recurrence. 131 patients with 138 meningioma (64 WHO grade II, 16 WHO grade III, 58 without histology) of the skull base, falx and convexity were treated between 01/2002 and 01/2015 at the Erlangen University Hospital by fractionated stereotactic radiotherapy (SRT) as primary treatment (adjuvant or definitive) and at recurrence. 53% (n = 53) lesions of patients with primary tumour received postoperative SRT and 47% (n = 47) as definitive treatment (without surgery). All 38 lesions (100%) of recurrent meningioma underwent surgery followed by SRT. SRT was mostly given in 28, 30 or 25 fractions to a median dose of 54.0 Gy in the reference point. Progression-free-survival at 8 years for patients with meningioma at primary treatment were significantly better with 100% for patients with definitive SRT (p = 0.008) or 85% for patients with adjuvant SRT (p = 0.009) compared to 42% after treatment (surgery + SRT) of recurrence. Progression-free-survival at 8 years for patients with SRT as adjuvant treatment after gross total resection of WHO grade II meningioma were significantly better at 83% (p = 0.016) compared to 46% after adjuvant SRT of recurrence. In 31% of patients after primary treatment and in 38.5% after recurrence treatment an improvement of pain symptoms was achieved. The favourable prognostic factor for better PFS at recurrence treatment was tumor location (skull base or convexity better compared to the falx). Postoperative SRT of WHO grade II meningioma after gross total resection (GTR) can effectively reduce recurrence risk.
EVALuna2:32870

Stereotactic radiotherapy of vestibular schwannoma : Hearing preservation, vestibular function, and local control following primary and salvage radiotherapy - Putz, Florian; Müller, Jan; Wimmer, Cornelia; Goerig, Nicole; Knippen, Stefan; Iro, Heinrich; Grundtner, Philipp; Eyüpoglu, Ilker Yasin; Roessler, Karl; Semrau, Sabine; Fietkau, Rainer; Lettmaier, Sebastian (Strahlentherapie und Onkologie, 2017)
OBJECTIVE: The aim of this publication is to present long-term data on functional outcomes and tumor control in a cohort of 107 patients treated with stereotactic radiotherapy (RT) for vestibular schwannoma. PATIENTS AND METHODS: Included were 107 patients with vestibular schwannoma (primary or recurrent following resection) treated with stereotactic RT (either fractioned or single-dose radiosurgery) between October 2002 and December 2013. Local control and functional outcomes were determined. Analysis of hearing preservation was limited to a subgroup of patients with complete audiometric data collected before treatment and during follow-up. Vestibular function test (FVT) results could be analyzed in a subset of patients and were compared to patient-reported dizziness. RESULTS: After a mean follow-up of 46.3 months, actuarial local control for the whole cohort was 100% after 2, 97.6% after 5, and 94.1% after 10 years. In patients with primary RT, serviceable hearing was preserved in 72%. Predictors for preservation of serviceable hearing in multivariate analysis were time of follow-up (odds ratio, OR = 0.93 per month; p = 0.021) and pre-RT tumor size (Koos stage I-IIa vs. IIb-IV; OR = 0.15; p = 0.031). Worsening of FVT results was recorded in 17.6% (N = 3). Profound discrepancy of patient-reported dizziness and FVT results was observed after RT. In patients with primary RT, worsening of facial nerve function occurred in 1.7% (N = 1). CONCLUSION: Stereotactic RT of vestibular schwannoma provides good functional outcomes and high control rates. Dependence of hearing preservation on time of follow-up and initial tumor stage has to be considered.
EVALuna2:32910

Stereotaktisch ablative Bestrahlung als Standardtechnik beim NSCLC im Stadium I bestätigt - Hecht, Markus; Fietkau, Rainer (Strahlentherapie und Onkologie, 2019)
CRIS-Team Scopus Importer:2019-10-08

Strukturelle, prozedurale und personelle Voraussetzung für die Erbringung radioonkologischer und strahlentherapeutischer Leistungen 2023 in Deutschland – ein Positionspapier der Deutschen Gesellschaft für Radioonkologie (DEGRO) - Fietkau, Rainer; Höller, Ulrike; Krause, Mechthild; Petersen, Cordula; van Kampen, Michael; Vordermark, Dirk; Willner, Jochen (Strahlentherapie und Onkologie, 2023)
CRIS-Team Scopus Importer:2023-07-07

Study on the Impact of CMV-Encephalopathy on the Survival of Brain Cancer Patients Undergoing Radio(Chemo) therapy of the Brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, M. A.; Engelhorn, Tobias; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, F.; et al. (2017)
EVALuna2:32868

Substantial Impairment of Quality of Life during COVID-19 Pandemic in Patients with Advanced Rectal Cancer - Dennison, Irene; Schweizer, Claudia; Fitz, Tim; Blasko, Daniel; Sörgel, Christopher; Kallies, Annett; Schmidt, Linda; Fietkau, Rainer; Distel, Luitpold (Healthcare, 2022)
The aim of this study was to analyze the quality of life of patients with advanced rectal cancer before and during the COVID-19 pandemic and to determine whether the pandemic affected patients' quality of life. The study included 389 patients and was performed from May 2010 to June 2021. The fifteen months from March 2020 to June 2021 were categorized as the COVID-19 period. Patients were surveyed using the QLQ-C30 and QLQ-CR38 questionnaires. The questionnaires were used at different phases of radiochemotherapy: prior to RCT (day 1), during RCT (day 14), at the end of RCT (day 35), and prior to mesorectal surgery (day 70). Scores were formed from the questions. In addition, scores were analyzed for different age groups (64) and sexes (female and male). Overall, patients reported lower functional scores and higher symptom scores during the pandemic than before the pandemic. Although it had been expected that older and younger patients would differ clearly, there were only minor differences. The comparison between the two sexes showed very different scores, with female patients having lower functional scores and higher symptom scores than male patients before and especially during COVID-19. In conclusion, age does not play a major role in quality of life, but sex does play an important role in perception of functioning and symptoms. COVID-19 also had a major impact on patients' lives, as it was a very isolating and stressful time for everyone, especially cancer patients, which was reflected in worsening scores.
CRIS-Team WoS Importer:2022-09-09

Successful implementation of online educational lectures of the German Society for Radiation Oncology (DEGRO) - Büttner, Marcel; Melton, Philip; Fietkau, Rainer; Petersen, Cordula; Krause, Mechthild; Borgmann, Kerstin; Wolf, Ulrich; Niyazi, Maximilian; Christiansen, Hans; Höller, Ulrike; Schmitt, Daniela; Käsmann, Lukas; et al. (Strahlentherapie und Onkologie, 2023)
Purpose: Modern digital teaching formats have become increasingly important in recent years, in part due to the COVID-19 pandemic. In January 2021, an online-based webinar series was established by the German Society for Radiation Oncology (DEGRO) and the young DEGRO (yDEGRO) working group. In the monthly 120-minute courses, selected lecturers teach curricular content as preparation for the board certification exam for radiation oncology. Methods: The evaluation of the 24 courses between 01.2021 and 12.2022 was performed using a standardized questionnaire with 21 items (recording epidemiological characteristics of the participants, didactic quality, content quality). A Likert scale (1–4) was used in combination with binary and open-ended questions. Results: A combined total of 4200 individuals (1952 in 2021 and 2248 in 2022) registered for the courses, and out of those, 934 participants (455 in 2021 and 479 in 2022) later provided evaluations for the respective courses (36% residents, 35% specialists, 21% medical technicians for radiology [MTR], 8% medical physics experts [MPE]). After 2 years, 74% of the DEGRO Academy curriculum topics were covered by the monthly webinars. The overall rating by participants was positive (mean 2021: 1.33 and 2022: 1.25) and exceeded the curriculum offered at each site for 70% of participants. Case-based learning was identified as a particularly well-rated method. Conclusion: The DEGRO webinar expands the digital teaching opportunities in radiation oncology. The consistently high number of participants confirms the need for high-quality teaching and underlines the advantages of e‑learning methods. Optimization opportunities were identified through reevaluation of feedback from course participants. In its design as a teaching format for a multiprofessional audience, the webinar series could be used as a practice model of online teaching for other disciplines.
CRIS-Team Scopus Importer:2023-11-03
Keywords: e‑learning; Medical education; Online webinar; Radiation oncology; Teaching format

Surgical and oncological outcome after extended lymph node dissection for carcinoma of the stomach and the esophagogastric junction: a retrospective analysis from an experienced single center - Raptis, Dimitrios; Maak, Matthias; Krautz, Christian; Merkel, Susanne; Brunner, Maximilian; Agaimy, Abbas; Hartmann, Arndt; Semrau, Sabine; Ott, Oliver; Fietkau, Rainer; Siebler, Jürgen; Grützmann, Robert; et al. (Archives of Medical Science, 2024)
Introduction: Gastric cancer remains the fourth leading cause of cancer-related death in Europe, while the proportion of adenocarcinomas of the esophagogastric junction has risen by more than one third over recent years. In 2018, 14,700 new cases of gastric cancer were estimated in Germany, while the 5-year relative survival rate is reported to be 33% for women and 30% for men; in the USA almost the same rate was reported, with 31% 5-year survival. Material and methods: Between 2001 and 2014, 590 patients with a diagnosis of gastric cancer underwent surgery in our institution, including 120 Siewert type II/III carcinomas of the esophagogastric junction. All patients underwent distal resection of the stomach, gastrectomy or total gastrectomy combined with transhiatal distal esophageal resection. All operations included D2-D3 lymph node dissection (LND). Data were recorded by the cancer registry of the department of surgery and analyzed retrospectively. Results: The patients were classified according to the TNM (UICC 2010) and Lauren classification. 29% of the patients underwent primary surgery and 31% received neoadjuvant therapy. The median number of harvested lymph nodes was 33 for patients diagnosed with gastric cancer, and 29 for esophagogastric adenocarcinomas, respectively. The anastomotic leak rate was 3%. In this study, the 5-year overall survival rate was 51% concerning gastric carcinomas, 44% for Siewert type II and 47% for Siewert III cancers of the esophagogastric junction. Conclusions: Increased survival with low complication rates were achieved after individualized and multimodal treatment concepts combined with consistently applied extended lymphadenectomy.
CRIS-Team Scopus Importer:2024-04-19
Keywords: D3 dissection; gastric cancer; Siewert II/III

Survey within the German Society for Radiation Oncology (DEGRO) on the Diagnosis and Treatment of Salivary Gland Carcinomas - Von Der Gruen, J.; Roedel, C.; Balermpas, P.; Martin, D.; Semrau, Sabine; Fietkau, Rainer; Haderlein, Marlen (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Survival analysis in rectal carcinoma after neoadjuvant chemoradiation: various methods with different results - Merkel, Susanne; Weber, Klaus; Göhl, Jonas; Agaimy, Abbas; Fietkau, Rainer; Hohenberger, Werner; Grützmann, Robert; Hermanek, Peter (International Journal of Colorectal Disease, 2017)
Survival is an important indicator of outcome quality in rectal carcinoma. The 5-year survival rate is the typical outcome measurement. In patients with neoadjuvant chemoradiation followed by curative surgery, 7 years of follow-up is recommended. Different methods of survival analysis lead to different results. Here, we compared four different methods.The data of 439 patients with rectal carcinoma treated with neoadjuvant chemoradiation followed by curative total mesorectal excision (TME) surgery between 1995 and 2010 were analysed. After stratifying by stage, relative survival (RS), cancer-related survival (CRS), overall survival (OS) and disease-free survival (DFS) were compared. In particular, the 3-year disease-free survival rate was compared to the 5- and 7-year overall survival rates.In the total cohort, the 5-year survival rates ranged from 90% (RS), over 84% (CRS) and 83% (OS) to 72% (DFS). Depending on the stage of disease, the differences between the 5-year survival rates varied between 10 and 32 percentage points. The differences were lowest in UICC stage y0 and highest in UICC stage yIV. The 3-year DFS-rate was always lower (worse) than the 5-year OS rate and higher (better) than the 7-year OS rate, with the exception of stage yIV.Comparisons of survival are only meaningful if the same methods are applied. The 3-year rate of DFS was always worse than the rate of 5-year OS. Therefore, the 3-year rate of DFS appears to be a useful surrogate indicator in rectal carcinoma treatment studies.
EVALuna2:6896

Synthetic CTs for MRI-only brain RT treatment: integration of immobilization systems - Masitho, Siti; Grigo, Johanna; Brandt, Tobias; Lambrecht, Ulrike; Szkitsak, Juliane; Weiß, Alexander; Fietkau, Rainer; Putz, Florian; Bert, Christoph (Strahlentherapie und Onkologie, 2023)
Purpose: Auxiliary devices such as immobilization systems should be considered in synthetic CT (sCT)-based treatment planning (TP) for MRI-only brain radiotherapy (RT). A method for auxiliary device definition in the sCT is introduced, and its dosimetric impact on the sCT-based TP is addressed. Methods: T1-VIBE DIXON was acquired in an RT setup. Ten datasets were retrospectively used for sCT generation. Silicone markers were used to determine the auxiliary devices’ relative position. An auxiliary structure template (AST) was created in the TP system and placed manually on the MRI. Various RT mask characteristics were simulated in the sCT and investigated by recalculating the CT-based clinical plan on the sCT. The influence of auxiliary devices was investigated by creating static fields aimed at artificial planning target volumes (PTVs) in the CT and recalculated in the sCT. The dose covering 50% of the PTV (D50) deviation percentage between CT-based/recalculated plan (∆D50[%]) was evaluated. Results: Defining an optimal RT mask yielded a ∆D50[%] of 0.2 ± 1.03% for the PTV and between −1.6 ± 3.4% and 1.1 ± 2.0% for OARs. Evaluating each static field, the largest ∆D50[%] was delivered by AST positioning inaccuracy (max: 3.5 ± 2.4%), followed by the RT table (max: 3.6 ± 1.2%) and the RT mask (max: 3.0 ± 0.8% [anterior], 1.6 ± 0.4% [rest]). No correlation between ∆D50[%] and beam depth was found for the sum of opposing beams, except for (45° + 315°). Conclusion: This study evaluated the integration of auxiliary devices and their dosimetric influence on sCT-based TP. The AST can be easily integrated into the sCT-based TP. Further, we found that the dosimetric impact was within an acceptable range for an MRI-only workflow.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Artificial intelligence; Image-guided radiotherapy; Radiotherapy setup; Stereotactic radiosurgery; Treatment planning

T1-SPACE vs. T1-MPRAGE for Target Volume Definition in Brain Metastases - a radiotherapy-oriented Comparison - Mansoorian, S.; Mengling, Veit; Masitho, Siti; Perrin, R.; Siavooshaghighi, H.; Weissmann, T.; Filimonova, Irina; Bert, Christoph; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Targeted Natural Killer Cell-Based Adoptive Immunotherapy for the Treatment of Patients with NSCLC after Radiochemotherapy: A Randomized Phase II Clinical Trial - Multhoff, Gabriele; Seier, Sophie; Stangl, Stefan; Sievert, Wolfgang; Shevtsov, Maxim; Werner, Caroline; Pockley, A. Graham; Blankenstein, Christiane; Hildebrandt, Martin; Offner, Robert; Ahrens, Norbert; Kokowski, Konrad; et al. (Clinical Cancer Research, 2020)
Purpose: Non-small cell lung cancer (NSCLC) is a fatal disease with poor prognosis. Amembrane-bound form of Hsp70 (mHsp70) which is selectively expressed on high-risk tumors serves as a target for mHsp70-targeting natural killer (NK) cells. Patients with advanced mHsp70-positive NSCLC may therefore benefit from a therapeutic intervention involving mHsp70-targeting NK cells. The randomized phase II clinical trial (EudraCT2008-002130-30) explores tolerability and efficacy of ex vivo-activated NK cells in patients with NSCLC after radiochemotherapy (RCT).
CRIS-Team WoS Importer:2020-11-13

Targeted Natural Killer (NK) cell based adoptive immunotherapy for the treatment of patients with non-small cell lung cancer (NSCLC) after radiochemotherapy results of a randomized phase II clinical trial (NSCLC-TKD/IL-2) (Eudra-CT Number 2008-002130-30) - Multhoff, Gabriele; Combs, Stephanie E.; Seier, Sophie; Stangl, Stefan; Sievert, Wolfgang; Shevtsov, Maxim; Blankenstein, Christiane; Hildebrandt, Martin; Kokowski, Konrad; Hautmann, Matthias; Hautmann, Hubert; Roedel, Claus; et al. (CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2021-03-05

Targeted Therapy, Chemotherapy, Immunotherapy and Novel Treatment Options for Different Subtypes of Salivary Gland Cancer - Müller, Sarina Katrin; Haderlein, Marlen; Lettmaier, Sebastian; Agaimy, Abbas; Haller, Florian; Hecht, Markus; Fietkau, Rainer; Iro, Heinrich; Mantsopoulos, Konstantinos (Journal of Clinical Medicine, 2022)
Surgical resection remains the first line treatment for salivary gland cancer (SGC). In the case of locally advanced disease, surgery is followed by adjuvant radiotherapy. Surgical resection should be favored in resectable locoregional recurrent disease as well, and even the complete resection of all distant oligometastases has clinical benefit for the patients. For inoperable and disseminated metastatic disease, a multitude of systemic therapies including chemotherapy, targeted therapy, and immunotherapy are available. In this review, the current therapeutic options for inoperable recurrent or metastatic SGCs are summarized. Systemic treatment can achieve prolonged progression-free and overall survival, while the overall prognosis remains poor. Current clinical trials include only a limited number of patients and mostly combine different histologic subtypes. Additionally, no randomized controlled trial comparing different therapeutic options has been performed. In the future, further studies with a larger patient cohort and ideally only one histologic subtype are needed in order to improve the outcome for SGC patients. However, this may be difficult to accomplish due to the rarity and diversity of the disease. Additionally, molecular analyses need to be performed routinely in order to individualize treatment and to go one step further towards precision medicine.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Acinic cell carcinoma; Adenoid cystic carcinoma; Chemotherapy; Immunotherapy; Mucoepidermoid carcinoma; Salivary duct carcinoma; Salivary gland cancer; Targeted therapy

Technical evaluation of the cone-beam computed tomography imaging performance of a novel, mobile, gantry-based X-ray system for brachytherapy - Karius, Andre; Karolczak, Marek; Strnad, Vratislav; Bert, Christoph (Journal of Applied Clinical Medical Physics, 2021)
Purpose A novel, mobile cone-beam computed tomography (CBCT) system for image-guided adaptive brachytherapy was recently deployed at our hospital as worldwide first site. Prior to the device's clinical operation, a profound characterization of its imaging performance was conducted. This was essential to optimize both the imaging workflow and image quality for achieving the best possible clinical outcomes. We present the results of our investigations. Methods The novel CBCT-system features a ring gantry with 121 cm clearance as well as a 43.2 x 43.2 cm(2) flat-panel detector, and is controlled via a tablet-personal computer (PC). For evaluating its imaging performance, the geometric reproducibility as well as imaging fidelity, computed tomography (CT)-number accuracy, uniformity, contrast-noise-ratio (CNR), noise characteristics, and spatial resolution as fundamental image quality parameters were assessed. As dose metric the weighted cone-beam dose index (CBDIw) was measured. Image quality was evaluated using standard quality assurance (QA) as well as anthropomorphic upper torso and breast phantoms. Both in-house and manufacturer protocols for abdomen, pelvis, and breast imaging were examined. Results Using the in-house protocols, the QA phantom scans showed altogether a high image quality, with high CT-number accuracy (R-2 > 0.97) and uniformity (<12 Hounsfield Unit (HU) cupping), reasonable noise and imaging fidelity, and good CNR at bone-tissue transitions of up to 28:1. Spatial resolution was strongly limited by geometric instabilities of the device. The breast phantom scans fulfilled clinical requirements, whereas the abdomen and pelvis scans showed severe artifacts, particularly at air/bone-tissue transitions. Conclusion With the novel CBCT-system, achieving a high image quality appears possible in principle. However, adaptations of the standard protocols, performance enhancements in image reconstruction referring to artifact reductions, as well as the extinction of geometric instabilities are imperative.
CRIS-Team WoS Importer:2021-12-24

Technical Note: A comparison of point set registration methods for electromagnetic tracking - Götz, T. I.; Wankerl, H.; Tomé, A. M.; Meyer-Baese, A.; Bert, Christoph; Hensel, Bernhard; Lang, E. W. (Medical Physics, 2019)
Purpose: High dose rate brachytherapy applies intense and destructive radiation. A treatment plan defines radiation source dwell positions to avoid irradiating healthy tissue. The study discusses methods to quantify any positional changes of source locations along the various treatment sessions. Methods: Electromagnetic tracking (EMT) localizes the radiation source during the treatment sessions. But in each session the relative position of the patient relative to the filed generator is changed. Hence, the measured dwell point sets need to be registered onto each other to render them comparable. Two point set registration techniques are compared: a probabilistic method called coherent point drift (CPD) and a multidimensional scaling (MDS) technique. Results: Both enable using EMT without external registration and achieve very similar results with respect to dwell position determination of the radiation source. Still MDS achieves smaller grand average deviations (CPD-rPSR: MD = 2.55 mm, MDS-PSR: MD = 2.15 mm) between subsequent dwell position determinations, which also show less variance (CPD-rPSR: IQR = 4 mm, MDS-PSR: IQR = 3 mm). Furthermore, MDS is not based on approximations and does not need an iterative procedure to track sensor positions inside the implanted catheters. Conclusion: Although both methods achieve similar results, MDS is to be preferred over rigid CPD while nonrigid CPD is unsuitable as it does not preserve topology.
CRIS-Team Scopus Importer:2019-05-17
Keywords: brachytherapy; electromagnetic tracking; multi-dimensional scaling; point set registration

Technical Note: Radiation properties of tissue- and water-equivalent materials formulated using the stoichiometric analysis method in charged particle therapy - Yohannes, Indra; Hild, Sebastian; Vasiliniuc, Stefan; Langner, Oliver; Graeff, Christian; Bert, Christoph (Medical Physics, 2016)
Five tissue- and water-equivalent materials (TEMs) mimicking ICRU real tissues have been formulated using a previously established stoichiometric analysis method (SAM) to be applied in charged particle therapy. The purpose of this study was an experimental verification of the TEMs-SAM against charged particle beam measurements and for different computed tomography (CT) scanners. The potential of the TEMs-SAM to be employed in the dosimetry was also investigated.Experimental verification with three CT scanners was carried out to validate the calculated Hounsfield units (HUs) of the TEMs. Water-equivalent path lengths (WEPLs) of the TEMs for proton (106.8 MeV/u), helium (107.93 MeV/u), and carbon (200.3 MeV/u) ions were measured to be compared with the computed relative stopping powers. HU calibration curves were also generated.Differences between the measured HUs of the TEMs and the calculated HUs of the ICRU real tissues for all CT scanners were smaller than 4 HU except for the skeletal tissues which deviated up to 21 HU. The measured WEPLs verified the calculated WEPLs of the TEMs (maximum deviation was 0.17 mm) and were in good agreement with the calculated WEPLs of the ICRU real tissues (maximum deviation was 0.23 mm). Moreover, the relative stopping powers converted from the measured WEPLs differed less than 0.8% and 1.3% from the calculated values of the SAM and the ICRU, respectively. Regarding the relative nonelastic cross section per unit of volume for 200 MeV protons, the ICRU real tissues were generally well represented by the TEMs except for adipose which differed 3.8%. Further, the HU calibration curves yielded the mean and the standard deviation of the errors not larger than 0.5% and 1.9%, respectively.The results of this investigation implied the potential of the TEMs formulated using the SAM to be employed for both, beam dosimetry and HU calibration in charged particle therapy.
EVALuna2:18348

Temozolomide-induced liver damage. A case report - Becker, F.; Hecht, Markus; Schmidtner, J.; Semrau, S.; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
Temozolomide (TMZ) is an alkylating agent used in chemoradiotherapy and adjuvant chemotherapy regimens for treatment of newly diagnosed or recurrent glioblastoma. In Germany alone, 900,000 daily doses of the drug are prescribed each year. Therefore, all severe side effects of TMZ, even those rarely observed, are relevant to radiotherapists.We report a case of severe drug-induced toxic hepatitis that developed during chemoradiotherapy with TMZ in a patient with glioblastoma multiforme.Transaminase elevation was observed after 5 weeks of TMZ treatment, followed by severe jaundice symptoms which only subsided 2 months later. These findings were consistent with diagnosis of the mixed hepatic/cholestatic type of drug-induced toxic hepatitis. Due to the early termination of treatment, no life-threatening complications occurred in our patient. However, rare reports of encephalopathy and fatality as complications of TMZ therapy can be found in the literature.When using TMZ for treatment of glioblastoma, monitoring of liver enzyme levels should be performed twice weekly to prevent fatal toxic hepatitis. In the case of any drug-induced hepatitis, TMZ must be discontinued immediately.
EVALuna2:18198

Temozolomide resistance in human glioblastoma cell line U251 is caused by mismatch repair deficiency and can be overcome by lomustine - Stritzelberger, Jenny; Distel, T.; Fietkau, Rainer; Putz, Florian (2016)
EVALuna2:18332

Temporarily increased TGFβ following radon spa correlates with reduced pain while serum IL-18 is a general predictive marker for pain sensitivity - Kullmann, Miriam; Rühle, Paul-Friedrich; Harrer, Alexandra; Donaubauer, Anna-Jasmina; Becker, Ina; Sieber, Renate; Klein, Gerhart; Fournier, Claudia; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Radiation and Environmental Biophysics, 2019)
Sustained pain relief following radon spa therapy in patients suffering from chronic painful diseases has been well described. But still, the underlying mechanisms are not fully understood. We conducted the prospective and explorative RAD-ON01 study which included 103 patients who suffered from chronic painful musculoskeletal disorders of the spine and/or joints and present here the data of the examination of pro- and anti-inflammatory cytokines in the serum of the patients before and at weeks 6, 12 and 30 after therapy. While TNFα, IL-1β, IFNγ, IL-1Ra and IL-10 were not altered, TGFβ was temporarily significantly (p = 0.013) elevated 6 weeks after therapy. Importantly, this elevation positively correlated with lowered pain sensitivity (r = 0.41). Further, the amount of IL-18 in the serum positively correlated with lowered pain sensitivity. Therefore, IL-18 can be considered as predictive marker for pain sensitivity of radon spa patients. We conclude that alterations in TGFβ and general IL-18 levels in serum have prognostic and predictive value in situations of lowered pain by exposure of patients to very low-doses of radiation as it is the case in radon spa.
EVALuna2:36449

The 2021 Updated European Association of Urology Guidelines on Metastatic Urothelial Carcinoma - Cathomas, Richard; Lorch, Anja; Bruins, Harman M.; Compérat, Eva M.; Cowan, Nigel C.; Efstathiou, Jason A.; Fietkau, Rainer; Gakis, Georgios; Hernández, Virginia; Espinós, Estefania Linares; Neuzillet, Yann; Ribal, Maria J.; et al. (European Urology, 2022)
Context: Treatment of metastatic urothelial carcinoma is currently undergoing a rapid evolution. Objective: This overview presents the updated European Association of Urology (EAU) guidelines for metastatic urothelial carcinoma. Evidence acquisition: A comprehensive scoping exercise covering the topic of metastatic urothelial carcinoma is performed annually by the Guidelines Panel. Databases covered by the search included Medline, EMBASE, and the Cochrane Libraries, resulting in yearly guideline updates. Evidence synthesis: Platinum-based chemotherapy is the recommended first-line standard therapy for all patients fit to receive either cisplatin or carboplatin. Patients positive for programmed death ligand 1 (PD-L1) and ineligible for cisplatin may receive immunotherapy (atezolizumab or pembrolizumab). In case of nonprogressive disease on platinum-based chemotherapy, subsequent maintenance immunotherapy (avelumab) is recommended. For patients without maintenance therapy, the recommended second-line regimen is immunotherapy (pembrolizumab). Later-line treatment has undergone recent advances: the antibody-drug conjugate enfortumab vedotin demonstrated improved overall survival and the fibroblast growth factor receptor (FGFR) inhibitor erdafitinib appears active in case of FGFR3 alterations. Conclusions: This 2021 update of the EAU guideline provides detailed and contemporary information on the treatment of metastatic urothelial carcinoma for incorporation into clinical practice. Patient summary: In recent years, several new treatment options have been introduced for patients with metastatic urothelial cancer (including bladder cancer and cancer of the upper urinary tract and urethra). These include immunotherapy and targeted treatments. This updated guideline informs clinicians and patients about optimal tailoring of treatment of affected patients.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Bladder cancer; European Association of Urology; Guidelines; Immunotherapy; Metastatic; Systemic therapy; Urothelial carcinoma

The 3rd ESTRO-EFOMP core curriculum for medical physics experts in radiotherapy - Garibaldi, Cristina; Essers, Marion; Heijmen, Ben; Bertholet, Jenny; Koutsouveli, Efi; Schwarz, Marco; Bert, Christoph; Bodale, Marin; Casares-Magaz, Oscar; Gerskevitch, Eduard; Koniarova, Irena; Korreman, Stine; et al. (Radiotherapy and Oncology, 2022)
Purpose: To update the 2011 ESTRO-EFOMP core curriculum (CC) for education and training of medical physics experts (MPE)s working in radiotherapy (RT), in line with recent EU guidelines, and to provide a framework for European countries to develop their own curriculum. Material and methods: Since September 2019, 27 European MPEs representing ESTRO, EFOMP and National Societies, with expertise covering all subfields of RT physics, have revised the CC for recent advances in RT. The ESTRO and EFOMP Education Councils, all European National Societies and international stakeholders have been involved in the revision process. Results: A 4-year training period has been proposed, with a total of 240 ECTS (European Credit Transfer and Accumulation System). Training entrance levels have been defined ensuring the necessary physics and mathematics background. The concept of competency-based education has been reinforced by introducing the CanMEDS role framework. The updated CC includes (ablative) stereotactic-, MR-guided- and adaptive RT, particle therapy, advanced automation, complex quantitative data analysis (big data/artificial intelligence), use of biological images, and personalized treatments. Due to the continuously increasing RT complexity, more emphasis has been given to quality management. Clear requirements for a research project ensure a proper preparation of MPE residents for their central role in science and innovation in RT. Conclusion: This updated, 3rd edition of the CC provides an MPE training framework for safe and effective practice of modern RT, while acknowledging the significant efforts needed in some countries to reach this level. The CC can contribute to further harmonization of MPE training in Europe.
CRIS-Team Scopus Importer:2022-05-13
Keywords: Core curriculum (CC); Education and training; ESTRO-EFOMP; Medical Physics Expert (MPE); Radiotherapy physics

The Differential Diagnosis and Inter - disciplinary Treatment of Anal Carcinoma - Raptis, Dimitrios; Schneider, Ignaz Hans Friedrich; Matzel, Klaus E.; Ott, Oliver; Fietkau, Rainer; Hohenberger, Werner (Deutsches Ärzteblatt international, 2015)
Anal carcinoma accounts for 2-4% of all cases of colorectal and anorectal carcinoma. Its peak incidence is from age 58 to age 64; women are affected somewhat more commonly than men. Its incidence has risen markedly in the past three decades.This article is based on a selective review of the literature, including the guidelines of the National Comprehensive Cancer Network and the European Society of Medical Oncology.Anal carcinoma is often an incidental finding. About 85% of newly diagnosed cases are associated with an HPV infection with strain 16, 18, or 33. Radiochemotherapy with 5-fluorouracil and mitomycin C is the treatment of choice. The 5-year survival rate is 80-90%. Primary surgery with curative intent is indicated only for well-differentiated carcinoma of the anal margin (T1, N0). 10-30% of patients now undergo radical resection. The utility of endosonography and positron emission tomography for staging is debated and needs further study.The treatment of patients with anal carcinoma requires a specialized multidisciplinary approach in accordance with the current evidence-based guidelines. The potential role of prophylactic vaccination against oncogenic types of HPV in the prevention of anal carcinoma merits further investigation.
EVALuna2:15196

The Distribution of Pelvic Nodal Metastases in Prostate Cancer Reveals Potential to Advance and Personalize Pelvic Radiotherapy - Filimonova, Irina; Schmidt, Daniela; Mansoorian, Sina; Weissmann, Thomas; Siavooshhaghighi, Hadi; Kuwert, Torsten; Bert, Christoph; Frey, Benjamin; Distel, Luitpold; Lettmaier, Sebastian; Fietkau, Rainer; Putz, Florian; et al. (Frontiers in Oncology, 2021)
Background: Traditional clinical target volume (CTV) definition for pelvic radiotherapy in prostate cancer consists of large volumes being treated with homogeneous doses without fully utilizing information on the probability of microscopic involvement to guide target volume design and prescription dose distribution. Methods: We analyzed patterns of nodal involvement in 75 patients that received RT for pelvic and paraaortic lymph node metastases (LNs) from prostate cancer in regard to the new NRG-CTV recommendation. Non-rigid registration-based LN mapping and weighted three-dimensional kernel density estimation were used to visualize the average probability distribution for nodal metastases. As independent approach, the mean relative proportion of LNs observed for each level was determined manually and NRG and non-NRG levels were evaluated for frequency of involvement. Computer-automated distance measurements were used to compare LN distances in individual patients to the spatial proximity of nodal metastases at a cohort level. Results: 34.7% of patients had pelvic LNs outside NRG-consensus, of which perirectal was most common (25.3% of all patients) followed by left common iliac nodes near the left psoas major (6.7%). A substantial portion of patients (13.3%) had nodes at the posterior edge of the NRG obturator level. Observer-independent mapping consistently visualized high-probability hotspots outside NRG-consensus in the perirectal and left common iliac regions. Affected nodes in individual patients occurred in highly significantly closer proximity than at cohort-level (mean distance, 6.6 cm vs. 8.7 cm, p < 0.001). Conclusions: Based on this analysis, the common iliac level should extend to the left psoas major and obturator levels should extend posteriorly 5 mm beyond the obturator internus. Incomplete coverage by the NRG-consensus was mostly because of perirectal involvement. We introduce three-dimensional kernel density estimation after non-rigid registration-based mapping for the analysis of recurrence data in radiotherapy. This technique provides an estimate of the underlying probability distribution of nodal involvement and may help in addressing institution- or subgroup-specific differences. Nodal metastases in individual patients occurred in highly significantly closer proximity than at a cohort-level, which supports that personalized target volumes could be reduced in size compared to a “one-size-fits-all” approach and is an important basis for further investigation into individualized field designs.
CRIS-Team Scopus Importer:2021-02-05
Keywords: lymph node metastases; mapping; patterns of recurrence; pelvic radiotherapy; prostate cancer

The Early Landscape of Immune Cell Subsets in Metastatic NSCLC Patients Treated with Immune Checkpoint Inhibitors - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Sun, R.; Ma, H.; Fietkau, Rainer; Deutsch, E.; Gaipl, Udo; Hecht, Markus (JOURNAL OF THORACIC ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-07

The Effect of Hyperthermia and Radiotherapy Sequence on Cancer Cell Death and the Immune Phenotype of Breast Cancer Cells - Sengedorj, Azzaya; Hader, Michael; Heger, Lukas; Frey, Benjamin; Dudziak, Diana; Fietkau, Rainer; Ott, Oliver; Scheidegger, Stephan; Barba, Sergio Mingo; Gaipl, Udo; Rückert, Michael (Cancers, 2022)
Hyperthermia (HT) is an accepted treatment for recurrent breast cancer which locally heats the tumor to 39–44◦C, and it is a very potent sensitizer for radiotherapy (RT) and chemotherapy. However, currently little is known about how HT with a distinct temperature, and particularly, how the sequence of HT and RT changes the immune phenotype of breast cancer cells. Therefore, human MDA-MB-231 and MCF-7 breast cancer cells were treated with HT of different temperatures (39, 41 and 44◦C), alone and in combination with RT (2 × 5 Gy) in different sequences, with either RT or HT first, followed by the other. Tumor cell death forms and the expression of immune checkpoint molecules (ICMs) were analyzed by multicolor flow cytometry. Human monocyte-derived dendritic cells (moDCs) were differentiated and co-cultured with the treated cancer cells. In both cell lines, RT was the main stressor for cell death induction, with apoptosis being the prominent cell death form in MCF-7 cells and both apoptosis and necrosis in MDA-MB-231 cells. Here, the sequence of the combined treatments, either RT or HT, did not have a significant impact on the final outcome. The expression of all of the three examined immune suppressive ICMs, namely PD-L1, PD-L2 and HVEM, was significantly increased on MCF-7 cells 120 h after the treatment of RT with HT of any temperature. Of special interest for MDA-MB-231 cells is that only combinations of RT with HT of both 41 and 44◦C induced a significantly increased expression of PD-L2 at all examined time points (24, 48, 72, and 120 h). Generally, high dynamics of ICM expression can be observed after combined RT and HT treatments. There was no significant difference between the different sequences of treatments (either HT + RT or RT + HT) in case of the upregulation of ICMs. Furthermore, the co-culture of moDCs with tumor cells of any treatment had no impact on the expression of activation markers. We conclude that the sequence of HT and RT does not strongly affect the immune phenotype of breast cancer cells. However, when HT is combined with RT, it results in an increased expression of distinct immune suppressive ICMs that should be considered by including immune checkpoint inhibitors in multimodal tumor treatments with RT and HT. Further, combined RT and HT affects the immune system in the effector phase rather than in the priming phase.
CRIS-Team Scopus Importer:2022-04-29
Keywords: breast cancer; dendritic cell activation; hyperthermia; hyperthermia treatment sequence; immune checkpoint molecules; immune phenotype; radiotherapy

The Emerging Evidence Supporting Integration of Deep Regional Hyperthermia With Chemoradiation in Bladder Cancer - Ott, Oliver; Gaipl, Udo; Lamrani, Allison; Fietkau, Rainer (Seminars in Radiation Oncology, 2023)
For decades, the antineoplastic potential of hyperthermia alone or in combination with radiotherapy and/or chemotherapy has been subject of intensive preclinical and clinical research in various tumor entities. The clinical evidence on the beneficial effects of additional hyperthermia in combination with intravesical Mitomycin C for superficial non-muscle-invasive bladder cancer as well as for deep regional microwave hyperthermia techniques applied during an external beam radiotherapy or chemoradiation treatment for more advanced tumors are summarized. In some series, deep regional hyperthermia in combination with an initial transurethral resection and Cisplatin-based chemoradiation increased the 5-year overall survival rates up to 20%. The presented data justifies a fresh irrespective chance for mild regional hyperthermia in the context of new progressive prospective trials on multimodality treatment for bladder preservation.
CRIS-Team Scopus Importer:2022-12-23

The Erlangen Dose Optimization trial for low-dose radiotherapy of benign painful elbow syndrome. Long-term results - Ott, O. J.; Hertel, Sascha; Gaipl, Udo; Frey, Benjamin; Schmidt, M.; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
To evaluate the long-term efficacy of pain reduction by two dose fractionation schedules used for low-dose radiotherapy of painful elbow syndrome.Between February 2006 and February 2010, 199 evaluable patients were recruited for this prospective trial. All patients received low-dose orthovoltage radiotherapy. One course consisted of 6 fractions in 3 weeks. In the case of insufficient pain remission after 6 weeks, a second course was administered. Patients were randomly assigned to one of two groups to receive single doses of either 0.5 or 1.0 Gy. Endpoint was pain reduction. Pain was measured before radiotherapy, as well as immediately after (early response), 6 weeks after (delayed response) and approximately 3 years after (long-term response) completion of radiotherapy using a questionnaire-based visual analogue scale (VAS) and a comprehensive pain score (CPS).Median follow-up was 35 months (range 9-57 months). The overall early, delayed and long-term response rates for all patients were 80, 90 and 94 %, respectively. The mean VAS scores before treatment and those for early, delayed and long-term response in the 0.5- and 1.0-Gy groups were 59.6 ± 20.2 and 55.7 ± 18.0 (p = 0.46); 32.1 ± 24.5 and 34.4 ± 22.5 (p = 0.26); 27.0 ± 27.7 and 23.5 ± 21.6 (p = 0.82) and 10.7 ± 15.0 and 21.5 ± 26.9 (p = 0.12), respectively. The mean CPS values before treatment and those for early, delayed and long-term response were 8.7 ± 2.9 and 8.1 ± 3.1 (p = 0.21); 4.5 ± 3.2 and 5.0 ± 3.4 (p = 0.51); 3.9 ± 3.6 and 2.8 ± 2.8 (p = 0.19) and 1.5 ± 2.3 and 2.4 ± 3.5 (p = 0.27), respectively. No significant differences in the quality of the long-term response were found between the 0.5- and 1.0-Gy arms (p = 0.28).Low-dose radiotherapy is an effective treatment for the management of benign painful elbow syndrome. For radiation protection reasons, the dose for a radiotherapy series should not exceed 3.0 Gy.
EVALuna2:18200

The Erlangen Dose Optimization Trial for radiotherapy of benign painful shoulder syndrome. Long-term results - Ott, O. J.; Hertel, Sascha; Gaipl, Udo; Frey, Benjamin; Schmidt, M.; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
To evaluate the long-term efficacy of pain reduction by two dose-fractionation schedules for radiotherapy of painful shoulder syndrome.Between February 2006 and February 2010, 312 evaluable patients were recruited for this prospective trial. All patients received low-dose orthovoltage radiotherapy. One course consisted of 6 fractions in 3 weeks. In the case of insufficient pain remission after 6 weeks, a second course was administered. Patients were randomly assigned to one of two groups to receive single doses of either 0.5 or 1.0 Gy. Endpoint was pain reduction. Pain was measured before radiotherapy, as well as immediately after (early response), 6 weeks after (delayed response) and approximately 3 years after (long-term response) completion of radiotherapy using a questionnaire-based visual analogue scale (VAS) and a comprehensive pain score (CPS).Median follow-up was 35 months (range 11-57). The overall early, delayed and long-term response rates for all patients were 83, 85 and 82 %, respectively. The mean VAS scores before treatment and those for early, delayed and long-term response in the 0.5- and 1.0-Gy groups were 56.8 ± 23.7 and 53.2 ± 21.8 (p = 0.16); 38.2 ± 36.1 and 34.0 ± 24.5 (p = 0.19); 33.0 ± 27.2 and 23.7 ± 22.7 (p = 0.04) and 27.9 ± 25.8 and 32.1 ± 26.9 (p = 0.25), respectively. The mean CPS values before treatment and those for early, delayed and long-term response were 9.7 ± 3.0 and 9.5 ± 2.7 (p = 0.31); 6.1 ± 3.6 and 5.4 ± 3.6 (p = 0.10); 5.3 ± 3.7 and 4.1 ± 3.7 (p = 0.05) and 4.0 ± 3.9 and 5.3 ± 4.4 (p = 0.05), respectively. No significant differences in the quality of the long-term response were found between the 0.5- and 1.0-Gy arms (p = 0.28).Radiotherapy is an effective treatment for the management of benign painful shoulder syndrome. For radiation protection reasons, the dose for a radiotherapy series should not exceed 3.0 Gy.
EVALuna2:18186

The Growth of primary and abscopal Tumors as well as their immunological Microenvironment are differently influenced by different Combinations of Radiation and Immunotherapies - Rückert, Michael; Deloch, Lisa; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

The health-related quality of life of sarcoma patients treated with neoadjuvant versus adjuvant radiotherapy – Results of a multi-center observational study - Singer, Susanne; Semrau, Sabine; Golcher, Henriette; Fechner, Katja; Kallies, Annett; Zapata Bonilla, Sergio; Grützmann, Robert; Fietkau, Rainer; Kluba, Torsten; Jentsch, Christina; Andreou, Dimosthenis; Bornhäuser, Martin; et al. (Radiotherapy and Oncology, 2023)
Aim: The sequence of radiotherapy and resection in patients with soft tissue sarcomas is usually discussed on an individual basis. Better understanding of potential differences of health-related quality of life (QoL) between patients undergoing adjuvant (ART) versus neoadjuvant radiotherapy (NART) is therefore helpful for clinical decision making. Methods: Adult sarcoma patients from 39 hospitals completed the European Organisation for Research and Treatment of Cancer Quality of Life Core Questionnaire (EORTC QLQ-C30). Differences in global QoL, physical functioning, role functioning, fatigue, pain, and insomnia between ART versus NART were investigated with multivariate regression, adjusting for age, gender, chemotherapy, grading, stage, tumor location, recurrence/distant metastasis, sarcoma type, time since last treatment, and treatment status using validated thresholds. Results: A total of 1110 patients participated. Of them, 340 had received radiotherapy (NART: n = 95, 28%; ART: n = 245, 72%). Global QoL was 59.3 on average after NART and 60.5 after ART (Badj = 1.0, p = 0.74). Physical functioning was 65.9 compared to 70.5 (Badj = 4.2; p = 0.16), role function 48.8 vs. 56.7 (Badj = 7.0, p = 0.08), fatigue 47.5 vs. 45.4 (Badj = -1.2; p = 0.71), pain 40.2 vs. 34.1 (Badj = -6.8; p = 0.08), and insomnia 33.7 vs. 41.6 (Badj = 5.5, p = 0.16). Among patients with NART, clinically relevant QoL impairments were less frequent 2 years after treatment compared to < 2 years thereafter (n = 6 vs. n = 4 on average). Conclusion: There is little evidence for QoL differences in most domains and overall QoL between the two irradiation groups. However, patients after NART might experience worse role functioning and pain but fewer problems with insomnia compared to patients after ART.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Leiomyosarcoma; Liposarcoma; Neoadjuvant Therapy; Neoplasms; Connective and Soft Tissue; Patient Reported Outcome Measures; Radiotherapy; Adjuvant

The IMMO-LDRT01 Study - Analgesic and immunomodulatory Effects of LDRT in Patients with chronic degenerative and inflammatory Diseases - Donaubauer, Anna-Jasmina; Fröhlich, Birgitta; Becker, Ina; Weissmann, Thomas; Fietkau, Rainer; Ott, Oliver; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

The IMMO-LDRT01 Study: Immunomodulatory Effects of X-ray Irradiation in chronic degenerative and inflammatory Diseases - Donaubauer, Anna-Jasmina; Gryc, Thomas; Froehlich, B.; Becker, I.; Ott, O. J.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

The immune reaction against allogeneic necrotic cells is reduced in Annexin A5 knock out mice whose macrophages display an anti-inflammatory phenotype - Frey, Benjamin; Munoz, Luis Enrique; Pausch, Friederike; Sieber, Renate; Franz, Sandra; Brachvogel, Bent; Poschl, Ernst; Schneider, Holm; Roedel, Franz; Sauer, Rolf; Fietkau, Rainer; Herrmann, Martin; et al. (Journal of Cellular and Molecular Medicine, 2009)
Proteins of the annexin family bind to phospholipids in a Ca2+ dependent manner. The exposure of phosphatidylserine (PS) by apoptotic as well as necrotic cells is one major eat-me-signal for macrophages. Annexin A5 (Anx A5) preferentially binds to PS. The availability of Anx A5 knock out (KO) mice allowed us to investigate for the first time if endogenous Anx A5 modulates the immune response towards allogeneic cells. Furthermore, the effect of Anx A5 gene deletion on the phagocytic process as well as on the inflammatory reaction of macrophages was explored. We found that Anx A5 KO mice have a strongly reduced allogeneic cellular immune reaction against primary as well as secondary necrotic cells. In vivo phagocytosis experiments revealed that macrophages of Anx A5 KO mice displayed an increased uptake of necrotic cells. Additionally, an increased secretion of the anti-inflammatory cytokine IL-10 of isolated macrophages of Anx A5 KO mice after contact with necrotic cells was observed. Furthermore, the promoter activity of the Anx A5 gene was enhanced after stimulation of macrophages. The tumour size of an allogeneic tumour regressed faster when endogenous Anx A5 was present. These data demonstrate that endogenous Anx A5 influences the phagocytosis of necrotic cells, modulates the immune response towards allogeneic cells and acts as an inflammatory protein. © 2009 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Allogeneic cells; Annexin A5; Immune modulation; Inflammation; Macrophages; Phagocytosis; Primary necrosis; Secondary necrosis

THE IMPACT OF LOW-DOSE RADIATION ON INFLAMMATORY DISEASES - Deloch, Lisa; Derer, Anja; Hueber, Axel; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2016)
EVALuna2:32924

The impact of surgical quality on prognosis in patients undergoing rectal carcinoma surgery after preoperative chemoradiation - Kiehlmann, Marcus; Weber, Klaus; Göhl, Jonas; Fietkau, Rainer; Agaimy, Abbas; Hohenberger, Werner; Merkel, Susanne (International Journal of Colorectal Disease, 2016)
The aim of the study was to analyse the impact of surgical quality on the prognosis of rectal carcinoma patients who underwent preoperative long-term chemoradiation and TME surgery.In a total of 314 patients, four quality indicators, including plane of surgery, pathological circumferential resection margin (pCRM), intraoperative local tumour cell dissemination and anastomotic leakage, were analysed with respect to locoregional recurrence, distant metastasis and overall survival.In 260 (82.8 %) of the patients, all four quality indicators were fulfilled. In 30 (9.6 %) of the patients, at least one quality indicator was not fulfilled; in 24 (7.6 %) of the patients, the data were not complete. Locoregional recurrence was significantly increased in patients who underwent surgery in the muscularis propria plane, who had a pCRM <= 1 mm or who experienced local tumour cell dissemination. In patients who had at least one quality indicator that was not fulfilled (suboptimal surgical quality), the 5-year rate of locoregional recurrence in those patients was 23.1 % compared to 4.8 % in patients who underwent optimal surgery (P = 0.001). In multivariate analysis, suboptimal surgery (hazard ratio (HR) 3.9; P = 0.020), abdominoperineal excision (HR 4.7; P = 0.003) and poor regression of primary tumours (HR 8.5; P < 0.001) were identified as independent prognostic factors for locoregional recurrence. In contrast to type of surgical treatment, ypT, ypN and regression grade, the quality of surgery did not significantly influence distant metastasis or overall survival.Even after preoperative chemoradiation, the surgical quality still has a strong impact on local control in patients with rectal carcinoma.
EVALuna2:6711

The Influence of Iron(II) Clathrochelates and Irradiation on Cell Death, reactive Oxygen Radicals, and Danger Signals in the human SK-MES1 Lung Cancer Cell Line - Roessel, T.; Becker, I.; Alomo, Jannik; Denzler, M.; Heim, L.; Klemt, Insa; Voloshin, Y.; Selin, R.; Mokhir, Andriy; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

The influence of radiation on bone and bone cells—differential effects on osteoclasts and osteoblasts - Donaubauer, Anna-Jasmina; Becker, Ina; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (International Journal of Molecular Sciences, 2020)
The bone is a complex organ that is dependent on a tight regulation between bone formation by osteoblasts (OBs) and bone resorption by osteoclasts (OCs). These processes can be influenced by environmental factors such as ionizing radiation (IR). In cancer therapy, IR is applied in high doses, leading to detrimental effects on bone, whereas radiation therapy with low doses of IR is applied for chronic degenerative and inflammatory diseases, with a positive impact especially on bone homeostasis. Moreover, the effects of IR are of particular interest in space travel, as astronauts suffer from bone loss due to space radiation and microgravity. This review summarizes the current state of knowledge on the effects of IR on bone with a special focus on the influence on OCs and OBs, as these cells are essential in bone remodeling. In addition, the influence of IR on the bone microenvironment is discussed. In summary, the effects of IR on bone and bone remodeling cells strongly depend on the applied radiation dose, as differential results are provided from in vivo as well as in vitro studies with varying doses of IR. Furthermore, the isolated effects of IR on a single cell type are difficult to determine, as the bone cells and bone microenvironment are building a tightly regulated network, influencing on one another. Therefore, future research is necessary in order to elucidate the influence of different bone cells on the overall radiation-induced effects on bone.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Bone; Bone microenvironment; Ionizing radiation; Osteoblast; Osteoclast; Osteocyte; Radiation therapy

The in vitro immunogenic potential of caspase-3 proficient breast cancer cells with basal low immunogenicity is increased by hypofractionated irradiation - Kötter, Bernhard; Frey, Benjamin; Winderl, Markus; Rubner, Yvonne; Scheithauer, Heike; Sieber, Renate; Fietkau, Rainer; Gaipl, Udo (Radiation Oncology, 2015)
Radiotherapy is an integral part of breast cancer treatment. Immune activating properties of especially hypofractionated irradiation are in the spotlight of clinicians, besides the well-known effects of radiotherapy on cell cycle and the reduction of the clonogenic potential of tumor cells. Especially combination of radiotherapy with further immune stimulation induces immune-mediated anti-tumor responses. We therefore examined whether hypofractionated irradiation alone or in combination with hyperthermia as immune stimulants is capable of inducing breast cancer cells with immunogenic potential.Clonogenic assay, AnnexinA5-FITC/Propidium iodide assay and ELISA analyses of heat shock protein 70 and high mobility group box 1 protein were applied to characterize colony forming capability, cell death induction, cell death forms and release of danger signals by breast cancer cells in response to hypofractionated radiation (4x4Gy, 6x3Gy) alone and in combination with hyperthermia (41.5 °C for 1 h). Caspase-3 deficient, hormone receptor positive, p53 wild type MCF-7 and caspase-3 intact, hormone receptor negative, p53 mutated MDA-MB231 breast cancer cells, the latter in absence or presence of the pan-caspase inhibitor zVAD-fmk, were used. Supernatants of the treated tumor cells were analyzed for their potential to alter the surface expression of activation markers on human-monocyte-derived dendritic cells.Irradiation reduced the clonogenicity of caspase deficient MCF-7 cells more than of MDA-B231 cells. In contrast, higher amounts of apoptotic and necrotic cells were induced in MDA-B231 cells after single irradiation with 4Gy, 10Gy, or 20Gy or after hypofractionated irradiation with 4x4Gy or 6x3Gy. MDA-B231 cells consecutively released higher amounts of Hsp70 and HMGB1 after hypofractionated irradiation. However, only the release of Hsp70 was further increased by hyperthermia. Both, apoptosis induction and release of the danger signals, was dependent on caspase-3. Only supernatants of MDA-B231 cells after hypofractionated irradiation resulted in slight changes of activation markers on dendritic cells; especially that of CD86 was upregulated and HT did not further impact on it.Hypofractionated irradiation is the main stimulus for cell death induction and consecutive dendritic cell activation in caspase proficient breast cancer cells. For the assessment of radiosensitivity and immunological effects of radio- and immunotherapies the readout system is crucial.
EVALuna2:18306

The long-term influence of hospital and surgeon volume on local control and survival in the randomized German Rectal Cancer Trial CAO/ARO/AIO-94 - Sprenger, Thilo; Beissbarth, Tim; Sauer, Rolf; Tschmelitsch, Joerg; Fietkau, Rainer; Hohenberger, Werner; Staib, Ludger; Raab, Hans-Rudolf; Roedel, Claus; Ghadimi, Michael (Surgical Oncology-Oxford, 2020)
Background: The association of treatment volume and oncological outcome of rectal cancer patients undergoing multidisciplinary treatment is subject of an ongoing debate. Prospective data on long-term local control and overall survival (OS) are not available so far. This study investigated the long-term influence of hospital and surgeon volume on local recurrence (LR) and OS in patients with locally advanced rectal cancers.
CRIS-Team WoS Importer:2021-01-08

The OAR Turing-Test Study: A blinded Comparison of expert-Based Organ at Risk Creation and three commercial Auto-Segmentation Solutions - Putz, Florian; Lamrani, Allison; Weissmann, Thomas; Mansoorian, Sina; Frey, Benjamin; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

The Prognostic and Predictive Significance of Tumor-Infiltrating Memory T Cells Is Reversed in High-Risk HNSCC - Hartan, Rebekka; Schnellhardt, Sören; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cells, 2022)
Tumor-infiltrating CD45RO+ memory T cells have unanimously been described as a positive prognostic factor in head and neck squamous cell carcinomas (HNSCCs). Here, we investigated the long-term prognostic relevance of CD45RO+ memory T cells in HNSCC with special regard to the influence of clinical characteristics. Pre-treatment biopsy samples from 306 patients with predominantly advanced HNSCC were analyzed. Immunohistochemistry was used to stain tissue microarrays for CD45RO+ memory T cells. CD45RO cell densities were semi-automatically registered and used for survival analysis. High CD45RO+ cell densities were clearly associated with prolonged overall survival (OS) and recurrence-free survival as well as no evidence of disease status after 10 years (p < 0.05). In contrast, the prognostic significance of tumor-infiltrating memory T cells was completely reversed in high-risk groups: in poorly differentiated tumors (G3, G4) and in cases with lymph node involvement (N+), high memory T cell densities correlated with reduced 10-year OS (p < 0.05). In conclusion, an increased density of tumor-infiltrating CD45RO+ cells in HNSCC can be a positive as well as a negative prognostic factor, depending on disease stage and histological grade. Therefore, if CD45RO+ cell density is to be used as a prognostic biomarker, further clinical characteristics must be considered.
CRIS-Team WoS Importer:2022-07-08
Keywords: CD45RO; head and neck cancer; memory T cells; prognostic value; reversal of prognostic value

The prognostic Significance of Tumor-associated Macrophages (TAM) and of Tumor-infiltrating Lymphocytes (TIL) in radiolabelled Patients with an Adenocarcinoma of the Pancreas - Zoske, Hanno; Distel, Luitpold; Fietkau, Rainer; Hecht, Markus (2017)
EVALuna2:32899

The Prognostic Value of FoxP3+Tumour-Infiltrating Lymphocytes in Rectal Cancer Depends on Immune Phenotypes Defined by CD8+Cytotoxic T Cell Density - Schnellhardt, Sören; Hirneth, Johannes; Büttner-Herold, Maike; Daniel, Christoph; Haderlein, Marlen; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Frontiers in Immunology, 2022)
Tumour-infiltrating FoxP3+ regulatory T cells have been identified as both positive and negative prognostic factors in colorectal cancer (CRC) and rectal cancer (RC). In this study we investigated whether immune phenotypes, defined by CD8+ cytotoxic T cell density, may influence the prognostic association of FoxP3+ T cell densities in RC. Tissue microarrays from 154 rectal cancer resections were immunohistochemically double stained for CD8 and FoxP3. CD8+ and FoxP3+ cell densities were measured in the stromal and intraepithelial compartment. Stromal FoxP3+ cell densities were not associated with 10-year overall survival (OS). In the "immune-desert" phenotype, defined by very low stromal CD8+ cell density, a high density of stromal FoxP3+ T cells displayed a tendency towards an association with decreased 10-year OS (p = 0.179). In "inflamed" tumours, defined by high intraepithelial CD8+ T cell infiltration, the opposite was the case and high stromal FoxP3+ T cell densities were a positive prognostic factor (p = 0.048). Additionally, patients with an increased FoxP3/CD8 cell density ratio demonstrated a strong trend towards decreased 10-year OS (p = 0.066). These contrasting findings suggest functional heterogeneity within the group of FoxP3+ T cells. They are consistent with experimental studies which reported suppressive and non-suppressive populations of FoxP3+ T cells in CRC. Furthermore, our study demonstrates that CD8 immunohistochemistry may act as an instrument to identify tumours infiltrated by possibly functionally differing FoxP3+ T cell subtypes.
CRIS-Team WoS Importer:2022-02-18

The Randomized AMBORA Trial: Impact of Pharmacological/Pharmaceutical Care on Medication Safety and Patient-Reported Outcomes During Treatment With New Oral Anticancer Agents - Dürr, Pauline; Schlichtig, Katja; Kelz, Carolin; Deutsch, Birgit; Maas, Renke; Eckart, Michael J.; Wilke, Jochen; Wagner, Harald; Wolff, Kerstin; Preuß, Caroline; Brückl, Valeska; Meidenbauer, Norbert; et al. (Journal of Clinical Oncology, 2021)
PURPOSE: Oral anticancer drugs (eg, kinase inhibitors) play an important role in cancer therapy. However, considerable challenges regarding medication safety of oral anticancer drugs have been reported. Randomized, controlled, multicenter studies on the impact of intensified clinical pharmacological/pharmaceutical care on patient safety and patient treatment perception are lacking. METHODS: Patients were eligible for the randomized, multicenter AMBORA study, if they were newly started on any of the oral anticancer drugs approved in 2001 or later without restriction to certain tumor entities. Patients were randomly assigned to receive either standard of care (control group) or an additional, intensified clinical pharmacological/pharmaceutical care, which included medication management and structured patient counseling, over a period of 12 weeks (intervention group). Primary end points were the number of antitumor drug-related problems (ie, side effects and unresolved medication errors) and patient treatment satisfaction with the oral anticancer therapy after 12 weeks measured with the Treatment Satisfaction Questionnaire for Medication, category convenience. RESULTS: Two hundred two patients were included. Antitumor drug-related problems were significantly lower in the intervention compared with the control group (3.85 v 5.81 [mean], P < .001). Patient treatment satisfaction was higher in the intervention group (Treatment Satisfaction Questionnaire for Medication, convenience; 91.6 v 74.4 [mean], P < .001). The hazard ratio for the combined end point of severe side effects (Common Terminology Criteria for Adverse Events ≥ 3), treatment discontinuation, unscheduled hospital admission, and death was 0.48 (95% CI, 0.32 to 0.71, P < .001) in favor of the intervention group. CONCLUSION: Treatment with oral anticancer drugs is associated with a broad range of medication errors and side effects. An intensified clinical pharmacological/pharmaceutical care has considerable, positive effects on the number of medication errors, patient treatment perception, and severe side effects.
CRIS-Team Scopus Importer:2021-07-02

Therapies for synchronous malignomas - the importance of interdisciplinary oncology - Müller, Sarina Katrin; Haderlein, Marlen; Traxdorf, Maximilian; Semrau, Sabine; Agaimy, Abbas; Lettmaier, Sebastian; Gostian, Antoniu-Oreste; Schubart, Christoph; Mantsopoulos, Konstantinos; Schmidt, Daniela; Wiesmüller, Marco; Sievert, Matti; et al. (Laryngo-Rhino-Otologie, 2021)
CRIS-Team WoS Importer:2021-08-06

The Role of local radical Therapy Approach in the metastatic Stage of Small Cell Lung Cancer (SCLC) - Zoske, Hanno; Lettmaier, S.; Fietkau, Rainer; Putz, Florian (2018)
EVALuna2:36511

The Treatment Reality of Octogenarians with Bladder Cancer in a Maximum Care Hospital - Sikic, D.; Wach, S.; Taubert, Helge; Richterstetter, M.; Kunath, F.; Lieb, V.; Krause, S.; Merten, Ricarda; Ott, O.; Fietkau, Rainer; Wullich, Bernd; Keck, Bastian (2016)
EVALuna2:18333

The use of bolus in postmastectomy radiation therapy for breast cancer: A systematic review - Dahn, Hannah M.; Boersma, Liesbeth J.; de Ruysscher, Dirk; Meattini, Icro; Offersen, Birgitte V.; Pignol, Jean Philippe; Aristei, Cynthia; Belkacemi, Yazid; Benjamin, Dori; Bese, Nuran; Coles, Charlotte E.; Franco, Pierfrancesco; et al. (Critical Reviews in Oncology Hematology, 2021)
Purpose: Post mastectomy radiation therapy (PMRT) reduces locoregional recurrence (LRR) and breast cancer mortality for selected patients. Bolus overcomes the skin-sparing effect of external-beam radiotherapy, ensuring adequate dose to superficial regions at risk of local recurrence (LR). This systematic review summarizes the current evidence regarding the impact of bolus on LR and acute toxicity in the setting of PMRT. Results: 27 studies were included. The use of bolus led to higher rates of acute grade 3 radiation dermatitis (pooled rates of 9.6% with bolus vs. 1.2% without). Pooled crude LR rates from thirteen studies (n = 3756) were similar with (3.5%) and without (3.6%) bolus. Conclusions: Bolus may be indicated in cases with a high risk of LR in the skin, but seems not to be necessary for all patients. Further work is needed to define the role of bolus in PMRT.
CRIS-Team Scopus Importer:2021-06-25
Keywords: bolus; breast cancer; mastectomy; PMRT; post-mastectomy; radiation therapy; tissue compensator

THE USE OF TTFIELDS FOR NEWLY DIAGNOSED GBM PATIENTS IN GERMANY IN ROUTINE CLINICAL CARE (TIGER: TTFIELDS IN GERMANY IN ROUTINE CLINICAL CARE) - Baehr, O.; Tabatabai, G.; Fietkau, Rainer; Goldbrunner, R.; Glas, M. (NEURO-ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-20

The use of TTFields for newly diagnosed GBM patients in Germany in routine clinical care (TIGER: TTFields in Germany in routine clinical care) - Baehr, O.; Tabatabai, G.; Fietkau, Rainer; Goldbrunner, R.; Glas, M. (2019)
EVALuna2:213635

The various functions and phenotypes of macrophages are also reflected in their responses to irradiation: A current overview - Deloch, Lisa; Rückert, Michael; Weissmann, Thomas; Lettmaier, Sebastian; Titova, Eva; Wolff, Teresa; Weinrich, Felix; Fietkau, Rainer; Gaipl, Udo (International Review of Cell and Molecular Biology, 2023)
Macrophages are a vital part of the innate immune system that are involved in healthy biological processes but also in disease modulation and response to therapy. Ionizing radiation is commonly used in the treatment of cancer and, in a lower dose range, as additive therapy for inflammatory diseases. In general, lower doses of ionizing radiation are known to induce rather anti-inflammatory responses, while higher doses are utilized in cancer treatment where they result, next to tumor control, in rather inflammatory responses. Most experiments that have been carried out in ex vivo on macrophages find this to be true, however in vivo, tumor-associated macrophages, for example, show a contradictory response to the respective dose-range. While some knowledge in radiation-induced modulations of macrophages has been collected, many of the underlying mechanisms remain unclear. Due to their pivotal role in the human body, however, they are a great target in therapy and could potentially aid in better treatment outcome. We therefore summarized the current knowledge of macrophage mediated radiation responses.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Immune cells; Immunology; Low-dose radiotherapy; Macrophage polarization; Macrophages; Radiotherapy; Rheumatoid arthritis; Tumor associated macrophages

Time course of pain response and toxicity after whole-nerve-encompassing LINAC-based stereotactic radiosurgery for trigeminal neuralgia—a prospective observational study - Koca, Selim; Distel, Luitpold; Lubgan, Dorota; Weissmann, Thomas; Lambrecht, Ulrike; Lang-Welzenbach, Marga; Eyüpoglu, Ilker Yasin; Bischoff, Barbara; Buchfelder, Michael; Semrau, Sabine; Fietkau, Rainer; Lettmaier, Sebastian; et al. (Strahlentherapie und Onkologie, 2019)
Purpose: To prospectively evaluate the time course of pain response and toxicity after linear accelerator-based whole-nerve-encompassing radiosurgery (LINAC-SRS) using a uniform treatment schedule for dosing and target volume definition in patients with refractory trigeminal neuralgia. Methods: From December 2012 to December 2016, 21 patients were treated using a standardized protocol. Patients received LINAC-SRS with 70 Gy to the cisternal portion while aiming for the 90% isodose to fully envelope the nerve in one cross-sectional plane. Data on pain, analgesics, and toxicity were gathered prospectively. Four time intervals (1–6, 6–12, 12–18, and 18–24 months) were defined and compared to baseline and each other. Results: The median follow-up from radiotherapy was 16 months. Freedom from pain was achieved at least once in 90.5, 81.0, and 85.7% of patients for everyday pain, rest pain, and pain peaks, respectively. At 1–6 months, pain was significantly reduced in everyday routine (mean VAS, 2.0/10 vs. 5.8/10; P = 0.004), at rest (1.5/10 vs. 4.0/10; P = 0.002), and for pain peaks (2.9/10 vs. 10/10; P < 0.001), as was the number of analgesics (mean 1.5 vs. 2.9; P < 0.001). No significant increase in pain or analgesics was observed for subsequent time intervals. At last follow-up, reduction in pain compared to baseline for everyday routine (2.1/10 vs. 5.8/10; P = 0.010) and for pain peaks (3.3/10 vs. 10/10; P < 0.001) was significant, whereas it was not for rest pain (1.8/10 vs. 3.9/10; P = 0.073). Most toxicities were related to trigeminal nerve impairment, with 42.9% reporting new-onset hypoesthesia at last follow-up. Conclusion: This study provides prospective data after whole nerve encompassing LINAC-SRS for trigeminal neuralgia. No significant pain relapse was observed.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Facial pain; Radiosurgery; SRS; Toxicity; Trigeminal neuralgia

Time-dependent risk factors for epileptic seizures in glioblastoma patients: A retrospective analysis of 520 cases - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Brandner, Sebastian; Welte, Tamara; Balk, Stefanie; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; Adler, Werner; Schwab, Stefan; Putz, Florian; et al. (Epilepsia, 2023)
Objective: Epilepsy is a common comorbidity of glioblastoma. Seizures may occur in various phases of the disease. We aimed to assess potential risk factors for seizures in accordance with the point in time at which they occurred. Methods: We retrospectively analyzed medical files of adult patients with de novo glioblastoma treated at our institution between January 2006 and January 2020. We categorized seizures as preoperative seizures (POS), early postoperative seizures (EPS; before initiation of radio[chemo]therapy [RCT]), seizures during radiotherapy (SDR; during or <30 days after RCT), and posttherapeutic seizures (PTS; ≥30 days after completion of RCT). We addressed associations between patients' characteristics and their seizures. Results: In the final cohort (N = 520), 292 patients experienced seizures. POS, EPS, SDR, and/or PTS occurred in 29.6% (154/520), 6.0% (31/520), 13.8% (70/509), and 36.1% (152/421) of patients, respectively. POS occurred more frequently in patients with higher Karnofsky Performance Scale scores (odds ratio [OR] = 3.27, p =.001) and tumor location in the temporal lobe (OR = 1.51, p =.034). None of the parameters we analyzed was related to the occurrence of EPS. SDR were independently associated with tumor location (parietal lobe, OR = 1.86, p =.027) and POS, but not EPS, and were independent of RCT. PTS were independently associated with tumor progression (OR = 2.32, p <.001) and with occurrence of SDR (OR = 3.36, p <.001), and negatively correlated with temporal lobe location (OR =.58, p <.014). In patients with tumors exclusively located in the temporal lobe, complete tumor resection was associated with a decreased risk of postoperative seizures. Significance: Seizures in glioblastoma patients have various, time-dependent risk factors. Temporal lobe localization was a risk factor for preoperative seizures; surgery may have had a protective effect in these patients. RCT did not have dose-dependent pro- or anticonvulsive effects. PTS were associated with tumor progression.
CRIS-Team Scopus Importer:2023-07-07
Keywords: glioblastoma; radiochemotherapy; seizures; surgery

TNT in rectal cancer: Final results of the CAO/ARO/AIO-12 randomized phase 2 trial - Fokas, E.; Schlenska-Lange, A.; Polat, B.; Klautke, G.; Fietkau, Rainer; Kuhnt, T.; Brunner, T.; Grosu, A.; Kirste, S.; Flentje, M.; Germer, C.; Bechstein, W.; et al. (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-11-26

Total Neoadjuvant Therapy as Organ Preserving Therapy for Rectal Cancer: The CAO/ARO/AIO-16 Phase II Study - Gani, C.; Polat, B.; Ott, Oliver; Germer, E.; Koenigsrainer, A.; Kirschniak, A.; Clasen, S.; Grosse, U.; Diefenhardt, M.; Reibetanz, J.; Bitzer, M.; Martus, P.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Toward a deep learning-based magnetic resonance imaging only workflow for postimplant dosimetry in I-125 seed brachytherapy for prostate cancer - Grigo, Johanna; Karius, Andre; Hanspach, Jannis; Mücke, Lion; Laun, Frederik B.; Huang, Yixing; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Brachytherapy, 2024)
Background and purpose: The current standard imaging-technique for creating postplans in seed prostate brachytherapy is computed tomography (CT), that is associated with additional radiation exposure and poor soft tissue contrast. To establish a magnetic resonance imaging (MRI) only workflow combining improved tissue contrast and high seed detectability, a deep learning-approach for automatic seed segmentation on MRI-scans was developed. Material and methods: Patients treated with I-125 seed brachytherapy received a postplan-CT and a 1.5 T MRI-scan on nominal day 30 after implantation. For MRI-based seed visualization, DIXON-sequences were acquired and deep learning-based quantitative susceptibility maps (QSM) were generated from 3D-gradient-echo-sequences from 20 patients. Seed segmentations created on CT served as ground truth. For automatic seed segmentation on MRI, a 3D nnU-net model was trained using QSM and DIXON, both solely and combined. Results: Of the implanted seeds 94.8 ± 2.4% were detected with deep learning automatic segmentation entrained on both QSM and DIXON data. Models trained on the individual sequence data-sets performed worse with detection rates of 87.5 ± 2.6% or 88.6 ± 7.5% for QSM and DIXON respectively. The seed centers identified on CT versus QSM and DIXON were on average 1.8 ± 1.3 mm apart. Postimplant dosimetry for evaluation of positioning inaccuracies revealed only small variations of up to 0.4 ± 4.26 Gy in D90 (dose 90% of the prostate receives) between the standard CT-approach and our MRI-only workflow. Conclusion: The proposed deep learning-based MRI-only workflow provided a promisingly accurate and robust seed localization and thus has the potential to compete with current state-of-the-art CT-based postimplant dosimetry in the future.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Magnetic resonance imaging; Magnetic resonance only workflow; Permanent brachytherapy; Postimplant dosimetry; Radiotherapy; Seed brachytherapy

Towards a Computable Data Corpus of Temporal Correlations between Drug Administration and Lab Value Changes - Newe, Axel; Wimmer, Stefan; Neubert, Antje; Becker, Linda; Prokosch, Hans-Ulrich; Beckmann, Matthias; Fietkau, Rainer; Forster, Christian; Neurath, Markus; Schett, Georg; Ganslandt, Thomas (PLoS ONE, 2015)
Background The analysis of electronic health records for an automated detection of adverse drug reactions is an approach to solve the problems that arise from traditional methods like spontaneous reporting or manual chart review. Algorithms addressing this task should be modeled on the criteria for a standardized case causality assessment defined by the World Health Organization. One of these criteria is the temporal relationship between drug intake and the occurrence of a reaction or a laboratory test abnormality. Appropriate data that would allow for developing or validating related algorithms is not publicly available, though. Methods In order to provide such data, retrospective routine data of drug administrations and temporally corresponding laboratory observations from a university clinic were extracted, transformed and evaluated by experts in terms of a reasonable time relationship between drug administration and lab value alteration. Result The result is a data corpus of 400 episodes of normalized laboratory parameter values in temporal context with drug administrations. Each episode has been manually classified whether it contains data that might indicate a temporal correlation between the drug administration and the change of the lab value course, whether such a change is not observable or whether a decision between those two options is not possible due to the data. In addition, each episode has been assigned a concordance value which indicates how difficult it is to assess. This is the first open data corpus of a computable ground truth of temporal correlations between drug administration and lab value alterations. Discussion The main purpose of this data corpus is the provision of data for further research and the provision of a ground truth which allows for comparing the outcome of other assessments of this data with the outcome of assessments made by human experts. It can serve as a contribution towards systematic, computerized ADR detection in retrospective data. With this lab value curve data as a basis, algorithms for detecting temporal relationships can be developed, and with the classification made by human experts, these algorithms can immediately be validated. Due to the normalization of the lab value data, it allows for a generic approach rather than for specific or solitary drug/lab value combination

Transient Enlargement in Meningiomas Treated with Stereotactic Radiotherapy - Maksoud, Ziad; Schmidt, Manuel; Huang, Yixing; Rutzner, Sandra; Mansoorian, Sina; Weissmann, Thomas; Bert, Christoph; Distel, Luitpold; Semrau, Sabine; Lettmaier, Sebastian; Eyüpoglu, Ilker Yasin; Fietkau, Rainer; et al. (Cancers, 2022)
To investigate the occurrence of pseudoprogression/transient enlargement in meningiomas after stereotactic radiotherapy (RT) and to evaluate recently proposed volumetric RANO meningioma criteria for response assessment in the context of RT. Sixty-nine meningiomas (benign: 90%, atypical: 10%) received stereotactic RT from January 2005–May 2018. A total of 468 MRI studies were segmented longitudinally during a median follow-up of 42.3 months. Best response and local control were evaluated according to recently proposed volumetric RANO criteria. Transient enlargement was defined as volumetric increase ≥20% followed by a subsequent regression ≥20%. The mean best volumetric response was −23% change from baseline (range, −86% to +19%). According to RANO, the best volumetric response was SD in 81% (56/69), MR in 13% (9/69) and PR in 6% (4/69). Transient enlargement occurred in only 6% (4/69) post RT but would have represented 60% (3/5) of cases with progressive disease if not accounted for. Transient enlargement was characterized by a mean maximum volumetric increase of +181% (range, +24% to +389 %) with all cases occurring in the first year post-RT (range, 4.1–10.3 months). Transient enlargement was significantly more frequent with SRS or hypofractionation than with conventional fractionation (25% vs. 2%, p = 0.015). Five-year volumetric control was 97.8% if transient enlargement was recognized but 92.9% if not accounted for. Transient enlargement/pseudoprogression in the first year following SRS and hypofractionated RT represents an important differential diagnosis, especially because of the high volumetric control achieved with stereotactic RT. Meningioma enlargement during subsequent post-RT follow-up and after conventional fractionation should raise suspicion for tumor progression. <
Keywords: meningioma; volumetric analysis; segmentation; transient enlargement; pseudoprogression; stereotactic radiotherapy; radiosurgery; response assessment

Treatment Characteristics and Real-World Progression-Free Survival in Patients With Unresectable Stage III NSCLC Who Received Durvalumab After Chemoradiotherapy: Findings From the PACIFIC-R Study - Girard, Nicolas; Bar, Jair; Garrido, Pilar; Garassino, Marina C.; McDonald, Fiona; Mornex, Françoise; Filippi, Andrea R.; Smit, Hans J.M.; Peters, Solange; Field, John K.; Christoph, Daniel C.; Sibille, Anne; et al. (Journal of Thoracic Oncology, 2022)
Introduction: The phase 3 PACIFIC trial established consolidation therapy with durvalumab as standard of care for patients with unresectable, stage III NSCLC and no disease progression after definitive chemoradiotherapy (CRT). The observational PACIFIC-R study assesses the real-world effectiveness of durvalumab in patients from an early access program. Here, we report treatment characteristics and a preplanned analysis of real-world progression-free survival (rwPFS). Methods: PACIFIC-R (NCT03798535) is an ongoing, international, retrospective study of patients who started durvalumab (intravenously; 10 mg/kg every 2 wk) within an early access program between September 2017 and December 2018. The primary end points are investigator-assessed rwPFS and overall survival (analyzed by Kaplan–Meier method). Results: As of November 30, 2020, the full analysis set comprised 1399 patients from 11 countries (median follow-up duration, 23.5 mo). Patients received durvalumab for a median of 11.0 months. Median rwPFS was 21.7 months (95% confidence interval: 19.1–24.5). RwPFS was numerically longer among patients who received concurrent versus sequential CRT (median, 23.7 versus 19.3 mo) and among patients with programmed cell death-ligand 1 expression greater than or equal to 1% versus less than 1% (22.4 versus 15.6 mo). Overall, 16.5% of the patients had adverse events leading to treatment discontinuation; 9.5% of all patients discontinued because of pneumonitis or interstitial lung disease. Conclusions: Consolidation durvalumab after definitive CRT was well tolerated and effective in this large, real-world cohort study of patients with unresectable, stage III NSCLC. As expected, rwPFS was longer among patients who received concurrent versus sequential CRT and patients with higher programmed cell death-ligand 1 expression. Nevertheless, favorable rwPFS outcomes were observed regardless of these factors.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Consolidation therapy; Immunotherapy; Locally advanced NSCLC; PD-L1 inhibition; Real-world data

Treatment of arrhythmias by external charged particle beams: a Langendorff feasibility study - Prall, Matthias; Lehmann, H. Immo; Prokesch, Hannah; Richter, Daniel; Graeff, Christian; Kaderka, Robert; Sonnenberg, Karin; Hauswald, Henrik; Weymann, Alexander; Bauer, Julia; Constantinescu, Anna; Haberer, Thomas; et al. (Biomedizinische Technik, 2015)
Hadron therapy has already proven to be successful in cancer therapy, and might be a noninvasive alternative for the ablation of cardiac arrhythmias in humans. We present a pilot experiment investigating acute effects of a 12C irradiation on the AV nodes of porcine hearts in a Langendorff setup. This setup was adapted to the requirements of charged particle therapy. Treatment plans were computed on calibrated CTs of the hearts. Irradiation was applied in units of 5 and 10 Gy over a period of about 3 h until a total dose of up to 160 Gy was reached. Repeated application of the same irradiation field helped to mitigate motion artifacts in the resulting dose distribution. After irradiation, PET scans were performed to verify accurate dose application. Acute AV blocks were identified. No other acute effects were observed. Hearts were kept in sinus rhythm for up to 6 h in the Langendorff setup. We demonstrated that 12C ions can be used to select a small target in the heart and, thereby, influence the electrical conduction system. Second, our pilot study seems to suggest that no adverse effects have to be expected immediately during heavy ion irradiation in performing subsequent experiments with doses of 30-60 Gy and intact pigs.
EVALuna2:18316

Treatment of cervical paragangliomas: is surgery the only way? - Künzel, Julian; Koch, Michael; Brase, Christoph; Fietkau, Rainer; Iro, Heinrich; Zenk, Johannes (American Journal of Otolaryngology, 2014)
To analyze the results after surgery or stereotactic radiotherapy (SRT) in the treatment of cervical paragangliomas. Against this background, the decision-making algorithm used in the treatment of carotid body tumors (CBTs) and vagal paragangliomas (VPs) was reevaluated relative to the existing literature on the topic.Retrospective study between 2000 and 2012. A total of 27 CBTs and nine VPs in 32 patients were treated. Shamblin class I: 59.3% (n=16); class II: 29.6% (n=8); class III: 11.1% (n=3). Treatment modalities were surgery, radiotherapy, or observation. The end points for analysis were long-term tumor control and integrity of the cranial nerves.21 CBTs and seven VPs underwent surgery; SRT was performed in three CBTs and two VPs. Three CBTs were clinically observed. Permanent nerve paresis followed after surgery for CBTs in five patients (20%) and in all patients with VPs. No impaired cranial nerve function resulted after SRT. The median follow-up period was 4.7 years. The tumor control rate after therapy for CBTs and VPs was 100%. One CBT that received clinical observation showed slow tumor progression.A surgical procedure should be regarded as the treatment of choice in patients with small CBTs. In larger CBTs, particularly in elderly patients with unimpaired cranial nerves, radical surgery should be regarded critically. As surgery for VPs caused regularly impairment of cranial nerves with functional disturbances of various degrees a comprehensive consultation with the patient is mandatory and nonsurgical strategies should be discussed.
EVALuna2:18181

Treatment Parameters Optimization to Compensate for Interfractional Anatomy Variability and Intrafractional Tumor Motion - Brevet, Romain; Richter, Daniel; Graeff, Christian; Durante, Marco; Bert, Christoph (Frontiers in Oncology, 2015)
Scanned ion beam therapy of lung tumors is severely limited in its clinical applicability by intrafractional organ motion, interference effects between beam and tumor motion (interplay), as well as interfractional anatomic changes. To compensate for dose deterioration caused by intrafractional motion, motion mitigation techniques, such as gating, have been developed. However, optimization of the treatment parameters is needed to further improve target dose coverage and normal tissue sparing. The aim of this study was to determine treatment-planning parameters that permit to recover good target coverage for each fraction of lung tumor treatments. For 9 lung tumor patients from MD Anderson Cancer Center (Houston, Texas), a total of 70 weekly time-resolved computed tomography (4DCT) datasets, which depict the evolution of the patient anatomy over the several fractions of the treatment, were available. Using the GSI in-house treatment planning system TRiP4D, 4D simulations were performed on each weekly 4DCT for each patient using gating and optimization of a single treatment plan based on a planning CT acquired prior to treatment. The impact on target dose coverage (V 95%,CTV) of variations in focus size and length of the gating window, as well as different additional margins and the number of fields was analyzed. It appeared that interfractional variability could potentially have a larger impact on V 95%,CTV than intrafractional motion. However, among the investigated parameters, the use of a large beam spot size, a short gating window, additional margins, and multiple fields permitted to obtain an average V 95%,CTV of 96.5%. In the presented study, it was shown that optimized treatment parameters have an important impact on target dose coverage in the treatment of moving tumors. Indeed, intrafractional motion occurring during the treatment of lung tumors and interfractional variability were best mitigated using a large focus, a short gating window, additional margins, and three fields.
EVALuna2:18368

Treatment Planning Studies in Patient Data With Scanned Carbon Ion Beams for Catheter-Free Ablation of Atrial Fibrillation - Constantinescu, Anna; Lehmann, H. Immo; Packer, Douglas L.; Bert, Christoph; Durante, Marco; Graeff, Christian (Journal of Cardiovascular Electrophysiology, 2016)
Catheter ablation with isolation of the pulmonary veins is a common treatment option for atrial fibrillation but still has insufficient success rates and carries several interventional risks. These treatment planning studies assessed if high-dose single fraction treatment with scanned carbon ions (12C) can be reliably delivered for AF ablation, while sparing risk structures and considering respiratory and contractile target motion.Time resolved CT scans of complete respiratory and cardiac cycles of 9 and 5 patients, respectively, were obtained. Ablation lesions and organs at risk for beam delivery were contoured. Single fraction intensity-modulated particle therapy with target doses of 25 and 40 Gy were studied and motion influences on these deliveries mitigated. Respiration had a large influence on lesion displacement (<= 2 cm). End expiration could be exploited as a stable gating window. Smaller, but less predictable, heartbeat displacements (< 6 mm) remained to be mitigated because cardiac contraction resulted in insufficient dose coverage (V95 < 90%) if uncompensated. Repeated irradiation (12C beam rescanning) during breath hold was used to accommodate contractile motion, resulting in good dose coverage. Dose depositions to all organs at risk were carefully examined and did not exceed values for X-ray cancer treatment.Treatment planning of 12C with delivery of physical ionizing radiation doses that have been described to induce complete block is feasible for AF ablation, considering human anatomy, dose constraints, and encasing underlying motion patterns from respiration and cardiac contraction at the LA-PV junction into treatment planning.
EVALuna2:18342

Treatment Response and Prophylactic Cranial Irradiation Are Important Prognostic Factors in LD SCLC Patients Staged with cMRI - Eze, Chukwuka; Roengvoraphoj, Olarn; Niyazi, Maximilian; Hildebrandt, Guido; Fietkau, Rainer; Belka, Claus; Manapov, Farkhad (2017)
EVALuna2:32914

Treatment Response and Prophylactic Cranial Irradiation Are Prognostic Factors in a Real-life Limited-disease Small-cell Lung Cancer Patient Cohort Comprehensively Staged With Cranial Magnetic Resonance Imaging - Eze, Chukwuka; Roengvoraphoj, Olarn; Niyazi, Maximilian; Hildebrandt, Guido; Fietkau, Rainer; Belka, Claus; Manapov, Farkhad (Clinical Lung Cancer, 2017)
INTRODUCTION: Prophylactic cranial irradiation (PCI) has proven to decrease the incidence of brain metastases (BMs), with a modest improvement in survival. PATIENTS AND METHODS: The impact of PCI was evaluated in 184 patients treated with chemoradiotherapy. PCI was applied to patients with disease with partial and complete response only when cranial magnetic resonance imaging before and after primary treatment revealed no BMs. Correlation between PCI and overall survival (OS), BM-free survival (BMFS), and time to progression (TTP) was analyzed to describe survival within subgroups. RESULTS: Concurrent and sequential chemoradiotherapy was applied in 71 patients (39%) and 113 patients (61%), respectively. Seventy-one patients (39%) with partial and complete response were treated with PCI. Metachronous BMs were detected in 16 (23%) of 71 patients in the PCI group compared to 42 (37%) of 113 patients in the non-PCI group. Median BMFS in the PCI group was not reached; it was 23.6 months in the non-PCI group. Median OS and TTP were 26 months (range, 19.4-32.6 months) in the PCI group versus 14 months (range, 11.4-16.6 months) in patients without PCI whose disease responded to therapy versus 9 months in patients with disease that did not respond to therapy (P < .0001), and 27 versus 14.5 months (range, 9.0-19.9 months) versus 8.8 months (range, 7.7-9.9 months) (P < .0001) in the PCI group versus those with response without PCI versus those with nonresponse. The effect of PCI was independent of gender. On multivariate analysis, PCI was a variable correlating with OS (hazard ratio = 1.899; 95% confidence interval, 1.370-2.632; P < .0001) and TTP (hazard ratio = 2.164; 95% confidence interval, 1.371-3.415; P = .001) after adjustment for other prognostic factors. CONCLUSION: In real-life patients comprehensively staged with cranial magnetic resonance imaging, treatment response and PCI strongly correlated with prolonged OS, TTP, and BMFS.
EVALuna2:36447

Treatment response lowers tumor symptom burden in recurrent and/or metastatic head and neck cancer - Hecht, Markus; Hahn, Dennis; Wolber, Philipp; Hautmann, Matthias G.; Reichert, Dietmar; Weniger, Steffi; Belka, Claus; Bergmann, Tobias; Göhler, Thomas; Welslau, Manfred; Große-Thie, Christina; Guntinas-Lichius, Orlando; et al. (BMC Cancer, 2020)
Background: Head and neck squamous cell cancer (HNSCC) frequently causes severe symptoms that may be reduced, when the tumor is successfully treated. The SOCCER trial studied the association of treatment response with patient reported tumor symptom burden in first line treatment of recurrent and/or metastatic HNSCC. Methods: In this prospective, multi-center, non-interventional trial patients were treated either with platinum-based chemotherapy and cetuximab or radiotherapy and cetuximab. Tumor symptom burden was assessed every four weeks with a questionnaire containing ten visual analogue scales (VAS, range 0-100), which were summarized to the overall VAS score. Results: Fourhundred seventy patients were registered in 97 German centers. A total of 315 patients with at least the baseline and one subsequent questionnaire were available for analysis. Changes in the VAS score were rated as absolute differences from baseline. Negative values indicate improvement of symptoms. The overall VAS score improved significantly at the first post-baseline assessment in responders (-2.13 vs. non-responders + 1.15, p = 0.048), and even more for the best post-baseline assessment (-7.82 vs. non-responders-1.97, p = 0.0005). The VAS for pain (-16.37 vs. non-responders-8.89, p = 0.001) and swallowing of solid food (-16.67 vs. non-responders-5.06, p = 0.002) improved significantly more in responders (best post-baseline assessment). In the multivariable Cox regression analysis, worse overall VAS scores were associated with worse overall survival (hazard ratio for death 1.12 per 10 points increment on the overall VAS scale, 95% CI 1.05-1.20, p = 0.0009). Conclusion: In unselected patients beyond randomized controlled trials, treatment response lowers tumor symptom burden in recurrent and/or metastatic HNSCC.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Cetuximab; Chemotherapy; HNSCC; Response; Symptom

Treatment strategy by radioiodine refractory differentiated thyroid cancer - Mantsopoulos, Konstantinos; Müller, Sarina Katrin; Pavel, Marianne Ellen; Kuwert, Torsten; Meidenbauer, Norbert; Fietkau, Rainer; Sievert, Matti; Iro, Heinrich (Laryngo-Rhino-Otologie, 2021)
Zusammenfassung Traditionell besteht das multimodale Therapiekonzept bei den differenzierten Schilddrusenkarzinomen in der Thyreoidektomie mit Neck-Dissection (bei cN+-Halsstatus) und adjuvanten Radiojodablation mit abschlie ss ender risikoadaptierter TSH-Suppression. Das Ausma ss der Radiojodaufnahme beim metastasierten Schilddrusenkarzinom spielt eine signifikante Rolle bei der Einschatzung der Prognose. Das fehlende Jodspeicherungsvermogen einer Lasion in Zusammenschau mit dem fehlenden Abfall des Tumormarkers Thyreoglobulin sowie radiologische Zeichen einer Tumorprogression charakterisieren den Radiojod-refraktaren Patienten. Aufgrund des meistens uber einen langen Zeitraum indolenten Verlaufs erscheint in den meisten Fallen ein abwartendes Verhalten in Kombination mit lokaler Metastasenbehandlung sowie Symptomlinderung primar sinnvoll zu sein. Der Nachweis einer Veranderung der Tumordynamik ist der Zeitpunkt, um eine Systemtherapie zu evaluieren. Diese beruht auf Multi-Tyrosinkinase-Inhibitoren (Sorafenib, Lenvatinib). Diese Substanzen sind gro ss tenteils mit einem ungunstigen Nebenwirkungsprofil assoziiert (Diarrho, Hautauschlage, arterielle Hypertonie mit hypertensiver Entgleisung, lokale Wundheilungsstorungen), welches zu einer nicht vernachlassigbaren Rate einer therapieassoziierten Morbiditat sowie einer hohen Anzahl an Therapieunterbrechungen fuhrt. Daher sind im Jahr 2020 2 selektive RET-Inhibitoren (Selpercatinib, Pralsetinib) fur die differenzierten Schilddrusenkarzinome von der FDA zugelassen worden. Eine neue Perspektive fur die Zukunft waren die unterschiedlichen Redifferenzierungsstrategien, welche auf die Steigerung der Sensitivitat der Tumorzellen auf Radiojod abzielen.
CRIS-Team WoS Importer:2021-10-08

Treatment with (chemo)-radiation in old patients (≥76 years of age) with newly diagnosed non-metastatic squamous cell cancer of the head and neck region: real-world data from a tertiary referral center - Winkler, Leah-Sophie; Haderlein, Marlen; Semrau, Sabine; Putz, Florian; Höfler, Daniel; Müller, Sarina Katrin; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer; Schubert, Philipp (Frontiers in Oncology, 2024)
Purpose: Treatment of patients with cancer of the head and neck region is in focus in a multitude of studies. Of these patients, one patient group, those aged 76 and more, is mostly underrepresented despite requiring thorough and well-reasoned treatment decisions to offer curative treatment. This study investigates real-world data on curative treatment of old (≥76 years) patients with newly diagnosed squamous cell carcinoma of the head and neck region (HNSCC). Patients and methods: Between January 2010 and December 2021, we identified 71 patients older than 76 years with newly diagnosed HNSCC and cM0 at the Department of Radiation Oncology of the University Hospital of Erlangen-Nuremberg. Using electronic medical records, we analyzed treatment patterns and outcomes in terms of overall survival (OS), progression-free survival (PFS), and locoregional control (LRC) rate. Additionally, we performed univariate risk analysis and Cox regression in order to identify predictive factors associated with the abovementioned treatment outcomes. Results: The median follow-up was 18 months. OS was 83%, 79%, and 72% after 1 year, 2 years, and 3 years, respectively. PFS was 69%, 54%, and 46% after 1 year, 2 years, and 3 years, respectively. A total of 34 (48%) patients were treated with standard therapy according to current guidelines. The reasons for deviation from standard therapy before or during treatment were as follows: unfitness for cisplatin-based chemotherapy (n = 37), reduction of chemotherapy (n = 3), and dose reduction/interruption of radiotherapy (n = 8). Carboplatin-based systemic therapy showed improved PFS compared to cisplatin or cetuximab (60 vs. 28 vs. 15 months, p = 0.037) but without impact on OS (83 vs. 52 vs. 38 months, p = 0.807). Oropharyngeal tumor localization (p = 0.026) and combined treatment (surgery and postoperative treatment) (p = 0.008) were significant predictors for a better OS. In multivariate analysis, oropharyngeal tumor localization (p = 0.011) and combined treatment (p = 0.041) showed significantly increased PFS. After 1 year, 2 years, and 3 years, the cumulative incidence of locoregional recurrences (LRRs) was 13%, 24%, and 27%, respectively, and was significantly decreased in patients with oropharyngeal tumor localization (p = 0.037). Conclusions: Adherence to treatment protocols for radiotherapy alone in old patients with HNSCC is good, whereas the application of concurrent chemotherapy often deviates from guidelines in terms of de-escalation. An important risk factor for decreased OS, PFS, and a higher rate of LRR appears to be non-oropharyngeal tumor location in old patients.
CRIS-Team Scopus Importer:2024-05-24
Keywords: chemoradiation; head and neck cancer; old patients; squamous cell carcinoma; tumor localization

Trends in radiotherapy inpatient admissions in Germany: a population-based study over a 10-year period - Medenwald, Daniel; Fietkau, Rainer; Klautke, Gunther; Langer, Susan; Wuerschmidt, Florian; Vordermark, Dirk (Strahlentherapie und Onkologie, 2021)
Objective With the increasing complexity of oncological therapy, the number of inpatient admissions to radiotherapy and non-radiotherapy departments might have changed. In this study, we aim to quantify the number of inpatient cases and the number of radiotherapy fractions delivered under inpatient conditions in radiotherapy and non-radiotherapy departments. Methods The analysis is founded on data of all hospitalized cases in Germany based on Diagnosis-Related Group Statistics (G-DRG Statistics, delivered by the Research Data Centers of the Federal Statistical Office). The dataset includes information on the main diagnosis of cases (rather than patients) and the performed procedures during hospitalization based on claims of reimbursement. We used linear regression models to analyze temporal trends. The considered data encompass the period from 2008 to 2017. Results Overall, the number of patients treated with radiotherapy as inpatients remained constant between 2008 (N = 90,952) and 2017 (N = 88,998). Starting in January 2008, 48.9% of 4000 monthly cases received their treatment solely in a radiation oncology department. This figure decreased to 43.7% of 2971 monthly cases in October 2017. We found a stepwise decrease between December 2011 and January 2012 amounting to 4.3%. Fractions received in radiotherapy departments decreased slightly by 29.3 (95% CI: 14.0–44.5) fractions per month. The number of days hospitalized in radiotherapy departments decreased by 83.4 (95% CI: 59.7, 107.0) days per month, starting from a total of 64,842 days in January 2008 to 41,254 days in 2017. Days per case decreased from 16.2 in January 2008 to 13.9 days in October 2017. Conclusion Our data give evidence to the notion that radiotherapy remains a discipline with an important inpatient component. Respecting reimbursement measures and despite older patients with more comorbidities, radiotherapy institutions could sustain a constant number of cases with limited temporal shifts.
CRIS-Team WoS Importer:2021-09-10
Keywords: Inpatient cases; Radiotherapy departments; DRG data; Germany; Non-radiotherapy departments

TTFIELDS IN ROUTINE CLINICAL CARE OF NEWLY DIAGNOSED GBM PATIENTS IN GERMANY - FIRST REPORT ON THE FULLY ENROLLED TIGER STUDY POPULATION - Baehr, Oliver; Tabatabai, Ghazaleh; Fietkau, Rainer; Goldbrunner, Roland; Glas, Martin (NEURO-ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-12-04

Tumor Cell-Based Vaccine Generated With High Hydrostatic Pressure Synergizes With Radiotherapy by Generating a Favorable Anti-tumor Immune Microenvironment - Seitz, Christoph; Ruckert, Michael; Weiss, Eva-Maria; Utz, Sebastian; Izydor, Marika; Ebel, Nina; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Deloch, Lisa (Frontiers in Oncology, 2019)
Dendritic cell (DC)-based vaccines pulsed with high hydrostatic pressure (HHP)-inactivated tumor cells have been demonstrated to be a promising immunotherapy for solid tumors. We focused on sole injection of tumor cells that were inactivated by HHP and their combination with local radiotherapy (RTx) for in vivo induction of anti-tumor immune responses. HHP-treatment of tumor cells resulted in pre-dominantly necrotic cells with degraded DNA. We confirmed that treatments at 200 MPa or higher completely inhibited the formation of tumor cell colonies in vitro. No tumor growth was seen in vivo after injection of HHP-treated tumor cells. Single vaccination with HHP-killed tumor cells combined with local RTx significantly retarded tumor growth and improved the survival as shown in B16-F10 and CT26 tumor models. In B16-F10 tumors that were irradiated with 2 x 5Gy and vaccinated once with HHP-killed tumor cells, the amount of natural killer (NK) cells, monocytes/macrophages, CD4+ T cells and NKT cells was significantly increased, while the amount of B cells was significantly decreased. In both models, a trend of increased CD8+ T cell infiltration was observed. Generally, in irradiated tumors high amounts of CD4+ and CD8+ T cells expressing PD-1 were found. We conclude that HHP generates inactivated tumor cells that can be used as a tumor vaccine. Moreover, we show for the first time that tumor cell-based vaccine acts synergistically with RTx to significantly retard tumor growth by generating a favorable anti-tumor immune microenvironment.
CRIS-Team WoS Importer:2019-09-10

Tumor infiltrating cells - cell-to-cell distances enable differentiation between functionally active and suppressed inflammatory cells - Distel, Luitpold; Nagl, Sandra; Fietkau, Rainer; Haas, M. (2016)
EVALuna2:18330

Tumor Infiltrating Inflammatory Cells as a prognostic Factor in Glioblastoma - Schnellhardt, Sören; Zorob, Alexander; Polat, B.; Lisowski, D.; Daniel, Christoph; Monoranu, C-M; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Tumor-infiltrating Memory T Cells in Head and Neck Tumors: An ambivalent prognostic Factor - Hartan, R.; Schnellhardt, Sören; Büttner-Herold, Maike; Daniel, Christoph; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Tumor Regression Grading After Preoperative Chemoradiotherapy as a Prognostic Factor and Individual-Level Surrogate for Disease-Free Survival in Rectal Cancer - Fokas, Emmanouil; Stroebel, Philipp; Fietkau, Rainer; Ghadimi, Michael; Liersch, Torsten; Grabenbauer, Gerhard G.; Hartmann, Arndt; Kaufmann, Marco; Sauer, Rolf; Graeven, Ullrich; Hoffmanns, Hans; Raab, Hans-Rudolf; et al. (Journal of the National Cancer Institute, 2017)
Background: We investigated tumor regression grading (TRG) as a prognostic marker and individual-level surrogate for disease-free survival (DFS) in patients with rectal carcinoma treated within the Chirurgische Arbeitsgemeinschaft fur Onkologie/Arbeitsgemeinschaft Radiologische Onkologie/Arbeitsgemeinschaft Internistische Onkologie (CAO/ARO/AIO)-04 randomized trial. Methods: TRG was recorded prospectively using the Dworak classification in 1179 patients after preoperative fluorouracil-based chemoradiotherapy (CRT) with or without oxaliplatin. Multivariable analysis was performed using Cox regression models adjusted for treatment arm, resection status, and pathologic stage. Individual-level surrogacy of TRG for DFS was examined using the four Prentice criteria (PC1-4). All statistical tests were two-sided. Results: With a median follow-up of 50 months, the addition of oxaliplatin to fluorouracil-based CRT led to statistically significantly improved three-year DFS (75.9%, 95% CI = 72.3 to 79.5, vs 71.3%, 95% CI = 67.6 to 74.9, P = .04, PC 1) and a shift toward more advanced TRG groups ( P < .001, PC 2) compared with CRT with fluorouracil alone. The three-year DFS was 64.6% (95% CI = 57.3 to 71.9), 77.6% (95% CI = 74.5 to 80.7), and 92.3% (95% CI = 88.4 to 96.2) for TRG 0 + 1 (poor regression), TRG 2 + 3 (intermediate regression), and TRG 4 (complete regression), respectively ( P < .001, PC 3). TRG constituted an independent prognostic factor for DFS (TRG 2 + 3 vs TRG 0 + 1, HR = 0.68, 95% CI = 0.51 to 0.90, P = .007). Due to multicollinearity, TRG 4 and pathologic stage could not be tested within the same model. The treatment effect on DFS was captured by TRG, satisfying individual-level PC4. Conclusions: Higher TRG after preoperative CRT predicted a favorable long-term outcome. At the individual patient level, TRG was a surrogate marker for DFS. Further phase III trials are needed to validate TRG as a surrogate at trial level.
EVALuna2:32865

Tumor regression grading after preoperative chemoradiotherapy as prognostic factor and individual-level surrogate for disease-free survival in rectal cancer: Results of the CAO/ARO/AIO-04 multicentre, open-label, randomised, phase 3 trial - Fokas, E.; Stroebel, P.; Fietkau, Rainer; Ghadimi, M.; Liersch, T.; Grabenbauer, G.; Hartmann, Arndt; Kaufmann, M.; Sauer, Rolf; Graeven, U.; Hoffmanns, H.; Raab, H-R; et al. (2017)
EVALuna2:32881

Tumor regression grading after preoperative chemoradiotherapy for locally advanced rectal carcinoma revisited: updated results of the CAO/ARO/AIO-94 trial - Fokas, Emmanouil; Liersch, Torsten; Fietkau, Rainer; Hohenberger, Werner; Beissbarth, Tim; Hess, Clemens; Becker, Heinz; Ghadimi, Michael; Mrak, Karl; Merkel, Susanne; Raab, Hans-Rudolf; Sauer, Rolf; et al. (Journal of Clinical Oncology, 2014)
We previously described the prognostic impact of tumor regression grading (TRG) on the outcome of patients with rectal carcinoma treated with preoperative chemoradiotherapy (CRT) in the CAO/ARO/AIO-94 trial. Here we report long-term results after a median follow-up of 132 months.TRG after preoperative CRT was determined in 386 surgical specimens by the amount of viable tumor cells versus fibrosis, ranging from TRG 4 (no viable tumor cells) to TRG 0 (no signs of regression). Clinicopathologic parameters and TRG were correlated to the cumulative incidence of local recurrence, distant metastasis, and disease-free survival (DFS).Ten-year cumulative incidence of distant metastasis and DFS were 10.5% and 89.5% for patients with TRG 4 (complete regression), 29.3% and 73.6% for TRG 2 and 3 (intermediate regression), and 39.6% and 63% for TRG 0 and 1 (poor regression), respectively (P = .005 and P = .008, respectively). On multivariable analysis, residual lymph node metastasis (ypN+) and TRG were the only independent prognostic factors for cumulative incidence of distant metastasis (P < .001 and P = .035, respectively) and DFS (P < .001 and P = .039, respectively), whereas local recurrence was significantly affected by ypN status (P < .001) and lymphatic invasion (P = .026).Complete and intermediate tumor regressions were associated with improved long-term outcome in patients with rectal carcinoma after preoperative CRT independent of clinicopathologic parameters. This classification system needs to be prospectively tested in multiple data sets to validate its reproducibility in a wider setting.
EVALuna2:15168

Tumor-specific radiosensitizing effect of the ATM inhibitor AZD0156 in melanoma cells with low toxicity to healthy fibroblasts - Scheper, Julian; Hildebrand, Laura; Faulhaber, Eva-Maria; Deloch, Lisa; Gaipl, Udo; Symank, Julia-Alice; Fietkau, Rainer; Distel, Luitpold; Hecht, Markus; Jost, Tina (Strahlentherapie und Onkologie, 2022)
Purpose Despite new treatment options, melanoma continues to have an unfavorable prognosis. DNA damage response (DDR) inhibitors are a promising drug class, especially in combination with chemotherapy (CT) or radiotherapy (RT). Manipulating DNA damage repair during RT is an opportunity to exploit the genomic instability of cancer cells and may lead to radiosensitizing effects in tumors that could improve cancer therapy. Methods A panel of melanoma-derived cell lines of different origin were used to investigate toxicity-related clonogenic survival, cell death, and cell cycle distribution after treatment with a kinase inhibitor (KI) against ATM (AZD0156) or ATR (VE-822, berzosertib), irradiation with 2 Gy, or a combination of KI plus ionizing radiation (IR). Two fibroblast cell lines generated from healthy skin tissue were used as controls. Results Clonogenic survival indicated a clear radiosensitizing effect of the ATM inhibitor (ATMi) AZD0156 in all melanoma cells in a synergistic manner, but not in healthy tissue fibroblasts. In contrast, the ATR inhibitor (ATRi) VE-822 led to additive enhancement of IR-related toxicity in most of the melanoma cells. Both inhibitors mainly increased cell death induction in combination with IR. In healthy fibroblasts, VE-822 plus IR led to higher cell death rates compared to AZD0156. A significant G2/M block was particularly induced in cancer cells when combining AZD0156 with IR. Conclusion ATMi, in contrast to ATRi, resulted in synergistic radiosensitization regarding colony formation in melanoma cancer cells, while healthy tissue fibroblasts were merely affected with respect to cell death induction. In connection with an increased number of melanoma cells in the G2/M phase after ATMi plus IR treatment, ATMi seems to be superior to ATRi in melanoma cancer cell treatments when combined with RT.
CRIS-Team WoS Importer:2022-10-28

Tumor-specific Toxicity to malignant Melanoma Cells by the dual DNA-PK and mTOR Inhibitor CC115 in Combination with ionizing Radiation - Burkel, F.; Jost, Tina; Proebstle, Stephanie; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36482

Tumour-infiltrating inflammatory cells in early breast cancer: An underrated prognostic and predictive factor? - Schnellhardt, Sören; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie Charlotte; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, Lillian; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2020)
The role of tumour-infiltrating inflammatory cells (TIICs) in the disease progression of hormone-receptor-positive breast cancer (HR+ BC) is largely unclear since it is generally regarded as the least immunogenic BC subtype. This study investigated the prognostic significance of CD1a+ dendritic cells, CD20+ B cells, CD45RO+ memory T cells and CD4+ T-helper cells in HR+ BC. One hundred and forty-six patients were treated for early stage, distant-metastases-free HR+ BC in an accelerated partial breast irradiation (APBI) phase II trial. Immunohistochemistry was used to double-stain two adjoining sets of tissue microarrays from pre-RT (radiotherapy) tumour resection samples for CD1a/CD20 and CD45RO/CD4. Cell densities of CD1a+, CD20+, CD45RO+ and CD4+ TIICs in the stromal and intraepithelial compartment were registered semiautomatically. High densities of CD20+ and CD4+ TIICs were strongly associated with reduced disease-free survival (DFS), while high stromal CD45RO+ TIIC densities were indicators of subsequent successful treatment. An immunoscore based on CD20+ and CD45RO+ TIIC densities identified three different risk groups (p < 0.001). Thus, contrary to current assumptions, intratumoural immune cell composition might be an important prognostic indicator and a possible contributing factor in the outcome of HR+ BC and should be the subject of further research. Specifically, B-cell infiltration entailed an increased relapse rate and could play an important role in disease progression.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Accelerated partial breast irradiation; Breast cancer; CD1a; CD20; CD4; CD45RO; Hormone receptor positive; Immunoscore; Prognosis; TIL

Two-ways validation of the feasibility of AI-based synthetic CT for MR-only brain radiotherapy - Masitho, Siti; Szkitsak, Juliane; Grigo, Johanna; Putz, Florian; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-07-22

Unified risk analysis in radiation therapy - Lohmann, Daniel; Shariff, Maya; Schubert, Philipp; Sauer, Tim-Oliver; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Purpose: The increasing complexity of new treatment methods as well as the Information Technology (IT) infrastructure within radiotherapy require new methods for risk analysis. This work presents a methodology on how to model the treatment process of radiotherapy in different levels. This subdivision makes it possible to perform workflow-specific risk analysis and to assess the impact of IT risks on the overall treatment workflow. Methods: A Unified Modeling Language (UML) activity diagram is used to model the workflows. The subdivision of the workflows into different levels is done with the help of swim lanes. The model created in this way is exported in an xml-compatible format and stored in a database with the help of a Python program. Results: Based on an existing risk analysis, the workflows CT Appointment, Glioblastoma Multiforme, and Deep Inspiration Breath Hold (DIBH) were modeled in detail. Part of the analysis are automatically generated workflow-specific risk matrices including risks of medical devices incorporated into a specific workflow. In addition, SQL queries allow to quickly retrieve e.g., the details of the medical device network installed in a department. Conclusion: Activity diagrams of UML can be used to model workflows in radiotherapy. Through this, a connection between the different levels of the entire workflow can be established and workflow-specific risk analysis is possible.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Activity diagram; IEC 80001-1; Risk analysis; UML

Union of light ion therapy centers in Europe (ULICE EC FP7) - Objectives and achievements of joint research activities - Poetter, Richard; Balosso, Jaques; Baumann, Michael; Bert, Christoph; Davies, Jim; Enghardt, Wolfgang; Fossati, Piero; Harris, Steve; Jones, Bleddyn; Kraemer, Michael; Mayer, Ramona; Mock, Ulrike; et al. (Radiotherapy and Oncology, 2018)
Under the umbrella of the European Network for Light Ion Therapy (ENLIGHT), the project on Union of Light Ion Centers in Europe (ULICE), which was funded by the European Commission (EC/FP7), was carried out from 2009 to 2014. Besides the two pillars on Transnational Access (TNA) and Networking Activities (NA), six work packages formed the pillar on Joint Research Activities (JRA). The current manuscript focuses on the objectives and results achieved within these research work packages: "Clinical Research Infrastructure", "Biologically Based Expert System for Individualized Patient Allocation", "Ion Therapy for Intra-Fractional Moving Targets", "Adaptive Treatment Planning for Ion Radiotherapy", "Carbon Ion Gantry", "Common Database and Grid Infrastructures for Improving Access to Research Infrastructures". The objectives and main achievements are summarized. References to either publications or open access deliverables from the five year project work are given. Overall, carbon ion radiotherapy is still not as mature as photon or proton radiotherapy. Achieved results and open questions are reflected and discussed in the context of the current status of carbon ion therapy and particle and photon beam therapy. Most research topics covered in the ULICE JRA pillar are topical. Future research activities can build upon these ULICE results. Together with the continuous increase in the number of particle therapy centers in the last years ULICE results and proposals may contribute to the further growth of the overall particle therapy field as foreseen with ENLIGHT and new joint initiatives such as the European Particle Therapy Network (EPTN) within the overall radiotherapy community.
EVALuna2:36474

Updated analysis of the phase II CheckRad-CD8 trial: First-line treatment of locally advanced head and neck squamous cell carcinoma with induction chemoimmunotherapy followed by radioimmunotherapy - Hecht, Markus; Eckstein, Markus; Kallies, Annett; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias; Brunner, Thomas; Tamaskovics, Bálint; Hinke, Axel; Zhou, Jianguo; et al. (35. Deutscher Krebskongress, Krebsmedizin: Schnittstellen zwischen Innovation und Versorgung, 2022)
CRIS-Team WoS Importer:2022-12-16

Update of the ESTRO-EFOMP core curriculum for medical physics experts in radiotherapy - Garibaldi, C.; Essers, M.; Heijmen, B.; Bertholet, J.; Koutsouveli, E.; Schwarz, M.; Bert, Christoph; Jornet, N.; Clark, C. H. (RADIOTHERAPY AND ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-11-26

Usability of magnetic resonance images acquired at a novel low-field 0.55 T scanner for brain radiotherapy treatment planning - Grigo, Johanna; Masitho, Siti; Fautz, Hans Peter; Voigt, Raphaela; Schonath, Miriam; Oleszczuk, Annika; Uder, Michael; Heiß, Rafael; Fietkau, Rainer; Putz, Florian; Bert, Christoph (Physics and Imaging in Radiation Oncology, 2023)
Background and Purpose: Low-field magnetic resonance imaging (MRI) may offer specific advantages over high-field MRI, e.g. lower susceptibility-dependent distortions and simpler installation. The study aim was to evaluate if a novel 0.55 T MRI scanner provides sufficient image accuracy and quality for radiotherapy (RT) treatment planning. Material and methods: The geometric accuracy of images acquired at a low-field MRI scanner was evaluated in phantom measurements regarding gradient non-linearity-related distortions. Patient-induced B0-susceptibility changes were investigated via B0-field-mapping in ten volunteers. Patients were positioned in RT-setup using a 3D-printed insert for the head/neck-coil that was tested for sufficient signal-to-noise-ratio (SNR). The suitability of the MRI-system for detection of metastases was evaluated in eleven patients. In comparison to diagnostic images, acquired at ≥1.5 T, three physicians evaluated the detectability of metastases by counting them in low- and high-field-images, respectively. Results: The phantom measurements showed a high imaging fidelity after 3D-distortion-correction with (1.2 ± 0.9) mm geometric distortion in 10 cm radius from isocentre. At the edges remaining distortions were greater than at 1.5 T. The mean susceptibility-induced distortions in the head were (0.05 ± 0.05) mm and maximum 0.69 mm. SNR analysis showed that optimised positioning of RT-patients without signal loss in the head/neck-coil was possible with the RT-insert. No significant differences (p = 0.48) in detectability of metastases were found. Conclusion: The 0.55 T MRI system provided sufficiently geometrically accurate and high-resolution images that can be used for RT-planning for brain metastases. Hence, modern low-field MRI may contribute to simply access MRI for RT-planning after further investigations.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Low-Field-MRI; MRI; Radiotherapy

Use of NGS Gene Panel Analyzes for molecularly targeted System Therapy - Roesch, Johannes; Haller, Florian; Lettmaier, Sebastian; Haderlein, Marlen; Hartmann, Arndt; Moskalev, Evgeny; Tögel, Lars; Putz, Florian; Weissmann, T.; Schubert, P.; Höfler, Daniel; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Variability in catheter reconstruction for multi-catheter interstitial brachytherapy - Kallis, Karoline; Kaltsas, Theodoros; Kreppner, Stephan; Lotter, M.; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Verbesserung der Deep Learning basierten Autodetektion von Hirnmetastasen durch Integration von MRT-Voraufnahmen - Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2022)
Keywords: Deep learning; brain metastasis

Volume Course of Acoustic Neuromas after stereotactic Radiotherapy - Putz, Florian; Lettmaier, S.; Knippen, S.; Gryc, Thomas; Fietkau, Rainer (2017)
EVALuna2:32889

Volumetric assessment of paragangliomas of the head and neck following stereotactic radiotherapy - Putz, Florian; Weissmann, T.; Lettmaier, S.; Semrau, S.; Fietkau, Rainer (2018)
EVALuna2:36506

Volumetric Regression in Brain Metastases After Stereotactic Radiotherapy: Time Course, Predictors, and Significance - Oft, Dominik; Schmidt, Manuel; Weissmann, Thomas; Roesch, Johannes; Mengling, Veit; Masitho, Siti; Bert, Christoph; Lettmaier, Sebastian; Frey, Benjamin; Distel, Luitpold; Fietkau, Rainer; Putz, Florian (Frontiers in Oncology, 2021)
Background: There is insufficient understanding of the natural course of volumetric regression in brain metastases after stereotactic radiotherapy (SRT) and optimal volumetric criteria for the assessment of response and progression in radiotherapy clinical trials for brain metastases are currently unknown. Methods: Volumetric analysis via whole-tumor segmentation in contrast-enhanced 1 mm³-isotropic T1-Mprage sequences before SRT and during follow-up. A total of 3,145 MRI studies of 419 brain metastases from 189 patients were segmented. Progression was defined using a volumetric extension of the RANO-BM criteria. A subset of 205 metastases without progression/radionecrosis during their entire follow-up of at least 3 months was used to study the natural course of volumetric regression after SRT. Predictors for volumetric regression were investigated. A second subset of 179 metastases was used to investigate the prognostic significance of volumetric response at 3 months (defined as ≥20% and ≥65% volume reduction, respectively) for subsequent local control. Results: Median relative metastasis volume post-SRT was 66.9% at 6 weeks, 38.6% at 3 months, 17.7% at 6 months, 2.7% at 12 months and 0.0% at 24 months. Radioresistant histology and FSRT vs. SRS were associated with reduced tumor regression for all time points. In multivariate linear regression, radiosensitive histology (p=0.006) was the only significant predictor for metastasis regression at 3 months. Volumetric regression ≥20% at 3 months post-SRT was the only significant prognostic factor for subsequent control in multivariate analysis (HR 0.63, p=0.023), whereas regression ≥65% was no significant predictor. Conclusions: Volumetric regression post-SRT does not occur at a constant rate but is most pronounced in the first 6 weeks to 3 months. Despite decreasing over time, volumetric regression continues beyond 6 months post-radiotherapy and may lead to complete resolution of controlled lesions by 24 months. Radioresistant histology is associated with slower regression. We found that a cutoff of ≥20% regression for the volumetric definition of response at 3 months post-SRT was predictive for subsequent control whereas the currently proposed definition of ≥65% was not. These results have implications for standardized volumetric criteria in future radiotherapy trials for brain metastases.
CRIS-Team Scopus Importer:2021-02-05
Keywords: brain metastases; longitudinal analysis; MRI; stereotactic radiosurgery; stereotactic radiotherapy; volumetric analysis; volumetric regression

Volumetric regression in brain metastases after stereotactic RT: Time course and significance - Putz, Florian; Oft, Dominik; Perrin, R.; Mengling, Veit; Weissmann, Thomas; Roesch, Johannes; Mansoorian, Sina; Distel, Luitpold; Bert, Christoph; Fietkau, Rainer (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Vulnerabilitäten bei Radiomics: Warum die populärste Radiomics-Signatur unbemerkt das Tumorvolumen gemessen hat - Putz, Florian; Fietkau, Rainer (Strahlentherapie und Onkologie, 2021)
CRIS-Team WoS Importer:2021-02-26

„Watchful Waiting“ als Alternative zur Rektumexstirpation nach kompletter Tumorremission infolge neoadjuvant intendierter Radiochemotherapie? - Hohenberger, Werner; Sauer, Rolf (Strahlentherapie und Onkologie, 2016)
EVALuna2:15230

Website on the individual Radiation Sensitivity of Tumor Patients - Rzepka, Dinah; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

When is a nonsurgical approach possible for metastatic primary tumors and lymph node metastases of the urinary bladder and prostate? - Fietkau, Rainer (Urologe, 2017)
For metastatic carcinomas of the urinary bladder and prostate, systemic therapy is of primary importance. Due to technological advances in radiation oncology such as stereotactic radiotherapy, intensity-modulated radiotherapy, interstitial radiotherapy, and the combination of radiotherapy and chemotherapy, pelvic irradiation can nowadays be carried out effectively and without the risk of major side effects. New data from other tumor entities and retrospective analyses suggest that the use of these technologies can lead to a clinical benefit in terms of improvement in quality of life, local control, and overall survival. For the time being, the decision to administer radiotherapy to the pelvic region should be made on an individual basis. Retrospective analyses of data from prostate carcinomas in particular are currently being planned. This review article introduces potential indications which are supported with real patient examples and discusses future developments giving an overview of the literature and referring to data from prospective randomized trials.
EVALuna2:32905

Which fractionation of radiotherapy is best for limited-stage small-cell lung cancer? - Fietkau, Rainer (Lancet Oncology, 2017)
EVALuna2:32872

Whole-Body Electromyostimulation combined with personalized Nutritional Support improves the Body Composition of Patients with advanced Cancer - Schink, Kristin; Herrmann, Hans Joachim; Schwappacher, Raphaela; Orlemann, Till; Meyer, Julia; Waldmann, Elisabeth; Wullich, Bernd; Kahlmeyer, Andreas; Fietkau, Rainer; Lubgan, Dorota; Beckmann, Matthias; Hack, Carolin; et al. (2018)
EVALuna2:35187

Wirkung von Flap Endonuclease 1 Inhibitor FEN1-IN-4 in Kombination mit ionisierender Strahlung auf Mammakarzinomzellen - Berfelde, Johanna; Hildebrand, Laura; Jost, Tina; Distel, Luitpold; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)

Work-related bladder cancer -The BK 1301 matrix as an algorithm and decision aid in the context of an assessment of an occupational disease Das beruflich bedingte Harnblasenkarzinom-Die BK 1301-Matrix als Algorithmus und Entscheidungshilfe fur eine Zusammenhangsbegutachtung - Weistenhöfer, Wobbeke; Golka, K.; Bolm-Audorff, U.; Bolt, H. M.; Bruning, T.; Hallier, E.; Pallapies, D.; Prager, H. M.; Schilling, Teresa; Schmitz-Spanke, Simone; Uter, Wolfgang; Weis, T.; et al. (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2022)
The risk of developing bladder cancer can be influenced by various occupational and non-occupational risk factors. These need to be evaluated in the context of an assessment of an occupational disease according to no. 1301 (BK 1301: Mucosal changes, cancer and other neoplasms of the urinary tract (hereinafter referred to as "bladder cancer") caused by aromatic amines) of the Annex to the Ordinance on Occupational Diseases. The BK 1301 matrix presented here for the assessment of the causal relationship in urinary bladder cancers after proven and relevant occupational exposure to carcinogenic aromatic amines was derived as a convention by a working group, based on the results of a workshop with more than 230 participants. It can be applied even in the absence of an individual cumulative exposure dose. The decision matrix is intended to support experts experienced in occupational medicine in the field of BK 1301 in the assessment procedure. It also provides an overview of relevant aspects of work-related bladder cancer for the purposes of accident insurance institutions and courts. The BK 1301 matrix includes occupational indicators such as exposure duration, exposure frequency and exposure intensity, as well as the age of onset, the latency period and competing non-occupational risk factors such as smoking behaviour. Based on the BK 1301 matrix, the relevant arguments favouring or refuting a causal occupational relationship in the individual case can be evaluated in detail by the occupational physician, resulting in a recommendation for or against recognition of the bladder cancer as an occupational disease. This notwithstanding, the decision as to whether an occupational disease is indeed present is ultimately an administrative act of the responsible accident insurance institution, which may be subject to review by the social courts.
CRIS-Team Scopus Importer:2022-05-06
Keywords: aromatic amines; bladder cancer; convention; expert opinion; matrix; occupational disease 1301

ypN0 nodal status after neoadjuvant chemoradiotherapy for rectal carcinoma is not associated with adverse prognosis as compared with pN0 after primary surgery - Erlenbach-Wuensch, Katharina; Semrau, Sabine; Fietkau, Rainer; Weber, Klaus; Hohenberger, Werner; Rau, Tilman; Hartmann, Arndt; Merkel, Susanne; Agaimy, Abbas (International Journal of Colorectal Disease, 2014)
Neoadjuvant chemoradiotherapy (nCRT) has been established as standard treatment for locally advanced rectal cancer (cT3/4 or cN+ cM0, distance from circumferential resection margin <=1 mm) to enhance local disease control and minimize the rate of locoregional recurrence. As a consequence of downstaging, a significant proportion of patients show non-viable tumor deposits within regional lymph nodes that qualify as ypN0 according to the current TNM classification irrespective of the actual pre-treatment status. Accordingly, the prognostic relevance of ypN0 status as compared with true pN0 without preceding nCRT is not known.We retrospectively analyzed 132 patients who underwent standard total mesorectal excision (TME) surgery after nCRT for rectal carcinoma and were classified as ypN0, and compared their prognoses with those of 341 patients with pN0 without nCRT.Re-evaluation of regional lymph nodes after nCRT showed no evidence of previous metastasis in 91 cases (ypN0(-)), sure but non-viable metastasis in 14 patients (ypN0(+)), and unsure status in 27 patients (ypN0(X)). The local recurrence rate, distant metastases, and disease-free, observed, and cancer-related survival were similar in all subgroups (p = 0.447, 0.695, 0.759, 0.655, and 0.354, respectively).Our results showed a similar outcome in patients with ypN0 and in the control group with pN0 regarding local recurrence rate, distant metastases, and disease-free, observed, and cancer-related survival. Validation of these results is necessary to clarify the questions regarding postoperative adjuvant chemotherapy for patients with ypN0(+).
EVALuna2:6516